A Fight for Justice: The Compelling Story of Temporary Foreign Workers & Human Rights - Barrett, Joe (Ronsdale Press, 2026)
How migrant workers, with the support of Canadian unions, won justice in a landmark court decision. In April 2006, 42 Latin Americans landed in Vancouver to excavate tunnels for the Canada Line Skytrain. They thought they'd won the lottery with promised wages far above what they would earn at home. But the reality was miserable wages, unpaid overtime and inadequate living conditions. It was the beginning of the Canadian construction industry's reliance on migrant workers and the treatment of temporary foreign workers has made headlines ever since. Author Joe Barrett, fluent in Spanish and a researcher for BC Building Trades unions, first spoke to three of the Costa Rican workers through a chain link around the worksite. They confirmed the low wages. He shares his unique insider perspective as he joined the team of union organizers and became a liaison between workers, union officials and lawyers throughout the court battles. The workers' resentment grew in the face of employer lies, intimidation, coercion and prejudice. Most of them came from a group of villages in central Costa Rica. They grew up together, sharing a background of poverty and hardship. These common bonds gave them the courage they needed to face fears of employer retaliation as they organized, which resulted in a successful vote for union certification, a first for temporary foreign workers in the Canadian construction industry. But their victory was short-lived and their unity was broken by a series of employer "sticks and sweeteners." The fight for fairness continued at the BC Labour Relations Board (BCLRB) and, ultimately, at the BC Human Rights Tribunal in a race against time before the workers left Canada with the completion of the tunnels. In 2008, the tribunal delivered a triumphant decision, a landmark case in the evolving issue of global migration. Workers were awarded $2.4 million to compensate for discrimination based on country of origin; for wages, inferior accommodations, meals and expenses and injury to dignity and feelings. A Fight for Justice is an inspiring story of collective action and relationships across progressive communities in Canada and Latin America and offers a remarkable story of migrant workers successfully fighting for fairness and equality. --Publisher's description

The Incognito Reporter and the On-to-Ottawa Trek - Dupuis, Michael (Friesen Press, 2026)
At the height of the Great Depression, 2,000 young, single, unemployed and homeless men decided to ride boxcars from Vancouver to Ottawa to seek work and wages from Prime Minister "Iron Heel" R.B. Bennett. Their undertaking became the On-To-Ottawa Trek. Vancouver Advocate cub reporter Mark Hunter is given the perilous assignment of infiltrating the Trek. Once accepted into the journey, can he remain incognito? Can he endure the odyssey's hardships and dangers? Also, can he survive the Trek's violent ending? Most important, can he provide objective and accurate reporting of the historic event? --Publisher's description

Confronting the Resurgent Right - Edelson, Miriam (University of Manitoba Press, 2026)
Exposing the deep roots and new threats of Canada's regressive right. Over the past decade, we have witnessed the global mainstreaming of hate as false narratives and conspiracy theories about equity and inclusion, immigration, COVID-19 and vaccinations, and the “gay agenda” have become permissible talking points among right-wing politicians, pundits, and influencers. In Confronting the Resurgent Right, scholars and activists take Canada’s 2022 “Freedom Convoy” as a recent manifestation of deep-rooted extremism. Providing intersectional commentary on the resurgence of the right, they demonstrate how its ideology permeates and shapes the structures of our society. Balancing evidence-based research with careful analysis of the genesis and methods of the right, this volume models pathways of resistance and charges us to work together to expose and counter the regressive forces that spew hate. --Publisher's description

Nouveaux dialogues et conversations émergentes en relations industrielles = New Dialogues and Emerging Conversations in Industrial Relations - Foster, Jason; Jalette, Patrice; Merkouche, Wassila; Yao, Yao (Presses de l'Université Laval, 2026)
Adoptant un format original axé sur le dialogue et la conversation, cet ouvrage collectif se situe dans la tradition des travaux en relations industrielles – un champ disciplinaire étudiant les problèmes variés associés au travail et à l’emploi. Il jette un regard d’ensemble sur les nouveaux enjeux émergents concernant le futur des milieux de travail et aborde des sujets tels que la crise climatique, le télétravail, la diversité, l’équité et l’inclusion au travail, l’avenir du syndicalisme et les droits des travailleurs. / With an original format centred on dialogue and conversation, this book is rooted in the tradition of industrial relations research, a disciplinary field that studies diverse problems associated with work and employment. As a collaborative work that takes a broad look at new and emerging issues concerning the future of workplaces, it addresses topics such as the climate crisis, telework, diversity, equity, and inclusion at work, the future of unionism, and workers’ rights. --Publisher's description / Résumé de l'éditeur

The Long Sixties: Stories from the New Left - Harding, Jim (Fernwood Publishing, 2026)
The sixties were not just “sex, drugs, and rock and roll.” Social movements aimed at overcoming patriarchy, colonialism, and corporate capitalism were equally part of the sixties revolution. These movements are still very much alive. In The Long Sixties, seven veteran political activists from the sixties, all still engaged in campaigns and organizations across Canada, tell their stories of transformational activism. What could veteran activists from the sixties teach about activism? In addition to telling their stories — how they got involved, why they stay involved, how they persevered into their twilight years — they also critically reflect on their victories and defeats, their personal and political challenges, what they learned, and how their perspectives deepened and changed along the way. This book provides hope, chronicling the significant gains — in advancing peace, international human rights, Indigenous rights, women’s and 2SLGBTQ+ rights, workers’ rights, and environmental protection. Weathered voices open an intergenerational conversation about social solidarity and transformation to address the grave crises we face globally and nationally, including climate catastrophe, escalating warfare, extreme wealth inequality, ethno-nationalism, and a heightened continental threat to Canada’s sovereignty. -- Publisher's description

Roles of Resistance: Game Plans for Teachers and Troublemakers - Harter, John-Henry; Leier, Mark (James Mark) (Between the Lines, 2026)
Designed for educators and facilitators from the union hall to the lecture hall, Roles of Resistance: Game Plans for Teachers and Troublemakers outlines revolutionary lesson plans on how to fight the power with people power. The thirteen lesson plans in this book created by John-Henry Harter and Mark Leier can be used independently or combined to create a semester-long course. Sections include units on teaching political economy, labour history, and social activism based on democratic, experiential teaching, including role-plays, simulations, and games. The tried and tested classroom activities in this teacher's guide--successfully applied in high schools, universities, and union classrooms--are bound to create a vibrant learning experience, enriching debates, and providing the main tool we need to change the world: collective action. --Publisher's description

The Red Baron of IBEW Local 213 : Les McDonald, Union Politics, and the 1966 Wildcat Strike at Lenkurt Electric - McDonald, Ian (Athabasca University Press/Canadian Committee on Labour History, 2026)
The “Red Baron” from Local 213 of the International Brotherhood of Electrical Workers (IBEW) was Les McDonald, once a firebrand Communist activist and the youthful leader of the left faction within the Vancouver electrical workers’ union. His fate would be intertwined with the Lenkurt Electric strike of 1966, a wildcat strike that led to the imprisonment of four trade union leaders. Following his involvement as a long-time trade unionist, McDonald went on to be better known for his dedication to the establishment of triathlon as an official sport of the Olympic Games. However, McDonald’s important role in Local 213 and the Lenkurt strike—a watershed moment in Canadian labour history—was, until now, the untold story of the first half of his life. Referencing Local 213’s Minute Books, newspaper articles, collected correspondence, as well as dozens of personal interviews conducted by the author, this book examines the history of IBEW Local 213 in the turbulent years leading up to the Lenkurt strike. In addition to describing these events and their important historical ramifications, author Ian McDonald chronicles how his father helped to rebuild a left faction within the local union. With a focus on the period between 1955 to 1985, this ground-breaking study of a single construction trade union local—its brief post-World War II experience with Communist leadership, well-known work-site militancy, and repeated interventions by the IBEW’s International Office—sheds light on the local’s “red” minority activism and ultimately explains why McDonald returned to the world of sport to finish his career. --Publisher's description

Weather and Work: How Climate Change Relates to Workers' Rights - Sukdeo, Vanisha (Irwin Law, 2026)
This book investigates the growing impact of climate change on Canadian workers, particularly those in outdoor occupations, who face increasing exposure to extreme conditions such as heat domes and wildfires. The book highlights the urgent need for collaboration between labour and corporate law, governments, businesses, and trade unions to address the unique risks encountered by these workers.Focusing on the Canadian context while drawing on global perspectives, the book examines the role of corporations as employers responsible for protecting their workers. It explores how existing legal frameworks can be adapted to address climate-related risks, as well as the potential for creating new tailored legal solutions. The book also highlights the importance of extralegal mechanisms, particularly corporate social responsibility, in enhancing worker safety in the face of climate change. As the nature of all work is made more hazardous at the hands of climate catastrophe, lawyer and pioneering scholar Vanisha H. Sukdeo uncovers the urgency for legal labour reform. By critiquing current legal approaches and proposing innovative solutions, Weather and Work illustrates how labour and corporate law can work together to protect some of the most vulnerable workers from the growing threats posed by global warming. --Publisher's description

The Labour of Care: Canada's Health Care Workers, 1945-2020 - Twohig, Peter L. (Osgoode Society for Canadian Legal History, 2026)
To be published: July 2026. The Labour of Care is the first national, comparative history of health care work. In this book, historian Peter L. Twohig analyses the responses of governments, employers, professional groups, training programs , and unions to the challenge of staffing Canada’s health care system and the reorganization of care.Through careful archival analysis, Twohig demonstrates the conditions under which employees’ boundaries become more flexible, the paths to health care work expand, and tensions emerge among workers in response to labour shortages, decreased funding, and health care reform. This book is attentive to the various identities of health care workers, as women, professionals, union members, and more. It also situates these developments within broader social, economic, and policy changes that reshaped Canada’s health care landscape in the second half of the twentieth century. Examining health care workers in this way reveals a new history of health care that highlights the experiences and contributions of a wide range of workers whose voices have not yet been heard. --Publisher's description

Triumph and Solidarity: BC Communists in the Early Years of the Great Depression - Bartlett, Jon (Working Canadians (Edmonton, Alta.), 2025)
British Columbia was the site of some of the most significant events in the history of the labour movement and had some of the best-organized and most politically conscious communist workers. In this illuminating volume, Jon Bartlett follows the activities of BC Communists from the onset of the Great Depression to the coming of the Popular Front and investigates the collisions between these Communists and the organs of the federal, provincial, and municipal governments. Reflecting on the vectors of cultural resistance, from the creation of vernacular newspapers to the circulation of popular song and verse, Bartlett charts workers’ efforts to resist wage cutbacks in mines, mills, and the logging and fishing industries and describes the organization of opposition to the relief camps and its outcomes. -- Publisher's description
Keywords: British Columbia Economic conditions 20th century; Communists British Columbia History 20th century; Grèves et lock-out Colombie-Britannique Histoire 20e siècle; HISTORY / Canada / Provincial, Territorial & Local / British Columbia (BC); Labor movement British Columbia History 20th century; Mouvement ouvrier Colombie-Britannique Histoire 20e siècle; Strikes and lockouts British Columbia History 20th century; Travailleurs Colombie-Britannique Histoire 20e siècle; Working class British Columbia History 20th century

The Making of a Radical Immigrant - Caccia, Ivana (Friesen Press, 2025)
The radical immigrant in the title of this book, Edo Jardas, was a young Croatian who arrived in Canada in May 1926 and worked for several years as a lumberjack in the hinterland of British Columbia. He was a loyal member of the Communist Party of Canada, a newspaper editor, and a militant trade union activist in the Canadian Croatian community. He fought in the Spanish Civil War in 1937 and returned to Canada as a war veteran. Jardas left Canada for Yugoslavia in 1948 where he assumed several prominent political functions, including the post of mayor of the largest harbour in the country-his hometown of Rijeka-from 1952 to 1955. Rather than being a simple biography, this book describes the circumstances that shaped the Croatian immigrant community in the hostile social and natural environment of Canada. The community was deeply engaged in the political debates concerning the Croatian status in the Kingdom of Serbs, Croats, and Slovenes (later renamed as Yugoslavia) since its foundation in 1919. The question of national identity and its affirmation at home and in the diaspora therefore figured pre-eminently in the Croatian immigrant press.The book is also very much a study in Canadian history. It is an account of the political radicalization of the Canadian working class, inspired by the international communist movement at a time of major economic and political upheaval in the post-WWI decades. --Publisher's description

35 Accords: Re-Imagining British Columbia's Public Sector Labour Relations - Calvert, John; Penikett, Tony (Ethics Press, 2025)
What does a cash-strapped government do when the collective agreements for almost a quarter million of its unionized employees expire simultaneously while wishing to maintain a respectful relationship with its labour supporters? In 1997, the Premier of British Columbia (BC), Canada, Glen Clark, thought of an imaginative solution. It was to offer unions an opportunity to participate with the government in developing policies on issues affecting their members and the services they provide. This was BC’s public sector policy Accord process. The goal was to establish a different, more collaborative relationship with unions, one in which they had a voice in shaping policy solutions. This parallel process – entirely separate from collective bargaining - would also avoid the adversarial relationship that so often characterizes a government’s relations with its unions, by recognizing the positive role unions and their members could play in contributing to improving BC’s public programs and services. The authors, who worked on the Accord process with Premier Clark, provide an insider’s story of the intensive three-year period, during which the parties negotiated 35 policy accords across the entire provincial public sector. The Accords covered a wide range of issues, including pension trusteeship and portability, early retirement, provincial school class size, benefits trusts, government procurement policy, hospital laboratory services, workforce training, pay equity, creation of a health and safety agency and numerous smaller policy fixes. The accord process demonstrated that it was possible for a government to initiate a new and more collaborative relationship with its unions by inviting them into the policy process. The accords definitely improved relations with the government and contributed to collective bargaining settlements within the government’s money mandate. --Publisher's description

Cold War Workers: Labour, Family, and Community in a Nuclear State - Campbell, Isabel (McGill-Queen’s University Press, 2025)
As Canada sought to protect its borders and aid its allies during the Cold War, many people were recruited to build the emerging security state: as construction and maintenance workers, engineers, members of the armed forces, medical researchers, and research subjects. Security work transformed the lives of individuals, families, and communities in ways that were both predictable and surprising, and both beneficial and harmful; the militarization and colonization of Indigenous lives and lands was especially disruptive. The opening essays of Cold War Workers intimately portray the complicated effects of Cold War labour upon Indigenous lives. Elmer Sinclair, a residential school survivor and member of the Canadian armed forces, achieved equality with white men through his militarized masculinity. His more positive professional experience contrasts with those of Indigenous workers on northern radar lines, many of whom lost languages, connections to the land, and other elements of traditional cultures as they sought new skills and better employment. Diverse Indigenous experiences of Cold War security work set the scene for the second set of essays, which explore the impact of security preoccupations on marginalized groups – the study of extreme isolation through scientific experimentation on human subjects; the targeting of gay men with psychiatric labelling to enforce an idealized masculinity; and the restriction of gender mobility in the Canadian military, and the pushback from servicewomen. Cold War Workers raises questions about the influence of settler-colonial masculine institutional values on those who laboured for the Cold War state and society. By comparing the experiences of different types of workers, families, and communities, this volume reveals how race, gender, and privilege affected people in varied and sometimes unexpected ways. -- Publisher's description
Keywords: Cold War Social aspects Canada; Cold War War work Canada; Guerre froide Aspect social Canada; Guerre froide Participation des civils Canada

Leading from the Heart: The Battles of a Feminist, Union Leader and Politician - Darcy, Judy (Douglas & McIntyre, 2025)
In this inspiring memoir, Judy Darcy recounts the remarkable turns that brought her from library worker to president of Canada’s largest labour union, and from there to groundbreaking legislator focused on many of our most pressing issues, including health care, the rights of immigrant workers and the toxic-drug crisis. As this rich memoir shows, the life of activist, union leader and legislator Judy Darcy mirrors many of the great social and political currents of the modern era. Opening in the charged atmosphere of the feminist movement in the late 1960s, when the twenty-year-old Darcy—swept up by the promise of historic, liberating change—infiltrates a beauty pageant and later disrupts Parliament over reproductive rights, the story then reaches back to her earliest years as the daughter of immigrants deeply scarred by World War II. In this tale of personal trauma and desire for justice, Darcy recounts the remarkable turns that brought her from library clerical worker to leading public figure. Her rise through the ranks of the country’s largest union—the Canadian Union of Public Employees, with several hundred thousand members—culminates in her 1991 election as national president, a traditionally male-dominated role. Years later, after moving from Ontario to British Columbia, she is elected to public office, becoming an NDP MLA. Here, as the only North American minister of mental health and addictions, she confronted the ravages of the toxic-drug crisis, working to help some of society’s most vulnerable. Throughout the tumultuous events of her career and personal life, Darcy is forever working for those on the margins, fighting to protect workers’ rights, water rights, health care, childcare and reproductive choice, and helping secure a landmark Supreme Court decision in favour of same-sex partner pensions. Powered by intense conviction and intimately personal experience, her candid story offers a vision of a new kind of leadership, steeped in compassion and able to negotiate the most urgent and complex challenges of our fractured era. -- Publisher's description
Keywords: Activistes Colombie-Britannique Biographies; Autobiographies; Darcy, Judy; Dirigeantes syndicales Colombie-Britannique Biographies; Dirigeants syndicaux Colombie-Britannique Biographies; Feminists British Columbia Biography; Femmes activistes Colombie-Britannique Biographies; Femmes politiques Colombie-Britannique Biographies; Féministes Colombie-Britannique Biographies; Labor leaders British Columbia Biography; Political activists British Columbia Biography; Politicians British Columbia Biography; Politiciens Colombie-Britannique Biographies; Women labor leaders British Columbia Biography; Women political activists British Columbia Biography; Women politicians British Columbia Biography

Seasonal Sociology - Davidson, Tonya K.; Park, Ondine (University of Toronto Press, 2025)
Life in Canada is shaped by the seasons – marked, celebrated, enjoyed, and sometimes dreaded in ways that respond directly to the changing cycles in nature. Sociological thinking encourages us to question the aspects of everyday life that we may otherwise take for granted. Seasonal Sociology takes a sociological approach to thinking about the seasons, providing a unique perspective for understanding social life. Each chapter in this collection explores key issues of sociological interest through the passage of time and seasonal change. The authors wield seasonality as a powerful tool that can bridge small-scale interpersonal interactions with large-scale institutional structures. This collection of contemporary Canadian case studies is wide-ranging and analyses topics such as pumpkin spice lattes, policing in schools, law and colonialism, summer cottages, seasonal affective disorder, Vaisakhi celebrations, and more. The second edition introduces new chapters on Labour Day and organized labour, disability and online dating, maple sugar shacks, seasonal agricultural work, wildfires, and social movements like Pride and Black Lives Matter. Seasonal Sociology ultimately offers fresh, provocative ways of thinking about the nature of our collective lives. -- Publisher's description
Keywords: Canada Mœurs et coutumes; Canada Social life and customs; Case studies; Saisons Aspect social Canada; Saisons Canada; Seasons Canada; Seasons Social aspects Canada; Sociologie Canada Études de cas; Sociology Canada Case studies; Études de cas

Le Moulin-à-Fleur de Sudbury: quartier ouvrier, territoire canadien-français - Dupuis, Serge; Carrey, Normand (Collection Amérique française, 2025)
À son apogée entre 1945 et 1975, le Moulin-à-Fleur ou la paroisse Saint-Jean-de-Brébeuf se vantait d'être le quartier francophone de Sudbury et de l'Ontario. Il représentait en effet la pierre angulaire pour les autres communautés francophones ainsi que le fondement de la vie culturelle, économique et politique des Franco-Ontariens. Mais l'histoire n'a jamais été racontée de façon détaillée. Des années de recherches approfondies ont incité les auteurs à se plonger dans de nombreux écrits, articles scientifiques, archives personnelles, articles de journaux et témoignages afin de livrer cette première étude globale. Divisé en deux volets qui se complètent, ce récit retrace à la fois l'héritage des familles qui se sont battues pour offrir un quotidien et un avenir brillants à leur descendance et la lutte féroce menée par des pionniers, notamment Omer Thériault, Gaétan Gervais et Hélène Gravel, pour la défense culturelle et patrimoniale. Mais tous ces souvenirs dorment dans les rues de l'ancien quartier ou comme Mme Tregonning-Whissell le disait, "à l'ombre des silos". Ce livre témoigne des origines d'une communauté marquée par le dur labeur des mineurs de l'International Nickel, tout en évoquant le rôle des enseignants qui éveillaient les jeunes générations à un monde de possibilités. Le Moulin-à-Fleur de Sudbury rend hommage aux valeurs de charité et d'entraide qu'incarnait ce quartier qui célèbre au-delà de 120 ans de vie communautaire et culturelle. -- Résumé de l'éditeur
Keywords: Canadiens français Ontario Grand Sudbury Histoire; Grand Sudbury (Ont.) Histoire; Moulin-à-Fleur (Grand Sudbury, Ont.) Histoire; Neighborhoods Ontario Greater Sudbury History; Quartiers (Urbanisme) Ontario Grand Sudbury Histoire

Industrial Relations in Canada - Foster, Jason; McQuarrie, Fiona A. E. (Wiley, 2025)
Industrial Relations in Canada, Fifth Edition, offers students a comprehensive and accessible introduction to the Canadian industrial relations system. Designed for learners with minimal knowledge of the subject, this market-leading textbook blends theory, practice, and process in a clear and engaging way. Student-friendly chapters walk through key topics such as unionization, collective bargaining, dispute resolution, and evolving legal frameworks, while minimizing jargon and legalistic language. Throughout the book, timely coverage of controversial and complex issues fosters critical thinking and real-world problem-solving skills. Integrating a process-oriented approach developed through years of classroom experience, Industrial Relations in Canada, Fifth Edition, is ideal for university and college students in introductory labour relations courses, as well as adult learners in business, human resource management, and labour studies programs. With its strong foundation in both academic theory and practical application, it is also an excellent springboard for more advanced studies in industrial relations. New to this edition: new chapter-opening vignettes featuring Canadian labour relations practitioners; new discussions of social media’s role in union organizing and labour activism, and the effects of technological change on labour-management dynamics; new coverage of current research on union and workplace issues; updated news stories in every chapter reflecting current events in Canadian workplaces; discussions of the impacts of COVID-19 and climate change on labour relations; enhanced analysis of recent court decisions affecting collective bargaining; and updated statistics and demographic data on unionization, strikes, and lockouts across Canada. --Publisher's description

Constructing Modern Slavery: Law, Capitalism, and Unfree Labour - Fudge, Judy (Cambridge University Press, 2025)
Modern slavery laws are a response to global capitalism, which undermines the distinction between free and unfree labour and poses intense challenges to state sovereignty. Instead of being a solution, Constructing Modern Slavery argues that modern slavery laws divert attention from the underlying structures and processes that generate exploitation. Focusing on unfree labour associated with international immigration and global supply chains, it provides a novel socio-legal genealogy of the concept 'modern slavery' through a series of linked case studies of influential actors associated with key legal instruments: the United Nations, the United States, the International Labour Organization, the European Union, the United Kingdom, and Walk Free Foundation. Constructing Modern Slavery demonstrates that despite the best efforts of academics, advocates, and policymakers to develop a truly multifaceted approach to modern slavery, it is difficult to uncouple antislavery initiatives from the conservative moral and economic agendas with which they are aligned. --Publisher's description

The Left in Power: Bob Rae's NDP and the Working Class - High, Steven C. (Between the Lines, 2025)
At the end of the twentieth century, as social democratic parties around the world struggled to produce a coherent response to the deindustrialization crisis, many pivoted towards progressive neoliberalism and Third Way social democracy. Almost everywhere, they turned their backs on the weakened trade union movement and embraced neoliberal assumptions about labour force flexibility and global competition. Shamefully, Third Way social democrats emphasized the moral dimension of poverty rather than its structural causes as they abandoned the old redistributive class politics of the Left. Based on extensive archival research and interviews with NDP politicians, senior economic policy advisors, and trade unionists, The Left in Power examines the response of the political Left in Ontario to the crisis that gripped the old ‘industrialized world.’ Steven High revisits the heartbreaking years of Bob Rae’s Ontario NDP government—from their historic and unexpected 1990 victory, to their policy shifts that left working-class voters feeling betrayed, to their landslide defeat in 1995—to uncover what we can learn from one social democratic party’s mistakes about how to govern from the Left. --Publisher's description
Keywords: New Democratic Party of Ontario; Ontario Economic conditions 1991-; Ontario Politics and government 1990-1995; Rae, Bob

Work and Labour in Canada: Critical Issues - Jackson, Andrew; Thomas, Mark P.; King, Adam D. K. (Canadian Scholars Press, 2025)
Over the last several decades, the workplace in Canada has experienced profound changes. Work has become increasingly insecure for a growing number of workers, and income inequality has deepened. New technologies have reshaped labour processes and have enhanced elements of employer control over work and workers. Entry into the labour market is itself a difficult process, as young workers struggle to match qualifications and credentials with jobs, while for many older workers, retirement with a secure income is a diminishing prospect. The demographic composition of the labour market is transforming, yet this change is conditioned by longstanding patterns of inequality in terms of gender, race, disability, and immigration status. Work and Labour in Canada explores the changing world of work, mapping out major trends and patterns that define working life and identifying the economic, social, and political factors that shape the contemporary workplace. Evaluating working conditions and the quality of jobs from a critical perspective, this text presents an analysis of recent trends in employment and unemployment as well as outlines the role and impact of unions and other workers’ organizations. The fourth edition includes a new chapter on work and technology, updated statistical data, and additional content on the basic income debate, labour and climate change, and COVID-19. This thoroughly revised and updated edition is essential for teachers, researchers, labour activists, and students of labour studies, sociology, political science, political economy, and economic geography programs. --Publisher's description

The Art of Solidarity: Labour Arts and Heritage in Canada - Kristofferson, Robert B.; Ross, Stephanie (Between the Lines, 2025)
The Art of Solidarity delves into the rich tapestry of labour arts and heritage in Canada—from protest music and union banners, to murals, community theatre, and oral histories, to workers’ history museums and arts festivals—showcasing how these expressions of working people’s culture have been essential to challenging inequality and fostering solidarity. This inspiring collection highlights the resilience and creativity of labour arts and heritage practitioners who, despite financial and organizational challenges, continue to amplify the voices and experiences of working-class communities. In an economy characterized by growing polarization, inequality, precarity, and uncertainty about the future and meaning of work, labour arts and heritage has a central role to play in providing answers that challenge the prevailing narratives about whose work matters and whose efforts are central to our communities’ wellbeing. This work is more important than ever before. -- Publisher's description
Keywords: Arts Aspect politique Canada; Arts Political aspects Canada; Arts and society Canada; Arts et société Canada; Arts, Canadian; Labor in art; Labor movement Canada; Labor movement in art; Mouvement ouvrier Canada; Mouvement ouvrier dans l'art; Political art Canada; Solidarity Canada; Solidarity Political aspects Canada; Travail dans l'art

Women United: Stories of Women's Struggles for Equality in the Canadian Auto Workers Union - Nash, Peggy; White, Julie (Between the Lines, 2025)
Based on the firsthand stories of dozens of women leaders in the Canadian Auto Workers (CAW), Women United examines what workplaces were like for women, how they became involved in the union, and the challenges women faced, sometimes at great personal cost. From struggles for representation in their union to their fight for affirmative action and childcare, and work against gender-based violence and harassment, Peggy Nash and Julie White show how these feminist activists were joined in struggle not only by their union sisters, but also by their sisters from the broader women’s movement, who learned from them about the importance of women’s workplace rights. Nash and White document the decades-long struggles of generations of women activists in the CAW, who, despite their few numbers, managed to build a better, more inclusive union. A testament to the union’s motto that "fighting back makes a difference," Women United makes an important contribution to feminist, labour, and social history. -- Publisher's description
Keywords: BIOGRAPHY & AUTOBIOGRAPHY; CAW-Canada History; Electronic books; Femmes dans le mouvement ouvrier Canada Histoire; Labor movement Canada History; Labor union members Canada History; Mouvement ouvrier Canada Histoire; POLITICAL SCIENCE; Syndiqués Canada Histoire; Women; Women in Politics; Women in the labor movement Canada History; Women labor union members Canada History

Rethinking Feminist History and Theory: Essays on Gender, Class, and Labour - Pasolli, Lisa; Smith, Julia (University of Toronto Press, 2025)
Rethinking Feminist History and Theory considers the past, present, and future of feminist history and theory, emphasizing how feminism has influenced the histories of gender, class, and labour, and their intersections. This vibrant collection, inspired by the work of historian and women’s studies scholar Joan Sangster, features essays from academics across multiple disciplines, highlighting the dynamism of feminist historical scholarship in Canada. The book explores questions such as: How has women’s resistance and radicalism been expressed, lived, represented, and repressed over the past century? How do we research these phenomena? How do we situate feminism in relation to other movements for egalitarian social change? Contributors explicitly address these recurring themes, aiming to chart new directions for future research and teaching. While primarily Canadian-focused, the collection includes global perspectives, with contributions from scholars in Chile, Finland, Sweden, and the UK. These essays emphasize the importance of cross-disciplinary collaboration, incorporating insights from labour studies, political economy, anthropology, legal studies, and feminist theory. Ultimately, Rethinking Feminist History and Theory engages deeply with Sangster’s rich and wide-ranging work to understand and interpret women’s experiences. It seeks to inspire future scholarship and teaching in feminist history and theory, showcasing the ongoing relevance and adaptability of feminist perspectives. -- Publisher's description
Keywords: Feminism Canada History; Feminist theory Canada History; Femmes Activité politique; Femmes Conditions sociales; Féminisme Canada Histoire; Théorie féministe Canada Histoire; Women Legal status, laws, etc; Women Political activity; Women Social conditions

Policing in Canada: Concepts, Actors and Challenges - Prado, Grégory Gómez del; Leman-Langlois, Stéphane (Éditions JFD, 2025)
Drawing on both the academic field and homeland security practices, this book addresses the essential themes in the study of policing: its origin, theorization and structure. It focuses on the public police in Canada, making it a unique and original perspective. It adopts a critical approach to the fundamental aspects of policing, including patrol, investigation, intelligence, private policing, and transnational policing. It also highlights the issues of legitimacy and image management, as well as the contemporary challenges organizations and individuals face. Reflecting the authors’ background, this book brings a criminological perspective to the study of Canadian policing while remaining rooted in its day-to-day practice. As such, it will appeal to those interested in the workings of traditional policing and those wishing to explore the more complex aspects of policing in society.

Standing Up to Big Nickel: The Story of the Mine, Mill and Smelter Workers Strike, 1958 - Quinlan, Elizabeth (McGill-Queen's University Press, 2025)
All miners and smelter workers know the folly of going on strike when their employer holds a stockpile. In 1958 the International Nickel Company had enough nickel on hand to guarantee sales for at least six months. Despite this, fourteen thousand miners and smeltermen in Sudbury, Ontario, downed their tools and struck against the corporate titan of the mining industry. Standing Up to Big Nickel is a comprehensive portrait of a pivotal strike by the International Union of Mine, Mill, and Smelter Workers, a union that has inspired exceptional levels of solidarity among its members. The Cold War and the resulting instabilities in the Canadian labour movement form the backdrop to Elizabeth Quinlan’s engrossing analysis. The union straddled the line, she shows, between its historical commitment to working-class struggle and the newly restrictive legal landscape of the postwar era. Retrospective accounts by surviving union members, leaders, family, and community members bring to life the history of a distinctive group of workers who sweated over smelter furnaces and toiled underground in perilous conditions. Quinlan traces the events before, during, and after one of Canada’s greatest strikes in both magnitude and duration. Featuring biographical sketches and scenes based on archival and documentary data, Standing Up to Big Nickel captures an intensely dramatic juncture in Canadian labour history. --Publisher's description

Social Determinants of Health: Canadian Perspectives - Raphael, Dennis (Canadian Scholars' Press, 2025)
Now in its fourth edition, Dennis Raphael’s Social Determinants of Health offers the definitive Canadian discussion of the primary factors that influence the health of Canada’s population.This unique text on the social determinants of health contains contributions from top academics and high-profile experts from across Canada. Taking a public policy approach, the contributors to this edited collection critically analyze the structural inequalities embedded in our society and the socio-economic factors that affect health―including income, education, employment, housing, food security, gender, and race. This new edition includes recent statistics, new developments in early childhood education and the implementation of Canada’s national childcare system, and new content on the social determinants of Indigenous Peoples’ health. Particular attention is paid to how economic globalization and the acceptance of neoliberal governing ideology is shaping the health of Canadians. The COVID-19 epidemic vividly illustrated the importance of the social determinants of health, as sickness and death rates were strikingly higher among Canadians in groups already experiencing adverse living and working conditions and poorer health: lower income Canadians, recent immigrants of colour, and those experiencing housing and food insecurity. If anything positive is to come out of this experience, it will be recognition that in the current post-COVID-19 environment, it is essential to understand the socio-economic conditions that shape the health of individuals and communities. Social Determinants of Health, Fourth Edition is aimed at courses focusing on the social determinants of health at Canadian universities and colleges, particularly those in health studies and nursing, but also allied health, sociology, and human services. --Publisher's description

The Price of Gold: Mining, Pollution, and Resistance in Yellowknife - Sandlos, John; Keeling, Arn (McGill-Queen's rural, wildland, and resource studies series, 2025)
Fifty years of gold mining at Yellowknife in the Northwest Territories spurred northern settlement and produced millions of dollars in profits. But mineral processing also had catastrophic environmental effects and left a troubled legacy. When two mining companies in Yellowknife began processing gold ore in the 1940s, they did so with little or no pollution controls. Giant Mine spewed thousands of kilograms of arsenic trioxide from its roaster stack into the environment, causing illness and death among people and animals, especially in the adjacent Yellowknives Dene community. Even after the companies installed controls, arsenic trioxide continued to enter the atmosphere and waterways. Eventually Giant Mine, the biggest polluter, would deposit the arsenic dust beneath the mine, leaving 237,000 tonnes of highly toxic material buried underground. For decades, the mining companies and the federal government hid the worst effects of the pollution, doubted their own studies, and resisted calls for action. Yet the Yellowknives Dene fought back with the support of labour unions and environmental groups, questioning the safety of the air and water in their community and the massive toxic deposit underground. The Price of Gold traces the troubling history of one of Canada’s most contaminated sites but also the inspiring story of Indigenous, labour, and environmental activists who resisted the ongoing poisoning of their communities. -- Publisher's description
Keywords: Arsenic trioxide Health aspects Northwest Territories Yellowknife; Dene Social conditions Northwest Territories Yellowknife; Environmental protection Northwest Territories Yellowknife; Environnement Protection Territoires du Nord-Ouest Yellowknife; Giant Mine (Yellowknife, N.W.T.); Gold mines and mining Environmental aspects Northwest Territories Yellowknife; Gold mines and mining Government policy Northwest Territories Yellowknife; Gold mines and mining Health aspects Northwest Territories Yellowknife; Or Mines et extraction Aspect de l'environnement Territoires du Nord-Ouest Yellowknife; Or Mines et extraction Politique gouvernementale Territoires du Nord-Ouest Yellowknife; Yellowknife (N.W.T.) Environmental conditions

The New Politics of Western Canada: Contested Histories, Uncertain Futures - Smith, Charles W.; McIntosh, Thomas A. (UBC Press, 2025)
The Canadian West: an economic engine with a history of grievance against federal power emanating from the east. The New Politics of Western Canada grapples with the West’s complex, multifaceted past to promote a better understanding of this vast region’s political realities and the challenges that lie ahead. Contributors re-examine the historical and contemporary meanings attached to “the West” as a form of identity, through themes such as colonialism, gender, and class. They develop a nuanced analysis of Western political ideology, from resentment-based populism to the regional left. And they explore pressing Western economic and policy concerns, such as labour, health care, and Indigenous democratic participation and protest. Together, these themes provide intelligent new ways of interpreting underexplored aspects of Western Canadian politics, adding depth to earlier attempts to explain the region as a political, economic, or sociological space. -- Publisher's description
Keywords: Canada, Western Politics and government

Young and Female: International Perspectives on the Future of Farming - Srinivasan, Sharada; Pan, Lu; Ambarwati, Aprilia (Practical Action Publishing, 2025)
Women’s roles in sustaining and the revival of farming are indispensable. Based on research in Canada, China, India and Indonesia, the book offers a global perspective on young women’s pathways into farming. It responds directly to concerns about the generational sustainability of smallholder farming worldwide. Despite their crucial contribution to the reproduction of farming and its belated recognition in policy discourse, women farmers continue to face constraints in access to agrarian resources and services, and recognition as farmers in their own right. --Publisher's description

A Labour of Love: In Pursuit of Just Causes - Stewart, Herman (Independently published, 2025)
From a small rural village in Jamaica to the negotiating tables of Canada’s labour movement, A Labour of Love traces the extraordinary journey of Herman Stewart, a community builder, labour activist, and relentless advocate for justice.This deeply personal memoir captures the heart of a man who arrived in Canada with modest beginnings and rose to become a respected leader in the Jamaican Canadian community and the broader labour movement. Through vivid storytelling, Stewart recounts his early life in Jamaica, the cultural challenges of immigration, and his unyielding commitment to workers’ rights and social justice.With wisdom, humour, and humility, Stewart sheds light on the struggles and triumphs of a generation that paved the way for change in Canadian society. His story is not only a tribute to activism and perseverance but also a call to action for future generations to carry forward the fight for equity and inclusion.This is more than a memoir; it’s a legacy of purpose, courage, and hope. --Publisher's description

Workers of War and Empire from New France to British America, 1688–1783 - Tomczak, Richard H. (McGill-Queen's Studies in Early Canada, 2025)
Throughout the eighteenth century, the French and British empires mobilized thousands of labourers in Canada through a system of mandatory labour known as “corvée.” This social arrangement was rooted in the feudal obligations of French peasants to landowners. Under the French regime, corvée was a custom, an obligation, and a form of obedience, a “local affair” embedded in an agricultural way of life that retainined a sense of reciprocity with mechanisms to discourage exploitation. However, with the British conquest of Quebec in 1763, and, later, the American Revolution, the corvée system assumed new dimensions. The British recognized the need for labour power in an underpopulated region and coopted the corvée customs for their own imperial ends. Though British officials retained some French statutes, they enacted new laws mobilizing the male inhabitants of New France to work in state enterprises (such as iron mining and logging), with Labourers holding little to no input into how the colonial state viewed their well-being. Leaning heavily on corvée as a form of conscription, the British army’s surging demand for workers in Quebec precipitated wide-spread protests. This crisis forced the royally appointed governor Frederick Haldimand to ratify a new provincial code regulating the use of corvée. Workers of War and Empire from New France to British America, 1688-1783 chronicles the transformation of the corvée system over a century, positioning French Canadian workers at the center of the narrative. -- Publisher's description
Keywords: Corvée Canada Histoire 17e siècle; Corvée Canada Histoire 18e siècle; Corvée Canada History 17th century; Corvée Canada History 18th century; French-Canadians History 17th century; French-Canadians History 18th century; Labor Canada History 17th century; Labor Canada History 18th century; Travail Canada Histoire 17e siècle; Travail Canada Histoire 18e siècle

Asian Canada Is Burning: Theories, Methods, Pedagogies, and Praxes - Torres, Rose Ann; Liujia Tian, Ian; Chau, Coly (Studies in critical social sciences, 2025)
This book is an invitation to trouble the mobilization of “anti-Asian hate” in the aftermath of COVID-19 pandemic. Bringing together activists, organizers, academic, and artists, this book explores the historical and contemporary conditions that make theorizing “Asian Canadian” feasible. Grounded in a transnational queer and feminist lens, this book also aims to envision possible futures and solidarities. Ultimately, this collection is concerned with moments and places of tensions, confrontations, relations, and solidarity. We offer stories of insurgent encounters as people who identify as “Asian” navigate and implicate settler colonial nation-state to make new dreams, histories and intimacies. -- Publisher's description
Keywords: Asians Canada Social conditions; Asians Race identity Canada; Canada Conditions sociales; Canada Race relations; Canada Social conditions; Communautés de minorités sexuelles Canada; Group identity Canada; Identité collective Canada; Racism Canada; Racisme Canada; Sexual minority community Canada

Migrant Work by Another Name: Differential Inclusion and Precarity in Canada’s International Mobility Program - Vosko, Leah F. (Studies in comparative political economy and public policy, 2025)
Migrant Work by Another Name explores the complexities of Canada's evolving international migration and employment policy landscape. It critically examines the shift towards “mobility” programs under the recently inaugurated International Mobility Program (IMP). This shift occurs alongside the contraction of certain streams within Canada’s long-standing Temporary Foreign Worker Program (TFWP). The book investigates the implications of policy changes, influenced at once by public outcry over migrant worker exploitation and persistent demands for labour in the face of qualitative labour shortages in high-income countries like Canada. Grounded in a decolonial feminist political economy approach, Leah F. Vosko employs a mixed methods analysis to contrast the narrative of “mobility” with the persistent realities of precarity among transnational workers. The book features in-depth case studies of the three largest IMP subprograms – Working Holiday, Post-Graduation, and Spousal Work Permit programs – revealing how these initiatives, despite being touted as promoting mobility, provide for temporary migrant work by another name and perpetuate distinct forms of precarity. This critical perspective challenges the notion of progress in contemporary migration policies, shedding light on the ongoing challenges faced by transnational workers in Canada. -- Publisher's description
Keywords: Foreign workers Employment Government policy Canada Evaluation; International Mobility Program (Canada) Evaluation; Labor mobility Government policy Canada Evaluation; Main-d'œuvre Mobilité Politique gouvernementale Canada Évaluation

Gender and Technology at Work: From Workplace Studies to Social Justice in Design - Balka, Ellen; Wagner, Ina; Weibert, Anne; Wulf, Volker (Cambridge University Press, 2024)
This book brings together the vast research literature about gender and technology to help designers understand what a gender perspective and a focus on intersectionality can contribute to designing information technology systems and artifacts, and to assist organizations as they work to develop work cultures that are supportive of women and marginalized genders and people. Drawing on empirical and analytical studies of women's work and technology in many parts of the world, the book addresses how to make invisible aspects of work visible; how to recognize women's skills without falling into the trap of gender stereotyping; how to engage in improving working conditions; and how to defend care of life situations and needs against a managerial logic. It addresses challenges for design, including many overlooked and undervalued aspects, such as the complexities involved in human–machine interactions, as well as the need to create safe spaces for research subjects. --Publisher's description

The Practice of Human Resource Management in Canada - Barnetson, Bob; Foster, Jason (Open paths to enriched learning, 2024)
This introductory human resource management (HRM) textbook provides students with an overview of the major domains of human resource management (the “how-to”) with a focus on the practical application of the most recent HRM research and best practices. Students will learn to understand, anticipate, and respond to how power, profit, and intersectionality shape the practice of HRM. Moving beyond the typical procedure-oriented textbook, Barnetson and Foster provide thought-provoking political analysis to better prepare students for the real-world practice of human resource management. --Publisher's description

Les pionniers irlandais du Québec et de l'Ontario: fermiers, ouvriers et bûcherons - Campey, Lucille H. (Septentrion, 2024)
Dès la fin de la guerre de Sept Ans, un nombre croissant d'Irlandais ont migré au Canada à la recherche d'une vie meilleure. Libérés des contraintes économiques et sociales étouffantes qui les retenaient dans leur pays d'origine, ils ont prospéré, notamment au Québec et en Ontario. Dans cet ouvrage synthèse, Lucille H. Campey dépeint les communautés irlandaises qui se sont formées dans différentes régions de l'Ontario et du Québec aux XVIIIe et XIXe siècles, à travers un récit informatif et vivant de cette grande saga de l'immigration. L'ouvrage décrit aussi les navires qui les ont transportés, dévoile les nombreuses réalisations de ces pionniers et déconstruit ainsi les interprétations modernes tendant à victimiser cette population. --Publisher's description
Keywords: Immigrants Ontario Histoire; Immigrants Ontario History; Immigrants Québec (Province) Histoire; Immigrants Québec (Province) History; Ireland Emigration and immigration History; Irlandais Ontario Histoire; Irlandais Québec (Province) Histoire; Irlande Émigration et immigration Histoire; Ontario Emigration and immigration History; Ontario Émigration et immigration Histoire; Québec (Province) Emigration and immigration History; Québec (Province) Émigration et immigration Histoire

Facing Precarity in Adult, Community, and Vocational Education: Role of Meaningful Work - Collister, Rupert Clive (IGI Global Scientific Publishing, 2024)
"This edited volume provides a comprehensive scan of the politics and policies that inform and shape precarity in adult, community, and vocational education. It will explore the in/adequacy of existing theories of adult and workplace education and professional development to capture the experiences of the precariat"-- Provided by publisher
Keywords: Adult education Case studies; Continuing education Case studies; Enseignement professionnel Études de cas; Vocational education Case studies; Éducation des adultes Études de cas; Éducation permanente Études de cas

An Accidental History of Canada - Davies, Megan Jean; Hudson, Geoffrey L. (McGill-Queen’s/AMS healthcare studies in the history of medicine, health, and society, 2024)
Although Canadian history has no shortage of stories about disasters and accidents, the phenomenon of risk, upset, and misfortune has been largely overlooked by historians. Disasters get their due, but not so the smaller scale accident where fate is more intimate. Yet such events often have a vivid afterlife in the communities where they happen, and the way in which they are explained and remembered has significant social, cultural, and political meaning. An Accidental History of Canada brings together original studies of an intriguing range of accidents stretching from the 1630s to the 1970s. These include workplace accidents, domestic accidents, childhood accidents, and leisure accidents in colonial, Indigenous, rural, and urban settings. Whether arising from colonial power relations, urban dangers, perils in resource extraction, or hazardous recreations, most accidents occur within circumstances of vulnerability, and reveal precarity and inequities not otherwise apparent. Contributors to this volume are alert to the intersections of the settler agenda and the elevation of risk that it brought. Indigenous and settler ways of understanding accidents are juxtaposed, with chapters exploring the links between accidents and the rise of the modern state. An Accidental History of Canada makes plain that whether they are interpreted as an intervention by providence, a miscalculation, inevitability, or the result of observable risk, accidents--and our responses to them--reveal shared values. -- Publisher's description
Keywords: Accidents Canada Histoire; Accidents Canada History

Unjust Transition: The Future for Fossil Fuel Workers - Eaton, Emily; Stevens, Andrew; Tucker, Sean (Fernwood Publishing, 2024)
In 2019, Regina’s Co-op Refinery Complex (CRC), a subsidiary of Federated Co-operative, locked out Unifor Local 594 after collective bargaining negotiations failed. CRC used the transition to a “low carbon” future as the justification for concessions on working conditions and reducing the workers' pension plan. The lockout demonstrates what a “just transition” means to fossil fuel corporations: rollbacks of collective bargaining, worker rights, cooperative spirit and environmental justice. In the name of a new future, Federated Co-operative and the Saskatchewan government trampled all over important worker rights — the right to strike and picket, occupational health and safety, pensions and collective bargaining. It also highlights the sorry state of co-operative values in Canada. As corporations and governments are poised to make a transition that will be detrimental to workers and communities, this books argues that solidarity between unions and community movements is absolutely necessary to make the transition away from fossil fuels a just one. -- Publisher's description
Keywords: Collective bargaining Saskatchewan Regina; Grèves et lock-out Pétrole Industrie et commerce Saskatchewan Regina; Labor unions Saskatchewan Regina; Négociations collectives Saskatchewan Regina; Petroleum industry and trade Saskatchewan Regina; Petroleum refineries Saskatchewan Regina; Pétrole Industrie et commerce Saskatchewan Regina; Pétrole Raffineries Saskatchewan Regina; Strikes and lockouts Petroleum industry Saskatchewan Regina; Syndicats Saskatchewan Regina

Who Killed Sir William? A Community-University Research Alliance Seeks Justice for Injured Workers - Endicott, Marion; Mantis, Steve (FriesenPress, 2024)
In 1910, Sir William Meredith led a Royal Commission to investigate the injury, death, and permanent disability of workers. In response to his findings, Meredith helped introduce a new system of compensation for injured and disabled workers that emphasized their rights and well-being. But today, Sir William’s principles appear to be dead: injured and disabled workers often end up living in poverty and are viewed with stigma by those who should be providing them with service. What happened? How can we find out the experiences and needs of injured and disabled workers, and how can the necessary changes be put into action? To answer such questions, the Research Action Alliance on the Consequences of Work Injury (RAACWI), a community-based research initiative that brought advocates, injured workers, and academics together, was formed. Who Killed Sir William? provides an engaging look at RAACWI’s eight years of groundbreaking work and what a successful community-academia partnership looks like to inform and inspire fellow academics, advocates, and community. Its discussion includes (and goes beyond): Developing a trusting, productive, community-advocate-academic relationship; successes such as the production of over twenty research publications and a speakers school for injured workers; the use of diverse teaching methods, including skits and theatre pieces; [and] some of the challenges RAACWI faced (and how they overcame them). In Who Killed Sir William? authors Marion Endicott and Steve Mantis not only offer insight on the systemic assailants, but also lay out a process of addressing them. --Publisher's description

Humans: The 300,000 Year Struggle for Equality - Finkel, Alvin (Lorimer, 2024)
For 300,000 years humans have pushed for equality in their societies. For the first time ever, historian Alvin Finkel brings together the evidence to tell the story of the 99% who have constantly sought to live in a society of equals. This is a history of humanity like it's never been told before. Historian Alvin Finkel builds on the work of archaeologists, anthropologists and historians to present the very long view of the history of the human species. His focus is not on the leaders whose exploits are recounted in traditional histories, but rather on the experiences of ordinary people, the 99%, whose experiences and activities are often overlooked. In the extensive research of many contemporary scholars, Alvin Finkel notes a common thread which most historians have ignored: the constant efforts of ordinary people throughout history to create and sustain societies based on equality of all individuals. Contrary to traditional historical writing, he finds that the earliest human communities usually treated all individuals as equals. In the histories of societies all around the world, he records how individuals who found ways to gain wealth and power have faced constant, often successful, resistance from the rest. From the first recorded communities in Mesopotamia to the COVID-19 pandemic, this book features the resistances, uprisings, struggles, and solidarities of the majority against those seeking to dominate. The result is a fresh and challenging interpretation of the history of our species, one that casts a new light on the true nature of humans. --Publisher's description
Keywords: Equality History

Le parcours d'un insatiable historien (Guy Gaudreau, 2024)
Ce livre retrace en 15 chapitres le parcours de l'historien Guy Gaudreau qui a choisi les textes les plus représentatifs de sa carrière. --Quatrième de couverture
Keywords: Ethnomycologie; Forêts Exploitation Ontario (Nord-Est); Gaudreau, Guy, 1953-; Grève de la Compagnie internationale de papier du Canada, Rouyn-Noranda, Québec, 1934; Mineurs d'or Ontario Kirkland Lake Histoire; Villeray (Montréal, Québec) Histoire

Law at Work: The Coercion and Co-Option of the Working Class - Glasbeek, H. J. (Harry J.) (Between the Lines, 2024)
The renowned Harry Glasbeek unpacks how law has been used to ensure that workers' aspirations are kept in check. Law at Work uncovers how the legal system, through its structures and mechanisms, legitimizes and reinforces the exploitation of workers. Using historic and contemporary examples, Glasbeek illustrates how conscious manipulations of law are part and parcel of how law protects capitalists at the expense of workers. He proves how the very laws designed to safeguard rights and freedoms often act as invisible shackles, compelling readers to reflect on their own struggles as they navigate a world where the legal system fails to serve their interests. These manipulations are made to look innocent because the underlying structures and ideology which give rise to specific rules are not challenged or challengeable. This thought-provoking book is an indispensable resource for those seeking to understand the hidden dynamics of worker oppression, empowering readers to question prevailing narratives and envision a future where the law truly serves the interests of all. -- Publisher's description
Keywords: Labor laws and legislation

Ontario Public Service Employment & Labour Law - Hadwen, Timothy; Strang, David (Irwin Law, 2024)
This book deals with the Crown Employees Collective Bargaining Act and the Public Service Act, the statutes that primarily govern unionized and non-unionized employment and labour relations in the Ontario Public Service and Crown Agencies. This updated edition provides a full review of all sections, and all judicial and arbitral consideration, of both acts. It also discusses the unique treatment of the Crown and its employees in the Public Sector Labour Relations Transition Act and the Employment Standards Act. -- Publisher's description
Keywords: Civil service; Civil service Ontario; Collective labor agreements Government employees; Collective labor agreements Government employees Ontario; Employee-management relations in government Law and legislation; Employee-management relations in government Law and legislation Ontario; Labor laws and legislation; Labor laws and legislation Ontario; Ontario

Needle Work: A History of Commercial Tattooing in Canada - Jelinski, Jamie (McGill-Queen's/Beaverbrook Canadian Foundation Studies In Art History Series, 2024)
An original history of those who made tattooing their livelihood. In 1891 J. Murakami travelled from Japan, via San Francisco, to Vancouver Island and began working in and around Victoria. His occupation: creating permanent images on the skin of paying clients. From this early example of tattooing as work, Jamie Jelinski takes us from coast to coast with detours to the United States, England, and Japan as he traces the evolution of commercial tattooing in Canada over more than one hundred years. Needle Work offers insight into how tattoo artists navigated regulation, the types of spaces they worked in, and the dynamic relationship between the images they tattooed on customers and other forms of visual culture and artistic enterprise. Merging biographical narratives with an examination of tattooing’s place within wider society, Jelinski reveals how these commercial image makers bridged conventional gaps between cultural production and practical, for-profit work, thereby establishing tattooing as a legitimate career. Richly illustrated and drawing on archives, print media, and objects held in institutions and private collections across Canada and beyond, Needle Work provides a timely understanding of a vocation that is now familiar but whose intricate history has rarely been considered. --Publisher's description

The Lights on the Tipple Are Going Out: Fighting Economic Ruin in a Canadian Coalfield Community - Langford, Tom (UBC Press, 2024)
To be published: June 2025. The Canadian postwar economic boom did not include one western coal-mining region. When the Canadian Pacific Railway switched to diesel power, over 2,000 coal-production jobs were lost in the Crowsnest Pass and Elk Valley. The Lights on the Tipple Are Going Out tells the story of its fight for survival. Underground mine closures began in 1950, prompting attempts by unions, leftist parties, municipal governments, and business groups to save the local economy. Efforts to reindustrialize in the mid-1960s brought unregulated growth, unsafe working conditions, and pollution. Starting in 1968, new strip mines were built to produce metallurgical coal for Asia-Pacific steelmakers. Not only is this an interesting regional history, but the consideration of the role of labour unions, local communists, and grassroots environmentalists makes it especially compelling. Today, with technological change in steel manufacturing on the horizon, propelled by the climate crisis, Langford argues that the Crowsnest Pass and Elk Valley must look toward ecosystem restoration, sustainable economic activities, and the inclusion of First Nations in decision making in order to embrace a future beyond coal. -- Publisher's description
Keywords: Coal trade Alberta Crowsnest Pass History 20th century; Coal trade British Columbia Elk River Valley History 20th century; Crowsnest Pass (Alta.) Economic conditions 20th century; Deindustrialization Alberta Crowsnest Pass History 20th century; Deindustrialization British Columbia Elk River Valley History 20th century; Economic development Alberta Crowsnest Pass; Economic development British Columbia Elk River Valley; Elk River Valley (B.C.) Economic conditions 20th century

The Truth About the '37 Oshawa GM Strike: They Made Cars and They Made Plans: Reds, The Rank and File, and International Solidarity Unionized GM - Leah, Tony (Baraka Books, 2024)
Autoworkers unionized the General Motors plant in Oshawa in 1937 after a bitterly fought strike that pitted them against a rabidly anti-union government, hostile press and GM corporation. It was a major turning point in Canadian labour history. Crucial factors contributing to the strike’s success include the historical background of working-class struggle in the community, patient and courageous prior organizing by Communists, the engaged leadership of rank-and-file GM workers, and the solid support of the United Autoworkers International Union. The author focuses on the voices and actions of rank-and-file workers and on the day-to-day events, many of which have been misunderstood or misinterpreted. The Truth About the ’37 Oshawa GM Strike takes down the long-accepted—but false—narrative espoused by the academic Irving Abella that the Oshawa workers were “on their own” without significant support from the UAW/CIO leadership and that they would have been better off not to organize under the banner of an international union. It also shows how that narrative fails to grasp the degree to which class struggle organizing principles were crucial to the strike’s success. A true understanding of the ’37 strike provides valuable lessons for people seeking to revive the labour movement today. --Publisher's description

Cape Breton in the Long Twentieth Century: Formations and Legacies of Industrial Capitalism - MacKinnon, Lachlan; Parnaby, Andrew (Working Canadians: Books from the CCLH, 2024)
The emergence, dominance, and alarmingly rapid retreat of modernist industrial capitalism on Cape Breton Island during the “long twentieth century” offers a particularly captivating window on the lasting and varied effects of deindustrialization. Now, at the tail end of the industrial moment in North American history, the story of Cape Breton Island presents an opportunity to reflect on how industrialization and deindustrialization have shaped human experiences. Covering the period between 1860 and the early 2000s, this volume looks at trade unionism, state and cultural responses to deindustrialization, including the more recent pivot towards the tourist industry, and the lived experiences of Indigenous and Black people. Rather than focusing on the separate or distinct nature of Cape Breton, contributors place the island within broad transnational networks such as the financial world of the Anglo-Atlantic, the Celtic music revival, the Black diaspora, Canadian development programs, and more. In capturing the vital elements of a region on the rural resource frontier that was battered by deindustrialization, the histories included here show how the interplay of the state, cultures, and transnational connections shaped how people navigated these heavy pressures, both individually and collectively. --Publisher's description

Nii Ndahlohke (AWE - Art Windsor Essex, 2024)
This catalogue of the Nii Ndahlohke exhibition at Art Windsor Essex (September 26, 2023 – June 25, 2024) features work by First Nations artists exploring the history of forced labour of students at Mount Elgin Industrial School (1851-1946). --WorldCat catalogue record
Keywords: Book; Chippewas of the Thames First Nation; First Nations — Ontario — Residential schools; Indigenous Art and Artists; Indigenous Education; Indigenous History; Indigenous Labour; Mount Elgin Indian Residential School (Muncey, Ont.)

Answers to the Labour Question: Industrial Relations and the State in the Anglophone World, 1880-1945 - Mucciaroni, Gary (University of Toronto Press, 2024)
Since the mid-nineteenth century, public officials, reformers, journalists, and other elites have referred to “the labour question.” The labour question was rooted in the system of wage labour that spread throughout much of Europe and its colonies and produced contending classes as industrialization unfolded. Answers to the Labour Question explores how the liberal state responded to workers’ demands that employers recognize trade unions as their legitimate representatives in their struggle for compensation and control over the workplace. Gary Mucciaroni examines five Anglophone nations – Australia, Canada, Great Britain, New Zealand, and the United States – whose differences are often overlooked in the literature on political economy, which lumps them together as liberal, “market-led” economies. Despite their many shared characteristics and common historical origins, these nations’ responses to the labour question diverged dramatically. Mucciaroni identifies the factors that explain why these nations developed such different industrial relations regimes and how the paths each nation took to the adoption of its regime reflected a different logic of institutional change. Drawing on newspaper accounts, parliamentary debates, and personal memoirs, among other sources, Answers to the Labour Question aims to understand the variety of state responses to industrial unrest and institutional change beyond the domain of industrial relations. --Publisher's description

Colonialism and Capitalism: A New History for the Twenty-First Century - Palmer, Bryan D. (Lorimer, 2024)
V. 1. In the past decade Canadian history has become a hotly contested subject. Iconic figures, notably Sir John A. Macdonald, are no longer unquestioned nation-builders. The narrative of two founding peoples has been set aside in favour of recognition of Indigenous nations whose lands were taken up by the incoming settlers. An authoritative and widely-respected Truth and Reconciliation Commission, together with an honoured Chief Justice of the Supreme Court have both described long-standing government policies and practices as "cultural genocide." Historians have researched and published a wide range of new research documenting the many complex threads comprising the Canadian experience. As a leading historian of labour and social movements, Bryan Palmer has been a major contributor to this literature. In this first volume of a major new survey history of Canada, he offers a narrative which is based on the recent and often specialized research and writing of his historian colleagues. One major theme in this book is the colonial practices of the authorities as they pushed aside the original peoples of this country. While the methods varied, the result was opening up Canada's rich resources for exploitation by the incoming European settlers. The second major theme is the role of capitalism in determining how those resources were exploited, and who would reap the enormous power and wealth that accrued. The first volume of this challenging and illuminating new survey history covers the period that concludes in the 1890s after the creation out of Britain's northern colonies of the semi-autonomous federal Canadian state. ----------------------- V.2. Capitalism and Colonialism: The Making of Modern Canada 1890–1960 continues the examination of our nation’s past through a new lens, incorporating the scholarship of Canadian historians to portray a richly endowed and wealthy but very unequal first-world country. This second volume of Bryan Palmer’s history of Canada covers 1890 to 1960. Weaving together themes that include business, labour, politics, and social history, this account brings the experiences of Indigenous peoples into the centre of the narrative. Canada experienced extraordinary growth during these decades, notably after the Second World War when many Canadians quickly became far better off Yet vast inequalities persisted, Indigenous peoples experienced ongoing and often worsening deprivation, and ordinary people saw little or no real improvement in their lives. These realities set the stage for the interplay of reform, resistance and reaction that followed after 1960. Palmer examines the continuing role of capitalism and colonialism in structuring Canada in the period between 1890 and 1960 from capital’s conflicts and fragile ententes with labour, to the struggles of Indigenous Peoples and francophone Canada, and the changing role of Canadian capital internationally. Relying on the work of scholars who have produced a vast academic literature on a wide range of topics in Canadian history, Bryan Palmer offers a new history of Canada which reflects the knowledge and values of 21st-century Canadians. -- Publisher's description
Keywords: Canada Conditions sociales; Canada Conditions économiques; Canada Economic conditions; Canada Histoire; Canada History; Canada Social conditions

Labour Relations in Canada - Reed, Melanie (TRU Pressbooks [Thompson Rivers University], 2024)
E-textbook that introduces Canadian labour relations, labour history, unions, collective bargaining (including resolving disputes), and grievance arbitration.

Trafficking Harms: Critical Politics, Perspectives and Experiences - Roots, Katrin; De Shalit, Ann; Van der Meulen, Emily (Fernwood Publishing, 2024)
Amid the proliferating scholarship and often sensational public campaigns, Trafficking Harms offers fresh insights and critical analyses. The collection’s four thematic areas — Discourses and Representations; Law and Prosecutions; Policing and Surveillance; Migrant Labour Exploitation — examine an array of issues, including the contested definitions of human trafficking, the application of trafficking law and policy, the conflation of sex work and trafficking, the impacts of anti-trafficking frameworks on racialized communities, questions around “victims” and “traffickers” and much more. Showcasing a mix of scholarly research, public advocacy and first-person narratives, this book is the first of its kind in Canada. The authors include a diverse group of academics, legal advocates, frontline activists who work with migrant and sex-working communities, individuals who have been charged and/or convicted of trafficking offences and those who are directly impacted by trafficking law and policing, such as domestic and migrant sex workers. --Publisher's description
Keywords: Human trafficking Canada; Human trafficking Canada Prevention; Human trafficking Law and legislation Canada; Human trafficking Political aspects Canada; Migrant labor Canada

Shifting Gears: Canadian Autoworkers and the Changing Landscape of Labour Politics - Ross, Stephanie; Savage, Larry (UBC Press, 2024)
In the decades following the Second World War, autoworkers were at the forefront of the labour movement. Their union urged members to rally in the streets and use the ballot box to effect change for all working-class people. But by the turn of this century, the Canadian Auto Workers union had begun to pursue a more defensive political direction. "Shifting Gears" traces the evolution of CAW strategy from transformational activism to transactional politics. Class-based collective action and social democratic electoral mobilization gave way to transactional partnerships as relationships between the union, employers, and governments were refashioned. This new approach was maintained when the CAW merged with the Communications, Energy and Paperworkers Union in 2013 to create Unifor, Canada’s largest private-sector union. Stephanie Ross and Larry Savage explain how and why the union shifted its political tactics, offering a critical perspective on the current state of working-class politics. -- Publisher's description
Keywords: CAW-Canada History; Labor unions Political activity Canada History; Syndicats Activité politique Canada Histoire; Unifor (Labor union) History

The Trudeau Record: Promise v. Performance: 25 Independent Experts Assess Key Issues from Housing to Health Care - Scott, Katherine; Macdonald, Laura; Trew, Stuart (Lorimer, 2024)
In this book, independent experts analyze the performance of Justin Trudeau’s years in power in over 20 important areas of government policy. The record of what has been done–and what hasn’t–will surprise even well-informed readers. The focus is on six policy areas: Indigenous rights, governance and housing; the environment and energy; taxes and spending; healthcare and social benefits; foreign policy, immigration, and trade; and social policy including drug reform, labour rights, and racism. Editors Katherine Scott, Laura Macdonald, and Stuart Trew of the Canadian Centre for Policy Alternatives have recruited Canada’s most knowledgeable experts in their areas to contribute to this volume. -- Publisher's description
Keywords: Administration publique (Science) Canada Évaluation; Canada Politics and government 2015- Evaluation; Canada Politics and government 21st century Evaluation; Canada Politique et gouvernement 21e siècle Évaluation; Public administration Canada Evaluation; Trudeau, Justin

Wînipêk: Visions of Canada from an Indigenous Centre - Sinclair, Niigaanwewidam James (McClelland & Stewart, 2024)
The story of a people told through the story of a city. Niigaan Sinclair is often accused of being angry in his columns. But how can he not be? In a collection of writing that spans the discovery of hundreds of unmarked graves at residential school sites, the murder of young Indigenous girls, and the indifference towards the basic human rights of his family members, this book is inspired by his award-winning columns 'from the centre.' Niigaan examines the state of urban Indigenous life and legacy. At a crucial moment in Canada's reckoning with its crimes against the Indigenous peoples of the land, one of our most essential writers begins at the centre, capturing a web spanning centuries of community, art, and resistance. Based on years' worth of columns in the Winnipeg Free Press, CBC, and elsewhere, Niigaan Sinclair delivers a defining essay collection on the resilience of Indigenous peoples. Here, we meet the creators, leaders, and everyday people preserving the beauty of their heritage one day at a time. But we also meet the ugliest side of settler colonialism, and the communities who suffer most from its atrocities. Sinclair uses the story of Winnipeg to illuminate the reality of Indigenous life all over what is called Canada. This is a book that demands change and celebrates those fighting for it, that reminds us of what must be reconciled and holds accountable those who must do the work. It's a book that reminds us of the power that comes from loving a place, even as that place is violently taken away from you, and the magic of fighting your way back to it. -- Publisher's description
Keywords: Canada; Canada Ethnic relations; Canadian essays; Colonialisme de peuplement Canada; Essays; Ethnic relations; Indigenous peoples; Indigenous peoples Canada; Indigenous peoples Canada Social conditions; Indigenous peoples Canada Social life and customs; Indigenous peoples Social conditions; Indigenous peoples Social life and customs; Peuples autochtones Canada; Peuples autochtones Canada Conditions sociales; Peuples autochtones Canada Mœurs et coutumes; Settler colonialism; Settler colonialism Canada

The Rough Poets: Reading Oil-Worker Poetry - Unrau, Melanie Dennis (McGill-Queen's rural, wildland, and resource studies series, 2024)
Oil workers are often typecast as rough: embodying the toxic masculinity, racism, consumerist excess, and wilful ignorance of the extractive industries and petrostates they work for. But their poetry troubles these assumptions, revealing the fear, confusion, betrayal, and indignation hidden beneath tough personas. The Rough Poets presents poetry by workers in the Canadian oil and gas industry, collecting and closely reading work published between 1938 and 2019: S.C. Ells’s Northland Trails, Peter Christensen’s Rig Talk, Dymphny Dronyk’s Contrary Infatuations, Mathew Henderson’s The Lease, Naden Parkin’s A Relationship with Truth, Lesley Battler’s Endangered Hydrocarbons, and Lindsay Bird’s Boom Time. These writers are uniquely positioned, Melanie Dennis Unrau argues, both as petropoets who write poetry about oil and as theorists of petropoetics with unique knowledge about how to make and unmake worlds that depend on fossil fuels. Their ambivalent, playful, crude, and honest petropoetry shows that oil workers grieve the environmental and social impacts of their work, worry about climate change and the futures of their communities, and desire jobs and ways of life that are good, safe, and just. How does it feel to be a worker in the oil and gas industry in a climate emergency, facing an energy transition that threatens your way of life? Unrau takes up this question with the respect, care, and imagination necessary to be an environmentalist reader in solidarity with oil workers. -- Publisher's description
Keywords: Canadian poetry (English) 20th century History and criticism; Canadian poetry (English) 21st century History and criticism; Canadian poetry 20th century History and criticism; Canadian poetry 21st century History and criticism; Literary criticism; Petroleum industry and trade in literature

Harvesting Freedom: The Life of a Migrant Worker in Canada - Allahdua, Gabriel; Dunsworth, Edward (Between the Lines, 2023)
In this singular firsthand account, a former migrant worker reveals a disturbing system of exploitation at the heart of Canada’s farm labour system. When Gabriel Allahdua applied to the Seasonal Agricultural Worker Program in Canada, he thought he would be leaving his home in St. Lucia to work in a country with a sterling human rights reputation and commitment to multiculturalism. Instead, breakneck quotas and a culture of fear dominated his four years in a mega-greenhouse in Ontario. This deeply personal memoir takes readers behind the scenes to see what life is really like for the people who produce Canada’s food. Now, as a leading activist in the migrant justice movement in Canada, Gabriel is fighting back against the Canadian government to demand rights and respect for temporary foreign labourers. Harvesting Freedom shows Canada’s place in the long history of slavery, colonialism, and inequality that has linked the Caribbean to the wider world for half a millennium--but also the tireless determination of Caribbean people to fight for their freedom. -- Publisher's description
Keywords: Agricultural laborers, Foreign; Agricultural laborers, Foreign Canada Biography; Allahdua, Gabriel; Autobiographies; Biographies; Canada; Foreign workers, West Indian; Foreign workers, West Indian Canada History; History

Unpaid Work in Nursing Homes: Flexible Boundaries - Armstrong, Pat (Policy Press, 2023)

Les plateformes de travail numériques: polygraphie d'un nouveau modèle organisationnel - Baril, Émile; Bernier, Jean; Busso, Mariana; Jalette, Patrice; Vultur, Mircea (Collection Sociologie contemporaine, 2023)
Au cours des dix à quinze dernières années, les plateformes de travail numériques se sont fortement développées dans différents secteurs d'activité, comme le transport de personnes et la livraison de repas, ou sous forme d'une multitude de microtâches réalisées en ligne. Des centaines de milliers de travailleurs et travailleuses se retrouvent actuellement dans cette nouvelle gig economy. Quelle est l'importance des plateformes numériques et quelle est leur signification pour le monde du travail ? Menacent-elles de supplanter les relations d'emploi traditionnelles fondées sur des contrats légalement réglementés ? Sont-elles compatibles avec les promesses d'autonomie et de liberté qui constituent leur image de marque ? Quelle est la situation vécue par les travailleurs et les travailleuses des plateformes ? Cet ouvrage tente de répondre à ces interrogations selon une perspective à la fois internationale et multidisciplinaire. Sociologues, économistes et juristes, spécialistes de la question, dressent un portrait saisissant de l'économie des plateformes numériques, analysent les effets de leur développement sur les manières de vivre le travail et soulèvent des nouveaux questionnements et enjeux sociaux pour l'action publique
Keywords: Actes de congrès; Marché du travail Effets des innovations technologiques 2000-...; Organisation du travail Effets des innovations technologiques 2000-...; Travail précaire 2000-...; Uberisation Société; Économie numérique 2000-...

Seeking Social Democracy: Seven Decades in the Fight for Equality - Broadbent, Ed; Abele, Frances; Sas, Jonathan; Savage, Luke (ECW Press, 2023)
The first full-length treatment of Ed Broadbent's ideas and remarkable seven-decade engagement in public life. Ed Broadbent is unique among living political leaders of international stature in offering a fully developed analysis of social democracy and its relevance in the 21st century. His career as a political philosopher, activist, and politician and his conversations with contemporaries such as Willy Brandt, Pierre Elliot Trudeau, Fidel Castro, and Mikhail Gorbachev inform his analysis of the struggles for social justice in the long 20th century. Having come to the socialist and social democratic traditions by way of academic study, Broadbent tested and tempered his ideas in the great postwar struggles over social rights, gender and racial equality, workers' rights, the containment of capital, and reversing the commodification of private life. The book explores the roots of his egalitarianism and the formation of his social democratic ideas, Broadbent's engaged internationalism and relationship with key historical figures, and his experiences and reflections in practical politics and pursuit of government across several of the most momentous decades in the history of Canada. He was a Member of Parliament for over two decades and was, for most of this period, leader of the New Democratic Party. He remains to this day an important social democratic voice in the public debates of the nation. Part political history, part intellectual biography, part manifesto for social democracy this first-ever full-length treatment of Broadbent's thought will be animated in dialogue with three collaborators from different generations, each similarly immersed in the history of social democratic ideas--the result being a fresh analysis of social democracy, Canadian politics, and a lively contribution to current debates and dilemmas. -- Publisher's description
Keywords: Autobiographies; Broadbent, Ed, 1936-; Canada; Canada Politics and government; Canada Politique et gouvernement; Equality; Ottawa authors, musicians, etc; Politics and government; Socialism; autobiographies (literary works)

Lost in Cabbagetown: A Memoir of Surviving Boyhood in 1960s Toronto - Burke, Terry (Dundurn Press, 2023)
A poignant memoir of a rough-and-tumble boyhood on the streets of Toronto's Cabbagetown. When the Burke family left Ireland in 1959, they thought they were leaving the trials and tribulations of the Dublin slums behind. Instead, Molly, Bill, and their nine children found the same poverty and hardship awaiting them in the east end of Toronto. For their sixth-born son, Terry, growing up in Cabbagetown was a daily struggle to survive. Whether it was the bullies on the street or the gangs in Regent Park, fights were an everyday occurrence. School should have been a refuge, but some of the priests and nuns were more terrifying than any street bully. The only escape for Terry was to find his way down into the Don Valley, where he could search the river for muskrat or imagine himself escaping on one of the freight trains, chucking north, up the valley floor. But a childhood in Cabbagetown didn't seem to last very long. Forced into adulthood and driven from home in the wake of tragedy, Terry struggled to survive on his own and find a way back to his family. In this touching memoir, Terry Burke tells a poignant story of hunger, pain, love, and loss, and the enduring bonds of family. --Publisher's description
Keywords: Autobiographies; Autobiography; Biographies; Burke, Terry, 1947- Childhood and youth; Burke, Terry, 1947- Enfance et jeunesse; Cabbagetown (Toronto, Ont.) Biographies; Cabbagetown (Toronto, Ont.) Biography; Ontario Toronto Cabbagetown; autobiographies (literary works)

Feminism's Fight: Challenging Politics and Policies in Canada Since 1970 - Cameron, Barbara; Luxton, Meg (UBC Press, 2023)
Feminism's Fight explores and assesses feminist strategies to advance gender justice through Canadian federal policy from the 1970s to the present. It tells the crucial story of a transformation in how feminism has been treated by governments and asks how new ways of organizing and emerging alliances can advance a feminist agenda of social and economic equality. This timely collection examines the ideas that feminists have put forward in pursuit of the goal of equality and traces the shifting frameworks employed by governments in response. The authors evaluate changing government orientations through the 1970s to 2020, revealing the negative impact on women's lives and the challenges posed for feminists. The COVID-19 pandemic has exacerbated the sexism, misogyny, and related systemic inequalities that remain widespread. Yet it has also revived feminist mobilization and animated calls for a new and comprehensive equality agenda for Canada. Feminism's Fight asks two key questions: What are the lessons from feminist engagement with federal government policy over fifty years? And what kinds of transformative policy demands will achieve the feminist goal of social and economic equality?-- Publisher's description
Keywords: Canada; Feminism Canada History; Femmes Activité politique Canada; Femmes Canada Conditions sociales; Femmes Droit Canada; Femmes Droits Canada; Femmes Politique gouvernementale Canada; Féminisme Canada Histoire; SOCIAL SCIENCE / Women's Studies; Women Canada Social conditions; Women Government policy; Women Government policy Canada; Women Legal status, laws, etc; Women Legal status, laws, etc. Canada; Women Political activity; Women Political activity Canada; Women Social conditions; Women's rights; Women's rights Canada

New Essays in Women's History - Chambers, Lori; Sangster, Joan (Essays in the History of Canadian Law, 2023)
Drawing on engaging case studies, Essays in History of Canadian Law brings the law to life. The contributors to this collection provide rich historical and social context for each case, unravelling the process of legal decision-making and explaining the impact of the law on the people involved in legal disputes. Examining the law not simply as legislation and institutions, but as discourse, practice, symbols, rhetoric, and language, the chapters show the law as both oppressive and constraining and as a point of contention and means of resistance. This collection presents new approaches and concerns, as well as re-examinations of existing themes with new evidence and modes of storytelling. Contributors cover many thematic areas, from criminal to labour, civil, administrative, and human rights law, spanning English and French Canada, and ranging from the mid-eighteenth century to the late twentieth century. The legal cases vary from precedent-setting cases to lesser-known ones, from those driven by one woman’s quest for personal justice to others in which state actors dominate. Bringing to light how the people embroiled in these cases interacted with the legal system, the book reveals the ramifications of a legal system characterized by multiple layers of inequality. -- Publisher's description
Keywords: Canada; Droit Canada Histoire; History; Law; Law Canada History; Women Legal status, laws, etc; Women Legal status, laws, etc. Canada History

United in Action: The History of the Union of Canadian Transportation Employees - Clavette, Ken (Union of Canadian Transportation Employees, 2023)
Despite the centrality of public sector trade unionism in Canada today, its history remains largely unknown. Our attention remains fixed on the classic male proletarians of the industrial revolution. It might surprise you that the history of public sector unionism spans the 20th century, reaching back to the 19th century. United in Action tells the fascinating story of the Union of Canadian Transportation Employees (UCTE), one of five founding components of the Public Service Alliance of Canada (PSAC) in 1966. --Foreword

Enduring Work: Experiences with Canada's Temporary Foreign Worker Program - Connelly, Catherine E. (McGill-Queen's University Press, 2023)
If you believed most of what's said about the Canadian Temporary Foreign Worker program, you might naturally assume that there is a trade-off between workers' poor experiences with the program and employers' significant benefits. In fact, neither is quite true: the experiences of workers are, in reality, far worse than is commonly acknowledged, while employers are not reaping as much benefit as the public might suppose. In Enduring Work Catherine Connelly draws on over one hundred interviews with people connected to different aspects of this program, analyzing their experiences from the perspective of organizational behaviour and human resources management. She compares the lived reality of agricultural workers, in-home caregivers, and low- and high-wage workers, showing how and why each group is vulnerable to mistreatment, albeit in different ways. She further explores how employment agencies and immigration consultants contribute to program abuses. Critically, Enduring Work provides the perspectives of employers, distinguishing between the reluctant users of the program who follow the rules and the reckless users who do not. Groundbreaking in its analysis of an issue very much in the news, Enduring Work unpacks the harms within Canada's Temporary Foreign Worker program and offers nuanced strategies to improve it. -- Publisher's description
Keywords: BUSINESS & ECONOMICS / Labor / General; Canada; Comportement organisationnel Canada; Foreign workers Canada Social conditions; Foreign workers Government policy; Foreign workers Government policy Canada; Foreign workers Social conditions; Organizational behavior; Organizational behavior Canada; Personnel Direction Canada; Personnel management; Personnel management Canada; Programme des travailleurs étrangers temporaires (Canada); Temporary Foreign Workers Program (Canada); Travailleurs étrangers Canada Conditions sociales; Travailleurs étrangers Politique gouvernementale Canada

Defending Animals: Finding Hope on the Front Lines of Animal Protection - Coulter, Kendra (MIT Press, 2023)
An in-depth look at the urgent struggle to protect animals from harm, cruelty, injustice, extinction, and their greatest threat—us. Beloved dogs and cats. Magnificent horses and mountain gorillas. Curious chickens. What do we actually do to protect animals from harm—and is it enough? This engaging book provides a unique and eye-opening exploration of the world of animal protection as people defend diverse animals from injustice and cruelty. From the streets of major US cities to remote farms and tropical forests, Defending Animals is a gritty and moving portrait of the real work of animal protection that takes place in communities, courtrooms, and boardrooms. Globally recognized expert Kendra Coulter takes readers across the different landscapes of animal protection to meet people and animals of all kinds, from cruelty investigators to forensic veterinarians, wildlife rehabilitators and conservation leaders to animal lawyers and entrepreneurs, each working in their own ways to defend animals. Bringing unparalleled research and a distinct and nuanced analytical viewpoint, Defending Animals shows that animal protection is not only physical, intellectual, and emotional work but also a labor so rooted in empathy and care that it just might bridge the vast divide between polarized people and help create a more humane future for us all. -- Publisher's description
Keywords: Animal rights; Animal welfare; Animaux Droits; Bien-être Aspect psychologique; Documents d'information; Human-animal relationships; Informational works; Relations homme-animal; Well-being Psychological aspects

On Class - Dundas, Deborah (Field Notes, 2023)
Deborah Dundas is a journalist who grew up poor and almost didn’t make it to university. In On Class, she talks to writers, activists, those who work with the poor and those who are poor about what happens when we don’t talk about poverty or class—and what will happen when we do. Growing up poor, Deborah Dundas knew what it meant to want, to be hungry, and to long for social and economic dignity; she understood the crushing weight of having nothing much expected of you. But even after overcoming many of the usual barriers faced by lower- and working-class people, she still felt anxious about her place, and even in relatively safe spaces reluctant to broach the subject of class. While new social movements have generated open conversation about gender and racism, discussions of class rarely include the voices of those most deeply affected: the working class and poor. On Class is an exploration of the ways in which we talk about class: of who tells the stories, and who doesn’t, which ones tend to be repeated most often, and why this has to change. It asks the question: What don’t we talk about when we don’t talk about class? And what might happen if, ﬁnally, we did? --Publisher's description

Gigs, Hustles, and Temps: How Precarious Work Lowers Wages, Makes Canadians Poorer and Deprives Workers of Rights- While It Empowers and Enriches Big Corporations - Foster, Jason (Lorimer, 2023)
In this profoundly troubling and incisive look at the state of work and welfare in Canada, Jason Foster reveals the long, often-hidden process that has left our jobs less secure, our livelihoods more uncertain, and the pockets of Canada’s wealthy fatter than ever. This phenomenon, the rise of “precarious work,” touches the entire economy and contributes to levels of income inequality unseen since the early 20th century. Our world is less secure than it has been in generations. Gigs, Hustles, and Temps describes how we got here, and why. Jobs across the economy are increasingly more precarious, and they share similar characteristics: impermanence, little to no benefits, and no union representation. Uber, Starbucks and Amazon have led the way. Governments are contracting out more labour than ever before. Tech companies hire workers on “flexible” contracts without the prospect of long-term employment. Migrant workers, too, are working without a safety net, figuratively and literally. No matter where you fall on the socio-economic ladder, your life is probably more precarious than your parents’ once was. Foster offers insights into the many consequences of our increasingly precarious world. He also details some of the less obvious repercussions of precarious work, including its contribution to the crisis of mental and public health across Canada. Foster argues that the rise of precarious work is more a “return to normal” for capitalist economies. But there is a flip side: advances in worker welfare have come through solidarity, struggle, and negotiation with the forces currently promoting precarious work across Canada's economy. Things don’t have to be the way they are. Gigs, Hustles, and Temps is a comprehensive, accessible, and essential guidebook on the road to a better world. --Publisher's description

Regards croisés sur la grève d'Amoco à Hawkesbury: une histoire ouvrière de l'Ontario français - Gagnon, Andréane (Collection Agora, 2023)
La grève d’Amoco de 1980, lors de laquelle s’est soulevée la population ouvrière de Hawkesbury, marque un temps fort de revendication franco-ontarienne, aujourd’hui pratiquement tombé dans l’oubli. Trois personnes qui ont, chacune à sa façon, pris part à la grève – Serge Denis, politologue, Richard Hudon, animateur social, et Jean Marc Dalpé, dramaturge et écrivain – replongent ici dans leurs souvenirs pour mettre en lumière la conjoncture sociopolitique qui a mené à la mobilisation des travailleurs et travailleuses de la région.Fruit d’un travail de terrain engagé, cet ouvrage, nourri par les témoignages et par de nombreux documents d’archives, démontre que la grève d’Amoco n’était pas une grève comme les autres. Microcosme du contexte sociohistorique dans lequel il s’inscrit, et bien qu’il consiste avant tout en une lutte ouvrière, le mouvement a permis à une communauté minoritaire doublement défavorisée, économiquement et politiquement, de s’affirmer en s’appropriant une nouvelle plateforme pour s’exprimer : le syndicalisme.Les combats de l’Ontario français pour la défense de ses droits se sont depuis déplacés vers les tribunaux, mais cette étude rappelle que sa culture politique s’est d’abord construite dans la rue et qu’il faut, à ce titre, assurer la transmission de ce pan de l’histoire populaire. -- Résumé de l'éditeur
Keywords: 1900-1999; Amoco Fabrics Strike, Hawkesbury, Ont., 1980; Canadiens français Ontario Conditions économiques 20e siècle; Grève de l'Amoco Fabrics, Hawkesbury, Ont., 1980; Grèves et lock-out Textiles et tissus Industrie et commerce Ontario Histoire; Hawkesbury (Ont.) Histoire 20e siècle; History; Labor disputes; Labor disputes Ontario Hawkesbury History; Ontario; Ontario Hawkesbury; Strikes and lockouts Textile industry; Strikes and lockouts Textile industry Ontario History; Textile workers Labor unions; Textile workers Labor unions Ontario History 20th century; Travail Conflits Ontario Hawkesbury Histoire; Travailleurs du textile Syndicats Ontario Histoire 20e siècle

Essential Work, Disposable Workers: Migration, Capitalism, and Class - Henaway, Mostafa (Fernwood Publishing, 2023)
Recent years have seen massive waves of migration from the Middle East, Latin America, and Africa to Europe and North America and a corresponding rise in anti-immigrant, far-right populism in host countries, placing the question of migration at the forefront of politics and social movements. Henaway seeks to understand these patterns through contextualizing global migration within a history of global capitalism, class formation, and the financialization of migration. As globalization intensifies, a neoliberal labour market forces workers around an unevenly developed world to compete for wages--not through foreign investment and outsourcing, but through an increasingly mobile working class. Henaway rejects the right-wing response of restricting or "managing" immigration through temporary worker programs and instead suggests that stopping a race to the bottom for all working people involves building solidarity with the struggles of these migrants for decent work and justice. Through examining the organizing strategies of migrant workers at giants like Amazon and Wal-Mart as well as discount retailers like Dollarama and Sports Direct, the immense power and agency of precarious workers in global companies like UBER or Airbnb, the successful resistance of taxi drivers or fast food workers around the world, and the contemporary mass labour movement organized by new unions and workers' centres, Henaway shows how migrant demands and strategies can help shape radical working class politics in North America and Europe. --Publisher's description
Keywords: Globalization; Labor movement; Migrant labor; Precarious employment; SOCIAL SCIENCE / Emigration & Immigration; Social classes

Gin, Turpentine, Pennyroyal, Rue - Higdon, Christine (ECW Press, 2023)
Four working-class Vancouver sisters, still reeling from the impact of World War I and the pandemic that stole their only brother, are scraping by but attempting to make the most of the exciting 1920s. Gin, Turpentine, Pennyroyal, Rue is a love story — but like all love stories, it’s complicated … Morag is pregnant; she loves her husband. Georgina can’t bear hers and dreams of getting an education. Harriet-Jean, still at home with her opium-addicted mother, is in love with a woman. Isla’s pregnant too — and in love with her sister’s husband. Only one soul knows about Isla’s pregnancy, and it isn’t the father. When Isla resorts to a back-street abortion and nearly dies, Llewellyn becomes hellbent on revenge. But can revenge lead to anything but disaster for a man like Llew — a policeman tangled up in running rum to Prohibition America? Gin, Turpentine, Pennyroyal, Rue is immersed in the complex political and social realities of the 1920s and, not-so ironically, of the 2020s: love, sex, desire, police corruption, abortion, addiction, and women wanting more. Beautifully written, with a loveable cast of characters, this novel is a tender account of love that cannot be acknowledged, of loss and regret, risk and defiance, abiding friendship, and the powerful bonds of chosen family. --Publisher's description

Tipping Point for Advanced Capitalism: Class, Class Consciousness and Activism in the “Knowledge Economy” - Livingstone, D. W. (David W.) (Fernwood Publishing, 2023)
The aim: to rejuvenate study and understanding of class relations in advanced capitalism. The book is an original synthesis of theorizing about class grounded in the production process, revealing a distinct tripartite class structure of owners, managers and non-managerial workers. Changes since the 1980s are traced and significant increases of non-managerial professional employees and middle managers are documented beyond any prior empirical research. Higher levels of oppositional and revolutionary class consciousness are conceptualized in terms of support for rights of capital and labour, and the extent of their expression in employed labour forces is estimated in terms only previously attempted briefly in the wake of 1960s protest movements. Connections between objective class positions and levels of class consciousness are analyzed in unprecedented depth; the solidary hegemonic consciousness of corporate capitalists, declining pro-capital oppositional consciousness among other employers and upper managers, and the pro-labour oppositional consciousness of pluralities of non-managerial workers (including professional employees) are all documented more fully than in prior studies. Strategic connections between class, class consciousness and issues of poverty and global warming are identified. Contending class forces’ engagement in actions toward an imminent system tipping point are uniquely traced. Main sources of evidence are all the national surveys in G7 and Nordic countries in the 1980s that provide relevant data, and the author’s unique Canadian national surveys in 2004, 2010 and 2016, supplemented by interviews with class leaders. A website encourages further class-based studies of advanced capitalism with similar measures to aid ecological sustainability and economic democracy. --Publisher's description (WorldCat record)
Keywords: Capitalism; Class consciousness; Knowledge economy; Social classes

Brightening My Corner: A Memoir of Dreams Fulfilled - Malloy, Ruth Lor (Barclay Press, 2023)
Ruth Lor started life Chinese in a small Canadian town. Driven by curiosity, a yen for adventure, and a wish to be useful, she managed to spend her life fighting racial discrimination. In Washington, D.C., she fought segregation by sitting in at "whites only" restaurants and swimming in "whites only" pools. She planted trees in Mexico, painted houses for Inuit victims of tuberculosis in the Canadian Arctic, and helped distribute food to refugees in Taiwan. When China reopened to foreigners after its Cultural Revolution, Ruth wrote the first English-language guidebook about that enormous country.Ruth covered the war in Vietnam, crossed Himalayan passes on foot and horseback, and faced down an angry elephant in Africa. She worked in India to reduce prejudice against that country's caste of transgender hijras. She and her husband housed refugees in their Maryland home after the Vietnam War ended.Now in her nineties, Ruth still works with refugees, and she still brightens her corner of the world, wherever she is. --Publisher's description

Cleaning Up: Portuguese Women's Fight for Labour Rights in Toronto - Miranda, Susana P.; Iacovetta, Franca (Between the Lines, 2023)
This fascinating book uncovers the little-known, surprisingly radical history of the Portuguese immigrant women who worked as night-time office cleaners and daytime “cleaning ladies” in postwar Toronto. Drawing on union records, newspapers, and interviews, feminist labour historians Susana P. Miranda and Franca Iacovetta piece together the lives of immigrant women who bucked convention by reshaping domestic labour and by leading union drives, striking for workers’ rights, and taking on corporate capital in the heart of Toronto’s financial district. Despite being sidelined within the labour movement and subjected to harsh working conditions in the commercial cleaning industry, the women forged critical alliances with local activists to shape picket-line culture and make an indelible mark on their communities. Richly detailed and engagingly written, Cleaning Up is an archival treasure about an undersung piece of working-class history in urban North America. --Publisher's description

From Consent to Coercion: The Continuing Assault on Labour - Panitch, Leo; Evans, Bryan M.; Fanelli, Carlo; Swartz, Donald; Gindin, Sam (University of Toronto Press, 2023)
From Consent to Coercion examines the increasing assault against trade union rights and freedoms in Canada by federal and provincial governments. Centring the struggles of Canadian unionized workers, this book explores the diminution of the welfare state and the impacts that this erosion has had on broader working-class rights and standards of living. The fourth edition witnesses the passing of an era of free collective bargaining in Canada--an era in which the state and capital relied on obtaining the consent of workers and unions to act as subordinates in Canada's capitalist democracy. It looks at how the last twenty years have marked a return to a more open reliance of the state and capital on coercion--on force and on fear--to secure that subordination. From Consent to Coercion considers this conjuncture in the Canadian political economy amid growing precarity, poverty, and polarization in an otherwise indeterminate period of austerity. This important edition calls attention to the urgent task of rebuilding and renewing socialist politics--of thinking ambitiously and meeting new challenges with unique solutions to the left of social democracy. -- Publisher's description
Keywords: Canada; Collective bargaining; Collective bargaining Canada History; History; Labor unions; Labor unions Canada History; Labor unions Law and legislation; Labor unions Law and legislation Canada History

Travailler moins ne suffit pas (Collection Polémos, 2023)
« Est-ce qu’il suffit de travailler moins pour retrouver l’équilibre entre les différentes facettes de nos vies surchargées ? La réduction du temps de travail est une revendication de longue date pour améliorer notre qualité de vie. En passant moins de temps au travail, nous pourrions enfin reprendre notre souffle et consacrer plus de temps à nos relations sociales, aux tâches domestiques ou encore pour s’engager dans la communauté. Mais est-ce que notre travail nous comble et contribue au bien commun ? Julia Posca interroge notre rapport au travail, explore sa nature et envisage les voies à emprunter pour lui redonner un sens. À la dystopie dans laquelle nous nous enfonçons toujours un peu plus, nous pourrions opposer l’utopie du travail « démarchandisé, démocratisé et dépollué ». Une invitation à revoir l’organisation du travail pour qu’il réponde d’abord aux besoins les plus « authentiques » : assurer à tous et toutes une existence digne, entretenir des relations riches, léguer une vie bonne aux futures générations. »--Quatrième de couverture
Keywords: Hours of labor; Industrial sociology; Methods engineering; Organisation du travail; Réduction du temps de travail; Sociologie industrielle; Syndicalism; Syndicalisme; Travail Aspect psychologique; Work Psychological aspects

Countercurrents: Women's Movements in Postwar Montreal - Ricci, Amanda (Studies on the history of Quebec, 2023)
In the decades following the Second World War, women from all walks of life became increasingly frustrated by the world around them. Drawing on long-standing political traditions, these women bound together to revolutionize social norms and contest gender inequality. In Montreal, women activists inspired by Red power, Black Power, and Quebec liberation, among other social movements, mounted a multifront campaign against social injustice. Countercurrents looks beyond the defining "waves" metaphor to write a new history of feminism that incorporates parallel social movements into the overarching narrative of the women's movement. Case studies compare and reflect on the histories of the Quebec Native Women's Association, the Congress of Black Women, the Front de libération des femmes du Québec, various Haitian women's organizations, and the Collectif des femmes immigrantes du Québec and the political work they did. Bringing to light previously overlooked archival and oral sources, Amanda Ricci introduces a new cast of characters to the history of feminism in Quebec. The book presents a unique portrait of the resurgence of feminist activism, demonstrating its deep roots in Indigenous and Black communities and a transnational scope with wide-ranging inspirations and preoccupations. Advancing cross-cultural perspectives on women's movements, Countercurrents looks to the history of women's activism in Montreal and finds new ways of defining feminist priorities and imagining feminist futures. -- Publisher's description
Keywords: 1900-1999; Feminism; Feminism Québec (Province) Montréal History 20th century; Femmes Activité politique Québec (Province) Montréal Histoire 20e siècle; Féminisme Québec (Province) Montréal Histoire 20e siècle; History; Mouvements sociaux Québec (Province) Montréal Histoire 20e siècle; Québec Montréal; SOCIAL SCIENCE / Women's Studies; Social movements; Social movements Québec (Province) Montréal History 20th century; Women Political activity; Women Political activity Québec (Province) Montréal History 20th century

Building a Better World: An Introduction to the Labour Movement in Canada - Ross, Stephanie; Savage, Larry (Fernwood Publishing, 2023)
This fourth edition...offers a comprehensive introductory overview of Canada’s labour movement. The book explores why workers form unions; assesses their organization and democratic potential; examines issues related to collective bargaining, grievances and strike activity; charts the historical development of labour unions; and describes the gains unions have achieved for their members and all working people. This new and expanded edition also analyzes the challenges facing today’s labour movement as a result of COVID-19 and the strategies being developed to overcome them. --Publisher's description
Keywords: Canada; Labor movement; Labor movement Canada; Labor unions; Labor unions Canada; Mouvement ouvrier Canada; Syndicats Canada

Forgiveness - Sakamoto, Mark (Playwrights Canada Press, 2023)
Mitsue Sakamoto and Ralph MacLean have both suffered tremendous loss during WWII: Mitsue as a survivor of a Japanese Canadian internment camp, and Ralph as a prisoner in a Japanese POW camp. In order to rebuild their lives and their families after the war, Ralph and Mitsue must find the grace and generosity necessary to forgive those who have wronged them. Their paths eventually cross in 1968 when Mitsue's son and Ralph's daughter begin dating, and Ralph is invited to Mitsue's home for dinner.This soaring adaptation of Mark Sakamoto's award-winning memoir affirms the power of forgiveness and shows us that in our challenging times characterized by political divisiveness, xenophobia, and race hatred, the story of Mitsue and Ralph's personal triumphs over hatred, injustice, violence, and bigotry remains vitally relevant and urgently necessary. -- Publisher's Description
Keywords: 1939-1945; Adaptations scéniques; Biographical drama; Canada; Canadiens d'origine japonaise Relogement et internement forcés, 1941-1949 Théâtre; Canadiens d'origine japonaise Théâtre; Drama; Families; Guerre mondiale, 1939-1945 Prisonniers et prisons des japonais Théâtre; Historical drama; Japan; Japanese Canada Drama; Japanese Canada Forced removal and internment, 1942-1945 Drama; Japanese Canadians Drama; Japanese Canadians Forced relocation and internment, 1941-1949 Drama; MacLean, Ralph, 1922- Famille Théâtre; MacLean, Ralph, 1922- Family Drama; Prisoners of war; Prisoners of war Canada Drama; Prisoners of war Japan Drama; Prisonniers de guerre Canada Théâtre; Prisonniers de guerre Japon Théâtre; Sakamoto, Mark, 1977- Famille Théâtre; Sakamoto, Mark, 1977- Family Drama; Sakamoto, Mitsue, 1920- Famille Théâtre; Sakamoto, Mitsue, 1920- Family Drama; Theatrical adaptations; Théâtre; Théâtre biographique; Théâtre historique; World War, 1939-1945 Prisoners and prisons, Japanese Drama

Conscripted to Care: Women on the Frontlines of the COVID-19 Response - Smith, Julia (McGill-Queen's University Press, 2023)
With the vast majority of healthcare and social workers identifying as women, the vanguard of the COVID-19 response was distinctly gendered. In Conscripted to Care, Julia Smith introduces us to the women who faced the worst effects of the pandemic and the inequities it exposed. Through clear prose and fascinating critical analysis, she documents their largely unseen contributions and sacrifices, both professionally and domestically. Drawing on interviews and focus groups with nearly 200 women from a range of backgrounds and occupations, Smith reveals how structural inequality put women on the frontlines of the pandemic response, yet with inadequate resources and little voice in decision-making. Women not only shouldered the triple burden of paid work, unpaid care, and mental load, but also increased emotional labour. While some women were categorized as "essential," others remained in the shadows--all faced unsustainable workloads, moral distress, and burnout, while continuing to demand better services for those in their care. An analysis of Canada's COVID-19 response from the perspective of those who staffed it, Conscripted to Care presents crucial lessons for those interested in public health and how it relates to gender and economic equality, as well as public policy. -- Publisher's description
Keywords: Aidantes naturelles Canada; COVID-19 Pandemic, 2020-2023 Social aspects Canada; Canada; Equality Health aspects; Equality Health aspects Canada; Femmes Canada Conditions sociales 21e siècle; Femmes Canada Conditions économiques 21e siècle; Medical personnel Canada; Pandémie de COVID-19, 2020-2023 Aspect social Canada; Personnel féminin Canada Conditions sociales 21e siècle; Personnel féminin Canada Conditions économiques 21e siècle; Personnel médical Canada; Public health; Public health Canada; Santé publique Canada; Since 2000; Social aspects; Women Canada Economic conditions 21st century; Women Canada Social conditions 21st century; Women Economic conditions; Women Social conditions; Women caregivers Canada; Women employees Canada Economic conditions 21st century; Women employees Canada Social conditions 21st century; Women employees Economic conditions; Women employees Social conditions; Égalité (Sociologie) Aspect sanitaire Canada

Care Activism: Migrant Domestic Workers, Movement-Building, and Communities of Care - Tungohan, Ethel (NWSA / UIP First Book Prize Series, 2023)
Care activism challenges the stereotype of downtrodden migrant caregivers by showing that care workers have distinct ways of caring for themselves, for each other, and for the larger transnational community of care workers and their families. Ethel Tungohan illuminates how the goals and desires of migrant care worker activists goes beyond political considerations like policy changes and overturning power structures. Through practices of subversive friendships and being there for each other, care activism acts as an extension of the daily work that caregivers do, oftentimes also instilling practices of resistance and critical hope among care workers. At the same time, the communities created by care activism help migrant caregivers survive and even thrive in the face of arduous working and living conditions and the pains surrounding family separation. As Tungohan shows, care activism also unifies caregivers to resist society's legal and economic devaluations of care and domestic work by reaffirming a belief that they, and what they do, are important and necessary. --Publisher's description

Transnational Employment Strain in a Global Health Pandemic: Migrant Farmworkers in Canada - Vosko, Leah F.; Basok, Tanya; Spring, Cynthia (Palgrave pivot, 2023)
The 2020-22 COVID-19 pandemic reinforced inequalities between the global North and South, amplifying pre-existing disparities between migrant and citizen/permanent resident workers in receiving and sending states worldwide. In contexts such as Canada, it also underscored that many workers in occupations and sectors deemed “essential” enough to be exempt from stay-at-home orders and other public safety measures are migrants, a sizeable number of whom sustain Canada’s food supply through their work in its agricultural industry. This book explores the dynamics behind the pandemic’s deleterious outcomes for this vital group of workers, highlighting migrant farmworkers importance to the Canadian economy, society, and the world of work alongside the conditions they endured before and during the global health pandemic through policy and media analysis and open-ended interviews with workers enrolled in two streams of Canada’s Temporary Foreign Worker Program (TFWP) as well as migrants without legal status employed in agriculture located in Ontario and Quebec. Advancing the notion of transnational employment strain, the authors derive insight from the employment strain model, a framework for understanding risks to the physical and psychological well-being of workers, and expand it to account for migrants’ relationships across transnational space. --Publisher's description
Keywords: COVID-19 Pandemic, 2020-2023 Economic aspects Canada; Canada; Economics; Influence (Literary, artistic, etc.); Migrant agricultural laborers; Migrant agricultural laborers Canada; Migrant agricultural laborers Government policy; Migrant agricultural laborers Government policy Canada; Pandémie de COVID-19, 2020-2023 Aspect économique Canada; Since 2020; Travailleurs agricoles migrants Canada; Travailleurs agricoles migrants Politique gouvernementale Canada

Denison Avenue - Wong, Christina (ECW Press, 2023)
Bringing together ink artwork and fiction, Denison Avenue by Daniel Innes (illustrations) and Christina Wong (text) follows the elderly Wong Cho Sum, who, living in Toronto’s gentrifying Chinatown–Kensington Market, begins to collect bottles and cans after the sudden loss of her husband as a way to fill her days and keep grief and loneliness at bay. In her long walks around the city, Cho Sum meets new friends, confronts classism and racism, and learns how to build a life as a widow in a neighborhood that is being destroyed and rebuilt, leaving elders like her behind. A poignant meditation on loss, aging, gentrification, and the barriers that Chinese Canadian seniors experience in big cities, Denison Avenue beautifully combines visual art, fiction, and the endangered Toisan dialect to create a book that is truly unforgettable. --Publisher's description

Working in Canada: A Sociological Exploration - Adams, Tracey Lynn (Oxford University Press, 2022)
Canada's student body is diverse and the transition from student to worker is often challenging. Working in Canada's intersectional and practical approach to work draws connections between sociological theory and examples to students lived and work experiences to help students better understand the workforce they will soon enter. -- Publisher's description
Keywords: Canada; Travail Aspect social Canada; Work Social aspects; Work Social aspects Canada

Cobalt: Cradle of the Demon Metals, Birth of a Mining Superpower - Angus, Charlie (House of Anansi Press, 2022)
The world is desperate for cobalt. It fuels the digital economy and powers everything from cell phones to clean energy. But this 'demon metal,' this 'blood mineral,' has a horrific present and troubled history. Then there is the town in northern Canada, also called Cobalt. It created a model of resource extraction a hundred years ago--theft of Indigenous lands, rape of the earth, exploitation of workers, enormous wealth generation--that has made Toronto the mining capital of the world and given the mining industry a blueprint for resource extraction that has been exported everywhere. Charlie Angus unearths the history of the town and shows how it contributed to Canada's mining dominance. He connects the town to present-day Congo, with its cobalt production and misery, to horrendous mining practices in South America and demonstrates that global mining is as Canadian as hockey. -- Publisher's description
Keywords: Canada; Cobalt (Ont.) History; Cobalt mines and mining; History; Mineral industries; Mineral industries Canada; Mineral industries Ontario Cobalt History; Mines Industrie Canada; Ontario Cobalt

Harvesting Labour: Tobacco and the Global Making of Canada's Agricultural Workforce - Dunsworth, Edward (Rethinking Canada in the World, 2022)
In recent decades an increasing share of Canada’s agricultural workforce has been made up of temporary foreign workers from the Global South. These labourers work difficult and dangerous jobs with limited legal protections and are effectively barred from permanent settlement in Canada. In Harvesting Labour Edward Dunsworth examines the history of farm work in one of Canada’s underrecognized but most important crop sectors — Ontario tobacco. Dunsworth takes aim at the idea that temporary foreign worker programs emerged in response to labour shortages or the unwillingness of Canadians to work in agriculture. To the contrary, Ontario’s tobacco sector was extremely popular with workers for much of the twentieth century, with high wages attracting a diverse workforce and enabling thousands to establish themselves as small farm owners. By the end of the century, however, the sector had become something entirely different: a handful of mega-farms relying on foreign guest workers to produce their crops. Taking readers from the leafy fields of Ontario’s tobacco belt to rural Jamaica, Barbados, and North Carolina and on to the halls of government, Dunsworth demonstrates how the ultimate transformation of tobacco - and Canadian agriculture writ large - was fundamentally a function of the capitalist restructuring of farming. Harvesting Labour brings together the fields of labour, migration, and business history to reinterpret the historical origins of contemporary Canadian agriculture and its workforce. --Publisher's description

Pour sortir les allumettières de l'ombre: les ouvrières de la manufacture d'allumettes E. B. Eddy de Hull (1854-1928) - Durocher, Kathleen (Études régionales, 2022)
Cet ouvrage dresse un portrait des allumettières de la E.B. Eddy de Hull en abordant leurs conditions de vie et de travail entre 1854 et 1928. Cette étude s'appuie principalement sur un portrait démographique basé sur les recensements canadiens, mais aussi sur diverses archives (gouvernementales, privées, paroissiales, journaux scientifiques et à grand tirage, etc.) qui nous permettent de mieux comprendre la vie et le travail de ces ouvrières. En raison du nombre restreint d'études sérieuses sur les allumettières et l'industrie de l'allumette au Canada, cet ouvrage se base largement sur les sources historiques et l'analyse approfondie de ces dernières. Cette monographie présente l'histoire des allumettières par le biais de différents grands thèmes : leur rôle au sein de la classe ouvrière, leur vie au quotidien, leurs différents rôles dans la manufacture, les dangers de l'emploi (principalement ceux associés au phosphore blanc), leurs conditions de travail (salaires et heures) ainsi que leur expérience syndicale qui durera de 1918 au départ de la manufacture en 1928. À travers ses sept chapitres, cette monographie vise à peindre un portait détaillé et nuancé de cette main-d'œuvre anonyme, mais aussi à présenter les filles et les femmes qui ont occupé cet emploi. En somme, cette étude permettra de mieux saisir qui sont celles souvent présentées sous les traits de jeunes filles exploitées ou de militantes syndicales engagées. -- Résumé de l'éditeur
Keywords: Allumettes Industrie Personnel Québec (Province) Gatineau; E.B. Eddy Company Histoire; Travailleuses Conditions de travail Québec (Province) Gatineau Histoire 19e siècle; Travailleuses Conditions de travail Québec (Province) Gatineau Histoire 20e siècle; Travailleuses Québec (Province) Gatineau Conditions sociales 19e siècle; Travailleuses Québec (Province) Gatineau Conditions sociales 20e siècle

This Has Always Been a War: The Radicalization of a Working Class Queer - Fox, Lori (Arsenal Pulp Press, 2022)
A powerful, personal critique of capitalist patriarchy as seen through the eyes of a queer radical. Capitalism has infiltrated every aspect of our personal, social, economic, and sexual lives. By examining the politics of gender, environment, and sexuality, we can see the ways straight, cis, white, and especially male upper-class people control and subvert the other - queer, non-binary, BIPOC, and female bodies - in order to keep the working lower classes divided. Patriarchy and classism are forms of systemic violence which ensure that the main commodity of capitalism - a large, disposable, cheap, and ideally subjugated work force - is readily available. There is a lot wrong with the ways we live, work, and treat each other. In essays that are both accessible and inspiring, Lori Fox examines their confrontations with the capitalist patriarchy through their experiences as a queer, non-binary, working-class farm hand, labourer, bartender, bush-worker, and road dog, exploring the ugly places where issues of gender, sexuality, class, and the environment intersect. In applying the micro to the macro, demonstrating how the personal is political and vice versa, Fox exposes the flaws in believing that this is the only way our society can or should work. Brash, topical, and passionate, This Has Always Been a War is not only a collection of essays, but a series of dispatches from the combative front lines of our present-day culture. -- Publisher's description
Keywords: Capitalism; Capitalism Social aspects; Fox, Lori; Minorities; Minorities Employment Social aspects; Minorities Social conditions; Minorités Conditions sociales; Minorités Travail Aspect social; Patriarcat (Sociologie); Patriarcat (Sociologie) Aspect social; Patriarchy; Patriarchy Social aspects; Queer theory; Théorie queer; Travailleurs; Travailleurs Conditions sociales; Working class; Working class Social conditions

Refracted Economies: Diamond Mining and Social Reproduction in the North - Hall, Rebecca Jane (University of Toronto Press, 2022)
Since the beginning of the twenty-first century, diamonds have been lauded as a "glistening" driver of the northern Canadian economy. Canadian diamonds are cast with an imagined purity as though they had emerged by magic. However, these diamonds are mined on Dene land, extracted by people who fly in from afar, separated from their families for long periods of time. Adopting a decolonizing and feminist approach to political economy, Refracted Economies analyses the impact of diamond mining in Yellowknife, Northwest Territories. The book centres Indigenous women's social reproduction labour--both at the mine sites and at sites of community, home, and care--as a means of understanding the diffuse impacts of the diamond mines. Grounded in ethnographic work, the narratives of northern Indigenous women's multiple labours offer unique insight into the gendered ways northern land and livelihoods have been restructured by the diamond industry. Rebecca Jane Hall draws on documentary analysis, interviews, and talking circles in order to understand and appreciate the--often unseen--labour performed by Indigenous women. Placing this day-to-day labour at the heart of her analysis, Hall shows that it both reproduces the mixed economy and resists the gendered violence of settler colonialism as exemplified by extractive capitalism. --Publisher's description
Keywords: Diamants Mines et extraction Aspect social Territoires du Nord-Ouest Yellowknife; Diamants Mines et extraction Aspect économique Territoires du Nord-Ouest Yellowknife; Diamond mines and mining Economic aspects Northwest Territories Yellowknife; Diamond mines and mining Social aspects; Diamond mines and mining Social aspects Northwest Territories Yellowknife; Economic history; Femmes autochtones Territoires du Nord-Ouest Yellowknife Conditions sociales; Femmes autochtones Territoires du Nord-Ouest Yellowknife Conditions économiques; Indigenous women Northwest Territories Yellowknife Economic conditions; Indigenous women Northwest Territories Yellowknife Social conditions; Northwest Territories Yellowknife; Social conditions; Yellowknife (N.W.T.) Economic conditions; Yellowknife (N.W.T.) Social conditions; Yellowknife (T.N.-O.) Conditions sociales; Yellowknife (T.N.-O.) Conditions économiques

Righting Canada’s Wrongs: 2023 set - Hickman, Pamela; Chan, Arlene; Arato, Rona; Wesley, Gloria Ann; Cavalluzzo, Jean Smith; Florence, Melanie; Setterington, Ken (Lorimer, 2022)
For educators seeking to build anti-racism learning into Canadian history classes, this 8-book set of classroom materials is an invaluable resource. Each book addresses a major instance of official racism and discrimination spanning more than 150 years. ...Titles included: Righting Canada's Wrongs: The Komagata Maru; Righting Canada's Wrongs: The Chinese Head Tax; Righting Canada's Wrongs: Anti-Semitism and the MS St. Louis; Righting Canada's Wrongs: The LGBT Purge; Righting Canada's Wrongs: Africville; Righting Canada's Wrongs: Italian Canadian Internment; Righting Canada's Wrongs: Residential Schools; Righting Canada's Wrongs: Japanese Canadian Internment; Righting Canada's Wrongs: Resource Guide. --Publisher's description

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C. (Studies on the history of Quebec, 2022)
Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom. -- Publisher's description
Keywords: 1900-1999; Deindustrialization; Deindustrialization Québec (Province) Montréal History 20th century; Désindustrialisation Québec (Province) Montréal Histoire 20e siècle; Economic history; History; Montréal (Québec) Black people History 20th century; Montréal (Québec) Conditions sociales 20e siècle; Montréal (Québec) Conditions économiques 20e siècle; Montréal (Québec) Economic conditions 20th century; Montréal (Québec) Race relations History 20th century; Montréal (Québec) Relations raciales Histoire 20e siècle; Montréal (Québec) Social conditions 20th century; Neighborhoods; Neighborhoods Québec (Province) Montréal History 20th century; Quartiers (Urbanisme) Québec (Province) Montréal Histoire 20e siècle; Québec Montréal; Race relations; Social conditions; Travailleurs Québec (Province) Montréal Histoire 20e siècle; Working class; Working class Québec (Province) Montréal History 20th century

Solidarity Beyond Bars: Unionizing Prison Labour - House, Jordan; Rashid, Asaf (Fernwood, 2022)
Prisons don’t work, but prisoners do. Prisons are often critiqued as unjust, but we hear little about the daily labour of incarcerated workers — what they do, how they do it, who they do it for and under which conditions. Unions protect workers fighting for better pay and against discrimination and occupational health and safety concerns, but prisoners are denied this protection despite being the lowest paid workers with the least choice in what they do — the most vulnerable among the working class. Starting from the perspective that work during imprisonment is not “rehabilitative,” this book examines the reasons why people should care about prison labour and how prisoners have struggled to organize for labour power in the past. Unionizing incarcerated workers is critical for both the labour movement and struggles for prison justice, this book argues, to negotiate changes to working conditions as well as the power dynamics within prisons themselves. --Publisher's description

Class Warrior: The Selected Works of E.T. Kingsley - Kingsley, E.T. (Eugene Thornton) (Athabasca University Press for the Canadian Committee on Labour History, 2022)
In October 1890, Eugene T. Kingsley’s life changed irrevocably while working as a brakeman on the Northern Pacific Railway when he was injured in a fall between two rail cars. While recuperating in hospital after the amputation of both legs, he began reading the works of Karl Marx. Joining a popular socialist movement, his activism eventually brought him to Vancouver, B.C. where he founded the Socialist Party of Canada (SPC). Kingsley, known as a passionate orator, went on to become one of the most prominent socialist intellectuals of his day. Class Warrior is a collection of Kingsley’s writing and speeches that underscores his tremendous impact on Canadian political discourse. --Publisher's description. Contents: Foreword: E. T. Kingsley: Canadian Marxism’s “Old Man” / Bryan D. Palmer -- Introduction: Re-evaluating the British Columbia School of Socialism: E. T. Kingsley, Disablement, and the “Impossiblist” Challenge to Industrial Capitalism in Western Canada / Benjamin Isitt and Ravi Malhotra. Part 1: Selected Writings of E. T. Kingsley. Part 2: Selected Speeches of E. T. Kingsley. Part 3: The Genesis and Evolution of Slavery. Part 4: On the World Situation. Appendix: Partial Record of E. T. Kingsley’s Public Speeches and Lectures; Kingley's Speeches.

Listening to the Fur Trade: Soundways and Music in the British North American Fur Trade, 1760-1840 - Laxer, Daniel Robert (McGill-Queen's studies in early Canada, 2022)
As fur traders were driven across northern North America by economic motivations, the landscape over which they plied their trade was punctuated by sound: shouting, singing, dancing, gunpowder, rattles, jingles, drums, fiddles, and--very occasionally--bagpipes. Fur trade interactions were, in a word, noisy. Daniel Laxer unearths traces of music, performance, and other intangible cultural phenomena long since silenced, allowing us to hear the fur trade for the first time. Listening to the Fur Trade uses the written record, oral history, and material culture to reveal histories of sound and music in an era before sound recording. The trading post was a noisy nexus, populated by a polyglot crowd of highly mobile people from different national, linguistic, religious, cultural, and class backgrounds. They found ways to interact every time they met, and facilitating material interests and survival went beyond the simple exchange of goods. Trust and good relations often entailed gift-giving: reciprocity was performed with dances, songs, and firearm salutes. Indigenous protocols of ceremony and treaty-making were widely adopted by fur traders, who supplied materials and technologies that sometimes changed how these ceremonies sounded. Within trading companies, masters and servants were on opposite ends of the social ladder but shared songs in the canoes and lively dances during the long winters at the trading posts. While the fur trade was propelled by economic and political interests, Listening to the Fur Trade uncovers the songs and ceremonies of First Nations people, the paddling songs of the voyageurs, and the fiddle music and step-dancing at the trading posts that provided its pulse. --Publisher's description
Keywords: 1700-1899; Canada; Coureurs de bois Chants et musique Histoire et critique; Criticism, interpretation, etc; Fiddle; Fourrures Commerce Canada Histoire 18e siècle; Fourrures Commerce Canada Histoire 19e siècle; French Voyageurs; Fur trade; Fur trade Canada History 18th century; Fur trade Canada History 19th century; Fur traders Songs and music History and criticism; History; Indigenous dances; Metis; Montreal merchants; SOCIAL SCIENCE / Ethnic Studies / Canadian Studies; Step-dancing; ceremonies; commercial compacts; early Canadian commerce; economy; instruments; intangible cultural heritage; jigging; musical interactions; practices; pre-Confederation; sound-making; trading posts; traditional

The Sleeping Car Porter - Mayr, Suzette (Coach House Books, 2022)
The Sleeping Car Porter brings to life an important part of Black history in North America, from the perspective of a gay man living in a culture that renders him invisible in two ways. Affecting, imaginative, and visceral enough that you'll feel the rocking of the train, The Sleeping Car Porter is a stunning accomplishment. Baxter's name isn't George. But it's 1929, and Baxter is lucky enough, as a Black man, to have a job as a sleeping car porter on a train that crisscrosses the country. So when the passengers call him George, he has to just smile and nod and act invisible. What he really wants is to go to dentistry school, but he'll have to save up a lot of nickel and dime tips to get there, so he puts up with "George." On this particular trip out west, the passengers are more unruly than usual, especially when the train is stalled for two extra days; their secrets start to leak out and blur with the sleep-deprivation hallucinations Baxter is having. When he finds a naughty postcard of two gay men, Baxter's memories and longings are reawakened; keeping it puts his job in peril, but he can't part with the postcard or his thoughts of Edwin Drew, Porter Instructor. --Publisher's description
Keywords: African American men; African American men Fiction; Black people North America Fiction; Dentisterie Romans, nouvelles, etc; Dentistry; Dentistry Fiction; FICTION / African American & Black / Historical; FICTION / LGBTQ+ / Gay; FICTION / World Literature / Canada; Fiction; Gay men; Gay men Fiction; Gays North America Fiction; Historical fiction; Hommes noirs américains Romans, nouvelles, etc; Homosexuels masculins Romans, nouvelles, etc; Novels; Porters; Porters Fiction; Porteurs de bagages Romans, nouvelles, etc; Pourboires Romans, nouvelles, etc; Racism; Racism Fiction; Racisme Romans, nouvelles, etc; Rail passengers; Rail passengers Fiction; Sleep deprivation; Sleep deprivation Fiction; Sommeil Privation Romans, nouvelles, etc; Tipping; Tipping Fiction

Nii Ndahlohke: Boys' and Girls' Work at Mount Elgin Industrial School, 1890-1915 - McCallum, Mary Jane Logan (Friesen Press, 2022)
This book takes its title from the phrase for “I work” in Lunaape, the traditional language of Munsee Delaware people, and was inspired by the work of the Munsee Delaware Language and History Group. Written for the descendants and communities of children who attended Mount Elgin and intended as a resource for all Canadians, Nii Ndahlohke tells the story of student life at Mount Elgin Industrial School between 1890 and 1915. Like the school itself, Nii Ndahlohke is structured in two sections. The first focuses on boys’ work, including maintenance and farm labour, the second on girls’ work, such as cooking, cleaning, and laundry. In Nii Ndahlohke readers will find a valuable piece of local, Indigenous, and Canadian history that depicts the nature of “education” provided at Canada’s Indian residential schools and the exploitation of children’s labour in order to keep school operating costs down. This history honours the students of Mount Elgin even as it reveals the injustice of Indian policy, segregated schooling, and racism in Canada. --Publisher's description

Displacement City: Fighting for Health and Homes in a Pandemic - Micallef, Shawn; Maynard, Robyn (Aevo UTP, an imprint of University of Toronto Press, 2022)
Canada's major cities have faced the humanitarian disaster of homelessness for decades, but the COVID-19 pandemic laid bare a massive deficit in social programs and widespread inattention to human rights. Are municipal public services designed to essentially produce displacement? Or can we do something to end the growing problem of urban homelessness in Canada? In Displacement City, outreach worker Greg Cook and street nurse Cathy Crowe illuminate this infrastructure of displacement through prose, poetry, and photography. Contributors to the book, including those with lived experience of homelessness in Toronto, report on the realities of the situation and how people responded: by providing disaster-relief supplies and tiny shelters for encampments, by advocating for shelter-hotels where people could physically distance, by taking the city to court, and by rising up against encampment evictions. The book provides particular insight into policies affecting Indigenous peoples and how the legacy of colonialism and displacement reached a critical point during the pandemic. This collection of first-hand accounts shows how people are fighting back for homes. It also mourns the hundreds of preventable deaths that resulted from an unjust shelter system and the lack of a national housing program. Offering rich stories of care, mutual aid, and solidarity, Displacement City provides a vivid account of a national tragedy. -- Publisher's description
Keywords: Aboriginal Canadians Economic conditions Ontario Toronto; Aboriginal Canadians Health Health services Ontario Toronto; Aboriginal Canadians Housing Ontario Toronto; Aboriginal Canadians Social services Ontario Toronto; COVID-19 Pandemic, 2020- Social aspects Ontario Toronto; Homeless persons Services for; Homeless persons Services for Ontario Toronto; Homelessness; Homelessness Ontario Toronto; Housing; Housing Ontario Toronto; Itinérance Ontario Toronto; Logement Ontario Toronto; Ontario Toronto; Pandémie de COVID-19, 2020- Aspect social Ontario Toronto; Sans-abri Logement Ontario Toronto; Sans-abri Services Ontario Toronto; Shelters for the homeless; Shelters for the homeless Ontario Toronto; Since 2020; Social aspects

For a Better World: The Winnipeg General Strike and the Workers' Revolt - Naylor, James; Hinther, Rhonda L.; Mochoruk, Jim (University of Manitoba Press, 2022)
Canada’s largest and most famous example of class conflict, the Winnipeg General Strike, redefined local, national, and international conversations around class, politics, region, ethnicity, and gender. The Strike’s centenary occasioned a re-examination of this critical moment in working-class history, when 300 social justice activists, organizers, scholars, trade unionists, artists, and labour rights advocates gathered in Winnipeg in 2019. Probing the meaning of the General Strike in new and innovative ways, For a Better World includes a selection of contributions from the conference as well as others’ explorations of the character of class confrontation in the aftermath of the First World War. Editors Naylor, Hinther, and Mochoruk depict key events of 1919, detailing the dynamic and complex historiography of the Strike and the larger Workers’ Revolt that reverberated around the world and shaped the century following the war. The chapters delve into intersections of race, class, and gender. Settler colonialism’s impact on the conflict is also examined. Placing the struggle in Winnipeg within a broader national and international context, several contributors explore parallel strikes in Edmonton, Crowsnest Pass, Montreal, Kansas City, and Seattle. For a Better World interrogates types of commemoration and remembrance, current legacies of the Strike, and its ongoing influence. Together, the essays in this collection demonstrate that the Winnipeg General Strike continues to mobilize—revealing our radical past and helping us to think imaginatively about collective action in the future. --Publisher's description

Jobs with Inequality: Financialization, Post-Democracy, and Labour Market Deregulation in Canada - Peters, John (University of Toronto Press, 2022)
Income inequality has skyrocketed in Canada over the past decades. The rich have become richer, while the average household income has deteriorated and job quality, plummeted. Common explanations for these trends point to globalization, technology, or other forces largely beyond our control. But as Jobs with Inequality shows, there is nothing inevitable about inequality. Rather, runaway inequality is the result of politics and policies, and what governments have done to aid the rich and boost finance, and what has not done to uphold the interests of workers. Drawing on new tax and income data, John Peters tells the story of how inequality is unfolding in Canada today by examining post-democracy, financialization, and labour market deregulation. Timely and novel, the book explains how and why business and government have rewritten the rules of the economy to the advantage of the few, and considers why progressive efforts to reverse these trends have so regularly run aground. -- Publisher's description
Keywords: Canada; Deregulation; Deregulation Canada; Déréglementation Canada; Financialization; Financialization Canada; Financiarisation Canada; Income distribution; Income distribution Canada; Labor market; Labor market Canada; Labor policy; Labor policy Canada; Marché du travail Canada; Revenu Répartition Canada; Salaires Canada; Travail Politique gouvernementale Canada; Wages; Wages Canada

Canadian Labour Policy and Politics - Peters, John; Wells, Donald M. (UBC Press, 2022)
Low-wage work and precarious employment are among the most urgent issues of our time. Canadian Labour Policy and Politics serves as essential reading for undergraduates who need to understand the politics of inequality in Canada’s labour market. This comprehensive textbook traces the rise of these pressing problems, reveals the resulting inequalities, and outlines the solutions for a sustainable future. Written by leading experts and practitioners, the text demonstrates how and why laws and public policy – intended to protect workers – often leave workers vulnerable with little economic or social security. Based on up-to-date data and international comparisons, chapters provide readers with real-world examples and case studies of how globalization, labour laws, employment standards, COVID-19, and other challenges affect workers on and off the job. Canadian Labour Policy and Politics also engages students in defining a far-reaching policy agenda for developing greater economic equality, political inclusiveness, and a green recovery in the wake of the coronavirus pandemic. Accessible and clearly written, it is a must-read for students as well as researchers, practitioners, activists, and policymakers. Key features include chapter summaries and outlines, suggestions for further reading, and glossaries. Students and scholars of Canadian politics and public policy, labour studies, political economy, and sociology will find this an invaluable addition to their bookshelves. The volume is a core text for second-, third-, and fourth-year level university labour and inequality courses. The fresh and insightful overview of Canada’s labour market and policies will also be essential reading for government policymakers, NGO representatives, union researchers and practitioners, and journalists. --Publisher's description

Law for a New Dominion, 1867-1914 - Phillips, Jim; Girard, Philip; Brown, R. Blake (A History of Law in Canada, 2022)
This is the second volume of what will be a three-volume history of law in what is now Canada. The main theme of A History of Law in Canada Volume II is encapsulated in its sub-title: Law for the New Dominion. As a new state on the global stage, Canada tried to use law to weld into one nation several disparate settler colonies established on Indigenous lands. But unity was elusive: Canada had to recognize Quebec civil law and tried to override or replace Indigenous law even as it faced challenges to its own authority, from the Northwest Rebellion to the claims of restive provincial premiers. The volume deals with all aspects of Canadian law and legal institutions, with chapters on the constitution, courts and judges, sources of law (common law, civil law, Indigenous law and statutes), the legal profession, Canadian law and Indigenous peoples (3 chapters), criminal law, law and the economy, labour law, property law, the law affecting women’s status, and civil rights and minorities. --Publisher's description
Keywords: Canada; Droit Canada Histoire; HISTORY; History; Law; Law Canada History; Post-Confederation (1867-)

It Should Be Easy to Fix - Robichaud, Bonnie (Between the Lines, 2022)
In 1977, Bonnie Robichaud accepted a job at the Department of Defence military base in North Bay, Ontario. After a string of dead-end jobs, with five young children at home, Robichaud was ecstatic to have found a unionized job with steady pay, benefits, and vacation time. After her supervisor began to sexually harass and intimidate her, her story could have followed the same course as countless women before her: endure, stay silent, and eventually quit. Instead, Robichaud filed a complaint after her probation period was up. When a high-ranking officer said she was the only one who had ever complained, Robichaud said, "Good. Then it should be easy to fix." This timely and revelatory memoir follows her gruelling eleven-year fight for justice, which was won in the Supreme Court of Canada. The unanimous decision set a historic legal precedent that employers are responsible for maintaining a respectful and harassment-free workplace. Robichaud's story is a landmark piece of Canadian labour history--one that is more relevant today than ever. --Publisher's description
Keywords: Autobiographies; Autobiography; Canada; Harcèlement sexuel Droit Canada; Robichaud, Bonnie; Sexual harassment Law and legislation; Sexual harassment Law and legislation Canada; Sexual harassment of women Law and legislation; Sexual harassment of women Law and legislation Canada; autobiographies (literary works)

Smelter Wars: A Rebellious Red Trade Union Fights for Its Life in Wartime Western Canada - Verzuh, Ron (Canadian social history series, 2022)
In 1938, the Congress of Industrial Organizations (CIO) came to organize the International Union of Mine, Mill and Smelter Workers (Mine Mill) in Trail, British Columbia. Six years later it was recognized as the legal representative of more than 5,000 workers at a smelter owned by the powerful Consolidated Mining and Smelting Company of Canada (CM&S). Smelter Wars aims to unfold the historic struggle of the working people who built the city of Trail. The book recounts the various difficulties of the rural community, providing glimpses into the political and social life in the smelter city, as well as the turbulent years marked by economic depression, war, and Cold War intolerance. Ron Verzuh draws upon archival and periodical sources, including the mainstream and labour press, to explore the CIO's complicated legacy in Trail as it battled a wide range of antagonists: a powerful employer (CM&S), a company union, local conservative citizens, and Cooperative Commonwealth Federation (CCF) leadership. More than a history of a union, Smelter Wars is a cultural study of a community that has been shaped by decades of corporate welfare. --Publisher's description
Keywords: British Columbia Trail; Fusion (Métallurgie) Colombie-Britannique Trail Histoire; History; Industrial relations; Industrial relations British Columbia Trail History; Iron and steel workers Labor unions; Iron and steel workers Labor unions British Columbia Trail History; Labor unions; Labor unions British Columbia Trail History; Relations industrielles Colombie-Britannique Trail Histoire; Smelting; Smelting British Columbia Trail History; Subsidies; Subsidies British Columbia Trail History; Subventions Colombie-Britannique Trail Histoire; Syndicats Colombie-Britannique Trail Histoire; Trail (B.C.) History; Trail (C.-B.) Histoire; Travailleurs du fer et de l'acier Syndicats Colombie-Britannique Trail Histoire

Being Neighbours: Cooperative Work and Rural Culture, 1830-1960 - Wilson, Catharine Anne (McGill-Queen's rural, wildland, and resource studies series, 2022)
Throughout history, farm families have shared work and equipment with their neighbours to complete labour-intensive, time-sensitive, and time-consuming tasks. They benefitted materially and socially from these voluntary, flexible, loosely structured networks of reciprocal assistance, making neighbourliness a vital but overlooked aspect of agricultural change. Being Neighbours takes us into the heart of neighbourhood - the set of people near and surrounding the family - through an examination of work bees in Southern Ontario from 1830 to 1960. The "bee" was a special event where people gathered to work on a neighbour's farm like bees in a hive for a wide variety of purposes, including barn-raising, logging, threshing, quilting, turkey plucking, and apple paring. Drawing on the diaries of over one hundred men and women, Catharine Wilson takes readers into families' daily lives, the intricacies of their labour exchange, their workways, feasts, and hospitality. Through the prism of the bee and a close reading of the diaries, she uncovers the subtle social politics of mutual dependency, the expectations neighbours had of each other, and their ways of managing conflict and crisis. This book adds to the literature on cooperative work that focuses on evaluating its economic efficiency and complicates histories of capitalism that place communal values at odds with market orientation. Beautifully written, engaging, and richly detailed and illustrated, Being Neighbours reveals the visceral textures of rural life. -- Publisher's description
Keywords: Bees (Cooperative gatherings); Bees (Cooperative gatherings) Ontario, Southern History; Communauté Ontario (Sud) Histoire; Community life; Community life Ontario, Southern History; Cooperation; Cooperation Ontario, Southern History; Corvées (Travail en commun) Ontario (Sud) Histoire; Country life; Country life Ontario, Southern History; HISTORY / Canada / General; History; Participation sociale Ontario (Sud) Histoire; Social participation; Social participation Ontario, Southern History; Southern Ontario

Ageism at Work: Deconstructing Age and Gender in the Discriminating Labour Market - Berger, Ellie D. (Canadian social history series, 2021)
The Canadian population is aging, bringing with it an increasing number of social and economic challenges. With the aging of the workforce, the reconceptualization of older workers and retirement, the increasing share of women in the labour force, the elimination of mandatory retirement, the fluctuating economy, and the changes to the pension system, barriers to employment for older workers, such as ageism, need to be of central concern. Ageism at Work examines the subjective experiences of older workers in Canada and explores how they negotiate ageism and manage their interactions in the employment setting. Further, this book looks at the intersection between age and gender and the pervasiveness of gendered ageism in the labour market. Finally, this book examines employers' attitudes toward older workers quantitatively, while also exploring their firsthand accounts about them through qualitative inquiry. Understanding how ageism plays out in the labour market, how it intersects with sexism, and its consequences on a personal level are critical to moving the discussion on discrimination and human rights forward in Canada. --Publisher's description

Grève des stages, grève des femmes: anthologie d'une lutte féministe pour un salaire étudiant (2016-2019) - Berthiaume, Annabelle; Poirier, Amélie; Simard, Valérie; Tremblay-Fournier, Camille; Simard, Étienne (Les Éditions du Remue-ménage, 2021)
De 2016 à 2019, les comités unitaires sur le travail étudiant (CUTE) ont mené une lutte contre l'exploitation du travail étudiant et pour la rémunération des stages. La mobilisation a touché 60 000 étudiant·e·s et, pour une première fois dans l'histoire du mouvement étudiant québécois, des milliers de stagiaires se sont mis·e·s en grève. Préfacée par George Caffentzis et Silvia Federici, cette anthologie retrace les temps forts d'une lutte étudiante et féministe singulière pour un salaire étudiant. Cet ouvrage s'apparente à une autopsie d'une mobilisation. Celle de la grève des stages lancée au Québec en 2016 et qui aura culminé en 2019 par l'obtention de la création de bourses dans seize programmes liés aux domaines de l'éducation, de la santé et des services sociaux, au sein des écoles de formation professionnelle, des cégeps et des universités. Une victoire sans précédent pour le mouvement étudiant depuis une quarantaine d'années. Or, pour les militantes et les militants qui ont vécu cette lutte de l'intérieur, les revendications dépassaient la simple rémunération des stages. Dans une perspective féministe, on invitait plutôt les grévistes à redéfinir le mouvement étudiant lui-même englué dans des rapports de pouvoir, à reconnaitre les études comme une forme de travail, à décentraliser les mouvements contestataires, à l'éclatement des méthodes du mouvement étudiant traditionnel. C'est que les stages ne se piquettent pas comme des cours. C'est que les stages reproduisent une forme d'aliénation propre au monde salarié, dans des domaines majoritairement constitués de femmes, sauf qu'il s'agit d'un travail gratuit, invisible. À travers les différents chapitres constitués de textes, de tracts et d'affiches qui proviennent des agissantes et agissants des Comités unitaires pour le travail étudiant (CUTE), on replonge dans la toute première grève des stages du Québec. De la fondation des CUTE aux tentatives de ralliement des autres branches de la gauche étudiante, en passant par l'organisation d'une grève qui s'articule de manière régionale et non nationale,--et qui arrive tout de même à faire écho à l'international,--jusqu'à la grève elle-même et tout ce qu'elle implique de sacrifices, de tensions et d'apprentissages. Pour nourrir les mouvements à venir, il était primordial pour les autrices de colliger les expériences et les témoignages de cette grève unique en son genre. -- Publisher's description
Keywords: Comités unitaires sur le travail étudiant; Enseignement Réforme Québec (Province); Enseignement supérieur Réforme Québec (Canada; province); Enseignement supérieur Réforme Québec (Province); Féminisme Québec (Canada; province) 2000-...; Grèves étudiantes Québec (Canada; province) 2000-...; Grèves étudiantes Québec (Province); Jeunes femmes Activité politique Québec (Canada; province) 2000-...; Mouvements étudiants Québec (Canada; province); Mouvements étudiants Québec (Province); Québec; Stages Québec (Province); Stages pédagogiques Québec (Province); Stagiaires (Éducation) Conditions de travail Québec (Province); Stagiaires Conditions sociales Québec (Canada; province) 2000-...; Student movements; Student movements Québec (Province); Étudiantes Activité politique Québec (Province); Étudiants salariés Québec (Province)

Just the Usual Work: The Social Worlds of Ida Martin, Working-Class Diarist - Boudreau, Michael; Huskins, Bonnie; Martin, Ida (McGill-Queen's University Press, 2021)
Born in 1907, Ida Martin spent most of her life in Saint John, New Brunswick. She married a longshoreman named Allan Robert Martin in 1932 and they had one daughter. In the years that followed, Ida had a busy and varied life, full of work, caring for her family, and living her faith. Through it all, Ida found time to keep a daily diary from 1945 to 1992. Bonnie Huskins is Ida Martin's granddaughter. In Just the Usual Work, she and Michael Boudreau draw on Ida's diaries, family memories, and the history of Atlantic Canada to shed light on the everyday life of a working-class housewife during a period of significant social and political change. They examine Ida's observations about the struggles of making ends meet on a longshoreman's salary, the labour confrontations at the Port of Saint John, the role of automobiles in the family economy, the importance of family, faith, and political engagement, and her experience of widowhood and growing old. Ida Martin's diaries were often read by members of her family to reconstruct and relive their shared histories. By sharing the pages of her diaries with a wider audience, Just the Usual Work keeps Ida's memory alive while continuing her abiding commitment to documenting the past and finding meaning in the rhythms of everyday life. --Publisher's description

Dissenting Traditions: Essays on Bryan D. Palmer, Marxism, and History - Carleton, Sean; McCoy, Ted; Smith, Julia; Finkel, Alvin; Niergarth, Kirk; Kealey, Gregory S.; Rogers, Nicholas; Pearson, Chad; Panitch, Leo; Gindin, Sam; McIlroy, John; Campbell, Alan; et al. (Working Canadians: Books from the CCLH, 2021)
The work of Bryan D. Palmer, one of North America’s leading historians, has influenced the fields of labour history, social history, discourse analysis, communist history, and Canadian history, as well as the theoretical frameworks surrounding them. Palmer’s work reveals a life dedicated to dissent and the difficult task of imagining alternatives by understanding the past in all of its contradictions, victories, and failures. Dissenting Traditions gathers Palmer’s contemporaries, students, and sometimes critics to examine and expand on the topics and themes that have defined Palmer’s career, from labour history to Marxism and communist politics. Paying attention to Palmer’s participation in key debates, contributors demonstrate that class analysis, labour history, building institutions, and engaging the public are vital for social change. In this moment of increasing precarity and growing class inequality, Palmer’s politically engaged scholarship offers a useful roadmap for scholars and activists alike and underlines the importance of working-class history. --Publisher's description

Shift Change: Scenes from a Post-Industrial Revolution - Dale, Stephen (Between the Lines, 2021)
Hamilton’s industrial age is over. In the steel capital of Canada, there are no more skies lit red by foundries at sunset, no more traffic jams at shift change. Instead, an urban renaissance is taking shape. But who wins and who loses in the city’s not-too-distant future? Is it possible to lift a downtrodden, post-industrial city out of poverty in a way that benefits people across the social spectrum, not just a wealthy elite? In Shift Change, author Stephen Dale sets up “the Hammer” as a battlefield, a laboratory, a chessboard. As investors cash in on a real estate gold rush and the all-too-familiar wheels of gentrification begin to turn, there’s still a rare opportunity for both old-guard and newcomer Hamiltonians to come together and write a different story--one in which Steeltown becomes an economically diverse and inclusive urban centre for all. What plays out in these pages and at this very moment is a real-time case study that will capture the attention and the imagination of anyone interested in equitable redevelopment, housing activism, and social justice in the North American city. -- Publisher's description
Keywords: Développement durable Ontario Hamilton; Economic history; Hamilton (Ont.) Economic conditions; Hamilton (Ont.) Social conditions; Ontario Hamilton; Social conditions; Sustainable development; Sustainable development Ontario Hamilton; Urbanisation Ontario Hamilton; Urbanization; Urbanization Ontario Hamilton

In the Kingdom of Shoes: Bata, Zlín, Globalization, 1894-1945 - Doleshal, Zachary Austin (University of Toronto Press, 2021)
One of the world’s largest sellers of footwear, the Bata Company of Zlín, Moravia has a remarkable history that touches on crucial aspects of what made the world modern. In the twilight of the Habsburg Empire, the company Americanized its production model while also trying to Americanize its workforce. It promised a technocratic form of governance in the chaos of postwar Czechoslovakia, and during the Roaring Twenties, it became synonymous with rationalization across Europe and thus a flashpoint for a continent-wide debate. While other companies contracted in response to the Great Depression, Bata did the opposite, becoming the first shoe company to unlock the potential of globalization.As Bata expanded worldwide, it became an example of corporate national indifference, where company personnel were trained to be able to slip into and out of national identifications with ease. Such indifference, however, was seriously challenged by the geopolitical crisis of the 1930s, and by the cusp of the Second World War, Bata management had turned nationalist, even fascist.In the Kingdom of Shoes unravels the way the Bata project swept away tradition and enmeshed the lives of thousands of people around the world in the industrial production of shoes. Using a rich array of archival materials from two continents, the book answers how Bata’s rise to the world’s largest producer of shoes challenged the nation-state, democracy, and Americanization. -- Publisher's description

Rising Up: The Fight for Living Wage Work in Canada - Evans, Bryan; Fanelli, Carlo; McDowell, Tom (UBC Press, 2021)
Canada has one of the highest rates of low-wage work among advanced industrial economies. In a labour market characterized by the ongoing fallout from COVID-19, deepening income inequality, increasingly uncertain job tenure, and steadily diluted union representation, the living wage movement offers a response. Rising Up traces the history and international context of living wage movements across Canada. Contributors to this astute and compassionate collection of essays examine union- and community-based approaches to organizing in marginalized communities, the role of social reproduction, migrant labour, and media (mis)representations, among other key topics. In the 1970s, the balance of political and economic power began to shift in favour of business, as trade unions weakened and governments proved unwilling to check corporate power. By the 2000s, austerity measures had dismantled social services spending, facilitating the growth of precarious, often gendered or racialized low-waged employment. Rapidly increasing wealth and income inequality has followed in the wake of these deteriorating labour market conditions and mounting social disparities.As more and more workers in Canada and elsewhere face permanent low-paid work, Rising Up will stimulate debate about living wages and social inequality, promoting alternatives to a neoliberalized labour market. --Publisher's description

Un regard contemporain sur les relations du travail dans les secteurs public et parapublic Québécois - Grenier, Jean-Noël; Bolduc, François (Collection l'essentiel (Presses de l'Université Laval), 2021)
Depuis une trentaine d’années, les services et les secteurs publics occidentaux sont l’objet de réformes inspirées par la nouvelle gestion publique. L’administration publique québécoise ne fait pas exception. Dans ce contexte, cet ouvrage cherche à saisir l’influence de la nouvelle gestion publique sur le régime de négociation collective propre au secteur public et parapublic québécois. Après une description des principales caractéristiques de ce régime, ainsi que des fondements de la nouvelle gestion publique, l’attention est portée sur la négociation collective dans les secteurs de la fonction publique, de la santé et des services sociaux et de l’éducation. L’analyse permet de réfléchir à l’influence du régime de négociation collective sur la capacité de l’État à imposer ses volontés en matière d’organisation du travail et de modes de gestion, et sur la capacité des organisations syndicales à y faire face. --Résumé de l'éditeur
Keywords: Collective bargaining Government employees; Collective bargaining Government employees Québec (Province); Industrial relations; Industrial relations Québec (Province); Négociations collectives Secteurs public et parapublic Québec (Province); Québec; Québec (Province) Fonctionnaires; Relations industrielles Québec (Province)

Class Action: How Ontario’s Elementary Teachers Became a Political Force. - Hanson, Andy (Between the Lines, 2021)
In this inspiring history of a union, labour historian Andy Hanson delves deep into the Elementary Teachers’ Federation of Ontario (ETFO) and how it evolved from two deeply divided unions to one of the province’s most united and powerful voices for educators. Today’s teacher is under constant pressure to raise students’ test scores, while the rise of neoliberalism in Canada has systematically stripped our education system of funding and support. But educators have been fighting back with decades of fierce labour action, from a landmark province-wide strike in the 1970s, to record-breaking front-line organizing against the Harris government and the Common Sense Revolution, to present-day picket lines and bargaining tables. Hanson follows the making of elementary teachers in Ontario as a distinct class of white-collar, public-sector workers who awoke in the last quarter of the twentieth century to the power of their collective strength. --Publisher's description

Code White: Sounding the Alarm on Violence Against Healthcare Workers - Keith, Margaret M.; Brophy, James T. (Between the Lines, 2021)
When health care workers call a Code White, its an emergency response for a violent incident: a call for help. But its one that goes unanswered in hospitals, clinics, and long-term care homes across the country. Code White exposes a shocking epidemic of violence thats hidden in plain sight, one in which workers are bruised, battered, assaulted, and demeaned, but carry on in silence, with little recourse or support. Researchers Margaret M. Keith and James T. Brophy lay bare the stories of over one hundred nurses and personal support workers, aides and porters, clerical workers and cleaners. The nightmarish experiences they relate are not one-off incidents, but symptoms of deep systemic flaws that have transformed health care into one of the most dangerous occupational sectors in Canada. The same questions echo in the wake of each and every brutal encounter: Is violence and trauma really just 'part of the job'? Why is this going underreported and unchecked? What needs to be done, and how? --Publisher's description. Contents: Foreword / Michael Hurley -- Preface . Part 1: Exposing a Hidden Epidemic. 1. Drawing Back the Curtain -- 2. Under the Scope -- 3. Finding an Abnormality. Part 2: A Forensic Examination. 4. Birth and Decline of the Health Care System -- 5. Birth and Decline of the Long-Term Care System. Part 3: Prescription for Healing. 6. Treatment Strategies -- 7. Rocky Road to Recovery -- 8. Collective Quest for the Cure. Afterword: Health Care Workers during COVID-19 -- Notes.

Spin Doctors: How Media and Politicians Misdiagnosed the COVID-19 Pandemic - Loreto, Nora (Fernwood Publishing, 2021)
As Canada was in the grips of the worst pandemic in a century, Canadian media struggled to tell the story. Newsrooms, already run on threadbare budgets, struggled to make broader connections that could allow their audience to better understand what was really happening, and why. Politicians and public health officials were mostly given the benefit of the doubt that what they said was true and that they acted in good faith. This book documents each month of the first year of the pandemic and examines the issues that emerged, from racialized workers to residential care to policing. It demonstrates how politicians and uncritical media shaped the popular understanding of these issues and helped to justify the maintenance of a status quo that created the worst ravages of the crisis. Spin Doctors argues alternative ways in which Canadians should understand the big themes of the crisis and create the necessary knowledge to demand large-scale change. -- Publisher's description
Keywords: COVID-19; COVID-19 (Disease); COVID-19 (Disease) Canada; COVID-19 (Disease) Government policy; COVID-19 (Disease) Government policy Canada; COVID-19 (Disease) Political aspects; COVID-19 (Disease) Political aspects Canada; COVID-19 (Disease) Press coverage Canada; COVID-19 Aspect politique Canada; COVID-19 Canada; COVID-19 Couverture de presse Canada; COVID-19 Pandemic, 2020-2023 Canada; COVID-19 Pandemic, 2020-2023 Government policy Canada; COVID-19 Pandemic, 2020-2023 Political aspects Canada; COVID-19 Pandemic, 2020-2023 Press coverage Canada; COVID-19 Politique gouvernementale Canada; Canada; Government policy; Health Communication methods; Information Theory; Information theory; Pandemics; Pandémie de COVID-19, 2020-2023 Aspect politique Canada; Pandémie de COVID-19, 2020-2023 Canada; Pandémie de COVID-19, 2020-2023 Couverture de presse Canada; Pandémie de COVID-19, 2020-2023 Politique gouvernementale Canada; Pandémies; Press coverage; Since 2020; Théorie de l'information; pandemics

Able to Lead: Disablement, Radicalism, and the Political Life of E.T. Kingsley - Malhotra, Ravi; Isitt, Benjamin (UBC Press, 2021)
Eugene T. Kingsley led an extraordinary life. Born in mid-nineteenth-century New York, by 1890 he was a railway brakeman in Montana. An accident left him a double amputee and politically radicalized, and his socialist activism that followed took him north of the border where he eventually was considered by the government to be "one of the most dangerous men in Canada." Able to Lead traces Kingsley's political journey from soapbox speaker in San Francisco to prominence in the Socialist Party of Canada. Ravi Malhotra and Benjamin Isitt illuminate a figure who shaped a generation of Canadian leftists during a time when it was uncommon for disabled people to lead. They examine Kingsley's endeavours for justice against the Northern Pacific Railway, and how Kingsley's life intersected with immigration law and free speech rights. Able to Lead brings a turbulent period in North American history to life, highlighting Kingsley's profound legacy for the twenty-first-century political left. --Publisher's description. Contents: Kingsley in Context: Labour History, Legal History, and Critical Disability Theory -- Incident at Spring Gulch: Disablement, Litigation, and the Birth of a Revolutionary -- California Radical: Fighting for Free Speech and Running for Congress in the Socialist Labor Party -- Crossing the Line: Kingsley Arrives in British Columbia -- No Compromise: Kingsley and the Socialist Party of Canada -- Kingsley and the State: Clashes with Authority in Early-Twentieth-Century Canada -- The Twilight Years: Kingsley and the 1920s Canadian Left.

Bent out of Shape: Shame, Solidarity, and Women's Bodies at Work - Messing, Karen (Between the Lines, 2021)
Award-winning ergonomist Karen Messing is talking with women—women who wire circuit boards, sew clothes, clean toilets, drive forklifts, care for children, serve food, run labs. What she finds is a workforce in harm’s way, choked into silence, whose physical and mental health invariably comes in second place: underestimated, underrepresented, understudied, underpaid. Should workplaces treat all bodies the same? With confidence, empathy, and humour, Messing navigates the minefield that is naming sex and biology on the job, refusing to play into stereotypes or play down the lived experiences of women. Her findings leap beyond thermostat settings and adjustable chairs and into candid, deeply reported storytelling that follows in the muckraking tradition of social critic Barbara Ehrenreich. Messing’s questions are vexing and her demands are bold: we need to dare to direct attention to women’s bodies, champion solidarity, stamp out shame, and transform the workplace—a task that turns out to be as scientific as it is political. --Publisher's description. Contents: Part 1: Shame and the Workplace. The third hour -- Shame and silence in health care -- A feminist intervention that hurt women? Part 2: Segregated Bodies. Jobs and bodies -- Same, different, or understudied? Part 3.Changing the Workplace: Re-engineering women's work -- Looking the dragon in the face -- Feminist ergonomic intervention with a feminist employer -- Solidarity. Part 4: Changing Occupational Health Science. Science and the second body -- Understanding women's pain -- The technical is political -- Going forward together. Index.

Perceptions de justice et santé au travail: l'organisation à l'épreuve - Moulin, Stéphane (Inégalité et justice sociale, 2021)
Qu’est-ce qu’une organisation juste? Quelles sont les injustices perçues par les travailleurs et les travailleuses? Quelles en sont les répercussions sur leur santé? Dans quelle mesure la COVID-19 a-t-elle exacerbé ces perceptions d’injustices?Cet ouvrage réunit des auteurs qui discutent des apports et des limites des études de justice organisationnelle pour comprendre les liens entre les perceptions d’injustice et la santé en milieu de travail. Ouvrage collectif de synthèse, ce livre innove en contribuant à une ouverture disciplinaire et méthodologique du champ de la justice organisationnelle et en examinant les conséquences de la COVID-19.Alors que les études de justice organisationnelle tendent à psychologiser le mal-être au travail, les auteurs invitent ici à des approches plus contextuelles et compréhensives. L’injustice ressentie par les travailleurs apparait ainsi principalement liée à des modes de gestion et d’évaluation autoritaires. Si les normes professionnelles partagées semblent contribuer à minimiser certaines souffrances vécues, la crise de la Covid-19 a accru les perceptions d’injustice et fragilisé la santé psychologique des travailleurs. --Publisher's description
Keywords: COVID-19 Pandemic, 2020-; Hygiène industrielle; Industrial hygiene; Justice organisationnelle; Occupational Health; Organizational justice; Pandémie de COVID-19, 2020-; Since 2020; Travailleurs Attitudes; Travailleurs Santé mentale; Working class Attitudes

Rethinking the Politics of Labour in Canada - Ross, Stephanie; Savage, Larry; Ernst, Alan; Evans, Bryan; Graefe, Peter; Ng, Winnie Wun Wun; Wall, Carol; Mills, Suzanne E.; McCreary, Tyler; Gardner, Karl; Magsumbol, Dani; Tungohan, Ethel; et al. (Labour in Canada (Halifax, N.S.), 2021)
In the wake of the COVID-19 pandemic, the need to re-establish the labour movement’s political capacity to exert collective power in ways that foster greater opportunity and equality for working-class people has taken on a greater sense of urgency. Understanding the strategic political possibilities and challenges facing the Canadian labour movement at this important moment in history is the central concern of this second edition of Rethinking the Politics of Labour in Canada. With new and revised essays by established and emerging scholars from a wide range of disciplines, this edited collection assesses the past, present and uncertain future of Canadian labour politics in the wake of the COVID-19 pandemic. Bringing together the traditional electoral-based aspects of labour politics with analyses of newer and rediscovered forms of working-class organization and social movement-influenced strategies, which have become increasingly important in the Canadian labour movement, this book seeks to take stock of these new forms of labour politics, understand their emergence and assess their potential impact on the future of labour in Canada. --Publisher's description

Canada, a Working History - Russell, Jason (Dundurn, 2021)
A deep exploration of the experience of work in Canada, Canada, A Working History describes the ways in which work has been performed in Canada from the pre-Colonial period to the present day. Since the time of European colonization, the need to obtain and ensure a steady supply of workers to drive Canada's economic growth has been a key objective for policy makers. This book argues that there are key themes found in the history of work in Canada that persist to the present day. Work is shaped by a wide array of influences including gender, race, ethnicity, geography, economics, and politics. It in turn shapes us when we perform it. Work can be paid or unpaid, meaningful or alienating, and always essential. The work experience led people to form unions, aspire to management roles, pursue education, form professional associations, and seek self-employment. It has been the subject of much theoretical research and academic inquiry. Work is often in our cultural consciousness while being pondered in song, lamented in literature, celebrated in film, and preserved for posterity in other forms of art. It has been driven by technological change, governed by laws, been the cause of disputes, and the means by which people earn a living in Canada's capitalist economy. Engaging in work is common in all modern societies, and that there are distinct aspects to the history of work in Canada that will continue into the country's future. Ennobling, rewarding, exhausting, and sometimes frustrating, work has helped define who Canadians are as people. --Publisher's description.

Mining Country: A History of Canada's Mines and Miners - Sandlos, John; Keeling, Arn (Lorimer, 2021)
Mining has a significant presence in every part of Canada - from east to west coasts to the far north. This book tells the stories of the people and companies who pushed mining into new territories, created new towns and generated jobs by the thousands. It highlights the experiences of those who lived and worked in mining settlements across the country, as well as the rise of major mining companies and the emergence of Toronto and Vancouver as centres of global mining finance. It also addresses the effects these developments have had on Indigenous communities and the environmental changes and challenges that have accompanied mining at every step. Mining Country is richly illustrated with more than 150 photos drawn from the well-recorded history up to the present. The story begins with the development of copper mining and trading networks among pre-contact Indigenous groups in Canada. Industrial scale mining of iron and coal emerged in Quebec and Nova Scotia in the eighteenth century. The book describes the growth of mining towns in northern Ontario, Quebec and western Canada in the nineteenth century, and the famous Cariboo and Klondike Gold Rushes. Demand for strategic minerals and metals during the Second World War and the Cold War pushed development into remote northern regions. The most recent period embraces the North West Territories diamond rush and controversial expansion into Ontario's "Ring of Fire" region. Much has been written about the history of individual mining towns, mine unions and mining companies. This book offers a readable account of the full scope of this key industry's story, in words and a collection of carefully researched and selected visuals. --Publiher's description
Keywords: Canada; History; Mineral industries; Mineral industries Canada History; Miners; Miners Canada History; Mines Canada Histoire; Mines Industrie Canada Histoire; Mines and mineral resources; Mines and mineral resources Canada History; Mineurs Canada Histoire; Mining corporations; Mining corporations Canada History; Sociétés minières Canada Histoire

Demanding Equality: One Hundred Years of Canadian Feminism - Sangster, Joan (UBC Press, 2021)
For one hundred years women fashioned different dreams of equality, autonomy, and dignity; yet what is Canadian feminism? In Demanding Equality, Joan Sangster explores feminist thought and organizing from mid-nineteenth-century, Enlightenment-inspired writing to the multi-issue movement of the 1980s.She broadens our definition of feminism, and – recognizing that its political, cultural, and social dimensions are entangled – builds a picture of a heterogeneous movement often characterized by fierce internal debates. This comprehensive rear-view look at feminism in all its political guises encourages a wider public conversation about what Canadian feminism has been, is, and should be. --Publisher's description. Contents: Spreading the word of women's emancipation -- The origins of socialist and labour feminism -- Women, democracy, and suffrage -- Reform feminism and women's right to work -- Agrarian, labour, and socialist feminism after the Frist World War -- Feminism and the party question -- Feminism, war, and peace -- Feminism in a Cold War climate -- Liberating feminism -- Feminist organizing in the 1970s and 1980s -- Afterword: Feminist challenges of the 1990s and beyond.

Solidarity: Canada's Unknown Revolution of 1983 - Spaner, David (Ronsdale Press, 2021)
The year 1983 began like any other year in Canada's West Coast province. Then "Bill's bills" unleashed four months of public unrest. The newly elected Social Credit government announced an avalanche of far-right legislation that shocked the country. By dropping viciously anti-union legislation that slashed protection for hard-won human rights, Premier Bill Bennett attacked nearly everyone in his contingency. A resistance movement called Solidarity sprung up across the province. Massive street protests, occupations and plans for an all-out general strike had all eyes on B.C. Like other uprisings - from France in 1968 to the anti-racism protests of 2020 - Solidarity arrived unexpectedly and rocked social foundations. Revolution, in one province? Filled with revealing interviews and lively, insightful prose, David Spaner's Solidarity goes behind the scenes of one of the greatest social uprisings in North American history. Spaner delves into the Solidarity months of 1983 through his own experience and that of the activists, both iconic and unsung, that organized B.C.'s masses. Solidarity's intimate storytelling mixes popular culture and rebel politics, finding political answers in the personal lives of those touched by the movement. In recreating this one singularly dramatic event, Spaner's Solidarity becomes the ongoing history of 20th century B.C. - exploring its great divides and unions, cultures and subcultures, and conflicts that continue into the 21st century. -- Publisher's description
Keywords: 1900-1999; British Columbia; British Columbia Politics and government 1975-1991; Colombie-Britannique Politique et gouvernement 1975-1991; History; Labor movement; Labor movement British Columbia History 20th century; Mouvement ouvrier Colombie-Britannique Histoire 20e siècle; Travailleurs Activité politique Colombie-Britannique Histoire 20e siècle; Working class Political activity; Working class Political activity British Columbia History 20th century

A Liberal-Labour Lady: The Times and Life of Mary Ellen Spear Smith - Strong-Boag, Veronica (UBC Press, 2021)
A Liberal-Labour Lady restores British Columbia's first female MLA and the British Empire and Commonwealth's first female cabinet minister to history. An imperial settler, liberal-labour activist, and mainstream suffragist, Mary Ellen Smith demanded a fair deal for "deserving" British women and men in the late nineteenth and early twentieth centuries. Born in England in 1863, the daughter and wife of miners, she emigrated to Nanaimo, BC, in 1892. As she became a well-known suffragist and her husband Ralph won provincial and federal elections, the power couple strove to shift Liberal parties leftward to benefit women and workers, while still embracing global assumptions of British racial superiority and bourgeois feminism's privileging of white women. His 1917 death launched Mary Ellen as a candidate in a tumultuous 1918 Vancouver by-election. In the BC legislature until 1928, Smith campaigned for better wages, mothers' and old age pensions, and greater justice, even as she endorsed anti-Asian, settler, and pro-eugenic policies. Her death in 1933 ended an experiment in extending democracy that was both brave and deeply flawed. A Liberal-Labour Lady sheds light on a Canadian suffragist undeservedly neglected by scholars and forgotten by posterity. It also illuminates a half a century of political history, first-wave feminism, immigration, and labour history set in a broad context of shifting ideas, ideologies, and strategies. Although simultaneously intrepid and flawed, Mary Ellen Smith is revealed to be a key figure in early Canada's compromised struggle for greater justice, who helped set the contours of a modern Canada. -- Publisher's description
Keywords: Biographies; Biography; British Columbia; Cabinet officers; Cabinet officers British Columbia Biography; Canada; Femmes ministres Colombie-Britannique Biographies; Femmes parlementaires Colombie-Britannique Biographies; Legislators; Legislators British Columbia Biography; Ministres Colombie-Britannique Biographies; Parlementaires Colombie-Britannique Biographies; Spear Smith, Mary Ellen, 1863-1933; Suffragettes Canada Biographies; Suffragists; Suffragists Canada Biography; Women cabinet officers; Women cabinet officers British Columbia Biography; Women legislators; Women legislators British Columbia Biography

Canada 1919: A Nation Shaped by War - Cook, Tim; Granatstein, J.L. (Studies in Canadian military history, 2020)
With compelling insight, Canada 1919 examines the year following the Great War--a war that was, for Canada, completely unexpected in its magnitude. In the midst of relief that the killing had ended, economic and political tensions were fraught as the survivors attempted to right the country and chart a path into the future. The Canadian Corps had played a significant role in the war and were hailed as the "shock troops" of the British empire. They came home full of both sorrow and pride in their accomplishments, wondering what they would do, and how would they fit in with their families. The military stumbled through massive demobilization. The government struggled to hang on to power, labour seethed, and the threat of Bolshevism emerged. At the same time there were positive changes, and a new Canadian nationalism was forged. This book offers a fresh perspective on the concerns of the time: the treatment of veterans, including nurses and Indigenous soldiers; the place of children; the influenza pandemic; the rising farm lobby; the role of labour; Canada's international standing; and commemoration of the fallen. Canada 1919 exposes the ways in which war shaped Canada--and the ways it did not. -- Publisher's description
Keywords: 1900-1999; Canada; Canada Conditions sociales 1918-1930; Canada Conditions sociales 20e siècle; Canada Conditions économiques 1918-1945; Canada Economic conditions 1918-1945; Canada Military policy; Canada Politics and government 1914-1945; Canada Politique et gouvernement 1914-1945; Canada Social conditions 1918-1930; Canada Social conditions 20th century; Economic history; Economics; Guerre mondiale, 1914-1918 Aspect social Canada; Guerre mondiale, 1914-1918 Aspect économique Canada; Guerre mondiale, 1914-1918 Canada; Military policy; Ottawa authors, musicians, etc; Politics and government; Social aspects; Social conditions; World War, 1914-1918 Canada; World War, 1914-1918 Economic aspects Canada; World War, 1914-1918 Social aspects Canada

The Law of Work - Doorey, David J. (Emond Publishing, 2020)
[This second edition] presents a comprehensive overview of all aspects of Canadian employment and labour law. Ideal for a non-legal audience, this resource considers the social context in which these laws are made and draws from various disciplines, including economics, management studies, and history. Through short, focused chapters, students will be introduced to the three regimes of work law: common law, regulation, and collective bargaining. Notable legal cases and explanations of key concepts are featured throughout, alongside practical problem-solving exercises and discussion questions that invite readers to apply the law to real-life workplace scenarios. --Publisher's description

Canadian Labour Relations: Law, Policy, and Practice - Doorey, David J.; Braley-Rattai, Alison (Emond Publishing, 2020)
This book offers non-legal students an in-depth exploration of work-related law, policy, and current issues. Topics include the unionization process, collective bargaining, regulation of unions, industrial conflict, collective agreement administration, and notable court decisions. Practical problem-solving exercises and questions are featured throughout in order to help readers apply the law to real-life scenarios. This edition includes updated legislation, mock arbitration and negotiation scenarios, and an entirely new section that explores key policy issues and debates. --Publisher's description

Women and Work: Feminism, Labour, and Social Reproduction - Ferguson, Susan (Between the Lines, 2020)
This edited collection introduces and explores the causes and consequences of precarious employment in Canada and across the world. After contextualizing employment precarity and its root causes, the authors illustrate how precarious employment is created amongst different populations and describe the accompanying social impacts on racialized immigrant women, those in the non-profit sector, temporary foreign workers and the children of Filipino immigrants. --Publisher's description.

The Canadian Precariat: Part-Time Faculty and the Higher-Education System - Gagné, Ann (2020)
This collection includes reflections about the precariousness of academic employment for non-tenured professionals across Canada. It includes articles from those who have taught in post-secondary education across Canada, as well as as from those some who have experienced precarity as student and union organizers. It also includes voices of students working and teaching in the higher education system. The texts are both in the form of critical engagement with the academic discourse and research as well as reflective memoirs on experiences of educational precarity from numerous social locations. They highlight precarity at all levels of employment in the Canadian higher education system and offer suggestions on how to improve this long-standing and damaging reality affecting tens of thousands of the precariously employed. --Publisher's description. Contents: Introduction / Ann Gagné -- Manufactured Precarity: Some Solutions to Help Mitigate the Impacts of Precarious Employment of Canadian Sessional Instructors / Amber Diaz -- The Tensions of Tenure and Allyship: On Becoming, Speaking, and Listening / Veronica J. Austen -- Reflections of Precarity from a Student and Student Representative / Gayle McFadden -- Immigrant Precarity in the Academe: The Quebec Version / Cristina Artenie -- Towards Best Practices in Canadian Higher Education: A Precarious Memoir in Miniature / Ann Gagné.

The Subjectivities and Politics of Occupational Risk: Mines, Farms and Auto Factories - Hall, Alan (Routledge advances in sociology, 2020)
The Subjectivities and Politics of Occupational Risk links restructuring in three industries to shifts in risk subjectivities and politics, both within workplaces and within the safety management and regulative spheres, often leading to conflict and changes in law, political discourses and management approaches. The state and corporate governance emphasis on worker participation and worker rights, internal responsibility, and self-regulative technologies are understood as corporate and state efforts to reconstruct control and responsibility for Occupational Health and Safety (OHS) risks within the context of a globalized neoliberal economy. Part 1 presents a conceptual framework for understanding the subjective bases of worker responses to health and safety hazards using Bourdieu’s concept of habitus and the sociology of risk concepts of trust and uncertainty. Part 2 demonstrates the restructuring arguments using three different industry case studies of multiple mines, farms and auto parts plants. The final chapter draws out the implications of the evidence and theory for social change and presents several recommendations for a more worker-centred politics of health and safety.The book will appeal to social scientists interested in health and safety, work, employment relations and labour law, as well as worker advocates and activists. --Publisher's description. Contents: 1. Introduction and Research MethodsPart 1: Risk Subjectivities and Practices2. Identifying Hazards and Judging Risk3. Taking Risks or Taking a Stand: Interests, Power and IdentityPart 2: Case Studies of Health and Safety in Hard Rock Mining, Family Farming and Auto Parts Manufacturing 4. Transforming the Mining Labour Process: Transforming Risk and its Social Construction5. Reconstructing Miner Consent: Management Objectives and Strategies6. The Transformation and Fragmentation of Canadian Agriculture7. Health and Safety in Farming8. The Transformation of Production and Health and Safety in Auto Parts Manufacturing.9. Participation and Control in a Non-Union Auto Parts Firm10. Conclusion and Implications for Change.

The Canadian Labour Movement: A Short History - Heron, Craig; Smith, Charles W. (Lorimer, 2020)
In The Canadian Labour Movement, historian Craig Heron and political scientist Charles Smith tell the story of Canada's workers from the midnineteenth century through to today, painting a vivid picture of key developments, such as the birth of craft unionism, the breakthroughs of the fifties and sixties, and the setbacks of the early twenty-first century. The fourth edition of this book has been completely updated with a substantial new chapter that covers the period from the great recession of 2008 through to 2020. In this chapter, Smith describes the fallout of the financial crisis, how Stephen Harper's government restricted labour rights, the rise of the "gig economy" and precarious work, and the continued de-industrialization in the private sector. These pressures contributed to fracturing the movement, as when Unifor, the largest private sector union, split from the Canadian Labour Congress, the established "house of labour." Through it all, rank-and-file union members have fought for better conditions for all workers, including through campaigns like the fight for a $15 minimum wage. --Publisher's description

Work, Industry, and Canadian Society - Krahn, Harvey; Hughes, Karen; Lowe, Graham S. (Top Hat, 2020)
Work, Industry, and Canadian Society provides a sociological introduction to the history, nature, organization, and management of work in Canada. The eighth edition expands and adds new coverage on the biggest work challenges faced now and in the future, such as Canada’s aging and increasingly diverse workforce, the work experiences of Canada’s Indigenous peoples, the rise of the app-based “gig” economy, and how technology will continue to impact future jobs and work organization. The new edition continues to incorporate recent empirical findings, review new and ongoing theoretical and policy debates, and provide a more international perspective. As the world of work continues to change rapidly, all trends and statistics have been updated. These authors are well regarded for their teaching and research, and their years of experience are evident in this comprehensive volume on the past, present, and future of work in Canada. --Publisher's description. Contents: Historical perspectives on work -- Contemporary debates and issues -- Canadian employment trends -- Good jobs, bad jobs, no jobs -- Labour markets: opportunities and inequality -- Gender and paid employment -- Household, family, and caring work -- Organizing and managing work -- In search of new managerial paradigms -- Conflict and control in workplace -- Unions and industrial relations -- Alternative approaches to organizing work -- Work values and work orientations -- Job satisfaction, alienation, and work-related stress.

Take the Plant, Save the Planet - Leah, Tony; Panitch, Leo; McQuaig, Linda; Gindin, Sam; Keetch, Rebecca; Wells, Jennifer; Christianson, Russ (Socialist Interventions pamphlet series, 2020)
On November 26, 2018, General Motors announced a number of plant closures in North America, the largest of which was in Oshawa, Ontario. The Oshawa facility, once the largest auto complex on the continent, was to end all its assembly operations by the end of 2019. ...This pamphlet provides background material on Oshawa and joins Green Jobs Oshawa in encouraging workers elsewhere to prepare now for the threats to their jobs and productive capacity that will inevitably come. --From introduction

Closing Sysco: Industrial Decline in Atlantic Canada's Steel City - MacKinnon, Lachlan (Studies in Atlantic Canada history, 2020)
This book is a history of deindustrialization and working-class resistance in the Cape Breton steel industry between 1945 and 2001. The Sydney Steel Works is at the heart of this study - having existed in tandem with Cape Breton's larger coal operations since the early twentieth century. Chapters explore the multi-faceted nature of deindustrialization, the internal politics of the steelworkers' union, successful efforts to nationalize the mill in 1967, the years in transition under public ownership, and confrontations over health, safety, and environmental degradation in the 1990s and 2000s. The book moves beyond the moment of closure to trace the cultural, historical, and political ramifications of deindustrialization as they continue to play out in post-industrial Cape Breton Island. This represents a significant intervention into the international literature on deindustrialization, pushing scholarship beyond the bounds of political economy and cultural change to begin tackling issues of bodily health, environment, and historical memory in post-industrial places. -- Publisher's description
Keywords: 1900-1999; Acier Industrie et commerce Nouvelle-Écosse Sydney Histoire 20e siècle; Acier Industrie et commerce Nouvelle-Écosse Sydney Personnel Conditions sociales 20e siècle; Deindustrialization; Deindustrialization Nova Scotia Sydney History 20th century; Deindustrialization Social aspects; Deindustrialization Social aspects Nova Scotia Sydney; Désindustrialisation Aspect social Nouvelle-Écosse Sydney; Désindustrialisation Nouvelle-Écosse Sydney Histoire 20e siècle; History; Nova Scotia Sydney; Plant shutdowns; Plant shutdowns Nova Scotia Sydney History 20th century; Social conditions; Steel industry and trade; Steel industry and trade Nova Scotia Sydney Employees Social conditions 20th century; Steel industry and trade Nova Scotia Sydney History 20th century; Sydney (N.-É.) Conditions sociales 20e siècle; Sydney (N.S.) Social conditions 20th century; Sydney Steel Corporation; Usines Fermeture Nouvelle-Écosse Sydney Histoire 20e siècle

The Violence of Work: New Essays in Canadian and US Labour History - Milloy, Jeremy; Sangster, Joan (2020)
From mining to sex work and from the classroom to the docks, violence has always been a part of work. This collection of essays highlights the many different forms and expressions of violence that have arisen under capitalism in the last two hundred years, as well as how historians of working-class life and labour have understood violence. The editors draw together diverse case studies, integrating analysis of class, age, gender, sexuality, and race into the scholarship. Essays span the United States and Canadian border, exploring gender violence, sexual harassment, the violent kidnapping of union organizers, the violence of inadequate health and safety protections, the culture of violence in state institutions, the mythology of working-class violence, and the changing nature of violence in extractive industries. The Violence of Work theorizes and historicizes violence as an integral part of working life, making it possible to understand the full scope and causes of workplace violence over time. --Publisher's description, Contents: Introduction: Accounting for violence / Jeremy Milloy -- The perils of sex work in Montreal: seeking security and justice in the face of violence, 1810-1842 / Mary Anne Poutanen -- The rules of discipline: workers and the culture of violence in progressive-era reform schools / James Schmidt -- The "new solution": anti-labour kidnapping, D.B. McKay, and the legacy of the second Seminole War / Chad Pearson -- Billy Gohl: labour, violence, and myth in the early twentieth-century Pacific Northwest / Aaron Goings -- Slow violence and hidden injuries: the work of strip mining in the American west / Ryan Driskell Tate -- The murder of Lori Dupont : violence, harassment, and occupational health and safety in Ontarion / Sarah Jessup -- "By the nuimbers" : workers' compensation and the (further) conventionalization of workplace violence / Robert Storey -- Gender violence in the hospitality industry: panic buttons, pants, and protest / Emily E. LB. Twarog.

À l'avant garde du progrès: I'institut professionnel de la fonction publique du Canada 1920-2020 - Russell, Jason (Between the Lines, 2020)
Le 6 février 1920, un petit groupe d’employés de la fonction publique se réunit pour la première fois afin de former une association professionnelle. Un siècle plus tard, l’Institut professionnel de la fonction publique du Canada (IPFPC) est un agent négociateur représentant près de 60 000 travailleurs du secteur public dont les efforts pour le bien collectif améliorent la vie de chaque Canadien. Publié à l’occasion du 100e anniversaire de fondation de l’IPFPC, À l’avant-garde du progrès dresse le portrait complet de son évolution, de 1920 à aujourd’hui, et lève le voile sur un pan souvent négligé de l’histoire syndicale nord-américaine. L’auteur, Jason Russell, s’appuie sur une abondante collection de sources, dont des documents d’archives et des témoignages de dizaines de membres actuels et passés de l’IPFPC. Marquée par des réussites et semée d’embûches, l’histoire est complexe et racontée avec clarté et modération. Après des décennies de changements démographiques et générationnels, de booms et de crises économiques et de bouleversements politiques, les membres de l’IPFPC entament les cent prochaines années guidés par la même mission importante que celle qui les a inspirés jusqu’à présent : militer pour une justice sociale et économique pour le bien de tous les Canadiens et Canadiennes. --Résumé de l'éditeur

Leading Progress: The Professional Institute of the Public Service of Canada, 1920-2020 - Russell, Jason (Between the Lines, 2020)
On February 6, 1920, a small group of public service employees met for the first time to form a professional association. A century later, the Professional Institute of the Public Service Canada (PIPSC) is a bargaining agent representing close to 60,000 public sector workers, whose collective efforts for the public good have touched the lives of every Canadian. Published on the centennial of PIPSC’s founding, Leading Progress is the definitive account of its evolution from then to now—and a rare glimpse into an under-studied corner of North American labour history. Researcher Dr. Jason Russell draws on a rich collection of sources, including archival material and oral history interviews with dozens of current and past PIPSC members. The story that unfolds is a complex one, filled with success and struggle, told with clarity and even-handedness. After decades of demographic and generational shifts, economic booms and busts, and political sea change, PIPSC looks toward its next hundred years with its mission as strong as ever: to advocate for social and economic justice that benefits all Canadians. --Publisher's description

Inequality in Canada: The History and Politics of an Idea - Sager, Eric W. (McGill-Queen's studies in the history of ideas, 2020)
Economic inequality is one of the great issues of our era. But what is inequality? Eric Sager argues that inequality is more than the distribution of income and wealth. Inequality is the idea that there are wide gaps between rich and poor, that the gaps are both an economic problem and a social injustice, and that the problem can be either eliminated or reduced. This idea arose in a transatlantic world, in the long evolution of political economy in Britain and the United States from classical economics to the emerging welfare economics of the twentieth century. Within this transatlantic frame inequality took a distinct form in Canada. It appeared among radical reformers and republicans in the 1830s. It arose in a critique of wealth among Protestant thinkers and their moral imperatives. The idea appeared among labour radicals and reformers who interpreted the conflict between capital and labour as a problem of distribution. For social gospelers inequality was a simplifying frame that made sense of an alien modernity of industry, urbanism, and class conflict. A tradition of idealist thought persisted in the twentieth century, sustaining the idea of inequality despite deep silences among Canadian economists. The idea appeared forcefully in social Catholicism in Quebec, and then waned in the political and intellectual justifications of the social security state. In the new era of inequality in our century, a political solution may rest upon the recovery of an older ethical idealism and in a historically-informed egalitarian politics."-- Publisher's description
Keywords: Canada; Classes sociales Canada; Equality; Equality Canada History; Equality Political aspects Canada History; History; Social classes; Social classes Canada; Égalité (Sociologie) Aspect politique Canada Histoire; Égalité (Sociologie) Canada Histoire

Chicken Girl - Smith, Heather (Penguin Random House Canada, 2020)
Poppy used to be an optimist. But after a photo of her dressed as Rosie the Riveter is mocked online, she's having trouble seeing the good in the world. As a result, Poppy trades her beloved vintage clothes for a feathered chicken costume and accepts a job as an anonymous sign waver outside a restaurant. There, Poppy meets six-year-old girl Miracle, who helps Poppy see beyond her own pain, opening her eyes to the people around her: Cam, her twin brother, who is adjusting to life as an openly gay teen; Buck, a charming photographer with a cute British accent and a not-so-cute mean-streak; and Lewis a teen caring for an ailing parent, while struggling to reach the final stages of his gender transition. As the summer unfolds, Poppy stops glorifying the past and starts focusing on the present. But just as she comes to terms with the fact that there is good and bad in everyone, she is tested by a deep betrayal. -- Publisher's description

How to Pronounce Knife: Stories - Thammavongsa, Souvankham (Penguin Random House Canada, 2020)
Named one of Time's Must-Read Books of 2020, and featuring stories that have appeared in Harper's, Granta, The Atlantic, and The Paris Review, this revelatory book of fiction from O. Henry Award winner Souvankham Thammavongsa establishes her as an essential new voice in Canadian and world literature. Told with compassion and wry humour, these stories honour characters struggling to find their bearings far from home, even as they do the necessary "grunt work of the world." A young man painting nails at the local salon. A woman plucking feathers at a chicken processing plant. A father who packs furniture to move into homes he'll never afford. A housewife learning English from daytime soap operas. In her stunning Giller Prize-winning debut book of fiction, Souvankham Thammavongsa focuses on characters struggling to make a living, illuminating their hopes, disappointments, love affairs, acts of defiance, and above all their pursuit of a place to make their own. In spare, intimate prose charged with emotional power and a sly wit, she paints an indelible portrait of watchful children, wounded men, and restless women caught between cultures, languages, and values. As one of Thammavongsa's characters says, "All we wanted was to live." And in these stories, they do—brightly, ferociously, unforgettably. A daughter becomes an unwilling accomplice in her mother's growing infatuation with country singer Randy Travis. A former boxer finds a chance at redemption while working at his sister's nail salon. A school bus driver must grapple with how much he's willing to give up in order to belong. And in the title story, a young girl's unconditional love for her father transcends language. Tender, uncompromising, and fiercely alive, How to Pronounce Knife establishes Souvankham Thammavongsa as one of the most important voices of her generation. --Publisher's description
Keywords: Audiobooks; Downloadable audio books; Livres audio; Nouvelles canadiennes; Short stories Women authors; Short stories, Canadian; Écrits de femmes

Closing the Enforcement Gap: Improving Employment Standards Protections for People in Precarious Jobs - Vosko, Leah F.; Closing the Enforcement Gap Research Group; Grundy, John; Akkayamak, Guliz; Noack, Andrea M.; Casey, Rebecca; Hoe, Alice; Hall, Alan; Tucker, Eric; Condratto, Shelley; Mirchandani, Kiran; Soni-Sinha, Urvashi; et al. (Studies in comparative political economy and public policy, 2020)
The nature of employment is changing: low wage jobs are increasingly common, fewer workers belong to unions, and workplaces are being transformed through the growth of contracting-out, franchising, and extended supply chains. Closing the Enforcement Gap offers a comprehensive analysis of the enforcement of employment standards in Ontario. Adopting mixed methods, this work includes qualitative research involving in-depth interviews with workers, community advocates, and enforcement officials; extensive archival research excavating decades of ministerial records; and analysis of a previously untapped source of administrative data collected by Ontario’s Ministry of Labour. The authors reveal and trace the roots of a deepening "enforcement gap" that pervades nearly all aspects of the regime, demonstrating that the province’s Employment Standards Act (ESA) fails too many workers who rely on the floor of minimum conditions it was devised to provide. Arguably, there is nothing inevitable about the enforcement gap in Ontario or for that matter elsewhere. Through contributions from leading employment standards enforcement scholars in the US, the UK, and Australia, as well as Quebec, Closing the Enforcement Gap surveys innovative enforcement models that are emerging in a variety of jurisdictions and sets out a bold vision for strengthening employment standards enforcement. -- Publisher's description.

Histoire du taxi à Montréal : des taxis jaunes à UberX - Warren, Jean-Philippe (Essai, 2020)
Comme toutes les grandes villes occidentales, Montréal fourmille de taxis qui parcourent les rues, font la navette entre l'aéroport et le centre-ville, attendent près des stations de métro, des hôpitaux et des grands hôtels. Trains, tramways, autobus, métros et vélos de Montréal ont eu droit à leur histoire, mais pas les taxis. Le monde du taxi est pourtant un sujet riche et complexe, un carrefour où se rencontrent plusieurs spécialisations de l'histoire : urbaine, politique, économique, sans oublier le travail et l'immigration. Depuis sa voiture, le chauffeur ou la chauffeuse est témoin des rapports tendus entre le travailleur et l'État, la ville et les citoyens, les quartiers excentrés et le centre-ville, le peuple et les élites. Il est aussi témoin des luttes entre la majorité francophone et les minorités culturelles, des mutations technologiques et de l'essor du transport en commun. Le monde du taxi, c'est aussi et surtout des travailleurs qui forment une catégorie sociale unique et qui pratiquent un métier rempli de paradoxes. Au fil de son enquête, faite de recherches sur l'industrie et d'entretiens avec ses acteurs, Jean-Philippe Warren en est venu à la conclusion que le chauffeur de taxi est la dernière incarnation du cowboy : libre de ses mouvements, de son emploi du temps, mais prisonnier de quantité de facteurs. Il peut arrêter de travailler quand il veut et travaille sans cesse. Il a toujours de l'argent dans ses poches, mais est pauvre. Il veut que l'État intervienne pour le protéger, mais exècre les régulations. Il pratique un métier monotone, mais rempli d'imprévus. Il est à la fois entouré de monde et seul. S'ajoutant à la diversité ethnique des membres de la profession, ces paradoxes créent une sous-culture absolument fascinante où se jouent des luttes de pouvoir économique et de contrôle territorial. Une sous-culture tout aussi difficile à intégrer qu'à quitter. En utilisant les ressources combinées de l'histoire et des sciences sociales, en mêlant l'examen des archives et l'enquête de terrain, cette première histoire du taxi à Montréal débouche sur un portrait inédit de la ville. Elle se veut aussi une contribution à la compréhension d'un monde qui cultive les extrêmes et qui, s'il veut se transformer pour le mieux, pour le bien-être de ses travailleurs, de leurs familles et des usagers, doit s'appuyer sur des données tangibles et une histoire critique. --Publisher's description
Keywords: History; Québec Montréal; Taxicabs; Taxicabs Québec (Province) Montréal History; Taxis Québec (Province) Montréal Histoire

Canadian Political Economy - Whiteside, Heather (University of Toronto Press, 2020)
In Canadian Political Economy, experts from a number of disciplinary backgrounds come together to explore Canada's empirical political economy and the field's contributions to theory and debate. Considering both historical and contemporary approaches to CPE, the contributors pay particular attention to key actors and institutions, as well as developments in Canadian political-economic policies and practices, explored through themes of changes, crises, and conflicts in CPE. Offering up-to-date interpretations, analyses, and descriptions, Canadian Political Economy is accessibly written and suitable for students and scholars. In 17 chapters, the book's topics include theory, history, inequality, work, free trade and fair trade, co-operatives, banking and finance, the environment, Indigeneity, and the gendered politics of political economy. Linking longstanding debates with current developments, this volume represents both a state-of-the-discipline and a state-of-the-art contribution to scholarship. -- Publisher's description
Keywords: 2000-2099; Canada; Canada Conditions économiques 21e siècle; Canada Economic conditions 21st century; Canada Politics and government 21st century; Canada Politique et gouvernement 21e siècle; Economic history; Economics; Economics Canada; Politics and government; Économie politique Canada

Winnipeg 1919: The Strikers' Own History of the Winnipeg General Strike - Penner, Norman (Lorimer, 2019)
The most important primary document from the Winnipeg General Strike now back in print with a new introduction on the occasion of the strike's 100th anniversary On May 15, 1919 workers from across Winnipeg, ranging from metal workers to telephone operators, united to spark the largest worker revolt in Canadian history. Even the Winnipeg police voted to join the strike, although they remained on duty at the request of the strike committee in order to prevent martial law. Approximately 30,000 workers walked off the job over the next six weeks, and the city was overtaken by lively demonstrations and marches in what the media, the city's leaders, and the federal government called a "Bolshevik uprising." The clash ended violently when RCMP on horseback charged and shot into a crowd of striking workers resulting in deaths, beatings, and arrests. The strike was called off and workers returned to their jobs without having earned the rights to higher wages and collective bargaining. Following the strike, union leaders published this account of the events leading up to and during the strike. Their volume is the most significant primary source describing the workers' experience of the strike. This book offers the full document in its original format along with an introduction to the 1974 edition by labour historian and activist Norman Penner. His essay has had a major impact on later research. This volume also includes a new introduction by historian Christo Aivalis discussing how the lessons learned in 1919 remain relevant today. Also included in this book are the key documentary photographs of strike events, including a minute-by-minute sequence showing the final RCMP fatal assault on the strikers. --Publisher's description

Everyday Transgressions: Domestic Workers' Transnational Challenge to International Labor Law - Blackett, Adelle (ILR Press, an imprint of Cornell University Press, 2019)
Adelle Blackett tells the story behind the International Labour Organization's (ILO) Decent Work for Domestic Workers Convention No. 189, and its accompanying Recommendation No. 201 which in 2011 created the first comprehensive international standards to extend fundamental protections and rights to the millions of domestic workers laboring in other peoples' homes throughout the world. As the principal legal architect, Blackett is able to take us behind the scenes to show us how Convention No. 189 transgresses the everyday law of the household workplace to embrace domestic workers' human rights claim to be both workers like any other, and workers like no other. In doing so, she discusses the importance of understanding historical forms of invisibility, recognizes the influence of the domestic workers themselves, and weaves in poignant experiences, infusing the discussion of laws and standards with intimate examples and sophisticated analyses. Looking to the future, she ponders how international institutions such as the ILO will address labor market informality alongside national and regional law reform. Regardless of what comes next, Everyday Transgressions establishes that domestic workers' victory is a victory for the ILO and for all those who struggle for an inclusive, transnational vision of labor law, rooted in social justice. --Publisher's description
Keywords: Decent work; Domestic work; Employées de maison Droit Législation; Foreign workers; Foreign workers Legal status, laws, etc; Hausarbeit; Hauswirtschaftsgehilfin; Household employees Legal status, laws, etc; International labour law; Internationales Arbeitsrecht; Labor laws and legislation, International; Legal status; Travail (Droit international) Législation; Travailleurs étrangers Droit Législation; Übereinkommen über menschenwürdige Arbeit für Hausangestellte 2011 Juni 16

A Diminished Roar: Winnipeg in the 1920s - Blanchard, Jim (University of Manitoba Press, 2019)
The third instalment in Jim Blanchard's popular history of early Winnipeg, 'A Diminished Roar' presents a city in the midst of enormous change. Once the fastest growing city in Canada, by 1920 Winnipeg was losing its dominant position in western Canada. As the decade began, Winnipeggers were reeling from the chaos of the Great War and the influenza pandemic. But it was the divisions exposed by the 1919 Winnipeg General Strike which left the deepest marks. As Winnipeg wrestled with its changing fortunes, its citizens looked for new ways to imagine the city's future and identity. Beginning with the opening of the magnificent new provincial legislature building in 1920, A Diminished Roar guides readers through this decade of political and social turmoil. At City Hall, two very different politicians dominated the scene. Winnipeg's first Labour mayor, S.J. Farmer, pushed for more public services. His rival, Ralph Webb, would act as the city's chief 'booster' as mayor, encouraging U.S. tourists with the promise of 'snowballs and highballs.' Meanwhile, promoters tried to rekindle the city's spirits with plans for new public projects, such as a grand boulevard through the middle of the city, a new amusement park, and the start of professional horse racing. In the midst of the Jazz Age, Winnipeg's teenagers grappled with 'problems of the heart, ' and social groups like the Gyro Club organized masked balls for the city's elite. --Publisher's description
Keywords: 1900-1999; Années vingt (Vingtième siècle); Electronic books; HISTORY / Canada / Post-Confederation (1867-); History; Manitoba Winnipeg; Nineteen twenties; Winnipeg (Man.) History 20th century

Land of Triumph and Tragedy: Voices of the Italian Fallen Workers: A Century of Italian Immigration to Canada: Immigrants Who Made It and Those Who Perished Trying - Breda, Paola; Toppan, Marino (Verità, 2019)
The Embassy of Italy, the Consulate General of Italy in Toronto and Villa Charities join together with authors Paola Breda and Marino Toppan to present a ground-breaking new history of the Italian-Canadian immigration experience, finally including the previously untold story of the thousands of Italian Fallen Workers who died building this beautiful country — a story that’s destined to become a new piece of Canadian History. Compiled after decades of research by Toppan, this epic new volume includes countless contributions from across the country, from scholars of Italian-Canadian history and the families of the fallen themselves. This ground breaking new book includes profiles of those in the Italian community in Canada who triumphed with incredible successes, those who died in tragic circumstances, as well as in-depth studies on immigration patterns, labour history, socio-adaptive patterns, labour action, strife and hardships experienced, and many more themes in the Italian-Canadian identity. It even coins a new phrase: Canadianità! --Publicity release, May 23, 2019

1919 : une histoire graphique de la grève générale de Winnipeg - Collectif d'histoire graphique; Lester, David; Michaud, William; Graphic History Collective (Between the Lines, 2019)

Clearing the Plains: Disease, Politics of Starvation, and the Loss of Aboriginal Life - Daschuk, James W. (Canadian plains studies, 2019)
Revealing how Canada's first Prime Minister used a policy of starvation against Indigenous people to clear the way for settlement, the multiple award-winning Clearing the Plains sparked widespread debate about genocide in Canada. In arresting, but harrowing, prose, James Daschuk examines the roles that Old World diseases, climate, and, most disturbingly, Canadian politics—the politics of ethnocide—played in the deaths and subjugation of thousands of Indigenous people in the realization of Sir John A. Macdonald’s "National Dream. " It was a dream that came at great expense: the present disparity in health and economic well-being between Indigenous and non-Indigenous populations, and the lingering racism and misunderstanding that permeates the national consciousness to this day. This new edition of Clearing the Plains has a foreword by Pulitzer Prize winning author, Elizabeth Fenn, an opening by Niigaanwewidam James Sinclair, and explanations of the book’s influence by leading Canadian historians. -- Publisher's description.
Keywords: Aspect sanitaire; Canada; Canada (Ouest); Canada, Western; Colonisation; Diseases; Diseases. Indians of North America; Government relations. Indians of North America; Government relations. Indians, North American; Health and hygiene; Health and hygiene. Ethnische Beziehungen Gesundheit Indianer Indianerpolitik Kolonisation Sozialer Wandel Indianerpolitik Ethnozid Indianer Krankheit Hunger Sozialer Wandel Indigenous peoples in Canada. Indiens d'Amrique; Health aspects. Ethnic relations. Indians of North America. Indians of North America; Histoire. Canada (Ouest); Histoire. Genre/Form: History. History; Histoire. Indiens d'Amrique; History. Indians of North America; Indians of North America; Maladies; Relations avec l'tat. Canada (Ouest); Relations interethniques; Sant et hygine; history. Colonization; history. Communicable Diseases; history. Health Status. Disease Outbreaks; history. Population Dynamics. Colonialism

They Call Me George: The Untold Story of Black Train Porters and the Birth of Modern Canada - Foster, Cecil (Biblioasis, 2019)
A historical work of non-fiction that chronicles the little-known stories of black railway porters-the so-called "Pullmen" of the Canadian rail lines. The actions and spirit of these men helped define Canada as a nation in surprising ways, effecting race relations, human rights, North American multiculturalism, community building, the shape and structure of unions, and the nature of travel and business across the US and Canada. Drawing on the stories and legends of several of these influential early black Canadians, this book narrates the history of a very visible, but rarely considered, aspect of black life in railway-age Canada. These porters, who fought against the idea of Canada as White Man's Country, open only to immigrants from Europe, fought for and won a Canada that would provide opportunities for all its citizens. -- Publisher's description. Contents: Introduction -- Leaving the station: Stan Grizzle's legacy of social change -- The railways are always hiring: working in white man's country -- "Did you ring, Sir?": Modern luxury and black labour -- The coloured commonwealth: reckoning with ah racist past -- "I know nothing about that": Legislating the colour line -- The ending of empire: Reimagining immigration -- Pressuring parliament: a new kind of Canadian citizenship -- A Creolized country: the black British of the West Indies -- Permanent residence: social identity and the state -- Demerits and deadheading: the rail companies' unreasonable demands -- An uphill battle: Pushing for policy changes -- Fair consideration: The porters gain new ground -- The porters' final fight: A multicultural country -- Beyond the rails: The battle for black identity -- Conclusion: A multicultural brotherhood fulfilling a dream -- Afterword: Appreciating the legacy -- Endnotes -- Index.
Keywords: Black Canadians History; Black people; Black people Canada History; Canada; HISTORY Canada General; History; Noirs canadiens Histoire; Personnes noires Canada Histoire; Porters; Porters Canada History; Porteurs de bagages Canada Histoire; Préposés aux pullmans Canada Histoire; Préposés de service ferroviaire Canada Histoire; Pullman porters; Pullman porters Canada History; Train attendants; Train attendants Canada History

Beginnings to 1866 - Girard, Philip; Phillips, Jim; Brown, R. Blake (A History of Law in Canada, 2019)
This book, the first of 2 volumes, presents the history of law in what is now Canada, from the first European contacts with northern North America in the very early sixteenth century to immediately before Confederation. Divided into four parts, the book first looks at the roots of Canada’s three legal traditions, Indigenous, French and English, in North America, France and England. Part 2 examines the period down to 1701 and the signing of the treaty known as the Great Peace of Montreal in 1701, during which New France was established. Part 3 deals with the eighteenth century – Anglo-French conflict, New France until 1760, the establishment and growth of English colonies of settlement, and, throughout, relations with indigenous peoples and governance of indigenous nations. Part 4 is devoted to the British North American period, after 1815. Indigenous people are central of the narrative throughout, including after 1815 when their influence waned as their land base was largely lost in central and eastern Canada. Included in Part 4 are the Red River settlement and early British Columbia. Although the background to this history are the well-known major political, military, social and economic transformations of this part of North America, the book is principally a legal history set against and integrated with that background. Court systems, the judiciary, the legal professions, are dealt with in every period and for each of the legal traditions, and the areas of law covered include criminal, family, constitutional, commercial, land, succession, and civil and criminal procedure. This volume combines the remarkable flowering of scholarship on Canadian legal history, so much of it fostered and published by the Osgoode Society over 35 years, and much new research. --Publisher's description
Keywords: Canada; Droit Canada Histoire; History; Law; Law Canada History

Direct Action Gets the Goods: A Graphic History of the Strike in Canada - Graphic History Collective; Balmes, Althea; Hill, Gord; Keresztesi, Orion; Lester, David (2019)
Art has always played a significant role in the history of the labour movement. Songs, stories, poems, pamphlets, and comics, have inspired workers to take action against greedy bosses and helped shape ideas of a more equal world. They also help fan the flames of discontent. Radical social change doesn't come without radical art. It would be impossible to think about labour unrest without its iconic songs like "Solidarity Forever" or its cartoons like Ernest Riebe's creation, Mr. Block. In this vein, The Graphic History Collective has created an illustrated chronicle of the strike-the organized withdrawal of labour power-in Canada. For centuries, workers in Canada-Indigenous and non-Indigenous, union and non-union, men and women-have used the strike as a powerful tool, not just for better wages, but also for growing working-class power. This lively comic book will inspire new generations to learn more about labour and working-class history and the power of solidarity. --Publisher's description

1919: A Graphic History of the Winnipeg General Strike - Graphic History Collective; Lester, David (Between the Lines, 2019)
In May and June 1919, more than 30,000 workers walked off the job in Winnipeg, Manitoba. They struck for a variety of reasons-higher wages, collective bargaining rights, and more power for working people. The strikers made national and international headlines, and they inspired workers to mount sympathy strikes in many other Canadian cities. Although the strike lasted for six weeks, it ultimately ended in defeat. The strike was violently crushed by police, in collusion with state officials and Winnipeg's business elites. One hundred years later, the Winnipeg General Strike remains one of the most significant events in Canadian history. This comic book revisits the strike to introduce new generations to its many lessons, including the power of class struggle and solidarity and the brutal tactics that governments and bosses use to crush workers' movements. The Winnipeg General Strike is a stark reminder that the working class and the employing class have nothing in common, and the state is not afraid to bloody its hands to protect the interests of capital. In response, working people must rely on each other and work together to create a new, more just world in the shell of the old. --Publisher's description,     Contents: Preface: Revisiting the workers' revolt by the Graphic history collective -- Acknowledgements -- Introduction: The Winnipeg general strike at 100 by James Naylor -- 1919: A graphic history of the Winnipeg general strike by the Graphic History Collective and David Lester -- The art of labour history: Notes on drawing 1919 by David Lester -- The character of class struggle in Winnipeg: A photo-essay -- Notes -- Bibliography -- Contributors.

Bureaucratic Manoeuvres: The Contested Administration of the Unemployed - Grundy, John (Studies in Comparative Political Economy and Public Policy, 2019)
In Bureaucratic Manoeuvres, John Grundy examines profound transformations in the governance of unemployment in Canada. While policy makers previously approached unemployment as a social and economic problem to be addressed through macroeconomic policies, recent labour market policy reforms have placed much more emphasis on the supposedly deficient employability of the unemployed themselves, a troubling shift that deserves close, critical attention. Tracing a behind-the-scenes history of public employment services in Canada, Bureaucratic Manoeuvres shows just how difficult it has been for administrators and frontline staff to govern unemployment as a problem of individual employability. Drawing on untapped government records, it sheds much-needed light on internal bureaucratic struggles over the direction of labour market policy in Canada and makes a key contribution to Canadian political science, economics, public administration, and sociology.

Cracking Labour's Glass Ceiling: Transforming Lives Through Women's Union Education - Hanson, Cindy; Paavo, Adriane; Sisters in Labour Education (Labour in Canada (Halifax, N.S.), 2019)
Although the health of the trade union movement may rest on its ability to include women in membership and leadership, little attention has been paid to women-only labour education. This original collection contains vibrant example of labour education events and the women involved who develop, implement, research, evaluate and facilitate at them. All the contributors speak from first-hand experience with women-only programs in unions across Canada, the United States and the world. They identify the methods used in pursuit of learner empowerment and transformation, and frankly discuss the outcomes. These real-life examples offer practical guidance and inspiration for all who create and support activist learning within unions and other social-justice organizations. -- Publisher's description

Reading Canadian Women's and Gender History - Janoviček, Nancy; Nielson, Carmen J. (Studies in gender and history, 2019)
Although Canadian womens history is now nearly forty years old, no volume exists that reflects explicitly upon the fields evolution and assesses its historiographical context. This retrospective is not merely summative; the essays in this collection are analytical engagements with the current state of the field, which draw on its rich past to generate new knowledge and propose innovative avenues for inquiry. The dual purposes of this collection are to contemplate the fields past and to contribute productively to its future. These thirteen original essays are written by scholars at all career stages. The diversity of these authors perspectives illustrates the contributions that Canadian scholarship has had in international dialogues about womens and gender history and that it continues to be a vibrant area of research. The collection includes chapters about the principal sub-fields in Canadian womens and gender history, including specialized chapters on Québecois, Indigenous, Black, and immigrant womens histories, religious history, labour history, war and society, history of sexuality, the history of reproductive labour and reproductive justice, two essays on the history of feminism that, taken together, cover the period from 1850 to the present, and a thematic essay on the colonial period. --Publisher's description
Keywords: Canada; Feminism; Feminism Canada History; Feminismus; Femmes Canada Conditions sociales; Femmes Canada Histoire; Femmes Conditions sociales Canada Histoire; Frau; Féminisme Canada Histoire; History; Identité sexuelle Canada Histoire; Kanada; Women; Women Canada History; Women Canada Social conditions; Women Social conditions; Women's studies; Women's studies Canada History; Études sur les femmes Canada Histoire

Unearthing Justice: How to Protect Your Community from the Mining Industry - Kuyek, Joan (Between the Lines, 2019)
The mining industry continues to be at the forefront of colonial dispossession around the world. It controls information about its intrinsic costs and benefits, propagates myths about its contribution to the economy, shapes government policy and regulation, and deals ruthlessly with its opponents. Brimming with case studies, anecdotes, resources, and illustrations, Unearthing Justice exposes the mining process and its externalized impacts on the environment, Indigenous Peoples, communities, workers, and governments. But, most importantly, the book shows how people are fighting back. Whether it is to stop a mine before it starts, to get an abandoned mine cleaned up, to change laws and policy, or to mount a campaign to influence investors, Unearthing Justice is an essential handbook for anyone trying to protect the places and people they love. --Publisher's description
Keywords: Canada; Citizen participation; Environmental policy; Environmental protection; Indigenous peoples; Mineral industries; Mines and mineral resources; Native peoples; Politics and government

Slagflower: Poems Unearthed from a Mining Town - Leduc, Thomas (Latitude 46, 2019)
Debut collection of poetry from Thomas Leduc, City of Greater Sudbury's past Poet Laureate and the fourth generation of a mining family. Stagflower captures a city struggling to grow beyond its past and become more than just a mining town, while reflecting the internal human conflict to be more than family history, more than a past. --Publisher's description. "At one time, this city / had a single plan / for every young man; / a straight, well-worn path / from their front doors / to an open rock face / at the end of a mine shaft. / A path chiselled out of stone, / a path paved in nickel. / Every young man / wanted his millwright ticket, / studied the ticking of gears, / the composition of rock; / had the culture of mining / drilled into him. / Plans were passed down / from lunch pail / to lunch pail. / Fathers and sons dug the same holes / fought the same fights. / How many boys / has this rock hardened / into men." -- Chiselled Out of Stone, poem by Thomas Leduc. Table of contents: Birthmark -- Rite of passage -- Buffalo souls -- The taste of sulfur -- Slagflower.

Magnificent Fight: The 1919 Winnipeg General Strike - Lewycky, Dennis (Fernwood, 2019)
In May 1919, 30,000 Winnipeg workers walked away from their jobs, shutting down large factories, forcing businesses to close and bringing major industries to a halt. Mounted police and hired security, at the behest of the ruling class, violently ended the protest after six weeks. Two men were killed. What started as trade union revolt, the Winnipeg General Strike became a mass protest and was branded as a revolution. In Magnificent Fight, Dennis Lewycky lays out the history of this iconic event, which remains the biggest and longest strike in Canadian history. He analyzes the social, political and economic conditions leading up to the strike. He also illustrates the effects the strike had on workers, unions and all three levels of government in the following decades. Far from a simple retelling of the General Strike, Magnificent Fight speaks to the power of workers' solidarity and social organization. And Lewycky reveals the length the capitalist class and the state went to in protecting the status quo. By retelling the story of the Strike through the eyes of those who witnessed it, Lewycky's account is both educational and entertaining. --Publisher's description

Enforcing Exclusion: Precarious Migrants and the Law in Canada - Marsden, Sarah Grace (Law and society series (Vancouver, B.C.), 2019)
In Canada’s liberal dream, the law extends its benefits to everyone. But the law also determines who is included in that “everyone.” Migrant workers, long welcomed in Canada for their labour, are often excluded from both workplace protections and basic social benefits such as health care, income assistance, and education due to their lack of permanent status. Enforcing Exclusion recasts what migration status means to both the state and to non-citizens. Through interviews with migrants and their advocates, Sarah Marsden shows that migrants face enforcement through law, policy, and practice, affecting their ability to address adverse working conditions and their interactions with institutions such as hospitals, schools, and employment standards boards. Canadian immigration laws create a status hierarchy; those at the bottom experience markedly different access to the protections and benefits of law. This book documents the impact of Canada’s system of migration enforcement on people’s lives and questions the adequacy of human-rights-based responses in addressing its exclusionary effects. -- Publisher's description. Contents: Introduction -- The Creation and Growth of Precarious Migration in Canada: “Illegal” Migration and the Liberal State -- Status, Deportability, and Illegality in Daily Life -- Working Conditions and Barriers to Substantive Remedies -- Exclusion from the Social State: Health, Education, and Income Security -- Multi-Sited Enforcement: Maintaining Subordinate Membership -- Rights and Membership: Toward Inclusion? -- Postscript -- Appendix A: Migrant Participant Profiles -- Appendix B: Sample Interview Script.

Papergirl - McCracken, Melinda; Jackson, Penelope (Roseway Publishing, an imprint of Fernwood Publishing, 2019)
Ten-year-old Cassie lives with her working-class family in 1919 Winnipeg. The Great War and Spanish Influenza have taken their toll, and workers in the city are frustrated with low wages and long hours. When they orchestrate a general strike, Cassie--bright, determined and very bored at school--desperately wants to help. She begins volunteering for the strike committee as a papergirl, distributing the strike bulletin at Portage and Main, and from her corner, she sees the strike take shape. Threatened and taunted by upper-class kids, and getting hungrier by the day, Cassie soon realizes that the strike isn't just a lark--it's a risky and brave movement. With her impoverished best friend, Mary, volunteering in the nearby Labour Café, and Cassie's police officer brother in the strike committee's inner circle, Cassie becomes increasingly furious about the conditions that led workers to strike. When an enormous but peaceful demonstration turns into a violent assault on Bloody Saturday, Cassie is changed forever. Lively and engaging, this novel is a celebration of solidarity, justice and one brave papergirl. -- Publisher's description
Keywords: 1919; Children's stories; Fiction; General Strike, Winnipeg, Man., 1919 Juvenile fiction; Grève générale, Winnipeg, Man., 1919 Romans, nouvelles, etc. pour la jeunesse; Historical fiction; Juvenile works; Manitoba Winnipeg; Papergirls; Papergirls Manitoba Winnipeg Juvenile fiction

Dix concepts pour penser le nouveau monde du travail - Mercure, Daniel; Vultur, Mircea (Collection Sociologie contemporaine, 2019)
Au cours des dernières décennies, de nombreux changements économiques, politiques et culturels ont bouleversé la nature du travail, la manière de l’organiser ainsi que la relation d’emploi. Ces transformations nécessitent de revoir, de critiquer et d’actualiser les principaux concepts à partir desquels la sociologie analyse le monde du travail. Dans cet ouvrage, les concepts revisités sont les suivants : salariat, précarité, informalité, conflit, contrôle et organisation du travail, qualification et compétence, rapport au travail, parcours professionnel, insertion professionnelle, temporalités. Chacun des concepts retenus est analysé selon une perspective critique, qui consiste à remettre en question les assises théoriques et empiriques de ceux-ci, et une perspective analytique, qui vise à arrimer ces concepts fondamentaux aux nouvelles réalités du monde du travail. --Publisher's description
Keywords: COMPETENCE; CONFLIT; CONTROLE; INFORMALITE; Industrial sociology; Methods engineering; ORGANISATION; Organisation du travail; PRECARITE; PROFESSIONNELLE; SALARIAT; Sociologie du travail; Sociologie industrielle; TRAVAIL; Work Simplification; Work environment

Walmart: Diary of an Associate - Meunier, Hugo (Fernwood, 2019)
In 2012, journalist Hugo Meunier went undercover as a Walmart employee for three months in St. Leonard, Quebec, just north of Montreal. In great detail, Meunier charts the daily life of an impoverished Walmart worker, referring to his shifts at the box store giant as “somewhere between the army and Walt Disney.” Each shift began with a daily chant before bowing to customer demands and the constant pressure to sell. Meanwhile Meunier and his fellow workers could not afford to shop anywhere else but Walmart, further indenturing them to the multi-billion-dollar corporation. Beyond his time on the shop floor, Meunier documents the extraordinary efforts that Walmart exerts to block unionization campaigns, including their 2005 decision to close their outlet in Jonquiere, QC, where the United Food and Commercial Workers union had successfully gained certification rights. A decade later he charts the Supreme Court of Canada ruling that exposed the dubious legal ground on which Walmart stood in invoking closure and throwing workers out on the street. In Walmart: Diary of an Associate, Meunier reveals the truths behind Walmart’s low prices. It will make you think twice before shopping there. --Publisher's description

Working Women in Canada: An Intersectional Approach - Nichols, Leslie; Forrest, Anne; Lippel, Katherine; Premji, Stephanie; Tyyskä, Vappu; Aggarwal, Pramila; Ignagni, Esther; Prentice, Susan; Acker, Sandra; Muzzin, Linda; Knight, Melanie; Gabay, Danielle; et al. (Canadian Scholars/Women's Press, 2019)
In this edited collection, Leslie Nichols weaves together the contributions of accomplished and diverse scholars to offer an expansive and critical analysis of women’s work in Canada. Students will use an intersectional approach to explore issues of gender, class, race, immigrant status, disability, sexual orientation, Indigeneity, age, and ethnicity in relation to employment. Drawing from case studies and extensive research, the text’s eighteen chapters consider Canadian industries across a broad spectrum, including political, academic, sport, sex trade, retail, and entrepreneurial work. Working Women in Canada is a relevant and in-depth look into the past, present, and future of women’s responsibilities and professions in Canada. Undergraduate and graduate students in gender studies, labour studies, and sociology courses will benefit from this thorough and intersectional approach to the study of women’s labour. Features include tables, case studies, a glossary of key terms, and chapter introductions and conclusions to assist with student comprehension encourages further learning by concluding each chapter with discussion questions, a list of additional key readings, and an extensive reference list provides a broad portrait of women’s work in Canada with contributions from over 20 scholars. --Publisher's description

Confronting Canadian Migration History - Ross, Daniel (Active History, 2019)
Confronting Canadian Migration History means two things. First, engaging with the history of population movements into, through, and from this territory, and their importance for our history as a multiethnic settler society. This has been one of the central projects of migration historians in Canada in recent decades. Second, to make and maintain a place for that historical knowledge in contemporary discussions of migration, and in doing so confront the present with the past. That latter goal is at the heart of this collection, which assembles in one volume fifteen texts published on ActiveHistory.ca over the last four years. --Publisher's description, Contents: Introduction / Daniel Ross. [Part] 1. Refugee migrations. Canada’s complicated history of refugee reception / Stephanie Bangarth -- Using old photographs to gain new perspectives on refugees, past and present / Sonya de Laat -- When to speak, when to act: Reflections on the recent MS St. Louis apology / Andrea Eidinger and Laura Madokoro -- Remembering the Prague Spring refugees / Jan Raska -- Little Bear’s Cree and Canada’s uncomfortable history of refugee creation / Benjamin Hoy. [Part] 2. Migration experiences and representations. Creating the Canadian mosaic / Ryan McKenney and Benjamin Bryce -- Conversations with Egyptian Uber drivers: Why emigrate? Why Canada? / Michael Akladios -- Old stock Canadians: Arab settlers in Western Canada / Sarah Carter -- Not so accidental: Farmworkers, car crashes, and capitalist agriculture / Edward Dunsworth -- Arab-Canadian foodscapes and authenticity / Michael Akladios. [Part] 3. Nativism and exclusion White Supremacy, political violence, and community, 1907 and 2017 / Laura Ishiguro and Laura Madokoro -- Immigration and White Supremacy: Past and present / David Atkinson -- Pork cuts: The sharp edges of nativism in Southern Europe / Aitana Guia -- X-Rays and the discriminatory science of migration / Laura Madokoro -- Baba wore a burqa, and Nona wore a niqab / Franca Iacovetta and Karen Dubinsky.

A Grander Vision: My Life in the Labour Movement - Ryan, Sid (Dundurn, 2019)
A stirring, heartfelt manifesto written by a man who fervently believes in what workers with their civil society allies can achieve for the good of all. Sid Ryan, one of Canada's most courageous and progressive union leaders, draws on the experience of his varied and colourful life to show what is right with the labour movement, what is wrong, and what has to change if it is to avoid becoming irrelevant. He calls for the adoption of Social Movement Unionism, in which labour forges an alliance with other progressive elements in civil society, taking up the cause of young people, precarious workers, and immigrants. He demands a renewed commitment to the NDP, the party that was built by unions, and he argues that the Leap Manifesto should become the pillars of the movement in Canada. --Publisher's description. Contents: Foreword by Gerry Adams -- Growing up in Ireland -- A new life in Canada -- President of CUPE Ontario -- Bob Rae and the social contract -- At home in the world -- OFL president -- The grander vision.
Keywords: Canada. Human rights movements. Labor movement. Progressivism (Canadian politics) Social conditions; Canada. Progressivism (Canadian politics) Human rights movements; Labor movement

Masters and Servants: The Hudson's Bay Company and Its North American Workforce, 1668-1786 - Stephen, Scott P. (University of Alberta Press, 2019)
With Masters and Servants, Scott P. Stephen has revealed startling truths about the men of the Hudson's Bay Company. Rather than dedicating themselves body and soul to the Company's interests, these workers hired out like domestic servants, joining a 'household' with its attendant norms of duty and loyalty. Through painstaking documentary research, Stephen shines welcome light on the lives of these largely overlooked historical actors. The household system produced a remarkably stable political-economic entity, connecting early Canadian resource extraction to larger trends in British imperialism and its emerging social relations. An essential book for labour historians, Masters and Servants will appeal to scholars of early modern Britain, the North American fur trade, Western social history, or business history, and anyone intrigued by the reach of the HBC. -- Publisher's description
Keywords: Canada; Compagnie de la Baie d'Hudson Histoire; Compagnie de la Baie d'Hudson Personnel Histoire; Contract labor; Contract labor Canada History; Employees; Employés de maison Canada Histoire; Employés de maison Grande-Bretagne Histoire; Fourrures Commerce Canada Histoire; Fur trade; Fur trade Canada History; Great Britain; History; Household employees; Household employees Canada History; Household employees Great Britain History; Hudson's Bay Company; Hudson's Bay Company Employees History; Hudson's Bay Company Histoire; Hudson's Bay Company History; Hudson's Bay Company Personnel; Main-d'oeuvre contractuelle Canada 1500-1800; Main-d'œuvre contractuelle Canada Histoire; Serviteurs Canada 1500-1800

Change and Continuity: Canadian Political Economy in the New Millennium - Thomas, Mark P; Vosko, Leah F.; Lyubchenko, Olena; Fanelli, Carlo (Carleton library series, 2019)
In a period characterized by growing social inequality, precarious work, the legacies of settler colonialism, and the emergence of new social movements, Change and Continuity presents innovative interdisciplinary research as a guide to understanding Canada's political economy and a contribution to progressive social change. Assessing the legacy of the Canadian political economy tradition — a broad body of social science research on power, inequality, and change in society — the essays in this volume offer insight into contemporary issues and chart new directions for future study. Chapters from both emerging and established scholars expand the boundaries of Canadian political economy research, seeking new understandings of the forces that shape society, the ensuing conflicts and contradictions, and the potential for social justice. Engaging with interconnected topics that include shifts in immigration policy, labour market restructuring, settler colonialism, the experiences of people with disabilities, and the revitalization of workers' movements, this collection builds upon and deepens critical analysis of Canadian society and considers its application to contexts beyond Canada. --Publisher's description.

The Voice of Labour: A Life in Toronto's Construction Industry - Toppan, Marino; Principe, Angelo; Breda, Paola; Frank Iacobucci Centre for Italian Canadian Studies (Frank Iacobucci Centre for Italian Canadian Studies monograph series., 2019)
The memoirs of union organizer Marino Toppan, during the union organizing days of the residential construction "jungle" in Toronto: 1955-1980.

The Class Politics of Law: Essays Inspired by Harry Glasbeek - Tucker, Eric; Fudge, Judy (Fernwood Publishing, 2019)
For nearly fifty years, Professor Harry Glasbeek has been at the forefront of legal scholars and public intellectuals challenging assumptions and understandings about the injustices embedded in the economic, social, political and legal orders of Western capitalist democracies. His writings and teachings have influenced generations of law students, academics and activists. [This book] brings together eleven incisive contributions from pre-eminent scholars across several disciplines activated by the same desire for democracy and justice that Glasbeek advances, showing how capitalism shapes the law and how the law protects capitalism. This collection foregrounds a class analysis of the laws responses to corporate killing, workplace violence, surveillance, worker resistance and income inequality, among other issues. --Publisher's description
Keywords: Economic aspects. Law; Political aspects. Law; Political aspects. Sociological jurisprudence; Sociological jurisprudence. Law

The Labour Companion: A Bibliography of Printed Sources of Canadian Labour History - Vaisey, G. Douglas (Canadian Committee on Labour History, 2019)
The Canadian Labour Bibliography was an initiative of the Committee on Canadian Labour History in the 1970s. The initial efforts to create an annual reading list of publications dealing with Canadian labour topics led to the creation of The Labour Companion: a bibliography of Canadian labour history based on materials printed from 1950 to 1975. ...The enthusiasm that greeted The Labour Companion prompted Greg Kealey, then teaching at Dalhousie University, to obtain a Social Sciences and Humanities Research Council grant for a much larger product – a comprehensive reading list of books, pamphlets, articles and theses pertinent to the Canadian labour experience (the labour movement, trade unions, living conditions, key legislation, etc.). The intent was to build on the 1980 bibliography and to catalogue the published record on the Canadian working class from earliest times to 1985. Items of more recent vintage have crept in, but no effort was made to deal comprehensively with the entire published record from the late 1980’s forward. To locate that material, researchers should consult Michael Lonardo’s Canadian Labour History Bibliography, an electronic compilation covering 1976 to 2009, found at Memorial University Library https://www.library.mun.ca/qeii/labour/ --Introduction

Disrupting Deportability: Transnational Workers Organize - Vosko, Leah F. (ILR Press, an imprint of Cornell University Press, 2019)
In an original and striking study of migration management in operation, Disrupting Deportability highlights obstacles confronting temporary migrant workers in Canada seeking to exercise their labor rights. Leah F. Vosko explores the effects of deportability on Mexican nationals participating in Canada's Seasonal Agricultural Worker Program (SAWP). Vosko follows the decade-long legal and political struggle of a group of Mexican SAWP migrants in British Columbia to establish and maintain meaningful collective representation. Her case study reveals how modalities of deportability—such as termination without cause, blacklisting, and attrition—destabilize legally authorized temporary migrant agricultural workers. Through this detailed exposé, Disrupting Deportability concludes that despite the formal commitments to human, social, and civil rights to which migration management ostensibly aspires, the design and administration of this "model" temporary migrant work program produces conditions of deportability, making the threat possibility of removal ever-present. --Publisher's description
Keywords: Agricultural laborers, Foreign; Agricultural laborers, Foreign British Columbia; British Columbia; CANADA; Canada; Deportation; Deportation British Columbia; Foreign workers Labor unions Organizing; Foreign workers Labor unions Organizing British Columbia; Foreign workers, Mexican Civil rights Canada; POLITICAL SCIENCE Labor & Industrial Relations; Precarious employment; Precarious employment British Columbia; Travail précaire Colombie-Britannique; Travailleurs agricoles étrangers Colombie-Britannique; Travailleurs étrangers Syndicalisation Colombie-Britannique; Travailleurs étrangers mexicains Droits Canada

The Great Canadian Sedition Trials: The Courts and the Winnipeg General Strike, 1919-1920 - Walker, Jack (University of Manitoba, Faculty of Law, 2019)
Few occurrences in modern times have produced the social upheaval, fear, and hatred that were seen during the Red Scare of 1919. Few events have brought forth such a frenzy of mob action and intolerance, or can match the excitement and drama. One of life's coincidences led me to study one of the manifestations of the Red Scare: the trials that grew out of the Winnipeg General Strike of 1919. Their prominent place in Manitoba's legal history has made them deserving of the title "The Great Canadian Sedition Trials." --From author's prologue

With Glowing Hearts: How Ordinary Women Worked Together to Change the World (and Did) - Webber, Jennifer Wynne (Scirocco Drama, 2019)
When the "Kirkland Lake gals of 1941" begin to share their story with a present-day audience, a siren sounds and they soon find themselves pulled right back into the fateful winter of 1941-42. There, they gather again at the mine-head, waiting for word on the men trapped underground, as their fear and rage builds. When the husband of one of the women is badly injured, their desire to help her quickly leads them into a much larger campaign to help all the families they can. Before long, they've become the heart and soul of a large-scale union-organizing drive that is fuelled by their sheer will - and sometimes giddy enthusiasm - but that is also put to the test by their own inexperience, a bitter strike, and the brutal force of the powers-that-be. --Publisher's description
Keywords: Drama. Labor unions; Drama. Labor unions. Miners. Women labor union members; Drama. Miners; Drama. Women labor union members; Gold Miners' Strike, Kirkland Lake, Ont., 1941-1942; Kirkland Lake; Ontario

A New Kind of Union: Unifor and the Birth of the Modern Canadian Union - Wilson, Fred (Lorimer, 2019)
The inside story of how two important Canadian unions decided to create a new kind of union with new ways of fighting for worker's rights In the fall of 2011 the leaders of two of the biggest Canadian unions, Canadian Auto Workers union (CAW) President Ken Lewenza and Communications, Energy and Paperworkers Union of Canada (CEP) President Dave Coles, found common ground. The labour movement was in crisis. They faced hostile governments, union busting corporations, and declining membership. Something drastic needed to be done. Fred Wilson was an insider in the process by which the leaders of these two large organizations found a way to create a new kind of union, one that was more democratic, more inclusive, and more powerful. Two years later, a new union with a new name was founded. From its inception, Unifor has been a source of optimism and inspiration that a fairer, more secure future can be won for working people, and that unions can adapt to changing times and remain a relevant voice for workplace and social justice. This book describes how this came about. --Publisher's description
Keywords: CAW-Canada; CAW-Canada Histoire,; CAW-Canada History; Canada; Communications, Energy and Paperworkers Union of Canada; Communications, Energy and Paperworkers Union of Canada History; History; Labor unions; Labor unions Canada History; Labor unions Mergers; Labor unions Mergers Canada History; Syndicat canadien des communications, de l'énergie et du papier Histoire; Syndicats Canada Histoire; Syndicats Fusion Canada Histoire; Unifor (Labor union) History; Unifor (Syndicat) Histoire

The Constant Liberal: Pierre Trudeau, Organized Labour, and the Canadian Social Democratic Left - Aivalis, Christo (UBC Press, 2018)
Pierre Elliott Trudeau – radical progressive or unavowed socialist? Christo Aivalis argues that although Trudeau found key influences and friendships on the left, he was in fact a consistently classic liberal, driven by individualist, capitalist principles. Trudeau’s legacy is still divisive. Most scholars portray Trudeau’s ties to unions and the Cooperative Commonwealth Federation as either evidence of communist affinities or as being at the root of his reputation as the champion of a progressive, modern Canada. The Constant Liberal traces the charismatic politician’s relationship with left and labour movements throughout his career. Trudeau worked with leftists in the 1950s to oppose right-wing Quebec premier Maurice Duplessis but against them as prime minister when workers and progressives were seen as obstacles to higher corporate profit margins. While numerous biographies have noted the impact of Trudeau’s engagement with the left on his intellectual and political development, this comprehensive analysis is the first to showcase the interplay between liberalism and democratic socialism that defined his world view – and shaped his effective use of power.The Constant Liberal suggests that Trudeau’s leftist activity was not so much a call for social democracy as a warning to fellow liberals that lack of reform could undermine liberal-capitalist social relations. Historians, political scientists, and political historians are the primary audience for this book, but it will also find readers among scholars of political economy, economics, industrial relations, and Canadian studies. It will appeal broadly to those interested in the life and thinking of Pierre Elliott Trudeau, the Canadian social democratic left, and liberalism/neo-liberalism. --Publisher's description
Keywords: Biography; Canadian History; History; Labour History; Memoirs & Letters; Political Science

Canada’s Labour Market Training System - Barnetson, Bob (Open paths to enriched learning, 2018)
How does the current labour market training system function and whose interests does it serve? In this introductory textbook, Bob Barnetson wades into the debate between workers and employers, and governments and economists to investigate the ways in which labour power is produced and reproduced in Canadian society. After sifting through the facts and interpretations of social scientists and government policymakers, Barnetson interrogates the training system through analysis of the political and economic forces that constitute modern Canada. This book not only provides students of Canada’s division of labour with a general introduction to the main facets of labour-market training—including skills development, post-secondary and community education, and workplace training—but also encourages students to think critically about the relationship between training systems and the ideologies that support them. --Publisher's description.

Le régime des décrets de convention collective au Québec. Quel avenir? - Bernier, Jean (Droit fondamental du travail, 2018)
Cet ouvrage réunit les actes du colloque tenu à Montréal le 11 mai 2017 dans le cadre du congrès de l'Association francophone pour le savoir (ACFAS) sous le thème «Régulation sociale et juridique : quel avenir pour le régime des décrets de convention collective au Québec ??». Il fait le point sur ce régime en vigueur depuis 1934 et régi par la Loi sur les décrets de convention collective. Le livre comprend deux parties. La première, qui porte sur les décrets et les acteurs sociaux, présente un état des lieux aussi bien au plan historique qu'en termes d'expériences très actuelles, éprouvées par les grandes organisations patronales et syndicales. La seconde partie propose un regard vers le futur et met en lumière certaines voies et hypothèses de changements susceptibles de bonifier le régime juridique. --Résumé de l'éditeur
Keywords: Actes de congrès; Collective labor agreements; Collective labor agreements Québec (Province) Congresses; Conference papers and proceedings; Congress; Conventions collectives Québec (Province) Congrès; Québec; Québec (Province). Congresses; Québec (Province). Congrès; proceedings (reports)

Rough Work: Labourers on the Public Works of British North America and Canada, 1842-1882 - Bleasdale, Ruth E. (Canadian social history series, 2018)
The labourers at the heart of this study built the canals and railways undertaken as public works by the colonial governments of British North America and the federal government of Canada between 1841 and 1882. Ruth Bleasdale's fascinating journey into the little-known lives of these labourers and their families reveals how capital, labour and the state came together to build the transportation infrastructure that linked colonies and united an emerging nation. Combining census and community records, government documents, and newspaper archives Bleasdale elucidates the ways in which successive governments and branches of the state intervened between labour and capital and in labourers' lives. Case studies capture the remarkable diversity across regions and time in a labour force drawn from local and international labour markets. The stories here illuminate the ways in which men and women experienced the emergence of industrial capitalism and the complex ties which bound them to local and transnational communities. Rough Work is an accessibly written yet rigorous study of the galvanization of a major segment of Canada's labour force over four decades of social and economic transformation. --Publisher's description

Ontario and Quebec's Irish Pioneers: Farmers, Labourers, and Lumberjacks - Campey, Lucille H. (The Irish in Canada, 2018)
Beginning in the eighteenth century, an increasing number of Irish people sought the better life that Ontario and Quebec offered. Set free from the stifling economic and social constraints that held them back in their homeland, they prospered. And yet, strangely enough, they continue to be mourned as victims. In the second book of the Irish in Canada series, Lucille Campey takes on the victim-ridden mythology of destitute Irish immigrants fleeing the famine of the 1840s. In fact, the Irish influx to Quebec and Ontario began a century earlier. Comprehensive and extensive research has been distilled to produce an informative and lively account of this great immigration saga, whose roots date back to the time of the British Conquest of New France in 1763. -- Publisher's description
Keywords: Canada Emigration and immigration History; Canada, Ontario Emigration and immigration History; Canada, Québec Emigration and immigration History; Emigration and immigration; History; Immigrants; Immigrants Ontario History; Immigrants Québec (Province) History; Ireland; Ireland Emigration and immigration History; Irish; Irish Ontario History; Irish Québec (Province) History; Irlandais Ontario Histoire; Irlandais Québec (Province) Histoire; Irlande Émigration et immigration Histoire; Ontario; Ontario Emigration and immigration History; Ontario Émigration et immigration Histoire; Québec; Québec (Province) Emigration and immigration History; Québec (Province) Émigration et immigration Histoire

Brother - Chariandy, David (Penguin Random House Canada, 2018)
David Chariandy's Brother is his intensely beautiful, searingly powerful, and tightly constructed second novel, exploring questions of masculinity, family, race, and identity as they are played out in a Scarborough housing complex during the sweltering heat and simmering violence of the summer of 1991. With shimmering prose and mesmerizing precision, David Chariandy takes us inside the lives of Michael and Francis. They are the sons of Trinidadian immigrants, their father has disappeared and their mother works double, sometimes triple shifts so her boys might fulfill the elusive promise of their adopted home. Coming of age in The Park, a cluster of town houses and leaning concrete towers in the disparaged outskirts of a sprawling city, Michael and Francis battle against the careless prejudices and low expectations that confront them as young men of black and brown ancestry--teachers stream them into general classes; shopkeepers see them only as thieves; and strangers quicken their pace when the brothers are behind them. Always Michael and Francis escape into the cool air of the Rouge Valley, a scar of green wilderness that cuts through their neighbourhood, where they are free to imagine better lives for themselves. Propelled by the pulsing beats and styles of hip hop, Francis, the older of the two brothers, dreams of a future in music. Michael's dreams are of Aisha, the smartest girl in their high school whose own eyes are firmly set on a life elsewhere. But the bright hopes of all three are violently, irrevocably thwarted by a tragic shooting, and the police crackdown and suffocating suspicion that follow. With devastating emotional force David Chariandy, a unique and exciting voice in Canadian literature, crafts a heartbreaking and timely story about the profound love that exists between brothers and the senseless loss of lives cut short with the shot of a gun. --Publisher's description
Keywords: Canada; Children of immigrants; Children of immigrants Canada Fiction; Enfants d'immigrants Canada Romans, nouvelles, etc; Fiction; Ontario Toronto; Ontario Toronto Scarborough; Scarborough (Toronto, Ont.) Fiction; Toronto (Ont.) Fiction; Trinidadians; Trinidadians Canada Fiction; Trinidadiens Canada Romans, nouvelles, etc

Aux marges de l’emploi : Parcours de travailleuses domestiques québécoises 1950-2000 - Charron, Catherine (Hors Collection, 2018)
La reconnaissance du travail ménager occupe les féministes depuis des décennies. Mais qu’ont à dire celles qui en ont fait leur gagne-pain, les travailleuses de l’ombre par excellence? Dans ce livre, Catherine Charron examine le travail domestique rémunéré au Québec entre les années 1950 et 2000. Elle expose les parcours d’une trentaine de femmes de la région de Québec et leur donne la parole. Dans un contexte où le marché du travail subit de profondes transformations, les boulots domestiques, loin de disparaître, se reconfigurent et continuent d’occuper une part non négligeable de la main-d’œuvre féminine. Tandis qu’une proportion croissante de femmes ont un meilleur accès à la scolarisation et au salariat, de nombreuses autres se trouvent refoulées dans diverses filières d’emplois domestiques: la garde d’enfants, l’aide à domicile pour les personnes âgées, les travaux d’entretien ménager. Les trajectoires des femmes interrogées par Catherine Charron, nées entre 1914 et 1958, illustrent le rapport changeant des femmes à l’emploi et à la famille à partir des années d’après-guerre ainsi que leurs réalités hétérogènes. À l’intersection du public et du privé, le travail domestique rémunéré s’exerce dans la continuité du travail gratuit assigné aux femmes au sein de la famille et de la communauté, ce qui contribue à le rendre invisible. Aux marges de l’emploi révèle cette face cachée de l’économie marchande et domestique, incontournable dans toute réflexion sur le travail, et rend justice à celles qui l’incarnent. --Résumé de l'éditeur

Labor and the Class Idea in the United States and Canada - Eidlin, Barry (Cambridge Studies in Contentious Politics, 2018)
Why are unions weaker in the US than in Canada, two otherwise similar countries? This difference has shaped politics, policy, and levels of inequality. Conventional wisdom points to differences in political cultures, party systems, and labor laws. But Barry Eidlin’s systematic analysis of archival and statistical data shows the limits of conventional wisdom, and presents a novel explanation for the cross-border difference. He shows that it resulted from different ruling party responses to worker upsurge during the Great Depression and World War II. Paradoxically, US labor’s long-term decline resulted from what was initially a more pro-labor ruling party response, while Canadian labor’s relative long-term strength resulted from a more hostile ruling party response. These struggles embedded ‘the class idea’ more deeply in policies, institutions, and practices than in the US. In an age of growing economic inequality and broken systems of political representation, Eidlin’s analysis offers insight for those seeking to understand these trends, as well as those seeking to change them. --Publisher's description
Keywords: Comparative Politics; Politics; Politics and International Relations; Poltical Sociology; Sociology

The Public Sector in an Age of Austerity: Perspectives from Canada's Provinces and Territories - Evans, Bryan M.; Fanelli, Carlo (McGill-Queen's University Press, 2018)
Following the 2008 global financial crisis, Canada appeared to escape the austerity implemented elsewhere, but this was spin hiding the reality. A closer look reveals that the provinces--responsible for delivering essential public and social services such as education and healthcare--shouldered the burden. The Public Sector in an Age of Austerity examines public-sector austerity in the provinces and territories, specifically addressing how austerity was implemented, what forms austerity agendas took (from regressive taxes and new user fees to public-sector layoffs and privatization schemes), and what, if any, political responses resulted. Contributors focus on the period from 2007 to 2015, the global financial crisis and the period of fiscal consolidation that followed, while also providing a longer historical context--austerity is not a new phenomenon. A granular examination of each jurisdiction identifies how changing fiscal conditions have affected the delivery of public services and restructured public finances, highlighting the consequences such changes have had for public-sector workers and users of public services. The first book of its kind in Canada, The Public Sector in an Age of Austerity challenges conventional wisdom by showing that Canada did not escape post-crisis austerity, and that its recovery has been vastly overstated. -- Publisher's description
Keywords: 2008-2009; Canada; Canada Appropriations and expenditures, Provincial; Canada Provinces Crédits budgétaires et dépenses; Civil service Canada Provinces; Civil service Canadian provinces; Crise financière mondiale, 2008-2009 Politique gouvernementale Canada Provinces; Finance, Public Canada Provinces; Finance, Public Canadian provinces; Finances publiques Canada Provinces; Finanzkrise; Finanzpolitik; Fiscal policy Canada Provinces; Fiscal policy Canadian provinces; Fonction publique Canada Provinces; Global Financial Crisis, 2008-2009 Government policy Canada Provinces; Haushaltskonsolidierung; Kanada; Länderhaushalt; Neoliberalism Canada Provinces; Néo-libéralisme Canada Provinces; Politique fiscale Canada Provinces; Regionalregierung; Öffentliche Dienstleistung; Öffentlicher Sektor

Defying Expectations: The Case of UFCW Local 401 - Foster, Jason (Working Canadians: Books from the CCLH, 2018)
In October 2005, Jason Foster, then a staff member of the Alberta Federation of Labour, was walking a picket line outside Lakeside Packers in Brooks, Alberta with the members of local 401. It was a first contract strike. And although the employees of the meat-packing plant—many of whom were immigrants and refugees—had chosen an unlikely partner in the United Food and Commercial Workers local, the newly formed alliance allowed the workers to stand their ground for a three-week strike that ended in the defeat of the notoriously anti-union company, Tyson Foods. It was but one example of a wide range of industries and occupations that local 401 organized over the last twenty years. In this study of UFCW 401, Foster investigates a union that has had remarkable success organizing a group of workers that North American unions often struggle to reach: immigrants, women, and youth. By examining not only the actions and behaviour of the local’s leadership and its members but also the narrative that accompanied the renewal of the union, Foster shows that both were essential components to legitimizing the leadership’s exercise of power and its unconventional organizing forces. -- Publisher's description
Keywords: United Food and Commerical Workers (UFCW)

From the Streets to the State: Changing the World by Taking Power - Gray, Paul Christopher (SUNY series in new political science, 2018)
For decades, emancipatory struggles have been deeply influenced by the slogan “Change the world without taking power.” Amid growing social inequalities and the return of right-wing authoritarianism, however, many now recognize the limits of disengaging from government and the state. From the Streets to the State chronicles many diverse and exciting projects to not only take state power but to fundamentally change it. A blend of scholars and activists explore issues like the nonsectarian relationships between new radical left parties, egalitarian social movements, and labor movements in Greece, Germany, Spain, Portugal, and Turkey. Contributors discuss municipal campaigns based in popular assemblies, solidarity economies, and independent political organizations fighting for racial, gender, and economic justice in cities such as Jackson, Vancouver, and Newcastle. This volume also studies the lessons learned from the Pink Tide in Latin America as well as the social movements of racialized and gendered workers transforming human rights across the United States. Finally, the book offers case studies from around the world surveying the role of state workers and public sector unions in radically democratizing public administration through coalitions between the providers and users of public services. -- Publisher's description. Contents: Part 1: Changing the World...and Ourselves: The Radical Left and the Problems of State Power. From the streets to the state : a critical introduction / Paul Christopher Gray -- Democratizing the party and the state : transcending the limits of the left / Leo Panitch. Part 2: Confronting Leviathan: Parties, Social Movements, and the Capitalist State. Building "parties of a new type" : a comparative analysis of new radical left parties In Western Europe / Xavier Lafrance and Catarina Príncipe -- Watching over the right to turn left : the limits of state autonomy in pink tide Venezuela and Ecuador / Thomas Chiasson-LeBel -- Casting shadows : Chokwe Lumumba and the struggle for racial justice and economic democracy in Jackson, Mississippi / Kali Akuno -- The radical democracy of the People's Democratic Party : transforming the Turkish state / Erdem Yörük -- Toward a radical politics of rights : lessons about legal leveraging and its limitations / Michael McCann and George I. Lovell. Part 3: In, against, and beyond the Behemoth: Projects for “Democratic Administration.” Market failures, failing states : challenges for democratization projects / Greg Albo -- Forging a "social knowledge economy" : transformative collaborations between radical left governments, state workers, and solidarity economies / Hilary Wainwright -- Femocratic administration and the politics of transformation / Tammy Findlay -- Beyond service, beyond coercion? : prisoner co-ops and the path to democratic administration / Greg McElligott.
Keywords: Capitalism; Case studies; Left-wing extremists; New Left; Political aspects; Right and left (Political science)

Hard Work Conquers All: Building the Finnish Community in Canada - Harpelle, Ronald N.; Ratz, David K.; Beaulieu, Michel S. (UBC Press, 2018)
Above the entrance to the Finnish Labour Temple, in what was once Port Arthur in northern Ontario, is the motto labor omnia vincit – “hard work conquers all.” Since 1910, these words have reflected the dedication of the Finnish community in Canada. This book is a social history of Finnish immigration and community building in Canada during the twentieth century. The first Finns to arrive ranged from conservative churchgoers to radical socialists, reflecting the ideologies that divided their homeland. After the First World War, left-wing Finns fled persecution; following the Second World War, Finns sought the economic security that Canada offered. Each new wave of immigration imbued the relationship between people, homeland, and host country with the politics, ideologies, and cultural expressions of its time. The story of Finns in Canada dovetails with the larger literature on immigration and enriches the history of socialism and ethnic repression in this country. The insightful essays in Hard Work Conquers All explore the nuanced cultural identities of Finnish Canadians, their continued ties to Finland, intergenerational cultural transfer, and the community’s connections with socialism and labour movements. This is a fresh interpretation of the successive waves of Finnish immigration and their influence on Canadian politics and society. --Publisher's description
Keywords: 1900-1999; Canada; Canadiens d'origine finlandaise; Canadiens d'origine finlandaise Conditions sociales 20e siècle; Canadiens d'origine finlandaise Conditions économiques 20e siècle; Canadiens d'origine finlandaise Mœurs et coutumes 20e siècle; Finnish Canadians; Finnish Canadians Economic conditions 20th century; Finnish Canadians Social conditions 20th century; Finnish Canadians Social life and customs 20th century; Finns; Finns Canada; Finns Canada Economic conditions 20th century; Finns Canada Social conditions 20th century; Finns Canada Social life and customs 20th century; Finns Social conditions; Finns Social life and customs

Working Lives: Essays in Canadian Working Class History - Heron, Craig (University of Toronto Press, 2018)
Craig Heron is one of Canada's leading labour historians. Drawing together fifteen of Heron's new and previously published essays on working-class life in Canada, Working Lives covers a wide range of issues, including politics, culture, gender, wage-earning, and union organization. A timely contribution to the evolving field of labour studies in Canada, this cohesive collection of essays analyzes the daily experiences of people working across Canada over more than two hundred years. Honest in its depictions of the historical complexities of daily life, Working Lives raises issues in the writing of Canadian working-class history, especially "working-class realism" and how it is eventually inscribed into Canada's public history. Thoughtfully reflecting on the ways in which workers interact with the past, Heron discusses the important role historians and museums play in remembering the adversity and milestones experienced by Canada's working class. -- Publisher's description. Table of contents: Part 1: On the job. On the job in Canada -- Ontario’s first factory workers -- Work and struggle in the Canadian steel industry, 1900-50. Part 2. Workers’ Cultures. Arguing about idleness -- Labour and liquor -- Into the streets. Part 3: Getting organized. Labourism and the working class -- The Great War, the state, and working-class Canada -- Contours of a workers’ revolt. Part 4: A gendered world. Working girls -- Boys will be boys -- Male wage-earners and the Canadian state. Part 5: Doing history. Workers in the camera’s eye -- The labour historian and public history -- The relevance of class.

One Job Town: Work, Belonging, and Betrayal in Northern Ontario - High, Steven C. (University of Toronto Press, 2018)
There's a pervasive sense of betrayal in areas scarred by mine, mill and factory closures. [This book] delves into the long history of deindustrialization in the paper-making town of Sturgeon Falls, Ontario, located on Canada's resource periphery. Much like hundreds of other towns and cities across North America and Europe, Sturgeon Falls has lost their primary source of industry, resulting in the displacement of workers and their families. One Job Town takes us into the making of a culture of industrialism and the significance of industrial work for mill-working families. One Job Town approaches deindustrialization as a long term, economic, political, and cultural process, which did not begin and simply end with the closure of the local mill in 2002. High examines the work-life histories of fifty paper mill workers and managers, as well as city officials, to gain an in-depth understanding of the impact of the formation and dissolution of a culture of industrialism. Oral history and memory are at the heart of One Job Town, challenging us to rethink the relationship between the past and the present in what was formerly known as the industrialized world. --Publisher's description.
Keywords: Conditions sociales; Ontario; Paper mills; Personnel; Sturgeon Falls. Deindustrialization; Sturgeon Falls. Mills and mill-work; Sturgeon Falls. Moulins; Sturgeon Falls. Paper industry workers; Sturgeon Falls. Papeteries (Usines); Sturgeon Falls. Produits du papier; Sturgeon Falls. Sturgeon Falls (Ont.)

The Deindustrialized World: Confronting Ruination in Postindustrial Places - High, Steven C.; MacKinnon, Lachlan; Perchard, Andrew; Storey, Robert H.; Parnaby, Andrew; Clark, Jackie; Taksa, Lucy; Stanton, Cathie; Contrepois, Sylvie; Neumann, Tracy; Hurley, Andrew; O'Hanlon, Seamus; et al. (UBC Press, 2018)
Since the 1970s, the closure of mines, mills, and factories has marked a rupture in working-class lives. The Deindustrialized World interrogates the process of industrial ruination, from the first impact of layoffs in metropolitan cities, suburban areas, and single-industry towns to the shock waves that rippled outward, affecting entire regions, countries, and beyond. Seeking to hear the “roar ... on the other side of the silence,” scholars from France, Canada, Australia, the United Kingdom, and the United States share their own stories of ruin and ruination and ask others what it means to be working class in a postindustrial world. In Part 1, they explore the ruination of former workplaces and the damaged health and injured bodies of industrial workers. Part 2 brings to light disparities of experiences between rural resource towns and cities, where hipster revitalization often overshadows industrial loss. Part 3 reveals the ongoing impact of deindustrialization on working people and their place in the new global economy. Together, the chapters open a window on the lived experiences of people living at ground zero of deindustrialization, revealing its layered impacts and examining how workers, environmentalists, activists, and the state have responded to its challenges. --Publisher's description

Perogies and Politics: Canada's Ukrainian Left, 1891-1991 - Hinther, Rhonda L. (Studies in gender and history, 2018)
In Perogies and Politics, Rhonda Hinther explores the twentieth-century history of the Ukrainian left in Canada from the standpoint of the women, men, and children who formed and fostered it. For twentieth-century leftist Ukrainians, culture and politics were inextricably linked. The interaction of Ukrainian socio-cultural identity with Marxist-Leninism resulted in one of the most dynamic national working-class movements Canada has ever known. The Ukrainian left's success lay in its ability to meet the needs of and speak in meaningful, respectful, and empowering ways to its supporters' experiences and interests as individuals and as members of a distinct immigrant working-class community. This offered to Ukrainians a radical social, cultural, and political alternative to the fledgling Ukrainian churches and right-wing Ukrainian nationalist movements. Hinther's colourful and in-depth work reveals how left-wing Ukrainians were affected by changing social, economic, and political forces and how they in turn responded to and challenged these forces. -- Publisher's description
Keywords: 1800-1999; Canada; Droite (Science politique) Canada Histoire 19e siècle; Droite (Science politique) Canada Histoire 20e siècle; Gauche (Science politique) Canada Histoire 19e siècle; Gauche (Science politique) Canada Histoire 20e siècle; History; Right and left (Political science); Right and left (Political science) Canada History 19th century; Right and left (Political science) Canada History 20th century; Ukrainians Canada Politics and government 19th century; Ukrainians Canada Politics and government 20th century; Ukrainians Politics and government; Ukrainiens Canada Politique et gouvernement 19e siècle; Ukrainiens Canada Politique et gouvernement 20e siècle

Power, Politics, and Principles: Mackenzie King and Labour, 1935-1948 - Hollander, Taylor (University of Toronto Press, 2018)
Set against the backdrop of the U.S. experience, Power, Politics, and Principles uses a transnational perspective to understand the passage and long term implications of a pivotal labour law in Canada. By utilizing a wide array of primary materials and secondary sources, Hollander gets to the root of the policy-making process, revealing how the making of P.C. 1003 in 1944, a wartime order, that forced employers to the collective bargaining table and marked a new stage in Canadian industrial relations, involved real people with conflicting personalities and competing agendas. Each chapter of Power, Politics, and Principles begins with a quasi-fictional vignette to help the reader visualize historical context. Hollander pays particular attention to the central role that Mackenzie King played in the creation of P.C. 1003. Although most scholars describe the Prime Minister's approach to policy decisions as calculating and opportunistic, Power, Politics, and Principles argues that Mackenzie King's adherence to key principles, especially his determination to preserve and enhance the cohesiveness of the country, created a more favourable legal environment in the long run for Canadian workers and their unions than a similar collective bargaining regime in the U.S. --Publisher's description
Keywords: 1935-1948; 20th century; Canada; Collective bargaining; History; King, William Lyon Mackenzie, 1874-1950; Labor laws and legislation; Labor policy; Labor unions; Politics and government

Dear Current Occupant: A Memoir - Knight, Chelene (Essais (Toronto, Ont.), 2018)
From Vancouver-based writer Chelene Knight, Dear Current Occupant is a creative nonfiction memoir about home and belonging set in the 80s and 90s of Vancouver's Downtown Eastside. Using a variety of forms including letters, essays and poems, Knight reflects on her childhood through a series of letters addressed to all of the current occupants now living in the twenty different houses she moved in and out of with her mother and brother. From blurry non-chronological memories of trying to fit in with her own family as the only mixed East Indian/Black child, to crystal clear recollections of parental drug use, Knight draws a vivid portrait of memory that still longs for a place and a home. Peering through windows and doors into intimate, remembered spaces now occupied by strangers, Knight writes to them in order to deconstruct her own past. From the rubble of memory she then builds a real place in order to bring herself back home. -- Publisher's description
Keywords: Autobiographical fiction; Biographies; Biography; Black people British Columbia Vancouver Social conditions; Black people Social conditions; British Columbia Vancouver; Creative nonfiction, Canadian; Creative nonfiction, Canadian (English); Essais fictionnels canadiens-anglais; Knight, Chelene, 1981-; Vancouver (B.C.) Biography; Women authors, Black; Women authors, Black Biography; Écrivaines noires Biographies

White Gloves Off: The Work of the Ontario Committee on the Status of Women - Marsden, Lorna; Atcheson, Beth (Second Story Press, 2018)
During the 1970s and 1980s, after the Royal Commission on the Status of Women made its far-reaching recommendations, the volunteer Ontario Committee on the Status of Women went head-to-head with the Ontario government of Premier William Davis to fully implement equality for women in Ontario. Areas of concern were in employment, pay and benefits, child care and reproduction rights, education and training, family law, pensions, politics and the civil service, and human rights generally. Members of this committed organization tell the stories of how they came together, how they organized and lobbied for change, how they collaborated with other groups, how the issues changed, and what the work means for women in Ontario today. --Publisher's description

Claiming the Land: British Columbia and the Making of a New El Dorado - Marshall, Daniel Patrick (Ronsdale Press, 2018)
This trailblazing history of early British Columbia focuses on a single year, 1858, the year of the Fraser River gold rush — the third great mass migration of gold seekers after the Californian and Australian rushes in search of a new El Dorado. Marshall’s history becomes an adventure, prospecting the rich pay streaks of British Columbia’s “founding” event and the gold fever that gripped populations all along the Pacific Slope. Marshall unsettles many of our most taken-for-granted assumptions: he shows how foreign miner-militias crossed the 49th parallel, taking the law into their own hands, and conducting extermination campaigns against Indigenous peoples while forcibly claiming the land. Drawing on new evidence, Marshall explores the three principal cultures of the goldfields — those of the fur trade (both Native and the Hudson’s Bay Company), Californian, and British world views. The year 1858 was a year of chaos unlike any other in British Columbia and American Pacific Northwest history. It produced not only violence but the formal inauguration of colonialism, Native reserves and, ultimately, the expansion of Canada to the Pacific Slope. Among the haunting legacies of this rush are the cryptic place names that remain — such as American Creek, Texas Bar, Boston Bar, and New York Bar — while the unresolved question of Indigenous sovereignty continues to claim the land. -- Publisher's website description. Contents: Introduction: Fraser River fever on the Pacific slope of North America -- Prophetic patterns: the search for a new El Dorado -- The fur trade world -- The Californian world -- The British world -- Fortunes foretold: the Fraser River War -- Mapping the new El Dorado -- Inventing Canada from west to east -- Conclusion: "The river bears south."
Keywords: 19th century. Indians of North America; British Columbia; Fraser River Valley; Fraser River Valley. Gold mines and mining; Frontier and pioneer life; Government relations; Government relations. Genre/Form: History; History. Frontier and pioneer life. Gold mines and mining. Indians of North America. Indians of North America

Law and the "Sharing Economy": Regulating Online Market 'Platforms - McKee, Derek; Makela, Finn; Scassa, Teresa (University of Ottawa Press, 2018)
Controversy shrouds sharing economy platforms. It stems partially from the platforms’ economic impact, which is felt most acutely in certain sectors: Uber drivers compete with taxi drivers; Airbnb hosts compete with hotels. Other consequences lie elsewhere: Uber is associated with a trend toward low-paying, precarious work, whereas Airbnb is accused of exacerbating real estate speculation and raising the cost of long-term rental housing. While governments in some jurisdictions have attempted to rein in the platforms, technology has enabled such companies to bypass conventional regulatory categories, generating accusations of “unfair competition” as well as debates about the merits of existing regulatory regimes. Indeed, the platforms blur a number of familiar distinctions, including personal versus commercial activity; infrastructure versus content; contractual autonomy versus hierarchical control. These ambiguities can stymie legal regimes that rely on these distinctions as organizing principles, including those relating to labour, competition, tax, insurance, information, the prohibition of discrimination, as well as specialized sectoral regulation. This book is organized around five themes: technologies of regulation; regulating technology; the sites of regulation (local to global); regulating markets; and regulating labour. Together, the chapters offer a rich variety of insights on the regulation of the sharing economy, both in terms of the traditional areas of law they bring to bear, and the theoretical perspectives that inform their analysis. --Publisher's description

On the Line: A History of the British Columbia Labour Movement - Mickleburgh, Rod (Harbour Publishing, 2018)
The BC tradition of fighting back against unfair pay and unsafe working conditions has been around since before the colony joined Confederation. In 1849 Scottish labourers at BC's first coal mine at Fort Rupert went on strike to protest wretched working conditions, and it's been a wild ride ever since. For years the BC labour movement was the most militant in the land, led by colourful characters like Ginger Goodwin, murdered for his pains, and pull-no-punches communist Harvey Murphy, who brought the house of labour down on himself with his infamous "underwear speech." Through years of battles with BC's power elite and small victories followed by bitter defeats, BC unions established the five-day work week, the eight-hour day, paid holidays, the right to a safe, non-discriminatory workplace and many more taken-for-granted features of the modern work landscape. But unions' enemies never sleep and, well into the second decade of the twenty-first century, battles still go on, like that of BC teachers in their long and ultimately successful struggle to improve classroom conditions. On the Line also highlights the role played by women, Indigenous and minority workers in working toward equality and democracy in workplaces and communities. In prose that is both accessible and engaging, accompanied by over two hundred archival photos, Mickleburgh tells the important story of how BC's labour organizations have shaped the economic, political and social fabric of the province--at a cost of much blood, sweat, toil and tears. This volume is the most comprehensive overview of labour's struggle in BC and will be of particular interest to union members, community activists, academics and readers of regional history. -- Publisher's description
Keywords: 1900-1999; BUSINESS & ECONOMICS / Labor; British Columbia; History; Labor movement; Labor movement British Columbia History 20th century; Labor unions; Labor unions British Columbia History 20th century; Mouvement ouvrier Colombie-Britannique Histoire 20e siècle; POLITICAL SCIENCE / Labor & Industrial Relations; Syndicats Colombie-Britannique Histoire 20e siècle

Grève et paix : une histoire des lois spéciales au Québec (Collection Mémoire des Amériques, 2018)
Les lois d'exception, ou lois « spéciales », ont été au cœur de l'histoire politique québécoise des cinquante dernières années. Depuis le milieu des années 1960, entre luttes sociales et crises économiques, tous les gouvernements y ont eu recours pour interdire et réprimer l'exercice du droit de grève dans les secteurs public et privé. Ces atteintes répétées visant un droit reconnu par l'Assemblée nationale ont suscité un fort mouvement de contestation syndicale, voire de désobéissance civile dans les années 1970. Affaibli par l'adoption de lois spéciales particulièrement sévères, de décrets imposant les conditions de travail et de réformes sociales draconiennes à partir du début des années 1980, le mouvement syndical peine toujours à retrouver sa combativité. Au moyen d'une documentation inédite, Grève et paix montre pour la première fois comment les lois d'exception ont bouleversé non seulement le monde du travail, mais la société québécoise dans son ensemble. --Résumé de l'éditeur
Keywords: Grèves et lock-out Droit Québec (Province) Histoire; History; Québec; Strikes and lockouts Law and legislation; Strikes and lockouts Law and legislation Québec (Province) History; Syndicalism; Syndicalism Québec (Province) History; Syndicalisme Québec (Province) Histoire

Sick and Tired: Health and Safety Inequalities - Premji, Stephanie (Labour in Canada (Halifax, N.S.), 2018)
Bringing together a multidisciplinary group of experts from the fields of labour studies, public health, ergonomics, epidemiology, sociology and law, Sick and Tired examines the inequalities in workplace health and safety. Using an anti-oppressive framework, chapters interrogate a wide range of issues, including links between precarious employment and mental health, the inverse relationship between power and occupational health through the experiences of women, immigrants and older workers, and the need for creative strategies that promote health and safety in ways that support empowerment and equity. --Publisher's description
Keywords: Canada. BUSINESS & ECONOMICS; Canada. Equality; Canada. Industrial safety; Economics; General. Equality. Industrial hygiene. Industrial safety; Industrial hygiene

Travail invisible : portraits d'une lutte féministe inachevée - Robert, Camille; Toupin, Louise (Remue-ménage, 2018)
Encore invisible, le travail des femmes? La question peut faire sourciller tant les féministes ont obtenu des gains sur ce front au cours des dernières décennies. Or, si les femmes ont massivement intégré le marché de l'emploi, le travail dit invisible, majoritairement effectué par celles-ci, n'a fait que croître et se complexifier. En plus du strict travail ménager, il se présente sous de multiples visages: la charge mentale de l'organisation familiale, le travail invisible d'intégration des femmes immigrantes, le travail des proches aidantes, celui des aides familiales venues d'ailleurs, des femmes autochtones et racisées, des étudiantes stagiaires, ou encore, des travailleuses du sexe. Comment se décline l'enjeu du travail invisible dans différents milieux, et où en sont les revendications pour faire reconnaître ce travail et le sortir de l'ombre? Rassemblant des militantes féministes et des intellectuelles engagées sur ces questions, cet ouvrage collectif entend remettre le sujet du travail invisible à l'ordre du jour politique tout en proposant des pistes de réflexion et de mobilisation concrètes. Encore invisible, le travail des femmes? La question peut faire sourciller tant les féministes ont obtenu des gains sur ce front au cours des dernières décennies. Or, si les femmes ont massivement intégré le marché de l'emploi, le travail dit invisible, majoritairement effectué par celles-ci, n'a fait que croître et se complexifier. En plus du strict travail ménager, il se présente sous de multiples visages: la charge mentale de l'organisation familiale, le travail invisible d'intégration des femmes immigrantes, le travail des proches aidantes, celui des aides familiales venues d'ailleurs, des femmes autochtones et racisées, des étudiantes stagiaires, ou encore, des travailleuses du sexe. Comment se décline l'enjeu du travail invisible dans différents milieux, et où en sont les revendications pour faire reconnaître ce travail et le sortir de l'ombre? Rassemblant des militantes féministes et des intellectuelles engagées sur ces questions, cet ouvrage collectif entend remettre le sujet du travail invisible à l'ordre du jour politique tout en proposant des pistes de réflexion et de mobilisation concrètes. Des textes de Stella Adjokê, Sandrine Belley, Sonia Ben Soltane, Annabelle Berthiaume, Jenn Clamen, Hélène Cornellier, Irène Demczuk, Myriam Dumont Robillard, Claudia Foisy, Monica Forrester, Elizabeth James, Elene Lam, Widia Larivière, Valérie Lefebvre-Faucher, Linda Li, Camille Robert, Annabelle Seery, Valérie Simard et Louise Toupin. -- Résumé de l'éditeur
Keywords: Charge cognitive; Femmes; Femmes Droit Québec (Province); Femmes Travail Canada Québec (Canada); Femmes Travail Québec (Province); Femmes au foyer; Femmes au foyer Québec (Province); Féminisme; Housekeepers; Housewives; Housewives Québec (Province); Québec; Travail; Travail domestique; Travail et vie personnelle; Travail non rémunéré; Unpaid labor; Women Employment; Women Employment Québec (Province); Women Legal status, laws, etc; Women Legal status, laws, etc. Québec (Province); housewives (people); Égalité des sexes Canada Québec (Canada)

Labour Under Attack: Anti-Unionism in Canada - Ross, Stephanie; Savage, Larry (Fernwood, 2018)
This multi-disciplinary edited collection critically examines the causes and effects of anti-unionism in Canada. Primarily through a series of case studies, the book’s contributors document and expose the tactics and strategies of employers and anti-labour governments while also interrogating some of the labour movement’s own practices as a source of anti-union sentiment among workers. -- Publisher's description
Keywords: Labour; Unions

Stolen City: Racial Capitalism and the Making of Winnipeg - Toews, Owen (ARP Books, 2018)
Through a combination of historical and contemporary analysis this book shows how settler colonialism, as a mode of racial capitalism, has made and remade Winnipeg and the Canadian Prairie West over the past one hundred and fifty years. It traces the emergence of a 'dominant bloc, ' or alliance, in Winnipeg that has imagined and installed successive regional development visions to guarantee its own wealth and power. The book gives particular attention to the ways that an ascendant post-industrial urban redevelopment vision for Winnipeg's city-centre has renewed longstanding colonial 'legacies' of dispossession and racism over the past forty years. In doing so, it moves beyond the common tendency to break apart histories of settler-colonial conquest from studies of urban history or contemporary urban processes. --Publisher's description
Keywords: City planning; City planning Manitoba Winnipeg History; History; Manitoba; Manitoba Winnipeg; Race relations; Racism Economic aspects; Racism Economic aspects Manitoba History; Racisme Aspect économique Manitoba Histoire; Urbanisation Manitoba Winnipeg Histoire; Urbanisme Manitoba Winnipeg Histoire; Urbanization; Urbanization Manitoba Winnipeg History; Winnipeg (Man.) Histoire; Winnipeg (Man.) History; Winnipeg (Man.) Race relations History; Winnipeg (Man.) Relations raciales Histoire

The Daunting Enterprise of the Law: Essays in Honour of Harry Arthurs - Archer, Simon; Zumbansen, Peer; Drache, Daniel (McGill-Queen's University Press, 2017)
Harry Arthurs, professor emeritus at Osgoode Hall Law School in Toronto and former president of York University, is one of the most widely respected scholars, educators, and policy makers in the world today. His enormous academic and institutional productivity has extended to administrative and labour law, legal pluralism and legal theory, legal education and institutional reform. This collection brings together essays, thought pieces, reminiscences and commentaries written in honour of Arthurs from scholars and colleagues from around the world whose work and thinking has been shaped by Arthurs' contributions over the years. --Publisher's description.
Keywords: Administrative Law & Regulatory Practice. LAW / General; Canada. LAW; Labor laws and legislation

The Mill: Fifty Years of Pulp and Protest - Baxter, Joan (Pottersfield Press, 2017)
The Mill - Fifty Years of Pulp and Protest explores the power that a single industry can wield. For fifty years, the pulp mill near Pictou in northern Nova Scotia has buoyed the local economy and found support from governments at all levels. But it has also pulped millions of acres of forests, spewed millions of tonnes of noxious emissions into the air, consumed quadrillions of litres of fresh water and then pumped them out again as toxic effluent into nearby Boat Harbour, and eventually into the Northumberland Strait. From the day it began operation in 1967, the mill has fomented protest and created deep divisions and tensions in northern Nova Scotia. This story is about people whose livelihoods depend on the pulp mill and who are willing to live with the "smell of money." It's about people whose well-being, health, homes, water, air, and businesses have been harmed by the mill's emissions and effluent. It's about the heartache such divisions cause and about people who, for the sake of peace, keep their thoughts about the mill to themselves. But it's also about hope, giving voice to those who led the successive groups that have protested and campaigned for a cleaner mill - First Nations, fishers, doctors, local councillors, tourism operators, artists and musicians, teachers and woodlot owners. Their personal stories are interwoven into a historical arc that traces the mill's origins and the persistent environmental and social problems it causes to this day. Baxter weaves a rich tapestry of storytelling, relevant to everyone who is concerned about how we can start to renegotiate the relationship between economy, jobs, and profits on one hand, and human well-being, health, and the environment on the other. The Mill tells a local story with global relevance and appeal. --Publisher's description
Keywords: Economic conditions; Environmental aspects; History; Northern Pulp (Pictou, N.S.); Nova Scotia Pictou; Pictou (N.S.); Pulp mills; Social aspects; Social conditions; Wood-pulp industry

Austerity: The Lived Experience - Evans, Brian; McBride, Stephen (University of Toronto Press, 2017)
Bryan M. Evans, Stephen McBride, and their contributors delve further into the more practical, ground-level side of the austerity equation in Austerity: The Lived Experience. Economically, austerity policies cannot be seen to work in the way elite interests claim that they do. Rather than soften the blow of the economic and financial crisis of 2008 for ordinary citizens, policies of austerity slow growth and lead to increased inequality. While political consent for such policies may have been achieved, it was reached amidst significant levels of disaffection and strong opposition to the extremes of austerity. The authors build their analysis in three sections, looking alternatively at theoretical and ideological dimensions of the lived experience of austerity; how austerity plays out in various public sector occupations and policy domains; and the class dimensions of austerity. The result is a ground-breaking contribution to the study of austerity politics and policies. Contents: Austerity as lived experience: An introduction / Bryan Evans and Stephen McBride. Pt. 1. Theory and ideology. Introduction: Manufacturing the common sense of austerity / Bryan Evans and McBride -- Articulating austerity and authoritarianism: Re-imagining moral economies? / John Clarke -- Speaking austerity: Policy rhetoric and design beyond fiscal consolidation / Sorin Mitrea -- No deal capitalism: Austerity and the unmaking of the North American middle class / Eric Pineault -- Framing the economic case for Austerity: The “expansionary fiscal contraction hypothesis” / Ellen Russell. Pt. 2. Impact and consequences. Introduction: Austerity on the ground / Evans and McBride -- Care and control in long term care work / Donna Baines -- ‘Negotiate your way back to zero’: Teacher bargaining and austerity in Ontario, Canada / Brendan A. Sweeny and Robert S. Hickey -- Austerity and the low wage economy: Living and other wages / Bryan Evans, Stephen McBride, and Jacob Muirhead -- Immigration in an age of austerity: Morality, the welfare state and the shaping of the ideal migrant / Susan Barrass and John Shields -- Pension reforms in the context of the global financial crisis: A reincarnation of pension privatization through austerity / Yanqiu Rachel Zhou and Shih-Jiun Shi. Pt. 3. Class, resistance, alternative. Introduction: The old strategies don’t work. So what’s possible? / Bryan Evans and Stephen McBride -- From austerity to structural reform: The erosion of the European social model(s) / Christophe Hermann -- Austerity of imagination: Quebec’s struggles in translating resistance into alternatives / Peter Graefe and Hubert Rioux -- Social democracy and social pacts: Austerity alliances and their consequences / Bryan Evans -- Austerity and political crisis: The radical left, the far right and Europe’s new authoritarian order / Neil Burron -- Conclusion.

Income Inequality: The Canadian Story - Green, David A.; Riddell, W. Craig; St-Hilaire, France (The Art of the State, 2017)
The Institute for Research on Public Policy, in collaboration with the Canadian Labour Market and Skills Researcher Network, has gathered some of the country’s leading experts to provide new evidence on the causes and effects of growing income inequality in Canada and the role of policy. Their research and analysis is collected in this volume, the fifth in the IRPP’s The Art of the State series. --Publisher's description
Keywords: American middle class; Culture; Economic inequality; Economics; Economy; Education; Employment; Gini coefficient; Human activities; Immigration

The Equity Myth: Racialization and Indigeneity at Canadian Universities - Henry, Frances; Kobayashi, Audrey Lynn; Smith, Malinda; Dua, Enakshi; James, Carl E.; Li, Peter; Ramos, Howard (UBC Press, 2017)
The university is often regarded as a bastion of liberal democracy where equity and diversity are vigorously promoted. In reality, the university still excludes many people and is a site of racialization that is subtle, complex, and sophisticated. This book, the first comprehensive, data-based study of racialized and Indigenous faculty members' experiences in Canadian universities, challenges the myth of equity in higher education. Drawing on a rich body of survey data, interviews, and analysis of universities' stated policies, leading scholars scrutinize what universities have done and question the effectiveness of their employment equity programs. They also make important recommendations as to how universities can address racialization and fulfill the promise of equity in the academy. --Publisher's description. Contents: Introduction : setting the context -- Representational analysis : comparing Canada, the United States, the United Kingdom, and Australia -- Differences in representation and employment income of racialized university professors in Canada -- Academic production, reward, and perceptions of racialized faculty members -- "Would never be hired these days" : the precarious work situation of racialized and indigenous faculty members -- The everyday world of racialized and indigenous faculty members in Canadian universities -- "You know why you were hired don't you?" Expectations and challenges in university appointments -- Shifting terrains : a picture of the institutionalization of equity in Canadian universities -- Mechanisms to address inequities in Canadian universities : the performativity of ineffectiveness -- Disciplinary silences : race, indigeneity, and gender in the social sciences -- A dirty dozen : unconscious race and gender biases in the academy -- Conclusion : challenging the myth. Includes bibliographical references (pages 328-355) and index.
Keywords: Canada Discrimination dans l'emploi; Canada Discrimination in employment. Discrimination in higher education. Equality. Indian college teachers. Race discrimination. Universities and colleges; Canada Discrimination raciale; Canada. Discrimination in employment; Canada. Discrimination in higher education; Canada. Equality; Canada. Race discrimination; Canada. Universities and colleges; Indian college teachers

Scarborough - Hernandez, Catherine (Arsenal Pulp Press, 2017)
A poignant, multi-voiced novel about life in the inner city. Scarborough is a low-income, culturally diverse neighbourhood east of Toronto, the fourth largest city in North America; like many inner-city communities, it suffers under the weight of poverty, drugs, crime, and urban blight. Scarborough the novel employs a multitude of voices to tell the story of a tight-knit neighbourhood under fire: among them, Victor, a black artist harassed by the police; Winsum, a West Indian restaurant owner struggling to keep it together; and Hina, a Muslim school worker who witnesses first-hand the impact of poverty on education. And then there are the three kids who work to rise above a system that consistently fails them: Bing, a gay Filipino boy who lives under the shadow of his father's mental illness; Sylvie, Bing's best friend, a Native girl whose family struggles to find a permanent home to live in; and Laura, whose history of neglect by her mother is destined to repeat itself with her father. Scarborough has already received recognition as winner of the Asian Canadian Writers' Workshop Emerging Writers Award in 2015, and finalist for the 2016 $50,000 Half the World Global Literati Award for best unpublished manuscript. It offers a raw yet empathetic glimpse into a troubled community that locates its dignity in unexpected places: a neighbourhood that refuses to be undone."-- Publisher's description
Keywords: Canadian fiction; Canadian fiction (English) 21st century; Fiction; Fictional Work; Ontario Scarborough; Pauvreté Romans, nouvelles, etc; Poverty; Poverty Fiction; Romans; Scarborough (Toronto, Ont.) Fiction

Workers' Compensation: Analysis for Its Second Century - Hunt, H. Allen; Dillender, Marcus (WE Focus Series, 2017)
Hunt and Dillender review the status of workers' compensation programs on three critical performance areas: 1) the adequacy of compensation for those disabled in the workplace, 2) return-to-work performance for injured workers, and 3) prevention of disabling injury and disease. [ Includes Canadian content.] --Publisher's abstract

Work and Labour in Canada: Critical Issues - Jackson, Andrew; Thomas, Mark P. (Canadian Scholars Press, 2017)
Over the last few decades, the workplace in Canada has experienced profound changes. Work has become increasingly insecure for a growing number of people, young workers struggle to match qualifications and credentials with jobs, and retirement with a secure income is a diminishing prospect. The demographic composition of the labour market is transforming, yet this change is conditioned by longstanding patterns of inequality in terms of gender, race, disability, and immigration status. This third edition of Work and Labour in Canada maps out major trends and patterns that define working life, and identifies the economic, social, and political factors that shape the contemporary workplace. While evaluating working conditions and job quality from a critical perspective, the authors point towards possibilities for a more equitable and democratic future of work. Thoroughly updated and featuring recommended readings, internet resources, and a new chapter on disability and work, this revised edition is an essential textbook for teachers, researchers, labour activists, and students of labour studies and sociology of work. --Publisher's description. Includes bibliographical references (pages 299-322) and index. Contents: The world of work in the 21st century -- Work, wages, and living standards in Canada -- Education, training, and lifelong learning : tensions and contradictions -- The unhealthy Canadian workplace -- Gender, work, and social reproduction -- Race, racialization, and racism at work -- The inaccessible Canadian workplace -- Troubled transitions : into and out of the labour force -- The impact of unions -- Workers' movements in the new millennium -- Globalization and work in Canada -- Improving work : reforming or transforming wage labour?

Spying on Canadians: The Royal Canadian Mounted Police Security Service and the Origins of the Long Cold War - Kealey, Gregory S. (University of Toronto Press, 2017)
Award-winning author Gregory S. Kealey's study of Canada's security and intelligence community before the end of World War II depicts a nation caught up in the Red Scare in the aftermath of the Bolshevik Revolution and tangled up with the imperial interests of first the United Kingdom and then the United States. Spying on Canadians brings together over twenty five years of research and writing about political policing in Canada. Through its use of the Dominion Police and later the RCMP, Canada repressed the labour movement and the political left in defense of capital. The collection focuses on three themes; the nineteenth-century roots of political policing in Canada, the development of a national security system in the twentieth-century, and the ongoing challenges associated with research in this area owing to state secrecy and the inadequacies of access to information legislation. This timely collection alerts all Canadians to the need for the vigilant defense of civil liberties and human rights in the face of the ever increasing intrusion of the state into our private lives in the name of countersubversion and counterterrorism. --Publisher's description
Keywords: Royal Canadian Mounted Police. Security Service -- History -- 20th century

Craft Capitalism: Craftsworkers and Early Industrialization in Hamilton, Ontario - Kristofferson, Robert B. (Canadian social history series, 2017)
Many studies have concluded that the effects of early industrialization on traditional craftsworkers were largely negative. Robert B. Kristofferson demonstrates, however, that in at least one area this was not the case. Craft Capitalism focuses on Hamilton, Ontario, and demonstrates how the preservation of traditional work arrangements, craft mobility networks, and other aspects of craft culture ensured that craftsworkers in that city enjoyed an essentially positive introduction to industrial capitalism. Kristofferson argues that, as former craftsworkers themselves, the majority of the city's industrial proprietors helped their younger counterparts achieve independence. Conflict rooted in capitalist class experience, while present, was not yet dominant. Furthermore, he argues, while craftsworkers' experience of the change was more informed by the residual cultures of craft than by the emergent logic of capitalism, craft culture in Hamilton was not retrogressive. Rather, this situation served as a centre of social creation in ways that built on the positive aspects of both systems. Based on extensive archival research, this controversial and engaging study offers unique insight to the process of industrialization and class formation in Canada. --Publisher's description. Contents: Introduction: Artisans, Craftsworkers, and Social Relations of Craft-Based Industrialization -- The Structure of Hamilton's Early Industrialization: Continuity and Change -- Personal Structures: Craftsworkers and Industrial Proprietors by 1871 -- Craft Mobility and Artisan-Led Industrialization: Continuity in Symbol and Practice -- A Culture in Continuity: Master-Man Mutualism in Hamilton, Ontario, during Early Industrialization -- The 'Self-Made Craftsworker': Transmodalism, Self-Identification, and the Foundations of Emergent Culture -- The 'Self-Improving Craftsworker': Dimensions of Transmodal Culture in Ideology and Practice -- Transmodal Culture in Apogee: 1872 Revisited -- Conclusion -- Notes -- Index.

Unions and the City: Negotiating Urban Change - MacDonald, Ian Thomas (ILR Press, an imprint of Cornell University Press, 2017)
Unions and the City serves as a road map toward both a stronger labor movement and a socially just urbanism. Focusing on four key economic sectors (film, hospitality, green energy, and child care), this book reveals that unions can exert a surprising level of influence in various aspects of urban policymaking.
Keywords: Community development, Urban; Community development, Urban New York (State) New York; Community development, Urban Ontario Toronto; Développement communautaire urbain New York (État) New York; Développement communautaire urbain Ontario Toronto; Labor movement; Labor movement New York (State) New York; Labor movement Ontario Toronto; Labor unions; Labor unions New York (State) New York; Labor unions Ontario Toronto; Mouvement ouvrier New York (État) New York; Mouvement ouvrier Ontario Toronto; New York (State) New York; Ontario Toronto; Sociologie urbaine New York (État) New York; Sociologie urbaine Ontario Toronto; Sociology, Urban; Sociology, Urban New York (State) New York; Sociology, Urban Ontario Toronto; Syndicats New York (État) New York; Syndicats Ontario Toronto

Policing Black Lives: State Violence in Canada from Slavery to the Present - Maynard, Robyn (Fernwood Publishing, 2017)
[This book] is a timely and much-needed exposure of historical and contemporary practices of state-sanctioned violence against Black lives in Canada. This groundbreaking work dispels many prevailing myths that cast Canada as a land of benevolence and racial equality, and uncovers long-standing state practices that have restricted Black freedom. A first of its kind, Policing Black Bodies creates a framework that makes legible how anti-Blackness has influenced the construction of Canada's carceral landscape, including the development and application of numerous criminal law enforcement and border regulation practices. The book traces the historical and contemporary mobilization of anti-Blackness spanning from slavery, 19th and 20th century segregation practices, and the application of early drug and prostitution laws through to the modern era. Maynard makes visible the ongoing legacy of a demonized and devalued Blackness that is manifest today as racial profiling by police, immigration agents and social services, the over-representation of Black communities in jails and prisons, anti-Black immigration detention and deportation practices, the over-representation of Black youth in state care, the school-to-prison pipeline and gross economic inequality. Following the dictums of the Black Lives Matter movement, Policing Black Bodies adopts an intersectional lens that explores the realities of those whose lives and experiences have historically been marginalized, stigmatized, and made invisible. In addressing how state practices have impacted Black lives, the book brings from margin to centre an analysis of gender, class, sexuality, (dis)ability, citizenship and criminalization. Beyond exploring systemic racial injustice, Policing Black Bodies pushes the limits of the Black radical imagination: it delves into liberatory Black futures and urges the necessity of transformative alternatives. --Publisher's description
Keywords: Blacks; Canada; Canada. Blacks; History. Blacks; History. Blacks. Blacks; Social conditions. Black Canadians; Social conditions. Race discrimination; Social conditions. Race discrimination. Race relations. Genre/Form: History. History

Blood, Sweat, and Fear: Violence at Work in the North American Auto Industry, 1960-80 - Milloy, Jeremy (UBC Press, 2017)
Going postal. We think of the rogue employee who snaps. But in [this book] Jeremy Milloy demonstrates that workplace violence never occurs in isolation. Using violence as a lens, he provides fresh and original insights into the everyday workings of capitalism, class conflict, race, and gender in the United States and Canada of the late twentieth century, bringing historical perspective to contemporary debates about North American violence. [The book] is the first full-length historical exploration of the origins and effects of individual violence in the automotive industry. Milloy’s gripping analysis spans 1960 to 1980, when North American auto plants were routinely the sites of fights, assaults, and even murders. He argues that the high levels of violence were primarily the result of workplace conditions – including on-the-job exploitation, racial tension, bureaucratization, and hypermasculinity – that made fear and loathing a shop-floor reality long before mass shootings attracted media attention in the 1980s. Workplace violence is typically the domain of management studies and psychology, but while we pass legislation and adopt best practices, the problem continues. Milloy’s explosive book reveals that workplace violence has been a constant aspect of class conflict – and that our understanding needs to go deeper. Blood, Sweat, and Fear will interest everyone concerned with the causes of workplace violence, and in particular scholars and students of labour history, sociology, sociological criminology, masculinity studies, and studies of race and of violence. --Publisher's description. Contents: Dripping with blood and dirt: confronting the history of workplace violence under capitalism -- Fights and knifings are becoming quite commonplace: Dodge main, 1965-80 -- The way boys and men took care of business: Windsor Chrysler plants -- The constant companion of all that earn their living here: workers, unions, and management respond -- Chrysler pulled the trigger: the courts and the press -- Out of the back streets and into the workplace: the discovery of workplace violence in the 1980s and 1990s.
Keywords: 20th century. Automobile industry and trade; 20th century. Automobile industry workers; 20th century. Violence; 20th century. Violence en milieu de travail; 20th century. Violence in the workplace; Aspect social; Canada; Conditions sociales; Histoire; History; Industrie et commerce; Social aspects; Social aspects. Genre/Form: History; Social conditions; United States; Violence in the workplace

An Exceptional Law: Section 98 and the Emergency State, 1919-1936 - Molinaro, Dennis G. (The Canadian social history series; Osgoode Society for Canadian Legal History, 2017)
During periods of intense conflict, either at home or abroad, governments enact emergency powers in order to exercise greater control over the society that they govern. The expectation though is that once the conflict is over, these emergency powers will be lifted. An Exceptional Law showcases how the emergency law used to repress labour activism during the First World War became normalized with the creation of Section 98 of the Criminal Code, following the Winnipeg General Strike. Dennis G. Molinaro argues that the institutionalization of emergency law became intricately tied to constructing a national identity. Following a mass deportation campaign in the 1930s, Section 98 was repealed in 1936 and contributed to the formation of Canada's first civil rights movement. Portions of it were used during the October Crisis and recently in the Anti-Terrorism Act of 2015. Building on the theoretical framework of Agamben, Molinaro advances our understanding of security as ideology and reveals the intricate and codependent relationship between state-formation, the construction of liberal society, and exclusionary practices. --Publisher's description. Contents: For the protection of people and state -- Defining suspects -- The trial -- Citizens of the world -- Outlaws -- Judgement.
Keywords: 20th century. War and emergency legislation. War and emergency powers. Mesures d'exception; 20th century. War and emergency powers; Canada; Histoire; History; War and emergency legislation

Precarious Employment: Causes, Consequences and Remedies - Procyk, Stephanie; Lewchuk, Wayne; Shields, John (Labour in Canada; 5, 2017)

Indians in the Fur Trade: Their Role as Trappers, Hunters, and Middlemen in the Lands Southwest of Hudson Bay, 1660-1870: with a new introduction - Ray, Arthur J. (Canada 150 Collection, 2017)
First published in 1974, this best-selling book was lauded by Choice as 'an important, ground-breaking study of the Assiniboine and western Cree Indians who inhabited southern Manitoba and Saskatchewan' and 'essential reading for anyone interested in the history of the Canadian west before 1870.' Indians in the Fur Trade makes extensive use of previously unpublished Hudson's Bay Company archival materials and other available data to reconstruct the cultural geography of the West at the time of early contact, illustrating many of the rapid cultural transformations with maps and diagrams. Now with a new introduction and an update on sources, it will continue to be of great use to students and scholars of Native and Canadian history. --Publisher's description

After Prison: Navigating Employment and Reintegration - Ricciardelli, Rose; Peters, Adrienne M.F. (Wilfrid Laurier University Press, 2017)
[This book] opens with a former prisoner's story of reintegration employment experiences. Next, relying on a combination of research interviews, quantitative data, and literature, contributors present an international comparative review of Canada's evolving criminal record legislation; the promotive features of employment; the complex constraints and stigma former prisoners encounter as they seek employment; and the individual and societal benefits of assisting former prisoners attain "gainful" employment. A main theme throughout is the interrelationship between employment and other central conditions necessary for safety and sustenance. [The] book offers suggestions for criminal record policy amendments and new reintegration practices that would assist individuals in the search for employment. Using the evidence and research findings of practitioners and scholars in social work, criminology and law, psychology, and other related fields, the contributors concentrate on strategies that will reduce the stigma of having been in prison; foster supportive relationships between social and legal agencies and prisons and parole systems; and encourage individually tailored resources and training following release of individuals. --Publisher's description. Contents: Section I – The Employment–Re-entry Enigma/Dilemma. Work after prison: one man's transition / James Young [pseudonym] -- Employment and desistance from crime / Kemi S. Anazodo, Christopher Chan, and Rose Ricciardelli -- Employment and criminal offenders with mental illness / Krystle Martin. Section II – Criminal Histories, Employment Prospects, and Moving Forward. Job search, suspended: changes to Canada's Pardon Program and the impact of finding employment / Samantha McAleese -- Vulnerabilities and barriers in post-release employment reintegration as indicated by parolees / Rose Ricciadelli and Taylor Mooney. Section III - Employment reintegration programming: supportive strategies and related outcomes. Is criminal history at the time of employment predictive of job performance? : A comparison of disciplinary actions and terminations in a sample of production workers / Mark G. Harmon, Laura J. Hickman, Alexandra M. Arneson, and Ashley M. Hansen -- Transforming rehabilitation: a critical evaluation of barriers encountered by an offender rehabilitation program for South Asian/Muslim offenders within the new probation service model / Christine Victoria Hough -- Promoting employment opportunities through mentorship for gang-involved youth reintegrating into the community / Adrienne M.F. Peters -- Barriers to community reintegration: the benefits of client-centred case management and pre-employment skills training / Ashley Brown. Section IV - The employment reintegration of unique populations. "Between a rock and a hard place": how being a "convict" hinders finding work in the neo-liberal, late-capitalist economy / Dale C. Spencer -- Does the "wrongful" part of wrongful conviction make a difference in the job market? / Kimberley A. Clow -- Conclusion. Employment reintegration / Rose Ricciardelli and Adrienne M.F. Peters.
Keywords: Canada. BUSINESS & ECONOMICS; Canada. Criminals; Employment; Employment. Genre/Form: Electronic books; Ex-convicts; Labor & Industrial Relations. Criminals; Labor. POLITICAL SCIENCE; Rehabilitation; Rehabilitation. Ex-convicts

Toutes les femmes sont d'abord ménagères : histoire d'un combat féministe pour la reconnaissance du travail ménager : Québec 1968-1985 - Robert, Camille (Collection Économie politique, 2017)
Dès les années 1970, le mouvement féministe québécois s’est largement mobilisé pour obtenir la reconnaissance sociale et économique du travail ménager. Toutefois, à partir des années 1980, cette lutte a été écartée, tant du mouvement des femmes que de son histoire. Combat abandonné, mais non gagné, son fardeau continue de peser aujourd’hui sur les femmes. Si la conciliation travail-famille ou la répartition des tâches dans le couple sont des thématiques présentes dans l’espace public, ce sont encore largement les femmes qui en assument la responsabilité. Ce livre propose une analyse historique des discours féministes sur le travail ménager et des débats entourant sa reconnaissance, à travers trois avenues : la socialisation, le salaire au travail ménager et les réformes gouvernementales. Rendre visible un travail qui ne l’est pas et réinscrire au sein des luttes féministes les enjeux liés à la reproduction sociale, tel est le but de cet ouvrage documenté et rigoureux. --Résumé de l'éditeur
Keywords: 1900-1999; Employés de maison Aspect économique Québec (Province); Employés de maison Québec (Province) Conditions économiques; Feminism; Feminism Québec (Province) History 20th century; Femmes au foyer Québec (Province) Conditions économiques; Féminisme Québec (Province) Histoire 20e siècle; History; Household employees Economic aspects Québec (Province); Household employees Québec (Province) Economic conditions; Housekeepers Québec (Province) Economic conditions; Housekeepers Salaries, etc. Québec (Province); Québec; Salaires Femmes au foyer Québec (Province); Wages Housewives; Wages Housewives Québec (Province)

Unions in Court: Organized Labour and the Charter of Rights and Freedoms - Savage, Larry; Smith, Charles W. (Law and society series (Vancouver, B.C.), 2017)
Since the turn of the twenty-first century, Canadian unions have scored a number of important Supreme Court victories, securing constitutional rights to picket, bargain collectively, and strike. Unions in Court documents the evolution of the Canadian labour movement’s engagement with the Charter, demonstrating how and why labour’s long-standing distrust of the legal system has given way to a controversial, Charter-based legal strategy. This book’s in-depth examination of constitutional labour rights will have critical implications for labour movements as well as activists in other fields. --Publisher's description.

As We Have Always Done: Indigenous Freedom Through Radical Resistance - Simpson, Leanne Betasamosake (Indigenous Americas, 2017)
Across North America, Indigenous acts of resistance have in recent years opposed the removal of federal protections for forests and waterways in Indigenous lands, halted the expansion of tar sands extraction and the pipeline construction at Standing Rock, and demanded justice for murdered and missing Indigenous women. In As We Have Always Done, Leanne Betasamosake Simpson locates Indigenous political resurgence as a practice rooted in uniquely Indigenous theorizing, writing, organizing, and thinking. Indigenous resistance is a radical rejection of contemporary colonialism focused around refusing the dispossession of Indigenous bodies and land. Simpson makes clear that the resistance's goal can no longer be cultural resurgence as a mechanism for inclusion in a multicultural mosaic. Instead, she calls for unapologetic, place-based Indigenous alternatives to the destructive logics of the settler colonial state, including heteropatriarchy, white supremacy, and capitalist exploitation. --Publisher's description.
Keywords: Activism. Ojibwa; Canada; Government relations; Government relations. Ojibwa Indians; Ojibwa Indians; Politics and government. Ojibwa; Politics and government. Ojibwa Indians

The Future of the Professions: How Technology will Transform the Work of Human Experts - Susskind, Richard E.; Susskind, Daniel (Oxford University Press, 2017)
This book predicts the decline of today's professions and describes the people and systems that will replace them. In an Internet society, according to Richard Susskind and Daniel Susskind, we will neither need nor want doctors, teachers, accountants, architects, the clergy, consultants, lawyers, and many others, to work as they did in the 20th century. The Future of the Professions explains how 'increasingly capable systems' -- from telepresence to artificial intelligence -- will bring fundamental change in the way that the 'practical expertise' of specialists is made available in society. The authors challenge the 'grand bargain' -- the arrangement that grants various monopolies to today's professionals. They argue that our current professions are antiquated, opaque and no longer affordable, and that the expertise of their best is enjoyed only by a few. In their place, they propose six new models for producing and distributing expertise in society. The book raises important practical and moral questions. In an era when machines can out-perform human beings at most tasks, what are the prospects for employment, who should own and control online expertise, and what tasks should be reserved exclusively for people? Based on the authors' in-depth research of more than ten professions, and illustrated by numerous examples from each, this is the first book to assess and question the relevance of the professions in the 21st century. --Publisher's description

Summer of My Amazing Luck - Toews, Miriam (https://www.penguinrandomhouse.ca/books/179092/summer-of-my-amazing-luck-by-miriam-toews/9780735274594, 2017)
Welcome to Winnipeg's Have-a-Life housing project... better known as Half-a-Life. Meet eighteen year-old Lucy and flamboyant Lish, two of the single moms who live there. Lucy has no idea who the father of her son is. Lish has four girls, and though she says she doesn't want a man around, she still pines for the father of her twins, a fire-eating busker who was just passing through town. Every Friday is "Deadbeat Dads" visiting day, but otherwise fathers aren't around much at Half-a-Life. Life at Half-a-Life has its ups and downs. The welfare regulations are endless and the ratfink neighbours won't mind their own business. Wagons and cheap strollers are the only way to get to and from the grocery stores, and it's hard enough to make ends meet without the welfare minister trying to take away the child tax credit. So when Lish decides they should go to Colorado to find the fire-eater, Lucy can't help but be excited. They borrow a van held together with coat hangers and electrical tape, load it up with kids and hit the road. Lucy knows they'll never find the fire-eater, but she doesn't know this will be the summer of her amazing luck. --Publisher's description
Keywords: Domestic fiction; Fiction; Humorous fiction; Logement social Romans, nouvelles, etc; Manitoba Winnipeg; Mères de famille monoparentale Romans, nouvelles, etc; Public housing; Public housing Fiction; Single mothers; Single mothers Fiction; Winnipeg (Man.) Fiction

Cobalt: Canada's Forgotten Silver Boom Town - Baldwin, Douglas O. (Indigo Press, 2016)
Cobalt's rich history is full of the romance of prospecting, stories of immense wealth, deaths and mining accidents, struggles to obtain pure drinking water and fire protection, labour-management turmoil, legal conflicts between the town and the mining companies, the founding of the Ontario Provincial Police, and the struggles to provide religion, education, and leisure activities in a mining boom town. Its story is one of immense capital accumulation, labour strife, technological progress, new government policies and ventures, regional growth, and the struggle for law and order. The discovery of the fabulously rich silver mines led to the emergence of northeastern Ontario and helped Toronto to assert its financial dominance. --From Introduction
Keywords: Argent Mines et extraction Ontario Cobalt Histoire; Cobalt (Ont.) Histoire; Cobalt (Ont.) History; History; Ontario Cobalt; Silver mines and mining; Silver mines and mining Ontario Cobalt History

Women Challenging Unions: Feminism, Democracy, and Militancy - Briskin, Linda; McDermott, Patricia; Coulter, Rebecca; Baker, Patricia L.; Cuneo, Carl J.; Stinson, Jane; Richmond, Penni; White, Julie; Kumar, Pradeep; Fudge, Judy; Warskett, Rosemary; Messing, Karen; et al. (University of Toronto Press, 2016)
[This book] is a collection of original papers that presents a vision of an invigorated and vibrant labour movement, one that would actively seek the full participation of women and other traditionally excluded groups, and that would willingly incorporate a feminist agenda. This vision challenges union complicity in the gendered segmentation of the labour market; union support for traditionalist ideologies about women's work, breadwinners, and male-headed families; union resistance to broader-based bargaining; and the marginalization of women inside unions. All of the authors share a commitment to workplace militancy and a more democratic union movement, to women's resistance to the devaluation of their work, to their agency in the change-making process. The interconnected web of militancy, democracy, and feminism provides the grounds on which unions can address the challenges of equity and economic restructuring, and on which the re-visioning of the labour movement can take place. The first of the four sections includes case studies of union militancy that highlight the experiences of individual women in three areas of female-dominated work: nursing, banking, and retailing. The second and third sections focus on the two key arenas of struggle where unions and feminism meet: inside unions, where women activists and staff confront the sexism of unions, and in the labour market, where women challenge their employers and their own unions. The fourth section deconstructs the conceptual tools of the discipline of industrial relations and examines its contribution to the continued invisibility of gender. --Publisher's description

Farm Workers in Western Canada: Injustices and Activism - Broadway, Michael J.; Bucklaschuk, Jill; Contractor, Delna; Dunlop, Darlene A.; Hambly, Brynna; Hamm, Zane; Kennett, Paul; Koshan, Jennifer; Lau, C. F. Andrew; Martinelli, J. Graham; McIntyre, Robin C.; Medeiros, Nelson; et al. (University of Alberta Press, 2016)
Bill 6, the government of Alberta’s contentious farm workers’ safety legislation, sparked public debate as no other legislation has done in recent years. The Enhanced Protection for Farm and Ranch Workers Act provides a right to work safely and a compensation system for those killed or injured at work, similar to other provinces. In nine essays, contributors to Farm Workers in Western Canada place this legislation in context. They look at the origins, work conditions, and precarious lives of farm workers in terms of larger historical forces such as colonialism, land rights, and racism. They also examine how the rights and privileges of farm workers, including seasonal and temporary foreign workers, conflict with those of their employers, and reveal the barriers many face by being excluded from most statutory employment laws, sometimes in violation of the Canadian Charter of Rights and Freedoms. -- Publisher's description
Keywords: Agricultural laborers; Canada, Western; Canada, Western. Agricultural laborers; Legal status, laws, etc.; Legal status, laws, etc. Agricultural laborers; Social conditions. Agricultural laws and legislation

Rethinking Canada: The Promise of Women's History - Campbell, Lara; Myers, Tamara; Perry, Adele (Oxford University Press, 2016)
Now in its seventh edition, Rethinking Canada presents compelling essays on the fascinating lives, struggles, and contributions of women in Canadian history. Reflecting an interdisciplinary approach, this comprehensive and engaging resources stresses the diversity of women's history and demonstrates the analytical richness of ongoing research in the field. Featuring insightful chapter introductions that provide scholarly and historical context for each reading, [the book] helps students gain a more nuanced understanding of women's experiences across Canads's history. --Publisher's description
Keywords: Women -- Canada -- History -- Textbooks

Imperial Plots: Women, Land, and the Spadework of British Colonialism on the Canadian Prairies - Carter, Sarah (University of Manitoba Press, 2016)
Sarah Carter's "Imperial Plots: Women, Land, and the Spadework of British Colonialism on the Canadian Prairies" examines the goals, aspirations, and challenges met by women who sought land of their own. Supporters of British women homesteaders argued they would contribute to the "spade-work" of the Empire through their imperial plots, replacing foreign settlers and relieving Britain of its surplus women. Yet far into the twentieth century there was persistent opposition to the idea that women could or should farm: British women were to be exemplars of an idealized white femininity, not toiling in the fields. In Canada, heated debates about women farmers touched on issues of ethnicity, race, gender, class, and nation. Despite legal and cultural obstacles and discrimination, British women did acquire land as homesteaders, farmers, ranchers, and speculators on the Canadian prairies. They participated in the project of dispossessing Indigenous people. Their complicity was, however, ambiguous and restricted because they were excluded from the power and privileges of their male counterparts. Imperial Plots depicts the female farmers and ranchers of the prairies, from the Indigenous women agriculturalists of the Plains, to the land army women of the First World War. --Publisher's description

Unfree Labour? Struggles of Migrant and Immigrant Workers in Canada - Choudry, Aziz; Smith, Adrian (PM Press, 2016)
Over the past decade, Canada has experienced considerable growth in labour migration. Moreover, temporary labour migration has replaced permanent immigration as the primary means by which people enter Canada. Utilizing the rhetoric of maintaining competitiveness, Canadian employers and the state have ushered in an era of neoliberal migration alongside an agenda of austerity flowing from capitalist crisis. Labour markets have been restructured to render labour more flexible and precarious, and in Canada as in other high-income capitalist labour markets, employers are relying on migrant and immigrant workers as "unfree labour." This book explores labour migration to Canada and how public policies of temporary and guest worker programs function in the global context of work and capitalist restructuring. Contributors are directly engaged with the issues emerging from the influx of temporary foreign workers and Canada's "creeping economic apartheid." --Publisher's description
Keywords: Canada; Foreign workers; Foreign workers Canada; Foreign workers Canada Social conditions; Foreign workers Government policy; Foreign workers Government policy Canada; Foreign workers Social conditions

Animals, Work, and the Promise of Interspecies Solidarity - Coulter, Kendra (Palgrave Macmillan, 2016)
In this thought-provoking and innovative book, Kendra Coulter examines the diversity of work done with, by, and for animals. Interweaving human-animal studies, labor theories and research, and feminist political economy, Coulter develops a unique analysis of the accomplishments, complexities, problems, and possibilities of multispecies and interspecies labor. She fosters a nuanced, multi-faceted approach to labor that takes human and animal well-being seriously and challenges readers to not only think deeply and differently about animals and work but to reflect on the potential for interspecies solidarity. The result is an engaging, expansive, and path-making text. --Publisher's description

Hired Hands: Labour and the Development of Prairie Agriculture, 1880-1930 - Danysk, Cecilia (Canadian social history series, 2016)
Farm workers were central to the development of Canada's prairie West. From 1878, when the first shipment of prairie grain went to international markets, to 1929, when the Great Depression signalled the end of the wheat boom, the role of hired hands changed dramatically. Prior to World War One, hired hands viewed themselves and were treated in the rural community as equals to their farmer employers. Many were farmers in training, informal apprentices who worked for wages so they could accumulate the capital and experience needed to secure their own free 160-acre parcels of land. In later years, as free lands were taken, hired hands increasingly faced the hkehhood of remaining waged labourers on the farms of others. They became agricultural proletarians. In this first full-length study of labour in Canadian prairie agriculture during the period of settlement and expansion, Cecilia Danysk examines the changing work and the growing rural community of the West through the eyes of the workers themselves. World War One was a catalyst in bringing into focus the conflicting nature of labour-capital relations and the divergent aims of workers and their employers. Yet, attempts at union organization were unsuccessful because most hired hands worked alone and because governments assisted farmers by stifling such attempts. The workers' greatest form of workplace control was to walk off one job and find another. --Publisher's description. Previously published in 1995 by McClelland & Stewart. Contents: Introduction -- Labour-Capital Relations in Prairie Agriculture -- Part 1. Beginnings, 1870s-1900. Recruiting the Agricultural Labour Force. Part 2. Expansion, 1900-1918. Agricultural Labour as Apprenticeship -- Class, Culture, and Community -- The Nature of Work --Part 3. Consolidation, 1918-1930. Proletarianization -- The Dialectic of Consent and Resistance -- Conclusion -- Appendix -- Notes -- Index.

Alien Capital: Asian Racialization and the Logic of Settler Colonial Capitalism - Day, Iyko (Duke University Press, 2016)
In [this book] Iyko Day retheorizes the history and logic of settler colonialism by examining its intersection with capitalism and the racialization of Asian immigrants to Canada and the United States. Day explores how the historical alignment of Asian bodies and labor with capital's abstract and negative dimensions became one of settler colonialism's foundational and defining features. This alignment allowed white settlers to gloss over and expunge their complicity with capitalist exploitation from their collective memory. Day reveals this process through an analysis of a diverse body of Asian North American literature and visual culture, including depictions of Chinese railroad labor in the 1880s, filmic and literary responses to Japanese internment in the 1940s, and more recent examinations of the relations between free trade, national borders, and migrant labor. In highlighting these artists' reworking and exposing of the economic modalities of Asian racialized labor, Day pushes beyond existing approaches to settler colonialism as a Native/settler binary to formulate it as a dynamic triangulation of Native, settler, and alien populations and positionalities. --Publisher's description
Keywords: Amérique du Nord Relations raciales Aspect économique; Asians North America Public opinion; Asians Public opinion; Asians Race identity North America; Asiatiques Amérique du Nord Opinion publique; Asiatiques Identité ethnique Amérique du Nord; Capitalism Social aspects; Capitalism Social aspects North America History; History; North America; North America Race relations Economic aspects; Race relations Economic aspects; Stereotypes (Social psychology); Stereotypes (Social psychology) North America; Stéréotypes Amérique du Nord

Ginger Goodwin: A Worker's Friend - Ellyn, Laura (Between the Lines, 2016)
With bright, strong imagery, Ginger Goodwin presents the story of labour activist and martyr Albert “Ginger” Goodwin. This accessible and thoughtful graphic history explores Goodwin’s life, work, and death in the mining communities of Cumberland and Trail, British Columbia. Drawing on local history, and exploring the ways the history of labour organizing affects contemporary movements, Ginger Goodwin is a story that needs to be shared. --Publisher's description

Health and Safety in Canadian Workplaces - Foster, Jason; Barnetson, Bob (Open paths to enriched learning, 2016)
Workplace injuries happen every day and can profoundly affect workers, their families, and the communities in which they live. This textbook provides workers and students with an introduction to effective injury prevention. It pays particular attention to how issues of precarious employment, gender, and ill-health can be better handled in Canadian occupational health and safety (OHS). Health and Safety in Canadian Workplaces offers an extensive overview of central OHS concepts and practices and provides practical suggestions for health and safety advocacy. It attempts to bring OHS into a twenty-first century context by discussing contemporary workplaces and the health effects of new work processes and structures while recognizing that safety has gendered and racialized dimensions. Foster and Barnetson contend that the practice of occupational health and safety can only be understood if we acknowledge that workers and employers have conflicting interests. Who identifies what workplace hazards should be controlled is therefore a product of the broader political economy of employment and one that should be well understood by those working in the field. -- Publisher's description. Contents: Workplace injury in theory and practice -- Legislative framework of injury prevention and compensation -- Hazard recognition, assessment and control -- Physical hazards -- Chemical and biological hazards -- Psycho-social hazards -- Health effects of employment -- Training and injury prevention programs -- Incident investigation -- Disability management and return to work -- The practice of health and safety.
Keywords: Canada; Industrial safety

Canada since 1960: A People's History: A Left Perspective on 50 Years of Politics, Economics and Culture - Gonick, Cy (Lorimer, 2016)
When Winnipeg's Cy Gonick started the magazine Canadian Dimension in 1963 to provide a home for the thinking and analysis of mostly young leftists engaged in Canadian economic, social, cultural, artistic and political issues, he had no grand plan. But Canadian Dimension was welcomed by intellectuals, scholars and students, and it proved enduring. Hundreds of Canada's leading figures of the left have contributed to its pages over the years, writing about every major topic in Canadian public life. This book offers an account of the most important developments in Canadian history from the sixties until today, as seen and interpreted by scholars and writers on the pages of Dimension. Each chapter reviews a major theme, such as Canada's relationship to the U.S., the development of our health care system, the dynamics of Aboriginal-non-Aboriginal relations and the role of Canadian cultural work in shaping Canadian society. Taken together, the book provides a unique and broad perspective on virtually every significant event and development in recent Canadian history. Readers who know the magazine will find this book a compelling summary of how Canada changed in the past five decades, and how the Left saw those changes and challenged them. Readers who discover Canadian Dimension through this book will find a multitude of compelling voices who challenge the dominant neoliberal thinking of mainstream Canadian intellectual life. --Publisher's description.
Keywords: New Left -- Canada

Bedside Matters: The Transformation of Canadian Nursing, 1900-1990 - McPherson, Kathryn (Canadian social history series, 2016)
Nursing embodies the seemingly timeless characteristics of feminine healing, caring, and nurturing, yet this archetypally female vocation also boasts a distinctive and complex history. Bedside Matters traces four generations of Canadian nurses to explore changes in who became nurses, what work they performed, and how they organized to defend their occupational interests. Whether in the apprenticeship method of the early twentieth century or in the present day restructuring of hospital work, the position of nurses within the health-care system has been structured by class, gender, and ethnic and racial relations. Located between the doctors and untrained or subsidiary patient-care attendants, nurses have struggled to define the boundaries of their occupation vis à vis other members of the health-care hierarchy, even as tensions between bedside and administrative nurses created divisions within nursing itself. Focusing on the daily labours of 'ordinary nurses', McPherson argues that the persisting sex-typing of nursing as women's work has meant that gender consistently complicated nursing's easy categorization as either professional or proletariat. Combining archival records and oral histories, the author shows how nurses, in their work, activities, and social and sexual attitudes, sought recognition as skilled workers in the health-care system. --Publisher's description

Inégalités, modes d'emploi: l'analyse sociologique des injustices dans le champ de l'emploi au Canada - Moulin, Stéphane (Presses de l'Université de Montréal, 2016)
Les débats sur les inégalités dans l’emploi adoptent habituellement un point de vue économique en se concentrant sur la distribution des revenus plutôt que sur les processus de différenciation sociale. Pourtant, avant d’être un facteur de production, le travail est foncièrement un rapport social, essentiel à l’intégration des individus. La question des inégalités dans l’emploi doit donc être approchée d’un point de vue sociologique. C’est ce que propose cet ouvrage qui, tout en s’inscrivant dans les débats en cours sur la justice sociale, offre une synthèse remarquable des perspectives théoriques, historiques et comparatives sur les inégalités dans les relations d’emploi. Se fondant sur un ensemble de données statistiques récentes, l’auteur décrit les forces qui animent le champ de l’emploi et qui contribuent à définir le statut social au Canada, et dégage ainsi le rôle décisif des politiques publiques dans ce domaine.
Keywords: Canada; Marché du travail; Sociologie industrielle

Three Men: Three Radical Canadian Voices WWI to ca. 1980 - Murphy, Harvey; Knight, Rolf; Smith, John; Arntzen, Arnt (Draegerman, 2016)
The accounts of three men who are presented here were members of the left in Canada between the first decade of the twentieth century until the late 1970s, when their stories were compiled. --Preface

The Fate of Labour Socialism: The Co-Operative Commonwealth Federation and the Dream of a Working-Class Future - Naylor, James (University of Toronto Press, 2016)
Almost a century before the New Democratic Party rode the first "orange wave," their predecessors imagined a movement that could rally Canadians against economic insecurity, win access to necessary services such as health care, and confront the threat of war. The party they built during the Great Depression, the Co-operative Commonwealth Federation (CCF), permanently transformed the country's politics. Past histories have described the CCF as social democrats guided by middle-class intellectuals, a party which shied away from labour radicalism and communist agitation. James Naylor's assiduous research tells a very different story: a CCF created by working-class activists steeped in Marxist ideology who sought to create a movement that would be both loyal to its socialist principles and appealing to the wider electorate. The Fate of Labour Socialism is a fundamental reexamination of the CCF and Canadian working-class politics in the 1930s, one that will help historians better understand Canada's political, intellectual, and labour history. --Publisher's description.
Keywords: 20th century. Labor; 20th century. Partis politiques; 20th century. Socialism; 20th century. Working class; Canada; Histoire; History; Political activity; Political parties

Toronto's Poor: A Rebellious History - Palmer, Bryan D.; Héroux, Gaétan (Between the Lines, 2016)
Toronto’s Poor reveals the long and too often forgotten history of poor people’s resistance. It details how the homeless, the unemployed, and the destitute have struggled to survive and secure food and shelter in the wake of the many panics, downturns, recessions, and depressions that punctuate the years from the 1830s to the present. Written by a historian of the working-class and a poor people’s activist, this is a rebellious book that links past and present in an almost two-hundred year story of struggle and resistance. It is about men, women, and children relegated to lives of desperation by an uncaring system, and how they have refused to be defeated. In that refusal, and in winning better conditions for themselves, Toronto’s poor create the possibility of a new kind of society, one ordered not by acquisition and individual advance, but by appreciations of collective rights and responsibilities. --Publisher's description

Working Mothers and the Child Care Dilemma: A History of British Columbia's Social Policy - Pasolli, Lisa (UBC Press, 2016)
Finding affordable, quality child care is a challenge for many Canadian families. In some areas of British Columbia, expectant mothers place their children on daycare waiting lists months before they are born. Yet, despite the demand, recent efforts to achieve a universal child care program have stalled. As Working Mothers and the Child Care Dilemma demonstrates, this is nothing new: child care policy in British Columbia has matured in the shadow of a persistent political uneasiness with working motherhood. Charting the growth of the child care movement in this province, Lisa Pasolli examines the arrival of Vancouver’s first crèche in 1912, the teetering steps forward during the debates of the interwar years, the development of child care policy, the rebellious advancements of second-wave feminists in the 1960s and 1970s, and the maturation of provincial and national child care politics since the mid-70s. In addition to revealing much about historical attitudes toward women’s roles at home and in the workplace, Working Mothers and the Child Care Dilemma celebrates the efforts of mothers and advocates who, for decades, have lobbied for child care as a central part of women’s rights as workers, parents, and citizens.... --Publisher's description
Keywords: 1900-1999; British Columbia; Child care; Child care British Columbia; Child care Government policy; Child care Government policy British Columbia History 20th century; Colombie-Britannique Politique sociale Histoire 20e siècle; Enfants Soins Politique gouvernementale Colombie-Britannique Histoire 20e siècle; History; Maternité Colombie-Britannique Histoire 20e siècle; Motherhood; Motherhood British Columbia History 20th century; Mères au travail Colombie-Britannique; Mères au travail Colombie-Britannique Conditions sociales 20e siècle; Travail et familles Colombie-Britannique; Women Employment; Women Employment British Columbia; Work and family; Work and family British Columbia; Working mothers; Working mothers British Columbia; Working mothers British Columbia Social conditions 20th century; Working mothers Social conditions

Worker Voice: Employee Representation in the Workplace in Australia, Canada, Germany, the UK and the US, 1914-1939 - Patmore, Greg (Studies in Labour History, 2016)
This book informs debates about worker participation in the workplace or worker voice by analysing comparative historical data relating to these ideas during the inter-war period in Australia, Canada, Germany, the UK and the US. The issue is topical because of the contemporary shift to a workplace focus in many countries without a corresponding development of infrastructure at the workplace level, and because of the growing ‘representation gap’ as union membership declines. Some commentators have called for the introduction of works councils to address these issues. Other scholars have gone back and examined the experiences with the non-union Employee Representation Plans (ERPs) in Canada and the US. This book will test these claims through examining and comparing the historical record of previous efforts of five countries during a rich period of experimentation between the Wars. --Publisher's description.

Social Determinants of Health: Canadian Perspectives - Raphael, Dennis (Canadian Scholars' Press, 2016)
The third edition of Social Determinants of Health focuses on the socio-economic conditions that shape the health of individuals and communities. This edited collection includes contributions from top academics and high-profile experts from across the country. The chapters take a public policy approach that sees the mainsprings of health emerging from the social distribution of resources. The collection as a whole integrates insights from the health sciences, the sociology of health, and the political economy of health. This revised edition has been well updated and includes a greater focus on the political pathways and mechanisms that explain how the social determinants of health come to be distributed amongst the population; early childhood development in Canada in relation to other developed nations; Indigenous health and its determinants; public policy and the social safety net; and the growing network of civil society organizations addressing the inequitable distribution of the social determinants of health. --Publisher's description
Keywords: Public health -- Social aspects -- Canada

A Future Without Hate or Need: The Promise of the Jewish Left in Canada - Reiter, Ester (Between the Lines, 2016)
Driven from their homes in Russia, Poland, and Romania by pogroms and poverty, many Jews who came to Canada in the wave of immigration after the 1905 Russian revolution were committed radicals. A Future Without Hate or Need brings to life the rich and multi-layered lives of a dissident political community, their shared experiences and community-building cultural projects, as they attempted to weave together their ethnic particularity—their identity as Jews—with their internationalist class politics.--Publisher's description
Keywords: 1900-1999; Canada; Canada Emigration and immigration History 20th century; Canada Émigration et immigration Histoire 20e siècle; Communism and Judaism; Communism and Judaism Canada History 20th century; Communisme et judaïsme Canada Histoire 20e siècle; History; Jewish socialists Canada; Jews; Jews Canada History; Jews Canada History 20th century; Jews Canada Identity; Jews Canada Politics and government; Jews Canada Social life and customs; Jews Identity; Jews Political activity Canada; Jews Politics and government; Jews Social life and customs; Judaism and politics; Judaism and politics Canada History 20th century; Judaïsme et politique Canada Histoire 20e siècle; Juifs Canada Histoire; Juifs Canada Histoire 20e siècle; Juifs Canada Identité; Juifs Canada Mœurs et coutumes; Juifs Canada Politique et gouvernement; Socialism and Judaism; Socialism and Judaism Canada History 20th century; Socialisme et judaïsme Canada Histoire 20e siècle

Building Global Labor Solidarity in a Time of Accelerating Globalization - Scipes, Kim (Haymarket Books, 2016)
Since the 1980s, the world’s working class has been under continual assault by the forces of neoliberalism and imperialism. In response, new labor movements have emerged across the Global South—from Brazil and South Africa to Indonesia and Pakistan.Building Global Labor Solidarity in a Time of Accelerating Globalization is a call for international solidarity to resist the assaults on labor’s power. This collection of essays by international labor activists and academics examines models of worker solidarity, different forms of labor organizations, and those models’ and organizations’ relationships to social movements and civil society. --Publisher's description.

Not Talking Union: An Oral History of North American Mennonites and Labour - Thiessen, Janis (McGill-Queen's University Press, 2016)
This book investigates the labour history of a people who have not been involved in the twentieth-century labour movement in large numbers: North American Mennonites. It explores their historically-constructed attitudes toward organized labour and unions, which it attempts to understand on its own terms. Although Mennonites are typically associated with rural life, they in fact became very involved as workers in specific locations in both traditional Mennonite enclaves in Ohio, Indiana, Ontario, and Manitoba, and those to which they migrated in the twentieth century, such as British Columbia and California. Mennonites in these locales found employment both as field workers for large agri-business operations (for example, the orchards and packing plants of the San Joaquin Valley in California) and as factory hands in manufacturing firms (such as the automotive factories in southern Ontario). The late twentieth century experiences of North American Mennonites in these settings caused them to confront and reassess their attitudes toward unions. A study of these Mennonites--united by transnational ties of ethnic and religious identity yet shaped, at times, in distinct ways by their differing geographic locations, immigration histories and ethnic origins, denominational ties, and class positions--provides insights into how and why the majority of North American Mennonites have rejected labour unions in the late twentieth and early twenty-first centuries. The oral histories of the 113 Mennonites interviewed provide insight into why many working North Americans are not union supporters, and how people in general negotiate tensions between their commitments to faith and conscience and the demands of their employment. An important aim of the book is to bring labour historians and historians of religion into conversation. --Publisher's description

A Town Called Asbestos: Environmental Contamination, Health, and Resilience in a Resource Community - Van Horssen, Jessica (Nature, history, society; Variation: Nature, history, society., 2016)
For decades, manufacturers from around the world relied on asbestos from the town of Asbestos, Quebec, to produce fire-retardant products. Then, over time, people learned about the mineral's devastating effects on human health. Dependent on this deadly industry for their community's survival, the residents of Asbestos developed a unique, place-based understanding of their local environment; the risks they faced living next to the giant opencast mine; and their place within the global resource trade. This book unearths the local/global tensions that defined Asbestos's proud and painful history to reveal the challenges similar resource communities have faced--and continue to face today. -- Publisher's description. Contents: Foreword: the long dying / Graeme Wynn -- Introduction: introducing Asbestos -- Creation stories: Asbestos before 1918 -- Land with a future, not a past, 1918-49 -- Negotiating risk, 1918-49 -- Essential characteristics, 1918-49 -- Bodies collide: the strike of 1949 -- "Une ville qui se deplace," 1949-83 -- Useful tools, 1949-83 -- Altered authority, 1949-83 -- Conclusion: surviving collapse: Asbestos post-1983.
Keywords: Asbestos mines and mining; Asbestos. Amiante; Asbestos. Asbestos industry; Asbestos. Asbestos mines and mining; Asbestos. Asbestos. Environmental Exposure; Aspect de l'environnement; Aspect politique; Aspect sanitaire; Environmental aspects; Health aspects; Industrie; Mines et extraction; Political aspects; Qubec (Province); economics. Cities; economics. History, 20th Century; history. Environmental Illness; psychology. Denial (Psychology) Mining

Building the Power: The Labourers' Union in British Columbia - Warrior, M. C. (Construction and Specialized Workers' Union, LiUNA Local 1611, 2016)
“Building The Power” is a fascinating look into the history of LiUNA Local 1611, documenting the dramatic events and accomplishments of its members since 1937, written by Local 1611’s Strategic Researcher and labour activist Mark Warrior. In 1953, Stacey Warner, while organizing pipeline workers, was threatened with a shotgun by a company thug hired for the sole purpose of intimidation. The police did not take notice. In 1981, the Labour Relations Board ignored the fact that the employer offered union member a $1,000 bribe to change his vote—right at the Labour Relations Board office—when LiUNA Local 1070 was attempting to certify his bargaining unit. Ignoring naked violence had been replaced by ignoring blatant lawbreaking. But the result was not the same. Warner succeeded in organizing the workers. These are examples of the conflict and often dangerous scenarios those in the Labour Movement have faced in their effort to secure workers’ right and fair working wages and safe working conditions. --Website description
Keywords: Laborers' International Union of North America; Laborers' International Union of North America. Local 1611

North to Bondage: Loyalist Slavery in the Maritimes - Whitfield, Harvey Amani (UBC Press, 2016)
Many Canadians believe their nation fell on the right side of history in harbouring escaped slaves from the United States. In fact, in the wake of the American Revolution, many Loyalist families brought slaves with them when they settled in the Maritime colonies of British North America. Once there, slaves used their traditions of survival, resistance, and kinship networks to negotiate their new reality. Harvey Amani Whitfield’s book, the first on slavery in the Maritimes, is a startling corrective to the enduring and triumphant narrative of Canada as a land of freedom at the end of the Underground Railroad. --Publisher's description

Soviet Princeton: Slim Evans and the 1932-33 Miners' Strike - Bartlett, Jon; Ruebsaat, Rika (New Star Books, 2015)
The winter of 1932-33 saw the small interior town of Princeton, BC divided. Charges of outside agitators and charges by mounted provincial police into picket lines of workers, Ku Klux Klan threats and a beating and cross-burning, the kidnapping of legendary labour organizer Slim Evans who was bundled onto the next train out of town (though he returned soon enough) — Princeton's few thousand citizens saw much of the human drama of the Great Depression play out right in their own lives over the course of just a few months. A ten percent paycut, in the depths of the Depression, galvanized the miners working Princeton's three coalmines into unionizing, and they brought in Arthur "Slim" Evans from the Workers Unity League to help them. Meanwhile, north of town, one of the federal government's Relief Camps had opened up, and soon Canadian Labour Defence League organizers were at work there. "Outside agitators" became the by-word as the town's merchants and propertied establishment rallied around the cause — to defeat the "Communist menace" that threatened the prospects of their little town. They were given voice by the colourful local paper the Princeton Star, whose archives provide the source material for much of Jon Bartlett and Rika Ruebsaat's engrossing history. Soviet Princeton provides an interesting sidebar as well to Canadian left-labour history, as two years later, one of the main actors in the Princeton drama, Slim Evans, led the On-to-Ottawa Trek of homeless and unemployed protesting the relief camps and their conditions. --Publisher's description

Bomb Girls: Trading Aprons for Ammo - Dickson, Barbara (Dundurn, 2015)
An account of the women working in high-security, dangerous conditions making bombs in Toronto during the Second World War. What was it like to work in a Canadian Second World War munitions factory? What were working conditions like? Did anyone die? Just how closely did female employees embody the image of “Rosie the Riveter” so popularly advertised to promote factory work in war propaganda posters? How closely does the recent TV show, Bomb Girls, resemble the actual historical record of the day-to-day lives of bomb-making employees? Bomb Girls delivers a dramatic, personal, and detailed review of Canada’s largest fuse-filling munitions factory, situated in Scarborough, Ontario. First-hand accounts, technical records, photographic evidence, business documentation, and site maps all come together to offer a rare, complete account into the lives of over twenty-one thousand brave men and women who risked their lives daily while handling high explosives in a dedicated effort to help win the war. -- Publisher's description

We’re Going to Run This City: Winnipeg’s Political Left after the General Strike - Epp-Koop, Stefan (University of Manitoba Press, 2015)
[E]xplores the dynamic political movement that came out of the largest labour protest in Canadian history and the ramifications for Winnipeg throughout the 1920s and 1930s. Few have studied the political Left at the municipal level—even though it is at this grassroots level that many people participate in political activity. Winnipeg was a deeply divided city. On one side, the conservative political descendants of the General Strike’s Citizen’s Committee of 1000 advocated for minimal government and low taxes. On the other side were the Independent Labour Party and the Communist Party of Canada, two parties rooted in the city’s working class, though often in conflict with each other. The political strength of the Left would ebb and flow throughout the 1920s and 1930s but peaked in the mid-1930s when the ILP’s John Queen became mayor and the two parties on the Left combined to hold a majority of council seats. Astonishingly, Winnipeg was governed by a mayor who had served jail time for his role in the General Strike. --Publisher's description. Contents: Introduction -- The second round --The reign of the furies -- The revolutionary party on the parliamentary map -- A victory for thoseengage in the struggle for better conditions -- For freedom's cause, your bayonet's bright -- A bombshell to many citizens -- Conclusion.

Lunch-Bucket Lives: Remaking the Workers' City - Heron, Craig (Between the Lines, 2015)
Using Hamilton's local history to tell the wider story of the North American working-class, Lunch-Bucket Lives investigates how workers dealt with the profound changes in their lives between the 1890s and the 1930s, as wage-earners, family members, and participants in various social networks. Heron takes wage-earning as a central element in working-class life, but also looks beyond the workplace into the households and neighbourhoods - settlement patterns and housing, marriage, child care, domestic labour, public health, schooling, charity and social work, popular culture, gender identities, ethnicity and ethnic conflict, and politics in various forms - presenting a comprehensive view of working-class life in the first half of the twentieth century. --Publisher's description
Keywords: 19th century; 19th century. Working class; 20th century; 20th century. Social conditions. Working class; Hamilton; Ontario; Social conditions; Working class

Work, Industry, and Canadian Society - Krahn, Harvey; Lowe, Graham S.; Hughes, Karen (Nelson Education, 2015)
Work, Industry and Canadian Society brings to light the social ramifications of work. With a focus on the Canadian workplace, the author team examines how individual, societal, national, and global issues shape this central human activity. In this seventh edition, the text draws upon the growing literature on work and employment, organizations, and management approaches to incorporate recent empirical findings, review new and ongoing theoretical and policy debates, and provide a more international perspective. The authors use their years of experience in research and teaching to compose this comprehensive volume on the past, present and future of work in Canada. --Publisher's description
Keywords: Work -- Social aspects -- Canada -- Textbooks

Women's History - Kubik, Wendee; Marchildon, Gregory P. (History of the Prairie West Series, 2015)
This fifth volume of the History of the Prairie West Series contains a broad range of articles spanning the 1870s to the present and examines the mostly unexplored place of women in the history of the Canada's Prairie Provinces. From "Spinsters Need Not Apply" to "Negotiating Sex: Gender in the Ukrainian Bloc Settlement," women’s roles in politics, law, agriculture, labour, and journalism are explored to reveal a complex portrait of women struggling to find safety, have careers, raise children, and be themselves in an often harsh environment.
Keywords: pioneer; prairies; women

Decolonizing Employment: Aboriginal Inclusion in Canada's Labour Market - MacKinnon, Shauna (University of Manitoba Press, 2015)
Indigenous North Americans continue to be overrepresented among those who are poor, unemployed, and with low levels of education. This has long been an issue of concern for Indigenous people and their allies and is now drawing the attention of government, business leaders, and others who know that this fast-growing population is a critical source of future labour. Shauna MacKinnon's Decolonizing Employment: Aboriginal Inclusion in Canada's Labour Market is a case study with lessons applicable to communities throughout North America. Her examination of Aboriginal labour market participation outlines the deeply damaging, intergenerational effects of colonial policies and describes how a neoliberal political economy serves to further exclude Indigenous North Americans. MacKinnon's work demonstrates that a fundamental shift in policy is required. Long-term financial support for comprehensive, holistic education and training programs that integrate cultural reclamation and small supportive learning environments is needed if we are to improve social and economic outcomes and support the spiritual and emotional healing that Aboriginal learners tell us is of primary importance. --Publisher's description. Contents: Introduction -- Social exclusion, poverty, inequality, and policy in the neo-liberal age -- The labour market, policy, and Canada's aboriginal population -- The Manitoba labour force and the policy environment -- Decolonization: confronting the elephant in the room -- Assessing the impact of neo-liberal training policy -- A continuum of training responses -- Voices from the front lines -- Lessons learned: implications for policy -- Conclusion. Includes bibliographical references (pages 193-204) and index.
Keywords: 21st century; Canada; Case studies. Autochtones; Case studies. Labor policy; Case studies. Native peoples; Conditions sociales; Economic conditions; Education; Employment; Labor policy; Politique gouvernementale; Social conditions; Travail

Transition to Common Work: Building Community at the Working Centre - Mancini, Joseph; Mancini, Stephanie (Wilfrid Laurier University Press, 2015)
The Working Centre in the downtown core of Kitchener, Ontario, is a widely recognized and successful model for community development. Begun from scratch in 1982, it is now a vast network of practical supports for the unemployed, the underemployed, the temporarily employed, and the homeless, populations that collectively constitute up to 30 percent of the labour market both locally and across North America. Transition to Common Work is the essential text about The Working Centre--its beginnings thirty years ago, the lessons learned, and the myriad ways in which its strategies and innovations can be adapted by those who share its goals. The Working Centre focuses on creating access-to-tools projects rather than administrative layers of bureaucracy. This book highlights the core philosophy behind the centre's decentralized but integrated structure, which has contributed to the creation of affordable services. Underlying this approach are common-sense innovations such as thinking about virtues rather than values, developing community tools with a social enterprise approach, and implementing a radically equal salary policy. For social workers, activists, bureaucrats, and engaged citizens in third-sector organizations (NGOs, charities, not-for-profits, co-operatives), this practical and inspiring book provides a method for moving beyond the doldrums of "poverty relief" into the exciting world of community building. --Publisher's website. Contents: Part 1: The Working Centre takes root -- Introduction: beyond us and them -- Building community: the Working Centre's roots -- Liberation from overdevelopment -- Part 2: Community engagement -- The Virtues -- St. John's Kitchen: redistribution through cooperation -- Searching for work at the Help Centre -- The nuts and bolts of an alternative organization -- Part 3: Toward a philosophy of work -- Ethical imagination: the Working Centre's approach to salaries -- Community tools -- Small is beautiful: re-embedding reciprocal relationships in daily work -- Conclusion: transition to common work -- Map of the Working Centre buildings and projects -- Map of the Working Centre locations in downtown Kitchener -- A thirty-year chronology of the Working Centre -- People of the Working Centre.
Keywords: Community development; Ontario; Services for. Social work with the unemployed. Unemployed; Waterloo (Regional municipality) Poor; Waterloo (Regional municipality) Social work with the unemployed; Waterloo (Regional municipality) Unemployed

Work in a Warming World - McBride, Stephen; Lipsig-Mummé, Caria (Queen's Policy Studies Series, 2015)
Global warming is perhaps the greatest challenge facing the twenty-first century. Environmental polices on the one hand, and economic and labour market polices on the other, often exist in separate silos creating a dilemma that Work in a Warming World confronts. The world of work - goods, services, and resources - produces most of the greenhouse gases created by human activity. In engaging essays, contributors demonstrate how the world of work and the labour movement need to become involved in the struggle to slow global warming, and the ways in which environmental and economic policies need to be linked dynamically in order to effect positive change. Addressing the dichotomy of competing public policies in a Canadian context, Work in a Warming World presents ways of creating an effective response to global warming and key building blocks toward a national climate strategy. --Publisher's description, Contents: Introduction / Stephen McBride and Carla Lipsig-Mummé -- International constraints on green strategies : Ontario's WTO defeat and public sector remedies / Scott Sinclair and Stuart Trew -- Unions and climate change in Europe : the contrasting experience of Germany and the UK / John Calvert -- Gendered emissions : counting greenhouse gas emissions by gender and why it matters / Marjorie Griffin Cohen -- Canadian labour's climate dilemma / Geoffrey Bickerton and Carla Lipsig-Mummé -- Renewable energy development as industrial strategy / Mark Winfield -- (Re)building sustainable infrastructure : implications for engineers / Kean Birch and Dalton Wudrich -- Construction and climate change : overcoming roadblocks to achieving green workplace competencies / John Calvert -- Labour and the greening of hospitality : raising standards or union greenwashing? / Steven Tufts and Simon Milne -- Cities, climate change, and the green economy / Stephen McBride, John Shields, and Stephanie Tombari -- Renewable energy, sustainable jobs : the case of the Kingston, Ontario Region / Andrea Megan MacCallum, Lindsay Napier, John Holmes, and Warren Edward Mabee.

Gendered Pasts: Historical Essays in Feminity and Masculinity in Canada - McPherson, Kathryn; Morgan, Cecilia; Forestell, Nancy M. (Canadian social history series, 2015)
It is commonplace today to suggest that gender is socially constructed, that the roles women and men fulfill in their daily lives have been created and defined for them by society and social institutions. But how have men and women negotiated and navigated the gender roles that have been thrust upon them? With Gendered Pasts, Kathryn McPherson, Cecilia Morgan, and Nancy M. Forestell have collected eleven engaging essays that seek to answer this question in a wide-ranging exploration of specific gendered dimensions of nineteenth- and twentieth-century Canadian history.The contributors cover all manner of topics related to gender and history across Canada, including: female vagrancy; gambling, drinking, and sex; the role of the miner's wife; the portrayal of gay men; and the sharply defined role of nurses. Unusual in its breadth, Gendered Pasts is essential to the understanding of the various threads and themes in Canadian gender history. Previously published by Oxford University Press, . --Publisher's description
Keywords: Sex role -- Canada -- History -- 19th century

Precarious Worlds: Contested Geographies of Social Reproduction - Meehan, Katie; Strauss, Kendra (Geographies of justice and social transformation, 2015)
This edited collection contributes to the theoretical literature on social reproduction - defined by Marx as the necessary labor to arrive the next day at the factory gate - and extended by feminist geographers and others into complex understandings of the relationship between paid labor and the unpaid work of daily life. The volume explores new terrain in social reproduction with a focus on the challenges posed by evolving theories of embodiment and identity, nonhuman materialities, and diverse economies. --Publisher's description
Keywords: Economics Sociological aspects; Feminist economics; Feminist geography; Géographie féministe; Households Economic aspects; Labor; Ménages (Statistique) Aspect économique; Travail; labor; Économie féministe

The Dignity of Every Human Being: New Brunswick Artists and Canadian Culture between the Great Depression and the Cold War - Niergarth, Kirk; University of Toronto Press (Canadian social history series, 2015)
“The Dignity of Every Human Being” studies the vibrant New Brunswick artistic community which challenged “the tyranny of the Group of Seven” with socially-engaged realism in the 1930s and 40s. Using extensive archival and documentary research, Kirk Niergarth follows the work of regional artists such as Jack Humphrey and Miller Brittain, writers such as P.K. Page, and crafts workers such as Kjeld and Erica Deichmann. The book charts the rise and fall of “social modernism” in the Maritimes and the style’s deep engagement with the social and economic issues of the Great Depression and the Popular Front. Connecting local, national, and international cultural developments, Niergarth’s study documents the attempts of Depression-era artists to question conventional ideas about the nature of art, the social function of artists, and the institutions of Canadian culture. “The Dignity of Every Human Being” records an important and previously unexplored moment in Canadian cultural history. --Publisher's description

Beyond Brutal Passions: Prostitution in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (McGill-Queen's University Press, 2015)
During a time of significant demographic, geographic, and social transition, many women in early nineteenth-century Montreal turned to prostitution and brothel-keeping to feed, clothe, protect, and house themselves and their families. Beyond Brutal Passions is a close study of the women who were accused of marketing sex, their economic and social susceptibilities, and the strategies they employed to resist authority and assert their own agency. Referencing newspapers, parish registers, census returns, coroners' reports, city directories, documents of Catholic and Protestant institutions, police books, and court records, Mary Anne Poutanen reveals how these women confronted limited alternatives and how they fought against established authority in the pursuit of their livelihoods. She details these women's lives not only as prostitutes but also as wives, mothers, sisters, and daughters who reconstructed the bonds of kinship and solidarity. An insightful history of prostitution, Beyond Brutal Passions explores the complicated relationships between women accused of prostitution and the society in which they lived and worked. A social history exploring the intersections between those accused of prostitution, their neighbours, families, clients, and criminal justice. --Publisher's summary (WorldCat record)

Cracked: How Telephone Operators Took on Canada's Largest Corporation ... And Won! - Roberts, Joan M. (Dundurn, 2015)
The story of the Bell Canada union drive and the phone operator strike that brought sweeping reform to women’s workplace rights. In the 1970s, Bell Canada was Canada’s largest corporation. It employed thousands of people, including a large number of women who worked as operators and endured very poor pay and working conditions. Joan Roberts, a former operator, tells the story of how she and a group of dedicated labour organizers helped to initiate a campaign to unionize Bell Canada’s operators. From the point of view of the workers and the organizers, Roberts tells an important story in Canada’s labour history. The unionization of Bell Canada’s operators was a huge victory for Canada’s working women. The victory at Bell established new standards for women in other so-called “pink-collar” jobs. --Publisher's description

Continental Crucible: Big Business, Workers and Unions in the Transformation of North America - Roman, Richard; Velasco Arregui, Edur (Fernwood, 2015)
The crucible of North American neo-liberal transformation is heating up, but its outcome is far from clear. [This book] examines the clash between the corporate offensive and the forces of resistance from both a pan-continental and a class struggle perspective. This book also illustrates the ways in which the capitalist classes in Canada, Mexico and the United States used free trade agreements to consolidate their agendas and organize themselves continentally. The failure of traditional labour responses to stop the continental offensive being waged by big business has led workers and unions to explore new strategies of struggle and organization, pointing to the beginnings of a continental labour movement across North America. The battle for the future of North America has begun. --Publisher's description
Keywords: Commerce; Corporate power; Economic aspects; Free trade; Labor Unions; Labor movement; Social conditions; Working class

Building a Better World: An Introduction to the Labour Movement in Canada - Ross, Stephanie; Savage, Larry; Silver, Jim; Black, Errol (Fernwood Books, 2015)
Substantially revised and updated for a new generation of labour studies students, this third edition of Building a Better World offers a comprehensive introductory overview of Canada's labour movement. The book includes an analysis of why workers form unions; assesses their organization and democratic potential; examines issues related to collective bargaining, grievances and strike activity; charts the historical development of labour unions; and describes the gains unions have achieved for their members and all working people. -- Publisher's description. Contents: What is a union? (pages 1-5) -- Understanding unions (pages 6-18) -- Early union struggles in Canada (pages 19-45) -- From Keynesianism to neoliberalism: Union breakthroughs and challenges (pages 46-70) -- Unions in the workplace (pages 71-91) -- Unions and political action (pages 92-111) -- How do unions work? (pages 112-137) -- What difference do unions make? (pages 128-143) -- Who belongs to unions? Who doesn't and why? (pages 144-163) -- The future of unions: Decline or renewal? (pages 164-189) -- References (pages 190-204) - Index (pages 206-216).

Economics for Everyone: A Short Guide to the Economics of Capitalism - Stanford, Jim; Biddle, Tony (Fernwood Books, 2015)
This concise and readable book provides non-specialist readers with all the information they need to understand how capitalism works (and how it doesn’t). Economics for Everyone, now in its second edition, is an antidote to the abstract and ideological way that economics is normally taught and reported. Key concepts such as finance, competition and wages are explored, and their importance to everyday life is revealed. --Publisher's description
Keywords: Capitalism; Economics; Working class

Solitudes of the Workplace: Women in Universities - Whittaker, Elvi (McGill-Queen's University Press, 2015)
Solitudes of the Workplace focuses on experiences of marginalization, uncertainty and segregation created by the hierarchical structures of categories in universities and by gendered identities. Studying a wider range of women’s roles in universities than prior research, the experiences of support staff, senior administrators, researchers, non-academic administrators, and contract teachers are added to those of faculty and students. The essays show how attempts to introduce new knowledge are manoeuvered and the resistance this process can encounter, as well as the ways in which institutional policies can blur and change identities. Addressing longstanding issues such as the entanglement of gender and the assessment of merit, attention is also given to how new identities are claimed and successfully projected. Essays presenting workers' points of view reveal the confusion that occurs when official policy and everyday knowledge conflict, when processes like tenure and other status changes create troublesome realities, and when it becomes routine to experience status denigration. Within the social order of the university and its existing boundaries, gender issues of past decades sometimes surface, but all too often remain an unspoken presence. Solitudes of the Workplace is a revealing look at the isolating experiences and inequities inherent in these institutional environments. --Publisher's description.

Security, Dissent, and the Limits of Toleration in War and Peace, 1914-1939 - Wright, Barry; Tucker, Eric; Binnie, Susan W. S. (Canadian State Trials, 2015)
This latest collection in our State Trials series, the fourth, looks at the legal issues raised by the repression of dissent from the outset of World War One through the 1930s and the Great Depression. Topics covered include enemy aliens, conscription and courts-martial in World War I, the trials following the Winnipeg General Strike, sedition laws and prosecutions generally and their application to labour radicals in particular, the 1931 trial of the Communist Party leaders, and the religious-political dissent of the Doukhobors. All regions of the country are covered, and special attention given in one essay to Quebec’s repression of radicalism. The volume focusses attention on older manifestations of contemporary dilemmas: what are the acceptable limits of dissent in a democracy, and what limits should be placed on state responses to perceived challenges to its authority. --Publisher's description
Keywords: Canada; Crimes et délits politiques Canada Histoire; History; Political crimes and offenses; Political crimes and offenses Canada History; Procès (Crimes et délits politiques) Canada; Trials (Political crimes and offenses); Trials (Political crimes and offenses) Canada

Employment Equity in Canada: The Legacy of the Abella Report - Agócs, Carol (2014)
In the mid-1980s, the Abella Commission on Equality in Employment and the federal Employment Equity Act made Canada a policy leader in addressing systemic discrimination in the workplace. More than twenty-five years later, Employment Equity in Canada assembles a distinguished group of experts to examine the state of employment equity in Canada today. Examining the evidence of nearly thirty years, the contributors – both scholars and practitioners of employment policy – evaluate the history and influence of the Abella Report, the impact of Canada’s employment equity legislation on equality in the workplace, and the future of substantive equality in an environment where the Canadian government is increasingly hostile to intervention in the workplace. They compare Canada’s legal and policy choices to those of the United States and to the UN Convention on the Rights of Persons with Disabilities, and examine ways in which the concept of employment equity might be expanded to embrace other vulnerable communities. Their observations will be essential reading for those seeking to understand the past, present, and future of Canadian employment and equity policy. --Publisher's description.

French Canadians, Furs, and Indigenous Women in the Making of the Pacific Northwest - Barman, Jean (UBC Press, 2014)
In [this book], Jean Barman rewrites the history of the Pacific Northwest from the perspective of French Canadians involved in the fur economy, the indigenous women whose presence in their lives encouraged them to stay, and their descendants. Joined in this distant setting by Quebec paternal origins, the French language, and Catholicism, French Canadians comprised Canadians from Quebec, Iroquois from the Montreal area, and metis combining Canadian and indigenous descent. For half a century, French Canadians were the largest group of newcomers in this region extending from Oregon and Washington east into Montana and north through British Columbia. Here, they facilitated the early overland crossings, drove the fur economy, initiated non-wholly-indigenous agricultural settlement, eased relations with indigenous peoples, and ensured that, when the Pacific Northwest was divided in 1846, the northern half would go to Britain, giving today's Canada its Pacific shoreline. In the generations that followed, Barman argues, descendants did not become Metis, as the term has been used to describe a people apart, but rather drew on both their French Canadians and indigenous inheritances to make the best possible lives for themselves and those around them. --Publisher's description. Contents: Pt. 1. French Canadians And The Fur Economy. To Be French Canadian -- Facilitating the Overland Crossings -- Driving the Fur Economy -- Deciding Whether to Go or to Stay. Pt. 2. French Canadians, Indigenous Women, And Family Life In The Fur Economy. Taking Indigenous Women Seriously -- Innovating Family Life -- Initiating Permanent Settlement -- Saving British Columbia for Canada. Pt. 3. Beyond The Fur Economy. Negotiating Changing Times -- Enabling Sons and Daughters -- To Be French Canadian and Indigenous -- Reclaiming the Past. Includes bibliographical references (pages 404-430) and index.
Keywords: Commerce; Fur trade; Histoire Femmes autochtones; Histoire Fourrures; Histoire Fur trade. Genre/Form: History; History Canadiens d'origine franaise; History Native women; History. French Canadians; Nord-Ouest, Cte (Amrique du Nord); Northwest, Pacific

Unions Matter: Advancing Democracy, Economic Equality, and Social Justice - Behrens, Matthew (Between the Lines, 2014)
Income inequality has risen rapidly over the past three decades. In Canada it is now at its highest level since 1928. One of the root causes: the consistent chipping away of labour rights. The labour movement has been left unable to maintain membership levels and incapable of narrowing the income gap through collective bargaining, with profound implications for Canadians. Labour rights are human rights. They provide a powerful democratic counterweight to the growing power of corporations and the wealthy, and are key to a functioning democracy. Unions Matter affirms the critical role that unions and strong labour rights play in creating greater economic equality and promoting the social wellbeing of all citizens. --Publisher's description
Keywords: Canada; Canadian Foundation for Labour Rights; Democracy; Employee rights; Equality; Labor movement; Labor unions; Social aspects; Social justice

Equality Deferred: Sex Discrimination and British Columbia's Human Rights State. - Clément, Dominique (Law and society series (Vancouver, B.C.), 2014)
[This book] traces the history of sex discrimination in Canadian law and the origins of human rights legislation, demonstrating how governments inhibit the application of their own laws, and how it falls to social movements to create, promote, and enforce these laws. Focusing on British Columbia – the first jurisdiction to prohibit discrimination on the basis of sex – Clément documents a variety of absurd, almost unbelievable, acts of discrimination. The province was at the forefront of the women’s movement, which produced the country’s first rape crisis centres, first feminist newspaper, and first battered women’s shelters. And yet nowhere else in the country was human rights law more contested. For an entire generation, the province’s two dominant political parties fought to impose their respective vision of the human rights state. This history of human rights law, based on previously undisclosed records of British Columbia’s human rights commission, begins with the province’s first equal pay legislation in 1953 and ends with the collapse of the country’s most progressive human rights legal regime in 1984. This book is not only a testament to the revolutionary impact of human rights on Canadian law but also a reminder that it takes more than laws to effect transformative social change. --Publisher's description. Contents: Introduction -- "No Jews or dogs allowed": anti-discrimination law -- Gender and Canada's human rights state -- Women and anti-discrimination law in British Columbia, 1953-69 -- Jack Sherlock and the failed Human Rights Act, 1969-73 -- Kathleen Ruff and the Human Rights Code, 1973-79 -- Struggling to innovate, 1979-83 -- Making new law under the Human Rights Code -- The politics of (undermining) human rights : the Human Rights Act, 1983-84 -- Conclusion.

Revolutionizing Retail: Workers, Political Action, and Social Change - Coulter, Kendra (Palgrave Macmillan, 2014)
Retail workers are a large labor force, yet their jobs are generally devalued and dominated by low wages, precarious conditions, and disrespect. Coulter draws on three years of comparative research on retail workers and political action, including fieldwork in Canada, the United States, and Sweden, to explore what is needed to improve workers' wellbeing and transform retail work. The only book of its kind, Revolutionizing Retail explains the strategies being used to improve retail jobs and retail workers' quality of life, including diverse forms of organizing, public policy, and good management. Coulter analyzes the degree to which current efforts are succeeding, and what lessons they offer about the present and future of work, forms of agency, and class, gender, and race relations. The power of culture, emotions, and workers' personal experiences of political action are at the heart of this engaging discussion of the challenges and possibilities of social change. --Publisher's description
Keywords: Commerce de détail Personnel; Labor movement; Mouvement ouvrier; Retail trade Employees; Social change

Red Skin, White Masks: Rejecting the Colonial Politics of Recognition - Coulthard, Glen Sean (Indigenous Americas, 2014)
Over the past forty years, recognition has become the dominant mode of negotiation and decolonization between the nation-state and Indigenous nations in North America. The term?recognition? shapes debates over Indigenous cultural distinctiveness, Indigenous rights to land and self-government, and Indigenous peoples' right to benefit from the development of their lands and resources. In a work of critically engaged political theory, Glen Sean Coulthard challenges recognition as a method of organizing difference and identity in liberal politics, questioning the assumption that contemporary difference and past histories of destructive colonialism between the state and Indigenous peoples can be reconciled through a process of acknowledgment. Beyond this, Coulthard examines an alternative politics--one that seeks to revalue, reconstruct, and redeploy Indigenous cultural practices based on self-recognition rather than on seeking appreciation from the very agents of colonialism. Coulthard demonstrates how a place-based modification of Karl Marx's theory of primitive accumulation throws light on Indigenous-state relations in settler-colonial contexts and how Frantz Fanon's critique of colonial recognition shows that this relationship reproduces itself over time. This framework strengthens his exploration of the ways that the politics of recognition has come to serve the interests of settler-colonial power. In addressing the core tenets of Indigenous resistance movements, like Red Power and Idle No More, Coulthard offers fresh insights into the politics of active decolonization. --Publisher's description.
Keywords: Canada; Canada. Ethnic relations; Canada. Indians, Treatment of; Canada. Native peoples; Government relations. Indians of North America; Government relations. Native peoples; Indians of North America; Legal status, laws, etc.; Legal status, laws, etc. Indians of North America; Political aspects. Indians of North America; Politics and government. Indians of North America; Politics and government. Indians, Treatment of. Indianerpolitik Rechtsstellung Indianer Selbstbestimmungsrecht Nordamerikas indianer; Politics and government. Native peoples; politiska aspekter

In Solidarity: Academic Librarian Labour Activism and Union Participation in Canada - Dekker, Jennifer; Kandiuk, Mary (Library Juice Press, 2014)
Provides a historical and current perspective regarding the unionization of academic librarians, an exploration of some of the major labour issues affecting academic librarians in a certified and non-certified union context,as well as case studies relating to the unionization of academic librarians at selected institutions in Canada. --Publisher's description
Keywords: Academic librarians; Canada; Collective bargaining; Faculty status; Labor Unions; Librarians' unions; Library employees

L'abbé Pierre Gravel, syndicaliste et ultranationaliste - Dumas, Alexandre (Septentrion, 2014)
Alors que le Québec est plongé dans la Grande Dépression, l'abbé Pierre Gravel promeut le syndicalisme dans l'industrie québécoise de l'amiante. Son discours radical et sévère à l'endroit des patrons tranche avec celui des autres prêtres qui oeuvrent dans le mouvement ouvrier. À l'aube de la Seconde Guerre mondiale, il encourage les Canadiens français à mener une révolution nationale en s'inspirant des dictateurs européens. Orateur aux idées sociales et nationales arrêtées et parfois dérangeantes, il fait face à l'opposition des gouvernements. Antisémite et ultranationaliste, ce réactionnaire prêche pourtant une doctrine sociale qui pouvait être considérée comme « communiste » à son époque et dont plusieurs éléments seront mis en place au cours de la Révolution tranquille, à commencer par la nationalisation de l'électricité. Comment peut-on concilier ces deux écoles de pensée à première vue contradictoires ? Peut-on être à la fois syndicaliste et fasciste ? Le parcours de l'abbé Pierre Gravel contribue à jeter un regard nouveau sur la droite nationaliste québécoise de cette époque tourmentée. --Publisher's description
Keywords: Biographies; Catholic Church; Catholic Church Clergy Biography; Clergy; Clergé Activité politique Canada 20e siècle; Gravel, Pierre; Gravel, Pierre, 1899-1977; Nationalisme et socialisme Canada Québec (Canada) (province) 20e siècle; Syndicalisme Canada Québec (Canada) (province) 20e siècle; Église catholique Clergé Biographies

Temporary Work, Agencies and Unfree Labour Insecurity in the New World of Work - Fudge, Judy; Strauss, Kendra (Routledge studies in employment and work relations in context, 2014)
Unfree labor has not disappeared from advanced capitalist economies. In this sense the debates among and between Marxist and orthodox economic historians about the incompatibility of capitalism and unfree labor are moot: the International Labour Organisation has identified forced, coerced, and unfree labor as a contemporary issue of global concern. Previously hidden forms of unfree labor have emerged in parallel with several other well-documented trends affecting labor conditions, rights, and modes of regulation. These evolving types of unfree labor include the increasing normalization of contingent work (and, by extension, the undermining of the standard contract of employment), and an increase in labor intermediation. The normative, political, and numerical rise of temporary employment agencies in many countries in the last three decades is indicative of these trends. It is in the context of this rapidly changing landscape that this book consolidates and expands on research designed to understand new institutions for work in the global era. This edited collection provides a theoretical and empirical exploration of the links between unfree labor, intermediation, and modes of regulation, with particular focus on the evolving institutional forms and political-economic contexts that have been implicated in, and shaped by, the ascendency of temp agencies. What is distinctive about this collection is this bi-focal lens: it makes a substantial theoretical contribution by linking disparate literatures on, and debates about, the co-evolution of contingent work and unfree labor, new forms of labor intermediation, and different regulatory approaches; but it further lays the foundation for this theory in a series of empirically rich and geographically diverse case studies. This integrative approach is grounded in a cross-national comparative framework, using this approach as the basis for assessing how, and to what extent, temporary agency work can be considered unfree wage labor. --Publisher's description
Keywords: Employment agencies; Job security; Labor market; Temporary employment

Trouble on Main Street: Mackenzie King, Reason, Race and the 1907 Vancouver Riots - Gilmour, Julie F. (Allen Lane, 2014)
The weather on Sept. 7, 1907 was hot and tempers were short. British Columbians had always been sensitive to Asian immigration and had become increasingly fearful over the summer. More Japanese immigrants were coming to B.C. and rumours smouldered of massive labour contracts for the projected Grand Trunk Pacific Railway.Like the citizens of Seattle and San Francisco, the residents of Vancouver had established a bipartisan Asiatic Exclusion League aimed at Japanese, Chinese, and South Asian immigrants in order to protect “White Canada.” The league had widespread support among trade union organizations and churches, and so a parade during the Labour Day weekend was scheduled. The result was a violent riot that drew the world’s attention to Vancouver, to Canadian immigration policy, and to Britain’s 1902 alliance with the Japanese. Historian Julie Gilmour traces the impact of these events on the life and work of future prime minister W.L. Mackenzie King, and on Canada’s relationships with Britain, the United States, China, Japan, and India. King’s involvement with the commissions set up to evaluate the damages incurred during the riots led to his interest in opium suppression and immigration control, and clarified his own sense of Canada’s role in the empire. Trouble on Main Street portrays a nation, and a time, at once relatively recent and shockingly unrecognizable. Over a century later, the links between local pressures, policy, and international events provide insight into current debates on terror, immigration, and Canadian security. -- Publisher's description

Gender History: Canadian Perspectives - Keough, Willeen G.; Campbell, Lara A. (Oxford University Press, 2014)
Seamlessly integrating primary and secondary sources with insightful original overviews, Gender History: Canadian Perspectives is a comprehensive resource for students of gender history in Canada. This reader-textbook takes and innovative historical and thematic approach - the first half is chronological in structure, tracing developments from the pre-contacts such as work, the law, sexuality, religion, and popular culture. The result is a solid introduction to the broad patterns and themes of gender history in Canada, with particular emphasis on the diversity of gender experiences and the intersections of gender with class and race. --Publisher's description
Keywords: Sex role -- Canada -- History

Resources, Empire and Labour: Crisis, Lessons and Alternatives - Leadbeater, David (Fernwood, 2014)
The interconnections of natural resources, empire and labour run through the most central and conflict-ridden crises of our times: war, environmental degradation, impoverishment and plutocracy. Crucial to understand and to change the conditions that give rise to these crises is the critical study of resource development and, more broadly, the resources question, which is the subject of this volume. --Publisher's description.

The Raids: Nickel Range Trilogy - Lowe, Mick (Baraka Books, 2014)
It’s spring, 1963 in the “Nickel Capital of the World.” Nineteen-year-old Jake McCool is about to undergo a rite of passage—his first shift underground in a hard rock mine. But the Cold War is at its height, and Jake is also about to become a reluctant participant in a bitter interunion battle fueled by the global struggle between two ideologies in the wake of the Second World War. So is his girlfriend, Jo Ann Winters. Together the couple are swept up in a web of intrigue; at its center is a terrible secret that will haunt their relationship for the rest of their lives, as their hometown becomes not only one of the world’s greatest hard rock mining centers, but also the epicenter of the Cold War in North America. In this fast-paced novel set against the little-known historical backdrop of a true-life battle that included vicious beatings, riots, and worse, author Mick Lowe posits a provocative premise: that the U.S. government sponsored a ruthless covert operation to destabilize a strategic community in the heartland of its closest ally, Canada. --Publisher's description
Keywords: Blue-collar work; Cold War; Miners; Nickel mines and mining; Ontario Sudbury; Strategy

Hobohemia and the Crucifixion Machine: Rival Images of a New World in 1930s Vancouver - McCallum, Todd (Fabriks: Studies in the working class, 2014)
In the early years of the Great Depression, thousands of unemployed homeless transients settled into Vancouver’s “hobo jungle.” The jungle operated as a distinct community, in which goods were exchanged and shared directly, without benefit of currency. The organization of life was immediate and consensual, conducted in the absence of capital accumulation. But as the transients moved from the jungles to the city, they made innumerable demands on Vancouver’s Relief Department, consuming financial resources at a rate that threatened the city with bankruptcy. In response, the municipality instituted a card-control system—no longer offering relief recipients currency to do with as they chose. It also implemented new investigative and assessment procedures, including office spies, to weed out organizational inefficiencies. McCallum argues that, threatened by this “ungovernable society,” Vancouver’s Relief Department employed Fordist management methods that ultimately stripped the transients of their individuality. Vancouver’s municipal government entered into contractual relationships with dozens of private businesses, tendering bids for meals in much the same fashion as for printing jobs and construction projects. As a result, entrepreneurs clamoured to get their share of the state spending. With the emergence of work relief camps, the provincial government harnessed the only currency that homeless men possessed: their muscle. This new form of unfree labour aided the province in developing its tourist driven “image” economy, as well as facilitating the transportation of natural resources and manufactured goods. It also led eventually to the most significant protest movement of 1930s’ Canada, the On-to-Ottawa Trek. Hobohemia and the Crucifixion Machine explores the connections between the history of transiency and that of Fordism, offering a new interpretation of the economic and political crises that wracked Canada in the early years of the Great Depression. --Publisher's description
Keywords: 1929; 20th century; British Columbia; Depressions; History; Public welfare; Services for; Services for. Unemployed; Social conditions; Transients, Relief of; Unemployed; Vancouver

Rebel Youth: 1960s Labour Unrest, Young Workers, and New Leftists in English Canada - Milligan, Ian (UBC Press, 2014)
During the "long sixties" - between 1964 and 1973 - baby boomers raised on democratic postwar ideals demanded a more egalitarian society for all. While a few became vocal leaders at universities across Canada, nearly 90% of Canada's young people went straight to work after high school. There, they brought the anti-authoritarian spirit of the youth revolt to the labour movement. While university-based activists combined youth culture with a new brand of radicalism to form the New Left, young workers were pressing for wildcat strikes and defying their aging union leaders in a wave of renewed militancy that swept the country. In Rebel Youth, Ian Milligan looks at these converging currents, demonstrating convincingly how they were part of a single youth phenomenon. With just short of seventy interviews complementing the extensive use of archival records, this book reveals a youth current that, despite regional differences, spanned an intellectual network from Halifax to Victoria that read the same publications, consulted the same thinkers, and found inspiration in the same shared ideas. Rebel Youth draws important connections between the stories of young workers and the youth movement in Canada, claiming a central place for labour and class in the legacy of this formative decade. --Publisher's description

Transformations des marchés du travail et innovations syndicales au Québec - Noiseux, Yanick (Collection Innovation sociale, 2014)
Pour qui s’intéresse à l’évolution du travail au Québec, le passage à un régime néolibéral au tournant des années 1980 renvoie à un concept : la flexibilisation. Trente ans plus tard, avec la montée en flèche du nombre d’emplois atypiques, force est de constater que flexibilité rime aussi avec précarité, l’emploi atypique se distinguant trop souvent par une moindre rémunération et un accès restreint aux multiples formes de protection sociale. Comment le syndicalisme peut-il s’ajuster aux besoins différenciés d’une main-d’œuvre de plus en plus diversifiée et employée sur des marchés du travail toujours plus segmentés ? L’auteur nous invite à penser le marché du travail à partir de sa périphérie, et à réfléchir à l’innovation syndicale à partir des pratiques, des stratégies et des revendications d’organisations de travailleurs se situant sur les marges de la société salariale. Dans une démarche qui vise le rajeunissement, voire la métamorphose du syndicalisme, il porte attention aux possibilités d’innovation sous-tendue par la nouvelle configuration du travail dans le capitalisme d’aujourd’hui. Pour ce faire, il présente un état des lieux du travail sur les marchés périphériques au Québec, en accordant une place prépondérante aux expériences des travailleurs, puis expose des pistes de réflexion sur le renouvellement de la théorie syndicale et sur le redéploiement de l’action syndicale au Québec. Enfin, il propose cinq études d’expériences portées, ici et maintenant, par des travailleurs atypiques et des organisations syndicales soucieuses de répondre à leurs besoins différenciés en matière d’organisation collective. L’ouvrage nous montre que les organisations de travailleurs demeurent déterminantes et constituent l’une des pistes majeures à explorer afin de repenser l’articulation des mobilisations et l’émancipation sociale à l’ère de la mondialisation néolibérale. --Publisher's description
Keywords: Labor market; Labor market Québec (Province); Marché du travail Québec (Province); Precarious employment; Precarious employment Québec (Province); Québec; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province); Travail précaire Québec (Province)

Seconds: A Graphic Novel - O'Malley, Bryan Lee (Ballantine, 2014)
The highly anticipated new standalone full-color graphic novel from Bryan Lee O’Malley, author and artist of the hugely bestselling Scott Pilgrim graphic novel series Katie’s got it pretty good. She’s a talented young chef, she runs a successful restaurant, and she has big plans to open an even better one. Then, all at once, progress on the new location bogs down, her charming ex-boyfriend pops up, her fling with another chef goes sour, and her best waitress gets badly hurt. And just like that, Katie’s life goes from pretty good to not so much. What she needs is a second chance. Everybody deserves one, after all—but they don’t come easy. Luckily for Katie, a mysterious girl appears in the middle of the night with simple instructions for a do-it-yourself do-over: 1. Write your mistake 2. Ingest one mushroom 3. Go to sleep 4. Wake anew And just like that, all the bad stuff never happened, and Katie is given another chance to get things right. She’s also got a dresser drawer full of magical mushrooms—and an irresistible urge to make her life not just good, but perfect. Too bad it’s against the rules. But Katie doesn’t care about the rules—and she’s about to discover the unintended consequences of the best intentions. From the mind and pen behind the acclaimed Scott Pilgrim series comes a madcap new tale of existential angst, everyday obstacles, young love, and ancient spirits that’s sharp-witted and tenderhearted, whimsical and wise. --Publisher's description
Keywords: Blue-collar work; Comic books, strips, etc; Gender; Graphic novels; Love stories; Man-woman relationships; Pink-collar work; Restaurants; Restaurateurs; Social Class and Equality; United States; Women cooks; Young adult fiction

Bad Time Stories: Government-Union Conflicts and the Rhetoric of Legitimation Strategies - Reshef, Yonatan; Keim, Charles (University of Toronto Press, Scholarly Publishing Division, 2014)
The 1990s and 2000s were especially difficult decades for government–public sector union relations in Canada. Rising costs and growing debts meant that governments were on the lookout for savings, and public sector unions and employees were easy targets for government actions. Bitter conflicts between unions and governments erupted and each labour dispute involved numerous rounds of public rhetoric in which both sides attempted to justify their actions and stigmatize their opponents.In Bad Time Stories, Yonatan Reshef and Charles Keim analyse the language of both parties in order to identify the legitimation strategies at work during government-union conflict. The authors use evidence drawn from newspapers, speeches, parliamentary transcripts, and legal statements in presenting a new framework for understanding the discursive strategies employed by governments and unions in labour disputes.Using a case study and linguistic approach, Bad Time Stories offers a unique perspective on industrial relations and will be of interest to scholars in the areas of business, public policy, and communications, as well to those directly involved in union-management negotiations. -- Publisher's description

Autonomie collective et droit du travail. Mélanges en l’honneur du professeur Pierre Verge - Roux, Dominic (Collection Travail et emploi à l'ère de la mondialisation, 2014)
L’apport du professeur Pierre Verge au droit du travail est remarquable! Ses travaux ont profondément marqué cette discipline et en ont accompagné le développement pendant plus de cinquante ans. Engagé, il occupa dès le début de sa carrière diverses fonctions administratives, dont celle de doyen (Normand). Visionnaire, il se tourna rapidement vers la recherche subventionnée et vers l’interdisciplinarité. Pluraliste, son approche se focalisa sur la multiplicité des sources – juridiques ou non - qui jalonnent sa discipline, élargissant ses horizons de recherche, vers la sociologie, notamment. Joueur d’équipe, il sut transmettre à d’autres, ici même et ailleurs dans le monde, son savoir et son expérience, ce qui se traduit par d’innombrables copublications et collaborations, et autant d’amitiés nouées. Rigueur intellectuelle, érudition et ardeur au travail sont des traits de personnalité connus du professeur Verge. Mais à cela s’ajoutent de belles qualités humaines : générosité, affabilité et modestie caractérisent en effet cet homme, authentique, qui, durant son illustre carrière, influença tant de collègues et d’étudiants. Plusieurs d’entre eux ont donc voulu lui rendre un vibrant hommage et exprimer leur attachement et leur reconnaissance sous la forme de Mélanges. --Publisher's description. Contents: 1 La contribution scientifique de Pierre Verge à l'affirmation et à la recomposition du droit du travail / Guylaine Vallée -- 2 Un décanat de développement et de consolidation / Sylvio Normand -- Autonomie collective et pluralisme juridique : Georges Gurvitch, Hugo Sinzheimer et le droit du travail / Michel Coutu -- 4 Corporatism, Neo-Corporatism, and Freedom of Association / Adrian Goldin -- 5 Le syndicat obligatoire au Québec : une contrainte individuelle à la faveur de l'autonomie collective / Pierre Verge, Christain Brunelle, Anne-Marie Laflamme et Doninic Roux -- 6 "La convention collective lie tous les salariés ..." mais, sans les ligoter! (art. 67 C.t.) / Me Fernand Morin -- 7 La solubilité de la convention collective dans son environnement normatif : quelques réflexions sur une mutation institutionnelle / Louis LeBel -- 8 Regulating strikes in essential (and other) services after the “New Trilogy” / Bernard Adell -- 9 L'arbitrage de grief et le développement de la spécificité du droit du travail : une contribution reconnue / Denis Nadeau -- 10 Embracing collective rights: Unions and the new struggle for relevance and autonomy : A view from the Commonwealth Caribbean / Rose-Marie Belle Antoine --11 Collective autonomy in New Zealand / Paul Roth -- 12 Social partners : Autonomy and its limits : A Polish perspective / Michal Sewerynski -- 13 Le droit français du travail est-il toujours un droit de protection des salariés? / Jean Pélissier -- 14 Les tribunaux judiciaires et les conflits collectifs de travail en Amérique latine / Héctor-Hugo Barbagelata -- 15 La détermination des conditions collectives de travail dans l'entreprise au Japon : le règlement intérieur et la modification des conditions de travail / Yasuo Ishil -- 16 The Wagner model and international freedom of association standards / Lance Compa -- 17 Strike ban for public servants in Germany -- an international anachronism / Udo R. Mayer-- 18 2019 : autonomie collective, élément clé du travail décent des travailleuses et travailleurs domestiques / Adelle Blackett --19 The new public and private international labour regulations and their implementation experiences / Pablo Lazo Grandi -- 20 Organisations nouvelles du travail et représentation collective des travailleurs / Jean-Michel Servais -- 21 Repenser les politiques des rapports collectifs de travail à l'ère des entreprises transnationales / Gregor Murray.
Keywords: Associations; Associations. Syndicats; Droit; Droit international. Travailleurs; Droit. Mlanges (Recueils) Labor laws and legislation. Labor laws and legislation, International. Labor unions; Droit. Travail; Labor laws and legislation. Labor laws and legislation, International. Working class; Law and legislation. Travail; Law and legislation. Working class; Mlanges et hommages; Mlanges et hommages. Droit du travail (droit international); Mlanges et hommages. Syndicats; Mlanges et hommages. Travailleurs; Societies, etc. Droit du travail; Societies, etc. Labor unions

Travail et syndicalisme : origines, évolution et défis d'une action sociale - Thwaites, James D. (James Douglas) (Presses de l'Université Laval, 2014)
D’où vient le syndicalisme ? À quoi répond-il ? Quelles sont ses formes ? De quelle façon agit-il ? Quels sont ses effets ? Quels sont ses défis ? Comment évolue-t-il ? Les 42 textes qui composent cette anthologie proposent diverses réponses à ces interrogations. Les auteurs sélectionnés traitent des aspects les plus significatifs du syndicalisme d’hier, d’aujourd’hui et de demain. Ils représentent neuf disciplines et des positions variées. Le résultat est un foisonnement remarquable d’idées qui pousse à la réflexion, au questionnement et aux remises en cause relativement à ce phénomène qui a des effets multiples sur l’économie, la politique et la société et qui fêtera bientôt ses 200 ans en territoire canadien et québécois. --Résumé de l'éditeur
Keywords: Histoire; Mouvement ouvrier; Relations industrielles; Syndicalisme; Syndicats; Travailleurs

Liberating Temporariness? Migration, Work, and Citizenship in an Age of Insecurity - Vosko, Leah F.; Preston, Valerie; Latham, Robert (McGill-Queen's University Press, 2014)
[E]xplores the complex ways in which temporariness is being institutionalized as a condition of life for a growing number of people worldwide. The collection emphasizes contemporary developments, but also provides historical context on nation-state membership as the fundamental means for accessing rights in an era of expanding temporariness - in recognition of why pathways to permanence remain so compelling. Through empirical and theoretical analysis, contributors explore various dimensions of temporariness, especially as it relates to the legal status of migrants and refugees, to the spread of precarious employment, and to limitations on social rights. While the focus is on Canada, a number of chapters investigate and contrast developments in Canada with those in Europe as well as Australia and the United States. Together, these essays reveal changing and enduring temporariness at local, regional, national, transnational, and global levels, and in different domains, such as health care, language programs, and security. The question at the heart of this collection is whether temporariness can be liberated from current constraints. While not denying the desirability of permanence for migrants and labourers, "Liberating Temporariness?" presents alternative possibilities of security and liberation. --Publisher's description, Contents: Introduction: Liberating Temporariness? Imagining Alternatives to Permanence as a Pathway for Social Inclusion  / Robert Latham, Leah F. Vosko, Valerie Preston, and Melisa Bretón. Part 1: Security, Temporary Status, and Rights. Rethinking Canadian Citizenship: The Politics of Social Exclusion in the Age of Security and Suppression / Yasmeen Abu-Laban -- Permanent Patriots and Temporary Predators? Post-9/11 Institutionalization of the Arab/Orientalized “Other” in the United States and the Contributions of Arendt and Said / Abigail B. Bakan -- Indefinitely Pending: Security Certificates and Permanent Temporariness / Mike Larsen. Part 2: International Organizations and Transnational Dynamics of Temporary Work. Managed Migration and the Temporary Labour Fix / Christina Gabriel -- Institutionalizing Temporary Labour Migration in Europe: Creating an “In-between”’ Migration Status / Tesseltje de Lange and Sarah van Walsu -- The Permanence of Temporary Labour Mobility: Migrant Worker Programs across Australia, Canada, and New Zealand / Emily Gilbert. Part 3: Temporary Status, Social Welfare, and Marginalization. Brain Circulation or Precarious Labour? Conceptualizing Temporariness in the United Kingdom’s National Health Service / Parvati Raghuram -- Language Training and Labour Market Integration for Newcomers to Canada / Eve Haque -- Resituating Temporariness as the Precarity and Conditionality of Non-citizenship / Luin Goldring -- Constructing and “Liberating” Temporariness in the Canadian Non-profit Sector: Neoliberalism and Non-profit Service Providers / John Shields. Part 4: (Re)Framing Temporariness. Mexican Migrant Transnationalism and Imaginaries of Temporary/Permanent Belonging / Marianne H. Marchand -- Temporariness: Other than Permanence, and in the Lives of People - Always… / Deepa Rajkumar -- Temporal Orders, Re-collective Justice, and the Making of Untimely States / Robert Latham.
Keywords: Canada; Foreign workers; Social conditions

La surqualification au Québec et au Canada - Vultur, Mircea (Collection Sociologie contemporaine, 2014)
La surqualification, définie comme la situation qui caractérise un individu dont le niveau de formation dépasse celui qui est normalement requis pour l’emploi occupé, a subi une forte tendance à la hausse au cours des vingt dernières années. Au Québec et au Canada, elle touche un tiers des travailleurs, surtout les plus jeunes. Ce phénomène, qui témoigne de l’incapacité du marché du travail à offrir à un grand nombre de personnes des emplois qui correspondent à leurs qualifications, est devenu pour tous les acteurs de la vie économique et sociale un enjeu de premier ordre. Ce livre présente un ensemble d’études récentes sur la surqualification. Son objectif est de mesurer l’étendue du phénomène du point de vue statistique et de mettre en relief les facteurs qui interviennent dans sa genèse et son développement. L’ouvrage évalue plusieurs approches et modèles analytiques et présente des résultats de recherches qui utilisent diverses bases de données. Il offre un portrait détaillé de la surqualification au Québec et au Canada. De manière plus fondamentale, il soulève la question de la valeur des diplômes sur le marché du travail et suggère des pistes de réflexion pour atteindre l’adéquation entre la formation de la main-d’œuvre et le profil des emplois. --Publisher's description
Keywords: Canada; Canada Conditions économiques 1991-; Canada Economic conditions 1991-; Diplômés de l'enseignement supérieur Travail Canada; Economic history; Livres numériques; Québec; Québec (Province); Québec (Province) Economic conditions 1991-; Recueil de contributions (Descripteur de forme); Since 1991; Sous-emploi; Sous-emploi Canada; Sous-emploi Canada Québec (Canada; province) Statistiques; Sous-emploi Canada Statistiques; Sous-emploi Québec (Province); Sous-emploi Québec (Province) Statistiques; Statistics; Statistiques (Descripteur de forme); Underemployment; Underemployment Canada; Underemployment Canada Statistics; Underemployment Québec (Province); Underemployment Québec (Province) Statistics; e-books

Quand travailler enferme dans la pauvreté et la précarité: travailleuses et travailleurs pauvres au Québec et dans le monde - Yerochewski, Carole (Collection Problèmes sociaux & interventions sociales, 2014)
Travailler ne met plus à l’abri de la pauvreté et peut enfermer dans la précarité. Car la société salariale est affaiblie par les transformations des interventions entrepreneuriales et étatiques. De plus en plus de travailleurs et, surtout, de travailleuses n’ont plus accès aux protections collectives et sociales qui leur donnaient un appui pour mener des projets professionnels et de vie. L’heure est à la remarchandisation du travail. Pour étayer le phénomène de la pauvreté en emploi et en mesurer l’ampleur au Québec, l’ouvrage propose de nouvelles constructions statistiques qui reposent sur une définition extensive de la notion de travailleur. Le choix de cette définition – définition qui s’accorde avec le caractère multidimensionnel de la pauvreté en emploi – se trouve justifié par les travaux de recherche menés par les membres du Groupe interuniversitaire et interdisciplinaire de recherche sur l’emploi, la pauvreté et la protection sociale (GIREPS). L’ouvrage met en lumière les différents facteurs de développement des formes d’emploi qui enferment dans la pauvreté et la précarité des travailleuses et travailleurs canadiens, résidents ou immigrants temporaires rendus vulnérables par leur position sociale. Il porte un regard à la fois sur les mutations du travail et de l’emploi, sur les transformations des États-providence et sur leur rôle dans l’informalisation du travail et de l’économie, sur les modalités de gestion de la main-d’œuvre par les entreprises ainsi que sur la réactualisation des rapports sociaux de classe, de genre et de race. Il montre que la forte remontée des inégalités socioéconomiques ne résulte d’aucun déterminisme, mais de l’absence ou de la remise en cause des protections légales ou collectives. Il expose comment le retour de la pauvreté en emploi s’inscrit dans la mise en concurrence des travailleurs à l’échelle planétaire. Il se conclut, enfin, sur les formes d’action collective qui interpellent les formes institutionnalisées et nourrissent de nouvelles aspirations et revendications possiblement communes. --Résumé de l'éditeur
Keywords: Precarious employment; Precarious employment Québec (Province); Québec; Québec (Province); Travail précaire; Travail précaire Québec (Canada; province); Travail précaire Québec (Province); Travailleur pauvre; Travailleurs pauvres; Travailleurs pauvres Québec (Canada; province); Travailleurs pauvres Québec (Province); Working poor; Working poor Québec (Province)

According to Baba: A Collaborative Oral History of Sudbury's Ukrainian Community - Zembrzycki, Stacey (UBC Press, 2014)
Dreams of steady employment in the mining sector led thousands of Ukrainian immigrants to northern Ontario in the early 1900s. As a child, historian Stacey Zembrzycki listened to her baba’s stories about Sudbury’s small but polarized community and what it was like growing up ethnic during the Depression. According to Baba grew out of those stories, out of a granddaughter’s desire to capture the experiences of her grandparents’ generation on paper. Eighty-two interviews conducted by Stacey and her grandmother, Olga, laid the groundwork for this insightful and deeply personal social history of one of Canada’s most colourful ethnic communities. The interview process also brought to light the challenges of doing collaborative oral history with community members, particularly as Stacey lost authority to her baba, wrestled it back, and eventually came to share it, and as interviewees met questions with nostalgic reminiscences, subversive humour, or impenetrable silence. By providing a realistic glimpse into the hard work that goes into making communities partners in oral history research, this book provides a new paradigm for studying the politics of memory, one that recognizes that people are not passive recipients of their histories but rather counter and create narratives about the past by invoking alternative ways of remembering. --Publisher's description
Keywords: Biographies; Canadiens d'origine ukrainienne Ontario Sudbury Biographies; Canadiens d'origine ukrainienne Ontario Sudbury Conditions sociales; Canadiens d'origine ukrainienne Ontario Sudbury Entretiens; Canadiens d'origine ukrainienne Ontario Sudbury Histoire; Histoire orale Ontario Sudbury; Interviews; Kanada Ontario Sudbury; Ontario Sudbury (Greater Sudbury); Ukrainare sociala förhållanden; Ukrainian Canadians Ontario Sudbury Biography; Ukrainian Canadians Ontario Sudbury History; Ukrainian Canadians Ontario Sudbury Interviews; Ukrainian Canadians Ontario Sudbury Social conditions; Ukrainians; Ukrainians Ontario Sudbury Biography; Ukrainians Ontario Sudbury Interviews; Ukrainians Ontario Sudbury Social conditions; Ukrainians Social conditions; Zembrzycki, Olga Entretiens; Zembrzycki, Olga Interviews; interviews

Tomorrow We're All Going to the Harvest: Temporary Foreign Worker Programs and Neoliberal Political Economy - Binford, Leigh (University of Texas Press, 2013)
From its inception in 1966, the Canadian Seasonal Agricultural Worker Program (SAWP) has grown to employ approximately 20,000 workers annually, the majority from Mexico. The program has been hailed as a model that alleviates human rights concerns because, under contract, SAWP workers travel legally, receive health benefits, contribute to pensions, are represented by Canadian consular officials, and rate the program favorably. Tomorrow We?re All Going to the Harvest takes us behind the ideology and examines the daily lives of SAWP workers from Tlaxcala, Mexico (one of the leading sending states), observing the great personal and family price paid in order to experience a temporary rise in a standard of living. The book also observes the disparities of a gutted Mexican countryside versus the flourishing agriculture in Canada, where farm labor demand remains high. Drawn from extensive surveys and nearly two hundred interviews, ethnographic work in Ontario (destination of over 77 percent of migrants in the author?s sample), and quantitative data, this is much more than a case study; it situates the Tlaxcala-Canada exchange within the broader issues of migration, economics, and cultural currents. Bringing to light the historical genesis of ?complementary? labor markets and the contradictory positioning of Mexican government representatives, Leigh Binford also explores the language barriers and nonexistent worker networks in Canada, as well as the physical realities of the work itself, making this book a complete portrait of a provocative segment of migrant labor. --Publisher's description

Building More Effective Labour-Management Relationships - Chaykowski, Richard P.; Hickey, Robert Sean (Queen's policy studies series, 2013)
Building More Effective Labour-Management Relationships combines valuable insights into new approaches to relationship-building and collective bargaining with unique knowledge and concrete lessons garnered from some of the foremost industrial relations practitioners in Canada. Contributors include Warren "Smokey" Thomas (president, OPSEU), Buzz Hargrove (former president, CAW), Warren Edmondson (former ADM Labour, Government of Canada, and chair of the CLRB), George Smith (former VP at CP Rail and CBC/Radio Canada), David Logan, (ADM, Government of Ontario) Glenda Fisk (Queen's University), Richard Chaykowski (Queen's University), Robert Hickey (Queen's University). -- Publisher's description. Contents: Fostering Innovation and Cooperation in Employee Relations in the Ontario Public Service  / Warren "Smokey" Thomas -- An Introduction and Context Advancing Labour-Management Relationships and Cooperation / David Logan -- Systemic Pressures on Ontario Public Sector Industrial Relations / Richard P. Chaykowski, Robert S. Hickey --  Experiences in Collective Bargaining and the Labour-Management Relationship Remaking the Union-Management Relationship between the CBC and Canadian Media Guild: "We used to walk ... Now we talk" / Richard P. Chaykowski --  Reflections on Creating More Effective Labour Relations / George C.B. Smith Dan Oldfield -- Interest-Based, Cooperative Approaches to Negotiations and Labour Relations: What Works and What Does Not / Buzz Hargrove.
Keywords: Collective bargaining; Industrial relations

Clearing the Plains: Disease, Politics of Starvation, and the Loss of Aboriginal Life - Daschuk, James W. (James William) (University of Regina Press, 2013)
Revealing how Canada's first Prime Minister used a policy of starvation against Indigenous people to clear the way for settlement, the multiple award-winning Clearing the Plains sparked widespread debate about genocide in Canada. In arresting, but harrowing, prose, James Daschuk examines the roles that Old World diseases, climate, and, most disturbingly, Canadian politics-the politics of ethnocide-played in the deaths and subjugation of thousands of Indigenous people in the realization of Sir John A. Macdonald's "National Dream." It was a dream that came at great expense: the present disparity in health and economic well-being between Indigenous and non-Indigenous populations, and the lingering racism and misunderstanding that permeates the national consciousness to this day. --Publisher's description
Keywords: Indians of North America -- Canada, Western -- History

From Crisis to Austerity: Neoliberalism, Organized Labour and the Canadian State - Fowler, Tim (Red Quill Books, 2013)
The Great Recession was the largest crisis of capitalism since the Great Depression and the largest crisis in neoliberalism to date, sending shockwaves throughout the global economy. States scrambled to right the sinking capitalist ship in order to maintain high levels of accumulation. In Canada, as in so many other countries, the state introduced austerity measures aimed at organized labour and the broader working class. This volume explores the political economy of The Great Recession in Canada, and focuses on how labour has responded to the crisis, neoliberalism, and austerity measures. --Publisher's description. Contents: 1. From Crisis To Austerity: An Introduction / Tim Fowler -- 2. The Canadian State and the Crisis: Theoretical and Historical Context / Stephen McBride & Heather Whiteside -- 3. From the Great Recession of 2008-2009 to Fiscal Austerity: The Role of Inequality / Akhter Faroque and Brian K. MacLean  -- 4. Neoliberalism, Capitalist Crisis, and Continuing Austerity in the Ontario State / Tim Fowler  -- 5. Collective Bargaining in a Time of Austerity: Public-Sector Unions and the University Sector in Ontario / Mathew Nelson & James Meades --  6. "We Will Fight This Crisis": Auto Workers Resist an Industrial Meltdown/ Bill Murnighan & Jim Stanford -- 7. The Decline of the Labour Movement: A Socialist Perspective / Murray E.G. Smith & Jonah Butovsky -- 8. Labour’s Response to the Crisis and the Future of Working-Class Politics / David Camfield.

Provincial Solidarities: A History of the New Brunswick Federation of Labour - Frank, David (Working Canadians: Books from the CCLH, 2013)
Established in 1913, the New Brunswick Federation of Labour is the second oldest provincial federation of labour in Canada. Its history began in early campaigns for workers’ compensation and union recognition and continues today in the latest battles to defend social standards, secure employment, and union rights. Active initially in the port city of Saint John and the railway centre of Moncton, the federation soon expanded to include workers in the mines and mills of the north, taking up the causes of public employees and women workers and confronting the realities of life and work in a bilingual society. A pioneering study, written in clear and forceful prose, this is the untold story of provincial labour solidarities that succeeded in overcoming divisions and defeats to raise the status of working men and women within New Brunswick society. Drawing on archives, newspapers, and workers’ own descriptions of their experiences, Frank makes an original contribution to our understanding of the political, economic, and social development of the province. In so doing, he helps meet the need for an informed public awareness of the history of workers and unions in all parts of Canada.
Keywords: History; Labor Unions; Labor movement; New Brunswick Federation of Labour

Solidarités provinciales: Histoire de la Fédération des travailleurs et travailleuses du Nouveau-Brunswick - Frank, David; Comite canadien sur l'histoire du travail (Working Canadians: Books from the CCLH, 2013)
La Fédération des travailleurs et travailleuses du Nouveau-Brunswick, fondée en 1913, est la deuxième plus ancienne fédération provinciale du travail au Canada. Son histoire remonte aux premières campagnes en faveur de l’indemnisation des accidents du travail et de la reconnaissance syndicale, et elle se poursuit dans les plus récentes luttes visant à défendre les normes sociales et à protéger les emplois et les droits syndicaux. La Fédération a vu le jour dans la ville portuaire de Saint John et le centre ferroviaire de Moncton, puis elle s’est étendue aux travailleurs des mines et des usines du nord de la province, soutenant la cause des employés du secteur public et des travailleuses, reflétant les réalités de la vie et du travail dans une société bilingue. Puisant dans les archives, les journaux et les expériences des travailleurs et des travailleuses, voici l’histoire inédite de solidarités syndicales provinciales qui ont surmonté les divisions et les revers afin de rehausser le statut des travailleurs et des travailleuses dans la société néo-brunswickoise. Par cette étude pionnière rédigée dans un style clair et puissant, Frank apporte une contribution originale à la compréhension de l’évolution politique, économique et sociale de la province, et il aide à combler le besoin d’éclairer la connaissance que le public a de l’histoire des travailleurs et des syndicats de toutes les régions du Canada. --Publisher's description
Keywords: Histoire; Work

Producing and Negotiating Non-Citizenship: Precarious Legal Status in Canada - Goldring, Luin; Landolt, Patricia (University of Toronto Press, 2013)
This timely volume contributes to conceptualizing multiple forms of precarious status non-citizenship as connected through policy and the practices of migrants and the institutional actors they encounter. Most examinations of non-citizens in Canada focus on immigrants, people who are citizens-in-waiting, or specific categories of temporary, vulnerable workers. In contrast, Producing and Negotiating Non-Citizenship considers a range of people whose pathway to citizenship is uncertain or non-existent. This includes migrant workers, students, refugee claimants, and people with expired permits, all of whom have limited formal rights to employment, housing, education, and health services. The contributors to this volume present theoretically informed empirical studies of the regulatory, institutional, discursive, and practical terms under which precarious-status non-citizens – those without permanent residence – enter and remain in Canada. They consider the historical and contemporary production of non-citizen precarious status and migrant illegality in Canada, as well as everyday experiences of precarious status among various social groups including youth, denied refugee claimants, and agricultural workers. -- Publisher's description.
Keywords: Aliens; Canada; Congresses. Aliens; Congresses. Emigration and immigration law; Droit; Government policy. Emigration and immigration law. Rechtspositie. Allochtonen. Auslnderpolitik Auslnderrecht Illegaler Einwanderer Genre/Form: Conference papers and proceedings; Social conditions; Social conditions. Emigration and immigration

Now You're Logging - Griffiths, Bus; Hodgins, Jack (Harbour Publishing, 2013)
This comic was originally produced for B.C. Lumbermen. It first appeared in a war-time comic strip. Whether readers are interested in logging history, a good yarn or folk art, they will be enthralled by Now You're Logging, British Columbia's first graphic novel and a enduring West Coast classic, published in celebration of what would have been Bus Griffiths' 100th birthday. Now You're Logging is the story of Al and Red, who go to work in a small West Coast logging show during the dirty thirties. As they learn their trades, the reader is treated to an amazingly detailed view of the camp's varied operations—falling and bucking timber by hand, topping and rigging of spar trees, moving steam donkeys and making up log booms, plus all the colourful characters, camaraderie, romance and life-threatening exploits of a BC adventure story. --Publisher's description
Keywords: Adventure; Agriculture, Forestry, Fishing and Hunting; Logging; Working class

The Left in British Columbia: A History of Struggle - Hak, Gordon H. (Gordon Hugh) (Ronsdale Press, 2013)
This comprehensive history of the left in British Columbia from the late nineteenth century to the present explores the successes and failures of individuals and organizations striving to make a better world. Nineteenth-century coal miners and carpenters; Wobblies, Single Taxers, and communists; worker militancy in two world wars; the New Democratic Party; the Squamish Five; the Solidarity movement of 1983; and the Occupy movement of 2011 are all part of an historical provincial left that is notable for its breadth and dynamism. Moreover, the political and union initiatives of the traditional left are seen in conjunction with broader movements, including the struggles for women's suffrage and equality, human rights, Canadian nationalist visions, racial equality, and environmental health. Ginger Goodwin and Dave Barrett (as well as WAC Bennett and Gordon Campbell) are present, as are reformist liberals and green activists. Drawing on extensive published scholarship and primary newspaper sources, Dr. Hak's thorough examination of the British Columbia experience offers an historical context for understanding the contemporary left and a framework for considering future alternatives.

Hazard or Hardship: Crafting Global Norms on the Right to Refuse Unsafe Work - Hilgert, Jeffrey (Cornell University Press, 2013)
Today, hazardous work kills 2.3 million people each year and injures millions more. Among the most compelling yet controversial forms of legal protection for workers is the right to refuse unsafe work. The rise of globalization, precarious work, neoliberal politics, attacks on unions, and the idea of individual employment rights have challenged the protection of occupational health and safety for workers worldwide. This book presents the protection of refusal rights as a moral and a human rights question. The book finds that the protection of the right to refuse unsafe work, as constituted under international labor standards, is a failure and calls for a reexamination of worker health and safety policy from the ground up. The current model of protection follows an individual employment rights framework, which fails to protect workers against the inherent social inequalities within the employment relationship. To adequately protect the right to refuse as a human right, both in North America and around the world, the book argues that a broader protection must be granted under a freedom of association framework.

Feminist History in Canada: New Essays on Women, Gender, Work, and Nation - Janoviček, Nancy; Carstairs, Catherine (UBC Press, 2013)
In the late 1970s, feminist historians urged us to “rethink” Canada by placing women’s perspectives and experiences at the centre of historical analysis. Forty years later, feminism continues to inform history writing in Canada and has inspired historians to look beyond the nation and adopt a more global perspective. This exciting new volume of original essays opens with a discussion of the debates, themes, and methodological approaches that have preoccupied women’s and gender historians across Canada over the past twenty years. The chapters that follow showcase the work of new and established scholars who draw on the insights of critical race theory, postcolonial theory, and transnational history to re-examine familiar topics such as biography and oral history, paid and unpaid work, marriage and family, and women’s political action. Whether they focus on the marriage of Governor James Douglas and his Metis wife, Amelia; representations of saleswomen in department store catalogues; or the careers of professional women such as international child activist Charlotte Whitton and Quebec social work professors at Laval University, the contributors demonstrate the continued relevance – and growth – of history informed by feminist perspectives, and they open a much-needed dialogue between francophone and anglophone historians in Canada.-- Publisher's description
Keywords: Aufsatzsammlung; Biographies; Canada; Feminism; Feminism Canada History; Feminismus; Femmes Canada Biographies; Femmes Canada Conditions sociales; Femmes Canada Histoire; Frau; Frauenbewegung; Féminisme Canada Histoire; Geschlechterrolle; History; Kanada; Women; Women Canada Biography; Women Canada History; Women Canada Social conditions; Women Social conditions

Fernand Daoust - Leclerc, André (Collection Militantismes, 2013)
Fernand Daoust est surtout connu pour avoir été un dirigeant central de la Fédération des travailleurs et travailleuses du Québec (FTQ) pendant vingt-quatre ans. Or, cela est le fruit d'un véritable parcours du combattant dans le mouvement ouvrier. Le syndicaliste est né en 1926 dans des conditions très modestes et élevé dans une famille monoparentale. Sa curiosité, sa soif de connaissance et sa détermination l'ont entraîné bien au-delà des activités auxquelles ses origines le destinaient. Dans cette première partie de sa biographie, qui couvre les années 1926-1964, nous l'accompagnons dans le Montréal de la grande dépression, nous assistons à ses premiers engagements nationalistes pendant la crise de la conscription, à sa découverte des idéologies progressistes et à son entrée dans le mouvement syndical, malgré les dures conditions imposées aux syndicalistes par le régime Duplessis. Nous le voyons découvrir la nécessité de l'action politique et pressentons le futur dirigeant syndical. Accédant aux études universitaires à force de courage et de persévérance, son horizon intellectuel s'élargit. C'est tout naturellement qu'il choisit le syndicalisme pour y développer et approfondir son engagement social et politique. En faisant sienne l'idéologie socialiste, qui inspire les courants les plus dynamiques du syndicalisme québécois, le jeune syndicaliste ne renie cependant pas ses racines. Son socialisme s'incarne dans une nation spécifique, celle du Québec. Il n'était pas d'accord avec une majorité de syndicalistes de gauche de l'époque, qui qualifiaient de rétrogrades les aspirations nationales québécoises. Au contact des idées de gauche, le nationalisme de droite, dans lequel il avait baigné à l'adolescence et auquel il n'avait jamais totalement adhéré, a fait place à un nationalisme progressiste, précurseur de celui qu'allait épouser une proportion grandissante de la population québécoise.
Keywords: 20e siècle; 20th century; Daoust, Fernand, 1926-; Dirigeants syndicaux; Fédération des travailleurs et travailleuses du Québec; Histoire; History; Labor leaders; Quebec Federation of Labour; Québec (Province); Syndicalism; Syndicalisme

Rebel Life: The Life and Times of Robert Gosden, Revolutionary, Mystic, Labour Spy - Leier, Mark (James Mark) (New Star Books, 2013)
Extensively revised throughout and including a chapter of new material, Rebel Life chronicles the life of labour organizer, revolutionary, anarchist and labour spy Robert Gosden. Mark Leier's revisions incorporate new information about Gosden's career that has come to light since the first edition was published in 1999. Canada's west coast was rife with upheaval in the second and third decades of the twentieth century. At the centre of the turmoil is Robert Gosden, migrant labourer turned radical activistヨturned police spy. In 1913, he publicly recommends assassinating Premier Richard McBride to resolve theminers' strike. By 1919, he is urging Prime Minister Robert Borden to "disappear" key labour radicals to quelch rising discontent. What happened?Rebel Life plumbs the enigma that was Gosden, but it is much more: an introduction to BC labour history: a trove of rarely seen archival photograph, and sidebars rich with historical arcana; and, with its chapter describing the research that unearthed Gosden's story, Rebel Life is a rich resource for instructors, students, and trade unionists alike.

Climate@Work - Lipsig-Mummé, Carla (Labour in Canada (Halifax, N.S.), 2013)
Climate change is having an increasingly significant impact on work in Canada, and the effect climate change has, and will continue to have, on work concerns many Canadians. However, this fact has not been seriously considered either in academic circles, in the labour movement nor especially by the Canadian government. Climate@Work addresses this deficit by systematically tackling the question of the impact of climate change on work and employment and by analyzing Canada’s conservative silence towards climate change and the Canadian government’s refusal to take it seriously.--Publisher's description. Contents: Introduction. Section 1: Contexts.Changing Patterns in the Literature of Climate Change and Canadian Work: The Research of Academics, Government and Social Actors / Elizabeth Perry -- Climate, Work and Labour: the International Context / Carla Lipsig-Mummé --International Trade Agreements and the Ontario Green Energy Act: Opportunities and Obstacles / Stephen McBride & John Shields. Section 2: Sectors. The Impact of Climate Change on Employment and Skills Requirements in the Construction Industry / John O’Grady -- Climate Change and Labour in the Energy Sector / Marjorie Griffin Cohen & John Calvert -- The Transportation Equipment Industry / John Holmes, with Austin Hracs -- The Forestry Industry / John Holmes -- Tourism, Climate Change and the Missing Worker: Uneven Impacts, Institutions and Response / Steven Tufts -- Climate Change and Work and Employment in the Canadian Postal and Courier Sector / Meg Gingrich, Sarah Ryan & Geoff Bickerton. Includes bibliographical references (pages 177-196).
Keywords: Canada. Climatic changes; Climatic changes; Economic aspects; Economic aspects. Climatic changes; Government policy

From Demonized to Organized: Building the New Union Movement - Loreto, Nora (Our schools, our selves book series, 2013)
This book seeks to explain unionization to my generation; to my friends who distrust civil society organizations as much as they distrust government; to my unemployed friends who are living from contract to contract and who would kill for a stable, unionized job; for the workers who have never had the benefit of being represented when facing injustice at work; for the workers who would rather not think of what would happen if they were injured on the job. It’s a reminder to unionized folks that many of the truths that they take for granted are not obvious to others and that the labour movement must change how it reaches out to its members, its communities and to non-unionized workers if it hopes to grow. It’s a call to action for activists to share their stories, debunk the existing right-wing, anti-union rhetoric, re-engage in their communities, and build a movement that can defeat neoliberal policies and their political proponents. --From author's introduction
Keywords: Labour unions

Indigenous Women, Work, and History, 1940-1980 - McCallum, Mary Jane (Critical studies in Native history ; 16, 2013)
When dealing with Indigenous women’s history we are conditioned to think about women as private-sphere figures, circumscribed by the home, the reserve, and the community. Moreover, in many ways Indigenous men and women have been cast in static, pre-modern, and one-dimensional identities, and their twentieth century experiences reduced to a singular story of decline and loss. In Indigenous Women, Work, and History, historian Mary Jane Logan McCallum rejects both of these long-standing conventions by presenting case studies of Indigenous domestic servants, hairdressers, community health representatives, and nurses working in “modern Native ways” between 1940 and 1980. Based on a range of sources including the records of the Departments of Indian Affairs and National Health and Welfare, interviews, and print and audio-visual media, McCallum shows how state-run education and placement programs were part of Canada’s larger vision of assimilation and extinguishment of treaty obligations. Conversely, she also shows how Indigenous women link these same programs to their social and cultural responsibilities of community building and state resistance. By placing the history of these modern workers within a broader historical context of Aboriginal education and health, federal labour programs, post-war Aboriginal economic and political developments, and Aboriginal professional organizations, McCallum challenges us to think about Indigenous women’s history in entirely new ways. --Publisher's description. Contents: Sweeping the Nation: Indigenous women and domestic labour in mid-twentieth-century Canada -- Permanent solution: the placement and relocation program, hairdressers, and beauty culture -- Early labour history of community health representatives, 1960-1970 -- Gaining recognition: labour as activism among Indigenous nurses -- Wages of whiteness and the Indigenous historian.
Keywords: 20th century; Economic conditions; Employment; History; Indigenous women; Social conditions

Dominion of Capital: The Politics of Big Business and the Crisis of the Canadian Bourgeoisie, 1914-1947 - Nerbas, Don (University of Toronto Press, 2013)
In the critical decades following the First World War, the Canadian political landscape was shifting in ways that significantly recast the relationship between big business and government. As public pressures changed the priorities of Canada's political parties, many of Canada's most powerful businessmen struggled to come to terms with a changing world that was less sympathetic to their ideas and interests than before. Dominion of Capital offers a new account of relations between government and business in Canada during a period of transition between the established expectations of the National Policy and the uncertain future of the twentieth century. Don Nerbas tells this fascinating story through close portraits of influential business and political figures of this period - including Howard P. Robinson, Charles Dunning, Sir Edward Beatty, R.S. McLaughlin, and C.D. Howe - that provide insight into how events in different sectors of the economy and regions of the country shaped the political outlook and strategies of the country's business elite. Drawing on business, political, social, and cultural history, Nerbas revises standard accounts of government-business relations in this period and sheds new light on the challenges facing big business in early twentieth-century Canada. --Publisher's description. Contents: Part 1: Big Business from Triumph to Crisis. Provincial Man of Mystery: Howard P. Robinson and the Politics of Capital in New Brunswick -- Charles A. Dunning: A Progressive in Business and Politics -- The Dilemma of Democracy: Sir Edward Beatty, the Railway Question, and National Government. Part 2: Continentalism and the Managerial Ethic. -- Stewardship and Dependency: Sam McLaughlin, General Motors, and the Labour Question -- Engineering Canada: C.D. Howe and Canadian Big Business -- Conclusion -- Après le déluge -- Endnotes.

Public Sector Unions in the Age of Austerity - Ross, Stephanie; Savage, Larry (Labour in Canada (Halifax, N.S.), 2013)
For decades, public sector unions in Canada have been plagued by austerity, privatization, taxpayer backlash and restrictions on union rights. In recent years, the intensity of state-led attacks against public sector workers has reached a fevered pitch, raising the question of the role of public sector unions in protecting their members and the broader public interest. Public Sector Unions in the Age of Austerity examines the unique characteristics of public sector unionism in a Canadian context. Contributors to this multi-disciplinary collection explore both the strategic possibilities and challenges facing public sector unions that are intent on resisting austerity, enhancing their power and connecting their interests as workers with those of citizens who desire a more just and equitable public sphere. --Publisher's description

Rethinking Workplace Regulation: Beyond the Standard Contract of Employment - Stone, Katherine Van Wezel; Arthur, Harry W. (Russell Sage Foundation, 2013)
During the middle third of the 20th century, workers in most industrialized countries secured a substantial measure of job security, whether through legislation, contract or social practice. This "standard employment contract," as it was known, became the foundation of an impressive array of rights and entitlements, including social insurance and pensions, protection against unsociable working conditions, and the right to bargain collectively. Recent changes in technology and the global economy, however, have dramatically eroded this traditional form of employment. Employers now value flexibility over stability, and increasingly hire employees for short-term or temporary work. Many countries have also repealed labor laws, relaxed employee protections, and reduced state-provided benefits. As the old system of worker protection declines, how can labor regulation be improved to protect workers? In Rethinking Workplace Regulation, nineteen leading scholars from ten countries and half a dozen disciplines present a sweeping tour of the latest policy experiments across the world that attempt to balance worker security and the new flexible employment paradigm. Edited by noted socio-legal scholars Katherine V.W. Stone and Harry Arthurs, Rethinking Workplace Regulation presents case studies on new forms of dispute resolution, job training programs, social insurance and collective representation that could serve as policy models in the contemporary industrialized world. The volume leads with an intriguing set of essays on legal attempts to update the employment contract. For example, Bruno Caruso reports on efforts in the European Union to "constitutionalize" employment and other contracts to better preserve protective principles for workers and to extend their legal impact. The volume then turns to the field of labor relations, where promising regulatory strategies have emerged. Sociologist Jelle Visser offers a fresh assessment of the Dutch version of the 'flexicurity' model, which attempts to balance the rise in nonstandard employment with improved social protection by indexing the minimum wage and strengthening rights of access to health insurance, pensions, and training. Sociologist Ida Regalia provides an engaging account of experimental local and regional "pacts" in Italy and France that allow several employers to share temporary workers, thereby providing workers job security within the group rather than with an individual firm. The volume also illustrates the power of governments to influence labor market institutions. Legal scholars John Howe and Michael Rawling discuss Australiaʹs innovative legislation on supply chains that holds companies at the top of the supply chain responsible for employment law violations of their subcontractors. Contributors also analyze ways in which more general social policy is being renegotiated in light of the changing nature of work. Kendra Strauss, a geographer, offers a wide-ranging comparative analysis of pension systems and calls for a new model that offers "flexible pensions for flexible workers. With its ambitious scope and broad inquiry, Rethinking Workplace Regulation illustrates the diverse innovations countries have developed to confront the policy challenges created by the changing nature of work. The experiments evaluated in this volume will provide inspiration and instruction for policymakers and advocates seeking to improve worker's lives in this latest era of global capitalism. --Publisherʹs description
Keywords: Arbetsavtal; Arbetsmarknad; BUSINESS & ECONOMICS Labor; Contrat de travail; Labor contract; Osgoodiana

The Wages of Relief: Cities and the Unemployed in Prairie Canada, 1929-39 - Strikwerda, Eric (Working Canadians: Books from the CCLH, 2013)
In the early part of the Dirty Thirties, the Canadian prairie city was a relatively safe haven. Having faced recession before the Great War and then again in the early 1920s, municipalities already had relief apparatuses in place to deal with poverty and unemployment. Until 1933, responsibilty for the care of the urban poor remained with local governments, but when the farms failed that year, and the Depression deepened, western Canadian cities suffered tremendously. Recognizing the severity of the crisis, the national government intervened. Evolving federal programs and policies took over responsibility for the delivery of relief to the single unemployed, while the government simultaneously withdrew financing for all public works projects. Setting municipal relief administrations of the 1930s within a wider literature on welfare and urban poor relief, Strikwerda highlights the legacy on which relief policymakers relied in determining policy directions, as well as the experiences of the individuals and families who depended on relief for their survival. Focusing on three prairie cities—Edmonton, Saskatoon, and Winnipeg—Strikwerda argues that municipal officials used their power to set policy to address what they perceived to be the most serious threats to the social order stemming from the economic crisis. By analyzing the differing ways in which local relief programs treated married and single men, he also explores important gendered dynamics at work in the response of city administrators to the social and economic upheaval of the Depression. Probing the mindset of local elites struggling in extraordinary circumstances, The Wages of Relief describes the enduring impact of the policy changes made in the 1930s in the direction of a broad, national approach to unemployment—an approach that ushered in Canada’s modern welfare system. --Publisher's description
Keywords: 1905-1945; 20th century; Cities and towns; Economic conditions; Government policy History; History; MUNICIPAL government; Prairie Provinces; Public welfare administration; Social aspects History; Social conditions; Unemployed; Urban economics

Manufacturing Mennonites: Work and Religion in Post-War Manitoba - Thiessen, Janis Lee (Canadian social history series, 2013)
Manufacturing Mennonites examines the efforts of Mennonite intellectuals and business leaders to redefine the group's ethno-religious identity in response to changing economic and social conditions after 1945. As the industrial workplace was one of the most significant venues in which competing identity claims were contested during this period, Janis Thiessen explores how Mennonite workers responded to such redefinitions and how they affected class relations. Through unprecedented access to extensive private company records, Thiessen provides an innovative comparison of three businesses founded, owned, and originally staffed by Mennonites: the printing firm Friesens Corporation, the window manufacturer Loewen, and the furniture manufacturer Palliser. Complemented with interviews with workers, managers, and business owners, Manufacturing Mennonites pioneers two important new trajectories for scholarship - how religion can affect business history, and how class relations have influenced religious history. --Publisher's description

Joe Salsberg: A Life of Commitment - Tulchinsky, Gerald J. J. (University of Toronto Press, 2013)
This book follows the life and intellectual journey of Joseph Baruch Salsberg, a Polish-Jewish immigrant who became a major figure of the Ontario Left, a leading voice for human rights in the Ontario legislature, and an important journalist in the Jewish community. His life trajectory mirrored many of the most significant transformations in Canadian political and social life in the twentieth century. Award-winning historian Gerald Tulchinsky traces Salsberg’s personal and professional journey – from his entrance into Toronto’s oppressive garment industry at age 14, which led to his becoming active in emerging trade unions, to his rise through the ranks of the Communist Party of Canada and the Workers’ Unity League. Detailing Salsberg’s time as an influential Toronto alderman and member of the Ontario legislature, the book also examines his dramatic break with communism and his embrace of a new career in journalism. Tulchinsky employs historical sources not used before to explain how Salsberg’s family life and surrounding religious and social milieu influenced his evolution as a Zionist, an important labour union leader, a member of the Communist Party of Canada, and a prominent member of Toronto’s Jewish community. --Publisher's description
Keywords: Communists; Jews; Labor union members; Politicians; Politics and government; Salsberg, J. B. (Joseph B.), ca. 1903-1998; Social conditions

Selling Sex: Experience, Advocacy, and Research on Sex Work in Canada - Van der Meulen, Emily; Durisin, Elya M.; Love, Victoria (Sexuality studies series, 2013)
Despite being dubbed "the world's oldest profession," prostitution has rarely been viewed as a legitimate form of labour. Instead, it has been criminalized, sensationalized, and polemicized across the socio-political spectrum by everyone from politicians to journalists to women's groups. Interest in and concern over sex work is not grounded in the lived realities of those who work in the industry, but rather in inflammatory ideas about who is participating, how they wound up in this line of work, and what form it takes. In Selling Sex, Emily van der Meulen, Elya M. Durisin, and Victoria Love present a more nuanced, balanced, and realistic view of the sex industry. They bring together a vast collection of voices - including researchers, feminists, academics, and advocates, as well as sex workers of differing ages, genders, and sectors - to engage in a dialogue that challenges the dominant narratives surrounding the sex industry and advances the idea that sex work is in fact work. Presenting a variety of opinions and perspectives on such diverse topics as the social stigma of sex work, police violence, labour organizing, anti-prostitution feminism, human trafficking, and harm reduction, Selling Sex is an eye-opening, challenging, and necessary book. --Publisher's description
Keywords: Government policy; Labor Unions; Law and legislation; Organizing; Prostitutes; Prostitution; Sex-oriented businesses

Du pain ou du sang : les travailleurs irlandais et le canal de Beauharnois - Viau, Roland (PUM, 2013)
Le 12 juin 1843 restera dans la mémoire comme le « Lundi rouge » : un jour funeste, où plusieurs ouvriers irlandais affectés au creusement du canal Beauharnois trouvent la mort pour avoir réclamé de meilleures conditions de travail. Plus de deux mille « canaliers » en grève illégale subissent la charge des troupes de la garnison qui les dispersent avec une violence démesurée devant l’hôtel où logent leurs patrons – feux, sabres et chevaux contre pelles, pioches et gourdins. Cet événement tragique marque à ce jour le conflit de travail le plus sanglant de l’histoire du Canada. L’indignation générale contraint le gouvernement à instituer une des premières enquêtes publiques du pays. Une enquête biaisée, comme le démontre brillamment Roland Viau qui examine de nouvelles pièces au dossier en faisant revivre le quotidien des familles irlandaises installées le long du canal. Il aboutit à des constats troublants, révélant l’arbitraire des tribunaux envers ces travailleurs migrants honteusement exploités et méprisés, et met à jour l’existence d’une société secrète qui préfigure le mouvement syndical. --Publisher's description
Keywords: 1800-1899; Beauharnois Canal (Québec) History 19th century; Beauharnois Canal Strike, Québec, 1843; Canal de Beauharnois (Québec) Histoire 19e siècle; Canals Design and construction; Canals Québec (Province) Beauharnois Design and construction History; Canaux Québec (Canada; province) Beauharnois (Canada) Conception et construction; Canaux Québec (Province) Beauharnois Conception et construction Histoire; Condition sociale; Condition économique; Foreign workers, Irish Québec (Province) Economic conditions 19th century; Foreign workers, Irish Québec (Province) Social conditions 19th century; Grève des ouvriers du canal de Beauharnois (Québec, 1843); Grève des ouvriers du canal de Beauharnois, Québec, 1843; History; Irlandais; Québec; Québec Beauharnois; Québec Beauharnois Canal; Travailleur étranger; Travailleurs étrangers irlandais Québec (Canada; province) Conditions rurales 19e siècle; Travailleurs étrangers irlandais Québec (Canada; province) Conditions rurales Conditions économiques 19e siècle; Travailleurs étrangers irlandais Québec (Province) Conditions sociales 19e siècle; Travailleurs étrangers irlandais Québec (Province) Conditions économiques 19e siècle

Debating Dissent: Canada and the 1960s - Azzi, Stephen; Boudreau, Michael; Campbell, Lara; Carstairs, Catherine; Dyck, Erika; Gidney, Catherine; Hayday, Matthew; Hewitt, Steve; Igartua, José E.; Lexier, Roberta; Martel, Marcel; McInnis, Peter S. (Peter Stuart); et al. (Canadian social history series, 2012)
Although the 1960s are overwhelmingly associated with student radicalism and the New Left, most Canadians witnessed the decade's political, economic, and cultural turmoil from a different perspective. Debating Dissent dispels the myths and stereotypes associated with the 1960s by examining what this era's transformations meant to diverse groups of Canadians - and not only protestors, youth, or the white middle-class.With critical contributions from new and senior scholars, Debating Dissent integrates traditional conceptions of the 1960s as a 'time apart' within the broader framework of the 'long-sixties' and post-1945 Canada, and places Canada within a local, national, an international context. Cutting-edge essays in social, intellectual, and political history reflect a range of historical interpretation and explore such diverse topics as narcotics, the environment, education, workers, Aboriginal and Black activism, nationalism, Quebec, women, and bilingualism. Touching on the decade's biggest issues, from changing cultural norms to the role of the state, Debating Dissent critically examines ideas of generational change and the sixties. --Publisher's description

Aboriginal History: A Reader - Burnett, Kristin; Reid, Geoff (Oxford University Press, 2012)
Combining contemporary articles with historical documents, this engaging reader examines the rich history of Canada's Aboriginal peoples. The 30 articles - half of which are original to this volume - explore a diverse range of topics, including spirituality, colonialism, self-identity, federal policy, residential schools, labour, and women's rights. With in-depth coverage of events and processes from the earliest times through to the modern day, [the reader] offers students a new appreciation for the long and complex history of Canada's First Nations, Métis, and Inuit peoples. --Publisher's description
Keywords: Indians of North America -- Canada -- Historiography

Saving for Retirement: Intention, Context, and Behavior - Clark, Gordon L.; Strauss, Kendra; Knox, Janelle Kallie (Oxford University Press, 2012)
Understanding the ways in which people save for their retirement is an urgent issue. So much has changed in the last 10 to 15 years, especially in the area of the provision of pensions and retirement income. Around the world, greater and greater responsibility is being allocated to individuals while governments discount their contributions to social security and employers retreat from the provision of supplementary retirement income. This book explores the behavioral revolution and its implications for understanding financial decision-making and saving for the future. Recognizing the profound implications of this research program, it goes beyond issues of risk aversion, framing, and decision-making to consider how social identity and the resources due to people by virtue of their place in society figure in savings behavior. It gives considerable attention to the context of the environment in which people make financial decisions, arguing that this allows a better understanding of the coexistence of sophistication and naivety apparent in patterns of retirement saving. Utilizing databases from the UK, the book provides an empirical foundation to its theoretical arguments, demonstrating how an integrated approach to individual financial decision-making is necessary if we are to address the apparent shortfall in many people's planning for the future. The book concludes by setting the agenda for the design, governance, and regulation of pension savings schemes consistent with delivering cost-effective solutions to pension adequacy. In these ways, it sets forth a strategy for rethinking individual behavior as well as the design of retirement income systems. --Publisher's description
Keywords: Altersversorgung; Finance, Personal Decision making; Pensions; Rentenversicherung; Retirement income Planning Psychological aspects; Revenu de retraite Planification Aspect psychologique; Soziale Sicherheit; Sparen; pensions (compensation)

Governing Cultures: Anthropological Perspectives on Political Labor, Power, and Government - Coulter, Kendra; Schumann, William R. (Palgrave Macmillan, 2012)
Governments are formal political institutions, places of work for thousands of women and men, and powerful social, cultural, and economic sites that shape the lives of all people. This collection demonstrates how anthropologists enrich our understandings of government by exploring the labor of those who govern, and how the dynamics of culture are at the heart of government actions that justify, modify, and reproduce political action. By assembling original, ethnographically-grounded research in legislatures, executives, and bureaucracies, this volume illuminates and unpacks the structures, practices, and values of government actors in local, regional, and national contexts. It will be of interest to scholars and students in anthropology, as well as sociology, political science, policy studies, and labor studies. --Publisher's description
Keywords: Anthropologie politique; Government policy; Legislative power; Political anthropology; Pouvoir législatif

Labour Goes to War: The CIO and the Construction of a New Social Order, 1939-45 - Cuthbertson, Wendy (Studies in Canadian military history, 2012)
During the Second World War, the Congress of Industrial Organizations in Canada grew from a handful of members to more than a quarter-million and from political insignificance to a position of influence in the emergence of the welfare state. What was it about the "good war" that brought about this phenomenal growth? And how did this coming of age during the war affect the emerging CIO? Labour Goes to War analyzes the organizing strategies of the CIO during the war to show that both economic and cultural forces were behind its explosive growth. Labour shortages gave workers greater power in the workplace and increased their militancy. But workers’ patriotism, their ties to those on active service, memories of the First World War, and allegiance to the "people’s war" also contributed to the CIO’s growth - and to what it claimed for workers. At the same time, union organizers and workers influenced one another as the war changed lives, opinions, expectations - and notions of women’s rights. Drawing on an impressive array of archival material, Wendy Cuthbertson illuminates this complex wartime context. Her analysis shows how the war changed lives, opinions, and expectations. She also shows how the complex, often contradictory, motives of workers during this period left the Canadian labour movement with an ambivalent progressive/conservative legacy. --Publisher's description
Keywords: 20th century. Labor unions; 20th century. Syndicalisation; Canada; Histoire; History; Labor Unions; Ontario; Organizing; Organizing. Labor unions; Political activity; Political activity. Social conditions

Raising the Workers' Flag: The Workers' Unity League of Canada, 1930-1936 - Endicott, Stephen Lyon (University of Toronto Press, 2012)
During the Great Depression, the conflicting interests of capital and labour became clearer than ever before. Radical Canadian workers, encouraged by the Red International of Labour Unions, responded by building the Workers' Unity League – an organization that greatly advanced the cause of unions in Canada, and boasted 40,000 members at its height. In Raising the Workers' Flag, the first full-length study of this robust group, Stephen L. Endicott brings its passionate efforts to light in memorable detail. Raising the Workers' Flag is based on newly available or previously untapped sources, including documents from the Royal Canadian Mounted Police's Security Service and the Communist Party's archives. Using these impressive finds, Endicott gives an intimate sense of the raging debates of the labour movement of the 1930s. A gripping account of the League's dreams and daring, Raising the Workers' Flag enlivens some of the most dramatic struggles of Canadian labour history. -- Publisher's description
Keywords: Economic conditions; History; Labor Unions; Politics and government; Social conditions; Working class

Michel Chartrand : les dires d'un homme de parole - Foisy, Fernand (PCL/Petite collection Lanctôt, 2012)
"Michel Chartrand/Les dires d'un homme de parole" est composé d'extraits de discours et d'entrevues qui s'échelonnent sur près de trente ans de vie syndicale active. Ces textes, ces réflexions, ces discours témoignent d'une même volonté, parfois provocatrice, de dénoncer la bêtise et l'injustice où qu'elles soient. Michel Chartrand est un des plus anciens leaders syndicaux du Québec. Depuis qu'il milite en faveur des plus démunis de la société, les gouvernements se sont succédé, les uns ont été remplacés par d'autres, parfois plus progressistes, et ses propos demeurent toujours d'actualité. Ce qu'il dénonçait durant les années soixante l'appauvrissement des classes populaires, le gaspillage et la dilapidation honteuse de nos richesses, l'insécurité des travailleurs, le manque de prévoyance des grands patrons d'industrie doit toujours l'être aujourd'hui. Et ce qu'il pronait hier la justice sociale, la solidarité entre les humains, la liberté d'expression fait encore partie des grandes priorités de l'heure. --Résumé de l'éditeur
Keywords: Biographies; Chartrand, Michel, 1916- Citations; Chartrand, Michel, 1916- Entretiens; Chartrand, Michel, 1916- Pensée politique et sociale; Dirigeants syndicaux Québec (Province) Biographies; Labor leaders; Labor leaders Québec (Province) Biography; Québec; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province)

May Day: A Graphic History of Protest - Folvik, Robin; Graphic History Collective (Group) (Between the Lines, 2012)
[This booklet] traces the development of International Workers’ Day, May 1st, against the ever-changing economic and political backdrop in Canada. Recognizing the importance of work and the historical struggles of workers to improve their lives, with a particular focus on the struggles of May 1st, the comic includes the reader as part of this history, and the story concludes that “We are all part of this historical struggle; it’s our history and our future." --Publisher's description

Le péril rouge: la première guerre canadienne contre le terrorisme, 1918-1919 - Francis, Daniel (Collection Mémoire des Amériques, 2012)
À la fin de la Première Guerre mondiale, le Canada menace de basculer dans une révolution sociale. Rassemblements et mobilisations des milieux ouvriers se succèdent durant l’hiver 1918-1919 et culminent avec la grève générale de Winnipeg en mai-juin 1919. Le mouvement est finalement écrasé par l’armée sur l’ordre de Robert Borden, premier ministre de l’époque. Cette suite d’événements, qui correspond dans les faits à un conflit de travail généralisé, est immédiatement associée par les autorités à la menace d’une révolution bolchevique. Le gouvernement et les médias lancent une grande campagne de diabolisation à l’endroit des chefs syndicaux et autres leaders politiques. Le but, bien évidemment, est d’user de la peur que suscitent partout les rouges pour étouffer le conflit social, et d’obtenir le soutien de l’opinion publique pour l’éradication de toute activité politique jugée radicale. Fondé sur des documents officiels et des témoignages de première main, cet ouvrage raconte un épisode méconnu mais déterminant de l’histoire canadienne. La campagne contre « le péril rouge » a joué un rôle fondamental dans la répression des conflits de travail de l’entre-deux-guerres. Depuis, la même recette a été utilisée pour les mêmes raisons. En outre, les parallèles avec la guerre actuelle contre le terrorisme se font sans effort. Aujourd’hui comme hier, les libertés d’expression et de contestation de l’ordre établi sont contraintes au nom d’une sécurité nationale aux frontières desquelles semblent s’arrêter les droits civils. --Résumé de l'éditeur
Keywords: Anticommunisme; Grève générale, Winnipeg, Man., 1919; Histoire; Influence

Constitutional Labour Rights in Canada: Farm Workers and the Fraser Case - Fudge, Judy; Tucker, Eric; Faraday, Fay (Irwin Law, 2012)
On 29 April 2011, the Supreme Court of Canada released its much-anticipated decision in Attorney General of Ontario v Fraser, which dealt with the scope of constitutional protection of collective bargaining. The case involved a constitutional challenge to an Ontario statute on the grounds that it violated agricultural workers’ freedom of association and right to equality by excluding them from the statutory protection that is available to virtually all other private sector workers and by failing to provide them with alternative legislative support for meaningful and effective collective bargaining rights. Although the Court upheld the constitutionality of the legislation by an eight to one majority, it provided four different, and incommensurable, sets of reasons. For the union that instigated the litigation, Fraser is a defeat. For the labour movement and their advocates, Fraser is ambiguous. What is clear, however, is that the Supreme Court of Canada was badly divided over the scope of protection that freedom of association provides to the right to bargain collectively. This collection of original essays untangles the two stories that are intertwined in the Fraser decision—the story of the farm workers and their union’s attempt to obtain rights at work available to other working people in Ontario, and the tale of judicial discord over the meaning of freedom of association in the context of work. The contributors include trade unionists, lawyers, and academics (several of whom were involved in Fraser as witnesses, parties, lawyers, and interveners). The collection provides the social context out of which the decision emerged, including a photo essay on migrant workers, while at the same time illuminating Fraser’s broader jurisprudential and institutional implications. --Publisher's description
Keywords: Agricultural laborers; Canada. Arbeitsrecht. Verfassungsrecht; Canada. Collective bargaining; Canada. Employee rights; Canada. Freedom of association; Canada. Liberté d'association; Canada. Migrant agricultural laborers; Canada. Négociations collectives; Canada. Personnel; Canada. Travailleurs agricoles; Canada. Travailleurs agricoles migrants; Droit; Droits; Law and legislation; Legal status, laws, etc.

Negotiating Risk, Seeking Security, Eroding Solidarity: Life and Work on the Border - Gibbs, Holly; Yates, Charlotte A. B. (Charlotte Alyce Bronwen); Leach, Belinda (Fernwood Publishing, 2012)
Through a series of interviews with workers in the automotive parts industry, Negotiating Risk argues that the restructuring of labour markets and welfare states, paired with firm-level work and management reorganization, has exposed working-class families to greater levels of job risk and insecurity. Focusing on workers in Canada and Mexico and using a gender and race analysis, this book paints a bleak portrait of the lives of working people, where workers and their families continually renegotiate the effects of neo-liberal economic and social change. These changes see individuals working harder, longer and travelling further from home to keep their jobs, while straining familial and community relations and eroding the basis for worker solidarity and collective action. --Publisher's description. Contents: Negotiating risk, seeking security, eroding solidarity -- Labour markets, the state and work through the lens of the automotive parts industry -- Communities and their labour markets -- Experiencing risk and seeking security -- Gendered practices of coping with risk and insecurity -- Sustaining livelihoods through mobility -- Whither solidarity?
Keywords: Canada. Automobile supplies industry; Canada. Automobiles; Canada. Labor market; Canada. Labor mobility; Canada. Working class families; Labor market; Mexico. Automobile supplies industry; Mexico. Labor mobility; Mexico. Working class families; Mexique. Automobiles

Breccia: Haiku and Related Forms - Golas, Irene; Fay, Ignatius (Irene Golas, Ignatius Fay, Lulu.com, 2012)
We chose Breccia as our title to reflect the nature of the [poetry] collection and our geographical location in Sudbury, Ontario. ...One section of this book, "Sudbury Breccia," grew out of a few poems about that northern mining town. We were attracted to the idea of examining life in such a town from World War II into the new millennium as seen through the eyes of a haiku poet. The diverse cultural mix of the miners themselves further enhances the breccia theme. The earliest miners were, primarily, a mélange of European immigrants who relocated to find a better life. This potpourri was enriched by large numbers of immigrants and displaced persons fleeing a war-ravaged Europe. The result was a northern Ontario mining culture with a distinctly varied foundation. --From authors' introduction. Six haiku by Ignatius Fay: headlamps off / inky black and the sounds / of shifting rock -- dad's St. Christopher / black with sweat / and mine dust -- two p.m. / the school shudders / with the mine's daily blast -- moving day / his father's job lost / to a Scooptram -- retired from mining / the school janitor's limp / worse in autumn -- played-out mine site - / the green of young thistles / in rust-stained soil. Tanka by Ignatius Fay: Levack North Mine / sixteen-hundred-foot level / the weight / of three billion years / over my head.

The Canadian Labour Movement: A Short History - Heron, Craig (Lorimer, 2012)
[H]istorian Craig Heron tells the story of Canada's workers from the mid-nineteenth century through to today, painting a vivid picture of key developments such as the birth of craft unionism, the breakthroughs of the fifties and sixties, and the setbacks of the early twenty-first century. This new edition has been completely updated, including a substantial new chapter that covers the period from 1995 to 2011. In this chapter, Heron describes the rise of globalization and the restructuring of the private sector that began in the nineties and continues today. The results have been catastrophic for Canadian working people as plants closed and union activities were curtailed. As the political right succeeded in dominating public debate during this period, workers suffered ever greater losses: fewer and more precarious jobs, rising unemployment, stagnating wages, and increases in poverty. Only with the crash of 2008 and the Occupy Wall Street movement has space for the political left and labour begun to open up once again. [This] is the definitive book for anyone who is interested in understanding the origins, achievements, and challenges of labour and social justice movements in Canada.--Publisher's description
Keywords: Histoire; History; Labor Unions; Syndicats

Legislated Inequality: Temporary Labour Migration in Canada - Lenard, Patti Tamara; Straehle, Christine (McGill-Queen's University Press, 2012)
Historically, Canada has adopted immigration policies focused on admitting migrants who were expected to become citizens. A dramatic shift has occurred in recent years as the number of temporary labourers admitted to Canada has increased substantially. Legislated Inequality critically evaluates this radical development in Canadian immigration, arguing that it threatens to undermine Canada's success as an immigrant nation. Assessing each of the four major temporary labour migration programs in Canada, contributors from a range of disciplines - including comparative political science, philosophy, and sociology - show how temporary migrants are posed to occupy a permanent yet marginal status in society and argue that Canada's temporary labour policy must undergo fundamental changes in order to support Canada's long held immigration goals. The difficult working conditions faced by migrant workers, as well as the economic and social dangers of relying on temporary migration to relieve labour shortages, are described in detail. Legislated Inequality provides an essential critical analysis of the failings of temporary labour migration programs in Canada and proposes tangible ways to improve the lives of labourers. --Publisher's description

The Punjabis in British Columbia: Location, Labour, First Nations, and Multiculturalism - Nayar, Kamala E. (Kamala Elizabeth) (McGill-Queen's studies in ethnic history, 2012)
In this richly detailed study, Kamala Nayar documents the social and cultural transformation of the Punjabi community in British Columbia. From their initial settlement in the rural Skeena region to the communities that later developed in larger urban centres, The Punjabis in British Columbia illustrates the complex and diverse experiences of an immigrant community that merits greater attention. Exploring themes of gender, employment, rural and urban migrant life, and the relationships between the Punjabis and surrounding First Nations and other immigrant groups, Nayar creates a portrait of a community in transition. Shedding light on the ways in which economic circumstances affect immigrant communities, Nayar presents findings from interviews conducted with over one hundred participants. She details the relocation of Punjabi populations from the Skeena region to British Columbia's lower mainland during the decline of the forestry and fishery industries, how their second migration changed their professional and personal lives, and how their history continues to shape the identities and experiences of Punjabis in Canada today. A nuanced look at the complexities of social and cultural adaptation, The Punjabis in British Columbia adds an essential perspective to what it means to be Canadian. --Publisher's description
Keywords: Panjabis (South Asian people) -- British Columbia -- Skeena River Region -- Economic conditions -- 20th century -- Case studies

Jobs and Justice: Fighting Discrimination in Wartime Canada, 1939-1945 - Patrias, Carmela (University of Toronto, 2012)
Despite acute labour shortages during the Second World War, Canadian employers—with the complicity of state officials—discriminated against workers of African, Asian, and Eastern and Southern European origin, excluding them from both white collar and skilled jobs. Jobs and Justice argues that, while the war intensified hostility and suspicion toward minority workers, the urgent need for their contributions and the egalitarian rhetoric used to mobilize the war effort also created an opportunity for minority activists and their English Canadian allies to challenge discrimination. Juxtaposing a discussion of state policy with ideas of race and citizenship in Canadian civil society, Carmela K. Patrias shows how minority activists were able to bring national attention to racist employment discrimination and obtain official condemnation of such discrimination. Extensively researched and engagingly written, Jobs and Justice offers a new perspective on the Second World War, the racist dimensions of state policy, and the origins of human rights campaigns in Canada. --Publisher's description
Keywords: Civil rights; Discrimination in employment; Employment; Government policy; History; Minorities; Race relations; Racism

Union Power: Solidarity and Struggle in Niagara - Patrias, Carmela; Savage, Larry (Working Canadians: Books from the CCLH, 2012)
From factory workers in Welland to retail workers in St. Catharines, from hospitality workers in Niagara Falls to migrant farm workers in Niagara-On-The-Lake, Union Power showcases the role of working people in the Niagara region. Charting the development of the region's labour movement from the early nineteenth century to the present, Patrias and Savage illustrate how workers from this highly diversified economy struggled to improve their lives both inside and outside the workplace. Including extensive quotations from interviews, archival sources, and local newspapers, the story unfolds, in part, through the voices of the people themselves: the workers who fought for unions, the community members who supported them, and the employers who opposed them. Early industrial development and the appalling working conditions of the often vulnerable common labourer prompted a movement toward worker protection. Patrias and Savage argue that union power – power not built on profit, status, or prestige – relies on the twin concepts of struggle and solidarity: the solidarity of the shared interests of the working class and the struggle to achieve common goals. Union Power traces the evidence of these twin concepts through the history of the Niagara region's labour movement. --Publisher's description
Keywords: History; Labor Unions; Labor movement; Nigara Peninsula

Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada - Peters, John (Labour in Canada (Halifax, N.S.), 2012)
Boom, Bust, and Crisis addresses...how work has changed across Canada, from the auto and steel industries of Ontario, to the tar sands of Northern Alberta and First Nations casinos in Saskatchewan. This edited collection explains the massive lay-offs in unionized manufacturing industries, the expansion of low-wage work and the rise of increasingly aggressive employers by critically examining Canada’s political economy and assessing the impact of government policy and labour market deregulation on Canada’s workers. The book also explores the recent policy changes to employment standards and health and safety protection in the context of neoliberal globalization. Written by leading political scientists, sociologists and journalists in concise, accessible language, this volume provides a rich and vibrant assessment of why some businesses have boomed while others have failed and why, through it all, Canadian workers have paid the price. --Publisher's description. Contents: Pt.1. The shifting political landscape. Free markets and the decline of unions and good jobs / John Peters -- The spoils of the Tar Sands: profits, work and labour in Alberta / Diana Gibson and Regan Boychuk -- Boom, bust, and bluster: Newfoundland and Labrador's "oil boom" and its impacts on labour / Sean T. Cadigan -- Steel City meltdown: Hamilton and the changing Canadian steel industry / Stephen R. Arnold -- Pt.2. Deregulation and changes in provincial labour market policy, politics and institutions. The biggest roll-back of worker rights in Canadian history: the Campbell government and labour market deregulation in British Columbia / David Fairey, Tom Sandhorn and John Peters -- Whither the Quebec model? Boom, bust and Quebec labour / Peter Graefe. Pt.3. New challenges facing labour organizing, health and safety. Indigenous workers, casino development and union organizing / Yale D. Belanger -- Precarious employment and occupational health and safety in Ontario / Wayne Lewchuk, Marlea Clarke and Alice de Wolff.
Keywords: Business and politics; Economic conditions; Employee rights; Industrial relations; Labor policy

Dynamic Negotiations: Teacher Labour Relations in Canadian Elementary and Secondary Education - Queen's University (Kingston, Ont.). School of Policy Studies (Queen's Policy Studies Series, 2012)
Taking an inter-provincial comparative approach, Dynamic Negotiations identifies potential avenues of reform. Academic and legal experts describe and analyse the history, current structure, and functioning of bargaining in public elementary and secondary schools in six key jurisdictions - Alberta, British Columbia, Manitoba, Ontario, Quebec, and Newfoundland - representing a spectrum of approaches. This is a vital area of public policy that is much discussed but not well enough understood. The volume is a valuable resource for policy-makers, academics, and practitioners in education and labour relations. --Publisher's description. Contents: Introduction: Labour Relations in Primary and Secondary Canadian Education / Sara Slinn and Arthur Sweetman -- Crosscurrents: Comparative Review of Elementary and Secondary Teacher Collective Bargaining Structures in Canada / Karen Schucher and Sara Slinn -- The Great Divide: School Politics and Labour Relations in British Columbia before and after 1972 / Thomas Fleming -- Conflict without Compromise: The Case of Public Sector Teacher Bargaining in British Columbia / Sara Slinn -- Oil and Ideology: The Transformation of K-12 Bargaining in Alberta / Kelly Williams-Whitt -- Teacher Collective Bargaining in Manitoba / Valerie J. Matthews Lemieux -- The Evolution of Teacher Bargaining in Ontario / Joseph B. Rose -- Collective Bargaining for Teachers in Ontario: Central Power, Local Responsibility / Elizabeth Shilton -- The Centralization of Collective Bargaining in Ontario's Public Education Sector and the Need to Balance Stakeholder Interests / Brendan Sweeney, Susan McWilliams, and Robert Hickey -- Labour Relations in the Quebec K-11 Education Sector: Labour Regulation under Centralization / Jean-Noël Grenier and Mustapha Bettache -- K-12 Teacher Collective Bargaining in Newfoundland and Labrador / Travor C. Brown.
Keywords: Collective bargaining; Public schools; Teachers; Teachers' unions

Rethinking the Politics of Labour in Canada - Ross, Stephanie; Savage, Larry (Labour in Canada (Halifax, N.S.), 2012)
Though the Canadian labour movement’s postwar political, economic and social achievements may have seemed like irrevocable contributions to human progress, they have proven to be anything but. Since the mid-1970s, labour’s political influence and capacity to defend, let alone extend, these gains has been seriously undermined by the strategies of both capitalist interests and the neoliberal state. Electoral de-alignment and the decline of class-based voting, bursts of unsustained extra-parliamentary militancy and a general lack of influence on state actors and policy outcomes all signal that the labour movement is in crisis. Despite much experimentation in an attempt to regain political clout, labour continues to experience deep frustration and stagnation. As such, the labour movement’s future political capacities are in question, and the need for critical appraisal is urgent. Understanding how and why workers were able to exert collective power in the postwar era, how they lost it and how they might re-establish it is the central concern of Rethinking the Politics of Labour in Canada. With essays from established and emerging scholars from a wide range of disciplines, this collection assesses the past, present and uncertain future of labour politics in Canada. Bringing together the traditional electoral-based aspects of labour politics with analyses of the newer and rediscovered forms of working-class organization and social movement-influenced strategies, which have become increasingly important in the Canadian labour movement, this book seeks to take stock of these new forms of labour politics, understand their emergence and assess their impact on the future of labour in Canada. --Publisher's description
Keywords: History; Labor Unions; Labor movement; Political activity; Political aspects

This Great National Object: Building the Nineteenth-Century Welland Canals - Styran, Roberta M. (Roberta McAfee); Taylor, Robert R. (McGill-Queen's University Press, 2012)
[The authors] recount the story of the canals, with particular emphasis on the experiences of the engineers, contractors, and labourers who built the inland waterways between 1824 and 1889. Making extensive use of the National Archives and the Archives of Ontario, Styran and Taylor unveil previously unpublished information about the construction of the canals, including technical plans and drawings from a wide variety of sources. They illustrate the technical and management intricacies of building a navigational trade and commerce lifeline while also revealing the vivid characters - from businessman William Hamilton Merritt to engineer John Page - who inspired the project and drove it to completion. The history of the Welland Canals is a gripping tale of epic proportions. Given the ongoing importance of the Great Lakes in the North American economy, interest in the St. Lawrence Seaway - of which the Welland is "the Great Swivel Link" - and the relevance of labour history, This Great National Object will be of interest to enthusiasts and historians alike. --Publisher's description
Keywords: Histoire; History

Company Towns: Corporate Order and Community - White, Neil (University of Toronto Press, 2012)
Company towns are often portrayed as powerless communities, fundamentally dependent on the outside influence of global capital. Neil White challenges this interpretation by exploring how these communities were altered at the local level through human agency, missteps, and chance. Far from being homogeneous, these company towns are shown to be unique communities with equally unique histories. Company Towns provides a multi-layered, international comparison between the development of two settlements—the mining community of Mount Isa, Queensland, Australia, and the mill town of Corner Brook, Newfoundland, Canada. White pinpoints crucial differences between the towns' experiences by contrasting each region's histories from various perspectives—business, urban, labour, civic, and socio-cultural. Company Towns also makes use of a sizable collection of previously neglected oral history sources and town records, providing an illuminating portrait of divergence that defies efforts to impose structure on the company town phenomenon. --Publisher's description
Keywords: Community life; Company towns; Corporations; Economic conditions; History; Social aspects; Social conditions

The Colonization of Mi'kmaw Memory and History, 1794-1928: The King V. Gabriel Sylliboy - Wicken, William Craig (University of Toronto Press, 2012)
In 1927, Gabriel Sylliboy, the Grand Chief of the Mi'kmaw of Atlantic Canada, was charged with trapping muskrats out of season. At appeal in July 1928, Sylliboy and five other men recalled conversations with parents, grandparents, and community members to explain how they understood a treaty their people had signed with the British in 1752. Using this testimony as a starting point, William Wicken traces Mi'kmaw memories of the treaty, arguing that as colonization altered Mi'kmaw society, community interpretations of the treaty changed as well. The Sylliboy case was part of a broader debate within Canada about Aboriginal peoples' legal status within Confederation. In using the 1752 treaty to try and establish a legal identity separate from that of other Nova Scotians, Mi'kmaw leaders contested federal and provincial attempts to force their assimilation into Anglo-Canadian society. Integrating matters of governance and legality with an exploration of historical memory, The Colonization of Mi'kmaw Memory and History offers a nuanced understanding of how and why individuals and communities recall the past."--Publisher's description. Contents: Part 1: Why the Men Testified. 1. Accounting for Alex Gillis's actions: the Mi'kmaq in rural society -- 2. Why Nova Scotia prosecuted Gabriel Sylliboy -- 3. Moving to appeal: Mi'kmaw and government motivations. Part 2: How the Men Remembered. 4. Parents, grandparents, and great grandparents, 1794-1853. 5. Reserve life, 1850-1881: remembering the treaty. Part 3: Why the Men Remembered. 6. The demography of Mi'kmaw communities, 1871-1911 -- 7. Moving into the city: the King's Road Reserve and the politics of relocation. Appendix: The Federal and DIA censuses, 1871-1911.
Keywords: Aspect social; Colonisation; Colonization; Government policy; Histoire. Collective memory. Memory; Histoire. Micmac (Indiens); History. Micmac (Indiens); History. Micmac Indians; Micmac Indians; Nouvelle-cosse; Nouvelle-cosse. Micmac (Indiens); Nouvelle-cosse. Mmoire; Nouvelle-cosse. Mmoire collective; Nova Scotia; Nova Scotia. Collective memory; Nova Scotia. Memory; Nova Scotia. Micmac Indians; Politique gouvernementale; Social aspects; Social aspects. Micmac Indians. Micmac Erinnerung

Indigenous Women and Work: From Labor to Activism - Williams, Carol (University of Illinois Press, 2012)
The essays in [this book] create a transnational and comparative dialogue on the history of the productive and reproductive lives and circumstances of Indigenous women from the late nineteenth century to the present in the United States, Australia, New Zealand/Aotearoa, and Canada. Surveying the spectrum of Indigenous women's lives and circumstances as workers, both waged and unwaged, the contributors offer varied perspectives on the ways women's work has contributed to the survival of communities in the face of ongoing tensions between assimilation and colonization. They also interpret how individual nations have conceived of Indigenous women as workers and, in turn, convert these assumptions and definitions into policy and practice. The essays address the intersection of Indigenous, women's, and labor history, but will also be useful to contemporary policy makers, tribal activists, and Native American women's advocacy associations. --Publisher's description
Keywords: Employment; Employment. Native women; Indigenous women

Dead Horse on the Tulameen: Settler Verse from B.C.'s Similkameen Valley - Bartlett, Jon; Ruebsaat, Rika (Canada Folk Workshop, 2011)
A drill makes the music that rings in his ears But a candle's the charmer to drive away fears, Down deep underground where grim shadows are thick - Here's to you always, my old candlestick! So said an underground miner in the Similkameen Valley back in 1900. This book brings the abandoned mines and ghost towns of southwestern BC back to life as voices from the grave tell their stories in verse. These voices lay silent for decades until Jon Bartlett and Rika Ruebsaat discovered them. Like prospectors panning for gold, Bartlett and Ruebsaat sifted through the fragile pages of old newspapers in the Princeton Archives until they hit paydirt in the form of poems about daily life in the Similkameen valley ~ how did it feel to leave the fields and hedgerows of England and come to the BC wilderness? What tools did our early miners use? Why did it take so long for the railway to come to the Similkameen? The poems in this book together with extensive archival photographs as well as Bartlett and RuebsaatÃ¢ÂÂs historical narrative paint a vivid picture of pioneer life in BC's Similkameen valley. --Publisher's description
Keywords: 1900-1999; Canadian poetry; Canadian poetry (English) 20th century; Canadian poetry (English) Similkameen River Valley (B.C. and Wash.); Canadian poetry 20th century; Canadian poetry Similkameen River Valley (B.C. and Wash.); Chansons folkloriques anglaises Similkameen, Vallée de la (C.-B. et Wash.) Textes; Folk songs, English; Folk songs, English Similkameen River Valley (B.C. and Wash.) Texts; History; North America Similkameen River Valley; Poésie canadienne-anglaise 20e siècle; Poésie canadienne-anglaise Similkameen, Vallée de la (C.-B. et Wash.); Similkameen River Valley (B.C. and Wash.) History; Similkameen, Vallée de la (C.-B. et Wash.) Histoire; Texts

Labour at the Lakehead: Ethnicity, Socialism, and Politics, 1900-35 - Beaulieu, Michel S. (UBC Press, 2011)
In the early twentieth century, the Canadian Lakehead was known as a breeding ground for revolution, a place where harsh conditions in dockyards, lumber mills, and railway yards drove immigrants into radical labour politics. This intensely engaging history reasserts Northwestern Ontario's rightful reputation as a birthplace of leftism in Canada by exposing the conditions that gave rise to an array of left-wing organizations, including the Communist Party, the One Big Union, and the Industrial Workers of the World. Yet, as Michel Beaulieu shows, the circumstances and actions of Lakehead labour, especially those related to ideology, ethnicity, and personality were complex; they simultaneously empowered and fettered workers in their struggles against the shackles of capitalism. Cultural ties helped bring left-wing ideas to Canada but, as each group developed a distinctive vocabulary of socialism, Anglo-Celtic workers defended their privileges against Finns, Ukrainians, and Italians. At the Lakehead, ethnic difference often outweighed class solidarity - at the cost of a stronger labour movement for Canada. --Publisher's description
Keywords: 20th century; Ethnic relations; History; Labor movement; Labor unions; Ontario; Politics and government; Social conditions; Thunder Bay, Ont.

Retail Nation: Department Stores and the Making of Modern Canada - Belisle, Donica (UBC Press, 2011)
[This book] traces Canada's transformation into a modern consumer nation back to an era when Eaton’s, Simpson's, and the Hudson’s Bay Company fostered and came to rule the country’s shopping scene. Between 1890 and 1940, department stores revolutionized selling and shopping by parlaying cheap raw materials, business-friendly government policies, and growing demand for low-priced goods into retail empires that promised to meet citizens' needs and strengthen the nation. Some Canadians found happiness and fulfillment in their aisles; others experienced nothing more than a cold shoulder and a closed door. The stores' advertising and public relations campaigns often disguised a darker, more complicated reality that included strikes, union drives, customer complaints, government inquiries, and public criticism. This vivid account of Canadian department stores in their heyday showcases them as powerful agents of nationalism and modernization. But the nation that their catalogues and shopping experience helped to define - white, consumerist, middle-class - was more limited than nostalgic portraits of the early department store suggest. --Publisher's description. Contents: Rise of mass retail -- Creating modern Canada -- Fathers of mass merchandising -- Crafting the consumer workforce -- Shopping, pleasure, and power -- Working at the heart of consumption -- Criticizing the big stores. Includes bibliographical references (p. 274-292) and index.
Keywords: Consumption (Economics); Department stores; History; Retail trade

Canadian Labour in Crisis: Reinventing the Workers' Movement - Camfield, David (Fernwood Publishing, 2011)
Does Canada have a working-class movement? Though most of us think of ourselves as middle class, most of us are, in fact, part of the working class: we work for wages and are not managers. Although many of us are members of unions - the most significant organizations of the working-class movement in Canada - most people do not understand themselves to be part of this movement. Is the working-class movement a relic of the twentieth-century factory worker, no longer relevant to workers in the twenty-first century? David Camfield argues that, despite its real deficiencies, the movement is as important today as it was a hundred years ago. Drawing on the ideas of union and community activists as well as academic research, David Camfield offers an analysis of the contemporary Canadian working-class movement and how it came to be in its current state. he argues that re-energizing the movement in its current form is not enough - it needs to be reinvented to face the challenges of contemporary capitalism. Considering potential ways forward, Camfield asserts that reforming unions from below and building new workers' organizations offer the best possibilities for effecting real change within the movement. --Publisher's description
Keywords: Canada; Labor Unions; Labor movement; Political activity; Social conditions; Working class

The Ocean Ranger: Remaking the Promise of Oil - Dodd, Susan (Fernwood, 2011)
On February 15, 1982, the oil rig Ocean Ranger sank off the coast of Newfoundland taking the entire crew of eighty-four men – including the author’s brother – down with it. It was the worst sea disaster in Canada since the Second World War, but the memory of this event gradually faded into a sad story about a bad storm – relegated to the “Extreme Weather” section of the CBC archives. Susan Dodd resurrects this disaster from the realm of “history” and maps the socio-political processes of its aftermath, when power, money and collective hopes for the future revised the story of corporate indifference and betrayal of public trust into a “lesson learned” by an heroic industry advancing technology in the face of a brutal environment. This book is a navigational resource for other disaster aftermaths, including that of the Deepwater Horizon in the Gulf of Mexico, and a call for vigilant government regulation of industry in all its forms. --Publisher's description
Keywords: Ocean Ranger (Drilling rig)

The Shifting Landscape of Work - Duffy, Ann; Glenday, Daniel; Pupo, Norene (Nelson Education, 2011)
The Shifting Landscape of Work is a contributed text that explores contemporary issues pertaining to labour in the context of race, class, age, economics, and gender, presented from a left-of-center perspective. All of the contributors are well known and respected scholars in their field of research. The authors challenge students to think about the dynamics of the labour market, including the realities of unpaid work and the impact of structural shifts in societal power relations. --Publisher's description
Keywords: Canada; Industrial relations -- Canada -- Textbooks; Labor; Labor Canada Textbooks; Labor Social aspects; Labor Social aspects Textbooks; Textbooks; Travail Aspect social Manuels d'enseignement supérieur; Travail Canada Manuels d'enseignement supérieur

Workers Across the Americas: The Transnational Turn in Labor History - Fink, Leon (Oxford University Press, 2011)
The first major volume to place U.S.-centered labor history in a transnational focus, Workers Across the Americas collects the newest scholarship of Canadianist, Caribbeanist, and Latin American specialists as well as U.S. historians. These essays highlight both the supra- and sub-national aspect of selected topics without neglecting nation-states themselves as historical forces. Indeed, the transnational focus opens new avenues for understanding changes in the concepts, policies, and practice of states, their interactions with each other and their populations, and the ways in which the popular classes resist, react, and advance their interests. What does this transnational turn encompass? And what are its likely perils as well as promise as a framework for research and analysis? To address these questions John French, Julie Greene, Neville Kirk, Aviva Chomsky, Dirk Hoerder, and Vic Satzewich lead off the volume with critical commentaries on the project of transnational labor history. Their responses offer a tour of explanations, tensions, and cautions in the evolution of a new arena of research and writing. Thereafter, Workers Across the Americas groups fifteen research essays around themes of labor and empire, indigenous peoples and labor systems, international feminism and reproductive labor, labor recruitment and immigration control, transnational labor politics, and labor internationalism. Topics range from military labor in the British Empire to coffee workers on the Guatemalan/Mexican border to the role of the International Labor Organization in attempting to set common labor standards. Leading scholars introduce each section and recommend further reading. -- Publisher's description. "Associate editors, Eileen Boris, John D. French, Julie Greene, Joan Sangster, Shelton Stromquist." Contents: Another World history is possible: reflections on the translocal, transnational, and global / John D. French -- Historians of the world: transnational forces, nation-states, and the practice of U.S. history / Julie Greene -- Transnational labor history: promise and perils / Neville Kirk -- Labor history as world history: linking regions over time / Aviva Chomsky -- Overlapping spaces: transregional and transcultural / Dirk Hoerder -- Transnational migration: a new historical phenomenon? / Vic Satzewich -- "black service ... white money": the peculiar institution of military labor in the British Army during the Seven Years' War / Peter Way -- "We speak the same language in the new world:: capital, class, and community in Mexico's "American century" / Steven J. Bachelor -- Indigenous labor in mid-nineteenth-century British North America: the Mi'kmaq of Cape Breton and Squamish of British Columbia in comparative perspective / Andrew Parnaby -- "De facto Mexicans": coffee workers and nationality on the Guatemalan-Mexican border, 1913-1941 / Catherine Nolan-Ferrell -- "No right to layettes or nursing time": maternity leave and the question of U.S. exceptionalism / Eileen Boris -- The battle within the home: development strategies and the commodification of caring labors at the 1975 International Women's Year Conference / Jocelyn Olcott -- Feminizing white slavery in the United States: Marcus Braun and the transnational traffic in white bodies, 1890-1910 / Gunther Peck -- Patronage and progress: the Bracero program from the perspective of Mexico / Michael Snodgrass -- Unspoken exclusions: race, nation, and empire in the immigration restrictions of the 1920s in North America and the greater Caribbean / Lara Putnam -- Claiming political space: workers, municipal socialism, and the reconstruction of local democracy in transnational perspective / Shelton Stromquist -- A migrating revolution: Mexican political organizers and their rejection of American assimilation, 1920-1940 / John H. Flores -- Fugitive slaves across North America / Jeffrey R. Kerr-Ritchie -- Movable type: Toronto's transnational printers, 1866-1872 / Jacob Remes -- Global sea or national backwater? The International Labor Organization and the quixotic quest for maritime standards, 1919-1945 / Leon Fink.
Keywords: America; History. Transnationalism. Labor. Transnationalism. Genre/Form: History; Labor

Working People in Alberta: A History - Finkel, Alvin (Working Canadians: Books from the CCLH, 2011)
Working People in Alberta traces the history of labour in Alberta from the period of First Nations occupation to the present. Drawing on over two hundred interviews with labour leaders, activists, and ordinary working people, as well as on archival records, the volume gives voice to the people who have toiled in Alberta over the centuries. In so doing, it seeks to counter the view of Alberta as a one-class, one-party, one-ideology province, in which distinctions between those who work and those who own are irrelevant. Workers from across the generations tell another tale, of an ongoing collective struggle to improve their economic and social circumstances in the face of a dominant, exploitative elite. Their stories are set within a sequential analysis of provincial politics and economics, supplemented by chapters on women and the labour movement and on minority workers of colour and their quest for social justice. Published on the occasion of the 100th anniversary of the Alberta Federation of Labour, Working People in Alberta contrasts the stories of workers who were union members and those who were not. In its depictions of union organizing drives, strikes, and working-class life in cities and towns, this lavishly illustrated volume creates a composite portrait of the men and women who have worked to build and sustain the province of Alberta. --Publisher's description. Contents: Introduction : Those who built Alberta -- Millennia of Native work / Alvin Finkel -- The fur trade and early European settlement / Alvin Finkel -- One step forward : Alberta workers, 1885-1914 / Jim Selby -- War, repression, and depression, 1914-1939 / Eric Strikwerda and Alvin Finkel -- Alberta labour and working-class life, 1940-1959 / James Muir -- The boomers become the workers : Alberta, 1960-1980 / Alvin Finkel -- Alberta labour in the 1980s / Winston Gereluk -- Revolution, retrenchment, and the new normal : the 1990s and beyond / Jason Foster -- Women, labour, and the labour movement / Joan Schiebelbein -- Racialization and work / Jennifer Kelly and Dan Cui -- Conclusion : A history to build upon / Alvin Finkel.
Keywords: Alberta; Economic conditions; Economic policy; History; Labor; Working class

Beyond Bylines: Media Workers and Women's Rights in Canada - Freeman, Barbara M. (Film and media studies series, 2011)
[E]xplores the ways in which several of Canada’s women journalists, broadcasters, and other media workers reached well beyond the glory of their personal bylines to advocate for the most controversial women’s rights of their eras. To do so, some of them adopted conventional feminine identities, while others refused to conform altogether, openly and defiantly challenging the gender expectations of their day. The book consists of a series of case studies of the women in question as they grappled with the concerns close to their hearts: higher education for women, healthy dress reforms, the vote, equal opportunities at work, abortion, lesbianism, and Aboriginal women’s rights. Their media reflected their respective eras: intellectual magazines, daily and weekly newspapers, radio, feminist public relations, alternative women’s periodicals, and documentary film made for television. --Publisher's description
Keywords: History; Press coverage; Women in mass media; Women in the mass media industry; Women's rights

Industrial Relations, the Economy, and Society - Godard, John (Captus Press, 2011)
A leading textbook in industrial relations at the university level, this book is valuable both as a primary and as a supplementary text for students of industrial relations, sociology, labour studies, economics and management programs. The book contains highly accessible coverage of conventional topic areas, including the history of industrial relations, contemporary employer practices, labour unions, labour law, collective bargaining, and contract administration. Yet it also includes coverage of broader economic and social issues relevant to the study of labour and employment relations in both the union and non-union sectors. Readers are thus able not only to develop a strong practical knowledge of Canadian industrial relations, but also to ground this knowledge in a deeper understanding of these relations and the broader issues and debates that surround them. This latest edition incorporates up-to-date statistics relevant to the study of industrial relations (e.g., strike activity, union membership, income inequality) as well as recent developments in the literature. It also streamlines the previous edition. The chapters on management practices and the effects of high performance practices have been merged and edited down, as have the chapters on contemporary developments and contemporary alternatives. --Publisher's description. Contents: Foundations: concepts, issues, and debates -- The broader debate: three theses on the nature and development of industrial relations, the economy, and society -- Understanding labour-management relations -- Work and industrial relations in historical perspective -- Contemporary management practices -- Understanding and explaining management -- Labour unions as institutions -- Labour unions as organizations -- The role of the state -- Understanding the state -- Labour law: the regulation of labour-management relations -- Collective bargaining: structure, process, and outcomes -- Strikes and dispute resolution -- The grievance and grievance arbitration processes -- The collective agreement: content and issues -- Contemporary problems, challenges, and alternatives. Includes bibliographical references (p. [431]-452) and index.
Keywords: Canada; Industrial relations

About Canada: Immigration - Gogia, Nupur; Slade, Bonnie (About Canada, 2011)
Many Canadians believe that immigrants steal jobs away from qualified Canadians, abuse the healthcare system and refuse to participate in Canadian culture. In About Canada: Immigration, Gogia and Slade challenge these myths with a thorough investigation of the realities of immigrating to Canada. Examining historical immigration policies, the authors note that these policies were always fundamentally racist, favouring whites, unless hard labourers were needed. Although current policies are no longer explicitly racist, they do continue to favour certain kinds of applicants. Many recent immigrants to Canada are highly trained and educated professionals, and yet few of them, contrary to the myth, find work in their area of expertise. Despite the fact that these experts could contribute significantly to Canadian society, deeply ingrained racism, suspicion and fear keep immigrants out of these jobs. On the other hand, Canada also requires construction workers, nannies and agricultural workers — but few immigrants who do this work qualify for citizenship. About Canada: Immigration argues that we need to move beyond the myths and build an immigration policy that meets the needs of Canadian society. --Publisher's description. Contents: Introduction -- Immigration: a critical analysis -- Evolution of immigration policy: learning about the past to understand the present -- Immigration policy and practices: the mechanics of migration -- Immigrants and the labour market: devaluation, frustration and downward mobility -- Reception party: the settlement process for immigrants -- Revolving door: temporary workers in Canada -- Under the surface: Canada's hidden labour force -- Coming to a better place? Not always a happy ending.
Keywords: 21st century; Canada; Economic conditions; Emigration and immigration Government policy History; Immigrants

Militant Minority: British Columbia Workers and the Rise of a New Left, 1948-1972 - Isitt, Benjamin (University of Toronto Press, Scholarly Publishing Division, 2011)
[This book] tells the compelling story of British Columbia workers who sustained a left tradition during the bleakest days of the Cold War. Through their continuing activism on issues from the politics of timber licenses to global questions of war and peace, these workers bridged the transition from an Old to a New Left.In the late 1950s, half of B.C.'s workers belonged to unions, but the promise of postwar collective bargaining spawned disillusionment tied to inflation and automation. A new working class that was educated, white collar, and increasingly rebellious shifted the locus of activism from the Communist Party and Co-operative Commonwealth Federation to the newly formed New Democratic Party, which was elected in 1972. Grounded in archival research and oral history, Militant Minority provides a valuable case study of one of the most organized and independent working classes in North America, during a period of ideological tension and unprecedented material advance. --Publisher's description
Keywords: 20th century; British columbia; History; New Left; Political activity; Working class

Through Feminist Eyes: Essays on Canadian Women's History - Joan Sangster (AU Press, 2011)
Through Feminist Eyes gathers in one volume the most incisive and insightful essays written to date by the distinguished Canadian historian Joan Sangster. To the original essays, Sangster has added reflective introductory discussions that situate her earlier work in the context of developing theory and debate. Sangster has also supplied an introduction to the collection in which she reflects on the themes and theoretical orientations that have shaped the writing of women's history over the past thirty years. Approaching her subject matter from an array of interpretive frameworks that engage questions of gender, class, colonialism, politics, and labour, Sangster explores the lived experience of women in a variety of specific historical settings. In so doing, she sheds new light on issues that have sparked much debate among feminist historians and offers a thoughtful overview of the evolution of women's history in Canada. --Publisher's description. Contents: Introduction: Reflections on Thirty Years of Women’s History -- Discovering Women’s History == The 1907 Bell Telephone Strike: Organizing Women Workers -- Looking Backwards: Re-assessing Women on the Canadian Left == The Communist Party and the Woman Question, 1922-1929 -- Manufacturing Consent in Peterborough -- The Softball Solution: Female Workers, Male Managers, and the Operation of Paternalism at Westclox, 1923–1960 -- Pardon Tales’ from Magistrate’s Court: Women, Crime, and the Court in Peterborough County, 1920–1950 --Telling Our Stories: Feminist Debates and the Use of Oral History -- Foucault, Feminism, and Postcolonialism -- Girls in Conflict with the Law: Exploring the Construction of Female ‘Delinquency’ in Ontario, 1940–1960 -- Criminalizing the Colonized: Ontario Native Women Confront the Criminal Justice System, 1920–1960 -- Constructing the ‘Eskimo’ Wife: White Women’s Travel Writing, Colonialism, and the Canadian North, 1940–1960 -- Embodied Experience -- Words of Experience/Experiencing Words: Reading Working Women’s Letters to Canada’s Royal Commission on the Status of Women -- Making a Fur Coat: Women, the Labouring Body, and Working-class History.
Keywords: Women

Along the No. 20 Line: Reminiscences of the Vancouver Waterfront - Knight, Rolf (New Star Books, 2011)
In Along the No. 20 Line, Rolf Knight takes the reader on a tour through working-class East Vancouver of a century ago. Knight's "through-line" is literally a line: the old No. 20 streetcar route that ran between downtown Vancouver and the present-day neighbourhood of the Pacific National Exhibition. From 1892 to 1949, when it was shut down and replaced by the No. 20 Granville / Victoria Drive bus, the No. 20 streetcar carried thousands of Vancouverites back and forth between their East Van homes and their jobs on the docks, and in the mills, factories, and workshops along the No. 20 line. --Publisher's description

Working Without Commitments: The Health Effects of Precarious Employment - Lewchuk, Wayne; Clarke, Marlea; De Wolff, Alice (McGill-Queen's University Press, 2011)
From the end of the Second World War to the early 1980s, the North American norm was that men had full-time jobs, earned a "family wage," and expected to stay with the same employer for life. In households with children, most women were unpaid caregivers. This situation began to change in the mid-1970s as two-earner households became commonplace, with women entering employment through temporary and part-time jobs. Since the 1980s, less permanent precarious employment has increasingly become the norm for all workers. Working Without Commitments offers a new understanding of the social and health impacts of this change in the modern workplace, where outsourcing, limited term contracts, and the elimination of pensions and health benefits have become the new standard. Using information from interviews and surveys with workers in less permanent employment, the authors show how precarious employment affects the health of workers, labour productivity, and the sustainability of the traditional family model. --Publisher's description. Contents: Working without commitments: employment relationships and health -- A short history of the employment relationship: control, effort, and support -- Working without commitments and the characteristics of the employment relationship -- Gender, race, and the characteristics of the employment relationship -- The employment strain model and the health effects of less permanent employment -- The blurred lines between precariousness and permanence -- Sustainable, less permanent employment -- "On a path" to employment security? -- Unsustainable, less permanent employment -- Creating commitments in less permanent employment: policy reforms to address rising insecurity.
Keywords: Health aspects; Job stress; Precarious Employment; Social aspects

Manufacturing Meltdown: Reshaping Steel Work - Livingstone, D. W. (David W.); Smith, Dorothy E.; Smith, Warren (Fernwood, 2011)
In the 1980s, following decades of booming business, the global steel industry went into a precipitous decline, which necessitated significant restructuring. Management demanded workers' increased participation in evermore temporary and insecure labour. Engaging the workers at the flagship Stelco plant in Hamilton, the authors document new management strategies and the responses of unionized workforces to them. These investigations provide valuable insights into the dramatic changes occurring within the Canadian steel industry. --Publisher's description
Keywords: Acier Industrie et commerce Canada; Acier Industrie et commerce Gestion Participation du personnel Canada; Canada; Iron and steel workers Labor unions; Iron and steel workers Labor unions Canada; Management; Steel industry and trade; Steel industry and trade Canada; Steel industry and trade Management Employee participation; Steel industry and trade Management Employee participation Canada; Stelco Inc. Management; Stelco inc. Gestion; Travailleurs du fer et de l'acier Syndicats Canada

Industrial Relations in Canada - McQuarrie, Fiona A. E. (Wiley, 2011)
{This textbook] received wide praise for helping students to understand the complex and sometimes controversial field of Industrial Relations, by using just the right blend of practice, process and theory.  The text engages business students with diverse backgrounds and teaches them how an understanding of this field will help them become better managers.The third edition retains this student friendly, easy-to-read approach, praised by both students and instructors across the country. The goal of the third edition was to enhance and refine this approach while updating the latest research findings and developments in the field. --Publisher's description
Keywords: Canada; Industrial relations

Onion Man - Mockler, Kathryn (Tightrope Books, 2011)
In the late 1980s of London, Ontario—a time in Canada when the recession lay like a lead weight on the shoulders of young people, leaving the future bleak—an eighteen-year-old girl is working for the summer at a corn canning factory. Her story is told through a series of masterfully-sculpted linked poems, following her relationship with her boyfriend, her alcoholic mother, her terminally-ill grandfather, the factory job, and the man who every night “peels an onion and eats it as if it were an apple.” The Onion Man doesn’t speak English and is tormented by the other workers, and ater his son dies, he commits suicide at the factory. The girl finds his body and the traumatic event prompts her to rethink the direction of her life. -- Publisher's description
Keywords: Englisch; Lyrik; Poetry; Poésie; poetry

Our Union: UAW/CAW Local 27 from 1950-1990 - Russell, Jason (Fabriks: Studies in the working class, 2011)
[The author] argues that the union local, as an institution of working-class organization, was a key agent for the Canadian working class as it sought to create a new place for itself in the decades following World War II. Using UAW/CAW Local 27, a broad-based union in London, Ontario, as a case study, he offers a ground-level look at union membership, including some of the social and political agendas that informed union activities. As he writes in the introduction, "This book is as much an outgrowth of years of rank-and-file union activism as it is the result of academic curiosity." Drawing on interviews with former members of UAW/CAW Local 27 as well as on archival sources, Russell offers a narrative that will speak not only to labour historians but to the people about whom they write. --Publisher's description
Keywords: Automobile industry workers; History; Labor Unions; Labor union locals; Social aspects

Racism in Canada - Satzewich, Vic (Issues in Canada, 2011)
There are widely divergent views about racism in Canada. Some believe that racism is a fundamental feature of Canadian society and national identity. This dystopian view of Canada as a fundamentally and irrevocably racist society carries considerable currency in some academic and activist circles. Others argue that racism is oversold as a social problem: while pockets of racism do exist, Canada remains a fundamentally fair place for people of diverse backgrounds to prosper and flourish.Vic Satzewich's short and accessible book explores how racism operates in Canadian society, past and present. Racism is a complex aspect of Canadian society; while it may not be an inherent and invariant feature of our country, it is also more prevalent than many people may realize. The book examines a variety of issues including racism and the immigration system, racial profiling, racism and First Nations and Islamophobia. It concludes with a discussion of some of the dilemmas and challenges associated with anti-racism theory and practice. --Publisher's description
Keywords: 1991-; CULTURAL pluralism; Canada; Race relations; Racism; Racisme; Relations raciales; Social conditions

Working in a Global Era: Canadian Perspectives - Shalla, Vivian (Canadian Scholars' Press, 2011)
Now in its second edition, this reader presents a critical examination of the changing structure of work in Canada and abroad. Its focus is on the role of Canadian labour in the globalized world. Contributors include David Livingstone, Pat Armstrong, Meg Luxton, Dave Broad, and other prominent Canadian scholars. Each of the seven themed sections begins with a contextual introduction by Vivian Shalla and concludes with critical thinking questions and suggestions for further reading. --Publisher's description.
Keywords: Economic aspects; Globalization; Labor; Labor movement

Champagne and Meatballs: Adventures of a Canadian Communist - Whyte, Bert; Hannant, Larry (Working Canadians: Books from the CCLH, 2011)
Active for over forty years with the Communist Party of Canada, Bert Whyte was a journalist, an underground party organizer and soldier during World War II, and a press correspondent in Beijing and Moscow. But any notion of him as a Communist party hack would be mistaken. Whyte never let leftist ideology get in the way of a great yarn. In Champagne and Meatballs — a memoir written not long before his death in Moscow in 1984 — we meet a cigar-smoking rogue who was at least as happy at a pool hall as at a political meeting. His stories of bumming across Canada in the 1930s, of combat and camaraderie at the front lines in World War II, and of surviving as a dissident in troubled times make for compelling reading. The manuscript of Champagne and Meatballs was brought to light and edited by historian Larry Hannant, who has written a fascinating and thought-provoking introduction to the text. Brash, irreverent, informative, and entertaining, Whyte's tale is history and biography accompanied by a wink of his eye — the left one, of course. --Publisher's description
Keywords: Canada; Communist Party of Canada; Communistes; Communists; Journalistes; Journalists; Militaires; Parti communiste canadien; Soldiers; WHYTE, Bert

One Day Longer: A Memoir - Williams, Lynn (Lynn Russell) (University of Toronto Press, 2011)
Lynn Williams remains one of the most influential North American union leaders of the twentieth century. His two terms as president of the United Steelworkers of America, from 1983 until 1994, capped off a career in labour relations spanning nearly five decades. Among his many notable achievements were the new bargaining techniques he developed to face challenges from anti-union politicians such as Ronald Reagan and Margaret Thatcher. Williams also played a major role in the structural readjustment of the North American steel industry during its most turbulent period, the 1980s and 1990s. In his memoirs, Williams vividly recounts his life in labour, with all its triumphs, challenges, hopes, and dreams. While telling his own story, Williams also traces the rise and transformation of the labour movement from the Second World War to today. Providing an insider's perspective on union developments and issues, One Day Longer is a profound reflection of Williams's impressive career. --Publisher's description. Contents: In the beginning -- War and peace -- The Eaton drive -- Joining the Steelworkers -- Back east -- Organizing -- Sudbury -- Director, District 6 -- On to Pittsburgh -- Assuming the presidency -- Trying times -- Union work and politics -- New directions -- Epilogue.
Keywords: 20th century; Autobiography; History; Labor movement; Labor union members; North America; Presidents; United Steelworkers of America; Williams, Lynn (Lynn Russell), 1924-2014

The Double Ghetto: Canadian Women and Their Segregated Work - Armstrong, Pat (Oxford University Press, 2010)
Named by members of the Canadian Sociology and Anthropology Association as one of the most important works of Canadian sociology of the twentieth century, The Double Ghetto is a classic study of the segregated nature of women's work - and women's lives. Writing in the Canadian Journal of Sociology, Maureen Baker declared the book "a valuable contribution" when it first appeared. Today's working women find that while much has changed during the past three decades, all too many things remain the same. The Double Ghetto remains not only a landmark of Canadian sociology, but a disturbingly relevant examination of the challenges facing women in the workplace. --Publisher's description
Keywords: Women -- Employment -- Canada

The Political Economy of Workplace Injury in Canada - Barnetson, Bob (Fabriks: Studies in the working class, 2010)
Labour relations scholar Bob Barnetson sheds light on the faulty system of workplace injury compensation, highlighting the way some employers create dangerous work environments yet invest billions of dollars into compensation and treatment.
Keywords: Accidents; Costs; Economic aspects; Industrial accidents; Industrial hygiene; Industrial safety; Occupational diseases; Political aspects; Workers' compensation

Northern Exposures: A Canadian Perspective on Occupational Health and Environment - Bennett, David (Work, health, and environment series, 2010)
David Bennett is the retired National Director of Health, Safety and Environment of the Canadian Labour Congress and the Book Review Editor of the journal New Solutions. Northern Exposures is the result of thirty years of work in the labor movement on workplace health and safety and environmental protection. In the 1990s, the author had a central responsibility in moving the Canadian Labour Congress from its established work in health and safety into environmental protection, a story detailed in Northern Exposures. The book is a collection of published articles and reviews, linked by a new Introduction that shows the development of the thinking and actions of the Canadian labor movement in areas that were in constant flux. --Publisher's description. Contents: The right to know about chemical hazards in Canada,1982-2006 -- Labour and the environment at the Canadian Labour Congress: the story of the convergence -- Occupational health: a discipline out of focus -- Pesticide reduction: a case study from Canada -- The Canadian Labour Congress' pollution prevention strategy -- Prevention and transition -- Cancer battles and the sleep of reason policy and science need not be related: review -- Book about cancer: pragmatic purpose, profound analysis: reviews -- The secret history of the war on cancer: review -- Industrial materials: a guidebook for the future: review -- 'Natural capitalism's' bold theory: review -- Beware ISO -- ISO and the WTO: a report to the International Confederation of Free Trade Unions' Working Party on Health, Safety, and Environment -- Health and safety management systems: liability or asset?
Keywords: Canada; Environmental health; Industrial hygiene; Occupational health and safety; Public Policy

Rose Henderson: A Woman for the People - Campbell, J. Peter (McGill-Queen's University Press, 2010)
Feminism and the political left come to life in this account of an important early twentieth-century social activist. The political movements and social causes of the turbulent 1920s and 30s are brought to life in this study of the work and times of feminist, socialist, and peace activist Rose Henderson (1871-1937). Her commitment to social justice led to frequent monitoring and repression by the authorities but her contributions to activist thought continue to pose challenges for interpretations of the history of Canada, leftism, labour, and women. In the first biography of Henderson, Peter Campbell provides a broader vision and deeper analysis of the period, drawing together the history of labour and of women's movements in French and English Canada, as well as the rise of the Cooperative Commonwealth Federation and its relationship with the Communist Party. Through analysis of Henderson's ground-breaking ideology Campbell shows that in the interwar years she and her comrades developed a distinctive feminism that differs from that of the first and second waves of feminist thought. A fresh look at the turmoil of the early twentieth century from an eye in the storm, Rose Henderson: A Woman for the People brings well-deserved attention to an influential feminist and leftist. --Publisher's description.

NAFTA and Labor in North America - Caulfield, Norman (University of Illinois Press, 2010)
A cogent analysis of North American trade unions' precipitous decline in recent decades. As companies increasingly look to the global market for capital, cheaper commodities and labor, and lower production costs, the impact on Mexican and American workers and labor unions is significant. National boundaries and the laws of governments that regulate social relations between laborers and management are less relevant in the era of globalization, rendering ineffective the traditional union strategies of pressuring the state for reform. Focusing especially on the effects of the North American Free Trade Agreement and the North American Agreement on Labor Cooperation (the first international labor agreement linked to an international trade agreement), Norman Caulfield notes the waning political influence of trade unions and their disunity and divergence on crucial issues such as labor migration and workers' rights. Comparing the labor movement's fortunes in the 1970s with its current weakened condition, Caulfield notes the parallel decline in the United States' hegemonic influence in an increasingly globalized economy. As a result, organized labor has been transformed from organizations that once pressured management and the state for concessions to organizations that now request that workers concede wages, pensions, and health benefits to remain competitive in the global marketplace. --Publisher's description. Contents: Labor and global capitalism in North America, 1850-1970 -- The politics of Mexican labor and economic development in crisis -- Mexican labor and workers' rights under NAFTA and NAALC -- Labor mobility and workers' rights in North America -- The crisis of union-management relations in the United States and Canada -- The North American auto industry: the apex of concessionary bargaining -- Veba Las Vegas! unions play casino capitalism : autoworkers lose.
Keywords: Industrial relations; Labor

More Than It Seems: Household Work and Lifelong Learning - Eichler, Margrit; Gouthro, Patricia; Albanese, Patrizia; Matthews, Ann; Liu, Lichun Willa; Ferguson, Susan; Hyndman, Nicky; Livingstone, D. W. (David W.); Spracklin, Kathryn (Women's Press, 2010)
Household work is an essential part of many people's lives, yet all too often it is rendered invisible. More Than It Seems aims not only to make this vitally important work visible, but also to reconsider it as a source of learning. Drawing on a large study conducted in Canada, the authors consider diverse forms of household work, including carework. They highlight the experiences of people at the margins — including immigrants, Aboriginal women, people with disabilities, nannies, and people who provide and receive care — and analyze those experiences through the prism of lifelong learning theory. The result is a pioneering work that challenges our assumptions about both household work and lifelong learning. -- Publisher's description. Contents: Foreword / Patricia Gouthro -- Introduction: More Than It Seems: Household Work and Lifelong Learning / Patrizia Albanese -- What Is Housework? / Margrit Eichler -- Learning through Household Work / Margrit Eichler with Ann Matthews -- Portrait: Dorica -- Encounters with the Self: Disability and the Many Dimensions of Self-Care / Ann Matthews -- Portrait: Fang -- "Have You Had Your Meal Yet?": Chinese Immigrants, Food-related Household Work and Informal Learning / Lichun Willa Liu -- Portrait: Mithreal -- Choreographing Care: Learning through Unpaid Carework / Susan Ferguson and Margrit Eichler -- Portrait: Dee -- The Case of Nannies: Shifting Unpaid Work onto Paid Work / Nicky Hyndman -- Conclusions / Patrizia Albanese -- Appendix 1: Methodological Overview / Ann Matthews -- Appendix 2: The WALL Project / D.W. Livingston -- Appendix 3: Mothers Are Women (MAW) / Kathryn Spracklin.
Keywords: Adult learning; Canada; Caregivers; Households; Housekeeping; Social aspects

Seeing Reds: The Red Scare of 1918-1919, Canada's First War on Terror - Francis, Daniel (Arsenal Pulp Press, 2010)
At the end of World War I, Canada was poised on the brink of social revolution. At least that is what many Canadians, inspired by the success of the Russian Revolution in 1917, hoped and others dreaded. Seeing Reds tells the story of this turbulent period in Canadian history during the winter of 1918-19, when a fearful government led by Prime Minister Robert Borden tried to suppress radical political activity by branding legitimate labour leaders as "Bolsheviks" and "Reds." Canada was in the grip of a widespread Red Scare promoted by the government and the media in order to discredit radical ideas and to rally public support behind mainstream political and economic policies. The story builds toward the events of the Winnipeg General Strike in May-June 1919 when the authorities, believing that the expected revolution had begun, sent soldiers into the streets to put down with force a legitimate labour dispute. Author Daniel Francis examines Canada's Red Scare in a global context, including government responses to similar activities in the United States and western Europe, as well as its ramifications for the contemporary war on terror, in which issues of free speech and political dissent are similarly compromised in the name of national security. Based on government documents and first-hand accounts by the participants themselves, Seeing Reds is a gripping account of a little known episode in Canadian history. --Publisher's description.
Keywords: Anti-communist movements; Anticommunisme; General Strike, Winnipeg, Man., 1919; Grève générale, Winnipeg, Man., 1919; Histoire; History; Influence

Labour Landmarks in New Brunswick = Lieux historiques ouvriers au Nouveau-Brunswick - Frank, David; Canadian Committee on Labour History; Labour History in New Brunswick Project.; Lang, Nicole (Canadian Committee on Labour History = Comité canadien sur l'histoire du travail, 2010)
An original adventure in public history — a tour of 50 sites where families, workers, unions and communities have recognized the place of workers in 20th-century New Brunswick history. Ten short chapters, with explanatory notes, illustrations and a map. // Une aventure originale en histoire publique — une tournée de 50 lieux où des familles, des travailleuses et des travailleurs, des syndicats et des communautés ont reconnu la place des travailleuses et des travailleurs dans l’histoire du Nouveau-Brunswick du 20e siècle. Dix courts chapitres, des notes explicatives, des illustrations et une carte. --Publisher's description
Keywords: Guidebooks; Historical markers; History; Labor; Labor movement; New Brunswick; Workers' monuments; Working class

Work on Trial: Canadian Labour Law Struggles - Fudge, Judy; Tucker, Eric (Irwin Law, 2010)
Work on Trial is a collection of studies of eleven major cases and events that have helped to shape the legal landscape of work in Canada. While most of the cases are well-known because of the impact they have had on collective bargaining, individual employment law, or human rights, less is known about the social and political contexts in which the cases arose, the backgrounds and personalities of the judges and the litigants, the legal manoeuvres that were employed, or the ultimate fate of all those who were involved. These studies, written by some of Canada's leading labour and legal historians, provide this context. Beginning with Toronto Electric Commissioners v. Snider, one of the earliest and most important cases involving the division of powers in the Canadian federation, to the events leading to the articulation of the "Rand Formula" in the immediate post Second World War period, and on to the struggles of women workers in the late 20th century in challenging the continu-ing employment practices based on hegemonic gender-based assumptions, each study tells a compelling story, rich in detail and full of perceptive insights into the complex relationship between law and work. -- Publisher's description.
Keywords: Labor laws and legislation

One Hundred Years of Social Work: A History of the Profession in English Canada, 1900-2000 - Jennissen, Therese; Lundy, Colleen (Wilfrid Laurier University Press, 2010)
One Hundred Years of Social Work is the first comprehensive history of social work as a profession in English Canada. Organized chronologically, it provides a critical and compelling look at the internal struggles and debates in the social work profession over the course of a century and investigates the responses of social workers to several important events. A central theme in the book is the long-standing struggle of the professional association (the Canadian Association of Social Workers) and individual social workers to reconcile advancement of professional status with the promotion social action. The book chronicles the early history of the secularization and professionalization of social work and examines social workers roles during both world wars, the Depression, and in the era of postwar reconstruction. It includes sections on civil defence, the Cold War, unionization, social work education, regulation of the profession, and other key developments up to the end of the twentieth century. Drawing on extensive archival research as well as personal interviews and secondary literature, the authors provide strong academic evidence of a profession that has endured many important changes and continues to advocate for a just society and a responsive social welfare state. --Publisher's description
Keywords: History; Social service

When the State Trembled: How A.J. Andrews and the Citizens' Committee Broke the Winnipeg General Strike - Kramer, Reinhold; Mitchell, Tom (Canadian social history series, 2010)
The Winnipeg General Strike of 1919, which involved approximately 30,000 workers, is Canada's best-known strike. When the State Trembled recovers the hitherto untold story of the Citizens' Committee of 1000, formed by Winnipeg's business elite in order to crush the revolt and sustain the status quo. This account, by the authors of the award-winning Walk Towards the Gallows, reveals that the Citizens drew upon and extended a wide repertoire of anti-labour tactics to undermine working-class unity, battle for the hearts and minds of the middle class, and stigmatize the general strike as a criminal action. Newly discovered correspondence between leading Citizen lawyer A.J. Andrews and Acting Minister of Justice Arthur Meighen illuminates the strategizing and cooperation that took place between the state and the Citizens. While the strike's break was a crushing defeat for the labour movement, the later prosecution of its leaders on charges of sedition reveals abiding fears of radicalism and continuing struggles between capital and labour on the terrain of politics and law. --Publisher's description. Contents: Permitted by Authority of the Strike Committee -- Who? Who? Who-oo? -- Seven Hundred and Four Years Ago at Runnymede -- The Anointing of A.J. Andrews -- The Flag-Flapping Stage -- To Reach the Leaders in this Revolutionary Movement -- Time to Act -- Enough Evidence to Convict the Whole Strike Committee -- The Road through Bloody Saturday -- The Only Way to Deal with Bolshevism -- They are all dangerous: Immigration Hearings -- They Started the Fire: Preliminary Hearing -- Poor Harry Daskaluk -- Duty to God, Country, and Family: The Russell Trial.
Keywords: General Strike, Winnipeg, Man., 1919; History

Making and Breaking the Rules: Women in Quebec, 1919-1939 - Levesque, Andrée (Canadian social history series, 2010)
During the interwar period, Quebec was a strongly patriarchal society, where men in the Church, politics, and medicine, maintained a traditional norm of social and sexual standards that women were expected to abide by. Some women in the media and religious communities were complicit with this vision, upholding the "ideal" as the norm and tending to those "deviants" who failed to meet society's expectations. By examining the underside of a staid and repressive society, Andrée Lévesque reveals an alternate and more accurate history of women and sexual politics in early twentieth-century Quebec. Women, mainly of the working class, left traces in the historical record of their transgressions from the norm, including the rejection of motherhood (e.g., abortion, abandonment, infanticide), pregnancy and birth outside of marriage, and prostitution. Professor Lévesque concludes, "They were deviant, but only in relation to a norm upheld to stave off a modernism that threatened to swallow up a Quebec based on long-established social and sexual roles. --Publisher's description --T.p. verso; Includes bibliographical references and index
Keywords: Women -- Quebec (Province) -- Sexual behavior -- History -- 20th century

Live Working or Die Fighting: How the Working Class Went Global - Mason, Paul (Haymarket Books, 2010)
Globalization has created a whole new working class - and they are reliving stories that were first played out a century ago. In Live Working or Die Fighting, Paul Mason tells the story of this new working class alongside the epic history of the global labour movement, from its formation in the factories of the 1800s through its near destruction by fascism in the 1930s and up to today's anti-globalisation movement. Blending exhilarating historical narrative with reportage from today's front line, he links the lives of 19th-century factory girls with the lives of teenagers in a giant Chinese mobile phone factory; he tells the story of how mass trade unions were born in London's Docklands - and how they're being reinvented by the migrant cleaners in skyscrapers that stand on the very same spot. It is a story of urban slums, self-help co-operatives, choirs and brass bands, free love and self-education by candlelight. And, as the author shows, in the developing industrial economies of the world it is still with us. Live Working or Die Fighting celebrates a common history of defiance, idealism and self-sacrifice, one as alive and active today as it was two hundred years ago. --Publisher's description
Keywords: Employee rights; Foreign workers; History; Labor movement; Working class

North of the Color Line: Migration and Black Resistance in Canada, 1870-1955 - Mathieu, Sarah-Jane (The John Hope Franklin series in African American history and culture; Variation: John Hope Franklin series in African American history and culture., 2010)
This book examines life in Canada for the estimated 5,000 blacks, both African Americans and West Indians, who immigrated to Canada after the end of Reconstruction in the United States. Through the experiences of black railway workers and their union, the Order of Sleeping Car Porters, the author connects social, political, labor, immigration, and black diaspora history during the Jim Crow era. By World War I, sleeping car portering had become the exclusive province of black men. White railwaymen protested the presence of the black workers and insisted on a segregated workforce. Using the first-hand accounts of former sleeping car porters, the author shows that porters often found themselves leading racial uplift organizations, galvanizing their communities, and becoming the bedrock of civil rights activism. Examining the spread of segregation laws and practices in Canada, whose citizens often imagined themselves as devoid of racism, she historicizes Canadian racial attitudes and explores how black migrants brought their own sensibilities about race to Canada, participating in and changing political discourse there. --Publisher's description
Keywords: Blacks; Canada; Canada. Blacks; History. African Americans; History. Immigrants; History. West Indians; Social conditions. African Americans; Social conditions. African Americans. African Americans; Social conditions. Blacks. Blacks; Social conditions. Genre/Form: History; Social conditions. Immigrants. Race relations. West Indians. West Indians; Social conditions. West Indians

Fort Chipewyan and the Shaping of Canadian History, 1788-1920s: "We Like to Be Free in This Country" - McCormack, Patricia Alice (UBC Press, 2010)
The story of the expansion of European civilization into the wilderness continues to shape perceptions of how Aboriginal people became part of nations such as Canada. This groundbreaking study subverts this narrative of progress and modernity by examining Canadian nation building from the perspective of a northern community and its residents. Drawing on decades of research and fieldwork, Patricia McCormack argues that Fort Chipewyan--established in 1788 and situated in present-day Alberta--was never an isolated Aboriginal community but a plural society that stood at the crossroads of global, national, and indigenous cultures and economies. The steps that led Aboriginal people to sign Treaty No. 8 and accept scrip in 1899 and their struggle to maintain autonomy in the decades that followed reveal that Aboriginal peoples and others can - and have - become modern without relinquishing cherished beliefs and practices. --Publisher's description. Contents: Writing Fort Chipewyan history -- Building a plural society at Fort Chipewyan: a cultural Rababou -- The fur trade mode of production -- The creation of Canada: a new plan for the Northwest -- Local impacts: state expansion, the Athabasca District, and Fort Chipewyan -- Christian missions -- The ways of life at Fort Chipewyan: cultural baselines at the time of treaty -- Treaty no. 8 and the Métis script: Canada bargains for the North -- The government foot in the door -- Fort Chipewyan and the new regime -- Epilogue: Facing the future -- Appendix: Personal testimony from Fort Chipewyan residents and related persons: memoirs and interviews.
Keywords: Alberta; Alberta, Northern; Canada; Commerce; Fort Chipewyan; Government relations. Fur trade. Indians of North America. Indigenous peoples. Indigenous peoples; Government relations. Native peoples; Histoire. Autochtones; Histoire. Genre/Form: History; History. Fur trade; History. Indigenous peoples; Indians of North America

La signification du travail: nouveau modèle productif et ethos du travail au Québec - Mercure, Daniel; Vultur, Mircea (Collection Sociologie contemporaine, 2010)
Ce livre dresse un portait pénétrant de la complexité des valeurs, des attitudes et des croyances relatives au travail de la population active québécoise. Quelle importance et quelle signification revêt le travail aujourd’hui ? Le travail est-il de plus en plus un lieu de réalisation de soi ou n’est-il qu’une valeur en perdition, voire un simple moyen en vue de financer la vie à l’extérieur du travail ? Quel est le modèle de travail idéal auquel aspirent les travailleurs et quelles sont leurs attitudes envers les nouvelles normes et pratiques de gestion mises de l’avant par les employeurs au cours des deux dernières décennies ? Plus fondamentalement, de quelle manière l’identité personnelle est-elle reliée ou dissociée du rôle professionnel ? Issu d’une vaste enquête auprès d’un millier de travailleurs québécois, ce livre montre que le travail est toujours une valeur importante, mais que la réalisation de soi et la quête d’équilibre entre la vie privée et la vie professionnelle sont des aspirations de plus en plus partagées par les individus. Les grands schèmes de valeurs et d’attitudes par rapport au travail mis au jour dans l’ouvrage témoignent de changements culturels récents ainsi que de la diversité des situations de travail vécues. À des degrés divers, ces schèmes convergent vers les exigences du modèle productif contemporain ou s’en distancient : ils contribuent à l’émergence d’un nouveau monde du travail. Cet ouvrage a été réalisé par une équipe de recherche de l’Université Laval et de l’Institut national de la recherche scientifique, sous la direction de Daniel Mercure et de Mircea Vultur, avec la collaboration de Marie-Pierre Bourdages-Sylvain, Charles Fleury et Lilian Negura. --Publisher's description
Keywords: Industrial sociology; Industrial sociology Québec (Province); Quality of work life; Quality of work life Québec (Province); Qualité de la vie au travail Enquêtes Québec (Province); Qualité de la vie au travail Québec (Province); Québec; Sociologie industrielle Enquêtes Québec (Province); Sociologie industrielle Québec (Province); Travail et familles Enquêtes Québec (Province); Travail et familles Québec (Province); Work and family; Work and family Québec (Province)

The Empire Within: Postcolonial Thought and Political Activism in Sixties Montreal - Mills, Sean (Studies on the history of Quebec, 2010)
In a brilliant history of a turbulent time and place, Mills pulls back the curtain on the decade's activists and intellectuals, showing their engagement both with each other and with people from around the world. He demonstrates how activists of different backgrounds and with different political aims drew on ideas of decolonization to rethink the meanings attached to the politics of sex, race, and class and to imagine themselves as part of a broad transnational movement of anti-colonial and anti-imperialist resistance. The temporary unity forged around ideas of decolonization came undone in the 1970s, however, as many were forced to come to terms with the contradictions and ambiguities of applying ideas of decolonization in Quebec. From linguistic debates to labour unions, and from the political activities of citizens in the city's poorest neighbourhoods to its Caribbean intellectuals, The Empire Within is a political tour of Montreal that reconsiders the meaning and legacy of the city's dissident traditions. It is also a fascinating chapter in the history of postcolonial thought. --Publisher's description

Interrogating the New Economy: Restructuring Work in the 21st Century - Pupo, Norene; Thomas, Mark P. (Mark Preston) (University of Toronto Press, 2010)
Interrogating the New Economy is a collection of original essays investigating the New Economy and how changes ascribed to it have impacted labour relations, access to work, and, more generally, the social and cultural experiences of work in Canada. Based on years of participatory research, sector-specific studies, and quantitative and qualitative data collection, the work accounts for the ways in which the contemporary workplace has changed but also the extent to which older forms of work organization still remain. The collection begins with an overview of the key social and economic transformations that define the New Economy. It then illustrates these transformations through examples, including essays on wine tourism, the regeneration of mining communities, the place of student workers, and changes in the public service workplace. It also addresses unions and their responses to the restructuring of work, as well as other forms of resistance. --Publisher's description
Keywords: Labor; Travail

Violence in the Workplace: A CLV Special Report - Roher, Eric M. (Carswell, 2010)
This report is a fully updated and concise discussion of leading cases in workplace violence (including physical and mental harrassment) and the various laws that apply to them, including human rights, health & safety, workplace insurance and the Criminal Code of Canada. This edition will help you to identify what constitutes violence, what obligations are created by the common law and what employers need to do to protect their workers and themselves. --Publisher's description
Keywords: Violence in the workplace

Transforming Labour: Women and Work in Post-War Canada - Sangster, Joan (University of Toronto Press, 2010)
The increased participation of women in the labour force was one of the most significant changes to Canadian social life during the quarter century after the close of the Second World War. Transforming Labour offers one of the first critical assessments of women's paid labour in this era, a period when more and more women, particularly those with families, were going 'out to work'. Using case studies from across Canada, Joan Sangster explores a range of themes, including women's experiences within unions, Aboriginal women's changing patterns of work, and the challenges faced by immigrant women. By charting women's own efforts to ameliorate their work lives as well as factors that re-shaped the labour force, Sangster challenges the commonplace perception of this era as one of conformity, domesticity for women, and feminist inactivity. Working women's collective grievances fuelled their desire for change, culminating in challenges to the status quo in the 1960s, when they voiced their discontent, calling for a new world of work and better opportunities for themselves and their daughters. --Publisher's description
Keywords: Employment; History; Labor Unions; Social conditions; Women

Breadwinning Daughters: Young Working Women in a Depression-Era City, 1929-1939 - Srigley, Katrina (Studies in gender and history, 2010)
As one of the most difficult periods of the twentieth century, the Great Depression left few Canadians untouched. Using more than eighty interviews with women who lived and worked in Toronto in the 1930s, Breadwinning Daughters examines the consequences of these years for women in their homes and workplaces, and in the city's court rooms and dance halls. In this insightful account, Katrina Srigley argues that young women were central to the labour market and family economies of Depression-era Toronto. Oral histories give voice to women from a range of cultural and economic backgrounds, and challenge readers to consider how factors such as race, gender, class, and marital status shaped women's lives and influenced their job options, family arrangements, and leisure activities. Breadwinning Daughters brings to light previously forgotten and unstudied experiences and illustrates how women found various ways to negotiate the burdens and joys of the 1930s. --Publisher's description
Keywords: 1929; 20th century; Depressions; Economic conditions; Employment History; History; Ontario Toronto; Social conditions; Toronto (Ont.); Women employees; Young women

Managing the Margins: Gender, Citizenship, and the International Regulation of Precarious Employment - Vosko, Leah F. (Oxford University Press, 2010)
[E]xplores the precarious margins of contemporary labour markets. Over the last few decades, there has been much discussion of a shift from full-time permanent jobs to higher levels of part-time and temporary employment and self-employment. Despite such attention, regulatory approaches have not adapted accordingly. Instead, in the absence of genuine alternatives, old regulatory models are applied to new labour market realities, leaving the most precarious forms of employment intact. The book places this disjuncture in historical context and focuses on its implications for workers most likely to be at the margins, particularly women and migrants, using illustrations from Australia, the United States, and Canada, as well as member states of the European Union. Managing the Margins provides a rigorous analysis of national and international regulatory approaches, drawing on original qualitative and quantitative material. It innovates by analysing the historical and contemporary interplay of employment norms, gender relations, and citizenship boundaries. --Publisher's description
Keywords: Employment; Employment. Foreign workers. Women; Employment. Women; Law and legislation. Foreign workers; Law and legislation. Temporary employment; Law and legislation. Women; Legal status, laws, etc. Part-time employment

Respectable Citizens: Gender, Family, and Unemployment in Ontario's Great Depression - Campbell, Lara A. (University of Toronto Press, 2009)
High unemployment rates, humiliating relief policy, and the spectre of eviction characterized the experiences of many Ontario families in the Great Depression. Respectable Citizens is an examination of the material difficulties and survival strategies of families facing poverty and unemployment, and an analysis of how collective action and protest redefined the meanings of welfare and citizenship in the 1930s.Lara Campbell draws on diverse sources including newspapers, family and juvenile court records, premiers' papers, memoirs, and oral histories to uncover the ways in which the material workings of the family and the discursive category of 'respectable' citizenship were invested with gendered obligations and Anglo-British identity. Respectable Citizens demonstrates how women and men represented themselves as entitled to make specific claims on the state, shedding new light on the cooperative and conflicting relationships between men and women, parents and children, and citizen and state in 1930s Canada. --Publisher's description

Fight Back: Workplace Justice for Immigrants - Choudry, Aziz; Hanley, Jill; Jordan, Steve; Stiegman, Martha; Schragge, Eric (Race & Racism, 2009)
[D]ocuments the struggles of immigrant workers and analyses them within the context of neoliberal globalization and the international and national labour markets. Fight Back grew out of collaboration between a group of university-affiliated researchers who are active in different social movements and community organizations in partnership with the Immigrant Workers Centre in Montreal. The book shares with us the experiences of immigrant workers in a variety of workplaces. It is based on the underlying belief that the best kind of research that tells “how it really is” comes from the lived experience of people themselves. -- Publisher's description. Contents: Introduction -- Context -- Making immigrant workers -- Access to social rights for migrants to Canada: the long divide between the law and the real world -- Seasonal agricultural workers -- Canada's live-in caregiver program : popular among both employers and migrants, but structured for dependency and inequality -- Survival and fighting back.
Keywords: Canada; Canada. Immigrants; Conditions économiques. Immigrants; Economic conditions. Immigrants; Employment; Immigrants; Social conditions. Immigrants; Travail

Philippe Vaillancourt : militant syndical et politique - Comby, Marc (VLB, 2009)
Philippe Vaillancourt (1913-1984) est venu à l'action syndicale par la politique et, durant toute sa carrière, il a conjugué ces deux formes d'engagement. Amorcé pendant la Grande Crise pour se terminer pendant la Révolution tranquille, le parcours militant de Philippe Vaillancourt a été particulièrement ardu, en butte entre autres à l'opposition du gouvernement de Maurice Duplessis. Suivre Philippe Vaillancourt dans cette période pionnière, c'est revivre des conflits du travail souvent violents, c'est suivre l'histoire des rivalités et des regroupements de syndicats, des tentatives de ces derniers de créer un parti ouvrier en s'alliant avec la Cooperative Commonwealth Federation (CCF), puis avec le Nouveau Parti Démocratique (NPD), de T.C. Douglas. Fermement convaincu de l'importance de l'éducation syndicale, Philippe Vaillancourt a consacré à cette priorité les dernières années de sa carrière au Congrès canadien du travail (CCT) pour le Québec, dont est membre la Fédération des travailleurs du Québec (FTQ). --Résumé de l'éditeur
Keywords: Vaillancourt, Philippe, 1913-1984

Games of Empire: Global Capitalism and Video Games - Dyer-Witheford, Nick; De Peuter, Greig (Electronic mediations, 2009)
In the first decade of the twenty-first century, video games are an integral part of global media culture, rivaling Hollywood in revenue and influence. No longer confined to a subculture of adolescent males, video games today are played by adults around the world. At the same time, video games have become major sites of corporate exploitation and military recruitment. In Games of Empire, Nick Dyer-Witheford and Greig de Peuter offer a radical political critique of such video games and virtual environments as Second Life, World of Warcraft, and Grand Theft Auto, analyzing them as the exemplary m
Keywords: Capitalism Social aspects; Computerspiel; GAMES Video & Electronic; Imperialism Social aspects; Impérialisme Aspect social; Jeux vidéo Aspect social; Jeux vidéo Aspect économique; Tv-spel ekonomiska aspekter; Tv-spel sociala aspekter; Video games Economic aspects; Video games Social aspects; Wirtschaft

Unions, Equity, and the Path to Renewal - Foley, Janice R.; Baker, Patricia L. (UBC Press, 2009)
Trade unions in Canada are losing their traditional support base, and membership numbers could sink to US levels unless unions recapture their power. Unions, Equity, and the Path to Renewal brings together a distinguished group of union activists and equity scholars who trace how traditional union cultures, practices, and structures have eroded solidarity and activism and created an equity deficit in Canadian unions. Informed by a feminist vision of unions as instruments of social justice, the contributors argue that equity within unions is not simply one possible path to union renewal – it is the only way to reposition organized labour as a central institution in workers’ lives. --Publisher's description
Keywords: Canada; Equality; Labor unions; Social aspects; Women in the labor movement

The Prestige Squeeze: Occupational Prestige in Canada Since 1965 - Goyder, John (McGill-Queen's University Press, 2009)
How Canadians rate the prestige of their occupations, and what this says about our understanding of the knowledge economy, social mobility and inequality, and our working selves. "What do you do?" is often the first question posed when strangers meet, as occupation reveals a great deal about both social identity and social standing or "occupational prestige." Sociologists have studied occupational prestige for decades, including a landmark national survey in 1965 by Peter Pineo and John Porter. John Goyder updates Pineo and Porter's work, providing a detailed comparison of their results with a similar national scale survey conducted in 2005. The results challenge the accepted view that prestige ratings are constant over time and across societies. Goyder shows that there have been some surprising changes in these ratings: instead of the expected premium on jobs in the knowledge sector, more traditional occupations - such as the skilled trades, even if they require little education or pay a low wage - have gained the most prestige. There has been a significant decrease in consensus about occupational prestige ratings and the tendency for respondents to upgrade the prestige of their own occupation is much more pronounced in the recent data. Goyder argues that these changes are a sign of the shifting nature of values in a meritocratic society in which increasing income inequality is a growing reality. Results from prestige surveys help in the construction of socio-economic scales for occupations and inform career counselling for young people and negotiations by labour unions and associations. "The Prestige Squeeze" goes beyond this to question the very nature of how we measure social equality and mobility. --Publisher's description

Canadian Labour and Employment Relations - Gunderson, Morley; Taras, Daphne Gottlieb (Pearson Addison Wesley, 2009)
Contents: Canadian labour and employment relations / Daphne G. Taras and Morley Gunderson -- Understanding the unionization decision / Ann C. Frost and Daphne G. Taras -- Labour history and the development of modern capitalism / Richard Marsden -- Unions : membership, structures, actions and challenges / Gregor Murray -- The management of industrial relations / Mark Thompson -- Managing the high-involvement workplace / Anil Verma and Daphne G. Taras -- Social, political, and economic environments / Frank Reid and Rafael Gomez -- Collective bargaining legislation in Canada / Sara Slinn -- The individual employment contract and employment / Geoffrey England -- Collective bargaining : structure, process, and innovation / Richard Chaykowski -- The collective agreement / Anthony Giles and Akivah Starkman -- Strikes and dispute resolution / Morley Gunderson, Bob Hebdon, and Douglas Hyatt -- The grievance arbitration process and workplace / Kenneth Wm. Thornicroft -- Union impact on compensation, productivity, and management of the organization / Morley Gunderson and Douglas Hyatt -- Public-sector collective bargaining / Mark Thompson and Patrice Jalette -- Union-management relations in Québec / Esther Déom and Jean-Noël Grenier with Marie-Pierre Beaumont -- Trade unions and labour relations regimes: international perspectives in a globalizing world / Carla Lipsig-Mummé. Previous eds. published under title: Union-management relations in Canada; Includes bibliographical references and index.
Keywords: Industrial relations -- Canada -- Textbooks

Laying It on the Line: Driving a Hard Bargain in Challenging Times - Hargrove, Buzz (HarperCollins, 2009)
In late 2008, the world’s economy began to tumble at avalanche speed, and at the forefront of the manufacturing collapse were the Big Three automakers: Chrysler, General Motors and Ford. For decades, these companies had been shining stars, providing billions of dollars of new investments and thousands of well-paying jobs. Yet suddenly the heads of these and other manufacturing giants found themselves begging governments for financial packages to save their industries. What the hell happened? Buzz Hargrove, the former head of the Canadian Autoworkers (CAW), retired right before the collapse, but not before witnessing the decades of bad decisionmaking— by federal governments and CEOs—that set the stage for the sudden crisis. No one knows the ins and outs of manufacturing like Hargrove, a man who championed the cause of on-the-line workers but who also earned the immense respect of political and business leaders. In Laying It on the Line, Hargrove explains the crisis from his side of the table, what it means for Canada and how the manufacturing sector can again become this country’s foremost economic driver. Along the way, he shares the behind-the-door dealings with GM, Ford, Air Canada and others, explaining the controversial agreements he reached over his decades as Canada’s chief labour leader. Laying It on the Line is a timely call to arms for industry, governments and indeed all Canadians. --Publisher's description
Keywords: 20th century; 21st century; Automobile industry History; Automobile industry and trade; Canada; Collective labor agreements; Hargrove, Buzz; History; Industrial relations; Manufacturing industries

Rig: An Oral History of the Ocean Ranger Disaster - Heffernan, Mike (Creative Publishers, 2009)
In the early hours of February 15, 1982, tragedy struck the Ocean Ranger oil rig when it capsized and sank in a severe weather storm 170 nautical miles east of St. John's, Newfoundland. All of the eighty-four crewmen perished, including fifty-six men from the province. This was Canada's greatest maritime disaster since World War II. Rig is a powerful story filled with first-person accounts and previously unpublished photographs. In an intimate journey through grief and sadness, Rig searches for reconciliation among the victims' families and those who risked their own lives to help those on the Ocean Ranger. --Publisher's description
Keywords: Ocean Ranger (Drilling rig)

Canadian Maverick: The Life and Times of Ivan C. Rand - Kaplan, William (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2009)
Ivan Rand had a long, varied and remarkable career. He is best known for his Supreme Court of Canada judgments in a series of cases emanating from Quebec in the 1950s and dealing with civil rights, cases which established limits on the government’s ability to persecute unpopular religious minorities. To labour lawyers he is also an icon for his invention of the ‘Rand formula’, one of the defining features of Canadian labour law. Rand was also a member of the United Nations special committee on Palestine in 1947, the founding Dean of the University of Western Ontario law school, and three times a royal commissioner, looking into the problems of the Canadian coal industry, the misconduct of Mr. Justice Leo A. Landreville, and labour disputes in Ontario. In this thoroughly researched and fast-paced book, William Kaplan traces Rand’s life and career in all its richness and controversy – Rand as lawyer, politician, judge, dean, and royal commissioner – through many seminal events of the twentieth century in Canada. The Rand that emerges is variously inspiring, frustrating to understand, sometimes contradictory, always complex. --Publisher's description

Essex County: A Graphic Novel - Lemire, Jeff. (Top Shelf Productions, 2009)
Where does a young boy turn when his whole world suddenly disappears? What turns two brothers from an unstoppable team into a pair of bitterly estranged loners? How does the simple-hearted care of one middle-aged nurse reveal the scars of an entire community, and can anything heal the wounds caused by a century of deception? Award-winning cartoonist Jeff Lemire pays tribute to his roots with Essex County, an award-winning trilogy of graphic novels set in an imaginary version of his hometown, the eccentric farming community of Essex County, Ontario, Canada. In Essex County, Lemire crafts an intimate study of one community through the years, and a tender meditation on family, memory, grief, secrets, and reconciliation. With the lush, expressive inking of a young artist at the height of his powers, Lemire draws us in and sets us free. This new edition collects the complete, critically-acclaimed trilogy (Tales from the Farm, Ghost Stories, and The Country Nurse) in one deluxe volume! Also included are over 40-pages of previously unpublished material, including two new stories. This title has been voted by Canada Reads Top 10 title for the decade! --Publisher's description
Keywords: Blue-collar work; Farming community; Nurse; Ontario Essex; Sabotage

The Factory Voice - Lynes, Jeanette (Coteau Books, 2009)
Wrapped around the stories of these four women, is a mystery. Something''s gone wrong with the Mosquitos being built for the war effort -- they keep crashing in flight tests, for no apparent reason. Is the problem with their design, or are they being sabotaged? By whom? The traitorous Red Finns? The political subversives who have recently escaped from one of the nearby prison camps? Everyone''s on high alert, and "The Factory Voice" keeps abreast of the details. Or at least the rumours. --Publisher's description
Keywords: 1939-1945; Airplane factories; Airplane factories Fiction; Amitié féminine Romans, nouvelles, etc; Avions Usines Romans, nouvelles, etc; Canada; Female friendship; Female friendship Fiction; Fiction; Guerre mondiale, 1939-1945 Femmes Romans, nouvelles, etc; Historical fiction; Northern Ontario; Ontario, Northern Fiction; Women; World War, 1939-1945 Canada Fiction; World War, 1939-1945 Women Fiction

The Guy in the Green Truck: A Biography of John St. Amand - McCrorie, James Napier (Roseway/Fernwood, 2009)
Affectionate portrait of John St. Amand (1943-2007) who, under the tutelage of the left-wing labour activist, Madeleine Parent, moved in 1981 from Ontario to Nova Scotia to become a union organizer.
Keywords: History; Labor Unions; Officials and employees; Organizing; St. Amand, John, 1943-2007

Labour Pains: Thunder Bay's Working Class in Canada's Wheat Boom Era - Morrison, Jean; Thunder Bay Historical Museum Society (Thunder Bay Historical Museum Society, 2009)
Through painful struggles and changing relationships, Thunder Bay’s working class defined itself during the tumultuous years before World War I. Labour Pains looks at many responses to the harshness of industrialism: trade unionism and labour politics, unrest and violence, the Social Gospel and socialism, mediation and conciliation. Alliances and conflict, many ethnicities and various expressions of class consciousness all contributed to the making of the working class whose members and defenders embraced many remarkable individuals, known and unknown. --Publisher's description. Contents: The beginnings of Thunder Bay's working class [Thunder Bay, Northwestern Ontario] -- Trade unions, municipal ownership & labour politics : Harry Bryan and the advent of organized labour] -- Dock workers, immigrants and the railways -- Socialism, the social gospel and labour politics [labor] -- The 1909 Freight Handlers Strike -- Who won the 1909 strike? -- Labour, socialists and the 1912 Coal Handlers Strike -- The Justice system, immigrants and waterfront strikes : socialists and violence -- The 1913 Street Railwaymen's Strike -- Reformers and rebels, good deeds and discord -- Appendix A. Labour unions in Port Arthur and Fort William in 1910. Includes bibliographical references (p. 170-174) and index.
Keywords: History; Labor unions; Ontario; Strikes and lockouts; Thunder Bay, Ont.; Working class

The National Farmers Union: Working for Farm Families for 40 Years. - National Farmers Union (Canada) (National Farmers Union, 2009)
The NFU was formed in 1969 through a merger of the Saskatchewan Farmers Union, the Ontario Farmers Union, the Farmers Union of British Columbia, and the Farmers Union of Alberta. In addition to these provincial unions, farmers from the Maritime provinces—not organized into farmers’ unions at the time—also became part of the NFU structure. Prior to ’69, these provincial unions each had worked autonomously in its respective province, but increasingly they were finding themselves at a disadvantage in attempting to work with the federal government. In an effort to solve that problem, the unions created a coordinating body, the National Farmers Union Council, consisting of representatives of the executives of each provincial union and representatives from the Maritime provinces. Over time, the officials and members from the provincial unions and the Maritimes realized that the major policy decisions affecting farmers were being made at the federal level. At a joint meeting of the executives of the provincial unions and others in Winnipeg in March 1968, the executive members passed a motion to strike a committee to develop a constitution for a direct membership national farm organization. The founding convention of the National Farmers Union was held in Winnipeg in July 1969. In the following months the provincial unions were phased out and their assets and liabilities transferred to the national organization. --Publisher's description

Harvest Pilgrims: Mexican and Caribbean Migrant Farm Workers in Canada - Pietropaolo, Vincenzo (Between the Lines, 2009)
Like migratory birds, most of Canada’s 20,000 “guest” farm workers arrive in the spring and leave in the autumn. Hailing primarily from Mexico, Jamaica, and smaller countries of the Caribbean, these temporary workers have become entrenched in the Canadian labour force and are the mainstay of many traditional family farms in Canada. Many of them make the trip year after year after year.Vincenzo Pietropaolo has been photographing guest workers and recording their stories since 1984 – in the process travelling to forty locations throughout Ontario and to their homes in Mexico, Jamaica, and Montserrat. The resulting photographs have been highly acclaimed internationally through many publications and exhibitions, including a travelling show curated by the Canadian Museum of Contemporary Photography that opened in Mexico City.With a foreword by Naomi Rosenblum, this beautiful and timely book of photography and exposition aims to shed light on a subject about which many Canadians know all too little. --Publisher's description

Neighbours and Networks: The Blood Tribe in the Southern Alberta Economy, 1884-1939 - Regular, W. Keith (William Keith) (University of Calgary Press, 2009)
[E]xplores the economic relationship that existed between the Blood Indian reserve and the surrounding region of southern Alberta between 1884 and 1939. The Blood tribe, though living on a reserve, refused to become economically isolated from the larger community and indeed became significant contributors to the economy of the area. Their land base was important to the ranching industry. Their products, especially coal and hay, were sought after by settlers, and the Bloods were encouraged, not only to provide them as needed, but also to become expert freighters, transporting goods from the reserve for non-Native business people. Blood field labor in the Raymond area sugar beet fields was at times critical to the functioning of that industry. In addition, the Bloods' ties to the merchant community, especially in Cardston and Fort Macleod, resulted in a significant infusion of money into the local economy. Regular's study fills the gap left by Canadian historiography that has largely ignored the economic associations between Natives and non-Natives living in a common environment. His microhistory refutes the perception that Native reserves have played only a minor role in regional development and provides an excellent example of a cross-cultural, co-operative economic relationship in the post-treaty period on the Canadian plains. --Publisher's description. Contents: Introduction -- 'Free Range or Private Property': Integrating Blood Reserve Land into the Non-Native Economy -- 'Selling to Outsiders': Marketing Coal, Hay, and Freighting Services -- 'All the Indians Have Gone to the Beet': Blood Labour in the Raymond Sugar Beet Fields -- 'A Prospective Citizen of No Mean Importance': The Bloods and the Business Community -- Conclusion: Change Over Time.
Keywords: Alberta; Blood Indian Reserve No. 148 (Alta.); Commerce; Economic conditions; History; Indian business enterprises; Kainah Indians

Regulating Flexibility: The Political Economy of Employment Standards - Thomas, Mark P. (McGill-Queen's University Press, 2009)
In a contemporary labour market that includes growing levels of precarious employment, the regulation of minimum employment standards is intricately connected to conditions of economic security. With a focus on the role of neoliberal labour market policies in promoting "flexible" employment standards legislation - particularly in the areas of minimum wages and working time - Mark Thomas argues that shifts toward "flexible" legislation have played a central role in producing patterns of labour market inequality. Using an analytic framework that situates employment standards within the context of the broader social relations that shape processes of labour market regulation, Thomas constructs a case study of employment standards legislation in Ontario from 1884 to 2004. Drawing from political economy scholarship, and using a qualitative research methodology, he analyses class, race, and gender dimensions of legislative developments, highlighting the ways in which shifts towards "flexible" employment standards have exacerbated longstanding racialized and gendered inequities. Regulating Flexibility argues that in order to counter current trends towards increased insecurity, employment standards should not be treated as a secondary form of labour protection but as a cornerstone in a progressive project of labour market re-regulation. --Publisher's description

Gender and the Contours of Precarious Employment - Vosko, Leah F.; MacDonald, Martha; Campbell, Iain (Routledge IAFFE advances in feminist economics, 2009)
Precarious employment presents a monumental challenge to the social, economic, and political stability of labour markets in industrialized societies and there is widespread consensus that its growth is contributing to a series of common social inequalities, especially along the lines of gender and citizenship. The editors argue that these inequalities are evident at the national level across industrialized countries, as well as at the regional level within federal societies, such as Canada, Germany, the United States, and Australia and in the European Union. This book brings together contributions addressing this issue which include case studies exploring the size, nature, and dynamics of precarious employment in different industrialized countries and chapters examining conceptual and methodological challenges in the study of precarious employment in comparative perspective. The collection aims to yield new ways of understanding, conceptualizing, measuring, and responding, via public policy and other means - such as new forms of union organization and community organizing at multiple scales - to the forces driving labour market insecurity. --Publisher's description
Keywords: Alemania; Allemagne; Analyse comparative; Arbeitsmarkt; Arbetsmarknad genusaspekter; Australia; Australie; Canada; Canadá; Contract system (Labor); Espagne; España; Estados Unidos; Etats-Unis; Etats-Unis d'Amérique; Fackligt arbete; France; Francia; Frau; Genre; Germany; Inégalités sociales; Ireland; Irlanda; Irlande; Japan; Japon; Japón; Marché du travail; Netherlands; Niedriglohn; Pays développés; Pays-Bas; Países Bajos; Precarious employment; Précarité; Reino Unido de Gran Bretaña e Irlanda del Norte; Royaume-Uni de Grande-Bretagne et d'Irlande du Nord; Rörlighet på arbetsmarknaden; Sexual division of labor; Spain; Suecia; Suède; Sweden; Temporary employment; Travail précaire; Travail temporaire; UE/CE Etats membres; USA; United Kingdom of Great Britain and Northern Ireland; Women Employment; Zeitarbeit; chômage; desempleo; division du travail basée sur le sexe; división del trabajo por sexo; empleo a tiempo parcial; empleo precario; empleo temporal; emploi précaire; emploi temporaire; emploi à temps partiel; men workers; part time employment; precarious employment; sexual division of labour; temporary employment; trabajadoras; trabajadores masculinos; travailleurs masculins; travailleuses; unemployment; women workers

If You're in My Way, I'm Walking: The Assault on Working People since 1970 - Workman, W. Thom (Fernwood Pub., 2009)
“If you’re in my way I’m walking.” This arrogant statement by former Prime Minister Jean Chrétien on the occasion of his physical altercation with a protester in Hull, Quebec in the mid-1990s symbolizes the spirit of the relentless drive of capital to rewrite the historical compromise reached with working people after World War II. This early post-war compromise—sometimes referred to as the Fordist Compact—was associated with improving wages and rising living standards for working people. But in recent decades those achievements of the working class are being deliberately rolled back. Workman surveys many features of this experience: changing public perceptions of working life, the deregulation of labour law, the decline in unionization rates, the eclipse of union militancy, the stagnation of real wages, the disproportionate absorption of women into the low-wage sphere and the dismantling of social policy. He demonstrates the unravelling of the post-war compact and its replacement with a far more ex-ploitative relationship between capital and labour. He also points to the decline of the Canadian left and its inability to counter the capitalist onslaught effectively. Nevertheless, there are reasons to be hopeful. Workman calls for a rebuilding of the left through the restoration of left culture. To do this he says that the left must “quit politics,” work to promote the collective memory of working-class achievements, create venues to listen to working people in today’s economy, reject nationalism outright and encourage the labour movement to exploit its disruptive capacity. This revitalized left will form the basis of a deepening social critique, the political lessons of which will prove to be invaluable for working people in the long run. -- Publisher's description
Keywords: Labor Unions; Labor movement; Neoliberalism; Right and left (Political science); Working class

Political Trials and Security Measures, 1840-1914 - Wright, Barry; Binny, Susan (Canadian State Trials, 2009)
This third volume of the Osgoode Society’s Canadian State Trials series covers the period from the 1840s to the First World War. It examines a range of political trials as traditionally defined, including those arising from the Fenian invasions and the North-West Rebellions. The volume also expands the definition of state trials to include studies on the early development of secret policing and the evolution of the legal regulation of riot and public order. The editors have assembled a team of experts from across the country in a variety of fields, and produced a comprehensive and fascinating set of studies of the use of law to control political dissent and public disorder.--Publisher's description.
Keywords: Political crimes and offenses -- Canada -- History

Why Unions Matter - Yates, Michael (Monthly Review Press, 2009)
In this new edition the author shows why unions still matter. Unions mean better pay, benefits, and working conditions for their members; they force employers to treat employees with dignity and respect; and at their best, they provide a way for workers to make society both more democratic and egalitarian. The author uses both data, and examples to show why workers need unions, how unions are formed, how they operate, how collective bargaining works, the role of unions in politics, and what unions have done to bring workers together across the divides of race, gender, religion, and sexual orientation. The new edition not only updates the first, but also examines the record of the New Voice slate that took control of the AFL-CIO in 1995, the continuing decline in union membership and density, the Change to Win split in 2005, the growing importance of immigrant workers, the rise of worker centers, the impacts of and labor responses to globalization, and the need for labor to have an independent political voice, and the Employee Free Choice Act. --Publisher's description
Keywords: Labor unions; Labor unions United States; United States

Selling Diversity: Immigration, Multiculturalism and Employment Equity - Abu-Laban, Yasmeen; Gabriel, Christina (Broadview Press, 2008)
Since the 1990s, Canadian policy prescriptions for immigration, multiculturalism, and employment equity have equated globalization with global markets. This interpretation has transformed men and women of various ethnic backgrounds into trade-enhancing commodities who must justify their skills and talents in the language of business. This particular neo-liberal reading of globalization and public policy has resulted in a trend the authors call selling diversity. Using gender, race/ethnicity, and class lenses to frame their analysis, the authors review Canadian immigration, multiculturalism, and employment equity policies, including their different historical origins, to illustrate how a preference for selling diversity has emerged in the last decade. In the process they suggest that a commitment to enhance justice in a diverse society and world has been muted. Yet, neo-liberalism is not the only or inevitable option in this era of globalization, and Canadians are engaging in transnational struggles for rights and equality and thereby increasing the interconnectedness between peoples across the globe. Consequently, the emphasis on selling diversity might be challenged.
Keywords: Diversity; Equality; Equity; Immigrants

Building a Better World: An Introduction to Trade Unionism in Canada - Black, Errol; Silver, James (Fernwood, 2008)
Substantially revised and updated, this widely used introductory text emphasizes how values, objectives and activities of unions are shaped in the face of employer resistance and hostile governments. It includes an analysis of why workers form unions; organization and democracy; collective bargaining and grievances; historical development; and gains unions have achieved for their members and all working people. It also examines the challenges created by rapid economic and technological change, the rise of neoliberalism and the increasingly contingent and acialized character of the labour force. --Publisher's description
Keywords: History; Labor Unions

Nation and Society: Readings in Post-Confederation Canadian History, volume 2 - Conrad, Margaret; Finkel, Alvin (Pearson Longman, 2008)
[This textbook] is a balanced collection of the best readings on the history of Canada since Confederation. The readings are separated into five parts: Inventing Canada, 1867-1914; Economy and society in the Industrial Age, 1867-1918; Transitional years, Canada 1919-1945; Reinventing Canada, 1945-1975; and Post-Modern Canada. With 13 new readings, the book will challenge and enlighten students by opening a window to Canada's past and to the ever-evolving examination of Canadian history. --Publisher's description
Keywords: Canada -- History -- 1867- -- Textbooks

Barnacle Love - De Sa, Anthony (Penguin Random House Canada, 2008)
Like Wayson Choy and David Bezmozgis before him, Anthony De Sa captures, in stories brimming with life, the innocent dreams and bitter disappointments of the immigrant experience. At the heart of this collection of intimately linked stories is the relationship between a father and his son. A young fisherman washes up nearly dead on the shores of Newfoundland. It is Manuel Rebelo who has tried to escape the suffocating smallness of his Portuguese village and the crushing weight of his mother’s expectations to build a future for himself in a terra nova. Manuel struggles to shed the traditions of a village frozen in time and to silence the brutal voice of Maria Theresa da Conceicao Rebelo, but embracing the promise of his adopted land is not as simple as he had hoped. Manuel’s son, Antonio, is born into Toronto’s little Portugal, a world of colourful houses and labyrinthine back alleys. In the Rebelo home the Church looms large, men and women inhabit sharply divided space, pigs are slaughtered in the garage, and a family lives in the shadow cast by a father’s failures. Most days Antonio and his friends take to their bikes, pushing the boundaries of their neighbourhood street by street, but when they finally break through to the city beyond they confront dangers of a new sort. With fantastic detail, larger-than-life characters and passionate empathy, Anthony De Sa invites readers into the lives of the Rebelos and finds there both the promise and the disappointment inherent in the choices made by the father and the expectations placed on the son. --Publisher's description
Keywords: Authors, Canadian (English) 21st century; Canadian fiction; Domestic fiction; Fiction; Immigrants; Immigrants Fiction; Newfoundland and Labrador; Newfoundland and Labrador Fiction; Nouvelles; Ontario Toronto; Short stories; Toronto (Ont.) Fiction; short stories

Cultivating Farmworker Rights: Ending the Exploitation of Immigrant and Migrant Farmworkers in BC - Fairey, David; Hanson, Christina; MacInnes, Glen; McLaren, Arlene Tigar; Otero, Gerardo; Thompson, Mark (Canadian Centre for Policy Alternatives, 2008)
A new study of farm work in BC reveals systematic violations of employment standards and health and safety regulations, poor and often dangerous working conditions, and dismal enforcement by government agencies. The study’s authors propose comprehensive policy changes that would ensure farmworkers — most of whom are immigrants and temporary migrants — are no longer relegated to second-class status. “Farmworkers are at the mercy of a complex and confusing system that exploits, threatens and silences them while putting their lives in danger,” says study co-author Arlene McLaren, Professor Emerita of Sociology at Simon Fraser University. The study draws from numerous sources, including interviews with key informants in government and the farm industry, interviews with 53 Indo-Canadian immigrant and Mexican migrant farmworkers, a survey 87 Mexican migrant farmworkers, and a review of better practices in other jurisdictions. The study is part of the Economic Security Project, a joint initiative of the Canadian Centre for Policy Alternatives and Simon Fraser University. --Publisher's description
Keywords: Agricultural laborers; British Columbia; Civil rights; Legal status, laws, etc

Industrial Relations in Canada - Hebdon, Robert; Brown, Travor C. (Nelson Series in Human Resources Management, 2008)
This text presents a hands-on examination of industrial relations balanced in both theoretical and practical coverage, as well as union and labour coverage. Industrial Relations in Canada is grounded in leading research and examines true-to-life issues. Experiential exercises, cases, and collective bargaining simulations bridge the academic content of the text with real-world issues in the field. --Publisher's description of 2011 edition.

Working in Steel: The Early Years in Canada, 1883-1935 - Heron, Craig (Canadian social history series, 2008)
In this indispensable study of Canadian industrialization, Craig Heron examines the huge steel plants that were built at the turn of the twentieth century in Sydney and New Glasgow, Nova Scotia, and Trenton, Hamilton, and Sault Ste. Marie, Ontario. Presenting a stimulating analysis of the Canadian working class in the early twentieth century, Working in Steel emphasizes the importance of changes in the work world for the larger patterns of working-class life. Heron's examination of the impact of new technology in Canada's Second Industrial Revolution challenges the popular notion that mass-production workers lost all skill, power, and pride in the work process. He shifts the explanation of managerial control in these plants from machines to the blunt authoritarianism and shrewd paternalism of corporate management. His discussion of Canada's first steelworkers illuminates the uneven, unpredictable, and conflict-ridden process of technological change in industrial capitalist society. As engaging today as when first published in 1988, Working in Steel remains an essential work in Canadian history. --Pubisher's description
Keywords: Canada; Capitalism; History; Industrial; Working class

One Step Over the Line: Toward a History of Women in the North American Wests - Jameson, Elizabeth; McManus, Sheila (West unbound, 2008)
This eclectic and carefully organized range of essays--from women's history and settler societies to colonialism and borderlands studies--is the first collection of comparative and transnational work on women in the Canadian and U.S. Wests. It explores, expands, and advances the aspects of women's history that cross national borders. Out of the talks presented at the 2002 "Unsettled Pasts: Reconceiving the West through Women's History," Elizabeth Jameson and Sheila McManus have edited a foundational text with a wide, inclusive perspective on our western past. --Publisher's description. Contents: Connecting the women's Wests / Elizabeth Jameson -- Unsettled pasts, unsettling borders: women, Wests, nations / Sheila McManus -- Making connections: gender, race and place in Oregon contry / Susan Armitage -- A transborder family in the Pacific North West: reflecting on race and gender in women's history / Sylvia van Kirk -- Writing women into the history of the North American Wests, one woman at a time / Jean Barman -- "That understanding with nature":region, race, and nation in women's stories from the modern Canadian and American Grasslands West / Molly P. Rozum -- The perils of rural women's history: (a note to storytellers who study the West's unsettled past) / Joan M. Jensen -- The great white mother: maternalism and American Indian child removal in the American West, 1880-1940 / Margaret D. Jacobs -- Pushing physical, racial, and ethnic boundaries: Edith Lucas and public education in British Columbia, 1903-1989 / Helen Raptis -- "Crossing the line": American prostitutes in Western Canada, 1895-1925 / Char Smith -- "Talented and charming strangers from across the line": gendered nationalism. class privilege, and the American woman's club of Calgary / Nora Faires -- Excerpts from Pourin' Down Rain / Cheryl Foggo -- "A union without women is only half organized": Mine Mill, women's auxiliaries, and cold war politics in the North American Wests / Laurie Mercier -- Jailed heroes and kithen heroines: class, gender, and the Medalta Potteries strike in postwar Alberta / Cynthia Loch-Drake -- Gendered steps across the border: teaching the history of women in the American and Canadian Wests / Margaret Walsh -- Latitudes and longitudes: teaching the history of women in the U.S. and Canadian Wests / Mary Murphy.
Keywords: Boundaries; Canada; Canada Boundaries United States; Canada Boundaries United States Congresses; Canada Frontières États-Unis; Canada Frontières États-Unis Congrès; Conference papers and proceedings; Femmes Canada (Ouest) Histoire Congrès; Femmes États-Unis (Ouest) Histoire Congrès; HISTORY General; History; United States; United States Boundaries Canada; United States Boundaries Canada Congresses; West United States; Western Canada; Women; Women Canada, Western History; Women Canada, Western History Congresses; Women West (U.S.) History; Women West (U.S.) History Congresses; États-Unis Frontières Canada; États-Unis Frontières Canada Congrès

Management of Occupational Health and Safety - Kelloway, E. Kevin; Francis, Lori D (Thomson Nelson, 2008)
Based on the premise that occupational health and safety concerns can directly impact an organizations productivity and profitability, this 4th Canadian edition of Management of Occupational Health and Safety helps Human Resource Managers understand health and safety issues, legislation and programs. This edition also provides an up-to-date review of current issues, and methodologies affecting the occupational health and safety standards and practices of Canadian organizations. --Publisher's description
Keywords: Canada; Health and Safety

Mining Town Crisis: Globalization, Labour, and Resistance in Sudbury - Leadbeater, David (Fernwood, 2008)
Sudbury is the largest hardrock mining centre in North America and among the largest in the world. Given the enormous mineral wealth that exists in the Sudbury Basin, one might think that prosperity would abound and that cultural, educational, health and social-welfare institutions would be of the highest order, existing within a well-maintained and attractive physical infrastructure. But this is not the Sudbury that people know. This book explores key aspects of Sudbury’s economic, health and social conditions. It analyzes how globalization and corporate power in a hinterland mining town have impacted on working people, how and why resistance has emerged and why alternative directions are needed. While Sudbury is the focus of this book, the Sudbury experience offers important lessons for other mining and resource communities. --Publisher's description.
Keywords: History / Canada / General; Political Science / Globalization; Political Science / Labor & Industrial Relations

Makúk: A New History of Aboriginal-White Relations - Lutz, John S. (UBC Press, 2008)
The history of Aboriginal-settler interactions in Canada continues to haunt the national imagination. Despite billions of dollars spent on the "Indian problem," Aboriginal people remain the poorest in the country. Because the stereotype of the "lazy Indian" is never far from the surface, many Canadians wonder if the problem lay with "Indians" themselves. John Lutz traces Aboriginal people's involvement in the new economy, and their displacement from it, from the first arrival of Europeans to the 1970s. Drawing upon oral histories, manuscripts, newspaper accounts, biographies, and statistical analysis, Lutz shows that Aboriginal people flocked to the workforce and prospered in the late 19th century. The roots of today's wide-spread unemployment and "welfare dependency" date only from the 1950s, when deliberate and inadvertent policy choices--what Lutz terms the "white problem"--drove Aboriginal people out of the capitalist, wage, and subsistence economies, offering them welfare as "compensation." -- Publisher's description. Contents: Introduction: Molasses stick legs -- Pomo Wawa: the other jargon -- Making the lazy Indian -- The Lekwungen -- The Tsilhqot'in -- Outside history: labourers of the aboriginal province -- The white problem -- Prestige to welfare: remaking the moditional economy -- Conclusion: the outer edge of probability, 1970-2007 -- Postscript: subordination without subjugation.
Keywords: British Columbia; Commerce; Commerce. Indians of North America; Economic conditions. Indians of North America; Employment; Employment. Indians of North America; Government relations. Indians of North America; Government relations. Whites; History. Indians of North America; Whites

Reasoning Otherwise: Leftists and the People's Enlightenment in Canada, 1890-1920 - McKay, Ian (Between the Lines, 2008)
In Reasoning Otherwise, author Ian McKay returns to the concepts and methods of 'reconnaissance' first outlined in Rebels, Reds, Radicals to examine the people and events that led to the rise of the left in Canada from 1890 to 1920. Reasoning Otherwise highlights how a new way of looking at the world based on theories of evolution transformed struggles around class, religion, gender, and race, and culminates in a new interpretation of the Winnipeg General Strike of 1919. As McKay demonstrated in Rebels, Reds, Radicals, the Canadian left is alive and flourishing, and has shaped the Canadian experience in subtle and powerful ways. Reasoning Otherwise continues this tradition of offering important new insight into the deep roots of leftism in Canada. --Publisher's description
Keywords: History; Politics and government; Right and left (Political science); Socialism

Working Girls in the West: Representations of Wage-Earning Women - McMaster, Lindsey (UBC Press, 2008)
As the twentieth century got underway in Canada, young women who entered the paid workforce became the focus of intense public debate. Young wage-earning women - "working girls"--Embodied all that was unnerving and unnatural about modern times: the disintegration of the family, the independence of women, and the unwholesomeness of city life. These anxieties were amplified in the West. Long after eastern Canada was considered settled and urbanized, the West continued to be represented as a frontier where the idea of the region as a society in the making added resonance to the idea of the working girl as social pioneer." "Using an interpretive approach that centres on literary representation, Lindsey McMaster takes a fresh look at the working heroine of western Canadian literature alongside social documents and newspaper accounts of her real-life counterparts. Working Girls in the West heightens our understanding of a figure that fired the imagination of writers and observers at the turn of the last century." --Publisher's description. Contents: Working women in the west at the turn of the century --The urban working girl in turn-of-the-century Canadian literature -- White slaves, prostitutes, and delinquents -- Girls on strike -- White working girls and the mixed-race workplace -- Conclusion: Just girls.

The Impossibilists: A Brief Profile of the Socialist Party of Canada - Newell, Peter E. (Athena, 2008)
Formed in January 1905, the Socialist Party of Canada's anti- reformist, anti-statist revolutionary platform led to ideological disputes with rival socialist groups and even arguments within the Party itself over what it stood for. Peter E Newell's absorbing and thorough account of the life and times of the Socialist Party of Canada charts the Party's pre-history in the 1890s, when the availability of translations of the works of Marx and Engels fuelled the radicalism of such figures as Daniel De Leon. It also covers the early years of the twentieth century when, with the merger of like-minded Provincial socialist parties, the SPC was founded. In the present day the party remains a beacon for socialists worldwide for its refusal to compromise its passions and beliefs. --Publisher's description
Keywords: Socialist Party of Canada

Solidarity First: Canadian Workers and Social Cohesion - O'Brien, Robert (UBC Press, 2008)
As working people’s lives become increasingly fragmented, competitive, and unequal, debates about social cohesion capture the unease of contemporary society over growing economic restructuring. Solidarity First examines the concept and practice of social cohesion in terms of its impact on, and significance for, workers in Canada. Contributors examine how social cohesion functions on multiple levels. They challenge standard approaches by highlighting the experiences of women and non-Canadians. They investigate attempts by Toyota and Magna to construct corporate forms of cohesion and efforts by a local community to forge cohesion via the new cultural economy. And they explore the relationship between cohesion in Canada and the international environment. Critically examining the issue from the ground up, Solidarity First concludes that reinvigorated worker solidarity is a prerequisite to a more worker-friendly form of social cohesion. It will be of interest to students and scholars in the fields of public policy, political science, sociology, and labour studies. --Publisher's description
Keywords: Economic conditions; Employees; Social conditions; Social integration; Social participation; Social values; Solidarity; Working class

Labouring Canada: Class, Gender, and Race in Canadian Working-Class History - Palmer, Bryan D.; Sangster, Joan (Oxford University Press, 2008)
This text is a collection of classic and contemporary articles exploring the nature of work in Canadian history from the late eighteenth century to the current day. Class relations and labour form the core of the volume, but attention will also be paid to the state and its relations with workers both formal and informal. The volume is designed as a core text for classes in Canadian labour/working-class history, taught out of history and labour studies departments. --Publisher's description
Keywords: Canada; History; Labor movement; Social history; Working class

Citizen Docker: Making a New Deal on the Vancouver Waterfront, 1919-1939 - Parnaby, Andrew (Canadian social history series, 2008)
After the First World War, many Canadians were concerned with the possibility of national regeneration. Progressive-minded politicians, academics, church leaders, and social reformers turned increasingly to the state for solutions. Yet, as significant as the state was in articulating and instituting a new morality, outside actors such as employers were active in pursuing reform agendas as well, taking aim at the welfare of the family, citizen, and nation. Citizen Docker considers this trend, focusing on the Vancouver waterfront as a case in point.After the war, waterfront employers embarked on an ambitious program - welfare capitalism - to ease industrial relations, increase the efficiency of the port, and, ultimately, recondition longshoremen themselves. Andrew Parnaby considers these reforms as a microcosm of the process of accommodation between labour and capital that affected Canadian society as a whole in the 1920s and 1930s. By creating a new sense of entitlement among waterfront workers, one that could not be satisfied by employers during the Great Depression, welfare capitalism played an important role in the cultural transformation that took place after the Second World War.Encompassing labour and gender history, aboriginal studies, and the study of state formation, Citizen Docker examines the deep shift in the aspirations of working people, and the implications that shift had on Canadian society in the interwar years and beyond. --Publisher's description. Contents: Introduction: "A good citizen policy" -- Welfare capitalism on the waterfront -- Securing a square deal -- "The best men that ever worked the lumber" -- Heavy lifting -- "From the fury of democracy, good Lord, deliver us!" -- Conclusion: from square deal to new deal. Includes bibliographical references (pages 221-234) and index.

The Dirt: Industrial Disease and Conflict at St. Lawrence, Newfoundland - Rennie, Rick (Fernwood, 2008)
In the cemeteries of St. Lawrence and several neighbouring towns on the south coast of Newfoundland lie the remains of some 200 workers, killed by the dust and radiation that permeated the area’s fluorspar mines. The Dirt chronicles the many forces that created this disaster and shaped the response to it, including the classic ‘jobs or health’ dilemma, the contentious process of determining the nature and extent of industrial disease and the desire of employers to ‘externalize’ the costs of production onto workers and communities. Central to the account is the persistent effort by workers, women in the community and other activists to gain recognition of health hazards in the mines, their effects on workers and to obtain adequate compensation for victims and their families. --Publisher's description.  Contents: Origins of a disaster: working conditions and labour relations in the 1930s -- Protest and retreat: the war years -- Industry revival, increasing hazards and the recognition of sislicosis, 1946-1956 -- More deadly perils: radiation and cancer -- "The truly ghastly total" and the lack of compensation coverage -- Mounting protest, industry closure, and the legacy of the past.
Keywords: Aspect sanitaire; Diseases; Employees; Employees Diseases; Employees Health and hygiene; Fluorspar industry; Health and hygiene; Health and hygiene. Mining; Health aspects; Industrie; Maladies; Mineral dusts; Miners; Newfoundland and Labrador; Newfoundland and Labrador St. Lawrence; Newfoundland and Labrador. Calcium Fluoride; Newfoundland and Labrador. Occupational Diseases; Newfoundland and Labrador. Silicosis; Personnel; St. Lawrence. Fluorite; St. Lawrence. Fluorspar industry; St. Lawrence. Mineral dusts; St. Lawrence. Miners; St. Lawrence. Mineurs; Terre-Neuve-et-Labrador; Toxicologie; Toxicology; Toxicology. Miners

Fighting for Justice and Dignity: The Homer Seguin Story: An Autobiography - Seguin, Homer (Journal Printing, 2008)
Self-published memoir of the Sudbury union activist, Homer Seguin (1934-2013), who championed workplace health and safety to reduce injuries and occupational diseases at mines and other industrial sites. Describes his experiences as a negotiator, president of Local 6500 of the United Steelworkers, and as a USW representative at Elliot Lake, Ontario. Also chronicles the rise of the labour movement in Sudbury and the bitter inter-union battle in the early 1960s between Mine Mill Local 598 and the Steelworkers over the right to represent 20,000 Inco workers.
Keywords: 20th century; Elliot Lake; History. Industrial relations; History. Trade-unions; International Union of Mine, Mill and Smelter Workers. Local 598; Miners; Northeastern Ontario; Occupational health and safety; Seguin, Homer; Sudbury; United Steelworkers of America. Local 6500

Canada's Jews: A People's Journey - Tulchinsky, Gerald J. J (University of Toronto Press, 2008)
The history of the Jewish community in Canada says as much about the development of the nation as it does about the Jewish people. Spurred on by upheavals in Eastern Europe in the late-eighteenth and early-nineteenth centuries, many Jews immigrated to the Dominion of Canada, which was then considered little more than a British satellite state. Over the ensuing decades, as the Canadian Jewish identity was forged, Canada underwent the transformative experience of separating from Britain and distinguishing itself from the United States. In this light, the Canadian Jewish identity was formulated within the parameters of the emerging Canadian national personality." "Canada's Jews is an account of this remarkable story as told by one of the leading authors and historians on the Jewish legacy in Canada. Drawing on his previous work on the subject, Gerald Tulchinsky describes the struggle against antisemitism and the search for a livelihood among the Jewish community. He demonstrates that, far from being a fragment of the Old World, Canadian Jewry grew from a tiny group of transplanted Europeans to a fully articulated, diversified, and dynamic national group that defined itself as Canadian while expressing itself in the varied political and social contexts of the Dominion. --Publisher's description

Détérioration des salaires des nouveaux immigrants au Québec par rapport à l'Ontario et à la Colombie-Britannique - Boudarbat, Brahim; Boulet, Maude (Choices (Institute for Research on Public Policy), 2007)
Notre étude a un double objectif. Elle vise d’abord à comparer l’évolution des salaires d’entrée des immigrants au Québec par rapport à l’Ontario et à la Colombie-Britannique. Ensemble, ces trois provinces ont accueilli 89,5 % des immigrants arrivés au Canada au cours des années 1990 (Statistique Canada 2003). Ensuite, notre analyse s’emploie à expliquer les changements observés à cet égard dans chacune des trois provinces en considérant notamment le rôle des trois facteurs relevés dans la littérature, à savoir la région d’origine et les compétences linguistiques, le rendement de l’expérience acquise à l’étranger et le cycle économique. -- Introduction
Keywords: British Columbia; British Columbia. Immigrants; Economic conditions. Immigrants; Economic conditions. Wages; Foreign workers; Ontario; Ontario. Wages; Wages

La pendaison d'Angélique : l'histoire de l'esclavage au Canada et de l'incendie de Montréal - Cooper, Afua (Éditions de l'Homme, 2007)
Dans la soirée du samedi 10 avril 1734, Montréal brûle. L'esclave Marie-Joseph- Angélique est traduite devant la justice et accusée d'avoir mis le feu. Soumise à la question extraordinaire, forme de torture atroce pendant laquelle on brise les os des jambes, elle craque et avoue avoir commis cet incendie criminel. Puis, elle est pendue. Angélique entre dans l'histoire canadienne en tant que criminelle. Cependant, son procès nous offre une occasion unique de raconter sa vie d'esclave, une vie dont on n'aurait pas entendu parler autrement. Afua Cooper fait revivre brillamment un chapitre méconnu de l'histoire du Canada, celui d'une Noire rebelle d'origine portugaise qui a cherché à briser ses chaînes. En nous présentant le vécu de cette jeune femme, elle met en lumière ce qui l'a sans doute poussée à commettre pareil crime. Par le fait même, elle détruit le mythe d'un Canada considéré comme un paradis pour les Noirs ayant échappé à l'esclavagisme des États-Unis. L'histoire d'Angélique est le plus ancien récit à propos de l'esclavage dans le Nouveau Monde. En lui consacrant cet ouvrage, Afua Cooper apporte une importante contribution à l'historiographie canadienne et met en perspective l'esclavage accepté légalement et culturellement au Canada. --Publisher's description
Keywords: Marie-Joseph-Angélique

Collective Bargaining in Canada: Human Right or Canadian Illusion? - Fudge, Derek (Fernwood, 2007)
Recounting the cuts to freedom of association and the collective bargaining process across Canada since the 1980s, this study challenges the notion that Canada is an international champion of human rights. With documentation on the assaults to the rights of Canadian workers, this text considers the ways governments intervene to stop the collective bargaining process and evaluates topics such as the history of collective bargaining in Canada, the role of the International Labor Office, and the future hope of restoring rights and fairness to labor laws. --Publisher's description
Keywords: Collective bargaining; Labor laws and legislation

Organizing the Transnational: Labour, Politics, and Social Change - Goldring, Luin; Krishnamurti, Sailaja (UBC Press, 2007)
Growing recognition of transnational practices and identities is changing the way scholars and activists ask questions about migration. Organizing the Transnational articulates a multi-level cultural politics of transnationalism to frame contemporary analyses of immigration and diasporas. With chapters by academics and activists working from diverse perspectives, the volume moves beyond the conventional focus on states and migrants to consider a wide array of institutions, actors, and forms of mobilization that shape transnational engagements and communities. Its unique approach will inform the work of researchers, practitioners, and activists interested in the dynamics of transnational social spaces. --Publisher's description
Keywords: Asians; Asians Canada; Asiatiques Canada; Asien; Canada; Changement social Canada; Community organization; Community organization Canada; Einwanderung; Ethnicity; Ethnicity Canada; Ethnicité Canada; Etnicitet Kanada; Hispanos; Immigrants; Immigrants Canada; Immigration Kanada; Kanada; Latin Americans; Latin Americans Canada; Latino-Américains Canada; Organisation communautaire Canada; Social change; Social change Canada; Social förändring Kanada; Sozialer Wandel; Transnationale Politik; Transnationalism; Transnationalisme

Guarding the Gates: The Canadian Labour Movement and Immigration, 1872-1934 - Goutor, David (UBC Press, 2007)
From the 1870s until the Great Depression, immigration was often the question of the hour in Canada. Politicians, the media, and an array of interest groups viewed it as essential to nation building, developing the economy, and shaping Canada’s social and cultural character. One of the groups most determined to influence public debate and government policy on the issue was organized labour, and unionists were often relentless critics of immigrant recruitment. Guarding the Gates is the first detailed study of Canadian labour leaders’ approach to immigration, a key battleground in struggles between different political factions within the labour movement. --Publisher's description
Keywords: Emigration and immigration; Employment; Government policy; History; Immigrants; Labor Unions; Race discrimination

Capital and Labour in the British Columbia Forest Industry, 1934-74 - Hak, Gordon H. (Gordon Hugh) (UBC Press, 2007)
The history of British Columbia’s economy in the twentieth century is inextricably bound to the development of the forest industry. In this comprehensive study, Gordon Hak approaches the forest industry from the perspectives of workers and employers, examining the two main sets of institutions that structured the relationship during the Fordist era: the companies and the unions. Drawing on theories of the labour process, Fordism, and discursive subjectivity, Hak relates daily routines of production and profit-making to broader forces of unionism, business ideology, ecological protest, technological change, and corporate concentration. The struggle of the small-business sector to survive in the face of corporate growth, the history of the industry on the Coast and in the Interior, the transformations in capital-labour relations during the period, government forest policy, and the forest industry’s encounter with the emerging environmental movement are all considered in this eloquent analysis. With its critical historical perspective, Capital and Labour in the British Columbia Forest Industry will be essential reading for anyone interested in the business, natural resource, political, social, and labour history of the province. --Publisher's description
Keywords: Forests and forestry -- British Columbia -- History

Race, Racialization, and Antiracism in Canada and Beyond - Johnson, Genevieve Fuji; Enomoto, Randy; Canadian Ethnocultural Council; National Association of Japanese Canadians; End Racism! Activism for the 21st Century Conference (2000 : Vancouver, BC) (University of Toronto Press, 2007)
This multidisciplinary volume brings together scholars and activists to examine expressions of racism in contemporary policy areas, including education, labour, immigration, media, and urban planning. While anti-racist struggles during the twentieth century were largely pitched against overt forms of racism (e.g., pogroms, genocide, segregation, apartheid, and 'ethnic cleansing'), it has become increasingly apparent that there are other, less visible, forms of racism. These subtler incarnations are of special interest to the contributors. The intent of Race, Racialization, and Antiracism in Canada and Beyond is to probe systemic forms of racism, as well as to suggest strategies for addressing them. The collection is organized by themes pertinent to political and social expressions of racism in Canada and the wider world, such as the state and its mediation of race, education and the perpetuation of racist marginalization, and the role of the media. The contributors argue that, in order to effectively combat racism, various methodological approaches are required, approaches that are reflective of the diversity of the world we seek to understand. -- Publisher's description. Contents: Introduction / Audrey Kobayashi and Genevieve Fuji Johnson -- Negotiating school: marginalized students' participation in their education process / Carl E. James -- Multicultural education: teacher candidates speak out / Donatille Mujawamariya -- The sky didn't fall: organizing to combat racism in the workplace -- the case of the alliance for employment equity / Abigail B. Bakan and Audrey Kobayashi -- Employment conditions of racial minorities in Canada: how bad is the problem of discrimination? / Mohammed A. Al-Waqfi and Harish C. Jain -- Immigrant women's activism: the past thirty-five years / Tania Das Gupta -- Critical discourse analysis: a powerful but flawed tool? / Frances Henry and Carol Tator -- Special plus and special negative: the conflict between perceptions and applications of 'special status' in Canada / Howard Ramos -- Who belongs? Expoloring race and racialization in Canada / Leanne Taylor, Carl E. James, and Roger Saul -- The racialization of space: producng surrey / Gurpreet Singh Johal -- Raceless states / David Theo Goldberg -- Multi-identifications and transformations: reaching beyond racial and ethnic reductionisms / Philomena Essed.
Keywords: Canada; Employment discrimination; Equity; Racism

Corporate Wasteland: The Landscape and Memory of Deindustrialization - Lewis, David; High, Steven C. (Between the Lines, 2007)
Deindustrialization is not simply an economic process; it is also a social and cultural phenomenon. The rusting detritus of our industrial past — the wrecked halls of factories, abandoned machinery too large to remove, and now useless infrastructures — has for decades been a part of the North American landscape. Through a unique blend of oral history, photographs, and interpretive essays, [this book] investigates this fascinating terrain and the phenomenon of its loss and rediscovery. --Publisher's description

Industrial Relations in Canada - McQuarrie, Fiona A. E. (Wiley and Sons Canada, 2007)
Makes it easier to understand the complex and sometimes controversial field of industrial relations. How? Its unique process-oriented approach gives you a clear road map by illustrating how and why unions are formed, and introduces you to the Canadian industrial relations system and the forces that shape it. --Publisher's description
Keywords: Industrial relations -- Canada -- Textbooks

Defining Work: Gender, Professional Work, and the Case of Rural Clergy - Mellow, Muriel (McGill-Queen's University Press, 2007)
An illuminating study of how gender and work intersect among the rural clergy. For rural clergy, the lines between private life and professional life can blur. Their offices are often in their homes, parishioners are also neighbours, and professional duties are intertwined with emotional caregiving and volunteer activity. In a society that defines work as paid, public, and intellectual the ambiguity inherent in the life of the rural clergy poses unique challenges. Muriel Mellow considers how men and women in this occupational group conceptualize "work" in the context of their unique circumstances and shows how their experience raises questions for feminist theories of work. Based on interviews with forty rural Protestant clergy, Mellow argues that male and female clergy challenge gendered definitions of work by focusing on obligation, context, visibility, and time. She also considers how clergy's work is shaped by the rural setting, arguing that we must consider how work is "placed" as well as gendered. --Publisher's description

Working People: An Illustrated History of the Canadian Labour Movement - Morton, Desmond (McGill-Queen's University Press, 2007)
From the dock workers of Saint John in 1812 to teenage "crews" at McDonald's today, Canada's trade union movement has a long, exciting history. Working People tells the story of the men and women in the labour movement in Canada and their struggle for security, dignity, and influence in our society. Desmond Morton highlights the great events of labour history - the 1902 meeting that enabled international unions to dominate Canadian unionism for seventy years, the Winnipeg General Strike of 1919, and an obscure 1944 order-in-council that became the labour's charter of rights and freedoms. He describes the romantic idealism of the Knights of Labor in the 1880s and looks at "new model" unions that used their members' dues and savings to fight powerful employers. Working People explores the clash between idealists, who fought for socialism, industrial democracy, and equality for women and men, and the realists who wrestled with the human realities of self-interest, prejudice, and fear. Morton tells us about Canadians who deserve to be better known - Phillips Thompson, Helena Gutteridge, Lynn Williams, Huguette Plamondon, Mabel Marlowe, Madeleine Parent, and a hundred others whose struggle to reconcile idealism and reality shaped Canada more than they could ever know. -- Publisher's description. Contents: Working people -- Getting organized -- International ideas -- Political movement -- Labour reformers -- Hinterland labour -- Trades and labour -- Gompers's shadow -- Business, labour, and governments -- Labour radicals -- Labour and the first World War -- Western revolt -- Unroaring twenties -- Surviving the depression -- Industrial unionism -- Fighting Hitler and management -- "People coming into their own" -- No falling back -- Struggle for allegiance -- Merger movement -- Times of frustration -- Prosperity and discontent -- Public Interest, Public Service -- Justice and nationalism -- Quebec and the common front -- Scapegoat for inflation -- Recession and hard times -- Levelling the playing field -- Struggling to the millennium -- Millennial achievements -- Graphs: Changes in the labour movement.
Keywords: Labor Unions; Labor movement; Working class

Confrontation, Struggle and Transformation: Organized Labour in the St. Catharines Area - Patrias, Carmela; Savage, Larry (Past CCLH Publications, 2007)
Confrontation, Struggle and Transformation is the story of working women and men in the St. Catharines area from the mid-1800s to the present. The study explores the labour movement's fight to survive and thrive in the Niagara region. Thanks to extensive quotations from interviews, archival sources and local newspapers, the story unfolds, in part, through the voices of the people themselves: workers who fought for unions, community members who supported them and employers who opposed them. --Publisher's description
Keywords: Discrimination in employment; History; Labor Unions; Labor movement; Political activity

Equity, Diversity, and Canadian Labour - Rayside, David M.; Hunt, Gerald (University of Toronto Press, 2007)
The Canadian labour movement has undergone several fundamental changes in response to demands for greater inclusion and representation by women, visible and sexual minorities, and people with disabilities. Equity, Diversity, and Canadian Labour explores the specific challenges put to outmoded conceptions of labour, charting the effort made towards establishing a more inclusive vision of labour in Canada. The study concludes that the Canadian labour movement has seen a fair amount of progress in this regard, though it still faces persistent impediments to equity and suffers from an uneven responsiveness within and across diversity issues. This collection of original essays brings together contributors from a variety of backgrounds womens studies, political science, sociology, industrial relations, and the labour movement itself. They provide detailed analyses of significant changes in union policies, practices, and cultures as viewed through different disciplinary lenses. With reference to gender, race, disability, and sexuality, the volume assesses the status of labour diversity in Canada and suggests what still needs to be done to advance the equity project. --Publisher's description. --Publisher's description. Contents: Looking back: A brief history of everything / Julie White -- Bargaining against the past: Fair pay, union practice, and the gender pay gap / Anne Forrest -- Union response to pay equity: A cautionary tale / Judy Haiven -- Labour's collective bargaining records on women's and family issues / Karen Bentham -- We are family: Labour responds to gay, lesbian, bisexual, and transgender workers / Gerald Hunt and Jonathan Eaton -- Broadening the labour movement's disability agenda / David Rayside and Fraser Valentine -- Racism and the labour movement / Tania Das Gupta -- Equity, diversity, and Canadian labour: A comparative perspective / David Rayside. Includes bibliographical references (pages 257-282).
Keywords: Activit politique. Mouvement ouvrier; Aspect social; Canada; Canada. Dmocratie syndicale; Canada. Genre/Form: Aufsatzsammlung; Canada. Labor movement; Canada. Labor movement. Labor union democracy. Labor unions; Canada. Labor union democracy; Canada. Labor unions; Canada. Pay equity; Canada. Syndicats; Canada. galit de rmunration; Labor unions; Political activity; Political activity. Labor unions; Social aspects; Social aspects. Pay equity. Arbeiterbewegung Gewerkschaft Syndicats

Labour and Employment Law in the Federal Public Service - Rootham, Christopher (Irwin Law, 2007)
[D]escribes the labour and employment law governing employees of Parliament, employees of government agencies, members of the RCMP, and most direct employees of the government (excluding members of the Canadian armed forces, judges, and employees of Crown corporations). Specifically, the book deals with the Public Service Labour Relations Act and the Public Service Employment Act. It also provides the leading cases and, where appropriate, a representative sample of decisions to explain or provide examples of particular points. The legal regime of the federal public service has undergone significant change in the past three years, and no other book addresses these significant changes. Part I of this book provides an overview of federal public service labour and employment law. Part II considers the normal labour law topics as they apply to direct employees of the government and employees of government agencies. Essentially, Part II of this book is about Part I of the Public Service Labour Relations Act. Part III concerns the terms and conditions of employment for both unionized and non-unionized employees — essentially, Part II of the Public Service Labour Relations Act. Part IV involves the legal regulation of the employment relationship in the federal public service — namely, the process for appointment to and within the federal public service. Part V of considers Crown servants — specifically RCMP members and parliamentary employees — who are not considered federal public servants for the purposes of the Public Service Labour Relations Act. Part VI considers the legal regulation of superannuation (pensions) for Crown servants and the role that courts play in the regulation of federal public service labour and employment law. --Publisher's description
Keywords: Canada; Civil service; Labor laws and legislation; Royal Canadian Mounted Police (RCMP)

Work in Tumultuous Times: Critical Perspectives - Shalla, Vivian; Clement, Wallace (McGill-Queen's University Press, 2007)
This interdisciplinary volume offers a powerful critique of how social structures and relations as well as ideologies shape workplaces, labour markets, and households in contemporary Canada. Contributors dissect recent transformations in work and expose the uncertainty, insecurity, and instability that increasingly characterize both paid and unpaid work. Using a progressive approach to political economy, contributors propose alternative policies and practices that might secure more decent livelihoods for workers and their families. -- Publisher's description
Keywords: Discrimination in employment; Job security; Labor

Labour Left Out: Canada's Failure to Protect and Promote Collective Bargaining as a Human Right - Adams, Roy J. (Canadian Centre for Policy Alternatives, 2006)
[The author] reports on his research into the failure of Canadian governments to protect and promote the collective bargaining rights of both unionized and non-unionized workers in this country. Far from honouring their solemn commitments to the UN’s International Labour Organization, our governments have blatantly and repeatedly violated them. Their many strike-breaking actions and arbitrarily imposed contract settlements have been condemned by the ILO, which has cited Canada as one of the world’s worst violators of basic labour rights. In exposing the appalling anti-labour record of our federal and provincial governments, Adams includes his exchange of correspondence with Canada’s labour ministries on their dismal labour-law policies. --Publisher's summary
Keywords: Collective bargaining -- Canada

Vers une transformation des relations industrielles en Amérique du Nord - Bernatchez, Jean-Claude (Gestion des relations humaines - Relations industrielles, 2006)
Dans un contexte où il semble impossible d’établir, ou encore de maintenir, un régime national de conditions de travail reflétant le niveau de prospérité observable dans les sociétés nord-américaines, la transformation des relations industrielles semble le moyen le plus sûr de rétablir l’équilibre entre le capital et le travail. En s’appuyant sur les fondements historiques des relations industrielles en Amérique du Nord, l’auteur dresse le portrait des syndicalismes américain, canadien et québécois, en tenant compte des lois qui les sous-tendent. Afin d’élaborer un nouveau régime de relations industrielles, il pose les principes à respecter et définit les étapes à franchir en vue d’instaurer de bonnes conditions de travail, garantissant ainsi une meilleure qualité de vie aux citoyens américains et canadiens. --Résumé de l'éditeur
Keywords: 2000-2099; 21e siècle; Amérique du Nord; Collective bargaining; Collective bargaining North America; Conditions de travail; Industrial relations; Industrial relations North America; North America; Négociation collective; Négociations collectives Amérique du Nord; Relations de travail; Relations industrielles; Relations industrielles Amérique du Nord; Syndicalisme; Travailleurs Amérique du Nord Conditions sociales 20e siècle; Travailleurs Amérique du Nord Conditions sociales 21e siècle; Working class North America Social conditions 21st century; Working class Social conditions; industrial relations

Social Reproduction: Feminist Political Economy Challenges Neo-Liberalism - Bezanson, Kate; Luxton, Meg (McGill-Queen's University Press, 2006)
How the unaccounted costs of neo-liberal policies fall on Canadian women. Using a feminist political economy approach, contributors document the impact of current socio-economic policies on states, markets, households, and communities. Relying on impressive empirical research, they argue that women bear the costs of and responsibility for care-giving and show that the theoretical framework provided by feminist analyses of social reproduction not only corrects the gender-blindness of most economic theories but suggests an alternative that places care-giving at its centre. In this illuminating study, they challenge feminist scholars to re-engage with materialism and political economy to engage with feminism. --Publisher's description. Contents: Introduction: Social Reproduction and Feminist Political Economy / Kate Bezanson and Meg Luxton (pages 3-10) -- Feminist Political Economy in Canada and the Politics of Social Reproduction / Meg Luxton (pages 11-44) -- Social Reproduction and Canadian Federalism / Barbara Cameron (pages 45-74) -- Whose Social Reproduction? Transnational Motherhood and Challenges to Feminist Political Economy / Sedef Arat-Koç (pages 75-92) -- Bargaining for Collective Responsibility for Social Reproduction / Alice De Wolff (pages 93-116) -- Privatization: A Strategy for Eliminating Pay Equity in Health Care / Marjorie Griffin Cohen and Marcy Cohen (pages 117-144) -- Crisis Tendencies in Social Reproduction: The Case of Ontario’s Early Years Plan / Leah F. Vosko (pages 145-172) -- The Neo-liberal State and Social Reproduction: Gender and Household Insecurity in the Late 1990s / Kate Bezanson (pages 173-214) -- Someone to Watch over You: Gender, Class, and Social Reproduction / Susan Braedley (pages 215-230) -- Motherhood as a Class Act: The Many Ways in Which “Intensive Mothering” Is Entangled with Social Class / Bonnie Fox (pages 231-262) -- Friends, Neighbours, and Community: A Case Study of the Role of Informal Caregiving in Social Reproduction / Meg Luxton (pages 263-92 ).

Push! The Struggle for Midwifery in Ontario - Bourgeault, Ivy Lynn (McGill-Queen's/Associated Medical Services (Hannah Institute) studies in the history of medicine, health, and society, 2006)
In the 1980s there were few midwives in Canada and their practice was neither legal nor officially recognized. Ontario midwives and their supporters pushed to integrate midwifery into provincial health care systems and by 1993 had established an internationally renowned model. Ivy Lynn Bourgeault analyses the struggle to professionalize midwifery in the context of the negotiations between women, as both consumers and providers of health care, and the state. Push! offers a historical account of the forces behind the integration of midwifery in Ontario, including public interest in funding midwifery services and the impact of political lobbying. Bourgeault also explores the specific features of Ontario's respected model, including the use of independent practitioners, funding for a self-regulatory college, a university-based education program, and the provision of midwifery care in both home and hospital settings. --Publisher's description
Keywords: Government policy; History; Home childbirth; Midwifery; Midwives; Ontario; Political aspects

The Hanging of Angélique: The Untold Story of Canadian Slavery and the Burning of Old Montréal - Cooper, Afua (Race in the Atlantic World, 1700-1900, 2006)
During the night of April 10, 1734, Montréal burned. Marie-Joseph Angélique, a twenty-nine-year-old slave, was arrested, tried, and found guilty of starting the blaze that consumed forty-six buildings. Suspecting that she had not acted alone and angered that she had maintained her innocence, Angélique's condemners tortured her after the trial. She confessed but named no accomplices. Before Angélique was hanged, she was paraded through the city. Afterward, her corpse was burned. Angélique, who had been born in Portugal, faded into the shadows of Canadian history, vaguely remembered as the alleged arsonist behind an early catastrophic fire. The result of fifteen years of research, [this book] vividly tells the story of this strong-willed woman. Afua Cooper draws on extensive trial records that offer, in Angélique's own words, a detailed portrait of her life and a sense of what slavery was like in Canada at the time. Predating other first-person accounts by more than forty years, these records constitute what is arguably the oldest slave narrative in the New World. Cooper sheds new light on the largely misunderstood or ignored history of slavery in Canada. She refutes the myth that Canada was a haven at the end of the Underground Railroad. Cooper also provides a context for Canada in the larger picture of transatlantic slavery while re-creating the tragic life of one woman who refused to accept bondage. --Publisher's description
Keywords: 18e siècle. Esclaves; 18e siècle. Fires. Slaves; 18e siècle. Noires; 18th century. Esclaves; Biographies. Esclavage; Biographies. Incendies; Biography. Fires; Canada; Commerce; Histoire; History; Montréal; Québec (Province); Slaves

Globalization and the Future of Labour Law - Craig, John D. R.; Lynk, Michael (Cambridge University Press, 2006)
How are national and international labour laws responding to the challenge of globalization as it re-shapes the workplaces of the world? This collection of essays by leading legal scholars and lawyers from Europe and the Americas was first published in 2006. It addresses the implications of globalization for the legal regulation of the workplace. It examines the role of international labour standards and the contribution of the International Labour Organization, and assesses the success of the European experiment with continental employment standards. It explores the prospects for hemispheric co-operation on labour standards in the Americas, and deals with the impact of international labour standards on the rights of women and migrant workers. As the nature and organization of work around the world is being decisively transformed, new regional and international institutions are emerging that may provide the platform for new labour standards, and for protecting existing ones. --Publisher's description
Keywords: Americas; Amériques; Droit du travail; European Union; Futur; Globalization; International Labour Organization; International labour law; Labor laws and legislation; Labor laws and legislation, International; Labour law; Labour standards; Mondialisation; Normes de travail; Normes internationales; Organisation internationale du travail; Travail (Droit international); UE/CE Union européenne

Women and Their Work in Upper Canada - Errington, Elizabeth Jane (Historical Booklet / Canadian Historical Association, 2006)

Red Light Neon: A History of Vancouver's Sex Trade - Francis, Daniel (Subway, 2006)
"This book is a history of hypocrisy." So begins Daniel Francis, BC's leading popular historian, as he explores the colourful and ultimately tragic story of prostitution in Vancouver. He writes: "The city's political and social leaders consistently have treated prostitutes as pariahs whose presence was tolerated, sometimes exploited, but never approved. All the while, the authorities collected millions of dollars in fines and licence fees from businesses that everyone knew were, and are, fronts for the sex trade." Working in long overlooked archives and drawing on personal interviews, Francis shows how in some ways commercial sex has been both a reflection and a result of Vancouver's essential character, with its tolerant social mores, ethnic diversity--and political opportunism. It's a tale that takes in mayors and masseuses, police chiefs and pimps, judges and johns. Francis explains: "Sex workers have never lacked for customers. What they have lacked is a secure place to conduct their business. A vast off-street sex trade flourished while police, at the urging of politicians vowing to purify the city, concentrated their attention on the comparatively small number of street prostitutes who worked out in the open. Because they were considered a nuisance, these sex workers were hounded from street to street and neighbourhood to neighbourhood [... These efforts salved the conscience of the morally righteous, but each attempt to discourage prostitution simply forced women to work in increasingly dangerous circumstances." The end result, ultimately, was the tragedy of the Missing Women--murdered sex workers from the Downtown Eastside--and the sensational criminal case that followed. --Publisher's description
Keywords: Prostitution -- British Columbia -- Vancouver -- History

Working on Screen: Representations of the Working Class in Canadian Cinema - Khouri, Malek; Varga, Darrell (University of Toronto Press, 2006)
As themes in film studies literature, work and the working class have long occupied a peripheral place in the evaluation of Canadian cinema, often set aside in the critical literature for the sake of a unifying narrative that assumes a division between Québécois and English Canada's film production, a social-realist documentary aesthetic, and what might be called a 'younger brother' relationship with the United States. In Working on Screen, contributors examine representations of socio-economic class across the spectrum of Canadian film, video, and television, covering a wide range of class-related topics and dealing with them as they intersect with history, political activism, globalization, feminism, queer rights, masculinity, regional marginalization, cinematic realism, and Canadian nationalism. Of concern in this collection are the daily lives and struggles of working people and the ways in which the representation of the experience of class in film fosters or marginalizes a progressive engagement with history, politics, and societies around the world. Working on Screen thus expands the scholarly debates on the concept of national cinema and builds on the rich, formative efforts of Canadian cultural criticism that held dear the need for cultural autonomy. -- Publisher's description

Paths to Union Renewal: Canadian Experiences - Kumar, Pradeep; Schenk, Christopher Robert (Broadview Press, 2006)
This book focuses on the efforts and progress of union revitalization and organizing, and documents the renewal initiatives undertaken by unions in Canada. Unions, separately or in coalition with other unions or social groups, have begun to re-examine the basis of their organization and activity in the face of a harsher economic and political climate. Signs of union renewal include increased rank-and-file participation in the life of the union, increased democratic decision-making, evidence of new horizontal union structures, the development of a worker-centred societal vision, and a new emphasis on organizing both internally and externally. Paths to Union Renewal addresses a subject of considerable political and social importance about which there have been a number of debates. A key impetus for this re-examination has originated in the United States where decades-long union decline has engendered new ideas adopted by a number of unions and the national central labour body the AFL-CIO. This in turn has led to debates on renewal strategies in Western Europe and Anglo-Saxon countries from Britain to Australia. Despite this, little detailed research of the processes, structures, and implications of union renewal has been undertaken across Canada. Paths to Union Renewal fills this gap by critically examining union renewal in a variety of unions, providing a basis for informed discussion and debate on the role and place of trade unions in contemporary society. --Publisher's description
Keywords: British Columbia Federation of Labour. Organizing Institute; British Columbia Government and Service Employees Union (BCGEU); Canadian Auto Workers (CAW); Canadian Union of Public Employees (CUPE); Communications, Energy and Paperworkers Union of Canada (CEP); Community unionism; Labor Unions; Labor movement; Organizational change; United Food and Commerical Workers (UFCW); United Steelworkers (USW)

Bloodletting & Miraculous Cures: Stories - Lam, Vincent. (Doubleday Canada, 2006)
Bloodletting & Miraculous Cures is a collection of mature and intricate stories connected through the relationships that develop among a group of young doctors as they move from the challenges of med school to the intense world of emergency rooms, evac missions, and terrifying new viruses. --Publisher's description. Contents: How to get into medical school, part I -- Take all of Murphy -- How to get into medical school, part II -- Code clock -- A long migration -- Winston -- Eli -- Afterwards -- An insistent tide -- Night flight -- Contact tracing -- Before light -- Glossary of terms -- Acknowledgements.
Keywords: Doctor; Medical Students; Physicians; Short Stories; White-collared work

Red Travellers: Jeanne Corbin and Her Comrades - Lévesque, Andrée (McGill-Queen's University Press, 2006)
Jeanne Corbin typifies the female militants of the first generation of Canadian Communists. Andrée Lévesque's powerful account of the experiences of Corbin and her female comrades reveals the essential role women played in the movement. Levesque also shows that, despite some efforts to construct egalitarian gender relations, these women subordinated gender issues to the class struggle. Corbin's red itinerary began when she joined the Young Communist League in Edmonton. She later held party posts across the country through her involvement with The Worker in Toronto, a French communist paper in Montreal, the Workers' Cooperative in Timmins, and a lumbermen's strike in Abitibi - where she was jailed for taking part in a protest. She died of tuberculosis in London, Ontario, in 1944. Levesque relies on a wide range of sources to provide a unique exploration of Canadian labour and social history. --Publisher's descriptioin

Social Reproduction: Feminist Political Economy Challenges Neo-Liberalism - Luxton, Meg; Bezanson, Kate (McGill-Queen's University Press, 2006)
Using a feminist political economy approach, contributors document the impact of current socio-economic policies on states, markets, households, and communities. Relying on impressive empirical research, they argue that women bear the costs of and responsibility for care-giving and show that the theoretical framework provided by feminist analyses of social reproduction not only corrects the gender-blindness of most economic theories but suggests an alternative that places care-giving at its centre. In this illuminating study, they challenge feminist scholars to re-engage with materialism and political economy to engage with feminism. -- Publisher's description
Keywords: Canada; Discrimination à l'égard des femmes Canada; Feminist economics; Feminist economics Canada; Feminist theory; Feminist theory Canada; Femmes Canada Conditions sociales; Femmes Canada Conditions économiques; SOCIAL SCIENCE Feminism & Feminist Theory; SOCIAL SCIENCE Sociology General; Sex discrimination against women; Sex discrimination against women Canada; Théorie féministe Canada; Women Canada Economic conditions; Women Canada Social conditions; Women Economic conditions; Women Social conditions; Économie féministe Canada

Canadian Working-Class History: Selected Readings - MacDowell, Laurel Sefton; Radforth, Ian Walter (Canadian Scholars' Press, 2006)
[This book updates] recent and classic scholarship on the history, politics, and social groups of the working class in Canada. Some of the changes...in the new edition include better representation of women scholars and nine provocative and ground-breaking new articles on racism and human rights; women's equality; gender history; Quebec sovereignty; and the environment. --Publisher's description
Keywords: Equality; History; Human rights; Labor Unions; Labor movement; Labour; Racism; Social history; Women; Working class; labour rights

Working Class Culture and the Development of Hull, Quebec, 1800-1929 - Martin, Michael (J. Bernier, 2006)
...This [book], most decidedly, is not only the narrative of the prominent citizens in the history of Hull. Rather, it is the story of thousands of virtually unknown men, women, and children of the working class of Hull, Quebec. Among many others, it’s the story of James McConnell, a worker from Nova Scotia, hired by Philemon Wright in Quebec City in 1801. It’s the story of Luther Colton, a carpenter from New York, who came to Hull in 1802. It’s the story of Joseph Delorme, one of the first French Canadians to be hired by Philemon Wright to work in his shanties, just to give three examples of normally unnamed workers. This study of the ordinary people of Hull reflects an agenda that emerged in the last half of the 20th century when historians came to see that “the real task of history in our time is to recreate, appreciate and analyze the full spectrum of past societies; that means, pre-eminently to attempt to understand the lives of the working people, the great mass of any society,” rather than merely the politicians and elites who governed past societies. This book also studies the workers who helped the workers of Hull forge an awareness of themselves as a class in a self-conscious attempt to improve the lot of ordinary working people. --Author's preface
Keywords: History; Hull (Gatineau, Québec) History; Hull (Gatineau, Québec) Social conditions; Québec Gatineau Hull; Social conditions; Working class; Working class Hull (Gatineau, Québec) History

Apprivoiser le syndicalisme en milieu universitaire: histoire du syndicat genéral des professeurs et professeures de l'Université de Montréal - Rouillard, Jacques (Boréal, 2006)
Un syndicat de professeurs d’université n’est pas un syndicat comme les autres. L’individualisme inhérent au travail et à la culture professorale a toujours contribué à rendre plusieurs d’entre eux méfiants et plutôt réservés face à la solidarité syndicale. Chez les professeurs, le « nous » syndical s’est graduellement construit, par étapes, parfois dans la tourmente et la division. C’est ce cheminement des universitaires, cet «apprivoisement» du syndicalisme, qui est l’objet de ce volume. La conscience syndicale chez les professeurs commence véritablement à prendre racine avec la création du Syndicat des professeurs en 1966. Elle aboutit à la formation du SGPUM en 1972 et à son accréditation trois ans plus tard. Dans les années 1980 et 1990 l’utilité du syndicalisme ne fait plus de doute chez les professeurs, frappés par de faibles augmentations salariales, quand ce n’est pas des gels et des récupérations. Dans les années 2000, leur solidarité se renforce avec l’objectif de rattrapage des conditions de travail qui va culminer avec la première grève des professeurs en hiver 2005. Jacques Rouillard propose ici un historique de quarante ans de vie syndicale et de plus de cinquante ans de vie associative. Soucieux également d’insérer l’évolution du syndicat dans la trame générale de l’histoire du syndicalisme québécois, il accorde une large place dans cet historique aux négociations des syndicats des secteurs public et parapublic. --Résumé de l'éditeur

Working in a Global Era: Canadian Perspectives - Shalla, Vivian (Canadian Scholars Press, 2006)
This progressive new reader examines work in a global era. It is an ideal text for sociology of work and labour courses across Canada. This book will also be relevant to a wide range of courses in labour studies and industrial relations programs in Canada." "Divided into eight key parts with a total of 16 essential readings, this volume covers a great deal of ground: Fordist and post-Fordist methods of work organization; labour markets in transition; working in the free-trade zones; migration, transnationalism, and domestic work; neo-liberalism and the dismantling of the welfare state; education, training, and skills in a knowledge-based economy; and the labour movement in transition. All major issues surrounding work in Canada are covered. Book jacket. --Publisher's description
Keywords: Labor -- Canada -- Textbooks

Home Economics: Nationalism and the Making of 'Migrant Workers' in Canada - Sharma, Nandita Rani (University of Toronto Press, 2006)
Home Economics is an urgent and much-needed reminder that society must pay careful attention to how nationalist ideologies construct ‘homelands’ that essentially leave the vast majority of the world's migrant peoples homeless. A massive shift has taken place in Canadian immigration policy since the 1970s: the majority of migrants no longer enter as permanent residents but as temporary migrant workers. In Home Economics, Nandita Sharma shows how Canadian policies on citizenship and immigration contribute to the entrenchment of a system of apartheid where those categorized as migrant workers live, work, pay taxes and sometimes die in Canada but are subordinated to a legal regime that renders them as perennial outsiders to nationalized Canadian society. In calling for a no borders policy in Canada, Sharma argues that it is the acceptance of nationalist formulations of home informed by racialized and gendered relations that contribute to the neo-liberal restructuring of the labour market in Canada. She exposes the ideological character of Canadian border control policies which, rather than preventing people from getting in, actually work to restrict their rights once within Canada. Home Economics is an urgent and much-needed reminder that in today's world of growing displacement and unprecedented levels of international migration, society must pay careful attention to how nationalist ideologies construct homelands that essentially leave the vast majority of the world's migrant peoples homeless. --Publisher's description
Keywords: Ausländischer Arbeitnehmer; Canada; Canada Emigration and immigration Government policy; Canada Émigration et immigration Politique gouvernementale; Capitalism; Capitalisme; Einwanderung; Electronic books; Emigration and immigration Government policy; Foreign workers Government policy; Foreign workers Government policy Canada; Globalization; Kanada; Kapitalismus; Mondialisation; Travailleurs étrangers Politique gouvernementale Canada; capitalism; globalism

The Struggle Against Wage Controls: The Saint John Story, 1975-1976 - Vair, George; Canadian Committee on Labour History (Past CCLH Publications, 2006)
In October 1976 one million Canadian workers walked off the job to protest the wage controls imposed by Prime Minister Pierre Elliott Trudeau. In a memorable personal account of this historic general strike, Saint John labour activist George Vair recalls how workers in one New Brunswick city mobilized to defend themselves and their unions and defeat the unpopular program. --Publisher's description
Keywords: General Strike, Saint John, N.B., 1976; Government policy; History; Labor movement; Strikes and lockouts; Wages

Precarious Employment: Understanding Labour Market Insecurity in Canada - Vosko, Leah F. (McGill-Queen's University Press, 2006)
This interdisciplinary volume offers a multifaceted picture of precarious employment and the ways in which its principal features are reinforced or challenged by laws, policies, and labour market institutions, including trade unions and community organizations. Contributors develop more fully the concept of precarious employment and critique outmoded notions of standard and nonstandard employment. The product of a five-year Community-University Research Alliance, the volume aims to foster new social, statistical, legal, political, and economic understandings of precarious employment and to advance strategies for improving the quality and conditions of work and health. --Publisher's description
Keywords: Industrial hygiene; Labor Unions; Labor laws and legislation; Labor market; Temporary employment

Mine Mill Fights Back: Mine Mill/CAW Local 598 Strike 2000-2001, Sudbury - Beck, Kaili; Kinsman, Gary; Steedman, Mercedes; Suschnigg, Peter; Bowes, Chris (Mine Mill / CAW Local 598, 2005)
Illustrated history of the 2000-2001 strike of the Mine Mill/Canadian Auto Workers Local 598 strike against Falconbridge in Sudbury, Ont. Published in collaboration with Laurentian University's Labour and Trade Union Studies' Program.
Keywords: History; Labor Unions; Mineral industries; Miners; Social aspects; Strikes and lockouts

Structure and Operation of the Steelworkers - Brasch, Hans (Journal Printers, 2005)
Abundantly illustrated update of "A Miner's Chronicle" from 1998 to 2004, that emphasizes union-related activities and events. Also includes a list of mining fatalities.
Keywords: History; Labor Unions; Miners; Sudbury, Ont.; United Steelworkers of America. Local 6500

From UI to EI: Waging War on the Welfare State - Campeau, Georges; Howard, Richard (Law and society series (Vancouver, B.C.), 2005)
Established in 1940 in response to the Great Depression, the original goal of Canada’s system of unemployment insurance was to ensure the protection of income to the unemployed. Joblessness was viewed as a social problem and the jobless as its unfortunate victims. If governments could not create the right conditions for full employment, they were obligated to compensate people who could not find work. While unemployment insurance expanded over several decades to the benefit of the rights of the unemployed, the mid-1970s saw the first stirrings of a counterattack as the federal government’s Keynesian strategy came under siege. Neo-liberalists denounced unemployment insurance and other aspects of the welfare state as inflationary and unproductive. Employment was increasingly thought to be a personal responsibility and the handling of the unemployed was to reflect a free-market approach. This regressive movement culminated in the 1990s counter-reforms, heralding a major policy shift. The number of unemployed with access to benefits was halved during that time. From UI to EI examines the history of Canada’s unemployment insurance system and the rights it grants to the unemployed. The development of the system, its legislation, and related jurisprudence are viewed through a historical perspective that accounts for the social, political, and economic context. Campeau critically examines the system with emphasis upon its more recent transformations. This book will interest professors and students of law, political science, and social work, and anyone concerned about the right of the unemployed to adequate protection. --Publisher's description. Contents: Why UI? -- The British Act of 1911 -- Developing a Canadian system -- The UI Act of 1940 -- UI expansion, 1940-75 -- Vision under siege, 1975-88 -- Rights enshrined in case law, 1940-90 -- The system hijacked, 1989-96 -- Onward to EI -- Case law in the neoliberal riptide of the 1990s. Translation of: De l'assurance-chômage à l'assurance-emploi.
Keywords: History; Law and legislation; Unemployment insurance

Self-Employed Workers Organize: Law, Policy, and Unions - Cranford, Cynthia; Fudge, Judy; Tucker, Eric; Vosko, Leah F. (McGill-Queen's University Press, 2005)
Over a million self-employed Canadians work every day but many of them are not entitled to the basic labour protections and rights such as minimum wages, maternity and parental leaves and benefits, pay equity, a safe and healthy working environment, and access to collective bargaining. The authors of "Self-Employed Workers Organize" offer a multi-disciplinary examination of the legal, political, and social realities that both limit collective action by self-employed workers and create huge impediments for unions attempting to organize them. Through case studies of newspaper carriers, rural route mail couriers, personal care workers, and freelance editors - four groups who have led pioneering efforts to organize - the authors provide a window into the ways political and economic conditions interact with class, ethnicity, and gender to shape the meaning and strategies of working men and women and show how these strategies have changed over time. They argue that the experiences of these workers demonstrate a pressing need to expand collective bargaining rights to include them. --Publisher's description
Keywords: Case studies; Labor unions; Legal status, laws, etc.; Organizing; Self-employed

Discounted Labour: Women Workers in Canada, 1870-1939 - Frager, Ruth A.; Patrias, Carmela (Themes in Canadian history, 2005)
The years between 1870 and 1939 were a crucial period in the growth of industrial capitalism in Canada, as well as a time when many women joined the paid workforce. Yet despite the increase in employment, women faced a difficult struggle in gaining fair remuneration for their work and in gaining access to better jobs. Discounted Labour analyses the historical roots of women's persistent inequality in the paid labour force. Ruth A. Frager and Carmela K. Patrias analyse how and why women became confined to low-wage jobs, why their work was deemed less valuable than men's work, why many women lacked training, job experience, and union membership, and under what circumstances women resisted their subordination. Distinctive earning discrepancies and employment patterns have always characterized women's place in the workforce whether they have been in low-status, unskilled jobs, or in higher positions. For this reason, Frager and Patrias focus not only on women wage-earners but on women as salaried workers as well. They also analyze the divisions among women, examining how class and ethnic or racial differences have intersected with those of gender. Discounted Labour is an essential new work for anyone interested in the historical struggle for gender equality in Canada. --Publisher's description
Keywords: 19th century; 20th century; Canada; Employment; History; Sexual division of labor; Women

Bora Laskin: Bringing Law to Life - Girard, Philip (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2005)
In the history of twentieth-century Canadian law, Bora Laskin (1912-1984) is by all accounts one of its most important figures. Born in northern Ontario to Russian-Jewish immigrant parents, Laskin became a prominent human rights activist, university professor, and labour arbitrator before embarking on his 'accidental career' as a judge on the Ontario Court of Appeal, a member of the Supreme Court of Canada, and Chief Justice of Canada. Throughout his entire professional life, he used the law to make Canada a better place for workers, racial and ethnic minorities, and the disadvantaged. As a judge, he sought to make the judiciary more responsive to changing expectations in regard to justice and fundamental rights." "In this biography, Philip Girard chronicles the life of a man who fought corporate capital, university boards, the Law Society of Upper Canada, and his own judicial colleagues in an effort to modernize institutions and reshape Canadian law. Girard draws on a wealth of previously untapped archival sources to provide, in vivid detail, a critical assessment of the contributions of a dynamic man on an important mission. --Book cover description
Keywords: Biographies; Biographies, memoirs and correspondance; Canada; Canada. Cour suprême Biographies; Canada. Supreme Court; Canada. Supreme Court Biography; Canada. Supreme Court History; Electronic books; Judges; Judges Canada Biography; Juges Canada Biographies; Laskin, Bora; Supreme court

Ontario Public Service Employment & Labour Law - Hadwen, Timothy; Eady, Don; Marvy, Leonard; Strang, David (Irwin Law, 2005)
This book deals with the Crown Employees Collective Bargaining Act and the Public Service Act, the statutes that primarily govern unionized and non-unionized employment and labour relations in the Ontario Public Service and Crown Agencies. The book provides a full review of all sections, and all judicial and arbitral consideration, of both acts. It also discusses the unique treatment of the Crown and its employees in the Public Sector Labour Relations Transition Act and the Employment Standards Act.
Keywords: Civil service; Collective labor agreements; Employee-management relations in government; Government employees; Law and legislation; Ontario

The Workers' Festival: A History of Labour Day in Canada - Heron, Craig; Penfold, Steve (University of Toronto Press, 2005)
For most Canadians today, Labour Day is the last gasp of summer fun: the final long weekend before returning to the everyday routine of work or school. But over its century-long history, there was much more to the September holiday than just having a day off. In The Workers' Festival, Craig Heron and Steve Penfold examine the complicated history of Labour Day from its origins as a spectacle of skilled workers in the 1880s through its declaration as a national statutory holiday in 1894 to its reinvention through the twentieth century. The holiday's inventors hoped to blend labour solidarity, community celebration, and increased leisure time by organizing parades, picnics, speeches, and other forms of respectable leisure. As the holiday has evolved, so too have the rituals, with trade unionists embracing new forms of parading, negotiating, and bargaining, and other social groups re-shaping it and making it their own. Heron and Penfold also examine how Labour Day's monopoly as the workers' holiday has been challenged since its founding, with alternative festivals arising such as May Day and International Women's Day. The Workers' Festival ranges widely into many key themes of labour history - union politics and rivalries, radical movements, religion (Catholic and Protestant), race and gender, and consumerism/leisure - as well as cultural history - public celebration/urban procession, urban space and communication, and popular culture. From St. John's to Victoria, the authors follow the century-long development of the holiday in all its varied forms. --Publisher's description

Madeleine Parent: Activist - Lévesque, Andrée; Lévesque, Andrée (Sumach Press, 2005)
"[B]rings together some of the papers presented at the conference, "Madeleine Parent, ses lutes et ses engagements /Madeleine Parent and her struggles," held in March 2001 at McGill University under the auspices of the Quebec Studies Programme and the McGill Centre for Research and Teaching on Women." -- Editor. Translation of: Madeleine Parent, militante (2003). Contents: Portfolio of photographs -- Introduction: setting the stage; Student life at McGill, 1936-1940 / Andrée Lévesque -- Textile strikes in Quebec: 1946, 1947, 1952 / Denyse Baillargeon -- Carrying on the struggle in Ontario, 1952-1973 / John Lang -- The Atlantic connection / John St-Amand -- The women's movement in Canada: setting the agenda / Lynn Kaye & Lynn Mcdonald  -- The importance of being Madeline: how an inactivist won the heart of Quebec's immigrant and minority women -- A tribute to a valiant lady / Françoise David -- Madeleine Parent: an unfailing ally of native women / Michèle Rouleau -- An iron will and a string of pearls / Rick Salutin -- A friend, a role model / Monique Simard.
Keywords: Feminism; History; Parent, Madeleine, 1918-2012; Social conditions; Syndicalism; Women political activists

Global Game, Local Arena: Restructuring in Corner Brook, Newfoundland - Norcliffe, Glen (Social and economic studies (St. John's, NL), 2005)
In Global Game, Local Arena, geographer Glen Norcliffe explores how powerful forces of global economic integration have played out in Corner Brook and interprets the town's creation as a company town in the colonial era, its slow transformation into a public municipality, and the phase of vigorous restructuring launched in 1984 to raise the paper mill's performance in response to increased global competition. Restructuring introduced lean production, and in turn this impacted on workers' families, and on the larger community. Through extensive interviews with former and present mill workers and their families, and by examining written records — newspaper accounts, legislative acts, earlier published sources — the author sheds valuable light on how the process of globalization has played out in one small but typical local arena. Since 1984 Corner Brook has experienced large-scale out-migration of younger adults, and a rapid aging of the population. Community resistance to this process has been mostly subtle, taking the form of a reconnection to the population's local roots in outports and the woods. --Publisher's description

Ma vie de syndicaliste - Parrot, Jean-Claude (Boréal, 2005)
Pendant quinze ans, Jean-Claude Parrot a occupé le poste de président du Syndicat des travailleurs et travailleuses des postes, et pendant plus de dix-huit ans, il en a été le négociateur en chef. Au cours de toutes ces années, le leadership de Jean-Claude Parrot a fait de ce syndicat un des plus militants et des plus démocratiques au Canada. Quand Pierre Elliott Trudeau a décidé de transformer le service postal en société de la Couronne, c’est Parrot qui était à la barre. C’est lui également qui a supervisé la fusion des divers syndicats des postiers en un seul grand syndicat. Jean-Claude Parrot raconte ici son histoire, mais en même temps celle de la formation d’une grande union syndicale. Il raconte également comment la démocratie syndicale s’est construite – comment les membres de la base ont pu s’imposer dans tout le mécanisme de prise de décisions. Ce livre nous permet de suivre la carrière de l’un des plus grands dirigeants syndicaux du Canada, de le voir engagé dans son combat pour donner une voix aux travailleurs. Dans ce combat, Parrot a souvent placé son engagement syndical avant sa vie privée, et il a préféré faire de la prison plutôt que de sacrifier ses principes. À travers le récit de Jean-Claude Parrot, nous voyons la démocratie en marche, nous voyons le combat d’un homme pour défendre la cause des travailleurs et des syndicats. Traduit de l'anglais (Canada) par Claire Laberge --Résumé de l'éditeur

My Union, My Life: Jean-Claude Parrot and the Canadian Union of Postal Workers - Parrot, Jean-Claude (Fernwood, 2005)
Jean-Claude Parrot was National President of the Canadian Union of Postal Workers for fifteen years and its chief negotiator for eighteen. During that time he provided the leadership which built what became Canada’s most militant and democratic union. When Pierre Trudeau decided to make the post office a crown corporation Parrot was there to guide the transition. He was also there to oversee the merger of the various postal unions into “one union for all.” As well as Jean-Claude Parrot’s story, this is also the story of the formation of a union. It is a story of how union democracy was built–of how the grassroots union membership became an integral part of decision making in the union. In the pages of this book you will follow the life of one of Canada’s greatest union leaders as he fought to give the workers a voice. In the course of the struggle Parrot often put his union work and commitments before his own personal life and spent time in prison rather than sacrifice his principles and the cause of the workers in the union. Through Parrot’s recounting of these years we learn about how the struggle was waged, how democracy was built and how a union leadership worked tirelessly in the service of the union membership. --Publisher's description
Keywords: Biography; Canadian Union of Postal Workers; Officials and employees; Parrot, Jean-Claude; Postal service

What Do They Call a Fisherman?: Men, Gender, and Restructuring in the Newfoundland Fishery - Power, Nicole Gerarda (Social and economic studies (St. John's, NL), 2005)
Newfoundland fisheries have been transformed from an industry once dominated by petty commodity production and merchant-fisher relations to one dominated by private enterprise and corporate capitalism. State efforts to enclose the fisheries through boat quotas and to limit participation through a core classification system demonstrate a shift in values. Science-based regulation, in which the estimates of fisheries scientists were overly optimistic, led to the collapse of the cod fishery. The recent turn to a fishery based on classical economics, emphasizing professionalization, has left inshore fishers caught between two value systems. The traditional view valorizes hard work and local knowledge about the fishing environment; the modern view embraces technology, rationalization and professionalization. In [this book] Nicole Power examines, through a feminist lens, how this tension between two views — between a way of life and a way to make a living — and how these changes have affected men (and women) in the Bonavista and Trinity Bays inshore fishery. Has a "crisis of fish" and the loss or diminution of livelihood led to a "crisis of masculinity"? Through extensive interviews with fishers and fish-plant workers, the author discovers that men have responded to restructuring in complex ways that are mediated, enabled and constrained by their class and gender positions, and by maritime cultural values and practices. --Publisher's description

The Tyranny of Work: Alienation and the Labour Process - Rinehart, James W. (Nelson, 2005)
[E]xamines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. Completely updated to reflect current trends in the labour force and research in the field of labour studies, The Tyranny of Work begins with a thorough discussion of work as a social problem and the sources of alienation. The book then examines the development of industrial capitalism in Canada, the white-collar and blue-collar worlds, and, finally, solutions to the problem of alienated labour. All statistics and data have been updated to reflect the most current research. Information from the 2001 Census has been integrated throughout the text. The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. --Publisher's description
Keywords: Alienation (Social psychology); Labor; Working class

Labour in the Laboratory: Medical Laboratory Workers in the Maritimes, 1900-1950 - Twohig, Peter (McGill-Queen's/Associated Medical Services (Hannah Institute) studies in the history of medicine, health, and society, 2005)
Medical laboratory technology is currently the third largest health profession in Canada but those who work in it remain largely invisible, both to the public and in the literature. In Labour in the Laboratory Peter Twohig examines the origins of the laboratory workforce in the Maritime provinces and rethinks the broader history of the twentieth-century Canadian hospital. --Publisher's description.
Keywords: 20th century; Biomedical technology; History; Hospital laboratories; Maritime Provinces; Medical Laboratory Personnel; Medical technologists

On the Side of the People: A History of Labour in Saskatchewan - Warren, Jim W.; Carlisle, Kathleen (Coteau Books, 2005)
A comprehensive history of working people in Saskatchewan, from the mid-1800s to the present, in a handsome coffee-table format, including numerous historical photos of the personalities and events that bring it to life. This book is created for the working people that it celebrates. In a plain-spoken and engaging narrative style, it captures the events and the personalities that shaped the working people of Saskatchewan, and the life of the province that those workers built. Jim Warren tells the fascinating tale of jobs, working conditions, and the attempts to effect meaningful changes in the condition of workers' lives. Starting with the Fur Trade period, and moving through the arrival of the railroad brotherhoods, the emergence of the craft unions, two world wars, modernization, and into the present age, Working in Saskatchewan shows the evolution of the work force, and the relationship between that work force and both private and public sector employers. The book wraps up with a short chapter on the imagined future of labour in the province, in the voices of a series of speakers ranging from former Premier Allan Blakeney to ordinary workers on the floor of a recent SFL convention. Working in Saskatchewan also includes a number of features that will make it even more useful for private study or school work. Two comprehensive indexes detail the chief characters who played a role in the development of the labour movement, and a list of events and important topics. A series of informational appendices present statistical information relating to the Saskatchewan labour force - size of the organized and unorganized labour force, number of women in the work force, etc. There will also be a helpful glossary of the acronyms and abbreviations that characterize written or oral discussions about labour, and a "genealogy of labour" which charts the rise and growth of certain unions and their transformation into, or absorption by, others. --Publisher's description
Keywords: History; Labor movement; Labor movement Saskatchewan History; Labor unions; Labor unions Saskatchewan History; Mouvement ouvrier Saskatchewan Histoire; Saskatchewan; Saskatchewan Conditions sociales; Saskatchewan Social conditions; Social conditions; Syndicats Saskatchewan Histoire; Travailleurs Saskatchewan Histoire; Working class; Working class Saskatchewan History

Canadian Bolsheviks: The Early Years of the Commmunist Party of Canada - Angus, Ian (Trafford, 2004)
Canadian communism did not spring out of the ground suddenly at the end of World War I, and it was not smuggled into the country by Russian agents. The men and women who built the new movement were long-time socialist and labour militants in Canada. Inspired by the Russian Revolution and by their own experiences as leaders of the post-war labour revolt in Canada, they set about to create a new kind of party, one that could lead the fight for workers' power. The new Communist Party, formed between 1919 and 1921, quickly became the largest party on the left, with strong roots and influence in the unions and basic industry. Its members led heroic strikes. They fought for labor unity, and engaged in united electoral activity with other currents in the workers movement. They were in the forefront of the struggle for democratic rights. Ten years later, the party was destroyed. Most of its founding leaders were expelled, and three quarters of its membership dropped out. The Communist Party abandoned the program it had adopted in its early years, and turned its back on its principles. The organization still called itself Communist, but it was now "Tim Buck's Party." It had been transformed from a revolutionary party into an agent of the new ruling caste in Moscow. In Canadian Bolsheviks, Ian Angus describes and explains the first attempt to build a Leninist party on Canadian soil, showing why it succeeded so well at first, and why it ultimately failed. The second edition of a book that has been widely hailed as a pathbreaking work, "the best yet to appear" on the origins of Canadian communism. --Publisher's description

Survival: A Thematic Guide to Canadian Literature - Atwood, Margaret. (McClelland & Stewart, 2004)
When first published in 1972, Survival was considered the most startling book ever written about Canadian literature. Since then, it has continued to be read and taught, and it continues to shape the way Canadians look at themselves. Distinguished, provocative, and written in effervescent, compulsively readable prose, Survival is simultaneously a book of criticism, a manifesto, and a collection of personal and subversive remarks. Margaret Atwood begins by asking: "What have been the central preoccupations of our poetry and fiction?" Her answer is "survival and victims." Atwood applies this thesis in twelve brilliant, witty, and impassioned chapters; from Moodie to MacLennan to Blais, from Pratt to Purdy to Gibson, she lights up familiar books in wholly new perspectives. This new edition features a foreword by the author. --Publisher's description.
Keywords: Canadian Literature; Criticism

Common and Contested Ground: A Human and Environmental History of the Northwestern Plains - Binnema, Ted (University of Toronto Press, 2004)
In Common and Contested Ground, Theodore Binnema provides a sweeping and innovative interpretation of the history of the northwestern plains and its peoples from prehistoric times to the Lewis and Clark Expedition. The real history of the northwestern plains between a.d. 200 and 1806 was far more complex, nuanced, and paradoxical than often imagined. Drawn by vast herds of buffalo and abundant resources, bands of Indians, fur traders, and settlers moved across the northwestern plains establishing intricate patterns of trade, diplomacy, and warfare. In the process, the northwestern plains became a common and contested ground. Drawing on a wide range of sources, Binnema examines the impact of technology on the peoples of the northern plains, beginning with the bow-and-arrow and continuing through the arrival of the horse, European weapons, Old World diseases, and Euroamerican traders. --Publisher's description
Keywords: Ethnic relations; Fourrures Commerce Grandes Plaines Histoire; Fur trade; Fur trade Great Plains History; Grandes Plaines Relations interethniques; Great Plains; Great Plains Ethnic relations; History; Indianen; Indians of North America; Indians of North America Commerce; Indians of North America Commerce Great Plains History; Indians of North America Great Plains History; Indiens d'Amérique Commerce Grandes Plaines Histoire; Indiens d'Amérique Grandes Plaines Histoire

Workplace Learning: A Critical Introduction - Bratton, John; Sawchuk, Peter H.; Helms Mills, Jean C.; Pyrch, Timothy (Garamond Press, 2004)
This innovative book is concerned with the power relations, complexities, and contradictions in the paid workplace. Workplace learning is not value-free or politically neutral, and cannot be studied independently of the political economy of work. [This book] is part of a growing body of work that offers an alternative to mainstream approaches to workplace learning, recognizing that power relations, politics and conflicts of interest all shape learning. The authors emphasize the lived experiences of working people, avoiding prescriptive accounts and uncritical Human Resource Development views. --Publisher's description. Contents: 1. Introduction -- 2. Management strategies and workplace learning -- 3. Groups, teams and workplace learning -- 4. Organizational learning and learning organizations -- 5. Unions and workplace learning -- 6. Adult education, learning and work -- 7. Toward the future of workplace learning. Includes bibliographical references (p. [181]-194) and index.
Keywords: Adult education; Employees; Experiential learning; Training of

Le quatuor d'asbestos : autour de la grève de l'amiante - Delisle, Esther; Malouf, Pierre K. (Collection Histoire et société (Montréal), 2004)
Comme son titre l'indique, Le Quatuor d'Asbestos est composé de quatre livres, qui replacent dans son contexte historique la fameuse grève de l'amiante de 1949. De nombreux documents y sont présentés pour la première fois ; tous les points de vue y sont exprimés, car ici l'histoire est racontée par ceux qui l'ont vécue. On constatera, entre autres choses, que l'ouvrage publié en 1956 sous la direction de Pierre Trudeau, La Grève de l'amiante, donne une interprétation très réductrice, voire mensongère des causes et des conséquences de la grève. Tout commence donc en mars 1948 avec la publication dans la revue Relations d'un article retentissant du journaliste franco-américain Burton LeDoux sur les conditions de vie inhumaines des mineurs de Saint-Rémi d'Amherst dans les Laurentides. Cet article se veut la première étape dans une campagne pour l'amélioration de l'hygiène industrielle au Québec. Mais le gouvernement de Maurice Duplessis vient de céder le monopole du développement de l'Ungava aux intérêts financiers qui traitent comme du bétail les mineurs de Saint-Rémi. Avec la complicité de Mgr Joseph Charbonneau, les compagnies et le gouvernement musèlent Relations. Le Devoir prend alors le relais et publie en janvier 1949 un deuxième article de Burton LeDoux, qui révèle l'existence à East Broughton dans la région de l'amiante d'un autre abattoir humain. Un mois plus tard, la grève éclate à Asbestos et à Thetford Mines. La première revendication des mineurs : l'élimination de la poussière. Les travailleurs sont galvanisés, car c'est de leur santé et de leur vie mêmes qu'il s'agit. La grève durera quatre mois et demi, mais sera, surtout sur la question essentielle de l'hygiène industrielle, un échec total. Il faudra attendre 1975 pour qu'on décide enfin de corriger une situation qui aurait pu et dû l'être un quart de siècle plus tôt. Ensuite, il y aura la nationalisation et le déclin de l'industrie. Mais c'est une histoire qui n'a pas de fin et il se publie encore de nos jours des articles qui confirment que Burton LeDoux avait vu clair dès 1948. --Résumé de l'éditeur
Keywords: 1900-1999; Asbestos Strike, Québec, 1949; Grève de l'amiante, Québec, 1949; Grèves et lock-out Mines d'amiante Québec (Province) Histoire; Grèves et lock-out Mines d'amiante Québec (Province) Histoire Sources; Grèves et lock-out Mines d'amiante Québec (Province) Val-des-Sources; History; Québec; Québec Asbestos; Silicose; Silicose Québec (Province) Histoire 20e siècle; Silicosis; Silicosis Québec (Province) History 20th century; Sources; Strikes and lockouts Asbestos mining; Strikes and lockouts Asbestos mining Québec (Province) Asbestos; Strikes and lockouts Asbestos mining Québec (Province) History; Strikes and lockouts Asbestos mining Québec (Province) History Sources

The Paradox of American Unionism: Why Americans Like Unions More Than Canadians Do, But Join Much Less - Lipset, Seymour Martin; Meltz, Noah M.; Katchanovski, Ivan; Gomez, Rafael (ILR Press, 2004)
Why have Americans, who by a clear majority approve of unions, been joining them in smaller numbers than ever before? This book answers that question by comparing the American experience with that of Canada, where approval for unions is significantly lower than in the United States, but where since the mid-1960s workers have joined organized labor to a much greater extent. Given that the two countries are outwardly so similar, what explains this paradox? This book provides a detailed comparative analysis of both countries using, among other things, a detailed survey conducted in the United States and Canada by the Ipsos-Reid polling group. The authors explain that the relative reluctance of employees in the United States to join unions, compared with those in Canada, is rooted less in their attitudes toward unions than in the former country's deep-seated tradition of individualism and laissez-faire economic values. Canada has a more statist, social democratic tradition, which is in turn attributable to its Tory and European conservative lineage. Canadian values are therefore more supportive of unionism, making unions more powerful and thus, paradoxically, lowering public approval of unions. Public approval is higher in the United States, where unions exert less of an influence over politics and the economy. --Publisher's description
Keywords: Labor movement; Labor unions; Mouvement ouvrier; Syndicats; trade unions

Hidden Knowledge: Organized Labour in the Information Age - Livingstone, D. W.; Sawchuk, Peter H. (Peter Harold); Roth, Reuben N.; Martin, D'Arcy; Morgan, Clara (Garamond Press, 2004)
This book offers an original contribution to understanding an often-ignored aspect of our knowledge society and the much-heralded ‘knowledge-based economy.’ It decisively explodes the dual myths that working-class adults have inferior learning capacities and that talented youths naturally leave blue-collar careers. Livingstone and Sawchuk document the genuine learning practices of working-class people in unprecedented detail, using richly textured accounts of prior school experiences; current adult education course participation; and a wide array of learning resources in paid workplaces, households, and community settings. The authors criticize dominant theories of learning and work and develop an alternative explanation of working-class adult learning. Their analysis, grounded in the specific practices of everyday life, pays careful attention to the ways in which differential economic power, labor processes, sectoral contexts, union cultures, and access to organized educational resources shape individual and collective learning activities. The book also provides a reflective discussion of research processes suitable for democratic knowledge production in partnership with workers and their organizations, as well as workers' own practical recommendations for changes in learning and work relations. --Publisher's description. Contents: Introduction: Dimensions of learning and work in the knowledge society -- Pt. 1. Researching learning and work. Starting with Workers and Researching the "Hard Way" / with D'Arcy Martin -- Beyond cultural capital theories: Hidden dimensions of working-class learning. Pt. 2. Case studies.  Auto workers: Lean manufacturing and rich learning / with Reuben Roth -- Building a workers' learning Culture in the Chemical Industry -- Learning, Restructuring and job segregation at a community college -- Divisions of labour / Divisions of learning in a small parts manufacturer -- Garment workers: learning under disruption / with Clara Morgan. Pt. 3. Comparative perspectives across case studies. Household and community-based learning: Learning cultures and class differences beyond paid work -- Surfacing the hidden dimension of the knowledge society: the struggle for knowledge across differences. Includes bibliographical references (p. [299]-309) and index.
Keywords: Adult learning; Canada; Case studies; Education; Information society; Interviews; Labor union members; Labor unions; Occupational training; Working class - Effect of technological innovations on

Racism, Eh?: A Critical Inter-Disciplinary Anthology of Race and Racism in Canada - Nelson, Charmaine; Nelson, Camille A. (Captus Press, 2004)
"Racism, Eh?" is the first publication that examines racism within the broad Canadian context. This anthology brings together some of the visionaries who are seeking to illuminate the topics of race and racism in Canada through the analysis of historical and contemporary issues, which address race and racism as both material and psychic phenomena. Fundamentally interdisciplinary in nature, this text will be an invaluable resource for undergraduate and graduate students, academics studying or practicing within the Humanities and the Social Sciences, and anyone seeking information on what has been a little explored and poorly understood Canadian issue."--Publisher's description. Contents: Part 1 Institutional Racism -- 1 Penn and Teller Magic -- 2 Lance Belanger's Tango Lessons -- 3 The Black Occupational Structure in Late-Nineteenth-Century Ontario -- Part 2 Crime and Justice -- 4 Raising Raced and Erased Executions in African-Canadian Literature -- 5 Examining Racism and Criminal Justice -- 6 Criminological Research on "Race" in Canada -- Part 3 First Nations -- Of Land, Law and Power -- 7 Across a Boundary of Lava -- 8 Treaty Federalism -- 9 Navigating Discrimination -- Part 4 Race, Place and Nation -- 10 Adrift in the Diaspora -- 11 Racism Between Jews -- 12 Local Colour -- Part 5 Complexity of Intersectionallity and Performance of Racial Identity -- 13 Speak White! -- 14 Jack Canuck Meets John Chinaman -- 15 Performing Desire -- Part 6 Popular Culture -- 16 Race In-Out of the Classroom -- 17 Other Canadian Voices -- 18 (Re)Visioning Histories -- Part 7 Production and Representation -- 19 Each Sentence Realized or Dreamed Jumps Like a Pulse with History and Takes a Side -- 20 Articulating Spaces of Representation -- 21 The "Hottentot Venus" in Canada -- 22 Racial Recognition Underpinning Critical Art -- Part 8 Multiculturalism -- 23 But Where Are You REALLY From? -- 24 Social Cohesion and the Limits of Multiculturalism in Canada -- 25 Racialising Culture-Culturalising Race -- 26 Re-articulating Multiculturalism.
Keywords: Racism -- Canada

CCF Colonialism in Northern Saskatchewan: Battling Parish Priests, Bootleggers, and Fur Sharks - Quiring, David M. (UBC Press, 2004)
Saskatchewan's Co-operative Commonwealth Federation (CCF) the forerunner of the NDP, is often remembered for its humanitarian platform and its pioneering social programs. But during the twenty years it governed, it wrought a much less scrutinized legacy in the northern regions of the province." "Until the 1940s, churches, fur traders, and other influential newcomers held firm control over Saskatchewan's northern region. Following its rise to power in 1944 the CCF made aggressive efforts to unseat these traditional powers and install a new socialist economy and society in largely Aboriginal communities. The next two decades brought major changes to the region as well-meaning government planners grossly misjudged the challenges that confronted the north and failed to implement programs that would meet its needs. Northerners lacked the voice and political clout to determine policies for their half of the province and the CCF effectively created a colonial apparatus, imposing its own ideas and plans in those communities without consulting residents. While it did ensure that parish priests, bootleggers, and fur sharks no longer dominated the north, it failed to establish a workable alternative." "In written history that documents the colonial relationship between the CCT and northern Saskatchewan, David Quiring draws on extensive archival research and oral history to offer a fresh look at the CCF era. This examination will find an audience among historians of the north. Aboriginal scholars and general readers interested in Canadian history."--Publisher's description. Contents: Pt. 1. At the crossroads -- 1. Another country altogether -- Pt. 2. Building the colonial structure -- 2. From the top -- 3. Ultimate solution -- 4. Deterrent to development -- Pt. 3. Segregated economy -- 5. Never before have we been so poor -- 6. At the point of a gun -- 7. Just one jump out of the stone age -- 8. Pre-industrial way of life -- Pt. 4. Poverty-stricken and disease-ridden -- 9. Scarcely more than palliative -- 10. Dollars are worth more than lives -- Epilogue : we will measure our success -- A. Comments on collection of oral history -- B. Electoral record.
Keywords: Saskatchewan; Socialism

Le syndicalisme québécois : deux siècles d'histoire - Rouillard, Jacques (Boréal, 2004)
Contrairement à ce qu’on a cru pendant longtemps, l’histoire du syndicalisme au Québec remonte au début du XIXe siècle et évolue sensiblement au même rythme que celle des autres mouvements syndicaux en Amérique du Nord. À ce chapitre, les facteurs économiques et géographiques qui la rattachent au continent pèsent aussi lourd que le caractère distinct de la société québécoise. Voilà un des éléments clés qui ressortent du vaste pano-rama du syndicalisme au Québec que Jacques Rouillard trace ici. À chacune des périodes étudiées, qui renvoient aux grands moments de l’histoire occidentale, l’auteur montre comment les syndicats ont représenté une composante essentielle de la classe ouvrière et l’un des principaux lieux de contestation de l’ordre établi. Ce livre est une nouvelle édition de la première synthèse sur le syndicalisme québécois que Jacques Rouillard faisait paraître au Boréal en 1989. Ce nouveau texte, entièrement refondu, a été augmenté non seulement pour relater les événements qui se sont déroulés de 1985 à 2003, mais également pour tenir compte, aux diverses époques, des fruits de la négociation collective et de l’avancement de la recherche historique dans ce domaine. --Résumé de l'éditeur

Challenging the Market: The Struggle to Regulate Work and Income - Stanford, Jim; Vosko, Leah F. (McGill-Queen's University Press, 2004)
Challenging the Market offers insights from eighteen scholars and activists from around the world. Calling on a tremendous range of experience in different countries, different industries, and with different groups of workers, contributors argue that labour market policy should shift to a more interventionist and compassionate footing. For two decades economic and social policy in most of the world has been guided by the notion that economies function best when they are fully exposed to competitive market forces. In labour market policy, this approach is reflected in the widespread emphasis on "flexibility" - a euphemism for the retrenchment of income support and social security, the relaxation of labour market regulations, and the enhanced power of private actors to determine the terms of the employment relationship. These strategies have had marked effects on labour market outcomes, leading to greater vulnerability and polarization - and not always in ways that enhance worker-centred flexibility. The authors offer a more balanced analysis of the functioning and effects of labour market regulation and deregulation. By questioning the underpinnings of the "flexibility" paradigm, and revealing its often damaging impacts (on different countries, sectors, and constituencies), they challenge the conclusion that unregulated market forces produce optimal labour market outcomes. The authors conclude with several suggestions for how labour policy could be reformulated to promote both efficiency and equity. --Publisher's description
Keywords: Emploi; Employment (Economic theory); Labor costs; Labor demand; Labor market; Labor policy; Labor supply; Main-d'œuvre Coût; Marché du travail; Travail Politique gouvernementale; employing

Fighting for Dignity: The Ginger Goodwin Story - Stonebanks, Roger (Past CCLH Publications, 2004)
Roger Stonebanks traces the life of charismatic labour leader Ginger Goodwin from his childhood in the Yorkshire Coalfields, through his mining career in Cape Breton and British Columbia, until his untimely and controversial death in the woods of Vancouver Island. Using archival research and contemporary accounts, Stonebanks explores the historical context that surrounded Goodwin's meteoric rise in BC's labour and socialist ranks. His life, from union hall to the soccer pitch, sheds light on working-class culture in resource communities in the early years of the 20th century. Ginger Goodwin was killed while trying to evade conscription during World War I. The Military police officer responsible claimed he shot only in self-defence, but rumors have since persisted that foul play was involved in the death of the prominent socialist and labour activist. Goodwin's own words explain his opposition to conscription and war, while Stonebanks examines the background and attitude of the police officers hunting down draft dodgers. Adrian Brooks provides a legal analysis and review of the case of His Majesty the King v. Daniel Campbell and how the trial might have unfolded — if there had been a trial of Constable Campbell. Written in engaging and accessible prose, the book features several never before published photographs. --Publisher's description
Keywords: British Columbia; Draft resisters; Goodwin, Ginger; Labor Unions; Labor leaders; Officials and employees; WORLD War, 1914-1918; World War, 1914-1918

Saskatchewan: The Roots of Discontent and Protest - Warnock, John W. (Black Rose Books, 2004)
Isolation is part of the psyche of this sparsely populated prairie province, and this abundance of great open space has uniquely shaped the people, their politics, their economy and their relationship with the rest of North America. Using the broad, interdisciplinary social science approach of political economy analysis, Warnock traces Saskatchewan's past in an attempt to understand the present and glimpse some of its future. Along the way, he tells the story of Saskatchewan, from inception to centennial. --Publisher's description
Keywords: Economic conditions; Political culture; Politics and government; Social conditions

Changing Canada: Political Economy as Transformation - Clement, Wallace; Vosko, Leah F. (McGill-Queen's University Press, 2003)
Changing Canada examines political transformations, welfare state restructuring, international boundaries and contexts, the new urban experience, and creative resistance. The authors question dominant ways of thinking and promote alternative ways of understanding and explaining Canadian society and politics that encourage progressive social change. They examine how the evolution of capitalism is producing new types of transformations and new forms of resistance, and show that aspects of the state and the wider society are being contested. They also discuss the often paradoxical or contradictory effects of various social forces, such as the liberating but also constraining features of new communications technologies, new employment norms, and new household forms. --Publisher's description
Keywords: Aufsatzsammlung; Canada; Canada Conditions sociales 1991-; Canada Conditions économiques 1991-; Canada Economic conditions 1991-; Canada Politics and government 1980-; Canada Politics and government 1993-2006; Canada Politique et gouvernement 1993-2006; Canada Social conditions 1991-; Capitalisme; Changement politique; Changement social; Changement économique; Développement social Canada; Economic history; Kanada; Politics and government; Politieke ontwikkeling; Politische Ökonomie; Politischer Wandel; Science économique; Since 1980; Sociaal-economische ontwikkeling; Social change; Social change Canada; Social conditions; Sozialer Wandel; Wirtschaftsreform; État-Providence

Narratives at Work: Women, Men, Unionization, and the Fashioning of Identities - Cullum, Linda K (Social and economic studies (St. John's, NL), 2003)
In February, 1948, a group of fish and blueberry processors formed the exclusively female, Ladies' Cold Storage Workers Union at Job Brothers fish plant in St. John's, Newfoundland. Unusual for the time, this organization was founded in the context of structural and social change in the Newfoundland fishery that altered the social relations of paid and unpaid work for women fish plant labourers. Cullum carefully explores this specific labour process and provides an open reading of the workers' narratives; a study of how the women of Job Brothers recounted stories of their work and domestic lives, and thus fashioned shifting identities as gendered, classed, and racialized subjects. --Publisher's description

Trade Unions in Renewal: A Comparative Study - Fairbrother, Peter; Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Employment and work relations in context series, 2003)
This comprehensive survey of continuity and change in trade unions looks at five primarily English-speaking countries: the USA, Canada, Australia, New Zealand and the UK. The authors consider the recent re-examination by trade union movements of the basis of union organization and activity in the face of a harsher economic and political climate. One of the impetuses for this re-examination has been the recent history of unions in the USA. American models of renewal have inspired Australia, New Zealand and the UK, while Canada has undergone a cautious examination of the US model with an attempt to develop a distinctive approach. This book aims to provide a thorough grounding for informed discussion and debate about the position and place of trade unions in modern economies. --Publisher's description
Keywords: Commonwealth countries. Comparative industrial relations. Syndicats. Relations industrielles comparées. Sindicalismo. Sindicato. Comparative industrial relations. Labor unions; Labor unions. Labor unions; United States. Labor unions

Michel Chartrand : la colère du juste, 1968-2003 - Foisy, Fernand (Lanctôt, 2003)
Deuxième volet de la biographie de Michel Chartrand (Les voix d’un homme de parole), La colère du juste retrace les événements marquants de la vie du célèbre syndicaliste depuis mai 1968 jusqu’à nos jours. Ses prises de position éclatantes, ses multiples démêlées avec l’appareil judicaire, ses nombreux emprisonnements, dont sa détention lors de la crise d’Octobre 1970 (« Un jour quelqu’un va payer pour tous ces jours passés sans soleil et sans femme… »), les luttes multiples, syndicales et autres, qu’il a menées pour le mieux-être et la sécurité des travailleurs, les complots et manigances douteuses dont il a été souvent victime, avec en toile de fond une tranche importante de l’histoire du Québec moderne, tels sont les principaux éléments qui forment la trame de cette biographie imposante. Fernand Foisy a réussi à recréer le climat de l’époque, en donnant la parole aux principaux acteurs, rectifiant ici et là certaines notions erronées qui ont été véhiculées à propos de ce indomptable justicier au tempérament fougueux, Michel Chartrand. Un homme d’action et de parole, dont on découvrira tout le charme et ses passions pour la culture. Ce deuxième tome coïncide avec la diffusion de la deuxième partie de la série Simone et Chartrand, diffusée cet automne sur les ondes de Télé-Québec. --Résumé de l'éditeur
Keywords: Biographies; Chartrand, Michel; Dirigeants syndicaux Québec (Province) Biographies; History; Labor leaders; Labor leaders Québec (Province) Biography; Labor unions; Labor unions Québec (Province) History; Politics and government; Québec; Québec (Province) Conditions sociales 1960-1991; Québec (Province) Politics and government 1960-; Québec (Province) Politique et gouvernement 1960-; Since 1960; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province); Syndicats Québec (Province) Histoire; Travailleurs Québec (Province) Conditions sociales; Travailleurs Québec (Province) Histoire; Working class; Working class Québec (Province) History; Working class Québec (Province) Social conditions; Working class Social conditions

L'histoire des mineurs du nord ontarien et québécois, 1886-1945 - Gaudreau, Guy; Daoust, Alain; De la Riva, Paul; Reilly, Karey (Cahiers des Amériques, 2003)
L’auteur fait revivre les itinéraires de milliers de travailleurs qui ont sillonné les mines du Nord-Est ontarien et du Nord-Ouest québécois au cours des premières décennies du xxe siècle. Grâce à l’exploitation des dossiers du personnel de sept sociétés minières réparties sur ce territoire, il scrute les arrivées et les départs des ouvriers-mineurs en cherchant à comprendre leurs motivations. L’image se dégageant de ces sources patronales reste fort différente de celle rapportée par l’histoire ouvrière et syndicale. En effet, ces travailleurs quittent d’eux-mêmes leur emploi beaucoup plus souvent qu’ils ne sont congédiés ou mis à pied, de sorte que leur chômage serait davantage volontaire qu’imposé. Étant donné la relative rareté de la main-d’œuvre spécialisée, les employeurs n’auraient pas eu d’autre choix que de réembaucher ceux qu’ils avaient auparavant engagés, et même ceux qu’ils avaient déjà congédiés. En somme, ces travailleurs, qui annoncent très souvent leur décision de « sacrer leur camp », affichent une indépendance face aux entreprises et une capacité de résistance qu’on ne soupçonnait pas. --Résumé de l'éditeur
Keywords: History; Mineral industries; Mineral industries Ontario, Northern History; Mineral industries Québec (Province) Abitibi-Témiscamingue History; Miners; Miners Ontario, Northern History; Miners Québec (Province) Abitibi-Témiscamingue History; Mineurs Québec (Province) Abitibi-Témiscamingue Histoire; Northern Ontario; Québec Abitibi-Témiscamingue

Westcountrymen in Prince Edward's Isle - Greenhill, Basil; Giffard, Ann (Formac, 2003)
This classic, first-of-its-kind study of merchant shipping illuminates the manner in which the rapid development of shipbuilding in Prince Edward Island played a significant role in Canada's early history. James Yeo, Sr., once a village labourer in his native Cornwall, came to the colony and quickly amassed a fortune from both shipbuilding and trade. His rough-and-ready business deals spawned his mercurial rise to prominence in the colony. First published in 1967, this book originated from an idea by Ann Giffard and was jointly executed with her husband, Basil Greenhill. It connects the burgeoning expansion of shipbuilding in the colonies with the settlers' hometown in Devon, and explains why, when Britain was cut off from supplies of wood in Europe, shipbuilding suddenly took hold in Canada. It is an unique study that shows that local history is an important window into the interconnected world of economic development. --Publisher's description
Keywords: Commerce; Great Britain; Great Britain Commerce Prince Edward Island; History; Prince Edward Island; Prince Edward Island Commerce Great Britain; Shipbuilding; Shipbuilding Prince Edward Island History; Shipping; Shipping Prince Edward Island History

Industrial Sunset: The Making of North America's Rust Belt, 1969-1984 - High, Steven C. (University of Toronto Press, 2003)
Plant shutdowns in Canada and the United States from 1969 to 1984 led to an ongoing and ravaging industrial decline of the Great Lakes Region. This book offers a comparative regional analysis of the economic and cultural devastation caused by the shutdowns, and provides an insightful examination of how mill and factory workers on both sides of the border made sense of their own displacement. The history of deindustrialization rendered in cultural terms reveals the importance of community and national identifications in how North Americans responded to the problem. Based on the plant shutdown stories told by over 130 industrial workers, and drawing on extensive archival and published sources, and songs and poetry from the time period covered, Steve High explores the central issues in the history and contemporary politics of plant closings. In so doing, this study poses new questions about group identification and solidarity in the face of often dramatic industrial transformation. --Publisher's description

When Coal was King: Ladysmith and the Coal-Mining Industry on Vancouver Island - Hinde, John Roderick (UBC Press, 2003)
The town of Ladysmith was one of the most important coal-mining communities on Vancouver Island during the early twentieth century. The Ladysmith miners had a reputation for radicalism and militancy and engaged in bitter struggles for union recognition and economic justice, most notably the Great Strike of 1912-14. This strike, one of the longest and most violent labour disputes in Canadian history, marked a watershed in the history of the town and the coal industry. --Publisher's description
Keywords: British Columbia Ladysmith; British Columbia Vancouver Island; Coal miners; Coal mines and mining; Coal mining History; History; Ladysmith (B.C.); Social aspects History; Social conditions History; Strikes and lockouts

From Consent to Coercion: The Assault on Trade Union Freedoms - Panitch, Leo; Swartz, Donald (Garamond Press, 2003)
Examines the "coercive assault" (i.e., legislative overrides) on trade union rights in Canada by both federal and provincial governments from the 1970s to the early 2000s. Also discusses labour-related decisions of the Supreme Court, and strategies for union renewal. Includes tables of union membership, strikes and lockouts, back-to-work measures, use of designations, and complaints of violations of union rights filed with the International Labor Organization.
Keywords: Collective bargaining; History; Labor Unions; Law and legislation

Gendered States: Women, Unemployment Insurance, and the Political Economy of the Welfare State in Canada, 1945-1997 - Porter, Ann (Studies in comparative political economy and public policy, 2003)
In the period since the Second World War there has been both a massive influx of women into the Canadian job market and substantive changes to the welfare state as early expansion gave way, by the 1970s, to a prolonged period of retrenchment and restructuring. Through a detailed historical account of the Unemployment Insurance (UI) program from 1945 to 1997, Ann Porter demonstrates how gender was central both to the construction of the post-war welfare state, as well as to its subsequent crisis and restructuring. Drawing on a wide range of sources (including archival material, UI administrative tribunal decisions, and documents from the government, labour and women's groups) she examines the implications of restructuring for women's equality, as well as how women's groups, labour and the state interacted in efforts to shape the policy agenda. Porter argues that, while the post-war welfare state model was based on a family with a single male breadwinner, the new model is one that assumes multiple family earners and encourages employability for both men and women. The result has been greater formal equality for women, but at the same time the restructuring and reduction of benefits have undermined these gains and made women's lives increasingly difficult. Using concepts from political economy, feminism, and public policy, this study will be of interest across a range of disciplines. --Publisher's description
Keywords: Economic policy; Employment; History; Social policy; Unemployment insurance; Women

Paul has a Summer Job: Graphic Novel - Rabagliati, Michel. (Drawn and Quarterly, 2003)
Rabagliati's strip "Paul: Apprentice Typographer" was one of the highlights of 1999's Drawn & Quarterly anthology, and his first comic book Paul in the Country won the 2000 Harvey award for Best New Talent. This, his first graphic novel, is eagerly anticipated by comix connoisseurs who enjoy a sweet, unsentimental story about being a teenager and Rabagliati's crisp retro-modern 1950s drawing style. This book continues the story of Paul, a Quebecois teenager in the 1970s, as he experiences the first conflicts of responsibility with his desire to be free. Paul is outraged that he is forced to stop his high school art training. But he's been asked to put art aside because his other grades are so terribly low. Defiant, he quits school and anticipates a summer of leisure. But instead Paul follows the path of so many Quebecois teenagers: he lands a job as a counselor at one of the many summer camps in the mountains outside the city. There he finds himself guiding a motley band of kids, misfits and troublemakers, much like himself. After quitting school and trying his luck in the "real world," average teenager Paul gets a job as a counselor at a summer camp run for underprivileged children in 1970s Quebec. --Publisher's description
Keywords: Blue-collar work; Camp Counsellor; Comic books, strips, etc; Factory; Montreal, Quebec; Teenager

Unions in the Time of Revolution: Government Restructuring in Alberta and Ontario - Reshef, Yonatan; Rastin, Sandra (University of Toronto Press, 2003)
The election of neo-conservative governments in Alberta and Ontario in the early 1990s brought dramatic changes to provincial public policy; both the Ralph Klein Revolution and Mike Harris' Common Sense Revolution emphasized fundamental changes in the role of government, balanced budgets, and the elimination of provincial debts. While public sector unions were forced to react, the response of the Alberta and Ontario unions differed significantly. The reasons, outcome, and long-term impact of the difference is the focus of Yonatan Reshef and Sandra Rastin's careful and revealing analysis. The authors' argument concentrates on union responses to the neo-conservative transformation in the two affected provinces, but the scope of the discussion expands to cover such issues as the differences between the two regimes, the damage to the Ontario labour movement dealt by the labour-oriented NDP government, the limits of inter-union cooperation, and the role of modern unions in politics. Lively and timely, Unions in the Time of Revolution places Canada's unions in the full context of the neo-conservative trend in provincial politics, and demonstrates the importance of individual union responses in times of such significant change. --Publisher's description. Contents: Alberta and Ontario: Industrial relations and their contexts -- Revolutions, Canada style -- Collective action conceptual framework -- Revolutionizing the Civil Service: OPSEU and AUPE -- Teachers: Protecting the profession, defending the union organization -- Sins of commission and sins of omissions: The Ontario days of action and missed opportunities in Alberta -- Sleeping with the devil: Strategic voting in the 1999 Ontario Election -- Revisiting the collective action model -- Additional thoughts on collective action.
Keywords: Alberta. Employee-management relations in government; Alberta. Government employee unions; Employee-management relations in government; Ontario. Employee-management relations in government. Government employee unions; Ontario. Fonction publique; Ontario. Fonctionnaires; Ontario. Government employee unions; Relations de travail; Syndicats

The Oriental Question: Consolidating a White Man's Province, 1914-1941 - Roy, Patricia (University of British Columbia Press, 2003)
[The author] continues her study into why British Columbians – and many Canadians from outside the province – were historically so opposed to Asian immigration. Drawing on contemporary press and government reports and individual correspondence and memoirs, Roy shows how British Columbians consolidated a “white man’s province” from 1914 to 1941 by securing a virtual end to Asian immigration and placing stringent legal restrictions on Asian competition in the major industries of lumber and fishing. While its emphasis is on political action and politicians, the book also examines the popular pressure for such practices and gives some attention to the reactions of those most affected: the province’s Chinese and Japanese residents. --Publisher's description
Keywords: 1900-1999; British Columbia; British Columbia Emigration and immigration History 20th century; British Columbia Politics and government 20th century; British Columbia Race relations; China; China Emigration and immigration History 20th century; Chinese; Chinese British Columbia History 20th century; Chinesen; Chinois Colombie-Britannique Histoire 20e siècle; Einwanderung; Emigration and immigration; Ethnische Beziehungen; History; Immigrants; Immigrants British Columbia History 20th century; Japan; Japan Emigration and immigration History 20th century; Japanese; Japanese British Columbia History 20th century; Japonais Colombie-Britannique Histoire 20e siècle; Politics and government; Race relations

Retooling the Mind Factory: Education in a Lean State - Sears, Alan (Garamond Press, 2003)
Alan Sears examines education reform in relation to a broad process of cultural and economic change. His book makes the case that education reform is one aspect of a broad-ranging neo-liberal agenda that aims to push the market deeper into every aspect of our lives by eliminating or shrinking non-market alternatives. The author begins by showing that advocates of education reform have had to make the case that the current system is not working. This sets the ground for an examination of the so-called 'Common Sense Revolution,' a claim that drastic change was required to redesign government policies to fit a changing world. Lean production methods are a crucial component of this changing world, and broader social and cultural change is now required to consolidate the emerging order built on the spread of these methods. Education reform is designed to recast the relations of citizenship, contributing to the cultural and social change promoted through the social policy of the lean state. --Publisher's description
Keywords: Conservatism; EDUCATIONAL change; Economic aspects; Education; Education and state; Ontario

Forces of Labor: Workers' Movements and Globalization since 1870 - Silver, Beverly J. (Cambridge studies in comparative politics, 2003)
Recasting labor studies in a long-term and global framework, the book draws on a major new database on world labor unrest to show how local labor movements have been related to world-scale political, economic, and social processes since the late nineteenth century. Through an in-depth empirical analysis of select global industries, the book demonstrates how the main locations of labor unrest have shifted from country to country together with shifts in the geographical location of production. It shows how the main sites of labor unrest have shifted over time together with the rise or decline of new leading sectors of capitalist development and demonstrates that labor movements have been deeply embedded (as both cause and effect) in world political dynamics. Over the history of the modern labor movement, the book isolates what is truly novel about the contemporary global crisis of labor movements. Arguing against the view that this is a terminal crisis, the book concludes by exploring the likely forms that emergent labor movements will take in the twenty-first century. --Publisher's description. Contents: Introduction -- Labor movements and capital mobility -- Labor movements and product cycles -- Labor movements and world politics -- Contemporary dynamics in world-historical perspective -- Appendix A: The World Labor Group Database: conceptualization, measurement, and data collection procedures -- Appendix B: Instructions for recording data from indexes -- Appendix C: Country classifications.
Keywords: Automobile industry workers; Business relocation; Capitalism; Economic aspects History; Globalization; History; Labor disputes; Labor movement; Manufacturing processes; TEXTILE workers

Walking the Union Walk: Stories From the Communications, Energy, and Paperworkers Union - Swift, Jamie (Between the Lines, 2003)
Hi-tech tactics during a strike at a dockside factory in Montreal. A workplace cancer tragedy in Sarnia, Ontario. Immigrant workers sticking with their union at the chocolate factory. A struggle for pay equity in the courts and on the streets. A campaign to create jobs by cutting hours of work in B.C. An organizing drive 350 kilometres out into the frigid Atlantic. These are some of the fascinating stories told by Jamie Swift in his chronicle of the first ten eventful years of one of the most dynamic labour unions in North America. --Publisher's description
Keywords: Communication, Energy and Paperworkers Union of Canada; Employees; Energy industries; History; Labor Unions; Paper industry workers; Telecommunication

All Hell Can't Stop Us: The On-to-Ottawa Trek and Regina Riot - Waiser, W. A. (Bill) (Fifth House Books, 2003)
In early June 1935, one thousand relief-camp strikers clambered aboard freight trains to take their grievances to Ottawa. Their trek would end in bloodshed on the streets of Regina on 1 July 1935, later known as "The bloodiest day of the Depression." In All Hell Can't Stop Us, noted historian Bill Waiser examines the social and political background of the On-to-Ottawa Trek and Regina Riot, and provides an in-depth account of the strikers, their supporters, and their powerful adversaries. This gripping history includes many unpublished sketches and photographs. --Publisher's description
Keywords: Unemployed -- Canada -- History -- 20th century

Naming the System: Inequality and Work in the Global Economy - Yates, Michael D. (Monthly Review Press, 2003)
The economic boom of the 1990s created huge wealth for the bosses, but benefited workers hardly at all. At the same time, the bosses were able to take the political initiative and even the moral high ground, while workers were often divided against each other. This new book by leading labor analyst Michael D. Yates seeks to explain how this happened, and what can be done about it. Essential to both tasks is "naming the system"-the system that ensures that those who do the work do not benefit from the wealth they produce. Yates draws on recent data to show that the growing inequality - globally, and within the United States - is a necessary consequence of capitalism, and not an unfortunate side-effect that can be remedied by technical measures. To defend working people against ongoing attacks-on their working conditions, their living standards, and their future and that of their children-and to challenge inequality, it is necessary to understand capitalism as a system and for labor to challenge the political dominance of capitalist interests. Naming the System examines contemporary trends in employment and unemployment, in hours of work, and in the nature of jobs. It shows how working life is being reconfigured today, and how the effects of this are masked by mainstream economic theories. It uses numerous concrete examples to relate larger theoretical issues to everyday experience of the present-day economy. And it sets out the strategic options for organized labor in the current political context, in which the U.S.-led war on terrorism threatens to eclipse the anti-globalization movement. --Publisher's description.
Keywords: ANTI-globalization movement; Capitalism; Globalization; Income distribution; Industrial relations; Labor; Labor movement; QUALITY of work life; Unemployment

Tortillas and Tomatoes: Transmigrant Mexican Harvesters in Canada - Basok, Tanya (McGill-Queen's studies in ethnic history, 2002)
An exploration of the vital role played by Mexican seasonal workers in Canadian agriculture and how they have become a structural necessity in some sectors. Based on interviews with Leamington greenhouse growers and migrant Mexican workers, Tanya Basok offers a timely analysis of why the Seasonal Agricultural Workers Program is needed. She argues that while Mexican workers do not necessarily constitute cheap labour for Canadian growers, they are vital for the survival of some agricultural sectors because they are always available for work, even on holidays and weekends, or when exhausted, sick, or injured. Basok exposes the mechanisms that make Mexican seasonal workers unfree and shows that the workers' virtual inability to refuse the employer's demand for their labour is related not only to economic need but to the rigid control exercised by the Mexican Ministry of Labour and Social Planning and Canadian growers over workers' participation in the Canadian guest worker program, as well as the paternalistic relationship between the Mexican harvesters and their Canadian employers. --Publisher's description
Keywords: Foreign workers, Mexican; Ontario. Agricultural laborers, Foreign; Ontario. Agricultural laborers, Foreign. Foreign workers, Mexican; Ontario. Trabajadores extranjeros mexicanos; Ontario. Travailleurs agricoles étrangers; Ontario. Travailleurs étrangers mexicains

Colonization and Community: The Vancouver Island Coalfield and the Making of the British Columbian Working Class - Belshaw, John Douglas (McGill-Queen's University Press, 2002)
An examination of the social, political, and demographic history of British miners and their households on Vancouver Island in the nineteenth century. In the nineteenth century coal-miners imported from Europe, Asia, and eastern North America burrowed beneath the Vancouver Island towns of Nanaimo, Wellington, and Cumberland. No group was as numerous and influential in this enterprise as the hundreds of British immigrants who traveled half-way around the world to take up back-breaking work in the most remote colony in the Empire. What drew the British miners and their families to the north Pacific? Why did they set aside six months to journey to a colony about which they knew little? Once they reached Vancouver Island, what did they make of it and what did they make it into? And how did they re-make themselves in the process? In Colonization and Community John Belshaw takes a new look at British Columbia's first working class, the men, women, and children beneath and beyond the pit-head. Beginning with an exploration of emigrant expectations and ambitions, he investigates working conditions, household wages, racism, industrial organization, gender, schooling, leisure, community building, and the fluid identity of the British mining colony, the archetypal west coast proletariat. By connecting the story of Vancouver Island to the larger story of Victorian industrialization, he delineates what was distinctive and what was common about the lot of the settler society. Belshaw breaks new ground, challenging the easy assumptions of transferred British political traditions, analyzing the colonial at the household level, and revealing the emergent communities of Vancouver Island as the cradle of British Columbian working-class culture. --Publisher's description

Labour Law in Canada - Carter, Donald D.; England, Geoffrey; Etherington, Brian; Trudeau, Gilles (Wolters Kluwer, 2002)
For a clear understanding of the legal protections and remedies available to employers and workers in Canada, this convenient survey and analysis is ideal. Although it may be said that there are eleven distinct systems of labour law in Canada - encompassing ten provinces and the Federal government - the authors ensure depth of treatment by focusing on common policy themes and typical legal solutions, with significant departures noted in whatever province or area of law they may arise. However, the relevant law of the three most populous and influential provinces - Quebec, Ontario, and British Columbia - is covered in particular detail, as is Federal labour legislation and case law. Among the important areas of Canadian law and practice emphasised are the following: the tension between trade union power and business flexibility; collective "labour law" and individual "employment law"; the effect of the North American Free Trade Agreement; the central place of the legal concept of the employment contract; labour standards legislation; the influence of the 1982 Charter of Rights and Freedoms; court intervention in labour law, both under common law principles and Quebec's civil code; the role of labour relations boards; and judicial review of administrative decisions and arbitration awards. As an accurate and usable guide for lawyers not expert in Canadian law, Labour Law in Canada is without peer. --Publisher's description
Keywords: Bargaining; Collective Agreements; Labour Movement; Labour law; Trades; Unions

Bienfait: The Saskatchewan Miners' Struggle of '31 - Endicott, Stephen Lyon (University of Toronto Press, 2002)
Against all odds, the miners of Bienfait, Saskatchewan, attempted, in 1931, to change their miserable situation by organizing a union. Exploring the social consequences of capitalist restructuring during the Great Depression, Stephen Endicott focuses on the miners' tumultuous thirty-day strike. Their bid to gain union recognition with the aid of the Workers' Unity League of Canada ultimately failed, and Endicott's in-depth examination of the key factors and players attempts to explain why this was the case and why a similar union drive a decade later succeeded." "Based on a large number of both oral and written primary resources, Bienfait offers a new interpretation of the role of corporations, governments, courts, and the police in the events surrounding the strike. In the process, Endicott demonstrates how a militant union leadership helped the workers gain the strength and unity of purpose to challenge the powers of wealth and deep-seated prejudice. Bienfait opens a new chapter in the history of Canadian labour relations that reveals much about Canadian and Canadian society during the Depression. --Publisher's description
Keywords: Coal Miners' Strike, Estevan, Sask., 1931.; Grève des mineurs de charbon, Estevan, Sask., 1931

Cabbagetown: The Classic Novel of the Depression in Canada - Garner, Hugh (McGraw-Hill Ryerson, 2002)
Toronto's Cabbagetown in the Depression...North America's largest Anglo-Saxon slum. Ken Tilling leaves school to face the bleak prospects of the dirty thirties-where do you go, what do you do, how do you make a life for yourself when all the world offers in unemployment, poverty and uncertainty?"As a social document, Cabbagetown is as important and revealing as either The Tin Flute or The Grapes of Wrath. Stern realism has also projected upon the pages of a whole gallery of types, lifelike and convincing. He is well fitted to hold the mirror up to human nature." Globe and Mail.Cabbagetown was first published in an abbreviated paperback edition in 1950 and was published in its entirety in 1968. This, the first quality paperback edition, contains the full unexpurgated text of Cabbagetown. --Publisher's description
Keywords: Poor; Poverty; Slums; Social Class and Equality; Toronto (Ont.); Unemployment

Their Own History: Women's Contribution to the Labour Movement of British Columbia - Griffin, Betty; Lockhart, Susan (United Fishermen & Allied Workers Union/CAW Seniors Club, 2002)
The United Nations declared 1975 International Women's Year for the purpose of promoting equality of men and women.... Canada alloted funds for projects aimed at achieving these objectives and many projects were undertaken across the country. The Central Council of Women's Auxiliaries to the United Fishermen & Allied Workers' Union at its annual convention in 1975 undertook to write a history highlighting women's contribution to the trade union movement in British Columbia. Finally, here is that book. Working people in BC have a proud history: a history that accalims the struggles for a better life, a better job and a better community. In 1975, we set out to record the history of the women of British Columbia who struggled for human rights and women's equality and who helped build our trade unions. We interviewed and recorded a wonderful group of women and men. And we appreciated all their stories. [This book] shares those stories. --Publisher's description
Keywords: Biographies; British Columbia; Femmes Travail Colombie-Britannique Histoire; Femmes dans le mouvement ouvrier Colombie-Britannique Histoire; History; Personnel féminin Colombie-Britannique Biographies; Women Employment; Women Employment British Columbia History; Women employees; Women employees British Columbia Biography; Women in the labor movement; Women in the labor movement British Columbia History

Is Anyone Listening?: Women, Work, and Society - Jacobs, Merle; Armstrong, Pat; Armstrong, Hugh; Bannerji, Himani; Hagey, Rebecca; MacKay, Robert W.; Ng, Roxana; Gupta, Tania Das; George, Usha; Bruckert, Chris; Kirk, Jo-Anne; Daenzer, Patricia; et al. (Women's Press, 2002)
Jacobs has brought together the work of a number of progressive feminist writers, who theorize gender, race, diversity research, the social construction of women and work, ethnicity and class. The essays in this reader are focused on issues relating to gender equality in workspaces in society. The editor has gathered essays from well-known and established social scientists. Among them are Pat and Hugh Armstrong, Himani Bannerji, Christine Bruckert and Tania Das Gupta. The result is a stimulating collection that focuses on health-care workers, teachers, strippers, wage-less workers and women who are hidden from view. The collection explores the construction of gender, the selection of careers and the differential in work conditions and wages. --Publisher's description. Contents: Theorizing women's work: feminist methodology / Pat Armstrong and Hugh Armstrong -- The paradox of diversity: the construction of a multicultural Canada and "women of colour" / Himani Bannerji -- Qualitative research to identify racialist discourse: towards equity in nursing curricula / Rebecca Hagey and Robert W. MacKay -- Teaching against the grain: contradictions and possibilities / Roxana Ng -- Racism in nursing / Tania Das Gupta -- Toward anti-racism in social work in the Canadian context / Usha George -- The world of the professional stripper / Chris Bruckert -- Gender inequality and medical education / Jo-Anne Kirk -- Benevolent patriarchy: the foreign domestic movement, 1980-1990 / Patricia Daenzer -- The new wageless worker: volunteering and market-guided health care reform / Elizabeth Esteves -- "Who else would do it?": female family caregivers in Canada / Kristin Blakely -- Marginal women: examining the barriers of age, race and ethnicity / Robynne Beugebauer -- Creating understanding from research: staff nurses' views on collegiality / Merle Jacobs -- Antiracism advocacy in the climate of corporatization / Rebecca Hagey, Jane Turrittin, Evelyn Brody -- Undertaking advocacy / Merle Jacobs.

Harnessing Labour Confrontation: Shaping the Postwar Settlement in Canada, 1943-1950 - McInnis, Peter S. (Peter Stuart) (University of Toronto Press, 2002)
The 1940s in Canada are crucial to the understanding of labour history in this country. Following the Depression, and sparked by the need to mobilize the workforce during the Second World War, this decade led to a restructuring of the relationship between labour and the state. In Harnessing Labour Confrontation, Peter S. McInnis examines the reformation of Canadian society and its industrial relations regime from the perspective of labour organizations and their supporters and from that of government and business. What results is a synthesis of labour and political history, which the author uses to analyze in a North American context the role of confrontation and heated debate in the formation of a national postwar compromise and in the birth of a modern welfare state.Among the factors affecting the postwar compromises were, argues McInnis, the divided jurisdiction between federal and provincial governments, the return to gender-biased societal norms, a developing Cold War climate of national insecurity, and a promise of strong consumer purchasing power based on postwar wages and benefits packages. While some of the results of the 1940s compromise and the welfare state remains intact today, many of the political and social structures have deteriorated in the last two decades. --Publisher's description

Cows Don't Know It's Sunday: Farming in St. John's - Murray, Hilda Chaulk (Social and economic studies (St. John's, NL), 2002)
Before 1950, the greatest number of Newfoundland farmers lived in the St. John's area. They and the townsfolk were interdependent, with the farmers providing meat, poultry, garden and dairy products to the city, while St. John's served as a ready market and a source of cash income. Although many street names serve as reminders of those who once worked the land, and others perpetuate old homesteads, the farmers of St. John's are as unknown today as though they had never been. Cows Don't Know It's Sunday gives a historical overview of farming and its importance to the economy of Newfoundland, and describes in detail, using the words of more than eighty people who grew up on or near farms, what it was like to farm in and around St. John's in the period within living memory. Farmers worked seven days a week throughout the year. This study of both the work life and social life of the farmers of St. John's is a tribute to the farming families who were the mainstay of the city during the first half of the twentieth century. --Publisher's description

The Contested Past: Reading Canada's History: Selections from the Canadian Historical Review - Shore, Marlene (University of Toronto Press, 2002)
This collection of selected excerpts focuses on the Canadian Historical Review's contribution to the study of Canadian history from the journal's founding in 1920 to the present. Using the CHR's own interconnected objectives as a benchmark - the promotion of high standards of historical research and writing in Canada, and the fostering of the study of Canadian history - Marlene Shore analyses the varying degrees of success the journals had in meeting its those goals. Her introductory essay shows how the CHR was shaped not only by its own editorial policies, but by international currents affecting the discipline of history and its practitioners. The excerpts, each accompanied by critical commentary, were chosen as representative of the major trends, crucial studies, and main controversies in Canadian historical writing. Shore has arranged them chronologically and thematically into four sections: Nation and Diversity, 1920-1939; War, Centralization, and Reaction, 1940-1965; The Renewal of Diversity, 1966 to the Present; and Reflections. Among the key themes explored by Shore and the contributing historians, Native-European contact, society and war, the nature of Canadian and Quebec nationalism, class-consciousness, and gender politics are highlighted. Broad in scope and focused in intent, The Contested Past offers an excellent introduction to twentieth century Canadian history and historiography. --Publisher's description
Keywords: Canada -- Historiography

Contingent Work, Disrupted Lives: Labour and Community in the New Rural Economy - Winson, Anthony; Leach, Belinda (Studies in comparative political economy and public policy, 2002)
[E]xamines the effects of economic globalization on several manufacturing-dependent rural communities in Canada. In looking at such contemporary corporate strategies as plant closures and downsizing, authors [The authors] consider the impact of capitalist restructuring on the residents of various communities. [They] argue that the new rural economy has caused considerable instability and hardship in the lives of rural residents as they struggle to adapt in the face of economic upheaval."--Publisher's description. Contents: The Global and the Local: Understanding Globalization through Community Research -- Community Sketches, History, and Method -- The New Rural Economy and the Shape of Restructuring -- Skidding into the Contingent Work World -- 'Forget All Your Dreams and Good Luck with Your Life': Lay-Off and the New Reality of Contingent Labour -- Economic Diversity, Sustainability, and Manufacturing Communities. Geographic: Ontario. Ontario. Includes bibliographical references (pages 205-220) and index.
Keywords: Aspect social; Ontario. Chômage en milieu rural; Ontario. Deindustrialization; Ontario. Deindustrialization. Displaced workers. Globalization; Ontario. Desempleo; Ontario. Displaced workers; Ontario. Désindustrialisation; Ontario. Globalization; Ontario. Industrie rurale; Ontario. Mondialisation; Ontario. Rural industries; Ontario. Trabajadores; Ontario. Travailleurs; Ontario. Travailleurs licenciés; Ontario. Working class; Rural unemployment; Social aspects; Social aspects. Rural industries. Rural unemployment. Working class. Landwirtschaft. Arbeitslosigkeit

Mirrors of Stone: Fragments from the Porcupine Frontier - Angus, Charlie; Palu, Louie (Between the Lines, 2001)
Mirrors of Stone delves into the many ethnic cultures that thrived in the mining areas of Northern Ontario from the 1920s to the 1960s. The stormy history of hardrock mining camps has never fit into the comfortable cliches by which Canada “tells its story.” Angus unearths the dark sides of this history–“the wild tales of bootleggers, mobsters, and prostitution rings” and in so doing opens up new ways of seeing Ontario’s history and culture. --Publisher's description

Building a Better World: An Introduction to Trade Unionism in Canada - Black, Errol; Silver, Jim (Fernwood, 2001)
This introductory text examines the vital role of trade unions in Canada. In particular, it emphasizes how the values. objectives and activities of unions are shaped and changed in the context of employer opposition and often hostile governments. --Publisher's description.
Keywords: Labor unions -- Canada

Framing Our Past: Canadian Women's History in the Twentieth Century - Cook, Sharon Anne; McLean, Lorna; O'Rourke, Kate (McGill-Queen's University Press, 2001)
Framing Our Past is about women's lived experience. Drawing from diaries, oral history, letters, organizational records, paintings, quilts, dressmaking patterns, milliners' records, and posters, the contributors offer fresh interpretations of this historical material and unique insights into the lives of individual Canadian women who expanded the boundaries of traditional roles. Lavishly illustrated, Framing Our Past looks at women and their social rituals with other women, organized sporting clubs, philanthropic, spiritual and aesthetic activities, study and reading groups. The authors explore women's roles as nurturers and keepers of the hearth and in family management, child care, and health care. They highlight women's work in areas as diverse as domestic labour, nursing, dressmaking, broadcasting, and banking as well as women's contributions to education and their instrumental political role in consumer activism, social work, and peace movements. --Publisher's description
Keywords: Women -- Canada -- History -- 20th century

La pensée de Gustave Francq, syndicaliste et réformateur social : textes choisis, 1905-1948 - Francq, Gustave; Leroux, Éric (Collection RCHTQ, 2001)
Keywords: 1900-1999; Canada; Francq, Gustave, 1871-1952 Pensée politique et sociale; Francq, Gustave, Political and social view; History; Labor unions; Labor unions Canada History 20th century; Québec; Québec (Province) Conditions sociales 20e siècle; Québec (Province) Social conditions 20th century; Social conditions; Syndicalism; Syndicalism Québec (Province) History; Syndicalisme Québec (Province) Histoire; Syndicats Canada Histoire 20e siècle

Labour Before the Law: The Regulation of Workers' Collective Action in Canada, 1900-1948 - Fudge, Judy; Tucker, Eric (Canadian social history series, 2001)
In this study of the relations between workers and the state, Judy Fudge and Eric Tucker examine the legal regulation of workers' collective action from 1900 to 1948. They analyze the strikes, violent confrontations, lockouts, union organizing drives, legislative initiatives, and major judicial decisions that transformed the labour relations regime of liberal voluntarism, which prevailed in the later part of the nineteenth century, into industrial voluntarism, whose centrepiece was Mackenzie King's Industrial Disputes Investigation Act of 1907. This period was marked by coercion and compromise, as workers organized and fought to extend their rights against the profit-oriented owners of capital, while the state struggled to define a labour regime that contained industrial conflict. The authors then trace the conflicts that eventually produced the industrial pluralism that Canadians have known in more recent years." "The book is simultaneously & history of law, aspects of the state, trade unions and labouring people, and their interaction within the broad and shifting terrain of political economy. The authors are attentive to regional differences and sectoral divergences, and they attempt to address the fragmentation of class experience. -- Publisher's description
Keywords: 20e siecle. Travail; 20th century. Syndicats; Canada; Droit; Histoire; History; Labor Unions; Law and legislation

A Very Red Life: The Story of Bill Walsh - Gonick, Cy (Past CCLH Publications, 2001)
Montreal-born Moishe Wolofsky was a nineteen year-old unemployed university drop-out in 1930 when he and his friend Dick Steele took a job aboard an ocean vessel, beginning a journey that would change his life forever. Out of money, they stumbled into Russia and took jobs in a tractor factory. There, they became dedicated communists. Dragged back to Canada by his father, the well-known Jewish publisher, Herschel Wolofsky, he soon began a career as an organizer for the Communist Party of Canada. By then Moishe Wolofsky had become Bill Walsh. Still a very young man, he led the drive to organize the rubber workers in Kitchener and subsequently the auto workers in Windsor. Jailed and interned along with several hundred other Communists, upon his release Walsh fought overseas in Holland and Belgium. After the war he took a staff position with the United Electrical Workers in Hamilton, a job he retained for over two decades. After years of conflict with UE President C.S. Jackson, Walsh was forced to quit his job and subsequently the Communist Party. In the late 60s, he began a new career in labour arbitration. This is the story of how a young idealist became a Red and helped build industrial unionism in Canada. But it is also a story of romance and adventure. Walsh actively participated in many of the 20th century's historic events. Everything he did was touched with an intensity. He was a brilliant strategist and an extraordinary teacher. Because he never held high office either in politics, in uniform, or in any of the unions he was associated with, his contributions have gone unheralded. This book provides an inside, bottom-up look at some of the most important episodes in our trade union history as well as an insight into the functioning of a venerable communist-led union. --Publisher's description
Keywords: Arbitrators, Industrial; Communist Party of Canada; Labor leaders; Political activists; United Electrical, Radio and Machine Workers of America; Walsh, Bill, 1910-2004

Gustave Francq : figure marquante du syndicalisme et précurseur de la FTQ - Leroux, Eric (VLB, 2001)
Intellectuel du mouvement ouvrier, Gustave Francq (1871-1952) a suivi une carrière hors de l’ordinaire. Il a occupé une place dans les hautes sphères décisionnelles du mouvement syndical nord-américain pendant plus de quarante ans. Sa contribution à la mise sur pied de la Fédération provinciale du travail du Québec fait de lui un précurseur de la Fédération des travailleurs et des travailleuses du Québec (FTQ). À ce sujet, soulignons qu’il est le fondateur du journal Le Monde ouvrier, aujourd’hui l’organe officiel de la FTQ. --Résumé de l'éditeur
Keywords: Francq, Gustave, 1871-1952

Getting By in Hard Times: Gendered Labour at Home and on the Job - Luxton, Meg; Corman, June Shirley (University of Toronto Press, 2001)
[D]escribes the experiences of daily life for predominantly white, working class women and men during the period of "economic restructuring" begun in the 1980s. Luxton and Corman show how the shift from a pattern where women were full-time housewives and men were income earners, to one where women are increasingly income earners as well, is altering the experience of everyday life Based on a case study conducted from 1980 to 1996, of households where one person was employed at Stelco's manufacturing plant in Hamilton, Ontario, the book examines how working class families make a living by combining paid employment and unpaid domestic labour. During this period of government cutbacks the loss of secure employment for men (as the steel plant cut its labour force by about two-thirds), combined with women's increasing participation in the labour force, resulted in lower standards of living, reduced income, and the imposition of more unpaid work on family households. [The book] examines how growing insecurities undermined class politics while increasing gender, racial, and ethnic tensions. By focusing on the daily coping strategies of white working class women and men, the book shows the human face of changing gender, race, and class politics in Canada. --Publisher's description.
Keywords: Attitudes; Case studies; Class consciousness; Hamilton, Ontario; Iron and steel workers; Sex role; Working class

Remember Kirkland Lake: The Gold Miners' Strike of 1941-42 - MacDowell, Laurel Sefton (Canadian Scholars' Press, 2001)
[This book] tells the story of one of the most important industrial disputes in Canadian labour history. This strike united the Canadian labour movement around the demand for collective bargaining legislation, which it won in 1944 and which remains central to our industrial relations system. The book provides a comprehensive analysis of all the factors in this dramatic dispute. At the community level, a social history approach examines the local living and working conditions of the miners and their families, the role of the women in the dispute, and the ethnic makeup of the workforce. -- Publisher's description
Keywords: Canada; Gold Miners' Strike, Kirkland Lake, Ont., 1941-1942. Collective bargaining; History; Mining industry

Renegade Lawyer: The Life of J.l. Cohen - MacDowell, Laurel Sefton (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2001)
J.L. Cohen, one of the first specialists in labour law and an architect of the Canadian industrial relations system, was a formidable advocate in the 1930s and 1940s on behalf of working people. A 'radical lawyer' in the tradition of the great American counsel Clarence Darrow or contemporary advocate Thomas Berger who represent the less powerful and seek to reform society and to protect civil liberties, Cohen was also a 'labour intellectual' in Canada, similar to those supporting Roosevelt's New Deal in the United States. He wrote Collective Bargaining in Canada, served on the National War Labour Board, and advised the Ontario government about policy issues such as mothers' allowances, unemployment insurance legislation, and labour law..

Beyond Service: State Workers, Public Policy, and the Prospects for Democratic Administration - McElligott, Greg (Institute of Public Administration of Canada series in public management and governance, 2001)
This study concerns one department of Canadian government - Employment and Immigration Canada (EIC) - and one policy field - labour market policy - from 1976 to 1991. McElligott unearths resistance in workplaces where 'cutting edge' neoconservative managers have been trying to reshape government services, and inserts front-line workers into state theories, policy debates, and progressive political strategies. He argues that the neglect of these workers makes key state theories incomplete and separates policy-making theory - and practice - from actual state outputs. One consequence is that progressive thinkers and activists have forgone many promising strategic opportunities." "Beyond Service challenges current trends in administrative theory and policy-making, and will be of interest to academics, policy research bodies, union researchers, educators, and, most important, front-line government workers themselves. --Publisher's description
Keywords: Angestellter; Canada; Canada. Emploi et immigration Canada (Ministère) Fonctionnaires Cas, Études de; Canada. Employment and Immigration Canada (Department); Canada. Employment and Immigration Canada (Department) Officials and employees Case studies; Case studies; Civil service; Civil service Canada; Employee-management relations in government; Employee-management relations in government Canada; Employees; Fonction publique Canada; Fonction publique Relations de travail Canada; Kanada Government; Management Employee participation; Management Employee participation Canada; Personalpolitik; Personnel Participation à la gestion Canada; Verwaltung; Études de cas

The Tyranny of Work: Alienation and the Labour Process - Rinehart, James W. (Harcourt Canada, 2001)
The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. Completely updated to reflect current trends in the labour force and research in the field of labour studies, The Tyranny of Work begins with a thorough discussion of work as a social problem and the sources of alienation. The book then examines the development of industrial capitalism in Canada, the white-collar and blue-collar worlds, and, finally, solutions to the problem of alienated labour. All statistics and data have been updated to reflect the most current research. Information from the 2001 Census has been integrated throughout the text. The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. --Publisher's description, 5th edition (2005).Contents: 1. Work as a social problem -- 2. Alienation and its sources -- 3. Alienation and the development of industrial capitalism in Canada -- 4. Post-industrial society and white-collar worlds -- 5. Blue-collar crime -- 6. Restructuring organizations and work -- 7. Solutions to alienated labour. Includes bibliographical references (pages 218-245) and index;
Keywords: Labor -- Canada

Montmorency : histoire d'une communauté ouvrière - Simard, Jean-François (Septentrion, 2001)
Voici une fresque émouvante de la vie des gens attachants qui ont fait au fil des siècles l’histoire touchante de cette petite ville dont le site naturel du " Sault de Montmorency ", comme l’avait baptisé Champlain, est connu de tous. Le syndicaliste Fernand Daoust, qui rédige la préface de cet ouvrage, n’hésite pas à affirmer que " Jean-François Simard, par un remarquable travail de recherche minutieuse et parfois inédite, brosse un saisissant tableau d’une petite société qui souffre, qui peine mais qui rêve aussi tout au long de ses inépuisables générations […] ". Ballottés du monde rural au monde industriel puis postindustriel, les gens de Montmorency ont développé une conscience sociale qui a marqué la lutte des travailleurs québécois. En rappelant les péripéties de ces bouleversements, Jean-François Simard nous convie à un devoir de mémoire, d’attachement et de reconnaissance envers un petit coin attachant du Québec dont le labeur et le sens des responsabilités de ses habitants ont contribué à forger l’identité d’un peuple et à perpétuer ses valeurs d’endurance et de solidarité. L’histoire des femmes et des hommes qui ont vécu à Montmorency fait partie de notre patrimoine collectif et appartient à tout le Québec. Cet ouvrage s’intéresse donc à l’essor puis au déclin d’une petite communauté ouvrière, patrie de Fernand Dumont qui s’en est grandement inspiré pour ses travaux. Cette communauté, dans sa relation au double mouvement d’industrialisation et de désindustrialisation qui a rythmé l’avènement du capitalisme au cours du dernier siècle, a marqué de manière indélébile la quête des ouvriers québécois pour une plus grande justice sociale. --Résumé de l'éditeur
Keywords: Classe ouvrière; Condition sociale; Condition économique; Développement économique régional; Histoire; History; Industrie Québec (Province) Montmorency (Beauport) Histoire; Industries; Industries Québec (Province) Montmorency (Beauport) History; Montmorency (Beauport, Québec); Montmorency (Beauport, Québec) Conditions sociales; Montmorency (Beauport, Québec) Histoire; Montmorency (Beauport, Québec) History; Montmorency (Beauport, Québec) Social conditions; Ouvrier; Québec (Canada; province) Conditions sociales; Social conditions; Sociologie rurale; Syndicalism; Syndicalism Québec (Province) Montmorency (Beauport) History; Syndicalisme Québec (Province) Montmorency (Beauport) Histoire; Travail

Public-Sector Labour Relations in an Era of Restraint and Restructuring - Swimmer, Gene; Rose, Joseph B.; Wagar, Terry H.; Philips, Paul; Stecher, Carolina; Reshef, Yonatan; Thompson, Mark; Bach, Sandra; Adams, Roy J. (Oxford University Press, 2001)
The 1990s in Canada will probably go down as the most stressful decade for public-sector industrial relations since the inception, 25 years earlier, of collective bargaining in the public service. Government debt and defecits became the rationale for downsizing, outsourcing, privatization, layoffs, buyouts, and early retirement packages at both the federal and provincial levels. When workers' bargaining units did not bend to government demands at the negotating table, and when leaders did not blink at the threat of restrictive legislation, then governments of both the right and the left at times found it convenient to legislate rule changes to suit their fiscal or ideological purposes. The contributors to Public-Sector Labour Relations examine in depth the events of recent years in the public service of six jurisdictions―Nova Scotia, Ontario, Manitoba, Alberta, British Columbia, and the federal government. Trends in the other five Canadian provinces are also considered. Only in BC has there been an essentially co-operative labour relations environment, although even in this province, public service employment has dropped considerably. Overall, from 1991 to 1997, provincial civil service employment fell by 15 per cent, while the federal employment reduction was 14 per cent. (From the employment peak in 1993-4, the overall provincial reduction was over 22 per cent.) Although collective bargaining is still alive, a major conclusion of this study is that collective bargaining in the Canadian public sector is not well. The cases reported here demonstrate that governments have adopted the attitude and policy that they may engage in bargaining or suspend it whenever they find that course of action to be convenient. Viewed from a broader international context, as discussed in the concluding chapter, the casual suspension of bargaining by Canadian governments cannot be justified by the norms and agreements that Canada has shared with the international community. -- Publisher's description. Contents: Public-sector labour relations in an era of restraint and restructuring: an overview / Gene Swimmer -- Provincial government restructuring in Nova Scotia: the freezing and thawing of labour relations / Terry H. Wagar -- From softball to hardball: the transition in labour-management relations in the Ontario public service / Joseph B. Rose -- Fiscal restraint, legislated concessions, and labour relations in the Manitoba civil service, 1988-1997 / Paul Phillips and Carolina Stecher -- The logic of union quiescence: the Alberta case / Yonatan Reshef -- Labour relations in the BC public service: blowing in the political wind / Mark Thompson -- Restructuring federal public-sector human resources / Gene Swimmer and Sandra Bach -- Public-employee relations: Canadian developments in perspective / Roy J. Adams.

Union Learning: Canadian Labour Education in the Twentieth Century - Taylor, Jeffery M. (Thompson Educational, 2001)
Over 100,000 Canadian workers participate annually in educational programs conducted by their union or the broader labour organizations to which their union belongs. Union-based education is the most significant nonvocational education available to working people. This activity has been going on for decades, and Jeffery Taylor's Union Learning: Canadian Labour Education in the Twentieth Century is the first comprehensive history of it. Union Learning chronicles the rise and decline of the Workers' Educational Association, the development of internal union educational programs, the consolidation of the Canadian Labour Congress's educational system after 1956, the origin and growth of the Labour College of Canada, and the patchy history of university and college involvement in labour education. Taylor argues that a new emphasis on broad-based and activist education today promises to rekindle the sense of an educational movement that was present in the labour movement in the 1930s and 1940s. The book includes a number of illustrative sidebars and photographs. The author has developed a website containing images, video and other materials related to the history of labour education in Canada: http://unionlearning.athabascau.ca. --Publisher's description
Keywords: 20th century; Canada; Education History; History; Labor unions and education; Working class

A Fishery for Modern Times: The State and the Industrialization of the Newfoundland Fishery, 1934-1968 - Wright, Miriam (Canadian social history series, 2001)
In the early 1990s, the northern cod populations off the coast of Newfoundland had become so depleted that the federal government placed a moratorium on commercial fishing. The impact was devastating, both for Newfoundland's economy and for local fishing communities. Today, although this natural resource exploited commercially for over 500 years appears to be returning in diminished numbers, many fisheries scientists and fishers question whether the cod will ever return to its former abundance. In A Fishery for Modern Times, Miriam Wright argues that the recent troubles in the fishery can be more fully understood by examining the rise of the industrial fishery in the mid-twentieth century. The introduction of new harvesting technologies and the emergence of 'quick freezing', in the late 1930s, eventually supplanted household production by Newfoundland's fishing families. While the new technologies increased the amount of fish caught in the northwest Atlantic, Wright argues that the state played a critical role in fostering and financing the industrial frozen fish sector. Many bureaucrats and politicians, including Newfoundland's premier, Joseph Smallwood, believed that making the Newfoundland fishery 'modern', with centralization, technology, and expertise, would transform rural society, solving deep-seated economic and social problems. A Fishery for Modern Times examines the ways in which the state, ideologies of development, and political, economic, and social factors, along with political actors and fishing company owners, contributed to the expansion of the industrial fishery from the 1930s through the 1960s. While the promised prosperity never fully materialized, the continuing reliance on approaches favouring high-tech, big capital solutions put increasing pressure on cod populations in the years that followed. As Wright concludes, 'We can no longer afford to view the fisheries resources as 'property' of the state and industry, to do with it as they choose. That path had led only to devastation of the resource, economic instability, and great social upheaval." --Publisher's description

Ringing in the Common Love of Good: The United Farmers of Ontario in Lambton, Simcoe and Lanark Counties, 1914-1926 - Badgley, Kerry (McGill-Queen's University Press, 2000)
Founded in 1914, the United Farmers of Ontario (UFO) became a significant force in the province, winning the most seats in the 1919 provincial election and forming a governing coalition with the Independent Labour Party. The UFO and its companion organizations, the United Farmers Cooperative Company (UFCC) and the United Farm Women of Ontario (UFWO), flourished, achieving much of its success by challenging those who controlled the economic, political, and social structures in Ontario and advancing an alternative vision of democracy that sought to maximize citizen participation in the decision-making process. By the mid-1920s the UFO had gone into a period of decline from which it never recovered. The promise of equality hoped for by UFWO members never materialized and the UFCC, once a key component in the development of an alternative vision, began to focus more on profits than on politics. In Ringing in the Common Love of Good Kerry Badgley explores both the rise and the fall of the UFO, focusing on the Ontario counties of Lambton, Simcoe, and Lanark. He challenges the liberal-capitalist interpretation that the movement was nothing more than a group of impatient Liberals, as well as the Marxist view that the UFO consisted of self-interested independent commodity producers. Badgley argues that as the UFO broke free from hegemonic forces it developed alternative economic, political, and social visions, but that it was these same forces, combined with internal struggles and a conservative leadership, that ultimately resulted in the decline of the movement as a vehicle for democratic change in Ontario. --Publisher's description

Employment Equity Policy in Canada: An Interprovincial Comparison - Bakan, Abigail B.; Kobayashi, Audrey Lynn (Status of Women Canada, 2000)
Keywords: Canada; Discrimination in employment; Employment Government policy; Government policy; Minority women

A Square Deal for All: Historical Essays on Labour in Brandon - Black, Errol; Mitchell, Tom (Canadian Committee on Labour History, 2000)
The authors' careful analyses of labour and working-class organizations in Brandon are aimed at reconstructing and disclosing aspects of the history of class and class relations. While other western Canadian cities, Winnipeg, for example, have received much deserved attention by historians, studies of other cities, such as Brandon, in the early 20th century help to provide a more well-rounded understanding of working-class life in Canada during this period. In the tradition of the new labour history Black and Mitchell pay close attention to the unique development of class relations in the community of Brandon, while placing that community in a broader, national context. This work includes a careful consideration of the working class in Brandon, the particular obstacles and challenges workers there faced, and makes an important contribution to our understanding of class relations in Canada. --Website description
Keywords: History; Labor; Labor Manitoba Brandon History; Labor movement; Labor movement Manitoba Brandon History; Manitoba Brandon; Mouvement ouvrier Manitoba Brandon Histoire; Travail Manitoba Brandon Histoire; Travailleurs Manitoba Brandon Histoire; Working class; Working class Manitoba Brandon History

English Immigrant Voices: Labourers' Letters from Upper Canada in the 1830s - Cameron, Wendy; Maude, Mary McDougall; Haines, Sheila (McGill-Queen's University Press, 2000)
Emigrants sent by the Petworth Emigration Committee were part of a wave of rural workers in the 1830s whose immigration to Upper Canada was sponsored by English parishes and landlords. Their letters written or dictated to family and friends, leave us a rare first-hand view of the immigrant experience from a working-class perspective. Collected from published, archival, and private sources, these letters place the Petworth immigrants in the context of their times and challenge the image of English immigrants to 1830s Upper Canada as officers and gentlewomen. Wendy Cameron, Sheila Haines, and Mary McDougall Maude have carefully annotated the letters to sketch the stories of individual writers, link letters by the same author or members of the same family, and explore the connections between writers. What eventually happened to some of the writers is also revealed in this engaging collection. English Immigrant Voices provides a valuable insight into the rural poor and their experiences in emigrating to a new land. --Publisher's description
Keywords: 19th century; British; Correspondence; History; Immigrants; Ontario; Working class

Canadian Marxists and the Search for a Third Way - Campbell, J. Peter (McGill-Queen's University Press, 2000)
The triumphs and failures of four Canadian Marxists who advocated organization and education rather than armed struggle in the revolutionary overthrow of capitalism and the creation of socialism. Literature on Marxist socialists in Canada has usually been written by those within the social democratic or Marxist-Leninist traditions and has generally failed to break free of the political biases of the defenders of these traditions. Canadian Marxists and the Search for a Third Way steps outside these approaches to appraise early Canadian Marxists on their own terms. Peter Campbell argues that their Marxism was a changing and evolving product of their intellectual development and day-to-day interaction with the Canadian working class. It was a dynamic, theoretical system that provided a "third way" to look at Marxism, a revolutionary socialism that rejected violence in favour of the broadest organization and education of the working-class majority. Focusing on four individuals, Canadian Marxists and the Search for a Third Way describes the lives and ideas of Ernest Winch, Bill Pritchard, Bob Russell, and Arthur Mould and examines their efforts to put their ideas into practice. Campbell begins by looking at their childhoods in Great Britain, particularly their religious upbringing. He considers their family life, their attitudes toward women and ethnic minorities, what they were reading, and what effect that reading had on their theory and practice. He describes their lives as labor leaders and advocates of socialism, revealing how tenaciously, in an increasingly hierarchical, bureaucratized, and state-driven capitalist society, they held to the idea that socialism must be created by the working class itself. This is a unique look at four Canadian Marxists and their struggle to create an educated, disciplined, democratic, mass-based movement for revolutionary change. --Publisher's description

Click, Clack, Moo: Cows That Type - Cronin, Doreen; Lewin, Betsy (Simon & Schuster Books for Young Readers, 2000)
Farmer Brown has a problem. His cows like to type. All day long he hears Click, clack, MOO. Click, clack, MOO. Clickety, clack, MOO. But Farmer Brown's problems REALLY begin when his cows start leaving him notes.... Doreen Cronin's understated text and Betsy Lewin's expressive illustrations make the most of this hilarious situation. Come join the fun as a bunch of literate cows turn Farmer Brown's farm upside down. --Publisher's description
Keywords: Cows; Domestic animals; Fiction; Typewriters

No Logo: Taking Aim at the Brand Bullies - Klein, Naomi (Flamingo, 2000)
The hotly debated report from the frontlines of mounting backlash against multinational corporations. A national bestseller, No Logo took Canadians by storm when it was published last year in hardcover. Equal parts cultural analysis, political manifesto, mall-rat memoir, and journalistic exposé, it is the first book to uncover a betrayal of the central promises of the information age: choice, interactivity, and increased freedom. No Logo takes apart our packaged and branded world and puts the pieces into clear pop-historical and economic perspective. Naomi Klein tracks the resistance and self-determination mounting in the face of our new branded world and explains why some of the most revered brands in the world are finding themselves on the wrong end of a bottle of spray paint, a computer hack, or an international anti-corporate campaign. --Publisher's description, Vintage edition
Keywords: Anti-Corporation; Brands; Corporate power; Multinational Corporations; Retail

Les relations du travail au Québec - Leclerc, Michel; Quimper, Michel (Presses de l'Université du Québec, 2000)
Les auteurs décrivent les aspects historiques, légaux et sociaux du Québec et les comparent avec ceux qui prévalent ailleurs. Ils brossent un tableau de la législation du travail, de la vie syndicale, de la négociation collective, de la gestion de la convention collective et de l'avenir des relations du travail. --Publisher's description
Keywords: Collective bargaining; Collective bargaining Québec (Province); Droit du travail; Employee-management relations in government; Employee-management relations in government Québec (Province); Industrial relations; Industrial relations Québec (Province); Labor laws and legislation; Labor laws and legislation Québec (Province); Labor unions; Labor unions Québec (Province); Livres électronique; Législation; Négociation collective; Négociations collectives Québec (Province); Personnel Direction Québec (Province); Personnel management; Personnel management Québec (Province); Québec; Québec (Province); Relations de travail; Relations industrielles Québec (Province); Secteur public; Secteurs public et para-public Relations de travail Québec (Province); Syndicat; Syndicats Québec (Province); Travail Droit Québec (Province)

Men for the Mountains - Marty, Sid, (Penguin Random House Canada, 2000)
As a park warden in the national parks of Canada's Rocky Mountains, Sid Marty came to know that beautiful and treacherous landscape as few men or women do. He was a mountain climber, rescue team member, firefighter, wildlife custodian, and adviser to tourists, adventurers, and people passing through. At all times, he was an acute observer of human and animal behaviour. In these pages he records with wry wit and bitter insight true stories of heroism and folly drawn from life in the high country. Marty writes vividly about a land and a way of life that are increasingly endangered. The visceral energy of his prose compels attention. This is a compulsive, alarming, and often hilarious read. --Publisher's description
Keywords: Adventure; Fire Fighter; Humour; Landscape; Mountains; Rescue Team Member; Working with the land

Boys in the Pits: Child Labour in Coal Mines - McIntosh, R. G. (Robert G.) (McGill-Queen's University Press, 2000)
A controversial and chilling examination of child labour in Canadian coal mines, Boys in the Pit shows that beginning early in the nineteenth century, thousands of boys, some as young as eight, laboured underground - driving pit ponies, manipulating ventilation doors, and helping miners cut and load the coal that fuelled the industrial revolution. Boys died in the mines in explosions and accidents but they also organized strikes for better working conditions. Robert McIntosh recasts these wage-earning children as more than victims, illustrating that they responded intelligently and resourcefully to their circumstances. Boys in the Pits is particularly timely as, despite the United Nations Convention on the Rights of the Child, accepted by the General assembly in 1989, child labour still occurs throughout the world and continues to generate controversy. McIntosh provides an important new perspective from which to consider these debates, reorienting our approach to child labour, explaining rather than condemning the practice. Within the broader social context of the period, where the place of children was being redefined as - and limited to - the home, school, and playground, he examines the role of changing technologies, alternative sources of unskilled labour, new divisions of labour, changes in the family economy, and legislation to explore the changing extent of child labour in the mines. --Publisher's description
Keywords: Child labor; Coal miners

Who has Seen the Wind - Mitchell, W. O. (William Ormond) (McClelland & Stewart, 2000)
When W.O. Mitchell died in 1998 he was described as “Canada's best-loved writer.” Every commentator agreed that his best – and his best-loved – book was Who Has Seen the Wind. Since it was first published in 1947, this book has sold almost a million copies in Canada. As we enter the world of four-year-old Brian O’Connal, his father the druggist, his Uncle Sean, his mother, and his formidable Scotch grandmother (“she belshes…a lot”), it soon becomes clear that this is no ordinary book. As we watch Brian grow up, the prairie and its surprising inhabitants like the Ben and Saint Sammy – and the rich variety of small-town characters – become unforgettable. This book will be a delightful surprise for all those who are aware of it, but have never quite got around to reading it, till now. --Publisher's description
Keywords: Drugs; Prairies; Social Class and Equality

The IWA in Canada: The Life and Times of an Industrial Union - Neufeld, Andrew; Parnaby, Andrew (IWA Canada/New Star Books, 2000)
The IWA, while closely linked to BC, has played a crucial role in nearly every province in Canada, from the Queen Charlotte Islands to Grand Falls, Newfoundland. The IWA in Canada is a definitive history of the union that follows its progress and setbacks throughout the past century. Its predecessors, the Industrial Workers of the World, the One Big Union, and the Lumber Workers' Industrial Union are examined, as are the historical tensions between craft and industrial unionism, the drive to organize the "timber beasts", and the pioneering role of communist activists. Today, the legendary militancy of IWA members is being brought to bear on the legalistic negotiations, environmental movements, and evolutions in governmental forest policy that continue to pose challenges. Generously illustrated with historical and present?day photographs, and enriched by numerous interviews with founding unionists, The IWA In Canada also features capsule histories of each local. In-depth analysis of specific issues and events such as the mysterious death of Viljo Rosval and Jon Voutilainen, the fight for relief in the Great Depression and the Loggers' Navy can be found in sidebars that enhance the text throughout. --Publisher's description.
Keywords: Canada; History. Lumbermen; IWA Canada; International Woodworkers of America-Canada; Labor Unions; Labor unions. Woodworkers; Woodworkers

Labouring the Canadian Millennium: Writings on Work and Workers, History, and Historiography - Palmer, Bryan D. (Past CCLH Publications, 2000)
As Canadian workers, the labour movement, and scholars confront a new millennium, new opportunities and new challenges loom large. This volume, which mirrors Labour/Le Travail Volume 46, commissions a number of articles addressing themes that will be of consequence as we enter the 21st century. The articles that appear in this collection are authored by some of the more prominent social scientists working in the field of labour-related studies, among them Desmond Morton, Ian McKay, Joan Sangster, Cynthia Comacchio, David Frank, and Jacques Rouillard. Their writing appears in the book, grouped in a series of thematic sections: institutions and ideas; gender, sexuality and family; Quebec and the national question; culture; and workers and the state. Topics such as Canadian socialism, pivotal events such as the 1949 Asbestos strike, and important cultural undertakings, such as working-class representations on film and video, are addressed. Historiographical controversies and debates associated with the relations of women’s and working-class histories or different generational styles associated with the presentation of labour’s past are surveyed. This is an issue all interested in Canadian society and its development will not want to miss. --Publisher's description
Keywords: Canada; History; History. Labor movement; History. Working class; Labor; Labor movement; Working class

A Memoir of the Spanish Civil War: An Armenian-Canadian in the Lincoln Battalion - Stephens, D. P. (Douglas Patrick) (Past CCLH Publications, 2000)
A Memoir of the Spanish Civil War is one man's bittersweet account of fighting with the International Brigades against the forces of General Francisco Franco in Spain from 1936 to 1939. Douglas Patrick (Pat) Stephens was born in Armenia in 1910 and emigrated with his family to Canada in 1926. Like countless others, his dream of finding a new and more prosperous life was severely shaken by the onset of the Great Depression, and he turned to the Communist Party of Canada in an attempt to combat the political and economic deterioration which had gripped much of the world. Franco's attempt to overthrow by military force the republican government of Spain seemed to Pat Stephens the ideal opportunity to put his political convictions into action. Through his connections in the Communist Party, he became one of some 1400 Canadians, and 40,000 International Volunteers in all, who went to Spain. Many of the volunteers, including the Canadians, went to Spain against the laws and the wishes of their governments. Many of them never came back. Stephens' memoir, dictated to his wife Phyllis Stephens shortly before his death in 1987, puts a very human face on this strange and complex war. It is a portrait of political and moral conviction tinged by creeping disillusionment. It is also a compelling depiction of the strength, frailty, doubt, and courage which can result from the sometimes incongruous intersection of the personal and the political. A Memoir of the Spanish Civil War is a valuable contribution to our understanding of the conflict which immediately preceded World War II, and of Canada's role in that conflict. -- Publisher's description
Keywords: Civil War, 1936-1939; Ejército Popular de la República. Abraham Lincoln Battalion; History; Personal narratives, Canadian; Soldiers; Spain

Temporary Work: The Gendered Rise of a Precarious Employment Relationship - Vosko, Leah F. (Studies in comparative political economy and public policy, 2000)
The first in-depth analysis of temporary work in Canada, this book by Leah F. Vosko examines a number of trends, including the commodification of labour power; the decline of the full-time, full-year job as a norm; and the gendered character of prevailing employment relationships. Spanning the period from the late nineteenth to the late twentieth century, Temporary Work traces the evolution of the temporary employment relationship in Canada and places it in an international context. It explores how, and to what extent, temporary work is becoming the norm for a diverse group of workers in the labour market, taking gender as the central lens of analysis." "Recent scholarship emphasizes that the nature of work is changing, citing the spread of non-standard forms of employment and the rise in women's participation in the labour force. Vosko confirms that important changes are indeed taking place in the labour market, but argues that these changes are best understood in historical, economic, and political context. This book will be invaluable to academics in a variety of disciplines as well as to policy analysts and practitioners in government, industry, and organized labour. --Publisher's descsription
Keywords: 1900-1999; Canada; Canadá; Convenio de la OIT; Division sexuelle du travail Canada Histoire 20e siècle; Estados Unidos; Etats-Unis; Femmes Travail Canada Histoire 20e siècle; History; ILO Convention; ILO Recommendation; Recomendación de la OIT; Sexual division of labor; Sexual division of labor Canada History 20th century; Temporary employment; Temporary employment Canada History 20th century; Travail temporaire Canada Histoire 20e siècle; USA; Women Employment; Women Employment Canada History 20th century; agence de travail temporaire; agence pour l'emploi privée; agencia de empleo privada; collective bargaining; comentario; comment; commentaire; condiciones de empleo; conditions d'emploi; conditions of employment; contrat de travail; contratación; contrato de trabajo; convention de l'OIT; cuadros estadísticos; developed countries; discriminación por razones de sexo; discrimination fondée sur le sexe; division du travail basée sur le sexe; división del trabajo por sexo; domestic worker; empleo temporal; emploi temporaire; employment security; employé de maison; empresa de trabajo temporal; femmes mariées; flexibilidad del trabajo; flexibilité du travail; formación; formation; histoire; historia; history; immigrant; inmigrante; labour contract; labour flexibility; labour force participation; labour legislation; legislación del trabajo; législation du travail; married women; migrant workers; mujeres casadas; negociación colectiva; négociation collective; papel de la OIT; pays développés; países desarrollados; private employment agency; protección social; protection sociale; recommandation de l'OIT; recruitment; recrutement; role of ILO; rôle de l'OIT; salaire; salario; seguridad en el empleo; sex discrimination; sexual division of labour; sindicalización; social protection; statistical table; syndicalisation; sécurité de l'emploi; tableau statistique; tasa de actividad de mano de obra; taux d'activité; temporary employment; temporary work agency; tendance; tendencia; trabajador doméstico; trabajador migrante; trabajadoras; trade unionization; training

Working: Images of Canadian Labour, 1900-2000 = Travailler : images de la vie ouvrière au Canada, 1900-2000 - Barna, Laszlo (Key Porter Books, 1999)
The companion book to The Labour Millenium Project, a four-part documentary film series and CD-ROM --Page 4 of cover. Text in English and French.
Keywords: 1900-1999; Canada; Grèves et lock-out Canada Histoire 20e siècle Ouvrages illustrés; History; Labor movement; Labor movement Canada History 20th century Pictorial works; Labor unions; Labor unions Canada History Pictorial works; Mouvement ouvrier Canada Histoire 20e siècle Ouvrages illustrés; Pictorial works; Strikes and lockouts; Strikes and lockouts Canada History 20th century Pictorial works; Syndicats Canada Histoire Ouvrages illustrés; Travailleurs Canada Histoire 20e siècle Ouvrages illustrés; Working class; Working class Canada History 20th century Pictorial works

Women Working the NAFTA Food Chain: Women, Food and Globalization - Barndt, Deborah; Harjo, Joy; Friedmann, Harriet; Reiter, Ester; Martinez-Salazar, Egla; Baron, Antonieta; Appendini, Kirsten; Ansley, Fran; Eyerman, Ann; Kainer, Jan; Field, Debbie; Villagomez, Maria Dolores; et al. (Women's issues publishing program, 1999)
This collection of compelling and original research makes connections in Canada, the US and Mexico among women who work in fast-food restaurants, supermarkets and agricultural production. The fourteen chapters take a critical look at how the North American Free Trade Agreement (NAFTA) has affected these women's working and living conditions, sharpening our understanding of how the workplace has been restructured in order to fulfill consumer demands for tomatoes, exotic flowers and fruits, as well as fast-food burgers and fries. Food activists in Latin America, the US and Canada propose alternatives to counteract the oppressive conditions of free trade and globalization. --Publisher's description. Contents: "Perhaps the world ends here" / Joy Harjo -- Introduction: In the belly of the beast: A moveable feast / Deborah Barndt -- Remaking "traditions": How we eat, what we eat and the changing political economy of food / Harriet Friedmann -- Whose "choice"?: "Flexible" women workers in the tomato food chain / Deborah Barndt -- Serving the McCustomer: Fast food is not about food / Ester Reiter -- The "poisoning" of Indigenous migrant women workers and children: From deadly colonialism to toxic globalization / Egla Martinez-Salazar -- Mexican women on the move: Migrant workers in Mexico and Canada / Antonieta Barrón -- "From where have all the flowers come?": Women workers in Mexico's non-traditional markets / Kirsten Appendini -- Putting the pieces together: Tennessee women find the global economy in their own backyards / Fran Ansley -- Serving up service: Fast-food and office women workers doing it with a smile / Ann Eyerman -- Not quite what they bargained for: Female labour in Canadian supermarkets / Jan Kainer -- Putting food first: Women's role in creating a grassroots system outside the marketplace / Debbie Field -- Grassroots responses to globalization: Mexican rural and urban women's collective alternatives / Maria Dolores Villagomez -- Women as organizers: Building confidence and community through food / Deborah Moffett & Mary Lou Morgan -- A day in the life of Maria: Women, food, ecology and the will to live / Ofelia Perez Peña -- A different tomato: Creating vernacular foodscapes / Lauren Baker.

Making Our Mark: Labour Arts and Heritage in Ontario - Beveridge, Karl; Johnston, Jude (Between the Lines, 1999)
Finally, a book that documents the rich history of labour arts in Ontario. Making Our Mark presents over 100 projects, showcasing the vibrant banners, photos, plays and lyrics that form the heart and soul of the labour movement. Diverse examples spring from the Artist in the Workplace Program, the Mayworks Festivals, independent labour arts projects, and exhibitions organized the Ontario Workers Arts and Heritage Centre. Making Our Mark celebrates the songs of Arlene Mantle and Charlie Angus, photos by First Nations ironworkers, and dance performances by Tom Brouillette and the Boilermakers, to name a few.... Publisher's description
Keywords: Ontario

Feminist Success Stories = Célébrons nos réussits féministes - Blackford, Karen A.; Garceau, Marie-Luce; Kirby, Sandra (University of Ottawa Press = Presses de l'Universite d'Ottawa, 1999)
Abuses by international corporations, withdrawal of social services and implementation of regressive legislation continue to impoverish women and reduce the quality of their everyday lives: women have reason to be demoralized. Recognizing this challenging and difficult situation, this volume reviews women's successes at feminizing Canadian institutions. It is intended to hearten the women's movement, and show the potential for feminist change and suggest ways to realize this potential
Keywords: Canada; Feminism; Feminism Canada; Feminism and feminist theory; Femmes Éducation Canada; Féminisme Canada; Social Science / Feminism & Feminist Theory; Social issues and processes; Society and culture: general; Society and social sciences Society and social sciences; Volunteers; Volunteers Canada; Women Education; Women Education Canada; Women Employment; Women Employment Canada; Women Health and hygiene; Women Health and hygiene Canada; canadian institutions; feminist; women

Service in the Field: The World of Front-Line Public Servants - Carroll, Barbara Wake; Siegel, David; Institute of Public Administration of Canada (McGill-Queen's University Press, 1999)
A tribute to the most important people in government. The most important people in government are not the prime minister, premiers, and senior bureaucrats but the people who work in government field offices across the country, providing service to Canadians. The first book to focus exclusively on the role of field-level public servants in Canada, Service in the Field examines the work they do and the relationship between field and head offices. As governments attempt to focus more on service delivery, it has become apparent that little is known about the people who actually provide the services. Barbara Wake Carroll and David Siegel discuss structural issues and analyse the various administrative reforms developed in the last few years. They highlight field officers' perceptions of the problems in the system and suggest ways to improve field office-head office relations and the operation of field offices generally. The authors' analysis is based on more than two hundred interviews with federal and provincial civil servants in all ten provinces, in the smallest hamlets and largest cities across Canada. Using extensive quotations from these interviews, the authors allow public servants to tell their own stories and, in so doing, provide examples of the application of systematic qualitative research to Canadian political science. --Publisher's description, Contents: Who Are These People and What Do They Do? -- Research Described -- "How We Do Things around Here" -- Service to the Public -- Workplace Environment -- Two Solitudes or One Big Happy Family? Dealing with Head Office -- Administrative Reform: How It Plays in the Field -- Bureaucrats Are People Too -- Where Do We Go from Here? Implications for Implementation and Management Theory.

Contracting Masculinity: Gender, Class, and Race in a White-Collar Union, 1944-1994 - Creese, Gillian (Canadian social history series, 1999)
The history of labour in Canada is most often understood to mean – and presented as – the history of blue-collar workers, especially men. And it is a story of union solidarity to gain wages, rights, and the like from employers. In Contracting Masculinity, Gillian Creese examines in depth the white-collar office workers union at BC Hydro, and shows how collective bargaining involves the negotiation of gender, class, and race. Over the first 50 years of the office union's existence male and female members were approximately equal in number. Yet equality has ended there. Women are concentrated at the lower rungs of the job hierarchy, while men start higher up the ladder and enjoy more job mobility; men's office work has been redefined as a wide range of 'technical' jobs, while women's work has been concentrated in a narrow range of 'clerical' positions. As well, for decades Canadian Aboriginals and people of colour were not employed by BC Hydro, which has resulted in a racialized-gendered workplace. What is the role of workers and their trade unions in constructing male and female work, a process that is often seen as the outcome solely of management decisions? How is this process of gendering also racialized, so that women and men of different race and ethnicity are differentiallv privileged at work? How do males in a white-collar union create and maintain their own image of masculinity in the face of a feminized occupation and a more militant male blue-collar union housed within the same corporation? What impact does the gender composition of union leadership have on collective bargaining? How do traditions of union solidarity affect attempts to bargain for greater equity in the office? These are the central questions that Contracting Masculinity seeks to answer in this in-depth look at a Canadian union. --Publisher's description

Life on the Line: One Woman's Tale of Work, Sweat, and Survival - De Santis, Solange (Penguin Random House Canada, 1999)
Just when Solange De Santis had achieved success and security in the white-collar world of journalism, she decided to leave it all to work on the line during the final year and a half of a General Motors van plant in Scarborough, Ontario. --Publisher's description
Keywords: Assembly Line; Automotive; Blue-collar work; Gender; Journalist; Ontario Scarborough; Pink-collar work

Michel Chartrand : les voies d'un homme de parole - Foisy, Fernand (Lanctöt Éditeur et Fernand Foisy, 1999)
On peut dire de Michel Chartrand qu'il est le dernier des vrais. À lui seul, il représente tout un programme politique: liberté, égalité, fraternité et justice, ces vieilles idées révolutionnaires dont on s'est plu, à maintes reprises, à annoncer la fin. À lui seul, il représente le courage, celui d'affirmer et de défendre en tout temps ses idées, qui, en fait, ne sont pas si vieilles. Ce combat, c'est l'histoire de sa vie, celle d'un homme en tout temps minoritaire, d'un simple citoyen de l'opposition qui n'a jamais connu le pouvoir mais qui aura sans doute réussi à exercer, en plusieurs occasions, un véritable contre-pouvoir. On a dit de Michel Chartrand qu'il était excessif, colérique, enragé, mal engueulé, mais c'est aussi un incorruptible, un insoumis, un idéaliste, un perpétuel insurgé, un prophète. Dans cet ouvrage, qui n'a pas la prétention d'une vraie biographie, mais qui nous permet également de survoler les moments marquants de l'histoire du Québec et du mouvement ouvrier, Fernand Foisy, qui a interviewé une centaine de personnes, amis ou détracteurs, nous présente le portrait d'un homme engagé, passionné par la politique, amoureux des mots et de la vie, celui qui fut pendant plus de cinquante ans l'époux assidu d'une autre personne exemplaire, Simonne Monet. À lire et à relire ce portrait d'un homme à part et pourtant bien de son temps, il m'arrive de croire à cette utopie toujours dérangeante d'un partage juste et équitable des grandes richesses, malgré le nouvel ordre mondial qu'on tend à nous imposer violemment. --Résumé de l'éditeur
Keywords: Biographies; Chartrand, Michel, 1916-; Chartrand, Michel, 1916-2010; Dirigeants syndicaux Québec (Province) Biographies; Labor leaders; Labor leaders Québec (Province) Biography; Politics and government; Québec; Québec (Province) Conditions sociales 1960-1991; Québec (Province) Politics and government 1960-; Québec (Province) Politique et gouvernement 1960-; Québec (Province) Social conditions 1960-1991; Since 1960; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province); Travailleurs Québec (Province) Conditions sociales; Working class Québec (Province) Social conditions; Working class Social conditions

Les récoltes des forêts publiques au Québec et en Ontario, 1840-1900 - Gaudreau, Guy (McGill-Queen's University Press, 1999)
Focusing on the transition from the production of squared timber to that of milled lumber and, finally, wood pulp, Gaudreau traces the constant depletion of the resource and the companies' resulting, inexorable push westward from Quebec into Ontario - an economic migration that led to the establishment of significant francophone communities across northern Ontario. He shows how recent generations of Quebec historians have failed to provide adequate historical explanations because of an overly exclusive focus on Quebec. Gaudreau's work provides an important historiographic corrective, showing that the history of Quebec is part of a complex fabric that, like the forests themselves, does not recognize provincial boundaries. Detailed annual data on the volume of principal forest products produced from Crown lands in Quebec and Ontario during the second half of the nineteenth century compiled systematically for the first time form the backbone of this study. Based on these data Gaudreau describes and clarifies the timing, scale, and significance of transitions in forest outputs as spruce joined pine as the principal type of wood logged and as milled lumber and subsequently pulp wood joined, and eventually replaced, square timber as the key product. The book addresses the implications of resource depletion and the economic and historical changes in the forestry industry, including the transition from a commercial and artisanal process to an industrial process and the implications this had for colonization and migration. --Publisher's description
Keywords: Forest reserves -- Ontario -- History -- 19th century

Solidarité et détermination: histoire de la Fraternité des policiers et policières de la Communauté urbaine de Montréal - Goulet, Henri; Rouillard, Jacques (Boréal, 1999)
En 1999, la Fraternité des policiers et policières de Montréal célébrait son cinquantième anniversaire. Quelles sont les étapes qui ont marqué la vie de ce syndicat? --Résumé de l'éditeur

Radical Roots: The Shaping of British Columbia - Griffin, Harold (Commonwealth Fund, 1999)
[T]his history is a major contribution in recording the tumultuous times and many sharp battles of the working class in British Columbia. --From introduction by Maurice Rush
Keywords: British Columbia; British Columbia History; Colombie-Britannique Histoire; History; Populism; Populism British Columbia History; Populisme Colombie-Britannique Histoire; Radicalism; Radicalism British Columbia History; Radicalisme Colombie-Britannique Histoire

The Woman Worker, 1926-1929 - Canadian Committee on Labour History; Hobbs, Margaret (Margaret Helen); Sangster, Joan (Past CCLH Publications, 1999)
This volume presents the inaugural issue and articles from The Woman Worker, the official newspaper of the Canadian Federation of Women's Labor Leagues, during its 1926 to 1929 run. Edited by prominent Communist Party of Canada leader Florence Custance, The Woman Worker's objective was to "champion the Protection of Womanhood, and the cause of the Workers generally." In this collection, Hobbs and Sangster have provided an introductory chapter examining the evolution The Woman Worker, its editor Florence Custance, the Communist-led Women's Labor Leagues, and, more generally, the socio-economic and political context of the mid to late 1920s. Each chapter includes an introduction and suggestions for further reading. Chapters include women and wage work, protective legislation, feminism and social reform, peace and war, women and the sex trade, marriage, the family and domestic labour, and the local Women's Labor Leagues at work. --Publisher's description
Keywords: 20th century; Canada; Employment; Employment History Sources; History; History Sources; Social conditions; Social conditions Sources; WOMEN labor union members; Woman worker (Toronto, Ont.); Women; Women employees

The Fur Trade in Canada: An Introduction to Canadian Economic History - Innis, Harold Adams; Ray, Arthur J. (University of Toronto Press, 1999)
At the time of its publication in 1930, The Fur Trade in Canada challenged and inspired scholars, historians, and economists. Now, almost seventy years later, Harold Innis's fundamental reinterpretation of Canadian history continues to exert a magnetic influence. Innis has long been regarded as one of Canada's foremost historians, and in The Fur Trade in Canada he presents several histories in one: social history through the clash between colonial and aboriginal cultures; economic history in the development of the West as a result of Eastern colonial and European needs; and transportation history in the case of the displacement of the canoe by the York boat. Political history appears in Innis's examination of the nature of French-British rivalry and the American Revolution; and business history is represented in his detailed account of the Hudson's Bay and Northwest Companies and the industry that played so vital a role in the expansion of Canada. In his introduction to this new edition, Arthur J. Ray argues that The Fur Trade in Canada is the most definitive economic history and geography of the country ever produced. Innis's revolutionary conclusion - that Canada was created because of its geography, not in spite of it - is a captivating idea but also an enigmatic proposition in light of the powerful decentralizing forces that threaten the nation today. Ray presents the history of the book and concludes that "Innis's great book remains essential reading for the study of Canada. --Publisher's description. Includes bibliographical references (p. [421]-441) and index.
Keywords: Fur trade -- Canada -- History

Race and Ethnic Relations in Canada - Li, Peter S. (Oxford University Press, 1999)
Race and Ethnic Relations in Canada was first published in 1990 by Oxford University Press as a collection of twelve original essays that provided a comprehensive overview of government policies and academic theories that affect the way race and ethnic relations are structured and interpreted in Canada. This second edition takes into account social changes and academic debates of the 1990s and updates materials and arguments in the original edition. The contributors, all leading Canadian sociologists and social scientists, discuss a wide range of topics, including theories of race and ethnicity, demographic trends, the 'vertical mosaic', immigration, multiculturalism, employment equity, policy on Native peoples, and language policy. The book is essential reading for understanding Canada's race and ethnic relations. --Publisher's description. Contents: Part 1: Introduction. Race and Ethnicity / Peter S. Li -- Demographic Overview of Ethnic Origin Groups in Canada / Madeline A. Kalbach, Warren E. Kalbach. Part 2: Race, Ethnicity, and the State. Immigration, Diversity, and Minority Communities / Morton Weinfeld and Lori A. Wilkinson -- State Policies and Practices as Racialized Discourse: Multiculturalism, the Charter, and Employment Equality / Frances Henry and Carol Tator -- Altered State: Federal Policy and Aboriginal Peoples / James Frideres -- The Multiculturalism Debate / Peter S. Li -- Language Policy in Canada / Wilfrid Denis. Part 3: Perspectives on Race and Ethnicity. Revisiting the Vertical Mosaic: Occupational Stratification Among Canadian Ethnic Groups / Hugh Lautard and Neil Guppy -- Studies of Ethnic Identity, Ethnic Relations, and Citizenship / K. Victor Ujimoto -- Intergroup Competition in the Symbolic Construction of Canadian Society / Raymond Breton -- The Political Economy of Race and Ethnicity / Vic Satzewich -- Feminist Intersectional Theorizing / Daiva K. Stasiulis.
Keywords: Canada; ETHNIC relations; Race relations

The Westray Chronicles: A Case Study in Corporate Crime - McCormick, Chris (Fernwood, 1999)
Was the Westray mining disaster a tragic accident or a corporate crime gone unpunished? In this book authors from backgrounds as diverse as engineering to public relations are brought together to create a holistic picture of what happened at Westray. From an analysis of the geology of the underlying coal seam to an assessment of the difficulties of pinning legal responsibility on the company, the government or any of the managers, this book constitutes one of the few case studies of corporate crime in Canada. The contributors offer the reader challenging new ways to think about workplace disasters and occupational injuries. Each contributor brings their special expertise to bear in a way that makes complicated issues transparent to the most general reader. At the same time, footnotes and references guide the reader who desires more extensive information. -- Publisher's description
Keywords: 1900-1999; Charbon Mines et extraction Accidents Nouvelle-Écosse Stellarton Histoire 20e siècle; Coal mine accidents; Coal mine accidents Nova Scotia Stellarton History 20th century; History; Nova Scotia Plymouth (Pictou); Nova Scotia Stellarton; Tragédie minière de Westray, Plymouth, Pictou, N.-É., 1992; Westray Mine Disaster, Plymouth, Pictou, N.S., 1992

Industrial Cathedrals of the North = Les cathédrales industrielles du nord - Palu, Louie; Angus, Charlie (Between the Lines, 1999)
Headframes dominate the landscape of mining communities in Northeastern Ontario and Northwestern Quebec. Distinctive structures built to house the apparatus at the head of the mine shaft, headframes tower above their surroundings, reminding every resident that without the mine, there would be no reason for their settlement to exist. For the past several years, photographer Louie Palu and writer Charlie Angus have been documenting historic mining sites in the north. Many of these have since been erased from the landscape. Co-produced with Prise de parole. --Publisher's description

No Justice, No Peace: The 1996 OPSEU Strike Against the Harris Government of Ontario - Rapaport, David (McGill-Queen's University Press, 1999)
The Ontario Public Service Employee Union (OPSEU) was an early target of the Mike Harris Common Sense Revolutionaries, neo-conservatives on a mission to shrink the social safety net, radically reduce social programs, and subvert Ontario's collective bargaining regimes. In No Justice, No Peace David Rapaport uses detail, insights, and anecdotes from over 150 interviews - with picket line captains, local executives, union leadership, journalists, mediators, and union and management negotiators among others - to provide an insider's view of the strike and its political and economic contexts, often told in the strikers' own voices. Vice-president from 1991 to 1997 of OPSEU's huge Region 5, covering Toronto, Rapaport describes how the election of the Harris government and the early "Common Sense Revolution" cutbacks led to a large opposition movement, the labour/social justice coalition, the Days of Action, and the province-wide OPSEU strike. No Justice, No Peace traces the politics involved, from ideology and belief in free trade to the downsizing of public and private enterprises, from the restructuring and privatization of the public sector to collective bargaining between OPSEU and the Ontario Government, and, finally, to the strike vote and the picket line. --Publisher's description
Keywords: Civil Service Strike, Ontario, 1996.; Strikes and lockouts

On a Cold Road: Tales of Adventure in Canadian Rock - Bidini, Dave. (Penguin Random House Canada, 1998)
Dave Bidini, rhythm guitarist with the Rheostatics, knows all too well what the life of a rock band in Canada involves: storied arenas one tour and bars wallpapered with photos of forgotten bands the next. Zit-speckled fans begging for a guitar pick and angry drunks chucking twenty-sixers and pint glasses. Opulent tour buses riding through apocalyptic snowstorms and cramped vans that reek of dope and beer. Brilliant performances and heart-sinking break-ups. Bidini has played all across the country many times, in venues as far flung and unalike as Maple Leaf Gardens in Toronto and the Royal Albert Hotel in Winnipeg. In 1996, when the Rheostatics opened for the Tragically Hip on their Trouble at the Henhouse tour, Bindini kept a diary. In On a Cold Road he weaves his colourful tales about that tour with revealing and hilarious anecdotes from the pioneers of Canadian rock - including BTO, Goddo, the Stampeders, Max Webster, Crowbar, the Guess Who, Triumph, Trooper, Bruce Cockburn, Gale Garnett, and Tommy Chong - whom Bindini later interviewed in an effort to compare their experiences with his. The result is an original, vivid, and unforgettable picture of what is has meant, for the last forty years, to be a rock musician in Canada. --Publisher's description
Keywords: Blue-collar work; Drinking; Memoir; Musician; Rock Band Music; Toronto (Ont.); White-collar work; Winnipeg

Le paysage industriel à Sudbury = Sudbury, The Industrial Landscape - Donegan, Rosemary (Art Gallery of Sudbury = Galerie d'art de Sudbury, 1998)
Catalogue of an exhibition held at the Art Gallery of Sudbury, July 30-Sept. 20, 1998.
Keywords: 1900-1999; Exhibition catalogs; Industrie dans l'art Expositions; Industries in art; Industries in art Exhibitions; Landscape painting, Canadian; Landscape painting, Canadian 20th century Exhibitions; Ontario Sudbury (Greater Sudbury); Painting, Canadian; Painting, Canadian 20th century Exhibitions; Peinture canadienne 20e siècle Expositions; Peinture de paysages canadienne 20e siècle Expositions; Sudbury (Greater Sudbury, Ont.) In art Exhibitions

La mobilité des ouvriers-mineurs du Nord ontarien et québécois, 1900-1939 - Gaudreau, Guy; Daoust, Alain; Reilly, Karey (Série monographique en sciences humaines, 1998)
Ce livre amorce une réflexion sur la mobilité des travailleurs miniers du Nord en exploitant une variété de sources, parmi lesquelles figurent les archives des sociétés mineurs qui composent le matérial le plus riche de l'ouvrage. Non seulement la mobilité géographique des travailleurs y est examiné, mais aussi leur mobilité interne. En fait, les mines ont aussi une lieu d'apprentissage pour une minorité des travailleurs et non uniquement une lieu de confrontation, comme les historiens ont l'habitude de la faire. Un des thèmes marquants de l'étude demeure le fait que les politiques d'embauche des entreprises ont fortement influencé la composition ethnique de la force de travail, et conséquemment, celle de la population de nord ontarien et québécois. --Quatrième de couverture
Keywords: Labor mobility -- Ontario, Northern -- History

My Name's Not George: The Story of the Brotherhood of Sleeping Car Porters: Personal Reminiscences of Stanley G. Grizzle - Grizzle, Stanley G.; Cooper, John (Umbrella Press, 1998)
Keywords: Autobiographies; Biographies; Blacks Employment Canada Hstory Sources; Brotherhood of Sleeping Car Porters; Brotherhood of Sleeping Car Porters History Sources; Canada; Grizzle, Stanley G., 1918-2016; History; Préposés aux pullmans Canada Histoire Sources; Préposés aux pullmans Syndicats Canada Histoire Sources; Pullman porters; Pullman porters Canada History Sources; Pullman porters Labor unions; Pullman porters Labor unions Canada History Sources; Sources; autobiographies (literary genre)

Labour of Love: The Fight to Create a More Humane Canada - Hargrove, Buzz; Skene, Wayne (Macfarlane Walter & Ross, 1998)
The outspoken leader of the Canadian Auto Workers Union now offers his passionate perspective in Labour of Love: The Fight to Create a More Humane Canada. Buzz Hargrove offers his reasons for his strong belief in unions, a scathing critique of Bob Rae's NDP and the Tories' "Common Sense Revolution," and an insightful analysis of Canada. Hargrove believes that "Days of Action" protests are vital in a society whose governments are threatening to unravel the already suffering Canadian social programs. Political and labour junkies will be riveted by Hargrove's unflinching look at the conservative policies that could destroy a country he loves. --Publisher's description
Keywords: 1993-; Canada; Hargrove, Buzz; Industrial policy; Labor Unions; Politics and government; Politique et gouvernement; Politique industrielle; Syndicats

The Vertical Mosaic Revisited - Helmes-Hayes, Richard C.; Curtis, James E. (Heritage, 1998)
When The Vertical Mosaic first appeared in 1965, it became an instant classic. Its key message was that Canada was not the classless democracy it fancied itself to be. In fact, Canada was a highly inegalitarian society comprising a 'vertical mosaic' of distinct classes and ethnic groups. This collection of papers by five of Canada's top sociologists subjects John Porter's landmark study to renewed scrutiny and traces the dramatic changes since Porter's time - both in Canadian society and in the agenda of Canadian sociology. Based on papers written for a conference held in commemoration of the thirtieth anniversary of The Vertical Mosaic's publication, the five essays revisit the central themes of the original work, including gender and race inequality; citizenship and social justice; and class, power, and ethnicity from the viewpoint of political economy. An introduction by the editors provides a historical biography of Porter and discusses his influence on Canadian sociology. --Publisher's description. Contents: Power, ethnicity, and class: Reflections thirty years after The vertical mosaic / Wallace Clement -- Ethnicity and race in social organization: Recent developments in Canadian society / Raymond Breton -- Missing women: A feminist perspective on The vertical mosaic / Pat Armstrong -- Three decades of elite research in Canada: John Porter's unfulfilled legacy / Michael Ornstein -- Social justice, social citizenship, and the welfare state, 1965-1995: Canada comparative context / Julia S. O'Connor.
Keywords: Canada; Canada Conditions sociales 1945-; Canada Social conditions 1945-; Classes sociales Canada; Porter, John, 1921-1979; Pouvoir (Sciences sociales) Canada; Power (Social sciences); Power (Social sciences) Canada; Since 1945; Social classes; Social classes Canada; Social conditions

The Workers' Revolt in Canada, 1917-1925 - Heron, Craig (University of Toronto Press, 1998)
Canadians often consider the Winnipeg General Strike of 1919 to be the defining event in working-class history after the First World War. This book, the collaboration of nine labour historians, shows that the unrest was both more diverse and more widespread across the country than is generally believed. The authors clarify what happened in working-class Canada at the end of the war and situate 'the workers' revolt' within the larger structure of Canadian social, economic, and political history. They argue that, despite a national pattern, the upsurge of protest took a different course and faced a different set of obstacles in each region of the country. Their essays shed light on the extent of the revolt nationally while retaining a sensitivity to regional distinctiveness. --Publisher's description
Keywords: 20th century. Labor movement; 20th century. Mouvement ouvrier; 20th century. Working class; Canada; Conflits; General. Labor movement. Working class. Arbeidersbeweging. Protestacties. Opstanden. Stakingen. Arbeiterbewegung. Genre/Form: Electronic books. History; Histoire; History; Labor & Industrial Relations. HISTORY; Labor movement; Labor. POLITICAL SCIENCE

Career Paths of Nursing Professionals: A Study of Employment Mobility - Hiscott, Robert Dennis (Carleton University Press, 1998)
A comprehensive study of the nursing profession using data collected from over 1600 surveys. This is the first and only comprehensive labour market study of the largest group of nursing professionals in any one province in Canada. It explores the career paths of more than 1600 registered nurses and registered practical nurses, using survey data collected in 1992-1993, just as these front line caregivers faced the sea change wrought by governmental restructuring in Ontario hospitals. A "snapshot" of key labour force and market issues in the nursing field, the study provides important baseline data from which the impact of present and future public policy trends and changes can be monitored, reviewed, and researched. The dimensions studied here include recent demographic shifts, the various forms of employment mobility, levels of voluntarism, career interruption, and nurses' reasons for leaving the field. Each line of inquiry raises pressing questions about the professional lives of those who work most directly and dynamically with patients but whose careers are being altered, perhaps detrimentally, by reorganization in the Canadian health care system. --Publisher's description

A Nation of Immigrants: Women, Workers, and Communities in Canadian History, 1840s-1960s - Iacovetta, Franca; Draper, Paula; Ventresca, Robert (Canada 150 Collection, 1998)
This collection brings together a wide array of writings on Canadian immigrant history, including many highly regarded, influential essays. Though most of the chapters have been previously published, the editors have also commissioned original contributions on understudied topics in the field. The readings highlight the social history of immigrants, their pre-migration traditions as well as migration strategies and Canadian experiences, their work and family worlds, and their political, cultural, and community lives. They explore the public display of ethno-religious rituals, race riots, and union protests; the quasi-private worlds of all-male boarding-houses and of female domestics toiling in isolated workplaces; and the intrusive power that government and even well-intentioned social reformers have wielded over immigrants deemed dangerous or otherwise in need of supervision.Organized partly chronologically and largely by theme, the topical sections will offer students a glimpse into Canada's complex immigrant past. In order to facilitate classroom discussion, each section contains an introduction that contextualizes the readings and raises some questions for debate. A Nation of Immigrants will be useful both in specialized courses in Canadian immigration history and in courses on broader themes in Canadian history. --Publisher's description. Contents: The Irish in nineteenth-century Canada: class, culture, and conflict -- American Blacks in nineteenth-century Ontario: challenging the stereotypes -- Settling the Canadian West: the 'exotic' continentals -- 'Women's work': paid labour, community-building, and protest -- Men without women: 'bachelor' workers and gendered identities -- Demanding rights, organizing for change: militants and radicals -- Encountering the 'other': society and state responses, 1900s-1930s -- Regulating minorities in 'hot' and 'cold' war contexts, 1939-1960s.

Enlisting Women for the Cause: Women, Labour, and the Left in Canada, 1890-1920 - Kealey, Linda (Studies in Gender and History, 1998)
[This book] re-creates the experiences of Canadian women on the left in the late nineteenth and early twentieth centuries, a crucial period when women became more prominent in the work force, in labour unions, and in politics, where they fought for, and ultimately won, the vote. The book examines discourse on women's work and on attempts to regulate it; labour activism, including formal membership in unions and parties as well as women's auxiliaries and organizations such as the Women's Labor League; and women's militancy during the First World War and the troubled postwar period. The author argues that while women helped mount an opposition to the inequalities inherent in industrial capitalism, they also had to struggle to move beyond the supporting role they were forced to play in the very movements to which they belonged. Kealey explores what the left thought about women's participation in politics and in left-wing organizations across the country, and also looks at the nature of that participation itself. The scope of her book puts it in the forefront of its field. --Publisher's description. Contents: Only a Working Girl': Women's Work and Regulation, 1890-1914 -- Gender Divisions: Women in Labour Organizations, 1890-1914 -- 'A Socialist Movement Which Does Not Attract the Women Cannot Live': Women in the Early Socialist Movement -- 'Full of the Spirit of Revolt': Women in the Socialist Party of Canada and the Social Democratic Party --  'Wanted -- Women to Take the Place of Men': Organizing Working Women in the Era of War and Reconstruction -- 'This Crimson Storm of War': Women, War, and Socialism -- 'No Special Protections...No Sympathy': Postwar Militancy and Labour Politics.

A Female Economy: Women's Work in a Prairie Province, 1870-1970 - Kinnear, Mary (McGill-Queen's University Press, 1998)
A comprehensive overview of women's place in the work force. A Female Economy analyses a hundred years of women's work in Manitoba from the province's entry into Confederation in 1870 to the publication of the Report of the Royal Commission on the Status of Women in 1970. Mary Kinnear shows that, whether women were working in the household or on a farm for no direct monetary reward or working for wages in the industrial, service, and professional sectors, their work was undervalued. Kinnear details how ordinary women - including early pioneers, East European immigrants, Native women, and professional women - lived and what they thought of the world of work, often telling their stories in their own words. She highlights the cultural and economic expectations for women and juxtaposes the activities society deemed suitable for women with what they actually did. Kinnear argues that a host of factors, such as class and ethnicity, differentiated their choices but that these women shared many common experiences. While women's own views furnish the main theme, A Female Economy contributes to a developing debate in feminist economics. By focusing on women's experiences in the sexually segregated economy of a Canadian province at the geographic centre of Canada, Kinnear furnishes a paradigm for women's economic activity in most western industrializing societies at the time. --Publisher's description

Patrick Lenihan: From Irish Rebel to Founder of Canadian Public Sector Unionism - Lenihan, Patrick (Past CCLH Publications, 1998)
Patrick Lenihan displayed rare courage and unwavering commitment to social justice, from his childhood in revolutionary Ireland through his leading role in the Communist Party of Canada to the formation of the first national union of public employees. Patrick Lenihan: From Irish Rebel to Founder of Canadian Public Sector Unionism chronicles a lifetime of rebellion, protest, and organizing, aganist the backdrop of the major economic, social, and political struggles of this century. Lenihan was constantly watched, repeatedly arrested, and often imprisoned, but he emerged time and again as a leader in the cause of the downtrodden, the working poor, and the unemployed. The On-to-Ottawa Trek, the work camps of the 1930's, the radicalism of the western mine towns, the Cold War -- Pat Lenihan was involved in it all, front and center. Drawn from interviews conducted by Gilbert Levine and written in an unadorned, engaging style, Patrick Lenihan is far more than the story of Canada's most infuential and colorful figures. It makes a valuable contribution to our understanding of western radicalism, Canadian communism, state repression union organizing, and the daily struggles which have shaped 20th-century Canada. --Publisher's description
Keywords: 20th century; Canadian Union of Public Employees (CUPE); History; Labor movement; Lenihan, Patrick, 1903-1981

Working People - Morton, Desmond (McGill-Queen's University Press, 1998)
Keywords: Labor unions

Du combat au partenariat : interventions critiques sur le syndicalisme québécois - Piotte, Jean-Marc (Éditions Nota bene, 1998)
Acteur majeur de la Révolution tranquille durant les années 1960, partisan d'une transformation révolutionnaire de la société durant la décennie suivante, le mouvement syndical est-il toujours animé par une volonté de changement social ? En prônant et en pratiquant un syndicalisme de concertation et de partenariat avec l'État et le patronat, demeure-t-il fidèle aux idéaux qui l'habitent depuis sa naissance ? C'est à ces questions que tente de répondre cet ouvrage de Jean-Marc Piotte en reconstituant la trajectoire du mouvement au cours des vingt-cinq dernières années. Militant politique et syndical au cours de cette période, principal théoricien du syndicalisme de combat, l'auteur nous livre un bilan critique du syndicalisme québécois au moment où celui-ci est durement confronté aux nouveaux défis posés par la mondialisation et la domination absolue du marché sur l'ensemble de la vie sociale dans nos sociétés contemporaines. --Présentation (quatrième de couverture)
Keywords: Labor movement -- Quebec (Province) -- History -- 20th century

Not One of the Family: Foreign Domestic Workers in Canada - Bakan, Abigail B.; Stasiulis, Daiva K. (University of Toronto Press, 1997)
In [this book], experts on foreign domestic workers and workers-turned-activists document how the Canadian system has institutionalized unequal treatment of citizen and non-citizen workers. Since the 1940s, rights of citizenship for immigrant domestic workers in Canada have declined while the number of women recruited from Third World countries to work in Canadian homes has dramatically increased. The analysis...is both theoretical and practical, framing ideologies of privacy, maternalism, familialism, and rights, as well as examining government policy, labour organizing, and strategies to resist exploitation. --Publisher's description. Contents: Introduction / Abigail B. Bakan and Daiva Stasiulis -- Foreign domestic worker policy in Canada and the social boundaries of modern citizenship / Abigail B. Bakan and Daiva Stasiulis -- From mothers of the nation to migrant workers / Sedef Arat-Koc -- An affair between nations: international relations and the movement of household service workers / Patricia M. Daenzer -- Little victories and big defeats : the rise and fall of collective bargaining rights for domestic workers in Ontario / Judy Fudge -- The work at home is not recognized: organizing domestic workers in Montreal / Miriam Elvir -- We can still fight back: organizing domestic workers in Toronto / Pura M. Velasco.

A Miner's Chronicle: Inco Ltd. and the Unions, 1944-1997 - Brasch, Hans (United Steelworkers of America, Local 6500, 1997)
Chronicles the 26 collective agreements signed by unions with the International Nickel Company (Inco) in Sudbury from 1944 to 1997. Describes the strikes and production shutdowns of 1958, 1966, 1969, 1975, 1978 , 1982, and 1997. Also includes a list of mining fatalities from 1890 to 1997.
Keywords: History; Industrial accidents; International Nickel Company of Canada (INCO); International Union of Mine, Mill and Smelter Workers. Local 598; Labor Unions; Miners; Occupational accidents; Sudbury, Ont.; United Steelworkers of America. Local 6500

Servants of the Honourable Company: Work, Discipline, and Conflict in the Hudson's Bay Company, 1770-1879 - Burley, Edith I. (Oxford University Press, 1997)
Historians have tended to view the Hudson's Bay Company `as an organization of crafty fur traders, bold explorers, lively voyageurs, and dour Scots' who opened up the Canadian west and protected it from American control. More recently, social historians have examined the roles of women and Native peoples to show that the HBC `was more than a business.' But, as Professor Edith Burley demonstrates, `the HBC was a business...the purpose of which was to provide shareholders with a return on their investments.' Low paid, subservient workers were required to fulful this purpose. In Servants of the Honourable Company, Professor Burley focuses on the work and workers of the HBC. About 15% of HBC workers were skilled tradesmen, while 70% were common labourers. Until now, however, these `servants' have been largely forgotten. The book looks at these workers from the points of view both of the HBC officers and the London committee and governor who oversaw the operations and of the men themselves, who came from the Orkney Islands, Norway, Scotland, Lower Canada, and the Red River Colony, the settlement created by the HBC in present-day Manitoba to become the nursery of future `halfbreed' workers for the company. The HBC sought workers from pre-industrial societies who would accept the traditional master-servant relationship. To a large extent they did. In fact, they never questioned this central tenet of the HBC hierarchy. They did, however, bargain for higher wages, refuse to work under intolerable and dangerous conditions, object to unfair treatment by authoritarian officers, cause work stoppages in protest for sufficient food and more grog, mutiny against tyrannical ships' captains, and even kill a particularly brutal officer. Servants of the Honourable Company details this important aspect of Canadian working-class experience. --Unattributed synopsis at Amazon

Good Jobs, Bad Jobs, No Jobs: The Transformation of Work in the 21st Century - Duffy, Ann; Glenday, Daniel; Pupo, Norene; Broad, Dave; Burman, Patrick W.; Shalla, Vivian; Glenday, Daniel; Stratton-Devine, Kay; Taylor, Laurel; Haryett, Kathy; Burman, Patrick; White, Jerry; et al. (Harcourt Brace Canada, 1997)
[This book] offers a progressive approach to the sociology of work and labour. Each chapter tackles an essential contemporary labour issue and includes original research from top scholars across Canada. The first of four parts is devoted to the contemporary turmoil of working Canadians caused by the upheaval in the manufacturing and service industries. Part Two discusses the tremendous impact of technology on the labour force. Specific case studies raise universal questions. ...Part Three examines issues specific to women in the new and changing workplace. The intrinsic conflict of work and family is established as the context for examining the division of labour inside and outside the family. ...Chapters in the final part examine the loss of manufacturing jobs, and the new realities of unemployment, underemployment, and under-qualification. --Publisher's description (abridged)
Keywords: 21st century; Transformation; Work; Working class

Profiles in Dissent: The Shaping of Radical Thought in the Canadian West - Gutkin, Harry; Gutkin, Mildred (NeWest Press, 1997)
A recounting of the lives of the leaders and organisers who were arrested and charged at the climax of the Winnipeg General Strike and how their efforts helped give birth to an active, organised Prairie labour movement that spread across the nation. --Publisher's description
Keywords: Biography; Labour leaders; Winnipeg general strike

Canada and the Aboriginal Peoples, 1867-1927 - Miller, James Rodger (Historical Booklet / Canadian Historical Association, 1997)

Making Fast Food: From the Frying Pan into the Fryer - Reiter, Ester (McGill-Queen's University Press, 1997)
An examination of the impact of the fast food industry on work and family life. Ester Reiter worked full-time at a Burger King outlet for ten months gathering information for this study. In Making Fast Food she shares her experiences and analyses the profound effect the fast food industry has had on women's work, youth employment, the labour movement, the family, and the community. Family life, for example, has changed dramatically in the last forty years as many activities that were traditionally part of the home have been replaced by services available in the marketplace. The second edition includes an epilogue that brings the study up to date. Reiter examines the way the fast food model is being adopted in other areas, such as health, and explores unionization in fast food businesses. --Publisher's description. Artwork by Richard Slye. Contents: The market moves into the family and the family moves into the market -- The restaurant industry in Canada -- The fast food invasion -- Burger King: a case study -- Working in a Burger King outlet -- Modern times in the hamburger business -- Martialling workers' loyalty -- Is this the work situation of the future?
Keywords: Burger King; Canada; Convenience foods; Fast food restaurants; Food industry and trade

Cold Warrior: C.S. Jackson and the United Electrical Workers - Smith, Doug (Past CCLH Publications, 1997)
C.S. Jackson was the labour leader that the establishment loved to hate. Tough, intelligent, courageous, and incorruptible, he was one of the founders of industrial unionism in Canada in the 1930's. He served as the head of the Canadian division of the United Electrical Workers for 43 years. During that time he battled with some of the world's largest corporations, with powerful politicians who had him interned, and with most of the leadership of the Candian labour movement. Long-associated with the Communist Party, Jackson and the UE were victimized by the Cold War, expelled from the Canadian Congress of Labour, and subjected to red-baiting raids conducted by unions under more moderate political leadership. But in the Cold War, which disfigured both Canadian society and the Candian labour movement, he gave as good as he got. This biography demonstrates that Jackson thrived on conflict and challange and rarely shrank from a confrontation - in either his public or private life. Making extensive use of interviews conducted with Jackson and his associates, it provides an intimate portrayal of one of the most controversial and successful radical labour leaders in Canadian history. --Publisher's description
Keywords: 20th century; Biography; History; Jackson, C.S. (Clarence Shirley), 1906-1993; Labor Unions; Labor leaders; Labor movement; Officials and employees; United Electrical, Radio and Machine Workers of America

Angels of the Workplace: Women and the Construction of Gender Relations in the Canadian Clothing Industry, 1890-1940 - Steedman, Mercedes (Canadian social history series, 1997)
In this study of the clothing industry in Canada, historian Mercedes Steedman examines how the intricate weaving together of the meanings of class, gender, ethnicity, family, and workplace served, often unconsciously, to create a job ghetto for women. Although 'girls', as working women were labelled, comprised a significant majority of garment workers - 80 percent in 1881, at the very beginnings of industrialization; 68 percent in 1941, when the percentage of women in all industrial sectors in Canada was only just over 15 percent - their roles were circumscribed both in the workplace and in the trade union bureaucracy. When strikes occurred, women were at the front of picket lines, gaining sympathy and favourable media coverage for the workers' cause. But when negotiations among union leaders, management, and government officials took place, women were conspicuous by their absence, and the subsequent agreements and job classifications invariably left them with lower wages and marginal status - in an industry where they were numerically dominant and often valued as the better workers. In "Angels of the Workplace," Professor Steedman presents a history of both the garment industry and the role of women in it. The rise of left-wing unionism held out some hope for a more equitable work environment, but by the 1930s a 'new unionism' that focused on labour-management co-operation - and on maintaining male hegemony on the shop floor and at the bargaining table - had formalized gender discrimination in the needle trades for the rest of the century. -- Publisher's description. Contents: Introduction: Across the Great Divide -- The Industrial Fields of Activity: Send Forth Your Daughters -- Worlds Apart: Women and Unions in the Needle Trades, 1890-1920 -- From Shop-Floor Action to New Unionism: The War Years and After -- Taking a Stand: Civil War in the Needle Trades -- 'A Real Man's Fight': Clothing Battles in the Depression Years -- When the Boys Get Together: Orchestrating Consent -- After the Acts: Setting the Standards, Putting on the Pressure -- Conclusion: 'This Group of Girls and Men .... '
Keywords: 20th century. Sex discrimination in employment; 20th century. Women; Canada; Clothing workers; Employment; History; History. Clothing trade; History. Labor unions; History. Sex discrimination in employment; History. Women labor union members; Women clothing workers

We Lived a Life and Then Some: The Life, Death, and Life of a Mining Town - Angus, Charlie; Griffin, Brit (Between the Lines, 1996)
Based on in-depth oral interviews with local residents, and rich archival sources, We Lived A Life and Then Some relates the common person’s struggle to overcome harsh working conditions and government neglect. The unique culture of the hardrock mining town of Cobalt is exposed through the eyes of retired miners, young welfare mothers, and grade-school children. Angus and Griffin reveal why, in spite of great adversity, Cobalt remains a distinctive and cohesive working-class community. --Publisher's description

Stanley Bréhaut Ryerson, un intellectuel de combat - Beaudry, Lucille; Bernard, Jean-Paul; Dansereau, Bernard; Denis, Serge; Endicott, Stephen Lyon; Fecteau, Jean-Marie; Frank, David; Fuyet, Hervé; Levesque, Andrée; Massé, Georges; Saint-Pierre, Céline; Comeau, Robert; et al. (Asticou. Histoire des idées politique, 1996)
Historien reconnu à l'échelle internationale, Stanley Bréhaut Ryerson a été un précurseur par sa réinterpretation de l'histoire des peuples de Canada. Ses ouvrages se tiennent une place tout à fait singulièredans l'historiographie canadienne. Intelluelle d'envergure, il a su allier l'excellence scientifique à la responsibilité sociale ; tout au longue une carrière de plus de soixante années, il a conservé ce profil de militant et d'historien engagé. Sa recherche, toujours inspirée des problèmes de société, a été animée par des valeurs de justice, de solidarité et de liberté. Cet ouvrage auquel participent quatorze collaborateurs qui veut faire connaître le plus important historien Marxiste du Canada. Il vise égalment rétracer la trajectoire militante et le cheminement intellectuel progressiste qui a laissé derrière lui une œuvre fort imposante. --Résumé de l'éditeur
Keywords: Ryerson, Stanley Bréhaut, 1911-

Making Western Canada: Essays on European Colonization and Settlement - Cavanaugh, Catherine Anne; Mouat, Jeremy (Garamond, 1996)
This ground-breaking collection demonstrates the research interests of a new generation of scholars. Stressing such themes as gender, race and class, the book is compelling evidence that Western Canadian history is far more complex and subtle than its depiction in the traditional literature. The contributors emphasize the way society has been made, and the extent to which it was - and is - the product of human agency rather than possessing an intangible existency beyond the interaction of groups of people. --Publisher's description
Keywords: Amérique du Nord (Ouest) Histoire; Aufsatzsammlung; Canada (Ouest) Histoire; Canada History; Canada, Western History; Geschichte; Geschiedschrijving; History; Kanada West; Kolonisation; Siedlung; Sociale geschiedenis; Western Canada

The System of Industrial Relations in Canada - Craig, Alton W. J. (Alton Westwood Joseph); Solomon, Norman A. (Prentice-Hall Canada, 1996)
[E]xamines thoroughly the ecological, economic, political, legal, and social influences that drive public, private, and parapublic sectors into intense and often bitter disputes over employment conditions. --From publisher's description
Keywords: Industrial relations -- Canada

The Canadian Labour Movement: A Brief History - Heron, Craig (Lorimer, 1996)
Recounts the story of labour from the mid-nineteenth century to the present day. A masterful overview that encompasses all regions of the country, the book paints a vivid portrait of labour's varied past, covering the birth of craft unionism prior to World War I, the setbacks of the interwar years, and the post-World War II breakthrough that gave unions a permanent, if still constrained, place in the national economy. In its analysis of the more recent past, the book ranges just as widely, discussing everything from the organization of public sector employees in the sixties to the anti-free-trade coalitions of the eighties and the massive layoffs of the nineties. --Publisher's description
Keywords: Canada; History; Labor unions; Labor unions Canada History; Syndicats Canada Histoire

Arvida au Saguenay : naissance d'une ville industrielle - Igartua, José E. (Studies on the history of Quebec, 1996)
Fondée en 1925, la ville d'Arvida est née de la nécessité de fournir de la main-d'oeuvre à l'usine Alcan qui venait de s'implanter sur les rives du Saguenay. L'arrivée de la grande enterprise dans le Québec rural a conduit au téléscopage de deux cultures: la culture industrielle moderne de l'Amérique du Nord Anglophone et la culture rurale traditionelle du Québec francophone. Arvida est un véritable microcosme de la naissance d'une ville industrielle et du développement de l'identité communautaire de sa population. José Igartua s'intéresse tout particulièrement au movement ouvrier local qui a atteint son apogée lors de la célèbre grève sauvage de 1941, démontrant que la lutte pour l'action collective a marqué un tournant dans l'épanouissement de la conscience communautaire. --Résumé de l'éditeur
Keywords: Arvida (Saguenay, Québec) Economic conditions; Economic history; History; Québec Arvida (Saguenay); Québec Saguenay; Travailleurs Québec (Province) Saguenay Histoire; Working class; Working class Québec (Province) Saguenay History

Indians at Work: An Informal History of Native Labour in British Columbia, 1848-1930 - Knight, Rolf (New Star Books, 1996)
[P]rovides an historical background to native labour in BC from the Gold Rush to the beginning of the Great Depression. It counters the common misconception that native people responded to European settlement and industrial development by retreating to a reserve existence. Evidence amassed from logging, transport, construction, longshoring, commercial fishing and canning, and a host of other industries shows that native Indians played a significant role in British Columbia's economy from the moment the first European explorers appeared off the coast. --Publisher's description. A massively documented history of Native Indian wage labour in British Columbia from initial European settlement in the mid 19th century to the beginning of the great depression. The first and as yet only historical study of Native Indian workers in Canada, it challenges many of the romantic misconceptions which have developed over the years. An expanded version of a title originally published in 1978. --Author's description
Keywords: British Columbia. Indians of North America; British Columbia. Labor supply; Employment; Employment. Labor supply; Indians of North America

Our History: The Ukrainian Labour-Farmer Movement in Canada, 1907-1991 - Kravchuk, Petro (Lugus Publications, 1996)
Discusses the origins and history of the Association of United Ukrainian Canadians, a progressive organization founded in 1918 as the Ukrainian Temple Labour Association.

Making Vancouver: Class, Status, and Social Boundaries, 1863-1913 - McDonald, Robert A. J. (UBC Press, 1996)
Making Vancouver is about the people of Vancouver, British Columbia. It traces the social transformation of the city and points out how Shaughnessy Heights lumber barons, Mount Pleasant trades people, and East End labourers were part of a complex society whose members exhibited sharp differences in attitudes and behaviour. In Making Vancouver, Robert McDonald depicts a western city that was neither egalitarian nor closed to opportunity. Vancouver up to the crash of 1913 was a dynamic centre. The rapidity of growth, easy access to resources, a narrow industrial base, and the homogeneous nature of its population, the majority of which was of British birth, softened the thrust towards class division inherent in capitalism. Far more powerful in directing social relations was the quest for status, creating a social structure that was no less hierarchical than that predicted by class theory but much more fluid. The social boundary that separated the working class from others is revealed as a division that for much of the pre-war boom period divided Vancouver society more fundamentally than the boundary separating labour from capital. --Publisher's description
Keywords: 15.85 history of America; British Columbia Vancouver; Canada; Classes sociales Colombie-Britannique Vancouver Histoire; History; Social classes; Social classes -- British Columbia -- Vancouver -- History; Social classes British Columbia Vancouver History; Social conditions; Sociale geschiedenis; Sozialgeschichte 1883-1913; Vancouver; Vancouver (B.C.) -- History; Vancouver (B.C.) -- Social conditions; Vancouver (B.C.) History; Vancouver (B.C.) Social conditions; Vancouver (C.-B.) Conditions sociales; Vancouver (C.-B.) Histoire

For a Working-Class Culture in Canada: a Selection of Colin McKay's Writings on Sociology and Political Economy, 1897-1939 - McKay, Colin (Past CCLH Publications, 1996)
This book sets out to present the economic and social writings of Colin McKay, a pioneer Marxian sociologist and economist in Canada (and no relation to the author), and to place McKay in the context of the international socialist tradition. The manuscript takes the form of an extensive biographical essay, five substantive sections that present and examine McKay's thought both thematically and chronologically, and a concluding essay that places McKay's thought in the context of contemporary discussions with regard to the "decline of Marx" in the late 20th century. Colin McKays's life and work determines the scope of the manuscript, but since this "life and work" extended to subjects as varies as the limitations of Kantian philosophy and the design of North Atlantic schooners, the book is rather less narrow than it might appear at first. --Publisher's description
Keywords: Arbeidersklasse; Canada; Conditions sociales; Histoire; History; Industrial relations; Relations industrielles; Social conditions; Travailleurs; Working class

Cheap Wage Labour: Race and Gender in the Fisheries of British Columbia - Muszynska, Alicja (McGill-Queen's University Press, 1996)
An important new critique of Marx's labour theory of value. Using the fishing industry in British Columbia as a case study, Alicja Muszynski explores how Marx's labour theory of value can be applied to a specific industry and the creation of a specific labour force. She reworks Marx's theory in order to incorporate race and gender as principles that not only created a proletarianized labour force but also legitimized the payment of low wages to particular groups. Cheap Wage Labour is the first analysis of shore work and shore-workers in British Columbia from the 1860s to the mid-1980s. Muszynski provides an interpretation of the events that led to the creation of a cheap wage labour force of shoreworkers, shows how they organized within the framework of the fishermen's union (the UFAWU), and explains how as a consequence their numbers steadily shrank until today they represent only a small portion of the labour force. She looks at factors contributing to the destruction of First Nations culture and economy, such as the displacement of aboriginal peoples from key fishing sites and from working in the salmon canneries, and examines the structure and patterns of Chinese and Japanese immigration and the development of the capitalist class and the white working class. Cheap Wage Labour situates the history of B.C. shoreworkers within the much larger and complex historical enterprise of industrialization, patriarchy, colonialism, and imperialism and provides keen insights into the current fisheries crisis on the West Coast. --Publisher's description. Contents: Introduction: The Problematic -- Marx's Labour Theory of Value: A Critique -- Patriarchy and Capitalism -- The First Nations, Property Rights, and Salmon Canning -- The Dialectics of Cheap Wage Labour -- Organized Resistance: The United Fishermen and Allied Workers Union -- -- State, Labour, and Capital -- Conclusion: Marx's Labour Theory of Value Reconsidered -- Appendix: J.H. Todd & Sons Ltd.

In the Skin of a Lion: A Novel - Ondaatje, Michael (Penguin Random House Canada, 1996)
n the Skin of a Lion is a love story and an irresistible mystery set in the turbulent, muscular new world of Toronto in the 20s and 30s. Michael Ondaatje entwines adventure, romance and history, real and invented, enmeshing us in the lives of the immigrants who built the city and those who dreamed it into being: the politically powerful, the anarchists, bridge builders and tunnellers, a vanished millionaire and his mistress, a rescued nun and a thief who leads a charmed life. This is a haunting tale of passion, privilege and biting physical labour, of men and women moved by compassion and driven by the power of dreams—sometimes even to murder. --Publisher's description
Keywords: Fiction; Love stories; Ontario Toronto; Poor; Social Class and Equality; Toronto (Ont.)

Changing Women, Changing History: A Bibliography of the History of Women in Canada - Pedersen, Diana L. (Diana Lynn) (Women's experience series, 1996)
Changing Women, Changing History is a bibliographic guide to the scholarship, both English and French, on Canadian's women's history. Organized under broad subject headings, and accompanied by author and subject indices it is accessible and comprehensive. [Includes sections on Families/Life stages, Unions/Labour activism, and Work/Economy.] --Publisher's description
Keywords: Women -- Canada -- History -- Bibliography

Gender and History in Canada - Rosenfeld, Mark; Parr, Joy (New Canadian readings, 1996)
[This book] is a collection of essays that surveys the burgeoning field of gender history in a Canadian context. Spanning a period from seventeenth century to the 1960s, and covering the regions of Canada, the selections focus on different historical representations and pratices of feminity and masculinity. Historians in the field examine neglected dimensions, and challenge previous interpretations of Canada's past, highlighting the importance of gender relations to our understanding of racism, sexuality, national identity, popular culture, class conflict, government policy, and family in Canadian history. --Publisher's description.

Seafaring Labour: The Merchant Marine of Atlantic Canada, 1820-1914 - Sager, Eric W (McGill-Queen's University Press, 1996)
A compassionate look at the effect of industrialization on the individual lives of sailors, Sager argues that sailors were not misfits or outcasts but were divorced from society only by virtue of their occupation. The wooden ships were small communities at sea, fragments of normal society where workers lived, struggled, and often died. With the coming of the age of steam, the sailor became part of a new division of labour and a new social hierarchy at sea. Sager shows that the sailor was as integral to the transition to industrial capitalism as any land worker. --Publisher's description

Le monde du travail au Québec : bibliographie = The World of Labour in Québec: Bibliography - Thwaites, James D.; Leblanc, André (Presses de l'Université du Québec, 1996)
5700 titres en francais et en anglais, mais aussi dans d'autres langues. Des milliers d'articles, de livres, de thèses, de documents audio et audiovisuels, ainsi que les journaux du monde ouvrier. Des sources essentielles pour tous ceux et celles qui s'intéressent au monde du travail. --Résumé de l'éditeur
Keywords: Bibliographies; Industrial relations; Industrial relations Québec (Province) Bibliography; Labor; Labor Québec (Province) Bibliography; Labor laws and legislation; Labor laws and legislation Québec (Province) Bibliography; Québec; Relations industrielles Québec (Province) Bibliographie; Syndicalism; Syndicalism Québec (Province) Bibliography; Syndicalisme Québec (Province) Bibliographie; Travail Québec (Province) Bibliographie; Work environment; Work environment Québec (Province) Bibliography

'As Their Natural Resources Fail': Native Peoples and the Economic History of Northern Manitoba, 1870-1930 - Tough, Frank (UBC Press, 1996)
In conventional histories of the Canadian prairies, Native people disappear from view after the Riel rebellions. In a fresh departure from traditional studies, Frank Tough examines the role of Native people, both Indian and Metis, in the economy of northern Manitoba from 1870 to the Depression. He argues that they did not become economically obsolete but rather played an important role in the transitional era between the mercantile fur trade and the emerging industrial economy of the mid-twentieth century. Tough reconstructs the traditional economy of the fur trade era and examines its evolution through reserve selection and settlement, scrip distribution, and the participation of Natives in the new resource industries of commercial fishing, transportation, and lumbering. His analysis clearly shows that Native people in northern Manitoba responded to the challenge of an expanding market economy in rational and enterprising ways, but that they were repeatedly obstructed by government policy. --Publisher's description. Revision of the author's thesis (Ph. D.)--York University. Contents: 1. 'To Look for Food Instead of Fur': Local Economies -- Indian Bands and Company Posts -- 2. 'The Only Remedy Is the Employment of Steam': Reorganizing the Regional System -- 3. 'Dependent on the Company's Provisions for Subsistence': The Decline of Kihchiwaskahikanihk (York Factory) -- 4. 'To Be Shut Up on a Small Reserve': Geographical and Economic Aspects of Indian Treaties -- 5. 'Lands Are Getting Poor in Hunting': Treaty Adhesions in Northern Manitoba -- 6. 'Terms and Conditions as May Be Deemed Expedient': Metis Aboriginal Title -- 7. 'Go and Pitch His Camp': Native Settlement Patterns and Indian Agriculture -- 8. 'Nothing to Make Up for the Great Loss of Winter Food': Resource Conflicts over Common-Property Fisheries -- 9. 'A Great Future Awaits This Section of Northern Manitoba': Economic Boom and Native Labour -- 10. 'They Make a Comfortable Living': Economic Change and Incomes. Includes bibliographical references (pages 334-363) and index.
Keywords: Canada; Conditions conomique. Autochtones; Conditions conomiques. Indiens; Conditions conomiques. Wirtschaft Indigenes Volk Geschichte 1870-1930. Native peoples; Economic conditions. Autochtones; Economic conditions. Economic history. Indians of North America. Indians of North America; Economic conditions. Native peoples; Histoire. Genre/Form: History; History. Autochtones; History. Indians of North America; Indians of North America; Manitoba; Manitoba (Nord); Manitoba, Northern

Beyond Labor's Veil: The Culture of the Knights of Labor - Weir, Robert E. (Pennsylvania State University Press, 1996)
The Noble and Holy Order of the Knights of Labor was founded in 1869 as a secret fraternal order committed to the goal of uniting American labor. At its height in 1886, the Knights claimed the allegiance of perhaps a million workers. Despite a host of local studies by the new labor historians of the 1970s and 1980s, there has been no general study of the Knights since Norman Ware's 1929 book, and no one has ever attempted a comprehensive study of the culture of the organization. In Beyond Labor's Veil, Robert E. Weir presents a fascinating cultural portrait of the Knights across regions, covering the years 1869 to 1893. From the start, the Knights of Labor was an unusual organization, equal parts fraternal order and labor union. It was the only nineteenth-century labor organization to organize African Americans, women, and unskilled workers on an equal basis with white craftsmen. Weir goes beyond the rhetoric of public pronouncements and union politics to consider the real influence of the Knights in communities and homes as well as in the workplace. Weir explores the many cultural expressions of the Knights' ritual, religion, poetry, music, literature, material objects, graphics, and leisure. Although the Knights barely survived into the twentieth century, Weir concludes that the creative cultural expressions of the Knights enabled it to do as well as it did in the face of powerful oppositional forces. What emerges in Beyond Labor's Veil is a rich, detailed description of the Knights as its members adapted to the confusion and contradiction of America's Gilded Age. --Publisher's description
Keywords: Knights of Labor -- History

Cold War Canada: The Making of a National Insecurity State, 1945-1957 - Whitaker, Reginald; Marcuse, Gary (University of Toronto Press, 1996)
Canadians might expect that a history of Canada's participation in the Cold War would be a self-congratulatory exercise in documenting the liberality and moderation of Canada set against the rapacious purges of the McCarthy era in the United States. Though Reg Whitaker and Gary Marcuse agree that there is some evidence for Canadian moderation, they argue that the smug Canadian self-image is exaggerated. Cold War Canada digs past the official moderation and uncovers a systematic state-sponsored repression of communists and the Left directed at civil servants, scientists, trade unionists, and political activists. Unlike the United States, Canada's purges were shrouded in secrecy imposed by the government and avidly supported by the RCMP security service. Whitaker and Marcuse manage to reconstruct several of the significant anti-communist campaigns. Using declassified documents, interviews, and extensive archival sources, the authors reconstruct the Gouzenko spy scandal, trace the growth of security screening of civil servants, and re-examine purges in the National Film Board and the trade unions, attacks on peace activist James G. Endicott, and the trials of Canadian diplomat Herbert Norman. Based on these examples Whitaker and Marcuse outline the creation of Canada's Cold War policy, the emergence of the new security state, and the alignment of Canada with the United States in the global Cold War. They demonstrate that Canada did take a different approach toward the threat of communism, but argue that the secret repression and silent purges used to stifle dissent and debate about Canada's own role in the Cold War had a chilling effect on the practice of liberal democracy and undermined Canadian political and economic sovereignty. --Publisher's description

Good Jobs, Bad Jobs, No Jobs: Tough Choices for Canadian Labor Law - Adams, Roy J. (C.D. Howe Institute, 1995)
In many industrialized countries over the past twenty years, including Canada, the supply of "good" jobs for those with low formal education has declined relative to demand. While the contributors to this volume do not agree on which labor policies are best, they share a common dissatisifaction with the current way of doing things. --Publisher's description. Includes separate bibliographies at the end of most chapters.
Keywords: Labor market -- Canada

Industrial Relations Under Liberal Democracy: North America in Comparative Perspective - Adams, Roy J. (University of South Carolina Press, 1995)
Most scholars and business people have traditionally regarded industrial relations in the United States and Canada to be so different from practices in other liberal democracies as to render comparison of little practical utility. Fundamental differences, such as the influence of "pure and simple" business-like philosophy on the American and Canadian labor movements in contrast to the socialist agenda of trade unions in other industrialized countries, have prompted observers to question the value of comparative analysis. Roy Adams, however, challenges this view by constructing a theoretical framework within which the comparison of industrial relations across the advanced liberal democratic world may be made comprehensible. --Publisher's description.
Keywords: Comparative management

Risks, Dangers, and Rewards in the Nova Scotia Offshore Fishery - Binkley, Marian (McGill-Queen's University Press, 1995)
An anthropological assessment of working conditions in one of the most hazardous and physically demanding industries in Canada, Risks, Dangers, and Rewards in the Nova Scotia Offshore Fishery describes the hidden cost paid by workers in the Nova Scotia offshore fishery, a cost measured not in dollars and cents but in deaths and injuries. According to Labour Canada, workers in the offshore fishery are more likely to be injured than workers in mining, construction, or forestry. Yet until recently these casualties at sea have been largely ignored by government and labour organizations. Risks, Dangers, and Rewards in the Nova Scotia Offshore Fishery describes the hidden cost paid by workers in the Nova Scotia offshore fishery, a cost measured not in dollars and cents but in deaths and injuries. In this comprehensive study Marian Binkley documents the level of risk and assesses the general health and stress level of workers in the Nova Scotia offshore fishery. She considers shipboard working environment; stress; accidents, injuries, and general health; safety awareness; job satisfaction and family life; and the impact on working conditions of government resource policies and companies' scientific management strategies. Using statistical analysis, participant observation, surveys, and interviews, Binkley establishes that factors such as technological developments, management changes, and home and community life affect the immediate work experience of fishers and can increase the dangers of an already hazardous occupation. --Publisher's description

Ninety-Nine Days: The Ford Strike in Windsor, 1945 - Colling, Herb (UAW Local 200's strike against the Ford Motor Company of Canada ended in partial victory, establishing the Rand Formula, providing union security and dues check-off, but restricting union activities during labour strife. It was the first large post-war strike, an emotional and bitter battle in an uncertain time. This new book is a day-to-day account of union and non-union workers fighting for their jobs, differences between a radical local and the more conservative international executive, the role of Communists and of the labour centres, and political parties and reluctant governments manoeuvring for control of the labour movement. It is a human drama with court challenges, confrontations, a rank and file blockade of cars that prevented police from breaking through to the plant, and Windsor's longest burning coal fire which could not be extinguished until the men returned to work. The book also tells the poignant stories of devoted women who made bologna sandwiches and coffee for the men on the line, and who struggled to put food on their own tables. Chickens, eggs and vegetables were delivered to the picket line by local farmers. Ford watchmen, afraid to leave the plant, had to scrounge for food until they thought it safe to come out; children aped their elders and struck their schools until they were forced back into class; and a superintendent refused to leave the plant and had to be carried out by the men. --Publisher's description, 1995)
Keywords: 1945; Ford Motor Company Strike, Windsor, Ont., 1945; Ford Motor Company of Canada; Ford Motor Company of Canada (Windsor, Ont.) Grève, 1945; Ford Motor Company of Canada Strike, Windsor, Ont., 1945; Grèves et lock-out Automobiles Industrie et commerce Ontario Windsor; International Union, United Automobile, Aerospace and Agricultural Implement Workers of America. Local 200; International Union, United Automobile, Aerospace and Agricultural Implement Workers of America. Local 200 (Windsor, Ont.); Ontario Windsor; Strikes and lockouts Automobile industry; Strikes and lockouts Automobile industry Ontario Windsor

Labouring Lives: Work and Workers in Nineteenth-Century Ontario - Craven, Paul (Ontario historical studies series, 1995)
For twenty years, labour and working-class history has emphasized the struggle for workplace control between skilled craftsmen and factory owners in Ontario's major industrial cities. This preoccupation not only has left the great majority of the province's working people in the shadows of history, but has isolated labour history from such other 'new histories' as women's history, ethnic history, and the history of mobility. This collaborative volume argues for a more nuanced account of the diversity of working people's experience in the nineteenth century. It presents detailed studies of a broad range of occupations and institutions that figured prominently in workers' lives. These include the more common jobs - farm labour, housework, lumbering - and the more pervasive institutions - the church, the law, the family - as well as new accounts of industrial labour in small-town factories and on the railways. The themes explored include class formation, the nature and meaning of work, labour relations, and the character of economic and social change in nineteenth-century Ontario. --Publisher's description. Contents: Introduction / Paul Craven (pages 3-12) -- Rural labour / Terry Crowley (pages 13-104) -- Labour and the law / Jeremy Webber (pages 105-203) -- The Shantymen / Ian Radforth (pages 204-277) -- Religion, leisure, and working-class identity / Lynne Marks (pages 278-334) -- Labour and management on the Great Western Railway / Paul Craven (pages 335-411) -- The home as workplace / Bettina Bradbury (pages 412-478) -- Factory workers (pages 479-589) - Picture credits (page 595) -- Index (pages 597-622).

Grace Hartman: A Woman for Her Time - Crean, Susan (New Star Books, 1995)
Years before women were allowed to read the news on television, Grace Hartman was on television making the news. In 1954, to help pay the mortgage on her family’s new suburban home, Grace Hartman took a job with the Township of North York. Hartman soon became active in her union, where she dedicated herself to improve the worker’s lot. Twenty-one years later Hartman was still a worker, but no longer a secretary for North York: she was president of the Canadian Union of Public Employees, the largest union in Canada. Hartman was the first woman to lead a major labour organization anywhere in North America. [This book] is the story of a labour activist who served two months in jail at the age of 62 for defying a court order and asserting her members’ right to strike. It is the story of a visionary feminist who helped found the National Action Committee on the Status of Women, who stood up to Pierre Trudeau over wage and price controls because she saw that her sisters would bear their brunt. It is the story of a lifelong and committed social activist who fought tirelessly, both inside and outside the labour movement, for women’s rights and progressive causes. --Author's description

Art and Work: A Social History of Labour in the Canadian Graphic Arts Industry to the 1940s - Davis, Angela E. (McGill-Queen's Univ. Press, 1995)
A notable addition to the growing body of work that examines art and work as social constructs, Art and Work traces the development of commercial illustration and the graphic arts industry in Canada from the late eighteenth century to the 1940s. Beginning with the origins of the graphic arts industry in Britain, Angela Davis describes the development of technology, commercial organization, and professionalization of artists in Canada. She focuses on the artists involved in the creation and reproduction of a "popular" art form. The evolution of commercial illustration and the graphic arts industry, Davis asserts, had a dramatic impact not only on the popular press and advertising but also on illustrators, engravers, photo-engravers, and lithographers, who still considered themselves to be artists but found that they were now working in an industrial atmosphere similar to that of other workers. Art and Work reveals that the foundations of Canadian art and popular culture rest not only on the European traditions of "fine" art but also on the commercial art produced in the early graphic arts houses. --Publisher's description

Labour and Working-Class History in Atlantic Canada: A Reader - Frank, David; Kealey, Gregory S. (Social & economic papers, 1995)
This collection of essays provides a generous introduction to the vibrant field of labour and working-class history in Canada's eastern provinces. Organized in four sections covering pre-industrial labour, the industrial revolution, labour's wars of the early twentieth century, and the rise of industrial legality, the book should prove useful in university classrooms and for all readers interested in the history of the region's ordinary people. Concluding chapters address topics of current interest such as public sector unionism, the role of women in the fishery, and the horrors of the Westray mine disaster. The editors provide an introduction, section heads, and suggestions for further reading. The volume is edited by David Frank, Department of History, University of New Brunswick, the former editor of Acadiensis, and Gregory S. Kealey, Department of History, Memorial University of Newfoundland, Dean of Graduate Studies. Authors include T. W. Acheson, Rusty Bittermann, Sean Cadigan, Jessie Chisholm, Patricia M. Connelly, Peter DeLottinville, E. R. Forbes, Eugene Forsey, Harry Glasbeek, Linda Little, Martha MacDonald, Robert McIntosh, Ian McKay, D. A. Muise, Nolan Reilly, Eric W. Sager, Anthony Thomson, and Eric Tucker. --Publisher's description
Keywords: 19th century; 20th century; Atlantic Provinces; History; Labor; Labor unions; Working class

The Canadian Auto Workers: The Birth and Transformation of a Union - Gindin, Sam (Lorimer, 1995)
The Canadian Auto Workers union, the CAW, has a long and rich history. Part of the U.S.-based United Auto Workers for almost fifty years, the CAW separated from its American parent in 1985. Today, the Canadian Auto Workers union encompasses members from a broad range of industries. It is also one of the most powerful unions in the country. Yet few people know the union's history, how it acquired its strength, or what accounts for its split with its American parent. This illustrated history provides a fascinating look at the union from its origins to the present. Beginning in the twenties, Sam Gindin describes the early years of the automobile industry and the emergence of GM, Ford, and Chrysler. He looks at the birth of the UAW in 1936, the conflicts that rocked the union in the fifties, the signing of theAutopact in the sixties, and the historic split of the Canadian section from the UAW two decades later. Finally, he considers the issues facing the union and the Canadian labour movement as the century draws to a close. By providing a profile of the CAW as well as the labour and social movements that it helped shape, The Canadian Auto Workers offers us something unusual — an engrossing glimpse of our past, written from a union perspective. --Publisher's description
Keywords: Automobile industry workers; Canadian Auto Workers (CAW); History; International Union, United Automobile, Aerospace, and Agricultural Implement Workers of America. Canadian Region; Labor Unions

Workers and Canadian History - Kealey, Gregory S. (McGill-Queen's University Press, 1995)
Workers and Canadian History is a collection of twelve essays by Gregory Kealey, the recognized Canadian leader in the growing field of working-class history. Available for the first time in a single volume, the essays provide an extensive study of various trends and themes in Canadian labour and working-class history, covering debates, major developments in historiography, and key events in the nineteenth and twentieth centuries. Kealey provides an overview of the study of workers in Canada as well as in-depth examinations of two of the field's leading scholars, political economist Clare Pentland and Marxist historian Stanley Bréhaut Ryerson. He analyses the development of Canadian labour history in particular and social history in general, and provides detailed empirical studies of the Orange Order in Toronto, printers and their unions, the Knights of Labor, and the Canadian labour revolt of 1919. The collection concludes with three synthetic views of Canadian working-class history focusing on the labour movement, the role of strikes, and attempts by the state to manage class conflict. --Publisher's description. Contents: Part 1: Antecedents. Writing about Labour -- H.C. Pentland and Working-Class Studies -- Stanley Bréhaut Ryerson: Canadian Revolutionary and Marxist Historian. Part 2: Debates. Labour and Working-Class History in Canada: Prospects in the 1980s. -- The Writing of Social History in English Canada, 1970-84. Part 3: Studies of Class and Class Conflict. Orangemen and the Corporation: The Politics of Class in Toronto during the Union of the Canadas -- Work Control, the Labour Process, and Nineteenth-Century Canadian Printers -- The Bonds of Unity: The Knights of Labor in Ontario, 1880-1900 / Gregory S. Kealey and Bryan D. Palmer -- 1919: The Canadian Labour Revolt. Part 4: Overviews. The Structure of Canadian Working-Class History -- Strikes in Canada, 1891-1950 / Gregory S. Kealey and Douglas Cruikshank -- The Canadian State's Attempt to Manage Class Conflict, 1900-48.
Keywords: Canada; History; Labor Unions; Labor movement; Strikes and lockouts; Working class

In Subordination: Professional Women, 1870-1970 - Kinnear, Mary (McGill-Queen's University Press., 1995)
From 1870 to 1970 between ten and twenty per cent of women in paid work held jobs described by the Canadian census as "professional." In this important historical study, Mary Kinnear explores the experience of the first generations of professional women in Canada. Kinnear presents five case studies of professional women in Manitoba: university teachers, physicians, lawyers, nurses, and schoolteachers. Although the unrelenting efforts of nineteenth-century feminists won women access to higher education and the professions, the author reveals that most women, whether in male- or female-dominated professions, were forced to accept subordinate positions. They responded with acquiescence, indifference, resentment, or resistance. Kinnear considers the reasons for and the cost of these various strategies. In addition to quantitative data culled from census and other records, Kinnear has collected testimony from more than two hundred professional women, a rich mine of information. A significant contribution to the growing literature on women and the professions, In Subordination helps explain why professional women continue to fight for equality today. --Publisher's description

Red Flags and Red Tape: The Making of a Labour Bureaucracy - Leier, Mark (James Mark) (University of Toronto Press, 1995)
Labour bureaucracy has long been a subject of interest to sociologists and industrial relations specialists, but it has rarely been examined by labour historians. In Red Flags and Red Tape Mark Leier aims to understand how and why bureaucracy came to dominate an organization that was established to promote greater democracy for the working class. The formative years of the Vancouver Trades and Labour Council, from 1889 to 1910, provide the basis for his study of the interplay between bureaucracy, class, and ideology. Leier sets himself three tasks: he examines the theoretical debates on the labour bureaucracy; he investigates the early history of the VTLC to show how and why bureaucratic structures evolve over time; and he looks at the ideology and personnel of the labour council to try to understand the complex relationship between bureaucrats on the left and right of the political spectrum. He describes the ideology of the bureaucrats (including their attitudes towards gender and race) and how it compares to that of the council's members, and observes that bureaucrats are defined by their power over a movement rather than by their ideology. Finally, since the VTLC was, at different times, dominated by labourists and socialists, Leier explores why different leaders held variant or antagonistic views. Leier concludes that the pressure of trade unionism and the class position of labour officials led to increased bureaucracy and conservatism, even among the socialists of the labour council, and as the Vancouver Trades and Labour Council matured, increased red tape isolated the officials from the membership. --Publisher's description
Keywords: History; Ideology; Labor Unions; Labour leaders; Labour union democracy; Labour union federations; Labour unions; Vancouver Trades and Labour Council (VTLC); Vancouver, British Columbia

Thinking Union: Activism and Education in Canada's Labour Movement - Martin, D'Arcy (Between the Lines, 1995)
Over the past seventeen years, trade union educator D'Arcy Martin has conducted hundreds of courses for Canadian workers. He has learned that there are people-"conscious romantics"-who dream of a more egalitarian world while confronting the obstacles that stand in the way of building it. This book provides a refreshing personal account of union culture and its dynamics. --Publisher's description
Keywords: Canada; Labor Unions; Labor unions and education; Political activity

Ideal Surroundings: Domestic Life in a Working-Class Suburb in the 1920s - Morton, Suzanne (Studies in gender and history, 1995)
The 1920s are seen by historians as a crucial period in the formation of the Canadian working class. In Ideal Surroundings, Suzanne Morton looks at a single working-class community as it responded to national and regional changes. Grounded in labour and feminist history, with a strong emphasis on domestic life, this analysis focuses on the relationship between gender ideals and the actual experience of different family members. The setting is Richmond Heights, a working-class suburb of Halifax that was constructed following the 1917 explosion that devastated a large section of the city. The Halifax Relief Commission, specially formed to respond to this incident, generated a unique set of historical records that provides an unusually intimate glimpse of domestic life. Drawing on these and other archives, Morton uncovers many critical challenges to working-class ideals. The male world-view in particular were seriously destabilized as economic transformation and unemployment left many men without the means to support their families, and as the daughters of Richmond Heights increasingly left their class-defined jobs for service and clerical positions. Drawing on recent theoretical and empirical work, Morton expertly combines interpretive and narrative material, creating a vivid portrayal of class dynamics in this critical postwar era. Her focus on the home and domesticity marks and innovative move towards the integration of gender in the study of Canadian history. --Publisher's description
Keywords: 1900-1999; Families; Families Nova Scotia Halifax History 20th century; Familles Nouvelle-Écosse Halifax Histoire 20e siècle; History; Manners and customs; Nova Scotia Halifax; Nova Scotia Halifax Richmond Heights; Richmond Heights (Halifax, N.-É.) Moeurs et coutumes; Richmond Heights (Halifax, N.S.) Social life and customs; Rôle selon le sexe Nouvelle-Écosse Halifax Histoire 20e siècle; Sex role; Sex role Nova Scotia Halifax History 20th century; Suburban life; Suburban life Nova Scotia Halifax History 20th century; Travailleurs Nouvelle-Écosse Halifax Histoire 20e siècle; Vie de la banlieue Nouvelle-Écosse Halifax Histoire 20e siècle; Working class; Working class Nova Scotia Halifax History 20th century

Roaring Days: Rossland's Mines and the History of British Columbia - Mouat, Jeremy (UBC Press, 1995)
In the 1890s, Rossland was the most important mining centre in southeastern British Columbia. In Roaring Days, Jeremy Mouat examines many different aspects of mining, from work underground to corporate strategies. He also brings to life the unique individuals who were a part of this history – the miners who toiled long hours under unimaginable working conditions, the citizens of Rossland who built a bustling town out of the wilderness, and the mine owners and entrepreneurs who became wealthy beyond all expectations. --Publisher's description

The Feminist Challenge to the Canadian Left, 1900-1918 - Newton, Janice (McGill-Queen's University Press, 1995)
Exploring the role of women and feminism in the early Canadian socialist movement, Janice Newton traces the growth and ultimate decline of feminist ideas within the Canadian Socialist League, the Socialist Party of Canada, and the Social Democratic Party. Newton argues that socialist women and their concerns posed a radical challenge to the male-dominated left. Early socialist women fought to be treated as equals and actively debated popular women's issues, including domestic work, women in industry, sexuality, and women's suffrage. They provided a unique and vibrant perspective on these issues and challenged the middle-class bias inherent in the women's movement. Broadening our understanding of Canadian social history, Newton analyses the intersection of two important social movements - the labour/socialist and the turn-of-the-century feminist movements - and draws conclusions that are essential for understanding the class and gender characteristics of social criticism and activism in this period. --Publisher's description
Keywords: 1900-1999; Börngen, ..; Canada; Feminism; Feminism Canada History; Feminismus; Femmes Activité politique Canada Histoire 20e siècle; Femmes en politique Canada Histoire 20e siècle; Femmes et socialisme Canada Histoire 20e siècle; Frau; Frauenbewegung; Féminisme Canada Histoire; Geschichte 1900-1918; History; Kanada; Linkspartei; Sozialismus; Vänsterpartiet; Women Political activity; Women Political activity Canada History 20th century; Women and socialism; Women and socialism Canada History 20th century

The Apprenticeship of Duddy Kravitz - Richler, Mordecai, (Penguing, 1995)
Duddy Kravitz is obsessed with his grandfather's maxim, “A man without land is nobody.” He sets his heart on acquiring property and does not let any obstacle dissuade him. If he becomes hated along the way, he couldn't care less. In spite of enormous sacrifices and setbacks, Duddy never loses faith in realizing his dream. The Apprenticeship of Duddy Kravitz is the novel that established Mordecai Richler as one of the world's best comic writers. A classic tale of coming of age on Montreal's St. Urbain Street, it is an unforgettable story of ambition, dreams, and familial love. --Publisher's description
Keywords: Blue-collar work; Class Consciousness; Humour; Immigrants; Montreal, Quebec; Race; Social Class and Equality

Earning Respect: The Lives of Working Women in Small-Town Ontario, 1920-1960 - Sangster, Joan (Studies in Gender and History, 1995)
Between 1920 and 1960 wage-earning women in factories and offices experienced dramatic shifts in their employment conditions, the result of both the Depression and the expansion of work opportunities during the Second World War. Earning Respect examines the lives of white and blue-collar women workers in Peterborough during this period and notes the emerging changes in their work lives, as working daughters gradually became working mothers. Joan Sangster focuses in particular on four large workplaces, examining the gendered division of labour, women's work culture, and the forces that encouraged women's accommodation and resistance on the job. She also connects women's wage work to their social and familial lives and to the larger community context, exploring wage-earning women's 'identities,' their attempts to cope with economic and family crises, the gendered definitions of working-class respectability, and the nature of paternalism in a small Ontario manufacturing city. Sangster draws upon oral histories as well as archival research as she traces the construction of class and gender relations in 'small town' industrialized Ontario in the mid-twentieth century. She uses this local study to explore key themes and theoretical debate in contemporary women's and working-class history. --Publisher's description

Hard Labour Lessons: The Mine Mill Centennial Conference [Sudbury : 1993] - Steedman, Mercedes; Suschnigg, Peter Theobald; Buse, Dieter K. (Dundurn Press, 1995)
This book brings together the voices of contemporary labour leaders, activists, old timers, and academics to discuss the first hundred years of the Mine, Mill and Smelter Workers Union. --Worldcat catalogue record
Keywords: Canada; Conference papers and proceedings; History; International Union of Mine, Mill, and Smelter Workers; International Union of Mine, Mill, and Smelter Workers History Congresses; Labor unions; Labor unions Canada History Congresses; Labor unions Canada Miners History Congresses; Labor unions Ontario Sudbury Region Miners History Congresses; Ontario Greater Sudbury Region; Syndicats Canada Histoire Congrès

Wheel of Fortune: Work and Life in the Age of Falling Expectations - Swift, Jamie (Between the Lines, 1995)
Jamie Swift combines sharp-eyed journalism that brings out the nuances of daily life with a penetrating analysis of jobless recovery. He describes the emerging world of work through the eyes and experiences of people in Kingston and Windsor-two Ontario cities with roots in the pre-industrial past, places poised for the post-industrial information age. --Publisher's description
Keywords: Employment forecasting; Kingston (Ont.); Labor; Labour market; Ontario; WINDSOR (Ont.); Working class

Workplace Industrial Relations and the Global Challenge - Bélanger, Jacques; Haiven, Larry; Edwards, P. K. (Paul K.) (ILR Press, 1994)
Contents: Introduction : the workplace and labor regulation in comparative perspective / P.K. Edwards, Jacques Bélanger, and Larry Haiven -- A comparison of national regimes of labor regulation and the problem of the workplace / P.K. Edwards -- Job control under different labor relations regimes : a comparison of Canada and Great Britain / Jacques Bélanger -- Workplace discipline in international comparative perspective / Larry Haiven -- Shopfloor relations at U.S. and Canadian plants of an automotive parts supplier, 1936-1988 / Stephen Herzenberg; Bargaining regimes and the social reorganization of production : the case of General Motors in Austria and Germany / Karen Shire -- New technology and the process of labor regulation : an international perspective / Anthony E. Smith -- Conflict and compliance : the workplace politics of a disk-drive factory in Singapore / Chung Yuen Kay -- The new international division of labor and its impact on unions : a case study of high-tech Mexican export production / Harley Shaiken -- Patterns of workplace relations in the global corporation : toward convergence? / Stephen Frenkel -- Conclusion : globalization, national systems, and the future of workplace industrial relations / Larry Haiven, P.K. Edwards, and Jacques Bélanger; Introduction : the workplace and labor regulation in comparative perspective / P.K. Edwards, Jacques Belanger, and Larry Haiven -- A comparison of national regimes of labor regulation and the problem of the workplace / P.K. Edwards -- Job control under different labor relations regimes : a comparison of Canada and Great Britain / Jacques Belanger -- Workplace discipline in international comparative perspective / Larry Haiven -- Shopfloor relations at U.S. and Canadian plants of an automotive parts supplier, 1936-1988 / Stephen Herzenberg; Bargaining regimes and the social reorganization of production : the case of General Motors in Austria and Germany / Karen Shire -- New technology and the process of labor regulation : an international perspective / Anthony E. Smith -- Conflict and compliance : the workplace politics of a disk-drive factory in Singapore / Chung Yuen Kay -- The new international division of labor and its impact on unions : a case study of high-tech Mexican export production / Harley Shaiken -- Patterns of workplace relations in the global corporation : toward convergence? / Stephen Frenkel -- Conclusion : globalization, national systems, and the future of workplace industrial relations / Larry Haiven, P.K. Edwards, and Jacques Belanger
Keywords: Vergelijkend onderzoek

Canadian Labour History: Selected Readings - Bercuson, David Jay (New Canadian readings, 1994)
The second edition of Canadian Labour History invites the reader to enter the debate that has made this field of study such a dynamic one in the past two decades. Covering the period from 1840 to 1980, these essays focus on a variety of Canadian regions demonstrating the similarities and differences of regional experiences. Similarly, alternate approaches to a single event-the Winnipeg General Strike-illustrate the diversity in the interpretation of labour history. --Publisher's description. Contents: The formation and fragmentation of the Canadian working class, 1820-1920 / Daniel Drache -- Listening to history rather than historians: Reflections on working class history / Bryan D. Palmer -- Ethnicity and class, transitions over a decade: Ontario, 1861-1871 / A. Gordon Darroch and Michael Ornstein -- Women and wage labour in a period of transition: Montreal, 1861-1881 / Bettina Bradbury -- Strikes in the Maritimes, 1901-1914 / Ian McKay -- Labour's civil war / David J. Bercuson -- 1919: The Canadian labour revolt / Gregory S. Kealey -- “We are all kin”: Reconsidering labour and class in Calgary, 1919 / David Bright -- Communists and auto workers: The struggle for industrial unionism in the Canadian automobile industry, 1925-1936 / John Manley -- The United Mine Workers and the coming of the CCF to Cape Breton / M. Earle and H. Gamberg -- The 1943 steel strike against wartime wage control / Laurel Sefton MacDowell -- Woodworkers and the mechanization of the pulpwood logging industry in Northern Ontario, 1950-1970 / Ian Radforth -- Inside postal workers: The labour process, state policy, and the workers' response / Bruce Laidlaw and Bruce Curtis -- A heritage of hope and struggle: Workers, unions, and politics in Canada, 1930-1982 / Wayne Roberts and John Bullen.
Keywords: Labour history; Strikes

Relations of Ruling: Class and Gender in Postindustrial Societies - Clement, Wallace; Myles, John (McGill-Queen's University Press, 1994)
For more than two decades sociologists have debated the social and political consequences of an emergent postindustrial society. This comparative study addresses these debates, using original empirical data from five advanced capitalist economies - Canada, the United States, Sweden, Norway, and Finland. For some, the postindustrial world promises a new kind of capitalism that will draw its vitality from an expansion of knowledge and the creative capacities of working men and women. Others have highlighted postindustrialism's darker side and concluded that it is simply the next stage in the degradation of labour. For some, the massive entry of women into paid labour that accompanies postindustrialism will finally liberate women from domestic patriarchy. For others, it is no more than an extension of private patriarchy into the public sphere. The authors show that historical residues and the contemporary impact of major economic and political factors have produced not one but several postindustrial trajectories. They reveal how postindustrialism has brought a new distribution of productive forces and of effective powers over people, and show that the shape of that distribution varies considerably in different countries and different fields as a result of both institutionalized practices (inherited from industrial capitalism) and the contemporary effects of state policies, organized labour, and the women's movement. Addressing issues of class and gender, Relations of Ruling deals with problems involved in regulating paid labour as well as the relationship between paid and domestic labour. It will be of particular interest to specialists in gender issues and scholars in women's, family, and labour studies. --Publisher's description
Keywords: Social classes

Constructing Modern Canada: Readings in Post-Confederation History - Gaffield, Chad (Copp Clark Longman, 1994)
[This textbook] includes examples of some of the best recent scholarship on the development of society, economy, and politics in post-Confederation Canada, scholarship that not only promotes new ways of viewing history, but new methods of research as well. The readings emphasize gender, class, ethnicity, and region, as well as people's relationship to the environment, to provide varied and wide-ranging views of Canada's past. --Publisher's description
Keywords: Aufsatzsammlung; Canada; Canada Conditions sociales 1867-; Canada Histoire 1867-; Canada History 1867-; Canada Social conditions 1867-; Geschichte 1867-1994; History; Kanada; Since 1867

Le syndicalisme : état des lieux et enjeux - Gagnon, Mona-Josée (Institut québécois de recherche sur la culture, 1994)
Le syndicalisme se donne à voir des profils souvent contradictoires: acteur institutionnel et néanmoins défenseur des exclus, partenaire des employeurs et néanmoins porteur de revendications. Quelle est sa vraie nature? Le syndicalisme d'aujourd'hui est-il le successeur du syndicalisme d'antan ou une créature hybride se définissant davantage par la notion de changement? Mona-Josée Gagnon connaît bien le sujet, pour l'avoir étudié et enseigné, mais aussi pour avoir fait du syndicalisme le lieu essentiel de sa vie professionnelle depuis plus de vingt ans (au service de la recherche de la FTQ
Keywords: Syndicalism -- Québec (Province)

The Early Years, 1919-1929 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1994)
In 1919 at the height of the post-war labour revolt,the Royal Canadian Mounted Police took responsibility for national security. This volume contains archival materials and other materials received through Canadian Access to Information legislation. It includes lists of personal files, subject files, and security bulletins circulated to the government. In general the material provides an excellent overview of the genesis of the Canadian state security system. --Publisher's description
Keywords: Activités subversives; Canada; Communism; Communisme; Gendarmerie royale du Canada; Histoire; History; Internal security; Royal Canadian Mounted Police (RCMP); Subversive activities; Sûreté de l'État

Women, Work and Place - Kobayashi, Audrey Lynn; Bondi, Liz; Bradbury, Bettina; Kaye, Allison; Parr, Joy; Villeneuve, Paul; Christopherson, Susan; Gold, Sylvia; Peake, Linda; Rose, Damaris (McGill-Queens University Press, 1994)
The experiences of working women are explored in Women, Work, and Place. Tied together by the conceptual theme "place matters," the essays emphasize the social, cultural, economic, historical, and geographical contexts in which women work, and the effect of specific conditions on women's experiences. Topics include the transformation of the work force in nineteenth-century Montreal (Bettina Bradbury), feminization of skill in the British garment industry (Allison Kaye), the relationship between work and family for Japanese immigrant women in Canada (Audrey Kobayashi), experiences of women during a labour dispute in Ontario (Joy Parr), contemporary restructuring of the labour force in the United States (Susan Christopherson) and in an urban context in Montreal (Damaris Rose and Paul Villeneuve), the effect of gentrification on women's work roles (Liz Bondi), inequality in the work force (Sylvia Gold), and theoretical issues involved in understanding women in the contemporary city (Linda Peake). An introductory essay provides a review of current issues. --Publisher's description
Keywords: Stedelijke economie

As We Come Marching: People, Power & Progressive Politics - Langdon, Steven; Cross, Victoria (Windsor Works Publications, 1994)
Authors/editors Langdon and Cross show that the Canadian left has energy and ideas. They bring together activist writers fighting for a sustainable environment, for quality health care and other key public services, for a community-based economy, and for equality for women and people of colour. All are engaged in real-world work for progressive change. The contributors are organizers, community activists, those who've run provincial governments, and some of Canada's most thoughtful labour leaders. --Publisher's description
Keywords: Canada; Canada Politics and government 1980-; Canada Politics and government 1993-2006; Canada Politique et gouvernement 1993-2006; New Democratic Party; Nouveau parti démocratique; Politics and government; Since 1980; Socialism; Socialism Canada; Socialisme Canada

Workers' Control on the Railroad: A Practical Example "Right Under Your Nose" - Morgan, Richard Ernest (Lefty) (Past CCLH Publications, 1994)
The late "Lefty" Morgan, a British Columbia railway engineer, outlines his philosophy of workers' control in this fascinating volume. The volume has a scholarly introduction by University of New Brunswick anthropologist, Gail Pool, and University of Toronto PhD student in anthropology, Donna Young. They situate Lefty politically and historically and locate Lefty's work in current debates about workers' control. --Publisher's description
Keywords: British Columbia; Canadian Pacific Railway Company; Employee participation; History; Management; Management Employee participation; Morgan, Lefty; Political activists; Railroads

Working the North: Labor and the Northwest Defense Projects, 1942-1946 - Morrison, William R.; Coates, Kenneth (University of Alaska Press, 1994)
They came north like a storm surge of humanity, those wartime workers driven by the forces of World War II. Men and women, black and white, civilian and military, they outnumbered and effectively overwhelmed the largely Native population of Canada's northwest. Under harsh and unfamiliar conditions, they built what the war effort needed - airfields, roads, pipelines. Then, like a storm tide when the winds have passed, they receded from the North, leaving both the terrain and themselves forever changed. --Publisher's description
Keywords: 1900-1999; Arbeiter; Canada Canadian Northwest; Guerre mondiale, 1939-1945; Guerre mondiale, 1939-1945 Canada (Nord) Génie et construction; History; Kanada Nordwest; Northern Canada; Travailleurs Canada (Nord) Histoire 20e siècle; Travailleurs Nord-Ouest canadien Histoire 20e siècle; Weltkrieg; Working class; Working class Canada, Northern History 20th century; Working class History 20th century Northwest, Canadian; Working class Northwest, Canadian History 20th century; World War, 1939-1945; World War, 1939-1945 Canada, Northern Engineering and construction

Capitalism Comes to the Backcountry: The Goodyear Invasion of Napanee - Palmer, Bryan D. (Between the Lines, 1994)
[E]xplores the human dimensions of plant relocation, sordid corporate practices, and ultimately, the corrosive cultural effects of corporate boosterism. A vivid, hard-hitting expose of big business in a small Ontario community. --Publisher's description

Labouring Children: British Immigrant Apprentices to Canada, 1869-1924 - Parr, Joy (University of Toronto Press, 1994)
Between 1868-1924, 80,000 British children, most of them under fourteen, came to Canada to be apprenticed as labourers and domestic servents. Joy Parr's study of these children, first published in 1980, became a significant resource for courses in women's history, family history, immigration history, and labour history. Out of print for several years, Labouring Children now has a substantial new introduction in which the author examines the historiography of the history of childhood, particularly in the light of recent literature on sexuality and the post-structuralist critique. She also considers recent popular historical views of children and their relationship to professional history. Out of print for several years, Labouring Children now has a substantial new introduction in which the author examines the historiography of the history of childhood, particularly in the light of recent literature on sexuality and the post-structuralist critique.
Keywords: Indentured servants -- Canada -- History

Patriots and Proletarians: Politicizing Hungarian Immigrants in Interwar Canada - Patrias, Carmela (McGill-Queen's studies in ethnic history, 1994)
This book examines the influence of political ideology on the development of cultural identity among Hungarian immigrants in Canada during the interwar years. It traces the politicization of the Hungarian community into two rival camps - the conservative, pro-Hungarian regime camp and the radical, pro-communist camp - and shows that these differing ideologies played an integral part in the development of community institutions and group consciousness." "Hungarian immigrants' status as foreigners and their disadvantageous class position prevented them from gaining power in Canadian society, forcing them to rely almost exclusively on ideologies and institutions within their own communities to better their situation. Focusing on the social and cultural dimensions of immigrant politics, Carmela Patrias places the Hungarian situation within the larger context of immigration history. --Publisher's description
Keywords: Hungarians -- Canada -- Politics and government

Don't Call Me Servant: Government Work and Unions in Ontario, 1911-1984 - Roberts, Wayne; Upshaw, Fred; Rooney, Frank (Ontario Public Service Employees Union, 1994)
How did an association formed in 1911 for self-help and social purposes become one of the largest and strongest unions in Ontario? [This book] is the story of that transformation: a history of the evolution of government in Canada's largest province, and of the working women and men who built the Ontario Public Services Employees Union. Analysis and anecdotes are woven into a tale of workers coping with a paternalistic employer, repressive laws and internal battles. Their story is an important part of the province's labour and political heritage. --Publisher's description

Working at Inglis: The Life and Death of a Canadian Factory - Sobel, David; Meurer, Susan (Lorimer, 1994)
This book covers 108 years of labour history at the John Inglis factory in Toronto's west end. For years, the Inglis plant was at the bedrock of Canada's manufacturing economy until it was finally closed in 1989. The authors present a critical narrative that looks at union struggles to organize the plant, discusses the gendered segregation of work during WWII, and analyses the importance of Free Trade to the plant's closure. The book includes over 150 archival and contemporary photographs, drawings, and other visual materials. --Publisher's description
Keywords: Inglis Limited -- Employees -- History

AUCE & TSSU: Memoirs of a Feminist Union, 1972-1993 - Stainsby, Jill; Newcombe, Honorée; Parker-Snedker, Jacqui; Reniers, Paul (Teaching Support Staff Union Publishing, 1994)
This history of the Teaching Support Staff Union is timely since, as TSSU's parent, the Association of University and College Employees, has now existed for twenty years. TSSU is the last remaining independent local of AUCE. though several other locals have joined mainstream unions. The three essays included describe three different eras in the history of AUCE and TSSU, but some of the tensions found in the organization have remained the same over time. For twenty years AUCE has represented, at least to the activists involved in it, an intersection between feminism and trade unionism in British Columbia. Because the principle of local control over union decisions rather than joining a larger union hierarchy has been consistently maintained, AUCE and TSSU have frequently operated from a locally-defined idealistic feminist standpoint. The tensions, broadly painted, have been between feminists and traditional trade unionists (most often male).... --Introduction
Keywords: Association of University and College Employees Histoire; Association of University and College Employees History; British Columbia; Employees; Femmes dans les syndicats Colombie-Britannique; History; Labor unions British Columbia College employees; Simon Fraser University; Simon Fraser University Employees; Simon Fraser University Personnel; Syndicats Universités Personnel Colombie-Britannique; Teaching Support Staff Union Histoire; Teaching Support Staff Union History; Women labor union members; Women labor union members British Columbia

My Past is Now: Further Memoirs of a Labour Lawyer - Stanton, John (Past CCLH Publications, 1994)
In this further volume of autobiography, BC labour and human rights lawyer John Stanton returns to his career in the law. After reviewing his childhood, education, and early political experiences in Vancouver during the Depression years, he discusses some of his most important cases. These include: the defence of Fergus McKean, a BC communist leader who was interned during World War II; an exceptional criminal libel suit prosecution in Cold War BC; and an account of his relations with the Mine Mill and Smelter Workers. --Publisher's description
Keywords: Depression; Education; History; Human rights; Labor laws and legislation; Labour; Lawyer; Lawyers; Mining, Oil, and Gas; Politics; Working class

Labour's Dilemma: The Gender Politics of Auto Workers in Canada, 1937-79 - Sugiman, Pamela H. (University of Toronto Press, 1994)
The growth of the United Auto Workers in Canada dramatically improved the lives of thousands of workers. Not only did it achieve impressive bargaining gains, but the UAW was regarded as one of the most democratic and socially progressive of the major industrial unions in North America. However, workers in the automotive sector, who constituted the largest segment of the UAW membership, witnessed blatant gender inequalities. From 1937 to 1979, UAW leaders did little to challenge these inequalities. Both the union and the workplace remained highly masculine settings in which male workers and bosses played out the gender politics of the times. Pamela Sugiman draws on archival materials and in-depth interviews with workers and union representatives to explore the ways in which the small groups of women in southern Ontario auto plants fought for dignity, respect, and rights within this restrictive context. During the Second World War, women auto workers formed close bonds with one another - bonds that rested largely around their identification as a sex. By the late 1960s, they were drawing on a growing union consciousness, the modern women's movement, and their gender identity, to launch an organized collective struggle for sexual equality. In describing the women's experiences, Sugiman employs the concept of a `gendered strategy.' A gendered strategy incorporates both reasoned decisions and emotional responses, calculated interests and compromises. Within a context of gender and class divisions, workers developed strategies of coping, resistance, and control. Labour's Dilemma reveals how people may be simultaneously agents and victims, compliant and resistant. --Publisher's description

Work: The Sociology of Work in Canada: Papers in Honour of Oswald Hall - Wipper, Audrey (Carleton library series, 1994)
A revised edition of Sociology of Work, this edition features the sociological relationships between English and French Canadians, taking into account the rapidity of social change that has occurred in Quebec and throughout Canada. --Publisher's description

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Canadian social history series, 1993)
Working Families takes the reader onto the streets of Montreal and into the homes of its working-class families during the years that it became a major, industrial city. Between the 1860s and 1890s the expansion of wage labour changed the bases of family survival. It offered new possibilities and created new points of tension within the families of the emerging working class. Here we meet the men, youth, and children who worked for wages. We see the women who stayed home with their young, cooked and sewed, planted gardens and tended animals, stretching their often meagre family wages into goods and services for survival. We also see the ingenuity and agony of women whose husbands lost their jobs, fell ill, drank up their wages, deserted their families, or died. Working Families explores the complex variety of responses of working-class families to their new lives within industrial capitalist society, and offers new ways of looking at the industrial revolution in Canada. --Publisher's description

Death on the Ice: The Great Newfoundland Sealing Disaster of 1914 - Brown, Cassie; Horwood, Harold (Doubleday Canada, 1993)
Each year, for generations, poor, ill-clad Newfoundland fishermen sailed out "to the ice" to hunt seals in the hope of a few pennies in wages from the prosperous merchants of St. John's. The year 1914 witnessed the worst in a long line of tragedies that were part of their way of life. For two long days and freezing nights a party of seal hunters - one hundred thirty-two men - were left stranded on a ice field floating in the North Atlantic in winter. They were thinly dressed, with almost no food, and with no hope of shelter on the ice against the snow or the constant, bitter winds. To survive, they had to keep moving, always moving. Those who lay down to rest died.... Publisher's description
Keywords: 1900-1999; Blizzards; Blizzards Newfoundland and Labrador; History; Newfoundland Sealing Disaster, Newfoundland and Labrador, 1914; Newfoundland and Labrador; Phoques Chasse Terre-Neuve-et-Labrador Histoire 20e siècle; Sealing; Sealing Newfoundland and Labrador History 20th century; Tempêtes de neige Terre-Neuve-et-Labrador

Recasting Steel Labour: The Stelco Story - Corman, June; Luxton, Meg; Livingstone, D.W. (David W.) (Fernwood Publishing, 1993)
This is a local study of steelworkers employed at, or aid off from, Stelco’s Hilton Works in Hamilton, Ontario. This local study has been situated in the context of the global restructuring of capitalism. The authors content that more than ever before the dynamics of the whole world economy limit and shape the actions of its past - a process referred to as “globalizing the local.” Restructuring is taking place in response to global demands. As the global net tighten, local regions and industry have less and less autonomy for independent development. Stelco is best conceived as a sit of the worldwide process of capital accumulation. How has this restructuring impacted on local regions and local worked? This question is the focus of this book, often answered in workers’ and management’s own words. --Publisher's description
Keywords: Iron and steel workers Ontario Hamilton; Steel industry and trade Ontario Hamilton Employees; Stelco Inc

Regulating Class Privilege: Immigrant Servants in Canada, 1940s-1990s - Daenzer, Patricia M. (Canadian Scholars' Press, 1993)
During the five decades of the transformation of the policies which regulated the importation and placement of immigrant women into household service work, the policy was variously regulated by internal procedures, policy statement, and operational guidelines. This book examines these changes with a focus on understanding how bureaucracy such as Employment and Immigration Canada contributes, through its mandate, to shaping social relationships in the Canadian labour force and society. --Publisher's description
Keywords: 1900-1999; Canada; Canadá; Einwanderin; Employées de maison Politique gouvernementale Canada Histoire; Employées de maison Politique gouvernementale Canada Histoire 20e siècle; Foreign workers Government policy; Foreign workers Government policy Canada History; Geschichte 1940-1990; Hausgehilfin; History; Immigrantes Politique gouvernementale Canada Histoire; Immigrantes Politique gouvernementale Canada Histoire 20e siècle; Kanada; Travailleurs étrangers Politique gouvernementale Canada Histoire; Travailleuses étrangères Politique gouvernementale Canada Histoire 20e siècle; Women foreign workers Government policy Canada History 20th century; Women household employees Government policy Canada History; Women household employees Government policy Canada History 20th century; Women immigrants Government policy; Women immigrants Government policy Canada History; Women immigrants Government policy Canada History 20th century; bibliografía; bibliographie; bibliography; cuadros estadísticos; derechos de los trabajadores; domestic worker; droits des travailleurs; employment policy; employment status; employé de maison; exclusion sociale; exclusión social; graph; graphique; gráfico; migrant workers; migration policy; politique de l'emploi; politique migratoire; política de empleo; política migratoria; protección social; protection sociale; situación ocupacional; social exclusion; social protection; statistical table; statut dans l'emploi; tableau statistique; tendance; tendencia; trabajador doméstico; trabajador migrante; trabajadoras; travailleur migrant; travailleuses; trend; women workers; workers rights

Improper Advances: Rape and Heterosexual Conflict in Ontario, 1880-1929 - Dubinsky, Karen (Chicago Series on Sexuality, History, and Society, 1993)
Why do men rape women? This is a question for which there are many political, psychological, and sociological answers, but few historical ones. Improper Advances is one of the first books to explore the history of sexual violence in any country. A study of women, men, and sexual crime in rural and northern Ontario, it expands the terms of current debates about sexuality and sexual violence. --Publisher's description
Keywords: Rape -- Ontario -- History

The Patriots and the People: The Rebellion of 1837 in Rural Lower Canada - Greer, Allan (Social history of Canada, 1993)
The Lower Canadian Rebellion of 1837 has been called the most important event in pre-Confederation history. Previously, it has been explained as a response to economic distress or as the result of manipulation by middle-class politicians. Lord Durham believed it was an expression of racial conflict. The Patriots and the People is a fundamental reinterpretation of the Rebellion. Allan Greer argues that far being passive victims of events, the habitants were actively responding to democratic appeals because the language of popular sovereignty was in harmony with their experience and outlook. He finds that a certain form of popular republicanism, with roots deep in the French-Canadian past, drove the anti-government campaign. Institutions such as the militia and the parish played an important part in giving shape to the movement, and the customs of the maypole and charivari provided models for the collective actions against local representatives of the colonial regime. In looking closely into the actions, motives, and mentality of the rural plebeians who formed a majority of those involved in the insurrection, Allan Greer brings to light new causes for the revolutionary role of the normally peaceful French-Canadian peasant. By doing so he provides a social history with new dimensions. --Publisher's description
Keywords: 1837-1838; Aufstand; Canada; Canada Histoire 1837-1838 (Rébellion); Canada History Rebellion, 1837-1838; Geschichte 1837-1838; Habitants Political activity Quebec(Province); History; Opstanden; Québec; Québec (Provinz) Aufstand (1837-1838); Québec Aufstand; Rebellions History

Such Hardworking People: Italian Immigrants in Postwar Toronto - Iacovetta, Franca (McGill-Queen's studies in ethnic history, 1993)
During the last century, 26 million Italian women, men, and children have traded an uncertain future in Italy for the prospect of a better life elsewhere. Canada has long been home to Italian immigrants, but in the years just after the Second World War they began to arrive in multitudes. Toronto emerged as the most popular Canadian destination and now, with more than 400,000 residents of Italian heritage, has one of the largest Italian populations outside Italy. Franca Iacovetta describes the working-class experiences of those who came to Toronto from southern Italy between 1946 and 1965, focusing on the relations between newly arrived immigrant workers and their families." "The Italians who came to Toronto before 1965 were predominantly young, healthy women and men eager to secure jobs and prepared to make sacrifices in order to secure a more comfortable life for themselves and their children. Franca Iacovetta examines the changes many of them had to face during the transition from peasant worker in an under-developed, rural economy to wage-earner in an urban, industrial society." "Although both women and men had to struggle and were exploited, Iacovetta shows that they found innovative ways to recreate cherished rituals and customs from their homeland and to derive a sense of dignity and honour from the labours they performed." "Such Hardworking People is informed by a feminist analysis. Iacovetta shows that for both sexes work patterns and experiences, as well as self-perceptions, were influenced by domestic responsibilities and gender relations within the household and by the labour market, employer strategies, and kin-linked networks of support. In addition to conducting numerous interviews with some of the immigrants, she has drawn on recent scholarship in immigration, family, labour studies, oral history, and women's history. --Publisher's description
Keywords: Canadiens d'origine italienne Ontario Toronto Conditions sociales; Foreign workers, Italian; Foreign workers, Italian Ontario Toronto; Immigrants Ontario Toronto Conditions sociales; Immigrants Ontario Toronto Social conditions; Immigrants Social conditions; Italian Canadians Ontario Toronto Social conditions; Italians Ontario Toronto Social conditions; Italians Social conditions; Italiens Ontario Toronto Conditions sociales; Ontario Toronto; Travailleurs étrangers italiens Ontario Toronto

Gender Conflicts: New Essays in Women's History - Iacovetta, Franca; Valverde, Mariana (Social history of Canada, 1993)
In the early 1970s, when women's history began to claim attention as an emerging discipline in North American universities, it was dominated by a middle-class Anglo-Saxon bias. Today the field is much more diverse, a development reflected in the scope of this volume. Rather than documenting the experiences of women solely in a framework of gender analysis, its authors recognize the interaction of race, class, and gender as central in shaping women's lives, and men's. These essays represent an exciting breakthrough in women's studies, expanding the borders of the discipline while breaking down barriers between mainstream and women's history. --Publisher's description. Contents: When the mother of the race is free': Race, reproduction, and sexuality in first-wave feminism / Mariana Valverde -- Maidenly girls' or 'designing women'? The crime of seduction in turn-of-the-century Ontario / Karen Dubinsky -- The 'hallelujah lasses': Working-class women in the Salvation Army in English Canada, 1882-92 / Lynne Marks -- The alchemy of politicization: Socialist women and the early Canadian left / Janice Newton -- Wounded womanhood and dead men: Chivalry and the trials of Clara Ford and Carrie Davies / Carolyn Strange -- Class, ethnicity, and gender in the Eaton strikes of 1912 and 1934 / Ruth A. Frager -- 'Feminine trifles of vast importance': Writing gender into the history of consumption / Cynthia Wright -- Making 'new Canadians': Social workers, women, and the reshaping of immigrant families / Franco Iacovetta.

The Depression Years, 1933-1934 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1993)
This volume completes the series of Royal Canadian Mounted Police Security Bulletins for late 1933 and 1934. It begins a new series on the Depression years. These Bulletins allow us to see not only the nature of RCMP Security concerns but also the underlying ideology of the Security Service. The volume also contains a critical introduction by Gregory S. Kealey. --Publisher's description
Keywords: Canada; Communism; History; Internal security; RCMP; Royal Canadian Mounted Police (RCMP); Subversive activities

The Depression Years, 1935 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1993)
This volume documents the Royal Canadian Mounted Police's surveillance activities during 1935 and contains informants', agents', and operatives' perspectives on developments within the Communist Party of Canada on labour unions, and on unemployed organizations. It includes coverage of the 1935 federal election, the successes of red unions, and the development of popular front strategies. The introduction by historian John Manley provides a considered overview of the events. The volume is fully indexed. --Publisher's description
Keywords: Canada; Communism; History; Internal security; Royal Canadian Mounted Police (RCMP); Subversive activities

The Depression Years, 1936 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1993)
This volume is a continuation of the Royal Canadian Mounted Police Security Bulletins series on the Depression. The RCMP Security Service reported in these Bulletins on security and intelligence matters to Cabinet and other government officals. Those for 1936 contain much material on labour and the left. --Publisher's description
Keywords: Canada; Communism; History; Internal security; ROYAL Canadian Mounted Police; Subversive activities

The Depression Years, 1937 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1993)
These Bulletins show that the Royal Canadian Mounted Police's continued fascination with the Communist Party of Canada (CPC) was broadened to include the Committee for Industrial Organization (CIO) in 1937. The RCMP believed the CPC's fingerprints were all over the CIO. Other topics examined in the bulletins include reports on the Spanish Civil War, municipal elections, ethnic newspapers and strikes. --Publisher's description
Keywords: Canada; Communism; History; Internal security; Royal Canadian Mounted Police (RCMP); Subversive activities

The Depression Years, 1938-39 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1993)
This volume completes the Depression Years Series and, for the time being, our publication of the Royal Canadian Mounted Police Bulletins, John Manley examines the RCMP fascination with the CPC and how the CPC coped with the Popular Front and the Nazi-Soviet pact. Manley concludes that the CPC's anti-war line was a disaster, claiming that "undoubtedly..., the Comintern was the RCMP's best friend"(29) --Publisher's description
Keywords: Canada; Communism; History; Internal security; Royal Canadian Mounted Police (RCMP); Subversive activities

The War Series, Part 2, 1942-1945 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1993)
This volume completes the series of Royal Canadian Mounted Police Security Bulletins for World War II, following on the War Series, Vol. 1, 1939-1941. These Bulletins allow us to see not only the nature of RCMP Security concerns but also the underlying ideology of the Security Service. The volume also contains a critical introduction by the editors. --Publisher's description
Keywords: Canada; Communism; History; Royal Canadian Mounted Police (RCMP); War

Canada Made Me - Levine, Norman (Porcupine's Quill, 1993)
First published in England in 1958, this book is a bitter, critical reassessment of the moral and cultural values of Canada. Levine's account of his three-month journey from Halifax to Ucluelet, a fishing village on the west coast, is an unconventional portrait of Canada's underbelly. The book ends with the words: `I wondered why I felt so bitter about Canada. After all, it was all part of a dream, an experiment that could not come off. It was foolish to believe that you can take the throwouts, the rejects, the human kickabouts from Europe and tell them: Here you have a second chance. Here you can start a new life. But no one ever mentioned the price one had to pay; how much of oneself you had to betray.' Canada Made Me was regarded as so controversial that it did not appear in a Canadian edition until 1979. Critical opinion, however, has slowly swung around to the point the book was recently described in the Globe and Mail as a `laconic classic'. For this new edition Norman Levine has written an introduction which traces the book's publishing history and reputation.
Keywords: Blue-collar work; Class Consciousness; Immigrants; Miners; Social Class and Equality

The Political Economy of North American Indians - Moore, John H. (University of Oklahoma Press, 1993)
This innovative collection of articles approaches American Indian history and culture from a Marxist perspective. The contributors, from the United States and Canada, have jumped the boundaries among the social sciences to consider issues of macroeconomics and intercultural conflict. The result is a stimulating and substantial contribution that will interest any reader concerned with policy affecting North American Indians. The contributors are particularly attentive to process and change. They show the relationships among the historical periods characterized by the fur trade, land cessions, and the reservation education system. They expose the collusion among agencies of the dominant society and how Indian people reacted, reorganizing themselves and their institutions to face every new, changed situation. --Publisher's description
Keywords: Anthropologie économique Grandes Plaines; BUSINESS & ECONOMICS Economic Conditions; BUSINESS & ECONOMICS Economic History; BUSINESS & ECONOMICS Economics Comparative; Economic anthropology; Economic anthropology Great Plains; Economic history; Grandes Plaines Conditions économiques; Great Plains; Great Plains Economic conditions; History; Indians of North America; Indians of North America Economic conditions; Indians of North America Great Plains Economic conditions; Indians of North America Great Plains History; Indians of North America Great Plains Politics and government; Indians of North America Politics and government; Indiens d'Amérique Grandes Plaines Conditions économiques; Indiens d'Amérique Grandes Plaines Histoire; POLITICAL SCIENCE Economic Conditions; Subsistence economy; Subsistence economy Great Plains; Économie de subsistance Grandes Plaines

Tangled Webs of History: Indians and the Law in Canada's Pacific Coast Fisheries - Newell, Dianne (University of Toronto Press, 1993)
Fishing rights are one of the major areas of dispute for aboriginals in Canada today. Dianne Newell explores this controversial issue and looks at the ways government regulatory policy and the law have affected Indian participation in the Pacific Coast fisheries." "For centuries, the economies of Pacific Coast Indians were based on their fisheries. Marine resources, mainly salmon, were used for barter, trade, ceremony, and personal consumption. This pattern persisted after the arrival of European and Asian immigrants, even during the first phases of the non-Indian commercial fishing industry when Indian families were depended upon for their labour and expertise. But as the industrial fishery grew, changes in labour supply, markets, and technology rendered Pacific Coast Indians less central to the enterprise and the aboriginal fishery became legally defined as food fishing. By the late 1960s, rigid new licence-limitation policies were introduced and regulations transformed the processing sector." "The result was reduced participation for fishers and shoreworkers, and the opportunities for Indian men and women declined dramatically. Government programs to increase or even stabilize Indian participation ultimately failed. Newell concludes that the governments of Canada and British Columbia have historically regarded the aboriginal fishery narrowly and unjustly as a privilege, not a right, and have in fact moved against any changes that might put Indians into competition with non-Indians. Recently, BC Indians won a Supreme Court victory in Regina v. Sparrow (1990) that will make it easier to change federal fisheries policies, but aboriginal fishing rights remain before the courts and under federal government investigation. --Publisher's description
Keywords: British Columbia; Fisheries British Columbia History; Fishery law and legislation; Fishery law and legislation British Columbia History; Fishing Law; History; Indians of North America Fishing Law and legislation; Indians of North America Fishing Law and legislation British Columbia; Indiens Amérique du Nord Colombie-Britannique Pêche Droit Histoire; Indiens Pêche Droit Canada Colombie-Britannique Législation; Iwi taketake; Pêches Droit Canada Colombie-Britannique Histoire; Salmon canning industry; Salmon canning industry British Columbia History; Salmon fisheries Law and legislation; Salmon fisheries Law and legislation British Columbia; Salmon fisheries Law and legislation British Columbia History; Saumon en conserve Industrie Colombie-Britannique Histoire; Saumons Pêche commerciale Droit Canada Colombie-Britannique Législation; Saumons Pêche commerciale Droit Colombie-Britannique Histoire

Riots in New Brunswick: Orange Nativism and Social Violence in the 1840s - See, Scott W. (Social history of Canada, 1993)
During the mid to late 1840s, dramatic riots shook the communities of Woodstock, Fredericton, and Saint John. Irish-Catholic immigrants fought Protestant Orangemen, with fists, club, and firearms. The violence resulted in death and destruction unprecedented in the British North American colonies. This book is the first serious historical treatment of the bloody riots and the tangled events that led to them. Scott See shows mid-century New Brunswick roughly awakened from the slumbering provincialism of its post-Loyalist phase by the stirrings of capitalism and by the tidal wave of Irish immigration that followed the potato famine. His main focus is the Loyal Orange Order, the anti-Catholic organization that clashed with the immigrants, many of them impoverished exiles. See presents an extraordinary profile of the Orange Order and concludes provocatively that it was a nativist organization similar to the xenophobic groups active at the time in the United States. Unlike other recent works on the Order, his book emphasizes the importance of the organization's specifically North American concerns, and questions the significance of its connections to Old World sectarianism. --Publisher's description
Keywords: 1800-1899; Canada, New Brunswick History; Canada, New Brunswick Minorities; Catholics; Catholics New Brunswick; Catholics New Brunswick History 19th century; Catholics New Jersey New Brunswick 19th century; Catholiques Nouveau-Brunswick Histoire 19e siècle; Electronic books; Geschichte 1840-1850; History; Irish; Irish New Brunswick; Irish New Brunswick History 19th century; Irish New Jersey New Brunswick 19th century; Irlandais Nouveau-Brunswick Histoire 19e siècle; Mouvements nativistes États-Unis; Nativism; New Brunswick; New Brunswick (N.J.) Social conditions 19th century; New Brunswick Social conditions 19th century; Nouveau-Brunswick Conditions sociales 19e siècle; Orangemen; Orangemen New Brunswick; Orangemen New Brunswick History 19th century; Orangemen New Jersey New Brunswick 19th century; Orangistes (Protestants) Nouveau-Brunswick Histoire 19e siècle; Orangistes Nouveau-Brunswick Histoire 19e siècle; Riots; Riots History; Riots New Brunswick History 19th century; Riots New Jersey New Brunswick 19th century; Social conditions; Unruhen; Émeutes Nouveau-Brunswick Histoire 19e siècle

The New Day Recalled: Lives of Girls and Women in English Canada, 1919-1939 - Strong-Boag, Veronica (Copp Clark Pitman, 1993)
Suffragists predicated that women's participation in politics would reform society and lead to a new day for Canadian women. In this highly original and important book, Veronica Strong-Boag examines the lives of girls and women in the post-suffrage decades and argues that the new day did not dawn quite as expected. The author traces the life courses of women in English Canada in the interwar years. Six richly detailed chapters on childhood, paid work, courtship and marriage, domestic work, motherhood, and aging capture the essence of what it meant to be a female in Canada between the wars. --Publisher's description
Keywords: 1900-1999; Canada; Canadians, English-speaking Social conditions; Canadiens anglais Conditions sociales; Femmes Canada Conditions sociales; Femmes Canada Histoire 20e siècle; Filles Canada Conditions sociales; Filles Canada Histoire 20e siècle; Girls; Girls Canada History 20th century; Girls Canada Social conditions; Girls Social conditions; History; Women; Women Canada History 20th century; Women Canada Social conditions; Women Social conditions

Wedded to the Cause: Ukrainian-Canadian Women and Ethnic Identity, 1891-1991 - Swyripa, Frances (Heritage, 1993)
Frances Swyripe here presents the interpretive study of women of Ukrainian origin in Canada. She analyses the images and myths that have grown up around them, why they arose, and how they were used by the leaders of the community. Swyripa argues that ethnicity combined with gender to shape the experience of Ukrainian-Canadian women, as statelessness and national oppression in the homeland joined with a negative group stereotype and minority status in emigration to influence women's roles and options. She explores community attitudes towards the peasant immigrant pioneer, towards her daughters exposed to the opportunities, prejudice, and assimilatory pressure of the Anglo-Canadian world, towards the 'Great Women' evoked as models and sources of inspiration, and towards the familiar baba. In these stereotypes of the female figure, and in the activities of women's organizations, the community played out its many tensions: between a strong attachment to canada and an equally strong attachment to Ukraine; between nationalists who sought to liberate Ukraine from Polish and Soviet rule and progressives who saw themselves as part of an international proletariat; between women's responsibilities as mothers and homemakers and their obligation to participate in both Canadian and community life. Swyripa finds that the concerns of community leaders did not always coincide with those of the grassroots. The differences were best expressed in the evolution of the peasant immigrant pioneer woman as a group symbol, where the tensions between a cultural ethnic consciousness and a politicized national consciousness as the core of Ukrainian-Canadian identity were played out in the female figure. --Publisher's description
Keywords: Ukrainian-Canadian women -- History

Fellow Worker: The Life of Fred Thompson - Thompson, Fred (First person series, 1993)
The autobiography of Fred W. Thompson - socialist, Wobbly, organizer, soapboxer, editor, class-war prisoner, educator, historian, and publisher. This book is an important contribution to the understanding of working-class radicalism in twentieth-century North America. --Website description
Keywords: Biographies; Industrial Workers of the World; Thompson, Fred, 1900-1987; Travailleurs États-Unis Biographies; United States; Working class; Working class United States Biography

Sisters and Solidarity: Women and Unions in Canada - White, Julie (Thompson Educational, 1993)
Sisters & Solidarity provides a clear and well-researched overview of the position of women in relation to the labour movement across Canada. After surveying the development of the labour movement at the turn of the century, the author traces the increasing influence of women members in the Canadian labour movement. Sisters & Solidarity considers not only what unions have negotiated with employers, but the position of women inside the union movement itself. Based on interviews with unions and labour centrals across the country, Julie White examines the representation of women in union executives, committees, conventions and staff. She describes the development of women's committees and examines the responses of unions to demands for change concerning family responsibilities, harassment, and union education. Using new data the author analyzes who are the unorganized, where they work, and why it is difficult to organize them. Three case studies examine the attempts to unionize homeworkers and cleaners and new labour relations legislation in Ontario. Sisters & Solidarity also considers the position of racial minorities, disabled persons and gays and lesbians in the Canadian union movement and the steps unions and labour centrals have taken to meet the needs of these workers. --Publisher's description
Keywords: Canada; History; Minority labor union members; WOMEN labor union members

From Plant to Politics: The Autoworkers Union in Postwar Canada - Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Temple University Press, 1993)
In the wake of the continuing recession and destabilized global economy, theorizing about the industrial peace that reigned after World War II through the 1970s has undergone considerable revision. In this path-breaking discussion of Canadian labor relations, Charlotte Yates shows how the state-centered European theories of political economy did not fit the Canadian and United States experiences and treated them as anomalies. Through a case study of the Autoworkers Union in Canada (a branch of the UAW until 1984), Yates subjects this theorizing to critical scrutiny. Using extensive archives of union political activities, Yates describes how unions were demobilized in their relationships with the state, employers, and political parties as Fordist regulatory structures and practices forced unions to accept the constraints of responsible union behavior. She argues that the Canadian Autoworkers' collective identity and internal organizational structure counteracted these demobilizing tendencies. This historical legacy laid the groundwork for the Autoworker Union's return to militancy in the 1980s and 1990s and has shaped its responses to the pressures of economic globalization and heightened competition. From Plant to Politics demonstrates how continued union militancy in resisting concessions from employers and other attacks on unions has placed the union in a position of strength from which it now hopes to negotiate the Canadian path to a restructured economy. This study of the internal dynamics of a major union contributes to an understanding of unions as complex organizations engaged in strategic activities that have a definite impact on the national political economy. --Publisher's description

Ole Boy: [Memoirs of Labour Leader J.K. Bell] - Calhoun, Sue (Nimbus, 1992)
J.K. Bell was one of the finest labour leaders of his time. Born in Halifax, Nova Scotia at the turn of the century, Jimmy Bell headed down the proverbial road to Toronto to find work as the depression years began. When war broke out, he returned to Saint John, New Brunswick and went to work at the dry dock where he founded a local of what would become the Maritime Marine Workers' Federation. For many years, Bell was ostracized by the labour movement because of his leftwing views. As the Cold War whipped the country into hysteria, Bell was "purged" from the provincial labour federation in 1949, and didn't succeed in being re-elected until 1965. Nonetheless, he managed to play a key role, and in this book, he remembers the events and recalls the characters with fondness and humour. --Publisher's description
Keywords: Bell, J. K. (James Koval); Biography; Nova Scotia; Officials and employees; Trade unions

Industrial Relations in Canadian Industry - Chaykowski, Richard P.; Verma, Anil (Dryden, 1992)
Contents: Adjustment and restructuring in Canadian industrial relations: challenges to the traditional system / Richard P. Chaykowski and Anil Verma -- Industrial relations in the Canadian automobile industry / Pradeep Kumar and Noah M. Meltz -- Industrial relations in the Canadian steel industry / Anil Verma and Peter Warrian -- Industrial relations in the Canadian mining industry: transition under pressure / Richard P. Chaykowski -- Industrial relations in the construction industry in the 1980s / Joseph B. Rose -- Industrial relations in the clothing industry: struggle for survival / Michael Grant -- Industrial relations in the Canadian textile industry / Terry Thomason, Harris L. Zwerling, and Pankaj Chandra -- Restraint, privatization, and Industrial relations in the public sector in the 1980s / Mark Thompson and Allen Ponak -- Industrial relations in elementary and secondary education: a system transformed? / Bryan M. Downie -- Canada's airlines: recent turbulence and changing flight plans / E.G. Fisher and Alex Kondra -- Industrial relations in the Canadian telephone industry / Anil Verma and Joseph M. Weiler -- Canadian industrial relations in transition / Richard P. Chaykowski and Anil Verma
Keywords: Geschichte

The Changing Workplace: Reshaping Canada's Industrial Relations System - Drache, Daniel; Glasbeek, Harry (Lorimer, 1992)
This book describes how business, labour and government have organized the production of goods and services in Canada since 1945. Daniel Drache and Harry Glasbeek focus on the industrial relations system and how it works. They call for fresh thinking on the economy and offer proposals for the reorganization of production. --Publisher's description

Louis Laberge : le syndicalisme c'est ma vie - Fournier, Louis (Montreal : Quebec/Amerique, 1992)
La vie d'un homme qui incarne la force d'une petite idée toute simple: la solidarité. Une histoire racontée avec l'aide de "Ti-Louis" (des heures d'entretiens) et de témoignages d'une soixantaine de syndicalistes, patrons et hommes politiques qui l'ont bien connu. -- Résumé de l'éditeur
Keywords: Labor leaders -- Québec (Province) -- Biography

Sweatshop Strife: Class, Ethnicity, and Gender in the Jewish Labour Movement of Toronto, 1900-1939 - Frager, Ruth A. (Social history of Canada, 1992)
In the first half of the twentieth century, many of Toronto's immigrant Jews eked out a living in the needle-trade sweatshops of Spadina Avenue. In response to their expliotation on the shop floor, immigrant Jewish garment workers built one of the most advanced sections of the Canadian and American labour movements. Much more than a collective bargaining agency, Toronto's Jewish labour movement had a distinctly socialist orientation and grew out of a vibrant Jewish working-class culture. Ruth Frager examines the development of this unique movement, its sources of strength, and its limitations, focusing particularly on the complex interplay of class, ethnic, and gender interests and identities in the history of the movement. She examines the relationships between Jewish workers and Jewish manufacturers as well as relations between Jewish and non-Jewish workers and male and female workers in the city's clothing industry. In its prime, Toronto's Jewish labour movement struggled not only to improve hard sweatshop condistions but also to bring about a fundamental socialist transformation. It was an uphill battle. Drastic economic downturns, hard employer offensives, and state repressions all worked against unionists' workplace demands. Ethnic, gender, and ideological divisions weakened the movement and were manipulated by employers and their allies. Drawing on her knowledge of Yiddish, Frager has been able to gain access to original records that shed new light on an important chapter in Canadian ethnic, labour, and women's history. --Publisher's description
Keywords: History; Jewish labor unions; Jews; Labor movement; Ontario Toronto; WOMEN in the labor movement

La révolte des traîneux de pieds: histoire du syndicat des employé(e)s de magasins et de bureaux de la SAQ. - Godin, Pierre (Editions du Boréal, 1992)
Le syndicat des employé(e)s de magasins et de bureaux de la SAQ a organisé la première grève dans le secteur public. Pierre Godin rend hommage à ce syndicat d'avant-garde en commémorant son évolution. --Résumé de l'éditeur

The Struggle for Social Justice in British Columbia: Helena Gutteridge, the Unknown Reformer - Howard, Irene (UBC Press, 1992)
Helena Gutteridge was a socialist and feminist whose vision helped to shape social reform legislation in British Columbia in the first decades of the twentieth century, and also one of the first women there to hold high public office." "She was born in England in 1879. A militant suffragist, tutored by the Pankhursts, she learned the politics of confrontation early. Emigrating to Vancouver in 1911, she found the suffrage movement there too polite and organized the BC Woman's Suffrage League to help working women fight for the vote. And she kept on organizing. As a journeyman tailor she was a power in her union local, and as the only woman on the Vancouver Trades and Labor Council - their 'rebel girl' - she championed the rights of workers and organized women to fight for themselves. In the 1930s, as a member of the feisty new political movement, the Co-operative Commonwealth Federation, she joined in the struggles of the unemployed for work and wages. Then, in 1937, as the first woman ever elected to Vancouver City Council, she led the fight for low-income housing." "As was typical for women of her class and time, Helena did not keep personal records, nor did organizational records exist to any extent. Irene Howard made it her task, over a period of years, to search out and assemble details of Helena's life and career, and to interview old comrades who knew Helena and the turbulent times in which she lived. Herself a miner's daughter, the author brings to her subject an affectionate regard and sympathy qualified by the larger view of the scholar and researcher. The result is a lively biography, shot through with humour and pathos, that pays homage to Helena Gutteridge and to many of the people who have been inspired by a cause and who have taught us about the politics of caring."--Publisher's description
Keywords: Biografie; Biographies; British Columbia; Feminists; Feminists British Columbia Biography; Femmes Activité politique Colombie-Britannique (Canada) Biographies; Femmes Activité politique Colombie-Britannique Biographies; Femmes en politique Colombie-Britannique Biographies; Femmes socialistes Colombie-Britannique Biographies; Femmes sociologues Colombie-Britannique (Canada) Biographies; Femmes sociologues Colombie-Britannique Biographies; Féministes Colombie-Britannique (Canada) Biographies; Féministes Colombie-Britannique Biographies; Gutteridge, Helena; Gutteridge, Helena 1879-1960; Gutteridge, Helena, (1860-1979); Gutteridge, Helena, 1879-1960; History; Labor unions; Labor unions British Columbia History; Labor unions Officials and employees; Labor unions Officials and employees British Columbia Biography; Syndicalistes Colombie-Britannique (Canada) Biographies; Syndicats Colombie-Britannique Fonctionnaires Biographies; Syndicats Colombie-Britannique Histoire; Women Political activity; Women Political activity British Columbia Biography; Women in politics British Columbia Biography; Women socialists; Women socialists British Columbia Biography; Women sociologists; Women sociologists British Columbia Biography

Not Working: State, Unemployment and Neo-Conservatism in Canada - McBride, Stephen (State and economic life, 1992)
Unemployment is once again a pernicious and growing fact of life in Canada. Stephen McBride rejects economic interpretations of the return of high unemployment after decades in which Canada enjoyed almost full employment. He argues that the phenomenon can best be understood as the product of a political choice by policy makers - a choice which can plausibly be linked to the preferences and growing power of Canadian business in the post-1975 period. This argument is based on an evaluation of the implications of the monetarist economic paradigm whose influence in the late 1970s, a comparative survey of the policy strategies followed in other countries and the employment outcomes associated with them, and a systematic examination of Canadian public policy in the macroeconomic, labour market, unemployment insurance, and industrial relations areas. McBride's analysis reveals the state's increasing emphasis on addressing the accumulation demands of capital and decreasing emphasis on the provision of concrete benefits (such as full employment and social services) to citizens. Much state activity can be understood as an attempt to legitimate by ideological change the means the change in the state's priorities and the shifting balance of benefits conferred by public policy. Thus the Canadian state has played an important role in managing the return to a high unemployment regime. --Publisher's description
Keywords: Arbeitslosigkeit; Arbeitsmarktpolitik; Canada; Chômage Politique gouvernementale Canada; Conservatism; Conservatism Canada; Conservatisme Canada; Kanada; Konservativismus; Labor policy; Labor policy Canada; Travail Politique gouvernementale Canada; Unemployment Government policy; Unemployment Government policy Canada

Working Class Experience: Rethinking the History of Canadian Labour, 1800-1991 - Palmer, Bryan D. (McClelland & Stewart, 1992)
Working Class Experience is a sweeping and sympathetic study of the development of the Canadian working class since 1800. Beginning with a substantial and provocative introduction that discusses the historiography of the Canadian working class, the book goes on to establish a general framework for analysis of what ultimately is a social history of Canada. Dividing the years into seven periods in the evolution of class struggle, it beings each chapter with an assessment of that period's prevailing economic and social context, followed by an examination of the many factors affecting the working class during that period. Written in a colourful and sometimes irreverent style, Working Class Experience focuses on the processes by which working people moved, and were moved, off the land and into the factories and other workplaces during the Industrial and post-Industrial Revolutions in Canada. Drawing on much recent work on contemporary capitalism, Working Class Experience offers a significant explanation of the malaise in current labour and management relations and speculates on its significance for progressive change in Canadian Life. --Publisher's description

Coal in Our Blood: 200 Years of Coal Mining in Nova Scotia's Pictou County - Ryan, Judith Hoegg; Weary, Dale J; Weary, Robert K (Formac, 1992)
This social history of coal mining in Nova Scotia's Pictou County offers a unique portrait of a long-established working-class community.There are detailed accounts of the changing work-life of miners told in the words of the miners themselves. Family and social life, union agitation, relations with the company and strikes are all described. There are several accounts of major disasters in the mines. The book concludes with a discussion of the revival of coal mining in recent years with the Westray Mine, and an account of the 1992 disaster. Extensively illustrated with historical photographs, Coal in our Blood is a valuable contribution to Nova Scotia's social and labour history. --Publisher's description
Keywords: Coal mining History; Community; Labour history; Mining, Oil, and Gas; Social History; Strikes; Working class

Homer Stevens: A Life in Fishing - Stevens, Homer; Knight, Rolf (Harbour, 1992)
Homer Stevens spent half a century in the BC fishing industry, both as a working fisherman and as a leader of the United Fishermen and Allied Workers' Union. His story, an oral autobiography, was recorded and compiled by Rolf Knight. Stevens grew up in Port Guichon, a polyglot fishing community on the Fraser River delta. He was one of an extended family of working people who argued constantly about the issues of the day. In 1936, when he was thirteen years old, Homer started fishing on his own in a leaky gillnetter called the Tar Box. Six years later, his uncle John said, "One of these days I'm going to have to take you down to a meeting of the United Fishermen's Union in Vancouver. It's run by a bunch of Reds but they're pretty good people." By 1946, Homer was a full-time organizer for the United Fishermen and Allied Workers' Union, going around "float to float, man to man" to sign up new members. Included here are Steven's ominous description of the Cold War years, and an evocative log of travelling the central BC coast during the 1950s, with its bustling fishermen's ports and canneries. There are accounts of the 1967 strike in Prince Rupert, Homer's year in jail for contempt of court and his drive to organize Nova Scotia fishermen, and there is a moving personal description of relearning how to fish in a modern and very different salmon industry. "All and all," he says, "if someone were to ask me, 'Would you do it again?' I'd say, 'Yeah, I'd do it again. I'd try to do it better if I could, but I'd be willing to tackle it.'" --Publisher's description

Private Lives, Public Policy: 100 Years of State Intervention in the Family - Ursel, Jane (Women's Press, 1992)
Historical sociologist Jane Ursel conducts a feminist analysis of reproductive labour in Canada focussing on the shift from the family to the state. --WorldCat record
Keywords: Canada; Droit social Canada Histoire; Familienpolitik; Family policy; Family policy Canada History; Femmes Canada Conditions sociales; Geschichte; History; Kanada; Patriarcat (Sociologie); Patriarchy; Politique familiale Canada Histoire; Social legislation; Social legislation Canada History; Social structure; Social structure Canada; Structure sociale Canada; Women Canada Social conditions; Women Social conditions

The First Forty Years: A History of the Tunnel and Rock Workers Union, Local 168 - Warrior, M. C.; Leier, Mark (James Mark) (The Local, 1992)
Keywords: History; Tunnel and Rock Workers Union. Local 168 Histoire; Tunnel and Rock Workers Union. Local 168 History

Petticoats and Prejudice: Women and Law in Nineteenth-Century Canada - Backhouse, Constance (Published for the Osgoode Society by Women's Press, 1991)
This is the first comprehensive work in the field of Canadian women's legal history. Author Constance Backhouse, an internationally-recognized authority on Canadian women's legal history, has compiled here the most important of her decade's worth of research. This highly-readable book highlights the status of women through in-depth case profiles of individual women who were swept up into the 19th century legal process as litigants, accused criminals and witnesses. The cases span the country, providing information about all the common law provinces as well as Quebec. --Publisher's description(Osgoode Society)
Keywords: 1800-1899; Börngen, ..; Canada; Discrimination à l'égard des femmes Droit Canada Histoire 19e siècle; Femmes Droit Canada Histoire 19e siècle; Frau; Geschichte 1800-1900; History; Kanada; Procès Canada; Rechtsstellung; Sex discrimination against women Law and legislation; Sex discrimination against women Law and legislation Canada History; Sex discrimination against women Law and legislation Canada History 19th century; Trials; Trials Canada; Women Legal status, laws, etc; Women Legal status, laws, etc Canada History; Women Legal status, laws, etc. Canada History; Women Legal status, laws, etc. Canada History 19th century

A Word to Say: The Story of the Maritime Fishermen's Union - Calhoun, Sue (Nimbus, 1991)
A Word to Say is a penetrating account of how inshore fishermen, most of them Acadian, came together to take control of their industry and their livelihood. Threatened with the loss of their way of life, they fought long and hard to be heard by governments and companies alike. In the process, they saw their union spread from the east coast of New Brunswick to the shores of Nova Scotia and Prince Edward Island. As the only union in the country made up strictly of inshore fishermen, the MFU is unique. Although it has not altered the social fabric of the region, it has played a major role in the momentous changes in the fishery since the mid-1970s. In telling the story, Sue Calhoun gives fishermen more than a word to say. She offers clear insights into the lives of inshore fishermen, so often ignored and taken for granted. Her characters aren't rich. They aren't powerful. Many aren't educated. They are ordinary people who have done extraordinary things. --Publisher's description
Keywords: Fishers; History; Maritime Fishermen's Union; Maritime Provinces; Trade unions

Le syndicalisme au Québec - Dionne, Bernard (Boréal, 1991)
Le Québec compte plus de un million deux cent mille syndiqués et, chaque année, des milliers de nouvelles demandes d'accréditation sont accordées. Le syndicalisme, en dépit des crises qui l'ont secoué, reste donc un important partenaire social et économique. Dans cet ouvrage, Bernard Dionne trace l'histoire du mouvement syndical au Québec depuis le XIXe siècle. Il brosse le portrait du syndicalisme québécois, de son cadre légal, de ses effectifs et de ses structures, en marquant bien ce qui fait sa spécificité. Il explique ensuite les défis qui se posent aujourd'hui au syndicalisme québécois, qu'ils touchent des questions économiques - comme le libre-échange -, sociales - comme la place des jeunes et l'équité salariale des femmes - ou stratégiques - comme la négociation collective dans le secteur public. --Résumé de l'éditeur

Slaves of the Lamp: A History of the Federal Civil Service Organizations, 1865-1924 - Doherty, Bill (Orca Book Publishers, 1991)
[This book] is the story of the Canadian men and women who, during the period from 1865 to 1924, struggled against the corruption of political patronage, abysmal working conditions and poverty-level salaries in the federal civil service. This is an account of the history of some of the organizations formed to overcome these adverse conditions, and the story of the dedicated men and women who guided them, often at great personal risk. The book documents their few victories and many defeats, and the significant impact that their dogged perseverance has had on the Canadian federal service of today. --Publisher's description
Keywords: Canada; Civil service Canada History; Civil service reform; Civil service reform Canada History; Fonction publique Canada Associations Histoire; Fonction publique Canada Histoire; Fonction publique Réforme Canada Histoire; Government employee unions; Government employee unions Canada History; History; Labor unions Canada Officials and employees History; Labor unions Officials and employees; Postal service Canada Employees History; Postal service Employees; Postes Canada Personnel Histoire; Syndicats Canada Fonctionnaires Histoire; Syndicats Canada Personnel Histoire; Syndicats Postes Canada Histoire

Solidarité inc. : un nouveau syndicalisme créateur d'emplois - Fournier, Louis (Québec/Amérique, 1991)
L'histoire du Fonds de solidarité des travailleurs du Québec (FTQ), ou le récit de l'émergence d'un nouveau syndicalisme engagé dans le développement des entreprises, de l'emploi, de l'économie québécoise, de la démocratie économique; "Le Fonds de solidarité des travailleurs du Québec (FTQ)." --Résumé de l'éditeur
Keywords: Fédération des travailleurs du Québec -- History

Just Wages: A Feminist Assessment of Pay Equity - Fudge, Judy; McDermott, Patricia (University of Toronto Press, 1991)
Papers presented at the Pay Equity: Theory and Practice Conference organized through York University's Centre for Public Law and Public Policy, May 14-15, 1990.
Keywords: Pay equity -- Canada -- Congresses

Perspectives on Canadian Economic Development: Class, Staples, Gender, and Elites - Laxer, Gordon D. (Oxford University Press, 1991)
This new collection of readings brings together articles offering a wide range of perspectives on the pattern of Canada's economic development. Among the features they emphasize are Canada's historical reliance on resource (staple) exportation; trade dependence on one or two metropolitan centres; regional economic disparities,; a tendency towards centralized control of economic institutions; and a high-wage labour force. Organized in five sections - neoclassical economics, the staples approach, elites, class politics, and the roles of gender and labour in economic development - the selections in this book reflect the variety of approaches to Canada's economic history that have developed over the last quarter century. --Publisher's description
Keywords: Canada; Canada Conditions économiques; Canada Economic conditions; Canada Economic conditions 1971-1991; Economic history; Kanada; Wirtschaftsentwicklung

Fool for Christ: The Political Thought of J.S. Woodsworth - Mills, Allen (University of Toronto Press, 1991)
James Shaver Woodsworth (1874-1942) stands as one of the half-dozen most important national political figures in twentieth-century Canadian history. Allen Mills acknowledges his outstanding achievements while providing a critical account of the Woodsworth legacy and revising the received opinion of him as a man of unbending conviction and ever-coherent principle. A product of western Canada's pioneer society and a stern Methodist household, Woodsworth grew up to make his way into social service and politcal action. A member of parliament for over twenty years, he rejected the traditional forms of political activity, seeking a new politics and a new political party. The latter turned out to be the Co-operative Commonwealth Federation founded in 1932. Its first leader was Woodsworth himself. In a crucial period between the World Wars, Woodsworth helped define the character of the modern Canadian, non-Marxist Left and of many of Canada's important economic and social institutions. Among them are the welfare state, the Bank of Canada, and Canada's internationalist role in the contemporary world.--Publisher's description.

The New Democracy: Challenging the Social Order in Industrial Ontario, 1914-1925 - Naylor, James (University of Toronto Press, 1991)
James Naylor traces the transformation of class relations in the industrial cities of southern Ontario, examining the character of the regional labour movement, the nature of employer and state response, and the reasons for the failure of labour's "new democracy." --Publisher's description. Inside front-cover summary: The period during and after the First World War was marked by tremendous labour unrest, not only in Winnipeg where the general strike of 1919 was a watershed, but across the country. James Naylor focuses on southern Ontario, in the industrial heartland of Canada, as a key to understanding the character of this phase of labour history. In the 1919 provincial election, the Independent Labor Party of Ontario swept most of the province's industrial constituencies outside Toronto and formed a coalition government with the organized farmer. Strike activity soared to unprecedented levels. The Toronto Trades Council organized a general strike, and new forms of industrial unionism began to emerge. If these events lacked some of the drama of those in the West, they reflect both an increasingly articulate working-class view of democracy and labour's determination not to be overlooked in the postwar reconstruction. Naylor examines a number of issues: the nature of working-class views of democracy and the state; the role of women in these movements; the logic participation in the electoral process; the dynamic between 'industrial' and 'political' activity in the context of a liberal-democratic system. He also considers the responses of employers and government with a view to undertanding the 'negotiated' character of postwar reconstruction in the context of social classes.
Keywords: Arbeidersbeweging; Electronic books; HISTORY Canada General; History; Livres numériques; Ontario; Politieke participatie; SOCIAL SCIENCE Discrimination & Race Relations; SOCIAL SCIENCE Minority Studies; Travailleurs Ontario Histoire; Working class; Working class Ontario History; e-books

United We Stand: A History of Winnipeg's Civic Workers - Pringle, Jim (Manitoba labour history series, 1991)
Presents a history of the Canadian Union of Public Employees, Local 500.
Keywords: Canadian Union of Public Employees. Local 500 Histoire; Canadian Union of Public Employees. Local 500 History; History; Labor unions Manitoba Winnipeg Municipal employees History; Manitoba Winnipeg; Syndicats Fonctionnaires municipaux Manitoba Winnipeg Histoire

Racism and the Incorporation of Foreign Labour: Farm Labour Migration to Canada Since 1945 - Satzewich, Vic (Critical studies in racism and migration, 1991)
Intended to be of interest to students of sociology, ethnic studies and history, this book assesses the political economy of migration. Labour shortages, the racialization of Caribbean migrant farm labour and alternatives to labour imports are discussed. --Publisher's description
Keywords: Agricultural laborers, Foreign; Agricultural laborers, Foreign Canada History; Boeren; Buitenlandse arbeiders; Canada; Canada Relations raciales Histoire; Children of foreign workers; Children of foreign workers Canada History; Discrimination raciale Canada Histoire; Einwanderung; Enfants de travailleurs étrangers Canada Histoire; Foreign workers; Foreign workers Canada History; Foreign workers, West Indian; Foreign workers, West Indian Canada History; Geschichte 1945-1990; History; Kanada; Landarbeiter; Migratie (demografie); Personnel Immigrants; Race discrimination; Race discrimination Canada History; Racism; Rassendiscriminatie; Travailleurs agricoles étrangers Canada Histoire; Travailleurs étrangers Canada Histoire; Travailleurs étrangers antillais Canada Histoire

The Social Passion: Religion and Social Reform in Canada, 1914-28 - Allen, Richard (University of Toronto Press, 1990)
Allen was raised in a Christian family, being the son of a United Church minister, and this no doubt influenced his academic interests, which took him to Duke University where he completed his doctoral studies. Out of this came his first major work, and one which still inspires scholars of Canadian socialism and Christianity to this day: The Social Passion: Religion and Social Reform in Canada, 1914-28. Published in 1971, it served as a defining work for how scholars understood the figures, events, motivations, ideologies, and theologies which shaped the social gospel movement in Canada. While of an age that many might deem ‘dated,’ this book was deeply influential on my own understanding of the Christian left in this country, which existed in rudimentary form given my interest in key CCF figures like J.S. Woodsworth and Tommy Douglas, but wasn’t developed in a meaningful way until graduate school. In Allen’s writing, I saw figures and movements that—however imperfectly—melded the ideas of secular social justice with a conviction that Christ was sent to earth not only to teach us about the afterlife, but about how to build a New Jerusalem in the here and now. --From "Remembering Richard Allen" by Christo Aivalis [blog posting, 2019-03-25]

Political Choices and Electoral Consequences: A Study of Organized Labour and the New Democratic Party - Archer, Keith (McGill-Queen's University Press, 1990)
The creation of the NDP out of the CCF in 1961 was intended to strengthen Canada's left-wing political party through a closer alliance with organized labour. This strength has failed to materialize. In Political Choices and Electoral Consequences, Keith Archer reveals why.The most important link between labour and the NDP is the direct party affiliation of union locals. While this sort of affiliation had existed with the CCF, the Canadian Labour Congress showed a greater commitment to encouraging union locals to affiliate with the NDP. Although, as Archer discusses in both theoretical and empirical terms, individuals who belong to union locals formally linked to the NDP are more likely to vote for that party than are other people with similar socio-demographic characteristics, this has had little positive effect on the NDP's fortunes. Archer reveals that although, in principle, each union local may favour high rates of affiliation, it is often not in a local's self-interest to affiliate. Archer suggests that the main reason for such a disappointing record of affiliation is structural rather than ideological or cultural. He compares the Canadian situation to that in Britain, where the Labour Party rules governing affiliation have supported high rates of affiliation. The rules of the NDP, Archer goes on to show, are not significantly different from those that were developed between labour and the CCF. However, the CCF was not a labour party as such but rather an amalgam of farmers, labourers, and members of constituency associations. Labour's role has consequently remained that of a junior partner with the constituency groups. Under these circumstances, Archer argues, one would expect rates of affiliation to remain low. --Publisher's description

Confrontation at Winnipeg: Labour, Industrial Relations, and the General Strike - Bercuson, David Jay (McGill-Queen's University Press, 1990)
Why was Winnipeg the scene of the longest and most complete general strike in North American history? Bercuson answers this question by examining the development of union labour and the impact of depression and war in the two decades preceding the strike. --Publisher's description

Regulating Labour: The State, Neo-Conservatism and Industrial Relations - Haiven, Larry; McBride, Stephen; Shields, John (Socialist studies (Toronto), 1990)
Have Mulroney, Reagan and Thatcher beaten labour into the ground? Are unions a spent force? Do ordinary people in Canada, the United States and Great Britain truly believe in the so-called free market? How are the Swedish social democrats handling challenges to their consensus society? Is there indeed a neo-conservative hegemony for the nineteen-nineties? These are some of the questions which the authors of this sixth Socialist Studies Annual try to answer. They present case studies from various countries, using the social and political insights of Gramsci and other progressive thinkers. --Publisher's description
Keywords: Conservatism; Conservatisme; Industrial relations Government policy; Labor policy; Relations industrielles Politique gouvernementale; Travail Politique gouvernementale; conservatism

Canadian and Australian Labour History: Towards a Comparative Perspective - Kealey, Gregory S.; Patmore, Greg (Australian Society for the Study of Labour History ; Committee on Canadian Labour History, in Association wth Australian-Canadian studies, 1990)
Keywords: Arbeiterbewegung; Australia; Australien; Canada; Conference papers and proceedings; Geschichte; History; Industrial relations; Industrial relations Australia History; Industrial relations Australia History Congresses; Industrial relations Canada History; Industrial relations Canada History Congresses; Kanada; Kongress; Kongreß Sydney (Kanada) 1988; Labor; Labor Australia History Congresses; Labor Canada History Congresses; Labor movement; Labor movement Australia History; Labor movement Canada History; Mouvement ouvrier Australie Histoire; Mouvement ouvrier Canada Histoire; Relations industrielles Australie Histoire; Relations industrielles Australie Histoire Congrès; Relations industrielles Canada Histoire; Relations industrielles Canada Histoire Congrès; Travail Australie Histoire Congrès; Travail Canada Histoire Congrès; Travailleurs Australie Histoire; Travailleurs Canada Histoire; Working class; Working class Australia History; Working class Canada History

Where the Fraser River Flows: the Industrial Workers of the World in British Columbia - Leier, James Mark (New Star Books, 1990)
"The heroic and principled struggle of the Industrial Workers of the World to become the organization representing the working class in its contest with capital has been celebrated in story and song for most of this century. That they eventually lost this struggle is well known; less well understood is why. It is this why that concerns Mark Leier in Where the Fraser River Flows. In recounting the IWW's glory days in British Columbia, particularly the famous Free Speech Fights of 1909 and 1912, Leier shows that they were pitted against not just the bosses and government, but also against conservative elements within labour and the left. To ask what happened to the IWW, says Leier, is to ask a larger question-why is there no socialism?"--Page 4 of cover
Keywords: British Columbia; History; Industrial Workers of the World; Industrial Workers of the World Histoire; Industrial Workers of the World History; Labor unions; Labor unions British Columbia History; Syndicats Colombie-Britannique Histoire; Travailleurs Colombie-Britannique Histoire; Working class; Working class British Columbia History

Ginger: The Life and Death of Albert Goodwin - Mayse, Susan (Harbour Publishing, 1990)
July 27, 1918. Heavy heat burned down on the small mining town of Cumberland on Vancouver Island. In the nearby wildernes of Comox Lake, a special police constable broke through the bush to come shockingly face to face with a stranger. A slight, red-haired man stood holding a rifle. This was the fugitive they sought, considered subversive and dangerous. With no time to aim, the constable shot as he raised his own weapon. This is the "official" version of the events of that day. The life of Albert "Ginger" Goodwin, one of British Columbia's most colourful figures, had come to a controversial end. [This book] is the story of a remarkable man, and a fascinating period in BC history. Arriving on Vancouver Island in 1910, Ginger Goodwin joined hundreds of others slaving in the hellholes of the Cumberland Mines. There he found blacklung, explosions, and deadly vapours; hazards which killed hundreds of miners in a short century of coal mining. What he saw made him one of the most effective labour leaders the province has ever seen, and led ultimately to his untimely end. Susan Mayse combines the skills of the historian and novelist in this gripping biography. From fragments of recorded history, official documents, and exhaustive interviews with the coal miners who knew Cumberland and knew Ginger Goodwin, she has pieced together an extraordinary tale. --Publisher's description
Keywords: Biographies; Biography; British Columbia; British Columbia Vancouver Island; Charbon Mines et extraction; Charbon Mines et extraction Colombie-Britannique Vancouver, Île de Histoire; Coal Mining; Coal miners; Coal miners Labor unions Officials and employees; Coal miners Labor unions Officials and employees British Columbia Biography; Coal mines and mining; Coal mines and mining British Columbia Vancouver Island History; Dirigeants syndicaux Colombie-Britannique Biographies; Goodwin, Ginger; History; Labor leaders; Labor leaders British Columbia Biography; Mineurs de charbon; Mineurs de charbon Syndicats Colombie-Britannique Fonctionnaires Biographies; coal mines

Descent into Discourse: The Reification of Language and the Writing of Social History - Palmer, Bryan D. (Temple University Press, 1990)
"Critical theory is no substitute for historical materialism; language is not life." With this statement, Bryan Palmer enters the debate that is now transforming and disrupting a number of academic disciplines, including political science, women’s studies, and history. Focusing on the ways in which literary or critical theory is being promoted within the field of social history, he argues forcefully that the current reliance on poststructuralism—with its reification of discourse and avoidance of the structures of oppression and struggles of resistance—obscures the origins, meanings, and consequences of historical events and processes. Palmer is concerned with the emergence of "language" as a central focus of intellectual work in the twentieth century. He locates the implosion of theory that moved structuralism in the direction of poststructuralism and deconstruction in what he calls the descent into discourse. Few historians who champion poststructuralist thought, according to Palmer, appreciate historical materialism’s capacity to address discourse meaningfully. Nor do many of the advocates of language within the field of social history have an adequate grounding in the theoretical making of the project they champion so ardently. Palmer roots his polemical challenge in an effort to "introduce historians more fully to the theoretical writing that many are alluding to and drawing from rather cavalierly." Acknowledging that critical theory can contribute to an understanding of some aspects of the past, Palmer nevertheless argues for the centrality of materialism to the project of history. In specific discussions of how critical theory is constructing histories of politics, class, and gender, he traces the development of the descent into discourse within social history, mapping the limitations of recent revisionist texts. Much of this writing, he contends, is undertheorized and represents a problematic retreat from prior histories that attempted to address such material forces as economic structures, political power, and class struggle. Descent into Discourse counters current intellectual fashion with an eloquent argument for the necessity to analyze and appreciate lived experience and the structures of subordination and power in any quest for historical meaning.--Publisher's description
Keywords: Language and history

The Gender of Breadwinners: Women, Men, and Change in Two Industrial Towns, 1880-1950 - Parr, Joy (University of Toronto Press, 1990)
This is a story of two Ontario towns, Hanover and Paris, that grew in many parallel ways. They were about the same size, and both were primarily one-industry towns. But Hanover was a furniture-manufacturing centre; most of its workers were men, drawn from a community of ethnic German artisans and agriculturalists. In Paris the biggest employer was the textile industry; most of its wage earners were women, assisted in emigration from England by their Canadian employer. Joy Parr considers the impacy of these fundamental differences from a feminist perspective in her study of the towns' industrial, domestic, and community life. She combines interviews of women and men of the towns with analyses of a wide range of documents: records of the firms from which their families worked, newspapers, tax records, paintings, photographs, and government documents. Two surprising and contrasting narratives emerge. The effects of gender identities upon both women's and men's workplace experience and of economic roles upon familial relationships are starkly apparent. Extending through seventy crucial years, these closely textured case studies challenge conventional views about the distinctiveness of gender and class roles. They reconfigure the social and economic change accompanying the rise of industry. They insistently transcend the reflexive dichtomies drawn between womena dn men, public and privae, wage and non-wage work. They investigate industrial structure, technological change, domesticity, militance, and perceptions of personal power and worth, simultaneously as products of gender and class identities, recast through community sensibilities. --Publisher's description
Keywords: 19th century; 20th century; Furniture industry and trade; History; Knit goods industry; Ontario Hanover; Ontario Paris; Sexual division of labor

Cracking the Canadian Formula: The Making of the Energy and Chemical Workers Union - Roberts, Wayne (Between the Lines, 1990)
A book about succeeding because you are Canadian - not in spite of it. About doing all those things we're not supposed to be very good at. Things like outmaneuvering monster corporations; like standing up to the Americans; like putting regional differences aside; like blowing the whistle on polluters; like rising above linguistic differrences. But, most of all, it's about cracking the Canadian formula--about learning how to win on our own terms, in our own time, in our own way. No fuss. No muss. Cracking the Canadian Formula is not just the story of Canadians building a unique union. The story of how we succeed in Canada when we have the courage to try it our own way. That makes it the story of far. It also makes it a story that might just hold the secret of Canadian yet to come." -- Publisher's description. "This is the encyclopedia of what unions can do to help build a made-in-Canada movement for personal, social and economic independence." -- Mel Hurtig.

Back to Work? Labour, State, and Industrial Relations in Canada - Russell, Bob (Nelson Canada, 1990)
The central argument of this book is that getting people to work and getting them to stay there is a significant political achievement in its own right. ...[W]e may assume that in any social situation in which labour is experienced as a coercive aspect of daily life, work, or more accurately obtaining work effort, becomes problematical. Often it entails state intervention in a well-developed system of industrial relations that includes an important element of public policy. This book is a study of that element in Canadian industrial relations. Proceeding from this starting point, two central questions are posed throughout the remainder of this text: 1) What does the state do when it practices industrial relations; and 2) What are the implications of such practices on work and those groups that are brought together in labouring processes? --From introduction
Keywords: Canada; History; Industrial relations; Labor policy

Brother Max: Labour Organizer and Educator - Swerdlow, Max (Past CCLH Publications, 1990)
Max Swerdlow's life as labour organizer and educator began in Depression-era Winnipeg and carried him to national and international prominence in the Trades and Labour Congress, the Canadian Labour Congress, and the International Labour Organization. In this lively memoir, Swerdlow recaptures the persons and events of his life in the Labour movement. --Publisher's description
Keywords: Biography; Canada; Labor Unions; Officials and employees; Officials and employees Biography; Organizing; Swerdlow, Max; Swerdlow, Max, 1915-1990

Administering Danger in the Workplace: The Law and Politics of Occupational Health and Safety Regulation in Ontario, 1850-1914 - Tucker, Eric (University of Toronto Press, 1990)
For Ontario workers during the industrial revolution the workplace was often an environment of terrible danger. Injuries and illness from unsafe working conditions were commonplace. Over time these conditions spurred efforts for reform from activists, legislators, and the courts. But change was slow in coming. To understand the impact of industrial revolution on the health and safety of workers generally, and on women and children in particular, tucker uses their testimony before various commissions, newspapers, and reported court cases. Initial efforts to effect change were made through the courts; they were largely unsuccessful. When the judiciary refused to regulate the risk-creating conduct of employers, through either the civil or the criminal law, workers and Victorian reformers found common ground in successfully promoting factory legislation. By prescribing and enforcing minimum standards, a measure of regulatory responsibility for the health of workers generally and women and children in particular was shifted from the market to the state. Class interest and gender ideology played a substantial role in this process. But the legislation's implementation belied its promise. The government was unwilling to provide adequate enforcement resources and inspectors accepted the conventional wisdom that workers had to adjust to the 'normal' hazards of industry, which were reasonable and, therefore, legal. Even when the accident rate began to soar as a result of the 'second industrial revolution, ' the authorities remained complacent. Tucker says that in industrial capitalist social formation, the nature and degree of hazards to which workers are exposed are determined largely by the employer-worker balance of power. Their respective power resources both shape and are shaped by the ideological, legal, political, and administrative environment in which they are deployed. Throughout the last half of the nineteenth century and up to the First World War, state regulation of occupational health and safety was substantially subordinated to market-driven forces; it still is today
Keywords: Factory laws and legislation; Factory laws and legislation Ontario History; History; Hygiène industrielle Droit Ontario Histoire; Hygiène industrielle Ontario Histoire; Industrial hygiene; Industrial hygiene Law and legislation; Industrial hygiene Law and legislation Ontario History; Industrial hygiene Ontario History; Industrial safety; Industrial safety Law and legislation; Industrial safety Law and legislation Ontario History; Industrial safety Ontario History; Ontario; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; Sécurité du travail Droit Ontario Histoire; Sécurité du travail Ontario Histoire; Usines Droit Ontario Histoire

Politics as if Women Mattered: A Political Analysis of the National Action Committee on the Status of Women - Vickers, Jill; Rankin, Pauline; Appelle, Christine (Heritage, 1990)
The National Action Committee on the Status of Women marked the twentieth anniversary of its founding in 1992. Today, it is the umbrella organization for roughly six hundred women’s groups in Canada. The authors of this study argue that, if women’s movements are to achieve their equality goals, they must develop enduring institutions that allow women’s efforts to be organized over the course of several generations. The authors examine the process of institutionalization through an in-depth study of the National Action Committee. In the belief that women’s movements in Canada have become more or less permanent features of the political system, operating parallel to its official structures, the author argue the need for a feminist political science that can accommodate the study of both women’s politics in their autonomous movements and women’s conventional activities in official politics. Indeed, this book undertakes political analysis ‘as if women mattered’: it focuses on women’s interests and draws on feminist theory while remaining connected to the broad framework of political science. The book documents NAC’s evolution as a ‘parliament of women.’ It shows how the organization moved from a fairly narrow status-of-women focus in its policies to a broadly conceived policy framework that linked such apparently sex-neutral issues as free trade, federalism, and taxation to feminism. Although the more comprehensive feminist approach to public policy proved dangerous for NAC in a conservative era, it also solidified its role and reputation as a major play in equality-seeking politics in Canada. --Publisher's description. Contents: Introduction : NAC and women's politics in Quebec ; NAC and women's politics in the first nations ; NAC and the politics of the 'new force' ; NAC as the coordinating institution of the English-Canadian women's movement ; Highlights of NAC's development -- The intellectual and political context for the development of NAC : An overview of women's movements and the National Action Committee ; Canadian political culture and Canadian women's movements ; Radical influences on feminist political culture ; NAC's political-opportunity structure: the Canadian political system -- NAC in the shadow of the royal commission: the founding era, 1972-1978 : 'Social' movements and the political process ; The founding of NAC -- The struggle for NAC: the transitional era, 1979-1982 : The issues in conflict: grafting on a radical grass roots ; Two coalitions competing for the future of NAC -- A new Parliament of women: institutionalizing NAC, 1982-1988 : Getting NAC 'back on track' ; The great leap forward: the expansion examined ; Opposition on the right ; Organizational review -- Agency, leadership, representation, and democracy in NAC : A revolution of rising expectations: NAC member groups ; Leadership and accountability: is anyone here in charge? ; Representation: the heart of the matter ; Process and democracy in NAC -- The policy process: structures for a new Parliament of women : Changing conceptions of the policy process in NAC ; Evolving policy structures in NAC ; NAC's ability to deal with short-term policy issues ; NAC's approach to long-term policy issues -- Feminist ideology and policy making in NAC : In search of a framework: understanding the ideological trends in NAC ; The development of a feminist ideological spectrum in NAC: some benchmark issues ; From a status-of-women approach to a feminist politics -- Conclusion : What is success? ; Can NAC's role as a Parliament of women continue? ; Is radical liberalism outmoded as a cultural basis for NAC politics? ; Will NAC survive? -- Appendixes : A. Ideological forces among Anglophone NAC delegates, 984 AGM ; B. Groups affiliated with NAC by type, circa 1987-1988.

Hospital Strike: Women, Unions, and Public Sector Conflict - White, Jerry Patrick (Thompson Educational Publishing, 1990)
Keywords: Hospital Strike, Ontario, 1981; Hospitals; Strikes and lockouts; Women labor union members

Mail & Female: Women and the Canadian Union of Postal Workers - White, Julie (Thompson Educational, 1990)
In Mail & Female, Julie White chronicles and analyzes changes at the Post Office during the thirty years prior to the merger between the Canadian Union of Postal Workers and the Letter Carriers Union of Canada in January 1989. She focuses on CUPW activities and changes during a period which saw both inside workers and postal managers move from thinking of Post Office jobs as men's work to jobs no longer characterized in gender-specific terms. Mail & Female: Women and the Canadian Union of Postal Workers is an original contribution to women's and labour studies in Canada. CUPW changed from refusing women membership in the union in the late 1950s to its present position where its collective agreement is regarded as one of the most progressive for women. This book documents and analyzes these changes. --Publisher's description
Keywords: Canada; Canadian Union of Postal Workers; Discrimination à l'égard des femmes Canada; Femmes dans les syndicats Canada; Frau; Postal service Canada Employees; Postal service Employees; Postes Canada Personnel; Sex discrimination against women; Sex discrimination against women Canada; Syndicat des postiers du Canada; Women labor union members; Women labor union members Canada

Prison of Grass: Canada from a Native Point of View - Adams, Howard (Fifth House Books, 1989)
Originally published in 1975, this important book is now back in print in a revised and updated edition. Since its first publication it has become a classic of revisionist history. Bringing a Native viewpoint to the settlement of the West, Howard Adam's book shook its readers. What Native people had to say for themselves was quite different from the convenient picture of history that even the most sympathetic books by white authors had presented. Until Adams's book, the cultural, historical, and psychological aspects of colonialism for Native people had not been explored in depth. In Prison of Grass Adams objects to the popular historical notion that Natives were warring savages, without government, seeking to be civilized. He contrasts the official history found in the federal government's documents with the unpublished history of the Indian and Métis people. In this new edition Howard Adams brings the latest statistics to bear on his arguments and provides a new Preface. --Publisher's description. Contents: The basis of racism -- The communal Indian society -- Fur traders trespass -- Colonization and missionaries -- Ossification of Native society -- The Halfbreed Nation and the civil war -- Subjugation of the Indians and Metis -- Causes of the 1885 struggle -- Ottawa invades the Northwest -- Courtroom : the mask of conquest -- The underdevelopment of Native communities -- Schooling the Redman -- The white ideal and the colonized personality -- The failure of Native leadership -- Decolonization and nationalism -- The struggle for liberation -- Appendix A. Casualties of Indians and Metis in 1885 Battles.

Le droit de se taire : histoire des communistes au Québec, de la Première Guerre mondiale à la Révolution tranquille - Comeau, Robert; Dionne, Bernard (VLB, 1989)
De la Première Guerre mondiale jusqu'aux débuts de la Révolution tranquille, le Parti communiste du Canada, contrairement à la plupart des partis politiques canadiens et québécois, n'auru connu qu'une quinzaine d'années de liberté d'expression. De 1921, date de sa création, aux années 60, d'interdiction en interediction, d'une répression à l'autre, le Parti communiste du Canada, n'aura qu'un droit : celui de se taire. Dans un essai historique aussi documenté que magistral, Robert Comeau et Bernard Dionne, entourés de leurs collaborateurs, analysent avec perspicacité et rigeur les principales phases de l'activité communiste au Canada et au Québec, les luttes ouvrières nationales, l'envronnement internationales et les idées marxistes-léninistes avec lesquels le Parti communiste devra composer tout au long de sa jeune existence. --Résumé de l'éditeur
Keywords: Communist Party of Canada -- History

Workers and the State in Twentieth Century Nova Scotia - Earle, Michael J.; Gorsebrook Research Institute for Atlantic Canada Studies (Gorsebrook studies in the political economy of the Atlantic region, 1989)
The origins of the modern system of industrial relations in Canada as seen in the key struggles and compromises with the power of employers and governments in the province of Nova Scotia. Focusing on changes in coal-mining, fishing and the public sector, this collection offers a challenging case study in Canadian labour history. --Publisher's description
Keywords: History; Industrial relations; Labor Unions; Nova Scotia; Strikes and lockouts

Fruits of the Earth - Grove, Frederick Philip (McClelland and Stewart, 1989)
During the author's travels, he meets Menalcas, a caricature of Oscar Wilde, who relates his fantastic life story. But for all his brilliance, Menalcas is only Gide's yesterday self, a discarded wraith who leaves Gide free to stop exalting the ego and embrace bodily and spiritual joy. Later Fruits of the Earth, written in 1935 during Gide's short-lived spell of communism, reaffirms the doctrine of the earlier book. But now he sees happiness not as freedom, but a submission to heroism. In a series of 'Encounters', Gide describes a Negro tramp, a drowned child, a lunatic and other casualties of life. These reconcile him to suffering, death and religion, causing him to insist that 'today's Utopia' be 'tomorrow's reality'. --Publisher's description
Keywords: Agriculture; Blue-collar work; Farming; Pioneers; Prairies

The War Series, Part 1, 1939-1941 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1989)
From its inception in 1919-1920 the Royal Canadian Mounted Police security service compiled periodic reports on "subversive" activity in Canada, which were circulated to the Prime Minister and Cabinet. Through use of Canada's Access to Information legislation Gregory S. Kealey and Reg Whitaker have acquired copies of the extant Bulletins, which are now held by the Canadian Security Intelligence Service....This volume covers the early years of World War II when the Communist Party of Canada was illegal and many CPC leaders were interned. --Publisher's description
Keywords: 20th century; Canada; Communism; History; Internal security; Royal Canadian Mounted Police (RCMP); Subversive activities; WORLD War, 1939-1945

Class, Community, and the Labour Movement Wales and Canada, 1850-1930 - Llafur (Society) (Past CCLH Publications, 1989)
This collection of essays stems from a joint conference held at the University College of Wales at Aberystwyth by the Committee on Canadian Labour History and the Society for the Study of Welsh Labour History. An Introduction by David Montgomery places the essays in a broader international perspective. Contributors from Wales include John Williams, Christopher Turner, Merfyn Jones, Dot Jones, and Deian R. Hopkin. Canadian essays are by Craig Heron, Robert Babcock, Bruno Ramirez, Allen Seager, Linda Kealey, Varpu Lindstrom-Best, and Gregory S. Kealey. The volume includes photographs, maps and tables. --Publisher's description. Contents: The rise and decline of the Welsh economy, 1890-1930 / John Williams -- Labour and industrial capitalist development in the North Atlantic Region, 1880-1920 / Robert Babcock -- The second Industrial Revolution in Canada, 1890-1930 / Craig Heron -- Conflicts of faith? / Christopher Turner -- Serfdom and slavery / Dot Jones -- Of men and stones / Merfyn Jones -- Migration and regional labour markets, 1870-1915 / Bruno Ramirez -- No special protection--no sympathy / Linda Kealey -- Miners'struggles in Western Canada, 1890-1930 / Allan Seager -- Canadian mining towns / Varpu Linstrom-Best -- The parameters of class conflict / Gregory S. Kealey -- The great unrest in Wales, 1910-1913 / Deian R. Hopkin. Papers from a conference of Committee on Canadian Labour History and Llafur, the Society for the Study of Welsh Labour History, held in April 1987 near Newtown in Mid-Wales.
Keywords: 19th century; 20th century; Canada; Congresses; Congresses. Labor movement; Congresses. Working class; Economic conditions; History; Social conditions; Wales; Working class

The Development of the Pacific Salmon-Canning Industry: A Grown Man's Game - Newell, Dianne (McGill-Queen's University Press, 1989)
The Pacific salmon fishery and the canning industry it supports have recently lost their status as the one of the most valuable fisheries in the world. In this study of early modern business, Dianne Newell discusses the beginning of the North American salmon canning industry, working from archives left by one of the leaders in the field, Henry Doyle. Doyle (1874-1961) was founder and first general manager of a major consolidation of packing companies, British Columbia Packers Association (established in 1902), which became British Columbia Packers Ltd., one of the few pioneer fish-packing companies that remains viable today. He was recognised by friends and enemies alike as the unofficial industry historian not only for British Columbia but also for Alaska and the Pacific US coastal states. Doyle was a vora-cious collector of "intelligence," whose extensive papers, now stored in the archives of the University of British Columbia, constitute the only comprehensive insider's history of the rise of the industry. Newell has culled this collection of documents for revealing highlights, important trends, and events within this profitable industry. These documents are reproduced in the text and are supported by editorial essays, annotations, a statistical appendix, and a lengthy glossary of historical terms. The result is an intriguing combination of both the personal and the scholarly view of this industry through its most exciting and critical years. --Publisher's description

Thirty Acres - Ringuet (Philippe Panneton) (New Canadian library, 1989)
One of the most important books to come out of Quebec, Thirty Acres (Trente arpents) traces the course of one man’s life as he enters into the age-old rhythms of the land and of the seasons. At the same time, it is a novel on a grand social scale, spanning and documenting the tumultuous half-century in which a new, industrial urban society crowded out Quebec’s traditional rural one. Winner of the Governor General’s Award and numerous other national and international literary prizes, Thirty Acres is a universal story of birth and death, renewal and reversal, ascent and decline, and a masterpiece of irony and realism. --Publisher's description
Keywords: Industrial; Quebec; Rural; Urban

Histoire du syndicalisme au Québec: des origines à nos jours - Rouillard, Jacques (Boréal, 1989)
Basé sur une documentation en partie inédite, voici l'histoire du syndicalisme québécois depuis le début du XIXe siècle jusqu'en 1985, histoire qui évolue sensiblement au même rythme que celle des autres mouvements syndicaux en Amérique du Nord. --Publisher's description
Keywords: Syndicalism -- Québec (Province) -- History

The Tin Flute - Roy, Gabrielle, (McClelland & Stewart, 1989)
The Tin Flute, Gabrielle Roy’s first novel, is a classic of Canadian fiction. Imbued with Roy’s unique brand of compassion and compelling understanding, this moving story focuses on a family in the Saint-Henri slums of Montreal, its struggles to overcome poverty and ignorance, and its search for love. An affecting story of familial tenderness, sacrifice, and survival during the Second World War, The Tin Flute won both the Governor General’s Award and the Prix Fémina of France. The novel was made into a critically acclaimed motion picture in 1983. --Publisher's description
Keywords: Montreal, Quebec; Poor; Poverty; Slums; Social Class and Equality

A White Man's Province: British Columbia Politicians and Chinese and Japanese Immigrants, 1858-1914 - Roy, Patricia (University of British Columbia Press, 1989)
"We are not strong enough to assimilate races so alien from us in their habits … We are afraid they will swamp our civilization as such." – Nanaimo Free Press, 1914. This book examines how British Columbians changed their attitudes towards Asian immigrants from one of toleration in colonial times to vigorous hostility by the turn of the century and describes how politicians responded to popular cries to halt Asian immigration and restrict Asian activities in the province. White workingmen objected to Asian sojourning habits, to their low living standards and wages, and to their competition for jobs in specific industries. Because employers and politicians initially supported Asian immigrants, early manifestations of antipathy often appeared just as another dispute between capital and labour. But as their number increased, complaints about Asians became widespread, and racial characteristics became the nucleus of such terms as a “white man’s province” – a “catch phrase” which, as Roy notes, “covered a wide variety of fears and transcended particular economic interests.” The Chinese were the chief targets of hostility in the nineteenth century; by the twentieth, the Japanese, more economically ambitious and backed by a powerful mother country, appeared more threatening. After Asian disenfranchisement in the 1870s, provincial politicians, freed from worry about the Asian vote, fueled and exploited public prejudices. The Asian question also became a rallying cry for provincial rights when Ottawa disallowed anti-Asian legislation. Although federal leaders such as John A. Macdonald and Wilfrid Laurier shared a desire to keep Canada a “white man's country,” they followed a policy of restraint in view of imperial concerns. The belief that whites should be superior, as Roy points out, was then common throughout the Western world. Many of the arguments used in British Columbia were influenced by anti-Asian sentiments and legislation emanating from California, and from Australia and other British colonies. Drawing on almost every newspaper and magazine report published in the province before 1914, and on government records and private manuscripts, Roy has produced a revealing historical account of the complex basis of racism in British Columbia and of the contribution made to the province in these early years by its Chinese and Japanese residents. --Publisher's description
Keywords: Chinese -- British Columbia -- History

Dreams of Equality: Women on the Canadian Left, 1920-1950 - Sangster, Joan (Canadian social history series, 1989)
Canadian women on the political left in the first half of the twentieth century fought with varying degrees of commitment for women's rights. Women's dreams of equality were in part a vision of economic and class equality, though they also represented profound desires for equality with men - both within their own parties and in the larger society. In both the Communist Party of Canada and the Co-operative Commonwealth Federation, a male-dominated leadership seldom embraced women's causes wholeheartedly or as a doctrinal priority. So-called women's issues, whether birth control, consumer issues, or equal pay, usually took second place to an emphasis on the general needs of workers or farmers. Nonetheless, many women continued to promote their feminist causes through the socialist movement, in the hope that, eventually, the socialist New Jerusalem would see their dreams of equality fulfilled. In Dreams of Equality, Joan Sangster chronicles in fascinating detail the first tentative stages of a politically aware women's movement in Canada, from the time of women's suffrage to the 1950's when the CPC went into decline and the CCF began to experience the changes that would evolve into the New Democratic Party a decade later. --Publisher's description. Originally published: Toronto: McClelland & Stewart, 1989. Contents: Preface --Theory and practice: early Canadian socialists explore the woman question -- The Communist Party of Canada confronts the woman question -- Red revolutionaries and pink tea pacifists: communist and socialist women in the early 1930's -- Militant mothering: women in the early CCF -- More militant mothering: communist women during the popular front -- From working for war to prices and peace: communist women during the 1940's -- The CCF confronts the woman question -- Conclusion: women and the party question.

Dreams of Equality: Women on the Canadian Left, 1920-1950 - Sangster, Joan (McClelland & Stewart, 1989)
Canadian women on the political left in the first half of the twentieth century fought with varying degrees of commitment for women's rights. Women's dreams of equality were in part a vision of economic and class equality, though they also represented profound desires for equality with men - both within their own parties and in the larger society. In both the Communist Party of Canada and the Co-operative Commonwealth Federation, a male-dominated leadership seldom embraced women's causes wholeheartedly or as a doctrinal priority. So-called women's issues, whether birth control, consumer issues, or equal pay, usually took second place to an emphasis on the general needs of workers or farmers. Nonetheless, many women continued to promote their feminist causes through the socialist movement, in the hope that, eventually, the socialist New Jerusalem would see their dreams of equality fulfilled. In this book, Joan Sangster chronicles in fascinating detail the first tentative stages of a politically aware women's movement in Canada, from the time of women's suffrage to the 1950's when the CPC went into decline and the CCF began to experience the changes that would evolve into the New Democratic Party a decade later. In Dreams of Equality, Joan Sangster chronicles in fascinating detail the first tentative stages of a politically aware women's movement in Canada, from the time of women's suffrage to the 1950's when the CPC went into decline and the CCF began to experience the changes that would evolve into the New Democratic Party a decade later.
Keywords: Right and left (Political science)

Beyond the Vote: Canadian Women and Politics - Sangster, Joan; Kealey, Linda (University of Toronto Press, 1989)
This collection of essays focuses on the experiences of women as poliutical activists in twentieth-century Canada, both in the mainstream of party politics and in groups outside the mainstream. The latter include women in the socialist and labour movements, the farm and peace movements, and women active in variouss ethnic communities. Expanding the notion of politics, the authors highlight the widespread naturee of women's activism - particularly at the local level - and challenge the easy formulation that women were primarily interest in the vote and lost interest in politics when they acquired it. Some of the essays suggest that even the suffrage campaign has been misrepresented as solely a middle-class movement. Women evolved their own styles of political pparticipation shaped by local contexts, class, culture, family, and life cycle. Women often organized at the community level, and worked both in combination with men and in women-only settings. Contributors to the volume explore women's involvement in organizations from the political left to right, and women's efforts to shape Canada's political priorities and activities. Politically minded women often found that their best outless for commitment and service was through women's organizations, which addressed their needs and provided a base for effective action. --Publisher's description

Women's Work, Markets, and Economic Development in Nineteenth-Century Ontario - Cohen, Marjorie Griffin (State and economic life, 1988)
In this study Marjorie Griffin Cohen argues that in research into Ontario’s economic history the emphasis on market activity has obscured the most prevalent type of productive relations in the staple-exporting economy – the patriarchal relations of production within the family economy. Cohen focuses on the productive relations in the family and the significance of women’s labour to the process of capital accumulation in both the capitalist sphere and independent commodity production. --Publisher's description

Native People, Native Lands: Canadian Indians, Inuit and Metis - Cox, Bruce Alden (Carleton library series; no. 142, 1988)
The changing roles of native women, devices for assimilation, the re-birth of the Metis: these are among the issues examined in this collection of provocative essays which explore the link between aboriginal culture and economic patterns. --Publisher's description. Contents: The Iroquois wars and native arms / Brian J. Given -- Epidemics / Susan Johnston -- Ktaqamkuk Ilnui Saqimawoutie : aboriginal rights and the myth of the micmac mercenaries in Newfoundland / Dennis Bartels -- Families of mixed descent in the Western Great Lakes Region / Harriet Gorham -- The significance of hunting territories today / Adrian Tanner -- Waswanipi Cree management of land and wildlife: Cree ethno-ecology revisited / Harvey A. Feit -- The Innu bands of Labrador / Eleanor Leacock -- The home guard Cree and the Hudson's Bay Company / J.E. Foster -- The Métis Nation: buffalo hunting versus agricullture in the Red River Settlement, 1810-1870 / Herman Sprenger -- The Métis: genesis and rebirth / Jennifer S.H. Brown -- Indian reserves in Western Canada: Indian homelands or devices for assimilation? / J.L. Tobias -- Slave raiding on the North Pacific Coast / Leland Donald -- Women traders in the maritime fur trade / Loraine Littlefield -- Fishing is women’s business: changing economic roles of carrier women and men / Jo-Anne Fiske -- The marginalization of the Tsimshian cultural ecology: the seasonal cycle / James Andrew MacDonald -- Changing perceptions of the industrial development of the North / Bruce Alden Cox -- Capital and economic development: a critical appraisal of the Mackenzie Valley Pipeline Commission / Michael J. Asch -- Survival and adaptation of the Innu ethnic identity: the importance of the Inuktituk / Jean-Philippe Chartrand -- Prospects for the northern Canadian native economy / Bruce Alden Cox -- Recent publications in Canadian native studies / John A. Price.
Keywords: Canada; Canada. Eskimos; Canada. Eskimos. Indians of North America. Indians of North America; Canada. Indians of North America; Canada. Indiens d'Amrique; Canada. Inuit; Canada. Mtis; Indians of North America; Mixed descent; Mixed descent. Inuits; Mtis

On the Job: Confronting the Labour Process in Canada - Heron, Craig; Storey, Robert H.; Steedman, Mercedes; Frank, David; Foster, John Bellamy; Lowe, Graham S.; Reiter, Ester; Radforth, Ian; Strong-Boag, Veronica; Kealey, Gregory S.; Craven, Paul; Traves, Tom; et al. (McGill-Queen's University Press, 1988)
Every day millions of Canadians go out to work. They labour in factories, offices, restaurants, and retail stores, on ships, and deep in mines. And every day millions of other Canadians, mostly women, begin work in their homes, performing the many tasks that ensure the well-being of their families and ultimately, the reproduction of the paid labour force. Yet, for all its undoubted importance, there has been remarkably little systematic research into the past and present dynamics of the world of work in Canada. The essays in this volume enhance our understanding of Canadians on the job. Focusing on specific industries and kinds of work, from logging and longshoring to restaurant work and the needle trades, the contributors consider such issues as job skill, mass production, and the transformation of resource industries. They raise questions about how particular jobs are structured and changed over time, the role of workers' resistance and trade unions in shaping the lives of workers, and the impact of technology. Together these essays clarify a fundamental characteristic shared by all labour processes: they are shaped and conditioned by the social, economic, and political struggles of labour and capital both inside and outside the workplace. They argue that technological change, as well as all the transformations in the workplace, must become a social process that we all control. --Publisher's description

Class, Gender, and Region: Essays in Canadian Historical Sociology - Kealey, Gregory S. (Committee on Canadian Labour History, 1988)
The essays are gathered around two themes: the relationship of sociology and social history, and the intersection of gender, ethnicity, and region with class. Unlike most Canadian essay collections, the contributors and their subjects cover Canada from British Columbia to Newfoundland, with forays into Cape Breton and central Canada. The volume contains articles by Ian McKay, Gordon Darroch, James R. Conley, Alicja Muszynski, Gillian Creese, and Jim Overton. An interesting collection of some of the new work being done in Canada by historians and sociologists, Class, Gender, and Region reflects Charles Tilly’s suggestion that “there should be no disciplinary division of labour: simply both doing social history.” --Publisher's description (Athabasca University Press) Contents: Introduction / Gregory S. Kealey -- The crisis of dependent development: class conflict in the Nova Scotia coalfields, 1872-1876 / Ian McKay --Class in nineteenth-century, central Ontario: a reassessment of the crisis and demise of small producers during early industrialization, 1861-1871 /Gordon Darroch -- “More theory, less fact?” Social reproduction and class conflict in a sociological approach to working-class history / James R. Conley -- Race and gender: structural determinants in the formation of British Columbia’s salmon cannery labour force / Alicja Muszynski -- The politics of dependence: women, work, and unemployment in the Vancouver labour movement before World War II / Gillian Creese -- Public relief and social unrest in Newfoundland in the 1930s: an evaluation of the ideas of Piven and Cloward / James Overton.
Keywords: Historical sociology

Class, Gender, and Region: Essays in Canadian Historical Sociology - Committee on Canadian Labour History; Kealey, Gregory S. (Past CCLH Publications, 1988)
The essays are gathered around two themes: the relationship of sociology and social history, and the intersection of gender, ethnicity, and region with class. Unlike most Canadian essay collections, the contributors and their subjects cover Canada from British Columbia to Newfoundland, with forays into Cape Breton and central Canada. The volume contains articles by Ian McKay, Gordon Darroch, James R. Conley, Alicja Muszynski, Gillian Creese, and Jim Overton. An interesting collection of some of the new work being done in Canada by historians and sociologists, Class, Gender, and Region reflects Charles Tilly's suggestion that "there should be no disciplinary division of labour: simply both doing social history." --Publisher's description
Keywords: Canada; Classes sociales; Conditions sociales; Historical sociology; Regionalism; Régionalisme; Social classes; Social conditions; Sociologie historique

The Fire-Dwellers - Laurence, Margaret (New Canadian library, 1988)
Stacey MacAindra burns – to burst through the shadows of her existence to a richer life, to recover some of the passion she can only dimly remember from her past. The Fire-Dwellers is an extraordinary novel about a woman who has four children, a hard-working but uncommunicative husband, a spinster sister, and an abiding conviction that life has more to offer her than the tedious routine of her days. Margaret Laurence has given us another unforgettable heroine – human, compelling, full of poetry, irony and humour. In the telling of her life, Stacey rediscovers for us all the richness of the commonplace, the pain and beauty in being alive, and the secret music that dances in everyone’s soul. --Publisher's description
Keywords: Canada; Class Consciousness; Fiction; Pink-collar work; Social Class and Equality; Women

The Assault on Trade Union Freedoms: From Consent to Coercion Revisited - Panitch, Leo; Swartz, Donald (Garamond Press, 1988)
Part 1 is a revised version of From Consent to Coercion, and Part 2 represents a study of new developments since 1984, including the Supreme Court's crucial ruling that the Charter of Rights and Freedoms does not protect the right to strike. Contents: Preface to second edition -- 1. Introduction: From consent to coercion -- 2. The era of free collective bargaining -- 3. The turn to coercion: permanent exceptionalism -- 4. The right to strike: freedom of association and the Charter -- 5. The Mulroney record: consolidating the era of coercion -- 6. The consolidation of coercion in the provinces -- 7. The labour movement in the new era -- 8. The social contract: labour, the NDP and beyond -- Appendix I. Legislation and orders suspending the right to strike 1950-1993 -- Appendix II. Legislation amending trade union rights 1982-1993.
Keywords: Canada; History; Labor Unions; Law and legislation History

Militer dans son syndicat: les différences entre les femmes et les hommes à la C.E.Q. et à la C.S.N. - Sarrazin, Hélène; Tardy, Évelyne; Desrosiers, Guy (Université du Québec à Montréal, Centre de recherche féministe, 1988)
Ce livre ne représente qu'un aspect d'une vaste recherche sur les différences entre les femmes et les hommes dans des structures politiques: partis provinciaux, municipaux et central`es syndicales. En effect, ne son présentés ici que les résultats de la recherche portant sur le militantisme dans deux centrales syndicales du Québec soit: la Centrale des syndicats nationaux (C.S.N.) et la Centrale de l'éducation du Québec (C.E.Q.). --From Introduction
Keywords: Centrale de l'enseignement du Québec; Confédération des syndicats nationaux; Femmes dans les syndicats Québec (Province); Québec; Women labor union members; Women labor union members Québec (Province)

A Communist Life: Jack Scott and the Canadian Workers Movement, 1927-1985 - Scott, Jack (Past CCLH Publications, 1988)
This volume is a reprint of a special edition of the Canadian Journal of Sociology.The essays are gathered around two themes: the relationship of sociology and social history, and the intersection of gender, ethnicity, and region with class. Unlike most Canadian essay collections, the contributors and their subjects cover Canada from British Columbia to Newfoundland, with forays into Cape Breton and central Canada. The volume contains articles by Ian McKay, Gordon Darroch, James R. Conley, Alicja Muszynski, Gillian Creese, and Jim Overton. An interesting collection of some of the new work being done in Canada by historians and sociologists, Class, Gender, and Region reflects Charles Tilly's suggestion that "there should be no disciplinary division of labour: simply both doing social history." --Publisher's description
Keywords: Communism; Communists; History; Labor movement; Scott, Jack, 1910-2000

The Rise of Industrial Unionism in Canada: A History of the CIO [Congress of Industrial Organizations] - Taylor, Don; Dow, Bradley (Research and current issues series, 1988)
Chronicles the transformative impact of the Congress of Industrial Organizations (CIO) on Canada's labour movement and society. Discusses the shift from craft-based unions to industrial unionism, emphasizing the CIO's success in organizing workers across industries, securing collective bargaining rights, and improving wages, working conditions, and benefits. The CIO played a pivotal role in shaping Canada's social security system, advocating for universal health care, pensions, and unemployment insurance, while supporting the Co-operative Commonwealth Federation (CCF) to push for progressive policies. The CIO's innovative methods, such as education programs and political action, reshaped industrial relations and laid the foundation for modern labour rights in Canada.
Keywords: AFL-CIO; AFL-CIO -- History; American Federation of Labor and Congress of Industrial Organizations Histoire; Canada; Canadian Labour Congress; Canadian Labour Congress History; Congress of Industrial Organizations (U.S.); Congress of Industrial Organizations (U.S.) History; Congress of Industrial Organizations Histoire; Geschichte; Gewerkschaftsbewegung; History; Kanada; Labor unions; Labor unions Canada History; Syndicats Canada Histoire

Radical Rag: The Pioneer Labour Press in Canada - Verzuh, Ron (Steel Rail, 1988)
Canada's trade unions have long claimed a prominent place in the struggle for social democracy. From the earliest years of that struggle, the labour movement's press has been on the front lines. Radical Rag tells the colourful story of those pioneer days, recounting the war for social justice fiercely waged through the pages of labour's weekly newspapers.... --Publisher's description on book cover
Keywords: 1800-1899; Arbeiterpresse; Canada; History; Kanada; Labor movement; Labor movement Canada History 19th century; Mouvement ouvrier Canada Histoire 19e siècle; Press, Labor; Press, Labor Canada History 19th century; Presse ouvrière Canada Histoire 19e siècle; Travailleurs Canada Histoire 19e siècle; Working class; Working class Canada History 19th century

Workers, Capital, and the State in British Columbia: Selected Papers - Warburton, Rennie; Coburn, David (University of British Columbia Press, 1988)
This collection of essays offers a comprehensive examination of the working class experience in British Columbia and contains essential background knowledge for an understanding of contemporary relations between government, labour, and employees. It treats workers' relationship to the province's resource base, the economic role of the state, the structure of capitalism, the labour market and the influence of ethnicity and race on class relations. --Publisher's description
Keywords: Canada; Capitalism; Labour; Working class

Canadian Labour History: Selected Readings - Bercuson, David Jay (New Canadian readings, 1987)
Contents: Section 1. The era of industrialization. Ethnicity and class, transitions over a decade: Ontario, 1861-1871 / A. Gordon Darroch and Michael Ornstein -- Women and wage labour in a period of transition: Montreal, 1861-1881 / Bettina Bradbury -- The 1907 Bell Telephone strike: Organizing women workers / Joan Sangster -- Industry and the good life around Idaho Peak / Cole Harris -- Through the prism of the strike: Industrial conflict in Southern Ontario, 1901-14 / Craig Heron and Brian D. Palmer. Section 2. World War I and its aftermath. Munitions and labour militancy: The 1916 Hamilton Machinists' Strike / Myer Siemiatycki -- Company town/labour town: Local government in the Cape Breton Coal Towns, 1917-1926 / David Frank. Section 3. The rise of modern unionism. Strike in the single enterprise community: Flin Flon, Manitoba, 1914 / Robert S. Robson -- The 1943 steel strike against wartime wage controls / Laurel Sefton MacDowell. Section 4: Overviews. Unionization versus corporate welfare: The "Dofasco Way" / Robert Storey -- Labour and working class history in Canada: Prospects in the 1980s / Gregory S. Kealey -- Through the looking glass of culture: An essay on the new labour history and working class culture in historical writing / David J. Bercuson -- Further reading.
Keywords: Arbeiterbewegung; Aufsatzsammlung; Canada; Geschichte; Geschichte (1861-1987); History; Kanada; Travailleurs Canada Histoire; Working class; Working class Canada History

Three Dollar Dreams - Bowen, Lynne (Oolichan Books, 1987)
In 1980...[the author] was approached by Nanaimo's Coal Tyee Society to write a book based on 105 interviews of Vancouver Island coal miners and their families. Nanaimo coal mines had closed 30 years before and the city had been home to some of the most important coal mines in the world, along with the one of largest explosions in history, the 1887 Nanaimo mine explosion. The miners wanted their oral histories preserved. Bowen compiled those oral histories in her first book, Boss Whistle, and later book, Three Dollar Dreams. --From Wikipedia article on Lynne Bowen
Keywords: British Columbia Vancouver Island; Charbon Mines et extraction Colombie-Britannique Vancouver, Île de Histoire; Coal miners; Coal miners British Columbia Vancouver Island History; Coal mines and mining; Coal mines and mining British Columbia Vancouver Island History; History; Mineurs de charbon Colombie-Britannique Vancouver, Île de Histoire

Free Trade and the Future of Women's Work: Manufacturing and Service Industries - Cohen, Marjorie Griffin (Garamond Press, 1987)
This important book makes a major contribution to the free trade debate. It is the first study to examine the impact of free trade on specific groups of workers, and to analyze the effect on the service sector. --Publisher's description on book cover
Keywords: Women -- Employment -- Canada -- Forecasting

Waterfront Warlord: The Life and Violent Times of Hal C. Banks - Edwards, Peter (Key Porter Books, 1987)
The shocking true story of Canada’s most powerful and feared labour leader. His supporters called him a tough and effective leader; his opponents called him a vicious thug. For nearly two decades, Hal C. Banks ruled the nation’s waterfronts with an iron fist. As head of the communist-busting Seafarers’ International Union, he carved out his fiefdom with a combination of intimidation, blacklisting and brutality. Now, award-winning investigative reporter Peter Edwards brings the complete, shocking story of Hal C. Banks to print for the first time. From ex-con on the San Francisco waterfront to Canada’s most powerful labour boss – with influence that reached onto Parliament Hill itself – here is the unexpurgated truth behind the myths of a larger-than-life warlord whose name still incites fear and controversy even years after his death… and whose ability to break the law and get away with it is an outrageous and fascinating testament of evil in our time. --From author's website
Keywords: Banks, Hal, 1909-1985; Biographies; Canada; Criminals; Criminals Canada Biography; Criminels Canada Biographies; Labor unions Canada Officials and employees Biography; Labor unions Officials and employees; Labor unions Officials and employees Canada Biography; Seafarers' International Union of Canada; Seafarers' International Union of Canada Biography; Syndicat international des marins canadiens Biographies; Syndicats Canada Fonctionnaires Biographies; Syndicats Canada Personnel Biographies

Everything That Floats: Pat Sullivan, Hal Banks, and the Seamen's Unions of Canada - Kaplan, William (University of Toronto Press, 1987)
"I will soon be in the dubious position of being the top labor man in all of Canada," Hal Chamberlain Banks wrote home in April 1949, "but let me tell you that I now know that uneasy lies the head that wears a crown." Hal Banks, an ex-convict and representative of the Searfarers' International Union of North America, was by nature a boastful man, but there was more than a little truth to what he wrote. Financed by the shipping companies and assisted by the federal government, the Royal Canadian Mounted Police, and the Canadian National Railways Police, Banks, along with a small army of SIU strongmen imported from the United States, had, in a matter of months, waged and won a violent battle against the long-established national Canadian Seaman's Union. With only a few companies outside the SIU's orbit, Banks controlled the collective bargaining rights of almost every seaman employed on the Canadian flag fleet and, with an iron fist, would do so for more than a decade. Eventually Banks's activities would be investigated by a commission of inquiry and, facing imprisonment, he would be forced to flee Canada in disgrace. In 1949 the situation was much different. ...How and why Banks and the SIU arrived in Canada is the first part of this story. --Author's preface
Keywords: Banks, Hal; Banks, Hal, 1909-1985; Canada; Canada Shipping services Trade unions, 1935-1969; Canadian Seamen's Union; Canadian Seamen's Union History; History; Marins (Marine marchande) Syndicats Canada Histoire; Merchant mariners Labor unions; Merchant mariners Labor unions Canada History; Seafarers' International Union of Canada; Seafarers' International Union of North America; Seafarers' International Union of North America History; Sullivan, John Allan Patrick; Sullivan, John Allan Patrick, 1896-; Sullivan, Pat, 1893-; Syndicats Marins (Marine marchande) Canada Histoire; Union internationale des marins de l'Amérique du Nord

On the Archival Heritage of the Finnish Canadian Working-Class Movement: A Researcher's Guide and Inventory to the Finnish Organization of Canada Collection at the National Archives of Canada - Laine, Edward W. (Tutkimuksia (Siirtolaisuusinstituutti (Finland)), 1987)
Keywords: Archives publiques du Canada Catalogues; Bibliographies; Canada; Canada Mœurs et coutumes Sources Bibliographie Catalogues; Canada Social life and customs Sources Bibliography Catalogs; Canadiens d'origine finlandaise Canada Associations Histoire Sources Bibliographie Catalgues; Catalogs; Finnish Canadians Canada Societies, etc. History Sources Bibliography Catalogs; Finnish Organization of Canada Collection; Finnish Organization of Canada Collection Catalogs; Finnish Organization of Canada Collection Catalogues; Finns Canada Societies, etc. History Sources Bibliography Catalogs; History; Manners and customs Sources; Public Archives of Canada; Public Archives of Canada Catalogs; Travailleurs Canada Histoire Sources Bibliographie Catalogues; Working class Canada History Sources Bibliography Catalogs; Working class Sources

Solidarity: The Rise and Fall of an Opposition in British Columbia - Palmer, Bryan D. (New Star Books, 1987)
1983's powerful Solidarity movement, which for a time seemed capable of deflecting the Social Credit government of British Columbia from its neo-conservative course - or even toppling it - instead died with a whimper. In Solidarity: The Rise and Fall of an Opposition in British Columbia, the first book-length account of this pivotal point in the province's history, Bryan Palmer concludes that it was not Social Credit tactics, but the nature of Solidarity's leadership which foreordained the defeat. --Publisher's description

Emporium of the North: Fort Chipewyan and the Fur Trade to 1835 - Parker, James McPherson (Alberta Culture and Multiculturalism/Canadian Plains Research Center, 1987)
History of Fort Chipewyan, the first European settlement in Alberta, an important fur-trading centre, and a vital base for the exploration of the continent's hinterland. Traces the development of the Fort Chipewyan fur trade from 1778, when Peter Pond entered the region, until 1835, when the rivalry between the North West and Hudson's Bay companies was no longer a factor, and a monopoly in the fur trade had been restored. Provides a vivid portrayal of life in a remote fur trade outpost during this crucial period in Canadian history. --WorldCat summary/Publisher's description
Keywords: Alberta Fort Chipewyan; Athabasca, Lac (Sask. et Alb.) Histoire; Athabasca, Lake (Sask. and Alta.) History; Athabasca, Région du lac (Sask. et Alb.) Histoire; Canada Lake Athabasca; Canada, Alberta, Fort Chipewyan History; Fort Chipewyan (Alb.) Histoire; Fort Chipewyan (Alta.) History; Fourrures Commerce Athabasca, Lac (Sask. et Alb.) Histoire; Fourrures Commerce Athabasca, Région du lac (Sask. et Alb.) Histoire; Fur trade; Fur trade Athabasca, Lake (Sask. and Alta.) History; Fur trade Canada; History; Nord-Ouest canadien Histoire Jusqu'à 1870; Northwest, Canadian History To 1870

Bushworkers and Bosses: Logging in Northern Ontario, 1900-1980 - Radforth, Ian Walter (Social history of Canada, 1987)
The lumberjack – freewheeling, transient, independent – is the stuff of countless Canadian tales and legends. He is also something of a dinosaur, a creature of the past, replaced by a unionized worker in a highly mechanized and closely managed industry. In this far-ranging study of the logging industry in twentieth-century Ontario, Ian Radforth charters the course of its transition and the response of its workers to the changes. Among the factors he considers are technological development, changes in demography and the labour market, an emerging labour movement, new managerial strategies, the growth of a consumer society, and rising standards of living. Radforth has drawn on an impressive array of sources, including interviews and forestry student reports as well as a vast body of published sources such as The Labour Gazette, The Pulp and Paper Magazine of Canada, and The Canada Lumberman, to shed new light on trade union organization and on the role of ethnic groups in the woods work force. The result is a richly detailed analysis of life on the job for logging workers during a period that saw the modernization not only of the work but of relations between the workers and the bosses. --Publisher's description
Keywords: 20th century; History; Labor unions History; Loggers; Logging; Ontario; Technological innovations

Hard Bargains: My Life on the Line - White, Robert (McClelland and Stewart, 1987)
Bob White, president of the Canadian Auto Workers, is without a doubt the single most influential figure in the Canadian labour movement. Respected by workers and business leaders alike. White has become a major voice in national; affairs. All his life he has bargained hard, and more often that not, won.

Weaving New Ways: Farm Women Organizing - Wiebe, Nettie; National Farmers Union (Canada) (National Farmers Union, 1987)

Labour Law and Urban Law in Canada - Bernier, Ivan; Royal Commission on the Economic Union and Development Prospects for Canada; Lajoie, Andrée (Royal Commission on the Economic Union and Development Prospects for Canada. Collected Research studies, 1986)
Research studies for the Royal Commission on the Economic Union and Developments Prospects for Canada. Contents: The role of law in labour relations / Joseph M. Weiler -- The use of legislation to control labour relations: the Quebec experience / Fernand Morin and Claudine Leclerc -- Urban law and policy development in Canada: the myth and reality / S.M. Makuch.
Keywords: Canada. Collective labor agreements; Canada. Collective labor agreements. Labor laws and legislation; Labor laws and legislation; Québec (Province) Collective labor agreements; Québec (Province) Labor laws and legislation

Looking into My Sister's Eyes: An Exploration in Women's History - Burnet, Jean R. (Multicultural History Society of Ontario, 1986)
Collection of papers presented at the conference, Immigrant and Ethnicity in Ontario: An Exploration of Women's History, held at the University of Toronto, May 1985.
Keywords: Canada; Canada, Ontario Emigration and immigration; Canada, Ontario Minorities History; Conference papers and proceedings; Femmes issues des minorités Canada Histoire; Femmes issues des minorités Ontario Histoire Congrès; History; Immigrantes Canada Histoire Congrès; Immigrantes Ontario Histoire Congrès; Minority women; Minority women Canada History; Minority women Ontario History Congresses; Ontario; Ontario Emigration and immigration History Congresses; Women Ontario History; Women immigrants; Women immigrants Canada History Congresses; Women immigrants Ontario History Congresses

A Class Act: An Illustrated History of the Labour Movement in Newfoundland and Labrador - Gillespie, Bill (Newfoundland and Labrador Federation of Labour, 1986)
Working people seldom make it into the history books, and when they do the picture is seldom flattering. Too often, ordinary Newfoundlanders have been cast as a race of cap-doffers and forelock-tuggers. In this book Bill Gillespie confrnts the myth. He tells the story of that most important of working class institutions - the trade union. And as the story unfolds, a new cast of characters is introduced to our written history. They are the men and women who struggled within an economic system they did not control to improve the lives of their families and their class. Gillespie records their losses and their victories, their weaknesses as well as their strengths. Ultimately he records their success. It is the story of how Newfoundlanders surprised even themselves and turned their tiny country into the most unionized corner of North America. --Publisher's description
Keywords: History; Labor Unions; Newfoundland and Labrador

Fighting Heritage: Highlights of the 1930s Struggle for Jobs and Militant Unionism in British Columbia - Griffin, Sean (Tribune Publishing, 1986)
Keywords: 1900-1999; British Columbia; Grèves et lock-out Colombie-Britannique Histoire 20e siècle; History; Labor unions; Labor unions British Columbia History 20th century; Strikes and lockouts; Strikes and lockouts British Columbia History 20th century; Syndicats Colombie-Britannique Histoire 20e siècle; Travailleurs Colombie-Britannique Histoire 20e siècle; Working class; Working class British Columbia History 20th century

The Character of Class Struggle: Essays in Canadian Working-Class History, 1850-1985 - Palmer, Bryan D.; McKay, Ian; Heron, Craig; Maroney, Heather Jon; Webber, Jeremy; Brandt, Gail Cuthbert; Kealey, Gregory S. (Canadian social history series, 1986)
These essays introduce readers to the changing and complex character of class struggle in Canada. Individual essays focus on specific features of Canadian class struggle: regional differences, the role of gender, the character of trade union leadership to the specific nature of conflict in particular industries; and the general features of national periods of upheaval such as the year 1919 and the World War II period. [Of the eight essays, two are original to the volume, while the others are abridged or revised versions of articles that previously appeared in publications such as Labour/Le Travail and New Left Review.] --Publisher's description
Keywords: 19th century; 20th century; Canada; History; Labor disputes; Social conflict; Working class

Shipping and Shipbuilding in Atlantic Canada, 1820-1914 - Sager, Eric W.; Fischer, Lewis R. (Historical Booklet / Canadian Historical Association, 1986)

Union Sisters: Women in the Labour Movement - Briskin, Linda; Yanz, Lynda; Adams, Jane; Attenborough, Susan; Colley, Susan; Cumsille, Alejandra; Darcy, Judy; David, Françoise; David, Hélène; Egan, Carolyn; Epstein, Rachel; Field, Debbie; et al. (Women's Press, 1985)
Women's activism in unions has increased dramatically in the last decade, creating a sense of renewed vitality and excitement in the trade union movement. Union Sisters is a attempt to document the struggles and victories of the movement of union women as well as to provide some direction to women and unions as they fight to defend the interests of working people. --Introduction

Lectures in Canadian Labour and Working-Class History - Committee on Canadian Labour History; Cherwinski, W. J. C. (Walter Joseph Carl); Kealey, Gregory S. (Past CCLH Publications, 1985)
In 1983 and 1984 the Canadian Studies Program of the Secretary of State funded four lecture series at Canadian universities on the history of the Canadian working class. This volume presents many of the lectures in a published version. Ranging from east to west and covering two centuries of Canadian labour history, the volume includes a selection of essays by some of Canada's leading social historians including Michael Cross, David Frank, Ross McCormack, Bryan Palmer and Joy Parr. Outstanding participants in the making of Canadian labour history Eugene Forsey and H. Landon Ladd have also contributed. Directed at a popular audience these fourteen lectures provide a major survey of Canada's labour past. --Publisher's description
Keywords: Canada; History; Labor; Labor Unions; Labor movement; Working class

Pre-industrial Canada, 1760-1849 - Cross, Michael S.; Kealey, Gregory S. (Readings in Canadian social history, 1985)
...This volume presents a selection of scholarly articles designed to introduce the student to currents of social change and development in Canada from 1760 to 1849. With contributions by such respected academic writers as Harold Adams Innis, Judith Fingard, and Sylvia Van Kirk, it provides valuable insights into the role of the working class, violence and protest, class conflicts, and the economic structure of a newly developing nation. --Publisher's description
Keywords: 1800-1899; Canada; Canada Conditions sociales 19e siècle; Canada Conditions économiques 19e siècle; Canada Economic conditions 19th century; Canada Social conditions 19th century; Economic history; Social conditions

A History of the Newfoundland Teachers' Association, 1890-1930 - Cuff, Harry Alfred (Creative Publishers, 1985)
Keywords: Newfoundland Teachers' Association -- History

The Politics of Work in the West: Historical and Contemporary Perspectives - Dickinson, Harley D.; Russell, Bob (Social Research Unit, Dept. of Sociology, University of Saskatchewan, 1985)
Keywords: Conference papers and proceedings; History; Labor policy; Labor policy Prairie Provinces Congresses; Prairie Provinces; Travail Politique gouvernementale Provinces des Prairies Congrès; Travailleurs Provinces des Prairies Congrès; Travailleurs Provinces des Prairies Histoire Congrès; Working class; Working class Prairie Provinces Congresses; Working class Prairie Provinces History Congresses

"We Were the Salt of the Earth!": A Narrative of the On-to-Ottawa Trek and the Regina Riot - Howard, Victor (Canadian plains studies, 1985)
The Regina Riot, which erupted in that city's Market Square on July 1, 1935, was the climax of a strike by relief camp workers which had begun in British Columbia on April 4. After lingering two months in Vancouver, the participants struck out east by freight train, on to Ottawa, where they intended to tell the Government of Canada that the situation of the unemployed had become intolerable. The origins of the Strike, the Trek, and the Riot -- the character of those events -- are what this book is all about. It is a narrative, composed from federal, provincial and municipal records, from news reports, from interviews with participants, from sworn testimony, from photographs, from maps, from sawn-off baseball bats. It is the story of an event which figured prominently, at the same instant, in the history of the Canadian worker, in the history of the Canadian radical, in the histories of two Canadian cities and in the history of R. B. Bennet's Depression years government. --Publisher's description
Keywords: 1900-1999; Abris pour travailleurs Canada; Abris pour travailleurs Canada Histoire 20e siècle; Aufruhr; Canada; Canada Conditions économiques 1918-1945; Canada Economic conditions 1918-1945; Canada Histoire 1914-1945; Canada History 1914-1945; Canada Unemployed persons Protest 1921-1935; Chômage Canada Histoire; Chômeurs Canada Histoire 20e siècle; Crise économique (1929) Saskatchewan (Canada); Crises économiques 1929 Canada; Depressions; Depressions 1929 Canada; Economic history; Grèves et lock-out Canada Histoire 20e siècle; Grèves et lock-out Saskatchewan (Canada); History; Labor camps; Labor camps Canada; Labor camps Canada History 20th century; On to Ottawa Trek; Regina; Regina (Sask.) History 20th century; Riots; Riots Saskatchewan Regina History 20th century; Saskatchewan Regina; Strikes and lockouts; Strikes and lockouts Canada History 20th century; Travailleurs Activité politique Canada Histoire; Travailleurs Activité politique Canada Histoire 20e siècle; Unemployed; Unemployed Canada History 20th century; Unemployment; Unemployment Canada History; Working class Political activity; Working class Political activity Canada History; Working class Political activity Canada History 20th century; Émeutes Saskatchewan Regina

Let Us Rise! A History of the Manitoba Labour Movement - Smith, Doug (New Star Books, 1985)
Contents: 1881-1914: The Age of the Craftsman -- 1914-1919: "No More Defeats" -- 1920-1930: Dress Rehearsal for a Depression -- 1930-1940: Reaching the Breaking Point -- 1940-1960: A System on Trial -- 1960-1984: New Strengths, New Challenges.
Keywords: Canada; History; Labour Movement; Manitoba

Mine Mill: The History of the International Union of Mine, Mill, and Smelter Workers in Canada Since 1895 - Solski, Michael; Smaller, John (Steel Rail, 1985)
Chronicles Mine Mill's US origins in the Western Federation of Miners, the WFM organization in Western Canada, and the union's arrival in Northeastern Canada, including Kirkland Lake and Sudbury Local 598.

Modern Canada, 1930-1980's - Cross, Michael S.; Kealey, Gregory S. (Readings in Canadian social history, 1984)
[This book] is the last of a 5-volume series of readers designed to present an overview of Canada's social history, encompassing such topics as economic development, social structure, protest and violence, social control, work and workers, and the changing role of women. In this volume the editors have commissioned a collection of original essays designed to provide a scholarly response to the vital questions: "Who are we as a people? How did we become what we are?" The extent and influence of foreign ownership in the post-war world is examined by Paul Phillips and Stephen Watson. David Wolfe chronicles the emergence of the welfare state after the war and its recent decline. Michael Behiels explores the ideological tensions among federalist, nationalist, and socialist intellectuals in Quebec and Canada. Ruther Pierson and Marjorie Cohen discuss sexual bias in federal manpower policies in depression, war, and reconstruction. The struggles of labour, management, and government are examined in articles by Wayne Robert and John Bullen, and by Wallace Clement. And the education system as a instrument of social control is the subject of Paul Axelrod's essay. --Publisher's description
Keywords: Aufsatzsammlung; Canada; Canada - Conditions sociales - 20e siècle; Canada - Conditions économiques - 20e siècle; Canada - Histoire - 20e siècle; Canada Conditions sociales; Canada Conditions économiques 1918-1945; Canada Conditions économiques 1945-; Canada Conditions économiques 20e siècle; Canada Economic conditions 1918-1945; Canada Economic conditions 1945-; Canada Economic conditions 20th century; Canada Social conditions; Economic history; Economic, Social, and Cultural History of North America; Economische, sociale en cultuurgeschiedenis van Noord-Amerika; Kanada; Since 1918; Social conditions; Sozialgeschichte 1930-1980; canada; geschiedenis; historical records; historische verslagen; history; social change; social processes; sociale processen; sociale verandering

The Subarctic Fur Trade: Native Social and Economic Adaptations - Krech, Shepard (University of British Columbia Press, 1984)
Contains six papers originally presented at the 1981 annual meeting of the American Society for Ethnohistory. These papers cover various aspects of Native economic and social adaptations in the context of the Canadian fur trade in the period ranging from the 17th century up to and including the 20th century. --Publisher's description. Contents: Periodic shortages, native welfare, and the Hudson's Bay Company, 1670-1930 / Arthur J. Ray -- The first century / Charles A. Bishop -- Economic and social accommodations of the James Bay Islanders to the fur trade / Toby Morantz -- Sakie, Esquawenoe, and the foundation of a dual-native tradition at Moose Factory / Carol M. Judd -- The trade of the Slavey and Dogrib at Fort Simpson in the early nineteenth century / Shepard Krech III -- The microeconomics of Southern Chipewyan fur-trade history / Robert Jarvenpa and Hetty Jo Brumbach.
Keywords: Conference papers and proceedings; Fourrures Commerce Canada (Nord) Histoire; Fourrures Commerce Canada (Nord) Histoire Congrès; Fur trade; Fur trade Canada, Northern History; Fur trade Canada, Northern History Congresses; History; Indians of North America Canada, Northern Economic conditions Congresses; Indians of North America Commerce; Indians of North America Commerce Canada, Northern History Congresses; Indians of North America Economic conditions; Indiens Amérique du Nord Canada (Nord) Commerce; Indiens d'Amérique Canada (Nord) Conditions économiques Congrès; Indiens d'Amérique Conditions économiques; Kanada (Nord); Kanada Nord; Kongress; Kongress Glyndwr Williams 1980; Native peoples Canada, Northern Economic conditions; Native peoples Commerce Canada, Northern; Northern Canada; Pelzhandel

Not Just Pin Money: Selected Essays on the History of Women's Work in British Columbia - Latham, Barbara; Pazdro, Roberta Jane (Camosun College, 1984)
Contents: Part 1. A Contrasting Regional Perspective: Conrad, Margaret; 'Sundays always make me think of home': time and place in Canadian women's history. Part 2: Native Women: 1. Mitchell, Marjorie and Anna Franklin; When you don't know the language, listen to the silence: An historical overview of Native Indian women in B.C. [First Nations women] -- 2. Ravicz, Marilyn and Diane Battung and Laura Buker; Rainbow women of the Fraser Valley: lifesongs through the generations. Part 3. Asian Women: 1. Adilman, Tamara; A preliminary sketch of Chinese women and work in British Columbia, 1858-1950 -- 2. van Dieren, Karen; The response of the WMS to the immigration of Asian women 1888-1942 -- 3. Doman, Mahinder Kaur; A note on Asian Indian women in British Columbia, 1900-1935. Part 4. Gentlewomen: 1. Gresko, Jascqueline; 'Roughing it in the Bush' in British Columbia: Mary Moody's pioneer life in New Westminister, 1859-1863 -- 2. Pazdro, Roberta; From pastels to chisel: the changing role of BC women artists -- 3. Barber, Marilyn; The gentlewomen of Queen Mary's Coronation Hostel. Part 5. Education: 1. Riley, Barbara; Six saucepans to one: domestic science vs. the home in British Columbia, 1900-1930 -- 2. Stewart, Lee; Women on campus in British Columbia: strategies for survival, years of war and peace, 1906-1920 -- 3. Small, Marion; Postscript: women in whose honour BC schools have been named. Part 6. Unpaid Workers. 1. Weiss, Gillian; The brightest women of our land: Vancouver clubwomen 1919-1928 -- 2. Dennison, Carol; They also served: the British Columbia Women's Institutes in two world wars -- 3. MacQuuen, Bonnie; Domesticity and discipline: the Girl Guides in British Columbia, 1910-1943 -- 4. Ogg, Kathryn; 'Especially when no one agrees': an interview with May Campbell. Part 7. Social Legislation: 1. Davies, Megan; 'Services rendered, rearing children for the state': Mothers' pensions in British Columbia, 1919-1931 -- 2. Matters, Indiana; Sinners or sinned against? historical aspects of female juvenile delinquency in British Columbia. Part 8. Labour and Auxiliaries: 1. Bernanrd, Elaine; Last back: folklore and the telephone operators in the 1919 Vancouver general strike -- 2. Diamond, Sara; A union man's wife: the Ladies Auxiliary Movement in the IWA, the Lake Cowichan experience.[1930s] -- 3. Bannerman, Josie and Kathy Chopik and Ann Zurbrigg; Cheap at half the price: the history of the fight for equal pay in BC. Part 9. Health: 1. Whittaker, Jo Ann; The search for legitimacy: nurses' registration in British Columbia , 1913-1935 -- 2. Bishop, Mary F.; Vivian Dowding: birth control activist 1892 [contraceptive use in British Columbia] -- 3. Lewis, Norah L.; Reducing maternal mortality in British Columbia: an educational process. Part 10. Politicians: 1. Norcross, Elizabeth; Mary Ellen Smith: the right women in the right place at the right time [1863-1933; first woman in any provincial legislature in Canada, first female cabinet minister in the British Empire in 1921 'minister without portfolio' -- 2. Walsh, Susan; The peacock and the guinea hen: political profiles of Dorothy Gretchen and Grace MacInnis. [Dorothy Gretchen Steeves, 1891-1970 and Grace MacInnis 1905-1991; BC's first female member of parliament] -- 3. Proom, Juliette; Tilly Jean Rolston: she knew how to throw a party. [1887-1953, first woman cabinet minster with portfolio in Canada, Education minister in W.A.C. Bennett's first cabinet] -- 4. Carter, Connie and Eileen Daust; From home to house: women in the BC legislature. Part 11. World War Two: 1. Wade, Susan; Joan Kennedy and the British Columbia Women's Service Corps -- 2. Turnbull, Elsie G.; Women at Cominco during the Second World War.
Keywords: 1800-1999; British Columbia; Femmes Colombie-Britannique Histoire 19e siècle; Femmes Colombie-Britannique Histoire 20e siècle; History; Women; Women British Columbia History 19th century; Women British Columbia History 20th century; Women Employment; Women Employment British Columbia History

The Language of the Skies: The Bilingual Air Traffic Control Conflict in Canada. - Borins, Sandford F (McGill-Queen's University Press, Institute of Public Administration of Canada., 1983)
[This book] chronicles one of the most bitter crises in French-English relations in Canada: the bilingual air traffic control conflict which arose in the mid-1970s when francophone controllers and pilots attempted to use French, as well as English, in Quebec aviation. [Summary: Worldcat record]

Boss Whistle: The Coal Miners of Vancouver Island Remember - Bowen, Lynne (Oolichan Books, 1983)
In 1980...[the author] was approached by Nanaimo's Coal Tyee Society to write a book based on 105 interviews of Vancouver Island coal miners and their families. Nanaimo coal mines had closed 30 years before and the city had been home to some of the most important coal mines in the world, along with the one of largest explosions in history, the 1887 Nanaimo mine explosion. The miners wanted their oral histories preserved. Bowen compiled those oral histories in her first book, Boss Whistle, and later book, Three Dollar Dreams. --From Wikipedia biography of Lynne Bowen
Keywords: British Columbia Vancouver Island; Charbon Mines et extraction Colombie-Britannique Vancouver, Île de Histoire; Coal miners; Coal miners British Columbia Vancouver Island History; Coal mines and mining; Coal mines and mining British Columbia Vancouver Island History; Grèves et lock-out Mines de charbon Colombie-Britannique Vancouver, Île de Histoire; History; Mineurs de charbon Colombie-Britannique Vancouver, Île de Histoire; Strikes and lockouts Coal mining; Strikes and lockouts Coal mining British Columbia Vancouver Island History

The Lockeport Lockout: An Untold Story in Nova Scotia's Labour History - Calhoun, Sue ([Published independently with a grant from Oxfam Canada, Atlantic region], 1983)
In the fall of 1939, more than 600 fishermen and fish handlers in the tiny town of Lockeport, Nova Scotia (pop. 1,400) walked the picket line in front of the town's only employers, Swim Brothers and the Lockeport Company. Both fishplants had locked their doors rather than recognize the Canadian Fishermen's Union as the official bargaining agent. The Fishermen's Union was an affiliate of the Canadian Seamen's Union, which had begun organizing along the shore. For eight weeks, as autumn turned to winter, the men, with their wives and families, held firm. It was a bread-and-butter struggle that made national headlines - one of the first attempts by Nova Scotia fishermen and fish handlers to win union recognition. It was one of the first major tests of N.S. Trade Union Act passed in 1937. This is the story of the Lockeport lockout of 1939. --Introduction
Keywords: Strikes and lockouts -- Fisheries -- Nova Scotia -- Lockeport -- History

Economy and Society During the French Regime, to 1759 - Cross, Michael S.; Kealey, Gregory S. (Readings in Canadian social history, 1983)
...As an introduction to the birth and growth of society in New France, the scholarly articles contained in the volume draw from the translated writings of Marcel Trudel and Fernand Ouellet, two of French Canada's leading historians. As well, contributions from Bruce Trigger and Calvin Martin look at the impact of European society on the culture of Native peoples. Together with articles on land use and labour, this informative volume offers a discerning view of the earliest of French Canada - the life of the habitant, the raucous beginning of the first craft brotherhoods, the movement toward a new social order which early European inhabitants took to with a "missionary zeal." By exploring the social roots of modern day Quebec [the book] sheds new light on our understanding of French Canada. --Publisher's description
Keywords: Canada; Canada Conditions sociales Jusqu'à 1763; Canada Conditions sociales Jusqu'à 1867 Discours, essais, conférences; Canada Conditions économiques Jusqu'à 1763; Canada Conditions économiques Jusqu'à 1867 Discours, essais, conférences; Canada Economic conditions To 1763; Canada Economic conditions To 1867; Canada Social conditions To 1763; Canada Social conditions To 1867; Economic history; Kanada; Social conditions; Sozialgeschichte 1642-1759; To 1763

The Consolidation of Capitalism, 1896-1929 - Cross, Michael S.; Kealey, Gregory S. (Readings in Canadian social history, 1983)
[This book] is the fourth of a five-volume series of readers designed to present an overview of Canada's social history, encompassing such topics as economic development, social structure, politics, religion, work and workers, and the changing role of women. In this volume the editors have assembled a series of scholarly essays examining such historic developments as government support of big business and the concentration of capital, the decline of craft unionism in Hamilton factories, the business impetus behind municipal reform, and the circumstances for working women in the 1920s. Articles such as Donald Avery's account of labour exploitation in the hiring of "foreign" navvies to build railroads in Western Canada and Don Macgillivray's analysis of state intervention and the use of troops in strikes among Cape Breton miners and steel workers in the 1920s highlight the issues and controversies which makes this one of the most telling chapters of Canada's social history. --Publisher's description
Keywords: 1918-1945; Aufsatzsammlung; Canada; Canada Conditions sociales; Canada Conditions sociales 1867-1918; Canada Conditions sociales 1918-1930; Canada Conditions économiques; Canada Conditions économiques 1867-1918; Canada Conditions économiques 1918-1945; Canada Economic conditions; Canada Economic conditions 1867-1918; Canada Economic conditions 1918-1945; Canada Social conditions; Canada Social conditions 1867-1918; Canada Social conditions 1918-1930; Economic history; Geschichte 1896-1929; Kanada; Social conditions; Sozialgeschichte 1896 - 1929; Wirtschaft

Partners in Furs: A History of the Fur Trade in Eastern James Bay, 1600-1870 - Francis, Daniel; Morantz, Toby (McGill-Queen's University Press, 1983)
In this innovative study the authors investigate the effects of the fur trade on the social patterns of the Algonquian peoples living in the Eastern James Bay region from 1600 to 1870. Of central concern are the problem areas of winter hunting arrangements, land tenure system, and patterns of leadership; but historical setting, ecological factors, and the relations of the Algonquians to other groups are also discussed. The patterns and course of contact between traders from Europe and the Indian populations are described and both English and French sources are used to reveal the competition between the two groups of traders and its impact on the native people. As the Hudson's Bay Company was the one permanent European presence during the period, this ethnohistorical study makes extensive use of unpublished HBC papers. The authors also examine such issues as the rise of a homeguard population at the trading posts, the trading captain system, the development of hamily hunting territories, and the issue of dependence and interdependence. Partners in Furs provides new insight and makes a significant contribution to current scholarly inquiry into the impact of the fur trade on the native populations. --Publisher's description

Working in Canada - Johnson, Walter (Black rose books, 1983)
This book is a collection of experiences written by workers, or based on interviews with them, about what they do and feel daily and what they think needs to be done to change their condition and that of other workers. --Publisher's description
Keywords: Canada; Sociologie industrielle Discours, essais, conférences; Travail Canada Discours, essais, conférences; Travailleurs Canada; Travailleurs Canada Discours, essais, conférences; Work; Working class; Working class Canada; labor

Traces of Magma: An Annotated Bibliography of Left Literature - Knight, Rolf (Draegerman, 1983)
An annotated bibliography of left wing novels about the lives of working people during the 20th century. Includes some collections of poetry, drama and short stories as well as a smattering of non-fictional material such as oral and life histories. Includes over 3,000 titles originally in some 50 languages by circa 1,500 authors from over 90 countries. --Publisher's description

"Remember Kirkland Lake": The History and Effects of the Kirkland Lake Gold Miners' Strike, 1941-42 - MacDowell, Laurel Sefton (Heritage, 1983)
On 18 November 1941, the gold miners of Kirkland lake struck for union recognition. The Kirkland Lake strike was a bitter struggle between the mine operators and their employees and became a national confrontation between the federal government and the labour movement over the issue of collective bargaining. Locally, the dispute was affected by the company-town environment and by the mine operators' paternalistic view of labour relations. Through the difficult winter womenths, the community -- polarized by the events -- tried to deal with both the 'political' and social impact of the conflict. The author's father, Larry Sefton, emerged as one of the local leaders of the strike, which itself was a training ground for many future trade unionists. The strike was waged in the special circumstances of the war economy, and was a microcosm of wartime developments, which produced unprecedented union growth, serious industrial unrest, hostile management response, and generally antagonistic labour/government relations. Professor MacDowell shows that, even though the strike was lost, its eventual effect on labour policy gave the dispute its particular significance. To win the strike, government intervention and the introduction of collective bargaining were necessary, yet the only intervention was by the Ontario Provincial Police, who were ordered to assist the mining companies to operate with strike-breakers. The federal government refused to intervene, in spire of virtually unanimous support for the strike by the Canadian labour movement. MacDowell confludes that the strike succeeded in unifying organized labour behind the demand for collective-bargaining legislation. It highlighted the inadequacy of the government's wartime labour poilcy, and ultimately forced the government to authorize collective bargaining, first for Crown companies and then for all industrial workers. Thus, the Kirkland Lake strike was not only an important wartime dispute affecting policy development, but it also established a special legacy for trade unionists as part of the history of their movement. --Publisher's description
Keywords: Gold Miners' Strike, Kirkland Lake, Ont., 1941-1942

Unequal Beginnings: Agriculture and Economic Development in Quebec and Ontario until 1870 - McCallum, John (State and economic life, 1983)
By the time of Confederation Ontario's economic lead over Quebec had been well established. John McCallum shows that the origins of this lead had little to do with the conservatism of the habitants and the church in Quebec, little to do with any anti-industrial bias of the Montreal merchants, and nothing to do with Confederation. Rather the origins lay in the wealth provided by Ontario's superior agricultural land.During much of the first part of the nineteenth century Ontario farmers were more specialized in wheat-growing than the twentieth-century farmers of Saskatchewan, and when the market conditions changed in the 1860s the province was able to use the capital derived from wheat to shift to other lines of production. The Quebec farmers, lacking both the virgin land of Ontario and the growing markets of the northeastern United States, were unable to find profitable substitutes for wheat. As a result, the cash income of the average Ontario farmer was at least triple that of his Quebec counterparts in the years before Confederation, and this enormous difference had profound effects on economic development in other sectors of the economy.In Ontario the growth of towns, transportation facilities, and industry was inextricably linked to the province's strong agricultural base. In Quebec little development occurred outside Montreal and Quebec City. Montreal industrialists did have several advantages; yet Quebec industry could not possibly absorb the province's surplus farm population. Ontario's wheat boom provided the capital which permitted Ontario industry to evolve in the classic fashion; indeed, Ontario wheat may be a rare instance of a staple whose surplus was retained in the producing area.John McCallum's analytical and historical account of economic patterns that persist today makes a solid and original contribution to Canadian economic history. --Publisher's description. Contents: Preface -- Introduction -- The rise and fall of the Ontario wheat staple -- The agricultural crisis in Quebec -- Agricultural transformation in Quebec and Ontario, 1850-70 -- Urban and commercial development until 1850 -- Transportation -- Industrial development, 1850-70 -- A modified staple approach -- Merchants and habitants -- Statistical appendix -- Subject index -- Index of authors cited.

The Company Store: James Bryson McLachlan and the Cape Breton Coal Miners, 1900-1925 - Mellor, John (Doubleday Canada, 1983)
The devastating story of the Cape Breton miners and the strikes they launched against the companies that owned their homes, their possessions, and their churches. Never before has the human drama of North America's last existing feudal system been written down for the general reader. Canadians - and the rest of the world - will shocked by the stories of police brutality and murder, mass demonstrations, rebellions, scandalouos politicking, and most of all, desperate poverty and hunger. The miners had always been paid starvation wages by companies that held total monopolies of such towns as Glace Bay. The first time they launched a strike in 1905, soldiers were brought in and machine guns and barbed wire were set up around the mining communities. Credit was cut off from company stores (the only stores). Miners were evicted from company-owned houses (the only houses) in the middle of winter. The death toll was enormous. Strikes over the next fifteen years simply led to continued harassment and eviction. At one time, the company was permitted, by government order, to employ hundreds of special police, mounted on horseback and supplied with guns and heavy sticks, to batter miners into submission. James Bryson McLachlan was the hero of the Cape Bretoners when he took up their cause and organized the strikers and entered into negotiations with the companies. This book is also his story - and the story of the beginning of the labour movement for all of Canada. --Publisher's description
Keywords: McLachlan, James Bryson, 1869-1937

Working-Class Experience: The Rise and Reconstitution of Canadian Labour, 1800-1980 - Palmer, Bryan D. (Butterworth, 1983)
Working Class Experience is a sweeping and sympathetic study of the development of the Canadian working class since 1800. Beginning with a substantial and provocative introduction that discusses the historiography of the Canadian working class, the book goes on to establish a general framework for analysis of what ultimately is a social history of Canada. Dividing the years into seven periods in the evolution of class struggle, it beings each chapter with an assessment of that period's prevailing economic and social context, followed by an examination of the many factors affecting the working class during that period. Written in a colourful and sometimes irreverent style, Working Class Experience focuses on the processes by which working people moved, and were moved, off the land and into the factories and other workplaces during the Industrial and post-Industrial Revolutions in Canada. Drawing on much recent work on contemporary capitalism, Working Class Experience offers a significant explanation of the malaise in current labour and management relations and speculates on its significance for progressive change in Canadian Life. --Description at Goodreads
Keywords: Working class -- Canada -- History -- 19th century

Women and Work: Inequality in the Labour Market - Phillips, Paul Arthur; Phillips, Erin (Lorimer, 1983)
Why are women still second class citizens at work? Recent years have seen demands by the women's movement for equality in the workplace, and "affirmative action" programs have been set up to achieve this goal. Yet little has really changed. Women still earn less than men, are underrepresented in unions, have less protection in pension plans, and are usually stuck in jobs with little chance of advancement. To understand women's inequality at work, Paul and Erin Phillips trace women's involvement in the paid labour market, and in labour unions, throughout Canadian history. They document the disadvantages that women face today and examine the explanations for the existence of these problems. --Publisher's description
Keywords: Women -- Employment -- Canada

Mining Photographs and Other Pictures, 1948-1968: A Selection from the Negative Archives of Shedden Studio, Glace Bay, Cape Breton - Shedden, Leslie (Press of the Nova Scotia College of Art and Design, 1983)
With essays by Donald Macgillivary and Allan Sekula and editing by Benjamin Buchloh and Robert Wilkie, this volume published a major selection from the photographic archives of Leslie Shedden, a local photographer active from the 1940s to the 1960s in Glace Bay, Nova Scotia. Besides his daily and common functions as a community photographer (portraits, advertising, work and school events, architecture), Leslie Shedden continuously worked on documentation of the working conditions in the coal and iron mines of Cape Breton. The photographic documentation was commissioned by the local coal mining corporation, which gave him access to the underground mines as well as to all other work areas. All major aspects of the mining activities, the conditions of manual labour, and the gradual transformation to mechanized mining are recorded in systematic and detailed photographs. An equally detailed systematic body of photographs recording the family and community life of the miners complements the body of photographic images documenting the labour conditions in one of the oldest North American coal mining districts.
Keywords: Nova Scotia -- Glace Bay

Women and Part-Time Work - White, Julie (Canadian Advisory Council on the Status of Women, 1983)
Keywords: Part-time employment -- Canada

Canada's Age of Industry, 1849-1896 - Cross, Michael S.; Kealey, Gregory S. (Readings in Canadian social history, 1982)
...This volume presents a series of scholarly articles which range from an essay by Gregory Kealey on Toronto's Industrial Revolution in the last half of the nineteenth century to a fascinating study by Wendy Mitchener of the Women's Christian Temperance Union, "A Study of Nineteenth-Century Feminism." Also included are examinations of the working class, violence and protest, social structure and government encouragement of industrial development from 1849 to 1896. --Publisher's description
Keywords: Aufsatzsammlung; Canada; Canada Conditions sociales 1867-1918; Canada Conditions sociales 19e siècle; Canada Conditions sociales Jusqu'à 1763; Canada Conditions économiques 1763-1867; Canada Conditions économiques 1867-1918; Canada Conditions économiques 19e siècle; Canada Economic conditions 1763-1867; Canada Economic conditions 1867-1918; Canada Economic conditions 19th century; Canada Industrialisation Socioeconomic aspects 1841-1911; Canada Social conditions 1867-1918; Canada Social conditions 19th century; Canada Social conditions To 1763; Economic history; Geschichte 1849-1896; History; Industrie Canada Histoire 19e siècle; Industries; Industries Canada History 19th century; Kanada; Social conditions; Sozialgeschichte 1849-1896; To 1899; Wirtschaft

Black Powder: Estevan 1931 - Deverell, Rex Kerr; Ursell, Geoffrey (Coteau Books, 1982)
Historical drama of the coal miners' strike and riot in Estevan, Saskatchewan, in 1931.
Keywords: Coal Miners' Strike, Estevan, Sask., 1931; Drama

Trade Unions in Canada, 1812-1902 - Forsey, Eugene Alfred (Heritage, 1982)
We are apt to think of labour unions as a feature of a relatively advanced industrial society. It comes as a surprise to many to learn how long ago in Canadian history they actually appeared. Unions already existed in the predominantly rural British North America of the early nineteenth century. There were towns and cities with construction workers, foundry workers, tailors, shoemakers, and printers; there were employers and employees - and their interests were not the same. From this beginning Dr Forsey traces the evolutions of trade unions in the early years and presents an important archival foundation for the study of Canadian labour. He presents profiles of all unions of the period - craft, industrial, local, regional, national, and international - as well as of the Knights of Labor and the local and national central organizations. He provides a complete account of unions and organizations in every province including their formation and function, time and place of operation, what they did or attempted to do (including their political activity), and their particular philosophies. This volume will be of interest and value to those concerned with labour and union history, and those with a general interest in the history of Canada. --Publisher's description
Keywords: 19th century; Canada; History; Industrial relations; Labor unions

1005: Political Life in a Union Local - Freeman, Bill (Lorimer, 1982)
Today the giant Stelco steel mills in Hamilton are shut down, but in Canada’s turbulent labour history it was a place of protracted conflict between the stubborn, anti-union management of the company and the equally stubborn and militant Local 1005 of the Steelworkers Union. The story is a fascinating one – a microcosm of the larger labour/management struggles in Canada. Among the events the book explores includes: the battle from 1919 to 1944 to establish a union in the face of hostile management; the struggle for supremacy at 1005 between Communist and CCF factions; the 1946 strike for union recognition which became the post war showdown in Canada between unions and management; and the chaotic 1966 wildcat strike that tore the union apart. The book tells the story of Local 1005 and at the same time explores the nature of political life in a local union, and the social and economic forces that shaped the politics of the local. This is a book that describes how working people struggled to improve their lives, and in the process changed the history of the trade union movement and the nature of Canadian political life. --Publisher's description

Dreaming of What Might Be: The Knights of Labor in Ontario, 1880-1900 - Kealey, Gregory S.; Palmer, Bryan D. (Cambridge University Press, 1982)
As Canada's most industrialised province, Ontario served as the regional centre of the Noble and Holy Order of the Knights of Labor, an organisation which embodied a late nineteenth-century working-class vision of an alternative to the developing industrial-capitalist society. The Order opposed the exploitation of labor, and cultivated working-class unity by providing an institutional and cultural rallying point for North American workers. By 1886 thousands of industrial workers had enrolled within the ranks of Ontario's local and district assemblies. This book examines the rise and fall of the Order, providing case studies of its experience in Toronto and Hamilton and chronicling its impact across the province. --Publisher's description
Keywords: Business & Economics / Labor / General; History / Europe / Renaissance

The Eaton Drive: The Campaign to Organize Canada's Largest Department Store, 1948 to 1952 - Sufrin, Eileen (Fitzhenry & Whiteside, 1982)
The Eaton Drive is the story of one of the most intensive and sustained organizing campaigns in Canadian labour history. With 30,000 employees, post-war Eaton's was the country's third largest employer, surpassed only by railways and the federal government. Because its stores and mail order operations extended across Canada, Eaton's influenced retail wages nationwide. Eaton's Toronto operations, dispersed over a dozen work location and embracing 16,000 employees at peak season, presented a formidable challenge to Local 1000 of the Retail Wholesale and Department Store Union and the Canadian Congress of Labour. When it applied for certification in October 1950, the Ontario Labour Relations Board was faced with the largest and most complex bargaining unit ever to come before it. The labour movement considered the success of the Eaton Drive central to removing the threat of a large, lower-paid, constantly shifting work force to their wage standards and supported it with unprecedented generosity. Eileen Tallman Sufrin, who was one of the organizers, describes the campaign from the union viewpoint in the hope that the insight it provides will assist retail workers in organizing in the future. --Publisher's description
Keywords: Labor unions -- Recognition

The Rise and Fall of the Toronto Typographical Union, 1832-1972: A Case Study of Foreign Domination - Zerker, Sally F. (Sally Friedberg) (University of Toronto Press, 1982)
This case study traces the development of the union which began as the Toronto Typographical Society. Through a close examination of this Canadian local's relations with its eventual parent organization in the US, Zerker reveals the 'domination' and brings into question the advantages of an international connection. A meeting of twenty-four journeymen printers at the York Hotel in Toronto in 1832 marked the birth of Canada’s earliest and still continuing labour organization. This case study of the printers of Toronto traces the development of the union which began as the Toronto Typographical Society. Through a close examination of this Canadian local’s relations with its eventual parent organization in the US, Zerker reveals the ‘domination’ and brings into question the advantages of an international connection. In 1866, under pressure from the American federation of printing unions, the Toronto body became an affiliate of the International Typographical Union, thus forming the crucial relationship which, as Zerker shows, came to govern every element of local decision and policy. Though the TTU achieved a pioneer victory in independently leading its members in their struggle for a shorter working day, from 1885 on the ITU directives and programs came to rule the Toronto union, causing enormous losses in membership and industry control. Zerker cites as examples the ITU program in the 1920s which resulted in a bitter strike which broke the Toronto union’s control of the labour force in the commercial sector; and, more recently, its misdirection of the printers’ strike of the Toronto newspapers in the 1960s which resulted in the expulsion of members from the workplaces that had been the preserve of the organization for nearly a century. Zerker blames the failure to respond effectively to the technology of the computer age on poor TTU management in pre-strike negotiations but, above all, on ITU intransigence, ignorance, and arrogance. In more recent years, after the end of this history, TTU membership has increased substantially and the local has been revitalized under its new leadership; the International, too, shows signs of being on the way to much-awaited reforms. This history is in many senses a microcosm of the Canadian labour movement and forms an important strand in general cultural history of Toronto. --Publisher's description
Keywords: Toronto Typographical Union

Labour Law and Industrial Relations in Canada - Arthurs, H. W. (Harry William); Carter, Donald; Glasbeek, Harry (Kluwer/Butterworths, 1981)
Originally published as a monograph in the International encyclopedia of labour law and industrial relations; Includes bibliographical references (page 52) and index
Keywords: Labor laws and legislation -- Canada

Sexual Harassment on the Job: How to Avoid the Working Woman's Nightmare - Backhouse, Constance; Cohen, Leah (Prentice-Hall, 1981)
This book, published in 1979, was the first book about sexual harassment to be published in Canada, and the second in North America. Quotation from the inside flap: If you thought women have finally become more accepted as real people with readier access to the conclaves of corporate power, read this book - you'll think again. Using statistical studies, interviews with executives and personnel managers, case studies, historical records, and court cases, Constance Backhouse and Leah Cohen show how pervasive sexual harassment is in the workplace. The authors provide us with a balanced and incisive understanding of what goes on. They also recommend ways to combat sexual harassment. Since this subject has till now been unexplored, avoided, and rife with myths and misinformation, this book is all the more important to our society. -- Author's website
Keywords: Harcèlement sexuel; Sex in the workplace; Sexual harassment of women; Sexualité dans les affaires; Sexualité en milieu de travail

Hardrock Mining: Industrial Relations and Technological Changes at Inco - Clement, Wallace (McClelland and Stewart, 1981)
Here is a hard-hitting look at Canada's wealthiest and most powerful mining company - the International Nickel Company of Canada. "Hardrock Mining" is the first in-depth study of both Inco Limited and the Canadian mining industry as a whole, an incisive look at both the effects of the technological revolution on a corporation and an industry which affects the lives of millions of Canadians. Respected sociologist Wallace Clement has interviewed hundreds of working men and women, and utilized unprecedented access to all facets of Inco's operations to build a fascinating and colourful portrait of a corporate giant. Clement documents the effect of the unions on the workers' welfare, the strikes and layoffs that are a fixture in the mining industry, and the effects of technological changes on health, safety, and the demand for specific skills. --Publisher's description
Keywords: Canada; Case studies; Inco Limited; Industrial relations; Industrial relations Canada Case studies; International Nickel Company; Nickel Mines et extraction Canada Cas, Études de; Nickel Mines et extraction Canada Études de cas; Nickel Mines et extraction Innovations Canada; Nickel mines and mining; Nickel mines and mining Canada Case studies; Nickel mines and mining Technological innovations Canada; Relations industrielles Canada Études de cas

All That Our Hands Have Done : A Pictorial History of Hamilton Workers - Heron, Craig; Roberts, Wayne; Storey, Robert H.; Hoffmitz, Shea (Mosaic Press in association with Office of Labour Studies, McMaster University, 1981)
The introduction to the memorable collection of photographs of Hamilton workers, All That Our Hands Have Done...announced: "Labour history is a new field. It demands new methods, new sources, new questions and new, mutual relations between researchers and their subjects." --From David Sobel, "Remembering Wayne Roberts, 1944-2021," Labour/Le travail, 87 (Spring 2021) 15.

Economic Inequality in Canada - Osberg, Lars (Butterworths, 1981)
The aim of this book is to present an up-to-date description of the extent of economic inequality in Canada and to outline existing theories as to its causes. and policies for its change. --Author's preface
Keywords: Income distribution -- Canada

Labour and Capital in Canada, 1650-1860 - Pentland, H. Clare (Harry Clare) (Lorimer, 1981)
First published in 1981, H. Clare Pentland's Labour and Capital in Canada, 1650-1860 is a seminal work that analyzes the shaping of the Canadian working class and the evolution of capitalism in Canada. Pentland's work focuses on the relationship between the availability and nature of labour and the development of industry. From that idea flows an absorbing account that explores patterns of labour, patterns of immigration and the growth of industry. Pentland writes of the massive influx of immigrants to Canada in the 1800s - taciturn highland Scots who eked out a meagre living on subsistence farms; shrewd lowlanders who formed the basis of an emerging business class; skilled English artisans who brought their trades and their politics to the new land; Americans who took to farming; and Irish who came in droves, fleeing the poverty and savagery of an Ireland under the heel of Britain. Labour and Capital in Canada is a classic study of the peoples who built Canada in the first two centuries of European occupation. --Publisher's description

Two Years on the Muckamuck Line - Potrebenko, Helen (Lazara Press / Service, Office, and Retail Workers’ Union of Canada, 1981)
Poetry.
Keywords: British Columbia Vancouver; Grèves et lock-out Restaurants Colombie-Britannique Vancouver Poésie; Muckamuck Restaurant Strike, 1978- Poetry; Poetry; Strikes and lockouts Restaurants; Strikes and lockouts Restaurants British Columbia Vancouver Poetry

Where Angels Fear to Tread: Eileen Tallman and the Labor Movement - Roberts, Wayne (Labor Studies, McMaster University, 1981)
Biography.
Keywords: 1900-1999; Biographies; Canada; History; Labor movement; Labor movement Canada History 20th century; Mouvement ouvrier Canada Histoire 20e siècle; Sufrin, Eileen; Women labor union members; Women labor union members Canada Biography

Histoire de la CSN: 1921-1981 - Rouillard, Jacques; Confédération des syndicats nationaux (Boréal Express : CSN, 1981)
La Confédération des syndicats nationaux, qui s'est appelée jusqu'en 1960 la Confédération des travailleurs catholiques du Canada (CTCC), et sans conteste l'une des institutions les plus importantes du Québec. Depuis sa fondation en 1921, elle a joué un rôle de tout premier plan, s'affirment à la fois comme un des mouvements organisés des travailleurs et travailleuses et un des principaux agent de transformation sociale. Au cours de son histoire, la CSN s'est toujours distinguée par sa volonté de réformer et profondeur la régime économique et d'instaurer une société plus juste, respecteuse de la dignité des travailleurs. Publié à l'occasion du 60e anniversaire de la CSN, ce livre ne se veut cependant pas une histoire officielle. Il a été écrit par une spécialiste de l'histoire des travailleurs et il s'adresse à ceux et celles qui s'intéressemt à cet aspect fondamental, pourtant encore largement méconnu de l'histoire du Québec. Sommaire de l'éditeur

Encyclopedia of Newfoundland and Labrador - Smallwood, Joseph R.; Story, George; Poole, Cyril (Memorial University, 1981)
The selection of topics for this Encyclopedia has not always been easy, especially as some topics coincide with the present, and obscure with their familiarity the context of the past. Yet we have learned from our research for this work that unless the present be recorded in print now it has less chance of being known in the future. In addition to the thousands of topics compiled by the Editor in Chief, Mr. Smallwood, the topics presented here have been selected from those suggested by many people and from nearly one hundred and fifty source books of Newfoundland society and history. Sometimes the work of choosing the best and most accurate sources has been as difficult as choosing the topics; history is an account of what has been recorded to have happened. This being so, we have attempted to corroborate and otherwise verify such records, and, where this is impossible, to present and identify conflicting statements... Robert D.W. Pitt --Website description

Going For Coffee: An Anthology of Contemporary North American Working Poems - Wayman, Tom (Harbour Publishing, 1981)
Here is the populist anthology that touches the heart of North American life, a collection that achieves in poetry what Stud Terkel's Working did in prose. Its wide appeal is obvious. Included are 200 selections by 90 Canadian and American writers, from foundry workers and short-order cooks to the likes of Joyce Carol Oates, Patrick Lane, Pier Giorgio di Cicco and Wayman himself. --Publisher's description
Keywords: Anthology; Blue-collar work; Cooks; Division of Labour; Poetry; Workers

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Ouvrages historiques, 1980)
Ce conflit impliquant surtout des travailleurs irlandais dura plusieurs mois; il fut marqué par des émeutes sanglantes qui firent au moins six morts. Le rappel des événements est suivi des témoignages recueillis par les commissaires chargés de l'enquête et du rapport officiel rédigé par ces derniers. Cette façon de procéder de l'auteur permet de porter un jugement éclairé sur la condition ouvrière au Québec au siècle dernier. --Résumé de l'éditeur

Getting Organized: Building a Union - Cornish, Mary F.; Ritchie, Laurell (Women's Press, 1980)
Practical guide for trade unionization and trade union recognition in Canada including legal aspects, trade union structures, legal aid possibilities, and selection of bargaining unit. Discusses woman workers' and immigrants' employment opportunities and trade unionism; reviews unfair labour practices and principles of collective bargaining. --Summary, WorldCat catalogue record
Keywords: Canada; Canadá; Handbooks and manuals; Labor unions; Labor unions Ontario; Labor unions Ontario Handbooks, manuals, etc; Ontario; Syndicats Ontario; Syndicats Ontario Guides, manuels, etc; asesoramiento jurídico; aspect juridique; aspecto jurídico; assistance juridique; bargaining unit; bibliografía; bibliographie; bibliography; collective bargaining; employment opportunity; estructura sindical; guide; guía; immigrant; inmigrante; legal aid; legal aspect; negociación colectiva; négociation collective; oportunidades de empleo; possibilités d'emploi; pratique déloyale de travail; práctica laboral desleal; reconnaissance syndicale; reconocimiento sindical; sindicalismo; sindicalización; structure syndicale; syndicalisation; syndicalisme; trabajadoras; trade union recognition; trade union structure; trade unionism; trade unionization; travailleuses; unfair labour practice; unidad de negociación; unité de négociation; women workers

'An Impartial Umpire:' Industrial Regulations and the Canadian State, 1900-1911 - Craven, Paul (The State and economic life, 1980)
This book is an insightful and detailed analysis of Canadian labour relations policy at the beginning of the 20th century, and of the formulation of distinctive features which still characterize it today. The development and reception of this policy are explained as a product of ideological and economic forces. These include the impact of international unionism on the Canadian working class, the emergence of scientific management in business ideology, and the special role of the state in economic development and the mediation of class relationships. The ideas and career of Mackenzie King, including his 'new liberalism,' and his activities in regard to the Department of Labour are examined, revealing how he moulded Canada's official position in the relations between capital and labour. With a focus on King's intellectual qualities in an international context, the author brings out another dimension, portraying him as Canada's first practising social scientist. The book examines implementation of policy through an analysis of the work of the Department of Labour through detailed case studies of government interventions in industrial disputes. The initial acceptance of the labour relations policy by the labour movement is explained and its repudiation in 1911 is examined against a background of setbacks which reflected its practical limits as much as its philosophical orientation. The result is a study which moves beyond a particular concern with labour policy to illuminate the contours of Canadian life in a crucial period of national development. --Publisher's description

Women's Labour History in British Columbia: A Bibliography, 1930-1948 - Diamond, Sara (Press Gang Publishers, 1980)
This is a bibliography of sources for research into the history of women workers and their activity as trade unionists in British Columbia. It spans an eighteen-year period, from 1930 to 1948. During these years dramatic changes occurred in the position of women within production as well as in strategies and strengths of the organized labour movement. --Introduction
Keywords: Bibliographies; British Columbia; Femmes Travail Colombie-Britannique Bibliographie; Femmes dans les syndicats Colombie-Britannique Bibliographie; Women Employment; Women Employment British Columbia Bibliography; Women labor union members; Women labor union members British Columbia Bibliography

Class, State, Ideology and Change: Marxist Perspectives on Canada - Grayson, J. Paul (Marxist perspectives on Canada, 1980)
[This book] is written in a way consistent with some of the fundamental concerns of Marxism. The contributions are from individuals who, according to conventional classifications, can be described as anthropologists, historians, political economists, and sociologists. ...Although the articles are grouped under the headings class, state, ideology and change, the concerns of many span more than one of these categories. In addition, the articles deal with matters of fundamental concern to Canadians: the question of unequal exchanges among regions, Canadian and Quebec nationalism, the ideological mechanisms that support the unequal treatment of women, deindustrialization, and so on. A final section of the book focuses on indigenous Canadian political economy tradition and Marxism. --Editor's preface
Keywords: Canada; Canada Conditions sociales; Canada Conditions économiques; Canada Economic conditions; Canada Social conditions; Communism and society; Communisme et société; Economic history; Social conditions; Socialism and society; Socialisme et société; Travailleurs Canada; Working class; Working class Canada

Le mouvement ouvrier au Québec. - Harvey, Fernand (Études d'histoire du Québec, 1980)
Fernand Harvey a réaménagé en profondeur le recueil de textes publié en 1973 sous le titre Aspects historiques du mouvement ouvrier au Québec. L'approche adoptée est plus thématique que chronologique. Sans prétendre être une histoire complète du mouvement ouvrier, cet ouvrage ne couvre pas moins les différentes périodes de cette histoire et aborde des thèmes essentiels à la compréhension de l'évolution historique de ce mouvement. --Résumé de l'éditeur (Google Books)

Toronto Workers Respond to Industrial Capitalism, 1867-1892 - Kealey, Gregory S. (University of Toronto Press, 1980)
Toronto's Industrial Revolution of the 1850s and 1860s transformed the city's economy and created a distinct working class. This book examines the workers' role in the transition to industrial capitalism and traces the emergence of a strong trade union movement in the latter half of the nineteenth century. Immigrant workers were already organized along ethnic lines and voluntary societies like the Orange Order played an informal but active part in the broad pattern of social change. Artisan groups were more directly instrumental in developing strategies to cope with the new pressures of industrial capitalism. In the period covered by this book Toronto's moulders and printers maintained and even strengthened the traditions of workers' control in the shop. The shoemakers and coopers were less successful, but the lessons of their defeats made them important early members of the Knights of Labor in the 1880s.The Knights of Labor gave new direction to labour organization. Ttiey recruited all workers regardless of skill, sex, creed, or race, and spearheaded the direct involvement of Toronto workers in electoral politics. The final chapters of the book trace the tortured path of working class politics from the early activities of the Orange Order to the emergence of a vibrant minority socialist tradition. Between I867 and I892 Toronto workers established a strong institutional base for the new struggles between craft unionism and monopoly capitalism in the early twentieth century and Kealey's detailed study of its development adds a new and important dimension to our understanding of Canadian labour history. -- Publisher's description.
Keywords: History / Canada / General

More Than a Labour of Love: Three Generations of Women's Work in the Home - Luxton, Meg (Women's Press, 1980)
Based on participant observation and in-depth interviews, this book describes the work women do in their homes, caring for children and partners, and maintaining the house. It shows how their lives are shaped by domestic responsibilities and challenges the ways in which their work is neither recognized nor valued. Arguing that the work they do is socially necessary and central to the economy, it calls for a transformation of current social and economic relations. -- Publisher's description (2009 reprint).

La grève de la United Aircraft - Pratt, Michel (Collection Histoire des travailleurs québécois, 1980)
United Aircraft: deux mots qui évoquent l'une des périodes les plus girses de l'histoire du Québec. Les premiers, les travailleurs de cette entreprise se battent pour l'indexation des salaries au coût de la vie. Cet ouvrage réalisé après cueillette, classement et dépouillement des sources écrites tant syndicales de patronales et des articles de journaux, avant et après la grève, relate l'histoire encore toute brûlante d'actualité de ce conflit majeure. ---Résumé de l'éditeur
Keywords: 1974-1975; Grève de la Pratt & Whitney Aircraft du Canada, 1974-1975; Relations industrielles Québec (Province) Cas, Etudes de; United Aircraft du Canada Grève, 1974-1975; United Aircraft of Canada Strike, 1974-1975

Kent Rowley, the Organizer: A Canadian Union Life - Salutin, Rick (Lorimer, 1980)
First published in 1980, Rick Salutin's biography captures Kent Rowley's unforgettable personality and details his life struggle: an epic tale in which one man's life intersects with all the major issues of his time. Kent Rowley's remarkable odyssey through Canadian history began with a Montreal high school strike. In the depths of the Depression he organized office workers. He was interned under the War Measures Act in 1940, emerging from jail to take on Premier Maurice Duplessis and the textile giants of Quebec alongside Madeleine Parent, a brilliant and influential union organizer. He survived fifteen years in the wilderness during the Cold War; and his stubborn opposition to international unions culminated in the founding, in 1968, of the Confederation of Canadian Unions dedicated to fight for independent Canadian trade unionism. Kent Rowley is a brilliant examination of the career of one of the great figures of Canadian labour history. --Publisher's description

Hidden in the Household: Women's Domestic Labour Under Capitalism - Seccombe, Wally; Briskin, Linda; Curtis, Bruce; Fox, Bonnie; Blumenfeld, Emily; Mann, Susan (Women's Educational Press, 1980)
The writers came together in the fall of 1977 to carry forward the discussion of domestic labour that began with such a promise in the late 1960s. In so doing, we hoped to develop the Marxist theory of women's oppression that is essential in the struggle for women's liberation. --From Editor's introduction
Keywords: Capitalism; Employés de maison; Femmes Conditions économiques; Femmes Travail; Femmes au foyer; Home labor; Household employees; Housewives; Marxism; Travail à domicile; Women; Women Economic conditions; Women Employment; Womyn; annotated bibliography; approche intégrée; bibliografía comentada; bibliographie annotée; cambio social; capitalism; capitalisme; capitalismo; capitalist; capitalista; capitaliste; changement social; clase trabajadora; classe ouvrière; diferencia del salario; discriminación por razones de sexo; discrimination fondée sur le sexe; disparité des salaires; division du travail basée sur le sexe; división del trabajo por sexo; economic role; economic system; evaluación; evaluation; femmes mariées; fonction de production; función de la producción; hogar; household; household production; housewives (people); integrated approach; labour force participation; married women; marxisme; marxismo; mujeres casadas; ménage; método integrado; papel económico; producción doméstica; production domestique; production function; rôle économique; sex discrimination; sexual division of labour; sistema económico; social change; système économique; tasa de actividad de mano de obra; taux d'activité; trabajadoras; trabajo no remunerado; travail non rémunéré; travailleuses; unpaid work; wage differential; women workers; working class; évaluation

50,000 Strong: The Federal Clerks' Strike of 1980 - Tieleman, Bill (Canada Employment and Immigration Union, 1980)
Keywords: Government Employee Unions Canada; Public Service Alliance Of Canada Officials And Employees; Strikes And Lockouts Civil Service Canada

The Labour Companion: A Bibliography of Canadian Labour History, Based on Materials Printed from 1950 to 1975 - Vaisey, G. Douglas; Battye, John; DeYoung, Marie; Kealey, Gregory S.; Committee on Canadian Labour History (Committee on Canadian Labour History, 1980)
This work is founded on the extensive working files of John Battye and Gregory Kealey, to which were added references pirated from other bibliographies, items accumulated from computer-assisted literature searches, and literary débris collected by methodical screening of such collections as Canadiana, Library of Congress Books: Subjects, and the Canadian Periodical Index. --Introduction
Keywords: Bibliography; History; Labor movement; Labour and labouring classes; Trade unions

Many Tender Ties: Women in Fur-Trade Society, 1670-1870 - Van Kirk, Sylvia (Watson & Dwyer, 1980)
Beginning with the founding of the Hudson’s Bay Company in 1670, the fur trade dominated the development of the Canadian west. Although detailed accounts of the fur-trade era have appeared, until recently the rich social history has been ignored. In this book, the fur trade is examined not simply as an economic activity but as a social and cultural complex that was to survive for nearly two centuries. The author traces the development of a mutual dependency between Indian and European traders at the economic level that evolved into a significant cultural exchange as well. Marriages of fur traders to Indian women created bonds that helped advance trade relations. As a result of these "many tender ties," there emerged a unique society derived from both Indian and European culture. -- Publisher's description.
Keywords: Conjoints; History. Fur trade; History. Fur trade. Fur traders' spouses. Indian women. Manners and customs. Social conditions Women. Vrouwen. Bonthandel. Sociale aspecten. Coureurs de bois; Indian women; Nord-Ouest canadien. Genre/Form: History; Nord-Ouest canadien. Indiennes d'Amrique; Northwest, Canadian; Northwest, Canadian. Fur traders' spouses; Northwest, Canadian. Women

Women and Unions - White, Julie (Canadian Advisory Council on the Status of Women, 1980)
Keywords: Women labor union members -- Canada -- History

"Dangerous Foreigners": European Immigrant Workers and Labour Radicalism in Canada, 1896-1932 - Avery, Donald (Canadian social history series, 1979)
The deplorable exploitation of immigrant workers from the 1890s to the Depression is documented in this vivid account of Canada's early immigration policies. Transported by boxcar and often herded at gun point, these "men in sheepskin coats" were lured from Central and Eastern Europe by promises of shared wealth in a veritable promised land. Their backbreakaing labour in industry and agriculture directly furthered Canada's economic development, transportation lines, and land settlement. But their status, as detailed here with public records, newspaper accounts, and private correspondence was little above that of slave labour. Professor Avery records the immigrants' poor working conditions, bad pay, violent treatment at the hands of challenged authorities, and wholesale deportation when work became scrace. Recounted as well as their hostile reception by British Canadian, the government neglect of immigrant assimilation programs, and the workers' ultimate recourse to radical ethnic and political organization to better their lot. --Publisher's description
Keywords: Canada; Employment History; Foreign workers; History; Minorities; Radicalism; Social conditions

An Account to Settle: The Story of the United Bank Workers (SORWUC) - Bank Book Collective (Vancouver, BC); Ainsworth, Jackie (Press Gang Publishers, 1979)
In 1976, a group of women bankers decided to organize their workplace. The banks were enraged. When they decided to do it themselves, the big unions were upstaged. Over the next two years, nearly a thousand bank employees in western Canada participated in a unionizing drive that challenged not only the banks but organizated labour's approach to a workplace that they had long considered beyond their range of union activity. This is the story of the United Bank Workers of SORWUC (Service, Office and Retail Workers of Canada). With honesty and humour, the clerks and tellers of the UBW tell why they decided to take on the banks and what happened when they did. --Publisher's description
Keywords: Bank employees Labor unions; Bank employees Labor unions British Columbia; Banques Personnel Syndicats Colombie-Britannique; British Columbia; Service, Office and Retail Workers Union of Canada. United Bank Workers Section; Syndicat canadien des employés de service, de bureau et de détail. United Bank Workers Section; Syndicats Banques Personnel Colombie-Britannique

Alberta Labour: A Heritage Untold - Caragata, Warren (Lorimer, 1979)
Without labour there would be no history. As this book shows, the history of labour in Alberta is colourful, exciting and filled with dramatic characters and events well worth discovering. Alberta Labour traces the growth of union organizations in Alberta: the Knights of Labour in the 1880s, the legendary Wobblies, the abortive One Big Union and finally the Alberta Federation of Labour, founded in 1912. This history, the first of its kind, has been compiled from interviews with union members, original letters and documents, and contemporary newspapers and magazines. Illustrated with over 90 full-page photographs, most of them never before published, Alberta Labour vividly depicts the working people of Alberta and their unparalleled contribution to the province's history. --Publisher's description
Keywords: Alberta; History; Labor movement; Labor movement Alberta History; Labor unions; Labor unions Alberta History; Mouvement ouvrier Alberta Histoire; Syndicats Alberta Histoire; Travailleurs Alberta Histoire; Working class; Working class Alberta History

"Building British Columbia": The Story of the Carpenter's Union and the Trade Union Movement Since 1881 - Carpenter Pensioner's Association of British Columbia (Carpenter Pensioner's Association of British Columbia, 1979)
Illustrated history based on research, interviews and recollections made by members of the Carpenter Pensioners Association of British Columbia. Foreword by Arnold Smith.

The Phone Book: Working at the Bell - Kuyek, Joan (Between the Lines, 1979)
If you believe the advertisements, Bell Canada is in the business of putting grannies in touch with their loved ones, helping blind kids play baseball, and generally making it easier for society to "communicate." In this book, Joan Newman Kuyek presentes a different story - a story of stifling bureaucracy, of increasingly fragmented and dehumanizing jobs, of the elimination of workers through changing technology, of flashy corporate expansion abroad and declining service at home. It's a story that reveals what lies behind the rate increases demanded almost annually in the last decade. It does much to explain the struggle for unionization and the wave of strikes that recently hit the phone company. The Phone Book is an "inside view" of work at the Bell. Joan Kuyek speaks from personal experience - she spent nearly three years as a Bell service representative, and interviewed dozens of her co-workers, operators, service representatives, installers and others, for the book. --Publisher's description
Keywords: Bell Canada; Bell Canada Employees; Bell Canada Personnel Direction; Canada; Case studies; Employees; Industrial relations; Industrial relations Canada Case studies; Innovations Canada Cas, Études de; Innovations Canada Études de cas; Relations industrielles Canada Études de cas; Technological innovations; Technological innovations Canada Case studies

William Irvine: The Life of a Prairie Radical - Mardiros, Anthony (Lorimer, 1979)
Along with J.S. Woodsworth, William Irvine was one of the pioneers of socialism in Canada, a member of the radical Ginger Group, progenitor of the C.C.F. and N.D.P. In the wake of the First World War Irvine struggled relentlessly to organize Alberta farmers for political action. Elected to Parliament in 1921, he along with close friend Woodsworth were the sole labour representatives in the House: they worked incessantly against the monopoly power of large corporations and financial institutions. Together they laid the basis for a socialist challenge to the Eastern-dominated, two-party system in Canada. William Irvine: The Life of a Prairie Radical chronicles his immense contribution to the search for political alternatives in this country, a contribution that can still be felt in Canadian politics today. --Publisher's description

We Stood Together: First-Hand Accounts of Dramatic Events in Canada's Labour Past - Montero, Gloria (Lorimer, 1979)
Told for the first time, here are the stories of twelve of Canada's outstanding labour leaders and organizers. Their accounts tell the behind-the-scenes stories of some of the key events in twentieth-century Canadian history: the 1919 Winnipeg General Strike; the 1935 On-to-Ottawa trek of the unemployed, which played a major role in the defeat of Tory Prime Minister R.B. Bennett; the 1945 Ford strike in Windsor, which consolidated the rights of big industrial unions; the 1972 Common Front of Quebec's public sector workers. Gloria Montero travelled across the country to interview the labour leaders whose stories make up this book. We see the Winnipeg General Strike and the trials which followed through the eyes of Bill Pritchard, one of the eight strike leaders arrested and later tried by the government. In Vancouver Bill Walsh gave a first-hand account of riding the rails to Regina with the On-to-Ottawa trekkers. Madeleine Parent tells about organizing Quebec workers in the Forties against the anti-labour regime of Maurice Duplessis. Among other noted labour leaders whose stories are told here there are BC's Homer Stevens, Quebec's Yvon Charbonneau, Ontario's Grace Hartman, and the UAW's George Burt. The result is a book alive with people who are usually shadowy figures in the news and in the history books, but who played major roles in Canada's colourful and turbulent labour past. --Publisher's description
Keywords: Absatz; Asymmetrische Information; Canada; Grèves et lock-out Canada Histoire; History; Labor movement; Labor movement Canada History; Labor unions; Labor unions Canada History; Mouvement ouvrier Canada Histoire; Produktqualität; Strikes and lockouts; Strikes and lockouts Canada History; Syndicats Canada Histoire; Theorie; Travailleurs Canada Histoire; Verhaltensökonomik; Werbung; Working class; Working class Canada History

A Culture in Conflict: Skilled Workers and Industrial Capitalism in Hamilton, Ontario, 1860-1914 - Palmer, Bryan D. (McGill-Queen's University Press, 1979)
[This book] is a study of continuity and change in the lives of skilled workers in Hamilton, Ontario, during a period of economic transformation. Bryan D. Palmer shows how the disruptive influence of devel oping industrial capitalism was counterbalanced by the stabilizing effect of the associational life of the workingman, ranging from the fraternal order and the mechanics' institute to the baseball diamond and the "rough music" of the charivari. On the basis of this social and cultural solidarity, Hamilton's craftsmen fought for and achieved a measure of autonomy on the shop-floor through the practice of workers' control. Working-class thought proved equally adaptable, moving away from the producer ideology and its manufacturer-mechanic alliance toward a recognition of class polarization. Making ample use of contemporary evidence in newspapers, labour journals, and unpublished correspondence, the author discusses such major developments in the class conflict as the nine-hour movement of 1872, the dramatic emergence of the Knights of Labor, and the beginnings of craft unionism after 1890. He finds that the concept of a labour aristocracy has litlle meaning in Hamilton, where skilled workers were the culling edge of the working-class movement, involved in issues which directly related to the experience of their less-skilled brethren. More remarkable than the final attainment of capitalist control of the work place, he concludes, are the long-continued resistance of the Hamilton workers and their success in retaining much of their power in the pre-World War I years. --Publisher's description

One Year Later: The 1978-79 Strike at Inco, The Effects on Families, A Report - Radecki, Henry (SIS Analysis, Laurentian University, 1979)
Keywords: Inco Strike, 1978-1979; Social aspects; Strikes and lockouts

Miner's Life: Bob Miner and the Union Organizing in Timmins, Kirkland Lake and Sudbury - Roberts, Wayne (McMaster University. Labour Studies Programme, 1979)
Keywords: Labor unions; Miners; Mining districts; Ontario

Les syndicats nationaux au Québec de 1900 à 1930 - Rouillard, Jacques (Les cahiers d'histoire de l'Université Laval, 1979)
Keywords: Trade-unions -- Québec (Province) -- History

Radical Heritage: Labor, Socialism, and Reform in Washington and British Columbia, 1885-1917 - Schwantes, Carlos A. (Emil and Kathleen Sick lecture-book series in western history and biography, 1979)
Historian Carlos A. Schwantes studies the forces that shaped the history of the labor movement on either side of the forty-ninth parallel and the reason for the eventual demise of the socialist movement in Washington State and its continuing vigor in British Columbia. --Publisher's description
Keywords: Socialism -- British Columbia -- History

The Canadian Worker in the Twentieth Century - Abella, Irving M.; Millar, David (Canadian social history series, 1978)
This anthology consists largely of eyewitness accounts of - and often by - the working men, women, and children of Canada. Beyond the institutional history of trade unions and labour partiees are massive changes in patterns of thought, economic life, standards of living, and conditions of work. In these primary sources, we may glimpse these changes, see their impact in human terms, and hear the voices of the unorganized, the unemployed, and the oppressed, as well as those of union officials and skilled workers with hopes of rapid upward mobility. Most significantly, these documents suggest not only new directions for the student of Canadian social history, but also major revisions of some traditional assumptions of the historian. These readings - most taken from rare, out-of-print, or previously unavailable documents -- tell of life and work in an industrializing, expanding Canada; of conditions in mines, factories, farms and lumber camps; of the cruel exploitation of women and immigrant workers; and of the great migration in these years from country to city. They represent almost all the provinces and range over conditions in Victorian times to those faced today by field labour and immigrant men and women in modern sweatshops. In their own words, describing their dailly confrtontation with life, we can listen to a Calgary charwoman, a Japanese fisherman, a Cape Breton miner, a Jewish ragpicker, an Italian railroad worker, a Quebec garment worker, a Ukrainian farm-boy, and scores of others. Here is the most vivid account yet of the problem faced by Canadian workers, both native and immigrant; of their distinctive attitudes and traditions; and, above all, of their courage and bitter struggle for equality and a better life. The book as a whole is an important contribution to the movement in recent years to deepen and broaden our labour history. -- Publisher's description. Partial contents note: Introduction (pages 1-2) -- Working conditions, 1900-1918 (pages 3- 75) -- Poverty, home life, and leisure (pages 76-150) -- Women's work (pages 151- 215) -- Working conditions and the rise of the CIO (pages 216-306) -- Bibliographical note (pages 307-310).
Keywords: 20th century; Canada; History; Working class

Fools and Wise Men - Bercuson, David Jay (McGraw-Hill Ryerson, 1978)
This is the story of the One Big Union--the people who built and those who tore it down. The tale is well known in its broad outlines to many people with an interest in Canadian history, but because it was a failure--and history is generally about winners--few have a clear idea of what the OBU was, why it was created and the reasons for its rapid demise. I have long believed the story should be told in full, because it carries with it an explanation of what happened to the spirit of radicalism and revolt that motivated many working people in the west prior to 1920. Sometimes the explanation of a failure is more revealing than the description of a success. --Author's preface
Keywords: Canada; One Big Union; Trade unions

Last Hired, First Fired: Women and the Canadian Work Force - Connelly, Patricia (Women's Educational Press, 1978)
Study of trends in the labour force participation of woman workers and their economic role in the labour market of Canada since 1901 - likens female underemployment and disguised unemployment to that of a reserve army of labour with cheap wages; denounces sexual division of labour as a form of sex discrimination; examines changing industrial structures and occupational structures; notes increasing need for labour force participation of married women to maintain standard of living within the family. Bibliography. --Summary, WorldCat catalogue record
Keywords: Canada; Canadá; Discrimination sexuelle dans l'emploi Canada; Discrimination à l'égard des femmes Canada; Femmes Travail Canada; Sex discrimination against women; Sex discrimination against women Canada; Sex discrimination in employment; Sex discrimination in employment Canada; Women Employment; Women Employment Canada; bibliografía; bibliographie; bibliography; chômage déguisé; desempleo disfrazado; discriminación por razones de sexo; discrimination fondée sur le sexe; disguised unemployment; division du travail basée sur le sexe; división del trabajo por sexo; economic role; estructura del empleo; estructura industrial; familia; famille; family; femmes mariées; industrial structure; labour force participation; labour market; marché du travail; married women; mercado de trabajo; mujeres casadas; niveau de vie; nivel de vida; occupational structure; papel económico; rôle économique; salaire; salario; sex discrimination; sexual division of labour; sous-emploi; standard of living; structure de l'emploi; structure industrielle; subempleo; tasa de actividad de mano de obra; taux d'activité; tendance; tendencia; trabajadoras; travailleuses; trend; underemployment; wages; women workers

Classe ouvrière et pauvreté, Les conditions de vie des travailleurs montréalais 1897–1929 - Copp, Terry (Histoire et sociétés, 1978)
L'auteur cherche à présenter "l'autre" Montréal, celui des travailleurs et de leur famille, par opposition au Montréal industriel en pleine expansion à cette époque. Il s'attache particulièrement à ce secteur de Montréal situé au pied de la montagne, à la classe ouvrière qui y vit, ses revenus, son éducation, au travail des femmes et des enfants, à l'habitation, à la santé publique, aux conflits ouvriers. Deux appendices complètent cette étude fondamentale : un sur des budgets familiaux typiques, un autre sur la conclusion d'une enquête du gouvernement québécois d'alors sur le taux élevé de mortalité par tuberculose (1909). --Sommaire de l'éditeur

Industrial Democracy in Western Europe: A North American Perspective - Crispo, John H. G. (McGraw-Hill Ryerson, 1978)
John Crispo reviews the latest trends in industrial democracy in Western Europe. The book is based upon his earlier work in this area and a recently completed 10-month tour of the countries involved, which he spent interviewing labour and management representatives and other interested individuals throughout Western Europe. The result is an up-to-date and comparative account of the dynamic field of industrial democracy, which is defined to embrace union and worker influence in decision-making in all levels of society. Although the book focuses on Western Europe, it has been written in a manner to highlight the relevance of what is taking place there for industrial relations in North America. --Publisher's description
Keywords: Collective bargaining -- Europe

The Canadian Industrial Relations System - Crispo, John H. G. (McGraw-Hill Ryerson, 1978)
Textbook on the system of labour relations in Canada - covers the nature of Canada's constitutional and legal system, the role of employers organizations, trade unions and employees associations, the labour movement (including Its history), collective bargaining and inflation, and comments on standards of labour legislation, labour disputes and dispute settlement, [and] future trends. Flow charts and references. --Google Books description
Keywords: Industrial relations -- Canada

Révolution industrielle et travailleurs : une enquête sur les rapports entre le capital et le travail au Québec à la fin du 19e siècle - Harvey, Fernand (Boréal Express, 1978)
C'est au cours des années 1880 que le problème de l'industrialisation s'est posé dans toute son ampleur au Canada et au Québec. À l'approche des élections de 1887, le gouvernement conservateur de J.A. Macdonald crut trouver une solution en instituant une commission royale chargée d'enquêter sur «les relations entre le capital et le travail». Les commissionaires ne se doutaient pas qu'ils s'attaquaient à un au-dessus de leur force. Au terme de leur travaux, ils rédigèrent deux maigre rapports sans grande inspiration et n'offrant aucune vision d'ensemble cohérente. Pourtant la «Commission du travail» présente un intérêt tout à fait exceptionnel. Les procès-verbaux des témoinages recueillis par les commissionaires constitutent sans doute le plus important document oral qui nous soit parvenu sur la condition ouvrière au moment où le Québec entre dans la revolution industrielle. La société québécoise connait alors une véritable mutation qui se manifeste tant au niveau de la technique et de l'économie qu'à celui de la organisation sociale et de la culture. Fernand Harvey analyse ici les diverses composantes de cette mutation en s'appuyant sur une étude fouillée les travaux de la Commission du travail et les conditions générales de l'époche. --Résumé de l'éditeur
Keywords: Industrial relations -- Québec (Province) -- History

Trade Unions and the State - Johnson, Walter (Black Rose Books, 1978)
[E]xamines in detail five important strikes in Canadian labour history to illustrate the dynamics underlying disruption and shows how direct action is often more effective than collective bargaining and State intervention. --Publisher's description
Keywords: Strikes and lockouts -- Canada

R. B. Russell and the Labour Movement - Osborne, Kenneth W. (We built Canada, 1978)
Chronicles Russell's rise to become one of the "Red Five" leaders of the Winnipeg General Strike as well as his instrumental role in founding the One Big Union. Also describes Winnipeg in the early 20th century and the labour movement's struggle to improve the conditions of the working class. Intended for secondary school students, the abundantly illustrated book includes suggestions for skits and debates about unions and issues that surround labour-management confrontations.
Keywords: Russell, Robert Boyd, 1888-1964

Le fondateur du syndicalisme catholique au Québec, Mgr Eugène Lapointe : sa pensée et son action syndicales - Parisé, Robert (Histoire des travailleurs québécois, 1978)
Pour rédiger cet ouvrage sur la pensée et l'action de Monseigneur Eugène Lapointe, l'auteur a puisé abondamment dans les archives de la Société historique du Saguenay. Il s'en tient exclusivement au domaine syndical. Rappelons que Mgr Lapointe est à l'origine de la Fédération ouvrière mutuelle du Nord, remplacée plus tard par la Fédération catholique des employés de pulperies et papeteries du Canada. --Résumé de l'éditeur
Keywords: Biographies; Catholic labor unions; Catholic labor unions Officials and employees; Catholic labor unions Québec (Province) History; Catholic labor unions Québec (Province) Officials and employees Biography; History; Lapointe, Eugène, 1860-1947; Québec; Syndicats catholiques Québec Histoire

The Hamilton Working Class, 1820-1977: A Bibliography - Roberts, Wayne (Hamilton, Ont. : Labour Studies Programme, McMaster University, 1978)
Contents: The working man in a frontier town, Hamilton, 1820-1850 ; The railway city, 1850-1870 / John Weaver -- Researching the Hamilton working class, 1870-1900 / Bryan Palmer -- The working class of Hamilton, 1900-1930 / Craig Heron -- The labour movement of Hamilton, 1930-1956 -- Selected bibliography of Hamilton labour, 1956-1977 / Charlotte A. Stewart.
Keywords: Trade-unions -- Ontario -- Hamilton -- History -- Bibliography

Canadian Workers, American Unions - Scott, Jack (Trade Unions and Imperialism in America, 1978)
Canada is the only country in the world whose unions have headquarters in a foreign country. More than two-thirds of Canadian workers in the private sector pay dues to "international" head offices in the United States. Canadian Workers, American Unions continues the historical account begun in the first volume of Trade Unions and Imperialism in America, "Yankee Unions, Go Home!: How the AFL Helped the U.S. Build an Empire in Latin America." --Publisher's description
Keywords: Labor unions

Life & Death of a Union: The Canadian Seamen's Union, 1936-1949 - Stanton, John E. (Steel Rail Educational, 1978)
[The author] introduces some of Canada's most extraordinary trade unionists. We encounter nine Ottawa mandarins who pave the way for the destruction of Canada's merchant navy, ship building industry, and 50,000 jobs. We meet certain employers whose greed was boundless and who were prone to violence and lawlessness. And we view the antics of politicians who turn out to be considerably less than honourable. Mr. Stanton tells the shameful story of the union's death from, as he says, "employer intransigence, government corruption, judicial bias, and American thuggery." It took a commission of inquiry, a government-imposed Administratioin, and almost a generation to clear up the mess left by U.S. gangsters. They had been brought into the shipping industry by ruthless employers unrestrained by the Mackenzie King government. For, as Mr. Stanton demonstrates, Mackenzie King was "an employer's man, first, last and always." --Publisher's description
Keywords: Canadian Seamen's Union; Canadian Seamen's Union Histoire

Quitting Time - Warrior, M.C. (Macleod Books, 1978)
Poetry chapbook.

Fighting for Labour: Four Decades of Work in British Columbia, 1910-1950 - Wejr, Patricia; Smith, Howie (Sound heritage, 1978)
Keywords: Biographies; British Columbia; History; Labor unions; Labor unions British Columbia Biography; Labor unions British Columbia History; SPAN-M; Syndicats Colombie-Britannique Biographies; Syndicats Colombie-Britannique Histoire; collective biographies

Le travail de la femme au Québec: l'évolution de 1940 à 1970 - Barry, Francine (Histoire des travailleurs québécois, 1977)
Keywords: Femmes Travail Canada; Femmes Travail Québec (Province); Québec; Québec (Province) Social conditions; Travailleurs Canada Québec (Canada; province); Women Employment; Women Employment Québec (Province)

Les apprentis artisans à Québec, 1660-1815 - Hardy, Jean Pierre; Ruddel, David-Thiery (Histoire des travailleurs québécois, 1977)
Keywords: Apprentices -- Québec (Province) -- History

Stump Ranch Chronicles and Other Narratives - Knight, Rolf (New Star Books, 1977)
Reminiscences of homesteading, railway construction, logging, mining and life in the farming and resource communities of western Canada in the years since1912 by two populist/socialist participants. Accounts markedly different from the usual picture of rural conservatism and quiescence. --Author's summary

A Man of Our Times: The Life-History of a Japanese-Canadian Fisherman - Knight, Rolf; Koizumi, Maya (New Star Books, 1977)

Capital & Labour, Partners?: Two Classes, Two Views - Levant, Victor (Steel Rail Educational, 1977)
There have been many attempts to convince Labor that Capital is a friend. In this book Victor Levant lays bare the ideological basis of the contention that Labor and Capital are partners and in so doing he exposes the mis-leaders of labor who week to take workers along the road paved by Capital. --Publisher's description
Keywords: Canada; Company unions; Company unions Canada; Company unions North America; Company unions Québec (Province); Company unions United States; North America; Québec; Syndicats d'entreprise Amérique du Nord; Syndicats d'entreprise Canada; Syndicats d'entreprise Québec (Province); Syndicats d'entreprise États-Unis; United States

Reformers, Rebels, and Revolutionaries: The Western Canadian Radical Movement, 1899-1919 - McCormack, A. Ross (Heritage, 1977)
The opening of the twentieth century saw a fervour of radical political movements in Western Canada. Ross McCormack explores the constituencies, ideologies, and development of early reformist, syndicalist, and socialist organizations from the 1880s up to the Winnipeg General Strike in 1919. He distinguishes three types of radicals - reformers, rebels, and revolutionaries - who competed with each other to fashion a gneral western constituency. The reformers wanted to change society for the betterment of the workers, but both their aims and methods were moderate, essentially transfering the philosophy and tactics of the British labour movement to the Canadian west. The rebels, militant industrial unionists, periodically battled the Trades and Labour Congress in order to establish unions strong enough to defeat the employers and, if necessary, the state. The revolutionary Marxists were committed to the destruction of industrial capitalism and the establishment of a society controlled by the workers. The book describes the origins of radicalism, traces the histories of the various organizations that expressed its ideals, and discusses the impact of the First World War on the labour movement. Using previously unexplored sources, McCromack has produced the first comprehensive examination of the early history of the radical movement in western Canada, adding an important dimension to our knowledge and understanding of Canadian labour history. --Publisher's description. Contents: The emergence of the socialist movement in British Columbia -- Militant industrial unionism and the first western rebellion -- The ascendancy of the Socialist Party of Canada -- A case study in labourism: Winnipeg 1899-1915 -- The Industrial Workers of the World and militant industrial unionism -- Western radicals and the Great War: the first phase -- Western radicals and the Great War: the second phase.

The Canadian Left: A Critical Analysis - Penner, Norman (Prentice-Hall, 1977)
When craftsman from Britain began to pour into Canada at the end of the nineteenth and the beginning of the twentieth century they brought more than industrial skills with them. They brought a trade union consciousness from a country where the labor movement was already highly developed, and many also came with socialist ideas, which they proceeded to implant on Canadian soil. Socialist ideas at the same time also came from the United States, and somewhat later immigrant laborers from eastern and central Europe added to the strength of socialism in Canada. --Introduction
Keywords: Socialism -- Canada

Honest Womanhood: Feminism, Femininity and Class Consciousness Among Toronto Working Women, 1896-1914 - Roberts, Wayne (New Hogtown Press, 1977)
If these arguments are correct [i.e., arguments against a sexist psychological interpretation], then we must set ourselves another course to explain the failure of working class women in the 1896 to 1914 [period] to respond to their problems in a more explicitly collective fashion. The framework for such an alternative explanation rests upon a more concrete understanding of the work-life and work-place ecology of working women. Reliance on reliable clichés and "momified" abstractions about feminine psychology has hindered a recognition of the strictures that demographic and occupational influences placed on the possibilities for a concerted action. Combined with an appreciation of some of the thoughts and activity of working women, this approach should help us to reevaluate both the objective constraints and organizing capacities of the woman worker and the interplay of various aspects of her consciousness--particularly her feminism, her sense of feminity and her class consciousness. --From author's introduction

The Big Nickel: Inco at Home and Abroad - Swift, Jamie (Between the Lines, 1977)
Inco is the world's largest producer of nicke. This gripping account of the corporation is an essential contribution to an understanding of concentrated economic power, how it operates in Canada and the Third World, and its human consequences. J.P. Morgan, Wilfrid Laurier, John Foster Dulles, and the CIA all play roles in the intrigue surrounding Inco's growth. Ranged against them are the workers who produce the wealth. Members of the Western Federation of Minders, the Industrial Workers of the World, the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America all confront Inco. A story of resistance emerges - of union busting, of attacks by company goons, and of successful organizing drives. Today the struggle broadens to achieve safe working conditions and a cleaner environment. As Inco extends its arms around the world in an attempt to keep up its profits, Indonesia and Guatemala are confronted with a new chapter in a familiar colonial story. Military dictatorship and corporate expansion go hand in hand. The largess of the Canadian government facilitates the process. --Publisher's description
Keywords: Canada; Canada Nickel industries International Nickel Company of Canada; Entreprises multinationales; History; INCO; Industrial relations; Industrial relations Canada; International Nickel Company Histoire; International Nickel Company of Canada; International business enterprises; Internationale ondernemingen; Nickel Industrie Ontario Sudbury; Nikkel; Relations industrielles Canada

The Enemy That Never Was: A History of the Japanese Canadians - Adachi, Ken (McClelland and Stewart, 1976)
Ken Adachi's historical study of racism in Canada towards those of Japanese ancestry spans almost a century, from 1877 to 1975. He focuses on Japanese immigration, the Japanese Canadian community organization and the forced evacuation and relocation during the second world war. Also included, is an afterword by Roger Daniels that documents the efforts of the Japanese Canadian community post 1975, to gain redress for their unjustified internment and dispossession during World War II. More than four decades later, their struggles successfully lead to the Canadian Government's formal apology and to the Japanese Canadian Redress agreement of 1988. --Canadian Race Relations website
Keywords: Japanese -- Canada -- History

Les relations du travail au Québec: la dynamique du système - Congrès des relations industrielles de l'Université Laval (31st : 1976); Bernier, Jean; Blouin, Rodrigue; Laflamme, Gilles; Laroque, Alain (Presses de l'Université Laval, 1976)
Commentaires sur les tendances des relations de travail et de la législation du travail au Québec, y compris les aspects politiques, les implications économiques, la liberté d'association, l'arbitrage et les conflits de travail. Bibliographie pages 113-119, graphique, références et tableaux statistiques.
Keywords: Canada; Canadá; Conference papers and proceedings; Industrial relations; Industrial relations Québec (Province) Congresses; Québec; Relations industrielles Québec (Province) Congrès; arbitrage; arbitraje; arbitration; aspect politique; aspecto político; bibliografía; bibliographie; bibliography; comentario; comment; commentaire; conflicto de trabajo; conflit du travail; consecuencias económicas; conséquences économiques; cuadros estadísticos; economic implication; freedom of association; graph; graphique; gráfico; labour dispute; labour legislation; labour relations; legislación del trabajo; libertad sindical; liberté syndicale; législation du travail; political aspect; reference; referencia; relaciones laborales; relations de travail; référence bibliographique; statistical table; tableau statistique; tendance; tendencia; trend

Eight Men Speak, and Other Plays from the Canadian Workers' Theatre - Endres, Robin (New Hogtown Press, 1976)
Contents: Theatre our weapon. Maguire. T. Unemployment / T. Maguire -- Looking forward / F. Love --  Eight men speak / O. Ryan, et al. -- Scientific socialism / N.W. Bowles -- Unity / O. Ryan -- Joe Derry / D. Livesay -- War in the East / S. Ryerson -- And the answer is / M. Reynolds.

On the Job: A Play - Fennario, David, (Talonbooks, 1976)
It is Christmas Eve, 1970. In the shipping room of a Montreal dress factory, the workers get drunk and decide to go on strike. "So many of the guys I knew on the street are gone dead or crazy, man. There's no escape. This whole country is just one big factory, one big jail, Billy … Either you're a good nigger or ya die. Know what I mean? … Black, yellow, white. We're all niggers down on Rockefeller's Plantation, man." "Punks, Billy. All we get now is punks … I used to have this shipping room running like a new machine, remember, Billy? … No trouble, no fuss, 'cause everybody did their job and knew their place, but now … In the last five years, the kids been getting more and more like that Gary Boyce. Shit disturbers. They all got that look in their eye. Know what I mean? Like they don't give a damn." On the Job is David Fennario's post-mortem on the '60s and a look at the Canadian class structure. The play was first performed at Centaur Theatre, Montreal. Subsequently, it has been performed at the National Arts Centre, Ottawa; been revived by Centaur Theatre; and been staged at the Arts Club Theatre, Vancouver. --Publisher's description
Keywords: Class Consciousness; Drunk; Factory; Humour; Montreal, Quebec; Social Class and Equality; Strike

Times of Trouble: Labour Unrest and Industrial Conflict in Canada, 1900-66 - Jamieson, Stuart Marshall; Canada. Task Force on Labour Relations (Study (Canada. Task Force on Labour Relations),, 1976)
The following lengthy study of "The History of Labour Unrest in Canada, 1900-66," was undertaken on behalf of the federal government's Task Force on Labour Relations, which is now sponsoring dozens of separate research projects, in response to what appeared to be a major "crisis" in labour relations in this country during 1965-66. ...One final, and more specific, justification for undertaking a lengthy and detailed history of labour unrest in Canada, as manifested in strikes and other forms of overt conflict, is, to put it simply, that it has not been done before. As noted below, in discussing sources that were drawn upon in writing this study, there is a remarkable paucity of literature on the subject of industrial unrest and conflict in Canada. This is particularly the case in scholarly, academic and literary circles. --From introduction

Essays in Canadian Working Class History - Kealey, Gregory S.; Warrian, Peter (Canadian social history series, 1976)
Part of the new aproach currently transforming the writing of Canadian history, this volume approaches the past in terms of people and the activities and events that shaped their existence. The essays explore the roots of the radical tradition and outline the struggle against industrial capitalism between 1850 and 1925. [This book] increases our understanding of the past, provides a valuable perspective on present struggles, and, in a broader sense, contributes substantially to a new and decisive synthesis of Canadian history. --Publisher's description
Keywords: Canada; History; Working class

Chronologie des mouvements politiques ouvriers au Québec de la fin du 19e siècle jusqu'à 1919 - L'Université du Québec à Montréal. Groupe de recherches sur l'histoire des mouvements politiques ouvriers (Histoire des travailleurs québécois, 1976)
Keywords: Québec; Travailleurs Activité politique Québec (Province); Working class Political activity; Working class Political activity Québec (Province)

Canada's Unions - Laxer, Robert M. (Lorimer, 1976)
This book presents a picture of Canada's labour movement in the mid-seventies - its structure, its leaders, and aims.Two parallel themes run through Canada's Unions: the surge in labour militancy led by teachers, hospital workers, federal government workers and other public employees in response to the pressure of rising inflation; and the rise of nationalism and the increasing independence of the Canadian union movement during the 1970s. Canada's Union offers an unparalleled, immediate portrait of the state of the Canadian labour movement during a crucial decade of its existence. --Publisher's description

Miners and Steelworkers: Labour in Cape Breton - MacEwan, Paul (Samuel Steven/Hakkert, 1976)
It is easy to forget today how desperate the need was for unions in the days of the worst exploitation and abuse of power by powerful companies. Who now could imagine workers being forced to strike to avoid wage cuts even in times of rising prices? Who could imagine them losing such a strike? This moving story of the miners and steelworkers of Cape Breton focuses on the issues which generated the most militant unions in Canada. Wage cuts, blacklisting, mine disasters, pit closings, police killings, collusion between management and government, company unions, bayonets and barbed wire, American interference, hostile legislation — all this and more have contributed to a century of labour violence and bitterness almost unparalleled in North America. This is a piece of Canadian history usually forgotten, a part of our history that affects us today more than we like to think. --Publisher's description
Keywords: Coal miners; Coal mining History; Iron and steel workers; Labor unions History; Nova Scotia Cape Breton Island; Steel industry History; Strikes and lockouts

An Illustrated History of Canadian Labour, 1800-1974 - Seymour, Edward E. (Canadian Labour Congress, 1976)
Keywords: Canada; Grèves et lock-out Canada Histoire; History; Labor movement; Labor movement Canada History; Labor unions; Labor unions Canada History; Mouvement ouvrier Canada Histoire; Strikes and lockouts; Strikes and lockouts Canada History; Syndicats Canada Histoire; Travailleurs Canada Histoire; Working class; Working class Canada History

The Canadian Labour Movement, 1902-1960 - Abella, Irving (Historical Booklet / Canadian Historical Association, 1975)
If, as Sir Wilfrid Laurier said, the twentieth century would be the century of Canada, by the end of the first decade of the new century it was already apparent that it would not be the century of the Canadian working man. The twentieth century ushered in the great Canadian boom.The twentieth century ushered in the great Canadian boom. And boom conditions produced a boom psychology. Nothing could stop Canada. Incredible industrial expansion; two new transcontinental railways pushing across the West; seemingly unstoppable floods of capital and immigrants pouring into the country; these were the hallmark of the decade. Indeed, everyone seemed to be prospering. Everyone, that is, but the Canadian worker. To him the twentieth century ushered in no new changes - or at least, no changes for the better. His conditions of work were still appalling, and his wages--though somewhat higher--could not keep up with spiralling living costs. Indeed, the influx of hundreds of thousands of hungry, penniless immigrants even made it difficult to hold a job. And what jobs? Stuffy, unventilated factories; sixty hours a week; back-breaking work; all for a dollar a day. These were the conditions of work for the men, women and children of Canada. And a dollar a day was considered excellent pay for the thousands of boys and girls, some not yet in their teens, who were forced to find jobs. --Introduction

The Communist Party in Canada: A History - Avakumovic, Ivan (McClelland and Stewart, 1975)
The Communist Party in Canada is the first thorough study of a political party whose limited size and position outside the mainstream of politics have not lessened its impact and the interest it has aroused among Canadians for over sixty years. Drawing on Communist sources in several languages, Ivan Avakumovic outlines the party's ups and downs from its origins at the turn of the century through to the present day, traces its connects with the American and Russian Communist parties, and describes its internal organization, its policies and tactics, its attitude to the rest of the left wing and other political parties, to labour groups, police, and the general public. Here is an objective, scholarly description, with appeal for the historian and the general reader. --Publisher's description
Keywords: Communism Canada; Communist Party of Canada; Communist Party of Canada History; Communist parties Canada; Geschichte; History; Parti communiste canadien Histoire

Ten Lost Years: Memories of Canadians Who Survived the Depression - Broadfoot, Barry (Paper-Jacks, 1975)
What was the Depression like? This book is made up of memories of it, memories collected by Barry Broadfoot from more than 600 men and women all across Canada. Although the stories they tell are true, anyone too young to remember the Depression will find them almost unbelievable. The Depression - as all its survivors know - was a time when unbelievable things happened regularly.... --Publisher's description

Leonard Hutchinson, People's Artist: Ten Years of Struggle, 1930-1940 - Brown, Lynn Hutchinson; Hutchinson, Leonard (Toward a people's art, 1975)
Leonard Hutchinson: Ten Years of Struggle is the first book in a series to be published by NC Press, collectively entitled Toward a People's Art. The series follows on the general study of our culture, The History of Painting in Canada: Toward a People's Art, and was conceived because NC Press, as Canadian Liberation Publishers, recognizes the need for a whole series of such books on our arts. There is a far vaster heritage of people's art in Canada than can be contained within the pages of one book. --From introduction
Keywords: Hutchinson, Leonard, 1896-

The Bitter Thirties in Québec - Dumas, Evelyn (Black Rose Books, 1975)
[The author] has undertaken to prove incorrect the notion previously widely held that the labour movement militancy associated with modern Quebec was a feature born in the post-World War II period, By examing, through the tradition of oral history, several strikes in the thirties and forties in transportation, textiles and other important industries, and by recording the impressions and feelings of some of the surviving strikers, whether leaders or rank-in-file militants, she captures the mood of the period. --Publisher's description, Translation of: Dans le sommeil de nos os [: quelques grèves au Québec de 1934 à 1944] (1971). Contents: Preface to the English edition (pages 11-14) -- Preface to the French edition (pages 15-18) -- The Basic Picture (pages 19-27) -- The Foreigners' Strike (pages 28-42) -- The Shmata Strikes (pages 43-49) -- The "Bleuets" Strikes (pages 70-77) -- The Tramway Strikes (pages 78-100) -- The Sky Will Be Red Hot (pages 101-127) -- Epilogue (pages 128-130) -- Appendix: The Choice of Conflicts and the Framework of the Study (pages 131-145).
Keywords: Quebec; Strikes

Les travailleurs contre l'Etat bourgeois : avril et mai 1972 - Ethier, Diane; Piotte, Jean-Marc; Reynolds, Jean (L'Aurore : distribution, Maison de diffusion-Québec, 1975)
Cet ouvrage, fruit d'un travail de plus de deux ans, veut cerner ce qu'a été le Front commun intersyndical dans la fonction publique et para-publique en 1971-72. Il a pour objectif d'aider les militants syndicaux (et les autres) à mieux comprendre le Front commun qu'ils ont vécu durant cette période et de leur donner des outils qui leur permettront d'améliorer la qualité de leurs luttes syndicales et politiques - tout en leur offrant une image détaillée et précise de l'état du syndicalisme au Québec à l'heure actuelle. --Résume de l'éditeur
Keywords: Working class -- Political activity -- Québec (Province)

Des milieux de travail à réinventer - Grand'Maison, Jacques (Presses de l'Université de Montréal, 1975)
Monograph on the work environment in Canada, with particular reference to efforts in quality of working life in Quebec - reviews the historical aspects of working conditions, trade union attitudes, group dynamics, workers participation, etc., and examines the type of work organization with would bring job satisfaction to a wide range of industrial worker. Bibliography and references. --WorldCat record
Keywords: Canada; Canadá; Industrial sociology; Industrie Aspect social Québec (Province); Industries Social aspects; Industries Social aspects Québec (Province); Psychologie du travail; Psychology, Industrial; Québec; Sociologie industrielle; Travail, aspect sociologique; Travail, sociologie; Travailleurs; Working class; actitud sindical; ambiente de trabajo; attitude syndicale; bibliografía; bibliographie; bibliography; calidad de la vida de trabajo; condiciones de trabajo; conditions de travail; dinámica de grupos; dynamique de groupe; group dynamics; histoire; historia; history; industrial worker; job satisfaction; milieu de travail; obrero industrial; organisation du travail; organización del trabajo; participación de los trabajadores; participation des travailleurs; quality of working life; qualité de la vie de travail; reference; referencia; référence bibliographique; satisfacción en el trabajo; satisfaction au travail; trade union attitude; travailleur de l'industrie; work environment; work organization; workers participation; working conditions

The Roar of the Twenties - Gray, James H. (Macmillan of Canada, 1975)
The roar of the fabled 1920's reverberated across the Canada's western prairies in ways in ways that were uniquely Canadian and often uniquely western. Decades after its release in 1975, James Gray's trademark energetic prose pulsates with the essence of this flamboyant era when idealism ran rampant across the prairies. Gray captures the: Political frustrations of the farmers and the resulting turbulent Progressive movement and the resulting Wheat Pools Radical idealism of the One Big Union, born after the Winnipeg General Strike in 1919 Gambling fever that struck not only Western Canadians, but all North Americans, spawned by those who put their paychecks in football pools, horse races, and the spectacular ups and downs of the Winnipeg Grain Exchange Social and religious movements such as the birth of the United Church and the Ku Klux Klan. James Gray has written of an exciting and flamboyant era, a time never to be forgotten.
Keywords: 1914-1945; Années vingt (Vingtième siècle); Canada; Canada Histoire 1914-1945; Canada History 1914-1945; Economic history; History; Nineteen twenties; Prairie Provinces; Prairie Provinces Economic conditions; Prairie Provinces History; Prairie Provinces History 1905-1945; Prairie Provinces Social conditions; Provinces des Prairies Conditions sociales; Provinces des Prairies Conditions économiques; Provinces des Prairies Histoire; Provinces des Prairies Histoire 1905-1945; Social conditions

Ouvrons nos contrats, résistons aux injonctions : la grève des travailleurs du transport de Montréal, été 1974 - Guèvremont, Normand (Presses socialistes internationales, 1975)
Keywords: Commission de transport de la communauté urbaine de Montréal Grève, 1974; Montreal Urban Community Transit Commission Strike, 1974

Canadian Labour and Industrial Relations: Public and Private Sectors: Text and Readings - Jain, H. C. (Hem Chand) (McGraw-Hill Ryerson, 1975)
Introductory textbook on labour relations in the public sector and the private sector in Canada - covers theoretical and environmental considerations, institutional framework and legal aspects, the structure of the labour movement, trade unionism, government policy, collective bargaining, the grievance procedure, labour disputes and dispute settlement procedures, etc.
Keywords: Canada; Canadá; Industrial relations; Industrial relations Canada; Relations industrielles; Relations industrielles Canada; arreglo de conflicto; aspect juridique; aspecto jurídico; bibliografía; bibliographie; bibliography; cadre institutionnel; collective bargaining; conflicto de trabajo; conflit du travail; dispute settlement; government policy; grievance; industrial relations; institutional framework; labour dispute; labour movement; labour relations; legal aspect; libro de texto; manuel d'enseignement; mouvement ouvrier; movimiento obrero; negociación colectiva; négociation collective; organización institucional; politique gouvernementale; política gubernamental; private sector; public sector; reclamación; reference; referencia; relaciones laborales; relations de travail; règlement de conflit; réclamation; référence bibliographique; secteur privé; secteur public; sector privado; sector público; sindicato; syndicat; teoría; textbook; theory; théorie; trade union

The History of Canadian Business, 1867-1914 - Naylor, R. T. (Robin Thomas) (Lorimer, 1975)
This comprehensive two-volume history of Canadian business is a detailed account of the development of commerce and industry in the formative period from Confederation to the First World War. Most of author Tom Naylor's information, gathered from contemporary sources and particularly the business press, is recorded here for the first time. This research has led him to offer a fundamental reinterpretaion of Canadian business and economic history which is bound to generate worldwide controversy. In Volume I on the banks and finance capital, the story of the growth of the Canadian chartered banking system is told in detail. Included is an analysis of the many bank failures, and an explanation of the techniques used successfully by the largest chartered banks to dominate banking and finance in the new confederation. Several chapters deal with hitherto unrecorded facets of the development of the financial system of Canada, the major financial institutions and the types of operations they financed. Volume II deals mainly with the development of manufacturing and industry. The rapid growth of foreign branch plants which followed the National Policy is examined in detail, as are business assistance measures like patent laws, tariffs, government subsidies and municipal 'bonusing'. Naylor offers detailed accounts of the rise of big business through the formation of cartels and mergers assembled out of smaller independent operations. These two volumes offer a completely new perspective on the development of the Canadian economy. They cast important new light on the historical forces which lie behind many pressing currrent economic and political issues. --Publisher's description, Lorimer R.T. Naylor traces the insidious interplay of big business and big government in Canada in the period between Confederation and World War I, presenting corruption as the norm rather than an abberation. He tells the often sordid story of the emergence and development of corporate capitalism in Canada during the country's formative years, exposing an epidemic of white-collar crime among the country's elite financial institutions and locating the origins of the modern corporate-welfare state in tax concessions and subsidies. A controversial study that went against the prevailing views of its time, some lauded its publication as an intellectual breakthrough, while others condemned it as a political rant. An unprecedented work in Canadian historiography, The History of Canadian Business, 1867-1914 has been chosen by the Social Sciences Federation of Canada as one of the twenty most outstanding works in the field in the last half of the twentieth century. --Publisher's description of "new edition," McGill-Queen's University Press
Keywords: Industries

"Man Along the Shore!" - The Story of the Vancouver (B.C.) Waterfront as Told By the Longshoremen Themselves 1860's-1975 - Vancouver Longshoremen/ILWU Local 500 Pensioners (ILWU Local 500 Pensioners, 1975)
This is the story of the Vancouver Waterfront - the ships, the docks, the men. It is not primarily a history of the companies - stevedoring, shipping and railways - that operate on the waterfront. Nor is it primarily a record of historical events, of dates and places. It includes some of these but is much more. It is primarily a story of the men who worked on the waterfront, who they were, where they came from, the lives they led, the conditions under which they laboured and the struggles in which they engaged to establish good working conditions on the docks. It is a story of people, of working people, of longshoremen as told by themselves. --Introduction

On Strike: Six Key Labour Struggles in Canada, 1919-1949 - Abella, Irving (James Lewis & Samuel Publishers, 1974)
[This book] focuses on six important - but largely unknown - strikes where Canadian workers fought the combined forces of capital and government for basic union rights and for decent wages and working conditions. The strikes described - the Winnipeg 1919 general strike, Estevan 1931, Stratford 1933, Oshawa 1937, the Ford Windsor strike of 1945, and Asbestos 1949 - were all major events in Canadian labour and political history. They demonstrate the strength of the labour movement, and they show the willingness of governments to use police, troops, intimidation and violence in attempts to break strikes and crush unions. --Publisher's description. Contents: Introduction. The Winnipeg General Strike / David Bercuson -- Estevan, 1931 / S.D. Hanson -- Aid to the civil power: the Stratford strike of 1933 / Desmond Morton -- Oshawa 1937 / Irving M. Abella -- Ford, Windsor, 1945 / David Moulton -- Asbestos 1949 / Fraser Isbester.
Keywords: Labour Movement; Strikes; Unions

Gompers in Canada: A Study in American Continentalism Before the First World War - Babcock, Robert H. (University of Toronto Press, 1974)
Samuel Gompers, the charismatic chief of the American Federation of Labor at the turn of the century, claimed to represent the interests of all workers in North America, but it was not until American corporations began to export jobs to Canada via branch plants that he became concerned with representing Canadian workers. Within a very short time the Canadian labour movement was rationalized into a segment of the American craft-union empire. In order to secure the loyalty of these new recruits, the AFI reduced the national trade-union centre of Canada, the Trades and Labor Congress, to the level of an American state federation of labour. But Gombers failed to perceive the different political, historical, and cultural climates north of the forty-ninth parallel, and his policies inevitably generated friction. Although some Canadian workers felt sympathy for labour politicians inspired by left-wing doctrines and the social gospel movement, Gompers strove to keep Canadian socialists at bay. And although Canadian workers expressed considerable interest in governmental investigation of industrial disputes, Gompers remained inimical to such moves. Canadian labour groups desired a seat on international labour bodies, but Gompers would not allow them to speak through their own delegate. Canadian unions deemed rivals to AFL affiliates were banished. Dues were siphoned off into union treasuries in the US, and American labour leaders kept firm control over organizing efforts in Canada. Perhaps most importance, the AFLs actions at the TLC convention of 1902 its opposition to dual unionism helped spawn a separate labour movement in Quebec. Yet by 1914, following nearly two decades of effort by Gompers, many Canadian workers had become his willing subjects. Though others struggled to loosen Gompers' grip on the Canadian labour movement, Canadian trade unions appeared firmly wedded to the AFLs continentalism. The story of Gompers in Canada has never been properly treated: this book is a significant addition to Canadian and American labour history and to the study of American expansion. Based upon exhaustive research in the Gompers papers, the AFL-CIO archives, and in various Canadian manuscript and newspaper sources, it clearly reveals an important aspect of the growth of American s informal empire at the turn of the century. --Publisher's description. Contents: Introduction -- First encounter --The rise of branch plants -- Organizing boom -- Labour politics in Canada -- Dual unions -- Berlin victory -- A ‘state’ federation -- External enemies -- Jurisdictional disputes and secessions -- Political action -- Master and servant -- Labour continentalism -- Appendixes -- Notes -- Bibliography.

The Anatomy of Poverty: The Condition of the Working Class in Montreal, 1897-1929 - Copp, Terry (Canadian social history series, 1974)

The Workingman in the Nineteenth Century - Cross, Michael S. (Canadian social history series, 1974)
This collection of documents gives a picture of the life of the workingman in the nineteenth century - his conditions of work, his housing, diet, health, and recreations, the way he viewed his problems, and was viewed as a problem by the upper classes, and his gradually developing an interest in unionism. The sources are mostly contemporary accounts, drawn from books, newspapers, and evidence supplied to the Royal Commission on the Relations of Labour and Capital. The documents are livelly, often amusing, always very revealing of the life of the ordinary people. -- Publisher's description
Keywords: Canada; History; Social conditions; Sources; Working class

The Canadian Labour Movement, 1812-1902 - Forsey, Eugene Alfred (Historical Booklet / Canadian Historical Association, 1974)

Women at Work: Ontario, 1850-1930 - Acton, Janice; Goldsmith, Penny; Shepard, Bonnie (Canadian Women's Educational Press, 1974)
Women's work has been fundamental to Canada's development - whether that work has involved serving the wealthy, struggling to maintain her own family, tending the ill, teaching, or producing profits for the owner of a garment factor through sweated labour. ...Women at Work attempts to explore the reality of Canadian women's experiences, and proposes the framework which begins to answer why the double exploitation of women as mothers and workers has persisted to the present day. --Publisher's description
Keywords: Employment; Femmes Travail Ontario; History; Ontario; Women; Women Employment; Women Employment Ontario

A Very Ordinary Life: As Told to Rolf Knight - Knight, Phyllis; Knight, Rolf (New Star Books, 1974)
A life history of a working class woman from the socialist milieu of WWI Berlin, accounts of that world and of emigration to and life in the resource frontier of western Canada from the 1930s to 1970. An underground classic of Canadian and immigrant history which ran through four printings in original. --Author's description

The History of Painting in Canada: Toward a People's Art - Lord, Barry (NC Press, 1974)
A complete history of painting in Canada, from the art of the native peoples right up to the 1970's. This outstanding work explodes many myths about Canadian and Quebecois art. In easy to understand language, it explains the effect on Canadian painting of the French, British , and U.S. imperialist regimes that have ruled Canada. This book shows how art has been part of the fight against that domination. --Publisher's description
Keywords: Painting, Canadian

The Winnipeg Strike: 1919 - McNaught, Kenneth; Bercuson, David Jay (Longman Canada, 1974)

A Ripple, A Wave: The Story of Union Organization in the B.C. Fishing Industry - North, George (Fisherman Publishing Society, 1974)
In 1967 the United Fisherman and Allied Workers Union established a history project to collect historical materials with a view to preparing a comprehensive history of trade union organization in the British Columbia fishing industry. This outline story, the joint work of staff members of The Fisherman, past and present, is the first publication.
Keywords: history

Les travailleurs du coton au Québec, 1900-1915 - Rouillard, Jacques (Collection Histoire des travailleurs québécois, 1974)
Keywords: Cotton trade -- Québec (Province) -- History

Sweat and Struggle: Working Class Struggles in Canada. Vol. 1, 1789-1899 - Scott, Jack (New Star Books, 1974)
Author Jack Scott has spent a lifetime of active involvement in many of the same kinds of working-class struggles he describes in this, his first book.... --Publisher's description
Keywords: Canada; History; Labor disputes; Labor disputes Canada History; Travail Conflits Canada Histoire; Travailleurs Canada Histoire; Working class; Working class Canada History

The Asbestos Strike - Trudeau, Pierre Elliott; Boake, James (James Lewis & Samuel, 1974)
On February 18, 1949 the asbestos industry went on strike at Asbestos, Quebec. During four and a half months, 5,000 miners faced the united forces of the mining companies and the Duplessis government in what turned out to be a bitter, hard-fought confrontation. The strikers received widespread support and sympathy in Quebec. In a dramatic break from tradition, the Catholic church came out strongly their side. The Duplessis government, however, put on a massive show of police power and used mass arrests and widespread beatings to intimidate the workers. Many Quebec intellectuals were active on the strikers' side. Their involvement led to the writing of this book, originally published in 1956. Contributors, including Fernand Dumont, Gérard Pelletier, Gérard Dion, and Pierre Elliott Trudeau, trace the history of the strike and analyze its causes and consequences. Like the strike itself, this book is a landmark. It marks the beginning of a new, critical traditioin of writing on Quebec history and society, and it is a major contribution to the history of the Quebec labour movement. This translation of the original 1956 edition makes the complet text of this important book available to English-speaking readers for the first time. --Publisher's description. Contents: Foreword / Frank R. Scott -- Preface / Jean-Charles Falardeau -- The province of Quebec at the time of the strike / Pierre Elliott Trudeau (pages 1-82) -- Financial history of the asbestos industry / Jean Gérin-Lajoie (pages 83-106) -- History of the trade union movement in the asbestos industry / Fernand Dumont (pages 107-142 )-- History of the strike at Asbestos / Gilles Beausoleil (pages 143-182) -- History of the negotiations (pages 183-204) -- The church and the conflict in the asbestos industry / Gérard Dion (pages 205-226) -- The strike and our judicial system / Charles A. Lussier (pages 227-238) -- The strike and the press / Gérard Pelletier (pages 239-274) -- Six years later / Maurice Sauvé (pages 275-298) -- The strike and the labour movement / Réginald Boisvert (pages 299-332) -- Epilogue / Pierre Elliott Trudeau (pages 333-352) -- Appendix 1: Bibliographical notice (pages 353-354) -- Appendix 2: The Custos report (pages 355-356) -- Appendix 3: Opinions on the police brutalities and extracts from a judgment of the superior court (pages 367-370) -- Appendix 4: The Rocque trial: A case of judicial oversimplification / J.P. Geoffroy (pages 371-376) -- Appendix 5: A reader's guide to The Asbestos Strike / James Boake (pages 377-382).

Then & Now: The Road Between: The Story of the United Steelworkers of America - United Steelworkers of America. Education Department (United Steelworkers of America, 1974)
Illustrated history of the Steelworkers that celebrates the principles of union organizing, service, and the volunteer. Preface by Lynn R. Williams, International President.
Keywords: Canada; History; Labour unions; United States; United Steelworkers of America

Nationalism, Communism, and Canadian Labour: the CIO, the Communist Party, and the Canadian Congress of Labour, 1935-1956 - Abella, Irving (University of Toronto Press, 1973)
This is neither a history of the Canadian Congress of Labour nor of the CIO in Canada, but rather a study of the interaction of the two. Two basic conflicts - one internal, the other external - pervaded this relationship: the internal struggle of both organizations to rid themselves of their Communist-dominated affiliates, and the external battle of the Congress, and to a lesser etent of its CIO affiliates, to achieve and defend their autonomy in the face of the aggressive incursions of the American unions to the south. A corollary to this latter conflict was the desperate struggle of the Congress to maintain its authority over its international affiliates. These two themes - the internal threat from the Communists and the external threat from the Americans - dominate the entire history of the Congress from its creation in 1940. Besides these two issues, all others seem insigificant. ...This study is based largely on the files of the Canadian Labour Congress and its affiliates. Interviews have filled in whatever information was not available in this voluminous correspondence. --From author's preface

Les travailleurs québécois, 1851-1896 - Bélanger, Noel (Histoire des travailleurs québécois, 1973)

Le travailleur québécois et le syndicalisme - Desrosiers, Richard; Héroux, Denis (Cahiers de l'Université du Québec, 1973)
Keywords: Trade-unions -- Québec (Province)

Primary Sources In Canadian Working Class History, 1860-1930 - Hann, Russell G.; Kealey, Gregory S.; Kealey, Linda; Warrian, Peter (Dumont, 1973)
Bibliography of primary sources including manuscripts, newspapers, pamphlets, and government documents from Canadian repositories.

Aspects historiques du mouvement ouvrier au Québec - Harvey, Fernand; Maheu, Louis; Charpentier, Alfred; Vallières, Pierre; Bélanger, Paul; Tremblay, Louis-Marie; Desrosiers, Richard (Éditions du Boréal express, 1973)
Un choix de textes récents qui reconstituent une histoire thématique du mouvement ouvrier québécois depuis le milieu du XIXe siècle jusqu'à nos jours. --Résumé de l'éditeur
Keywords: Labor unions

Industrial Relations in Canada - Jamieson, Stuart (Macmillan Company of Canada, 1973)
First published in 1957, [this book] has established itself as one of the best brief surveys on the subject available today. Many of the features of the original book have been retained in this second edition: its conciseness, its clarity of style, and its analysis of Canadian labour relations in the wider North American context. In the complex and dynamic field of of industrial relations in Canada, many important developments have occurred since 1957. Even in such a slow-moving area as labour disputes legislation and pollicy, provincial and federal governments have passed a considerable amount of new legislation since 1957. In his extensive revision, Professor Jamieson deals with these developments. This new edition also places increased emphasis on problem areas in labour relations, for example, the labour scene in Quebec, the incidence of industrial conflict and strikes, and the influence of American-dominated unions in Canada. For this edition Professor Jamieson has provided a revised and enlarged bibliography which should serve as excellent guide to the increasing range of literature now available in the field of industrial relations. --Publisher's description

Canada Investigates Industrialism: The Royal Commission on the Relations of Labor and Capital, 1889 (abridged) - Kealey, Gregory S. (Social history of Canada, 1973)
In the 1880s Canadians began to cope with the meaning of their emerging industrial society. During that decade the federal government first investigated industrial conditions and provincial governments passed Canada's first factory legislation. The same period saw the resurgence of an articulate and angry labor movement protesting against the excesses of modern industry. Through the Royal Commission on the Relations of Labor and Capital we can perhaps gain our best insight into the everyday world of workers and capitalists in late nineteenth-century Canada. The commission gathered evidence in Ontario, Quebec, Nova Scotia, and New Brunswick and talked to thousands of workers, businessmen, and other concerned citizens. This edited version of its investigation includes much of the best testimony; it describes working class living conditions, the emergence of organized labor, and the attitudes of businessmen to industrial capitalism. The testimony takes us with the commissioners on their tour of New Brunswick cotton mills, Capre Breton coal pits, Ontario shops and foundries, and Quebec City wharves; it explores as well the darkest corners of Montreal cigar factories. Industrialists discuss profits, markets, sources of raw material, and problems with labor. But what is perhaps more important, the working people themselves are also heard, men and women who in most historical records appear as little more than cold statistics. The warmth and humanity of these Canadians reflecting on their lives and on the society around them bring the commission documents to life. Aging craftsmen, ten-year-old saw-mill hands, girls from the spindles and looms, describe their workplaces, wages, hours, and aspects of their lives away from the job. These almost unique interviews allow us to enter their intellectual and cultural world – to learn of their past and present and of some of their hopes and aspirations. The Labor Commission reports and testimony are essential for an understanding of the Canadian working class as it was being transformed by the new techniques of industrial production. --Publisher's description
Keywords: Canada; Industrial relations; Industrial relations Canada; Relations industrielles Canada

Working Class Toronto at the Turn of the Century - Kealey, Gregory S. (New Hogtown Press, 1973)
This paper represents a distillation of an earlier, more ambitious essay on the creation of an industrial working class in late Victorian Toronto; its focus will be on living and working conditions during the transition to industrial capitalism, a necessary prelude to any discussion of working class consciousness.
Keywords: Working class -- Ontario -- Toronto

The Trade Union Movement of Canada, 1827-1959 - Lipton, Charles (NC Press, 1973)
Year by year the trade union movement assumes new significance. [This book] records labour's progress through about 130 years of Canadian history. During these years there were thousands of strikes, negotiations, organizing campaigns, legislative and political struggles. Many of the outstanding events are described here. One of the important features of this book is its outline of how Canadian unions came to form connections with United States unions - the origins, status, and significance of International Unions in Canada. The writer has sought to give an account of trade union evolution as a whole from the period 1827-1959. In addition he has outlined certain continuing spheres of Labour's effort, such as organization of the unorganized, the fight for better conditions, legislative and political action, peace and Canadian independence. -- Publisher's description
Keywords: Labor unions -- Canada -- History

Recollections of the On to Ottawa Trek - Liversedge, Ronald (Carleton library series, 1973)
Table of contents: Introduction -- Chronology of the Vancouver Strike and the On to Ottawa Trek, 1935. Part 1: Recollections of the On to Ottawa Trek. A Note on Editing, part 1. Prelude to Struggle -- The Origin of the Family -- The Slave Camps -- Strike -- The Trek. Part 2: Documents Related to the Vancouver Strike and the on to Ottawa Trek. A Note on Editing, part 2. The Report of the Macdonald Commission -- The Vancouver Relief Camp Strike -- The On to Ottawa Trek -- The Interview Between the Delegation of Strikers and the Prime Minister and His Cabinet, June 22, 1935 -- Continuing Documents on the Trek -- The Regina Riot -- Debate in the House of Commons . Footnotes for Part 1. Suggestions for Further Reading.
Keywords: Depressions; Labour camps; Unemployed

The Winnipeg General Strike - Masters, Donald C. (Donald Campbell) (University of Toronto Press, 1973)
This job very much needed doing, and Dr. Masters has done it in a scholarly, judicial, yet forthright manner. The hysteria engendered by the Winnipeg general strike of 1919, heightened by the singularly unenlightened form that government intervention took, continues to trail clouds of distortion and bitterness. By careful analysis of facts, circumstances, and personalities of the strike leaders, Dr. Masters has cleared away the haze and given us a historical record of the utmost value. --review, Canadian Forum (on book jacket cover)
Keywords: General Strike (Winnipeg, Manitoba : 1919)

Winnipeg 1919: The Strikers' Own History of the Winnipeg General Strike - Winnipeg Defence Committee (James Lewis & Samuel, 1973)
This book presents a remarkable account of the 1919 Winnipeg General Strike, written by the workers who organized the strike. Their day-to-day description of events was prepared for pro-labour sympathizers across Canada and to counteract anti-strike accounts carried in the mass. It is a particularly lively and informative description of this landmark events. --Publisher's description
Keywords: General Strike, Winnipeg, Man., 1919

The Bunkhouse Man: A Study of Work and Pay in the Camps of Canada, 1903-1914 - Bradwin, Edmund W.; Burnet, Jean (Social history of Canada, 1972)
Journalists and poets, economists and political historians, have told the story of Canada's railways, but their accounts pay little attention to the workers who built them. The Bunkhouse Man is the only study devoted to these men and their lives in construction camps; a pioneering work in sociology, it is still the best description of what it was like to be a working man in Canada before the First World War. E.W. Bradwin drew on his own experience as an instructor for Frontier College, working alongside his students during the day and teaching at night, to present this graphic portrait of life in the camps from 1903 to 1914. No detached observer, Bradwin played a vigorous role trying to improve the lot of the men--practicing the sociology of engagement advocated by radical sociologists today. Work camps have existed in Canada from early pioneer times to the 1970s and are unlikely to disappear. In the years of Bradwin's study there were as many as 3,000 large camps employing 200,000 men, 5 per cent of the male labour force. Like the settling of the prairies, these camps are a characteristic Canadian phenomenon, but they have never drawn comparable attention. The republication of The Bunkhouse Man, with an introduction by Jean Burnet, makes available once more a work essential to the exploration of Canada's history and social structure. --Publisher's description

Quebec - Only the Beginning; The Manifestoes of the Common Front - Drache, Daniel (Studies Quebec, 1972)
These manifestoes, issued by the Confederation of National Trade Unions, Quebec Federation of Labour, and Quebec Teachers Corporation, represent a new stage in the Quebec independence movement. They are a call to working-class politics. The Quiet Revolution brought the middle class to life. With the appearance of the manifestos, the working class enters Quebec politics as a coherent active force in its own right. -- Editor's introduction
Keywords: Labor unions Political activity; Labor unions Political activity Québec (Province); Québec; Syndicats Activité politique Québec (Province)

Work Camps and Company Towns in Canada and the U.S.: A Working Bibliography. - Knight, Rolf (Draegerman, 1972)
An annotated bibliography of about 290 items ranging from books to articles in popular journals intended as an introductory guide for student research of this topic. Knight's bibliography deals with life and work in the company towns, camps and single enterprise communities of Canada and the U.S. during the last eighty years. Within it, there are economic studies , sociological surveys, local histories, but also memoirs and autobiographies that touch on the daily lives of the primary resource workers whose labour built these countries. --Publisher's description. Contents: Nobody here but us (pages 1-14) -- Work camps and company towns. In B.C. (pages 14-38). In Canada (pages 39-58). In U.S. (pages 59-90).

The Trade Union Movement in Canada - Lazarus, Morden (Co-operative Press Associates, 1972)
"This lecture was originally given in a course on 'Contemporary Issues in Economics and Finance' at the University of Toronto Continuing Education Program in Extension, July 1971. It was updated for an economics class at Wellington College, University of Guelph, February 1972. This is the revised text."
Keywords: Trade-unions -- Canada

Capitalism and the National Question in Canada - Teeple, Gary (University of Toronto Press, 1972)
Very little has been thought or published about Canada that uses a Marxist critique of capitalism and its dynamics. This book aims to advance such thinking by analysing the reasons for the openness of the dominion to capitalist domination to labour domination from the United States, and to a sell-out policy in regard to its land and farms. Capitalism is the accepted, and so intellectually an almost invisible, way of life in Canada. Very little has been thought or published about Canada that uses a Marxist critique of capitalism and its dynamics, and this book aims to advance such thinking by analysing the reasons for the openness of the dominion to capitalist domination, first by Europeans and then by Americans, to labour domination from the United States, and to a sell-out policy in regard to its land and farms. The dependency of the Canadian ruling class on foreign capitalists is an important factor in Canada’s continued colonial-mindedness, and the rise of nationalism in Quebec is based on the inevitabilities of the class antagonisms set up by capitalism. The authors believe that it is only through such Marxist theory and practice that a way can be found for Canada to escape at last from imperialist exploitation and that a way can be found to shape a socialist future for the whole country. --Publisher's description
Keywords: Social classes -- Canada

Working People: Life in a Downtown City Neighbourhood - Lorimer, James; Phillips, Myfanwy (J. Lewis [and] Samuel, 1971)
This book is a portrait of the people and events of a working-class Toronto neighbourhood under pressure from developers and middle-class renovators. The book is a classic, intimate study of the people of Toronto's East of Parliament neighbourhood in the 1970's, a time when the working-class district came under unprecedented pressure from developers and middle-class gentrification. An unconventional account, Working People combines a wide variety of materials - interviews, economic analysis, songs, jokes, newspaper advertisements, community newspapers, photographs - to present an unparalleled portrait of a changing urban community in depth. Working People remains a fascinating record of a community in transition. --Publisher's description
Keywords: City and town life; Neighborhoods; Ontario Toronto; Poor; Toronto (Ont.) Poor; Vie urbaine

Minetown, Milltown, Railtown: Life in Canadian Communities of Single Industry - Lucas, Rex A. (University of Toronto Press, 1971)
The company town, source of so much of Canada's wealth, was - and is - a place with nowhere to hide. First published in 1971, Rex Lucas's Minetown, Milltown, Railtown is a groundbreaking study of what it's like to live in such communities. Today, with the oil-sands boom and rising commodity prices affecting everything from the value of the Canadian dollar to the balance of power within Confederation, single-industry towns remain as central as ever to the country's economic and social life. Minetown is a compelling portrait not just of Canada's past, but of its present and future, too. Minetown, Milltown, Railtown: Life in Canadian Communities of Single Industry is a Wynford Book - one of a series of titles representing significant milestones in Canadian literature, thought, and scholarship. New introductions place each book in a modern context and show its continuing relevance. --Publisher's description (Oxford University Press)
Keywords: 1945-; Canada; Communauté; Community life; Company towns; Conditions sociales; Conditions économiques; Economic conditions; Industrial; Industry; Oil sands/Tar sands; Resource-based communities; Social conditions; Villes fermées

The Brandon Packers Strike: A Tragedy of Errors - MacDowell, G. F. (George F.) (McClelland and Stewart, 1971)
Illustrates the need for reform and reinterpretation of the labour laws of Canada, and Manitoba in particular. -- Publisher's description

Radical Politics and Canadian Labour, 1880-1930. - Robin, Martin (Research series (Queen's University (Kingston, Ont.). Industrial Relations Centre), 1971)

Question nationale et classes sociales au Québec (1760-1840) - Bourque, Gilles (Collection Aspects, 1970)
Table des matières: Introduction -- Cadre théorique -- Hypothèses. Première partie : 1760-1791. 1- Conquête et bourgeoisie française : Qu’est-ce qu’une bourgeoisie ? -- Conquête et bourgeoisie française --Conséquence pour la société française. 2- Conquête et aristocratie cléricale : Conquête et collaboration -- Élaboration de la politique de conciliation -- Opposition anglo-saxonne à la politique de conciliation -- Volonté de collaboration de l’aristocratie cléricale -- Acte de Québec -- Éléments de la collaboration de l’aristocratie cléricale -- Idéologie de la collaboration -- Portée de la conciliation -- Déclin des seigneurs -- Conclusion. 3- Apparition d'une bourgeoisie anglo-saxonne : Économie 1760-1792 -- L’Acte constitutionnel de 1791. 4- Le peuple : Le régime seigneurial -- Peuple et classe collaboratrice -- Conclusion. Deuxième partie : 1792-1815. Introduction. 1- Petite-bourgeoisie professionnelle : Idéologie nouvelle -- Oppositions de classes et de nations -- Conclusion. 2- Aristocratie cléricale. 3- La bourgeoisie marchande canadienne-anglaise : L’économie -- Les fourrures -- L’agriculture -- Le bois -- La guerre -- Aspect socio-politique -- Conclusion. 4- Le peuple : Conclusion. Troisième partie : 1815-1850. Introduction. 1- Société canadienne-française : Les quatre-vingt-douze résolutions -- Composition, groupes et factions -- Idéologie --Lutte de classe et lutte nationale --Le peuple --Londres. 2- Société canadienne-anglaise 1815-1836 : Économie -- Bourgeoisie marchande canadienne-anglaise -- L’union --Lutte et alliance -- Conclusion 1815-1836. 3- Guerre civile et guerre nationale 1837-1838. Rébellions -- Caractère du phénomène -- La marche de l’union 1838-1840. Conclusion générale -- Aspect théorique -- Bibliographie.
Keywords: 1837-1838; Canada; Canada Histoire 1837-1838 (Rébellion); Canada History Rebellion, 1837-1838; Canadians, French-speaking Social conditions; Classes sociales Québec (Province); History; Québec; Québec (Province) Conditions sociales; Québec (Province) Histoire; Québec (Province) History; Social classes; Social classes Québec (Province)

Répertoire des grèves dans la province de Québec au XIXe siècle - Hamelin, Jean; Larocque, Paul; Rouillard, Jacques (Presses de l'Ecole des hautes études commerciales, 1970)
Presents an annotated chronology of strikes and lockouts in Quebec from 1843 to 1900. Includes sources.
Keywords: Strikes and lockouts -- Québec (Province)

The On to Ottawa Trek - Howard (Hoar), Victor (Problems in Canadian history, 1970)
Keywords: Canada; Canada Histoire; Canada History; Chômeurs Canada; Crises économiques; Depressions; History; Unemployed; Unemployed Canada

Chalk, Sweat, and Cheers: A History of the Manitoba Teachers' Society Commemorating Its Fiftieth Anniversary, 1919-1969 - Chafe, J. W. (James Warren) (Manitoba Teachers' Society, 1969)
Chalk, Sweat and Cheers, A History of the Manitoba Teachers’ Society was published for the Society’s fiftieth anniversary in 1969, following two years of intensive research and assistance from fellow teachers. [The author] was selected to lead the project because, in the words of the Society’s President, of his “long and distinguished teaching career not only as a recognized writer, but a character in the history he relates.” His complex story of the MTS told of the evolution of the Province, the livelihood of teachers, and the fights for a rise in educational standards. It was thorough and detailed, ending with a severe reminder that, despite technological advances and innovations, teachers remain at the core of education. --From author biography at Manitoba Historical Society Archives' website
Keywords: History; Manitoba Teachers' Society History

The Power & Dilemma of the Trade Unions - Dowson, Ross (Workers Vanguard, 1969)
For many years the Workers Vanguard [newspaper] has closely followed and participated in developments in the trade union movement. A collection of back issues would present and accurate and moving story of the victories and defeats, the present circumstances, and the future prospects before this mighty and complex movement forged by the Canadian working class. The article that follows is a summary, an evaluation and a projection of Canadian labor's struggles. -- Introduction
Keywords: Labor unions -- Canada

The Long March: History of the Ontario Public School Men Teachers' Federation - Hopkins, R. A. (Robert Alexander) (Baxter, 1969)
The writing of this account of the Ontario Public School Men Teachers' Federation has been based on the information contained in the minutes, annual reports, newsletters, correspondence, confidential files, the "Advance," the "Courier," and the author's personal diaries of 1934-69. ....I am grateful especially to those who contributed so much in interviews and by correspondence. The first-hand knowledge of so many teachers and former teachers has been invaluable. --Author's acknowledgements
Keywords: Ontario Public School Men Teachers' Federation

Canadian Labour in Politics - Horowitz, Gad (Studies in the Structure of Power: Decision Making in Canada, 1968)
This important new study in Canadian politics discusses the role of socialism in Canada. By means of comparison between the English-Canadian and the American political importance of socialism in Canada than the United States. In this section Louis Hartz's theory of "fragment" cultures is carried forward and applied to Canada. The remainder of the book is devoted to a detailed historical study of the relationship between the labour movement and the socialist parties in Canada. It starts in the early years of the century and follows the story through to its significant conclusion—the support (and formation) by many Canadian unions of a labour party. The brilliant analysis of Canadian politics in Hartzian terms restores ideology to a place in our political culture, and the meticulous, objective recounting of labour's involved in the formation of the NDP is a timely and valuable contribution to our limited understanding of how Canadian political parties "live and move and have their being." The main sources used by the author were correspondence, minutes, and other materials in the files of the NDP and the Canadian Labour Congress, and personal interviews with labour leaders and socialist politicians. --Publisher's description

Ecological Factors in Changing Economy and Social Organization Among the Rupert House Cree - Knight, Rolf (Anthropology Papers / National Museum of Canada, 1968)
A brief ethnographic study done for the National Museum of Canada in 1961-62 focusing on the then continuing economic importance of hunting and trapping for the native people of the region. --Author's description

Agrarian Socialism: The Cooperative Commonwealth Federation in Saskatchewan: A Study in Political Sociology - Lipset, Seymour Martin (Anchor books, 1968)
The Cooperative Commonwealth Federation government in Saskatchewan, which was elected in 1944, remains the only government with avowed socialist goals to have come to power in Canada or the United States. In 1949, Seymour Martin Lipset wrote Agrarian Socialism, which has since become a classic, a study of the social background that enabled the movement to succeed in the region that it did. The CCF government, however, remained in power for twenty years. So this new Anchor edition contains not only a new introduction by the author, evaluating his earlier research in terms of later developments, but five new chapters by other sociologists who, taking off from the findings in Agrarian Socialism, studied later developments in Saskatchewan.... -- Publisher's description
Keywords: Co-operative Commonwealth Federation. Saskatchewan; Political Science(General); Politics and government; Politieke wetenschappen (algemeen); Saskatchewan; Saskatchewan Politics and government; Socialism; Socialism Saskatchewan; agricultural policy; agriculture; canada; landbouw; landbouwbeleid; politics; politiek; saskatchewan; socialism; socialisme; sociologie; sociology

A Study of the Changing Social, Economic, and Political Background of the Canadian System of Industrial Relations - Pentland, H. Clare (Harry Clare); Canada. Task Force on Labour Relations (Draft study (Canada. Task Force on Labour Relations), 1968)

Soldiers of the International: A History of the Communist Party of Canada, 1919-1929 - Rodney, William (Canadian studies in history and government, 1968)
Covers the origins and growth of the Canadian party in detail and shows that its programme and development paralleled those of other Communist parties throughout the world. --Publisher's description
Keywords: Canada. CPC; Communist Party of Canada; Parti communiste canadien

High Button Bootstraps: Federation of Women Teachers' Association of Ontario, 1918-1968 - Shackleton, Doris French (Ryerson Press, 1968)

Not by Gods but by People: The Story of Bella Hall Gauld - Vance, Catharine (Progress Books, 1968)
Her life spanned two centuries and led from pioneer social welfare work and church activity as a contemporary of J.S. Woodsworth to directorship of Canada's first University Settlement house in Montreal; and then forward to the larger horizons of the modern day labour and socialist movement. Bella Hall's epitomizes the unceasing struggle of ordinary men and women for a better life and is a tribute to the real makers of Canada. --Publisher's description
Keywords: Gauld, Bella Hall, 1878-1961

The Winnipeg General Strike - Balawyder, Aloysius (Copp-Clark, 1967)
The Winnipeg General Strike is undoubtedly one of the most controversial events in Canadian history. Many Canadian newspapers and a considerable portion of correspondence among the federal, provincial and municipal officials claimed that strike was inspired by the Bolsheviks who allegedly aimed to create a soviet in Winnipeg. On the other hand, the majority of the strikers as well as labour leaders contended that strike was a last-resort weapon used by the workers to gain the rights of collective bargaining and to obtain higher wages. Documents, newspapers editorials, and extracts from critical works have been selected for giving the students a relatively complete picture of government and public opinion of the causes, events and effects of this strike. There has been one notable exception, for no excerpt from the Robson Report is included in this volume. --From author's preface
Keywords: General Strike, Winnipeg, Man., 1919

International Unionism: A Study in Canadian-American Relations - Crispo, John H. G. (McGraw-Hill of Canada, 1967)
The relationship between the Canadian and American labour movements is unique. It has given rise to considerable controversy and yet has been the subject of surprisingly little intensive examination. While a fair amount has been written about this unusual phenomenon, little of this material is very complete or incisive. As a result the door has been left open for those with an axe to grind to express themselves freely on the subject without the fear of contradiction based on cold hard facts. This study may reduce the frequence of such utterances in the future. It endeavours to deal objectively with an area of Canadian-American relations where emotions and prejudices have distorted public debate. Many of the events which have provided fuel for this debate over the past few years are dealt with, including the Seafarers' International Union dispute on the Great Lakes and the Internaitonal Typographical Union strike againist the three Toronto newspapers. --Preface. Contents: Introduction (pages 1-10) -- Explaining the presence of international unionism in Canada (pages 11-49) -- The Canadian membership within international unions (pages 50-95) -- Relations between the central federations of labour in Canada and the United States (pages 96-145 -- The unity and structure of the Canadian labour movement /(pages 146-178) -- Collective bargaining policies and practices in Canada (pages 179-230) -- Policies and practices outside the area of collective bargaining (pages 231-258) -- The flow of funds and benefits across the border (pages 259-278) -- Employer and government attitudes towards international unionism (pages 279-301) -- Summary and conclusion (pages 302-324) -- A selected bibliography (pages 325-327).

The Role of International Unionism in Canada - Crispo, John H. G. (Canadian-American Committee, 1967)
The relationship between the Canadian and American labour movements is unique. It has given rise to considerable controversy and yet has been the subject of surprisingly little intensive research. As a result those with an axe to grind have been able to express themselves without fear of contradiction based on cold, hard facts. This study may reduce the frequency of such utterances. It endeavors to deal objectively with an area of Canadian-American relations where emotion and prejudice have distorted public debate. The reader will have to judge for himself whether sufficient detachment has been shown to achieve real objectivity. --From author's preface
Keywords: Labor unions -- Canada

No Power Greater: A Century of Labour in British Columbia - Phillips, Paul (B. C. Federation of Labour, Boag Foundation, 1967)
[The author] is the research director of the British Columbia Federation of Labour and is responsible for researching and writing the Federation's briefs on matters concerning labour. This book is his first and grew out of his thesis on the British Columbia labour movement spanning the years 1917-1940. --From author's note on back cover
Keywords: British Columbia; Canada; Colombie-Britannique; Histoire. Labor unions. Genre/Form: History; Histoire. Syndicats; History. Labor unions; History. Syndicats; Labor Unions

Canadian Labour and Politics: A Short History on the Development of the Canadian Labour Movement and Its Relationship to and Influence on the Canadian Political Scene - Scotton, Cliff (Political Education Dept., Canadian Labour Congress, 1967)
Keywords: Canada; Labor unions Political activity; Labor unions Political activity Canada; Syndicats Activité politique Canada

Industrial Relations: Challenges and Responses - Crispo, John H. G. (Heritage, 1966)
Industrial relations, which in the past have focused almost entirely on union-management relations, have recently been expanded to include such new areas of interest as manpower and poverty problems. At the University of Toronto a new Centre for Industrial Relations has been established, a research-oriented institution whose primary objective is to further scholarly investigations into all phases of industrial relations. To launch the new Centre a conference was held with distinguished Canadian and international authorities invited to discuss the challenges and responses for Industrial Relations in the next decade, from various points of view. This volume, based on the papers presented, will be a welcome contribution to knowledge in this challenging field. In Part I, "An International Perspective," David A. Morse considers the conference's general theme in terms of its world-wide ramifications. Part II, "Collective Bargaining in an Age of Change," is devoted mainly to a discussion of the impact of industrial change on collective-bargaining institutions and practices. James R. Bright begins with a reminder that there are two schools of thought about the effect of automation upon such variables as skill and wage differentials. Then Frederick Harbison and Arnold R. Weber assess the recent record of collective bargaining: Professor Harbison provides a wide-ranging analysis of the performance of the American collective-bargaining system to date, and Professor Weber describes the effect of technological change upon the respective power of union and management, upon negotiating procedures, and upon the substantive results of collective bargaining. Harry W. Arthurs explores the role of law in coping with change, especially the technological variety. The third part of the volume, "On the Frontier of Industrial Relations," considers two of the many new industrial relations problems: Wilbert E. Moore, discussing the individual in an organizational society, asks for a reconsideration of the roles of institutional responses to the challenges posed by industrialization. Finally, there are two discussions devoted to one of the most pressing economic and social problems: poverty. The Honourable Maurice Sauvé, who, as Canada's Minister of Forestry, is in charge of the Agriculture Rehabilitation and Development Act, discusses the earnest response of governments to the challenge of poverty; Tom Cosgrove, discussing the United States "war on poverty," reviews the dimensions of the challenge posed by poverty in the United States and outlines the federal legislative response to date. These provocative contributions should be received with great interest by representatives of labour, management, and government, as well as by those members of the public who are concerned with the problems of a growing industrial society. --Publisher's description
Keywords: Collective bargaining

The Vertical Mosaic: An Analysis of Social Class and Power in Canada - Porter, John A. (Studies in the structure of power, decision-making in Canada, 1965)
This book looks at two important aspects in Canadian society: its class structure and the composition of its elites or power holding groups. A recurring theme in the analysis of both class and elite groups is that Canada has found itself in the middle of the twentieth century with inadequate institutional arrangements for the industrial society it has become. Its educational systems have failed to provide the necessary skills which in large measure have been recruited through immigration. Its elites have been drawn largely from middle and upper class "British charter groups." The author further submits that the strong emphasis in the Canadian value system on regionalism and ethnic differentiation has resulted in the fragmentation of the society, particularly at the political level, and lef tit incapable of dealing with some of its major problems as an industrial society. Although this is a sociological study in which evidence in related to social theory, the author has tried to avoid technical terms, and this, together with the particular relevance at the present time of a discussion of the nature of Canadian society, will make this book interesting to laymen as well as specialists. --Publisher's description. Contents: Part I: The Structure of Class 1. Class and Power: The Major Themes 2. Class, Mobility, and Migration 3. Ethnicity and Social Class 4. Classes and Incomes 5. Rural Decline and New Urban Strata 6. Social Class and Educational Opportunity Part II: The Structure of Power 7. Elites and the Structure of Power 8. The Concentration of Economic Power 9. The Economic Elite and Social Structure 10. The Structure of Organized Labout 11. The Labour Elite 12. The Canadian Political System 13. The Political Elite 14. The Federal Bureaucracy 15. The Ideological System: The Mass Media 16. The Ideological System: The Higher Learning and the Clergy 17. Relations Between Elites Appendixes 1. Class and Social Structure: Tables and Figures 2. The Concentration of Economic Power 3. How the Other Elites Were Selected.
Keywords: Canada; Canada Conditions sociales; Canada Social conditions; Classes sociales Canada; Social classes; Social classes Canada; Social conditions

Faith, Sweat, and Politics: The Early Trade Union Years in Canada - Shackleton, Doris French (McClelland and Stewart, 1962)
Keywords: Labor unions -- Canada

Justice Through Power: A Study of Labor in Its Present Situation - Boyle, Thomas O'Reilly (Longmans, 1961)
"Our unions cannot get us started to work; they are geared to help only the employed worker, and they can do no more for the unemployed than they can for the dead - send condolences." Faced with this brutal fact by a notice of lay-off, Tom Boyle decided to spend his enforced leisure in trying to discover "what labor should do to stop this sort of thing." Needless to say, this one question opened up whole areas of other questions - the actual purpose and value of unions, the efficacy of strikes, where union funds go, how wage rates are set and how wages are spent, the relation of union to management (and its trained bargainers) - and now, five years and many lay-offs later, he sums up his findings in this thoughtful, lively book, Justice Through Power. Since unions have no economic power to provide work, Canadian labor must acquire political power if it is to control its own well-being, he concludes, after a careful and entertaining investigation of Canada's present-day society and such fascinating questions as whether or not there are recognizable classes in this country and, if so, which class really sways the Government. Boyle believes that the workers exert no actual political power to-day, although their potential power is obvious; and "the proposed party sits comfortably within our constitution." He conducts his examination with originality and a keen insight born of practical experience, bringing to this study of present-day Canada attributes all too rarely found in writers in this field - warmth of understanding and a refreshing sense of humour. --Publisher's description
Keywords: Canada; Canada Social conditions 1945-1971; Labor laws and legislation; Labor laws and legislation Canada; Labor unions Political activity; Labor unions Political activity Canada; Syndicats Activité politique Canada

It Was Never Easy, 1908-1958: A History of the Canadian Brotherhood of Railway, Transport and General Workers - Greening, William E.; Maclean, Murdoch MacKay (Printed by Mutual Press, 1961)
The story of the development of what is now the Canadian Brotherhood of Railway, Transport and General Workers, from the initial meeting in Moncton in October, 1908, to its present status of one of Canada's most important unions, is one which should be read with pride by any Canadian, and which should be of deep interest to the workers of the nation, organized and unorganized. I am very happy that this history was undertaken during my term in office as National president, and that it is available on the occasion of the 1961 convention of the Brotherhood. --From preface by William J. Smith
Keywords: Canada; Canadian Brotherhood of Railway, Transport and General Workers; Railroads Canada Employees; Railroads Employees; Transport workers; Transport workers Canada; Travailleurs des transports Canada

Les bourgeois de la compagnie du Nord-Quest: récits de voyages, lettres et rapports inédits relatifs au Nord-Quest canadien - Masson, L. R. (Louis Rodrigue) (Antiquarian Press, 1960)
Keywords: Canada Canadian Northwest; Nord-Ouest canadien Descriptions et voyages; North West Company; Northwest, Canadian Description and travel; Travel

The Luck of Ginger Coffey - Moore, Brian (Little, Brown, 1960)
Ireland was too small for Ginger Coffey. No matter how hard he tried to get on, he just ended up as a glorified errand boy. That was why he emigrated to Canada with his wife and daughter. But even there his manifold talents were slow to be recognized. By the author of "The Colour of Blood"
Keywords: 1900-1999; Canadian fiction; Canadian fiction 20th century

The Compassionate Rebel: Ernest E. Winch and His Times - Steeves, Dorothy G. (Boag Foundation, 1960)
[This book] is not only the story of Ernest Winch, but an account of the early socialist and labour activities in British Columbia in which Ernest became involved with a bird's eye view of the legislative events during his tenure. It describes the evolution of a man who was a revolutionary socialist during the twenties and became one of the most persistent and successful reformers in Canada during his career in the B.C. legislature. --Publisher's description
Keywords: Biographies; Biography; British Columbia; British Columbia Politics and government; British Columbia Politics and government 1903-1952; Co-operative Commonwealth Federation; Colombie-Britannique Politique et gouvernement 20e siècle; Politicians; Politicians British Columbia Biography; Politics and government; Socialism; Socialism Canada, Western; Socialists; Socialists British Columbia Biography; Western Canada; Winch, Ernest E., 1879-1957; Winch, Ernest Edward, 1879-1957

A Prophet in Politics: A Biography of J.S. Woodsworth - McNaught, Kenneth William Kirkpatrick (University of Toronto Press, 1959)
In this elegant and rigorously researched work, Kenneth McNaught details the life, work, and principles of J.S Woodsworth and shows the powerful moral and political force that the pacifist, Methodist thinker exerted on Canadian politics. Woodsworth first went to the House of Commons in 1922, and became leader of the Cooperative Commonwealth Federation at its formation in 1933. A socialist to the end, he exhibited his anti-war convictions to Parliament, when, in 1939, he alone spoke out against joining the war in Europe. Woodsworth's ideas and strong social conscience helped to shape the development of the welfare state in Canada, and have left an intellectual legacy in both socialist and liberal circles. A Prophet in Politics marks the progress of socialism in Canada, as well as the economic and political conditions in the first half of the twentieth century. McNaught, who died in 1997, is himself an important figure in Canadian history, having fought as a professor of history for academic freedom and having brought the scholarly discussion of national politics into the public sphere. At the time of its original publication, Globe and Mail reviewers called it 'a definitive biography that in drama and organization ranks with the best books about the makers of Canada.' This edition, presented in the 'Reprints in Canadian History' series, includes a new introduction by Allen Mills. --Publisher's description, 2017 reprint edition
Keywords: Woodsworth, J. S. (James Shaver), 1874-1942

Early Printers and Printing in the Canadas - Gundy, H. Pearson (Bibliographic Society of Canada, 1957)
Based on papers given to the Sunday Club, Queen's University, March 17, 1956 and to the annual meeting of the Bibliographic Society of Canada, June 14, 1956.
Keywords: Canada; Composition Edition Histoire Imprimerie Imprimeur Typographe Typographie; History; Imprimerie Canada Histoire; Imprimeurs; Imprimeurs Canada; Printers; Printers Canada; Printing; Printing Canada History; Printing Documents, Printing of; printers (people)

Industrial Relations in Canada - Jamieson, Stuart Marshall (Macmillan Company of Canada, 1957)
Contents: Preface, by Adolf Sturmthal -- Economic and social setting -- Origin and growth of the Canadian labour movement -- Structure, government and policies of Canadian unionism -- Government policy -- Appendix -- Notes -- Suggested readings.

La grève de l'amiante : une étape de la révolution industrielle au Québec - Trudeau, Pierre Elliott (Éditions Cité libre, 1956)
Keywords: Grève de l'amiante, Québec, 1949

J.S. Woodsworth: A Man to Remember - MacInnis, Grace Woodsworth (Macmillan Company of Canada, 1953)
The influence of a great man continues long after controversy has faded from the issues he battled. And all Canadians feel the personal impact of the founder of the CCF party, James S Woodworth. He was drawn into politics almost by chance. His early calling was pastor in the Methodist Church of Canada, but a life-long interest in social reform brought him into Canada's House of Commons; a single voice speaking for every man's interest and freedom. In one debate after another, he staked his personal integrity against greed and sloth in the Thirties. Many of his social reforms, indignantly shouted down as radical, are now vital parts of national life. What are the inward springs that shape and propel such a man as Woodsworth? In his biography, written by his daughter Grace, is a strong clear picture of his life and convictions, and the family that mirrored his faith. Here is Woodsworth seen through family eyes; through the eyes of fellow workers; the targer of editorial writers, yet personally esteemed by his Parliamentary opponents. A full-length biography, well over 350 pages, it gives a rare portrait of a great Canadian - a man to remember. --Publisher's description (Google Books)
Keywords: Woodsworth, J. S. (James Shaver)1874-1942

Paper Makers in Canada: A History of the Paper Makers Union in Canada - Greening, William E. (International Brotherhood of Paper Makers, 1952)
Contents: Origin of the union -- The struggle for recognition in the province of Quebec -- Recent progress.
Keywords: Canada; International Brotherhood of Paper Makers; International Brotherhood of Paper Makers Canada Histoire; Paper industry; Paper industry Canada; Paper industry workers; Paper industry workers Canada; Papier Industrie Canada

He Wrote for Us: The Story of Bill Bennett, Pioneer Socialist Journalist - McEwen, Thomas Alexander (Tribune Publishing, 1951)
Keywords: Bennett, William, 1881-1949; Canada; Socialism; Socialism Canada

Trade Unions in Canada: Their Development and Functioning - Logan, Harold Amos (Macmillan Company of Canada, 1948)
This book is a foundational historical text detailing the growth and structure of Canadian labor movements from the 19th century up to its publication in 1948. Logan's work analyzes the economic and political factors influencing unions, the emergence of craft and industrial unions, and the impact of trade unions on Canadian labor laws, working-class life, and culture. The book provides a factual account of unionism's development, examining disputes over American vs. Canadian union structure and the role of key figures and organizations in shaping the movement.
Keywords: Canada; Labor unions

Land and Labour: A Social Survey of Agriculture and the Farm Labour Market in Central Canada - Haythorne, George Vickers; Marsh, Leonard (McGill Social Research Series, 1941)

A Social Approach to Economics - Logan, Harold Amos; Inman, Mark K. (University of Toronto Press, 1939)
Includes chapters on production, economic insecurity and other problems of labor.
Keywords: Economic history -- 1918-1945

Builders of British Columbia - Bennett, William (Broadway Printers, 1937)
"Traces the position of the working class and the development of unionism. The author was a member of the Communist Party of Canada."-- Lowther, B. J., & Laing, M. (1968). A bibliography of British Columbia: Laying the foundations, 1849-1899. Victoria, BC: University of Victoria, p. 192.
Keywords: British Columbia; Labor and laboring classes British Columbia; Labor unions; Labor unions British Columbia; Syndicats Colombie-Britannique

The Indians of Canada - Jenness, Diamond (Anthropological Series, 1934)
First published in 1932, The Indians of Canada remains the most comprehensive works available on Canada's Indians. Part one includes chapters on languages, economic conditions, food resources, hunting and fishing, dress and adornment, dwellings, travel and transportation, trade and commerce, social and political organization, social life, religion, folklore and traditions, and drama, music, and art. The second part of the book describes the tribes in different groupings: the migratory tribbes of the eastern woodlands, the plains tribes, tribes of the Pacific coast, of the Cordillera, and the Mackenzie and Yukon River basins, and finally the Eskimo. --Publisher's description, University of Toronto Press, 1977
Keywords: Indians of North America -- Canada

Labor's Case in Parliament: A Summary and Compilation of the Speeches of J.S. Woodsworth in the Canadian House of Commons, 1921-1928 - Woodsworth, J. S. (James Shaver) (Canadian Brotherhood of Railroad Employees, 1929)
This book has been prepared by Mr. J.L. Cohen of Toronto, a lawyer and labor research specialist, at the request of the Canadian Brotherhood of Railroad Employees. The Brotherhood, which is the largest national and industrial labor union in Canada, is deeply interested in the political representation of workers, and it was felt that the publishing of a brief analysis of the speeches of Mr. J.S. Woodsworth, M.P., during the past seven years, would be a distinct contribution to understanding what Labor men can do in Parliament. --Foreword
Keywords: Woodsworth, J. S. (James Shaver)1874-1942

The History of Trade-Union Organization in Canada - Logan, Harold Amos (University of Chicago Press, 1928)
The aim of this book is to give a general survey of trade-union organization in Canada from the beginnings down to the present. The manner of approach is to follow as far as possible the chronological order of events, and the method is mainly descriptive. With this conception of the task I have sought to present the facts clearly and without prejudice, introducing only a limited amount of interpretation.... -- Author's preface
Keywords: Trade-unions -- Canada

La question ouvière au Canada - Saint-Pierre, Arthur (Montpetit, 1920)
Keywords: Canada -- Labour and labouring classes

A History of Canadian Wealth - Myers, Gustavus (Charles H. Kerr Publishing, 1914)
In this pioneering work, Gustavus Myers lays bare the corruption, swindling, land deals, and bribery that are at the basis of Canadian history. This is Canada's past seen through the eyes of a muckraker, and in it the heroes of other histories appear in quite a different light. This book was first published in 1914—in the United States. It has never before been published in Canada. Canadian historians have mostly ignored, suppressed, or mocked it. But history is not the preserve of apologists for big business and the political parties, and A History of Canadian Wealth is certain to be widely read and recognized at last as a classic. A landmark revisionist history of Canada, A History of Canadian Wealth remains as lively and startling as it was when first published. --Publisher's description (from 1st Canadian edition (Lorimer, 1972) with an introduction by Stanley Ryerson)

The Vancouver Island Strike - Kavanagh, Jack (John Patrick Marcus) (B.C. Miners' Liberation League, 1913)
Keywords: Strikes and lockouts -- Coal mining Vancouver Island

The Labour Gazette - Canada. Department of Labour (Queen (or King's) Printer/Department of Labour, 1900)
V. 1, 1900-1901, to v. 65, 1965 , 1971, and 1975

The Conditions of Female Labour in Ontario - Scott, Jean Thomson (Toronto University Studies in Political Science, 1892)
In this paper some attempt will be made to discuss the conditions under which women are working in the Province of Ontario; referring, perhaps more particularly, to the City of Toronto, which has afforded the most convenient field of observation. ...[W]e find a large and increasing number of women employed was wage-earners; and Ontario, following the example of older countries, has found it necessary to subject their labour to various restrictions in order to protect the interests of society. Since the subject of child labour is intimately connected, both in factory law and inspection, with that of the employment of women, it has been discussed in connection therewith in this paper. --From author's introduction

The Politics of Labor: A Critique of American Radical Social Thought by a Canadian Labor Spokesman in 1887 - Thompson, T. Phillips (Thomas Phillips) (Belford, Clarke, 1887)
1886 witnessed the height of a period of violent industrial strife in North America. In that year the eight-hour day movement culminated in Chicago's notorious Haymarket Riot. Both the Trades and Labor Congress of Canada and the American Federation of Labor became firmly established and held their first annual meetings; the Knights of Labor were at their peak. Unemployment, working dislocation, and social unrest were focusing public attention on the abuses of the emerging industrial system. Those with power - the big business monopolies - were exploiting those without, and the various levels of government seemed unable or unwilling to intervene. It was all too evident that wealth and progress were for the few, and poverty and alienation were for the many. What were the cases of this inequality, and how could the balance be restored? This was the 'Labor Question' that engaged the imagination of so many writers in the 1880s, men such as Henry George, Laurence Gronlund, Edward Bellamy - and T. Phillips Thompson. Thompson was one of the leading spokesmen of the Canadian labor and socialist movements for over three decades. This book presents a distillation of his thought in a constructive critique of the American political and economic system. Time has proved Thompson a prophet: much of what he advocated in The Politics of Labor has come to pass in the years since 1886. --Publisher's description (from University of Toronto Press reprint edition with a new introduction by Jay Atherton, 1975)

Sacré Chartrand! - Foisy, Fernand (Lanctôt)
Recueil des courts extraits des discours de Michel Chartrand.
Keywords: Chartrand, Michel, 1916-2010 Citations; Dirigeants syndicaux Québec (Province) Citations; Labor leaders; Labor leaders Québec (Province) Quotations; Quotations; Québec